Abnormal epigenetic modification of lysosome and lipid regulating genes in Alzheimer's disease. - Ruan, Tingting; Ling, Yunxiang; Wu, Can; Niu, Yanfang; Liu, Guili; Xu, Chunshuang; Lv, Zhongyue; Yuan, Yalan; Zhou, Xinkai; Wang, Qinwen; Xu, Shujun (J Alzheimers Dis, 2025)
BackgroundAbnormal lipid metabolism has been identified as a potential pathogenic mechanism of Alzheimer's disease (AD), which might be epigenetically regulated. Lysosomes are critical organelles for lipid metabolism. However, the epigenetic modifications of lysosome and lipid regulating genes remain unclear in AD patients.ObjectiveExplore the role of abnormal epigenetic modifications, especially methylation of lysosome and lipid metabolism-related genes in AD.MethodsMethylation beadchip and MALDI-TOF mass spectrometry were used to detect genome-wide DNA methylation levels and validate key gene methylation, respectively. Clinical data were collected from all participants. Associations between clinical biochemical characteristics and altered DNA methylation in AD patients were analyzed, and a risk factor model of AD was established.Results41 differentially methylated positions (DMPs) corresponding to 33 genes were identified in AD patients, with 18 hypermethylated and 23 hypomethylated positions. Significant alterations were observed in lipid regulating genes () and lysosomal transmembrane gene (). Clinical analysis revealed that TP, ALB, IB, ADA, ALP, HCY, GLU, TC, BUN, HDL-C, LDL-C, and APOA1 levels were significantly higher in AD patients, whereas A/G and DB levels were lower. hypermethylation was further verified and found to correlate with TC, HDL-C, LDL-C, APOA1, IB, and HCY. The AUC of the AD risk model, which integrated clinical lipid markers and methylation, reached 0.9519 (< 0.0001).ConclusionsAbnormal epigenetic regulation of lysosomal gene and lipid dyshomeostasis were high-risk factors in AD. Methylation modifications of lysosome and lipid regulating genes might be key processes in AD pathogenesis.

ApoE ε4-dependent Alteration of CXCR3 CD127 CD4 T cells associates with elevated plasma neurofilament light chain in Alzheimer's disease. - Hu, Dan; Chen, Mei; Li, Xuyang; Daley, Sarah; Morin, Peter; Han, Yuyang; Hemberg, Martin; Weiner, Howard L; Xia, Weiming (J Alzheimers Dis, 2025)
BackgroundRecent findings indicate a correlation between the peripheral adaptive immune system and neuroinflammation in Alzheimer's disease (AD).ObjectiveTo characterize the composition of adaptive immune cells in the peripheral blood of AD patients.MethodsWe utilized single-cell mass cytometry (CyTOF) to profile peripheral blood mononuclear cells (PBMCs). Concurrently, we assessed the concentration of proteins associated with AD and neuroinflammation in the plasma of the same subjects.ResultsWe found that the abundance of proinflammatory CXCR3  CD127 Type 1 T helper (Th1) cells in AD patients was negatively correlated with the abundance of neurofilament light chain protein. This correlation is apolipoprotein E (ApoE) ε4-dependent. Analyzing public single-cell RNA-sequencing (scRNA-seq) data, we found that, contrary to the scenario in the peripheral blood, the cell frequency of CXCR3  CD127 Th1 cells in the cerebrospinal fluid (CSF) of AD patients was increased compared to healthy controls (HCs). Moreover, the proinflammatory capacity of CXCR3 CD127 Th1 cells in the CSF of AD patients was further increased compared to HCs.ConclusionsThese results reveal an association of a peripheral T-cell change with neuroinflammation in AD and suggest that dysregulation of peripheral adaptive immune responses, particularly involving CXCR3  CD127 Th1 cells, may potentially be mediated by factors such as ApoE ε4 genotype.

Chronic gingivitis increases the risk of early-onset Alzheimer's disease. - Mo, Dongcan; Li, Xiaoling; He, Jing; Lin, Xiaozuo; Wang, Pingkai; Zeng, Yinan; Wu, Xiaoju; Liu, LiuYu; Chi, Li; Luo, Man (J Alzheimers Dis, 2025)
BackgroundPeriodontal disease has two types of inflammatory states: gingivitis and periodontitis. While studies suggest a link between periodontal disease and Alzheimer's disease (AD), current evidence is insufficient to establish causality. This study employed Mendelian randomization (MR) and bioinformatics to investigate causal relationships between gingivitis, periodontitis, and AD types, while identifying diagnostic biomarkers through transcriptome-based bioinformatics approaches.ObjectiveThis study aims to explore the causal relationship between periodontal disease and AD using MR combined with bioinformatics analysis, investigate potential pathogenesis, and construct/validate diagnostic biomarkers.MethodsExposures and outcomes were selected from the Open whole-genome association study. Causal relationships were assessed using inverse variance-weighted (IVW), MR-Egger, and other supplementary methods. Transcriptome sequencing datasets were downloaded from Gene Expression Omnibus datasets. Key pathways and functions were identified through Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analysis. Protein-protein interaction and LASSO regression were used to construct and evaluate the diagnostic signature for early-onset AD (EOAD). Gene Set Enrichment Analysis was applied to analyze gene set enrichment between high and low-risk groups.ResultsIVW showed a positive correlation (OR = 1.161, 95% CI = 1.011-1.332, p = 0.035), and MR-Egger validated this result (OR = 1.296, 95% CI = 1.020-1.645, p = 0.049). These findings suggest that chronic gingivitis may increase EOAD risk. Reverse analysis results were negative. Immune activation, angiogenesis, and blood-brain barrier damage link the two diseases. The Inter-alpha-trypsin inhibitor heavy chain H5 () gene and pathway emerged in MR and bioinformatics analyses. A gene signature composed of , , and shows potential for diagnosing EOAD.ConclusionsChronic gingivitis may be associated with an increased risk of EOAD.

Cost-effectiveness of diagnosing and treating patients with early Alzheimer's disease with anti-amyloid treatment in a clinical setting. - Wimo, Anders; Handels, Ron; Blennow, Kaj; Kirsebom, K Bjørn-Eivind; Selnes, Per; Bon, Jaka; Emersic, Andreja; Gonzalez-Ortiz, Fernando; Gregoric Kramberger, Milica; Sköldunger, Anders; Speh, Andreja; Timón-Reina, Santiago; et al. (J Alzheimers Dis, 2025)
BackgroundThe introduction of anti-amyloid treatments (AAT) for Alzheimer's disease (AD) has put the cost-effectiveness into focus.ObjectiveEstimate the potential cost-effectiveness of diagnostic pathways combined with AAT for early AD.MethodsDiagnostic accuracy of blood-based (BBM) and cerebrospinal fluid (CSF) biomarkers was obtained from Norwegian memory clinics using positron emission tomography (PET) as reference standard. In a health-economic model, the cost-effectiveness of three diagnostic strategies was estimated relying either on BBM (p-tau 217), CSF (Aβ ratio), and BBM with CSF confirmatory testing and compared with standard of care (SoC) and compared with CSF-AAT. The model consisted of a decision tree reflecting the diagnostic process and a subsequent Markov cohort model starting at mild cognitive impairment due to AD. All strategies except SoC were combined with AAT including costs of treatment (assumed €5000/year), infusions and monitoring.ResultsCompared with SoC all three strategies (CSF-AAT, BBM-AAT, and BBM-CSF-AAT) resulted in QALY gains at higher costs, with an incremental cost-effectiveness ratio (ICER) of 110k€, 141k€ and 110k€ respectively. Compared with CSF-AAT both BBM-AAT and BBM-CSF-AAT strategies resulted in QALYs lost at lower costs, with an ICER of 27k€ and 109k€ respectively. Results were particularly sensitive to the price of AAT and possible subcutaneous administration.ConclusionsCompared with SoC all three strategies are potentially not cost-effective as they exceeded the Swedish maximum willingness to pay threshold of €94,800 per QALY gained. BBM-CSF-AAT versus CSF-AAT is potentially cost-effective if willing to accept its QALY loss. Discussions on budget impact on different payers are needed after introducing AAT.

DNA methylation age acceleration is associated with incident cognitive impairment in the health and retirement study. - Blostein, Freida; Bakulski, Kelly M; Fu, Mingzhou; Wang, Herong; Zawistowski, Matthew; Ware, Erin B (J Alzheimers Dis, 2025)
BackgroundDNA methylation clocks have emerged as promising biomarkers for cognitive impairment and dementia. Longitudinal studies exploring the association between DNA methylation clocks and cognitive decline have been constrained by limited sample sizes and a lack of diversity.ObjectiveOur study aimed to investigate associations between DNA methylation clocks and incident cognitive impairment using a larger and US nationally-representative sample from the Health and Retirement Study.MethodsWe measured DNA methylation age acceleration in 2016 by regressing the DNA methylation clocks, including GrimAge, against chronological age. Cognitive change over time was determined by Langa-Weir cognition status from 2016 to 2018. Multivariable logistic regression evaluated the association between DNA methylation age acceleration and cognitive change, adjusting for cell-type proportions, demographic, and health factors. We also applied inverse probability weighting to address potential selection bias from varying loss-to-follow-up rates.ResultsThe analytic sample (N = 2713) was 54% female, 8.4% Black/African American, 86% White, 7.5% Hispanic, and 68 years old at baseline. During the two years of follow-up, 12% experienced cognitive change and had higher baseline GrimAge (mean = 1.2 years) acceleration compared to those maintaining normal cognition (mean = -0.8 years). A one-year increase in GrimAge acceleration was associated with 1.05 times higher adjusted and survey-weighted odds of cognitive change during follow-up (95% CI: 1.01-1.10). This association was consistent after accounting for loss-to-follow-up (OR = 1.07, 95% CI: 1.04-1.11).ConclusionsOur study offers insights into DNA methylation age acceleration associated with cognitive change over time, suggesting avenues for improved prevention, diagnosis, and treatment.

Factors associated with a healthy diet and willingness to change dietary behavior in older adults at increased risk of dementia. - Blotenberg, Iris; Zülke, Andrea E; Luppa, Melanie; Wittmann, Felix; Fankhänel, Thomas; Weise, Solveig; Döhring, Juliane; Escales, Catharina; Kosilek, Robert P; Michel, Irina; Brettschneider, Christian; Oey, Anke; et al. (J Alzheimers Dis, 2025)
BackgroundHealthy dietary patterns have been linked to reduced risks for cardiovascular diseases and dementia, making nutrition an essential part of a comprehensive approach for dementia prevention. Knowledge about factors associated with a healthy diet in people with increased dementia risk is scarce.ObjectiveTo analyze dietary habits and associated factors in older adults with increased dementia risk in Germany.MethodsWe used baseline-data of the AgeWell.de-trial (n = 1001, %= 52.2, M= 69.0, SD = 4.9). Nutrition was assessed using a composite score, comprising 11 components covered by national recommendations for a healthy diet (range = 0-11 points). Linear regressions assessed associations of sociodemographic, social, health-related and psychological factors with consumption of a healthy diet. Further, we assessed stages of change based on the transtheoretical model of behavior change.ResultsConsumption of a healthy diet was moderate (Median = 4, IQR = 2). Female sex (b = 0.64, 95% CI: 0.41, 0.88), higher levels of motivation for healthy eating (b = 0.22, 95% CI: 0.10, 0.34) and higher self-efficacy (b = 0.33, 95% CI: 0.20, 0.46) were linked to a healthy diet. Regarding the stages of behavior change, the majority were in the maintenance stage (45.2%), followed by the contemplation (21.5%) and precontemplation (21.2%) stages.ConclusionsResults suggest room for improvement regarding a healthy diet in our sample. Lifestyle-based interventions in older adults should be tailored towards current levels of motivation and self-efficacy of participants. Including modules targeting motivation and self-efficacy might help maximize intervention effectiveness.

Impact of obesity on neuropsychiatric symptoms in Alzheimer's disease: Insights from the ADNI cohort. - Wang, Shuoshi; Ni, Jingnian; Wei, Mingqing; Li, Ting; Shi, Jing; Tian, Jinzhou (J Alzheimers Dis, 2025)
BackgroundObesity is a major global health issue linked to increased risks of dementia, including Alzheimer's disease (AD). While the association between obesity and neuropsychiatric symptoms (NPS) in AD remains underexplored, identifying these links could aid in weight management in AD patients.ObjectiveThis study investigates the relationship between body mass index (BMI) and NPS in AD dementia patients, focusing on the potential mediating role of systemic inflammation.MethodsWe employed Generalized Additive Models (GAMs) to explore the relationship between BMI and NPS, as measured by the Neuropsychiatric Inventory Questionnaire (NPI-Q). Participants were classified into ideal, overweight, and obese groups based on WHO criteria. Longitudinal analyses assessed the trajectory of NPI-Q scores in different groups over a one-year follow-up.ResultsBMI significantly affects NPI-Q total scores and specific symptoms, including delusions, hallucinations, agitation/aggression, elation/euphoria, disinhibition, irritability/lability, aberrant motor behavior, nighttime disturbances, and appetite/eating disturbances. Obese patients exhibited higher NPI-Q total scores and greater severity in symptoms such as hallucinations, agitation/aggression, elation/euphoria, apathy/indifference, disinhibition, aberrant motor behavior, and nighttime disturbances. Additionally, CRP and complement C3 were identified as mediators in the relationship between obesity and NPS, highlighting the role of systemic inflammation.ConclusionsThis study demonstrates that obesity is associated with a heightened burden of NPS in AD dementia patients. The identification of CRP and complement C3 as mediators suggests inflammation plays a crucial role in the association between obesity and NPS. These findings underscore the importance of addressing obesity and its inflammatory consequences in managing NPS among this vulnerable population.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Body Mass Index; Cohort Studies; Female; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Obesity

Increased risk of dementia associated with herpes simplex virus infections: Evidence from a retrospective cohort study using U.S. electronic health records. - Araya, Katherine; Watson, Riley; Khanipov, Kamil; Golovko, George; Taglialatela, Giulio (J Alzheimers Dis, 2025)
BACKGROUND: Alzheimer's disease is the most common age-related dementia. Recent compelling evidence from previous retrospective electronic health record (EHRs) studies suggests that herpes simplex virus (HSV) infections may be a risk factor for developing dementia. However, no age and propensity score matched studies have been published in a United States general population cohort study to date. OBJECTIVE: We aimed to identify whether HSV infection shows a significantly increased risk of the development of dementia in a sizable and heterogeneous cohort. We investigated whether herpes simplex virus type 1 (HSV1), herpes simplex virus type 2 (HSV2), or coinfections with both serotypes pose a greater risk of developing dementia across different biological sexes and racial groups. METHODS: EHRs from patients with a history of HSV or specific serotypes (HSV1 or HSV2) infection were selected for analysis. These records were compared to a propensity-matched control group and analyzed for hazard and odds ratios through TriNetX. RESULTS: There was a significant difference in dementia incidence in the HSV-infected group versus the control. Individuals with a history of HSV, HSV1, HSV2, and coinfection all showed a significant risk of developing dementia compared to controls. Males with HSV2 are at a higher risk of dementia outcome than females with HSV2. CONCLUSIONS: While consistent with previous reports, these findings are the first to establish a higher risk of developing dementia in patients who have any HSV diagnosis using a nationwide, population-based matched cohort study in the United States.

Leptin, adiponectin, body mass index, and incident cognitive impairment. - Thacker, Evan L; Karki, Reena; Gabor, Rachel; Blades, Natalie J; Sawyer, Russell P; Kouambo Beckodro, Cyrille N; Preece, Quinn; Prince, Samuel; Smith, McKay M; Gillett, Sarah R; Judd, Suzanne E; Kennedy, Richard E; et al. (J Alzheimers Dis, 2025)
BackgroundDisordered metabolism affects risk for cognitive decline, Alzheimer's disease, and other dementias, likely through pathways involving adipokines.ObjectiveAnalyze incident cognitive impairment in relation to leptin, adiponectin, body mass index, and other risk factors.MethodsNested case-control study within the Reasons for Geographic and Racial Differences in Stroke (REGARDS) cohort of 30,239 adults in the US. Cases with incident cognitive impairment (n = 489) scored >1.57 SD below demographically adjusted means on ≥2 of 3 cognitive tests: word list learning, word list delayed recall, and category fluency. Cognitively intact controls (n = 583) were randomly selected within demographic strata. Leptin and adiponectin were assayed in thawed blood that had been stored at baseline.ResultsIn participants with normal weight, lower leptin was associated with higher odds of cognitive impairment. Relative to leptin = 25 ng/mL, adjusted ORs were 1.5 (95% CI: 1.2, 1.9) at leptin = 15 ng/mL, 0.8 (0.8, 0.9) at leptin = 30 ng/mL, and 0.5 (0.4, 0.8) at leptin = 45 ng/mL. In participants with obesity, higher adiponectin was associated with higher odds of cognitive impairment. Relative to adiponectin = 25 ng/mL, adjusted ORs were 0.8 (95% CI: 0.7, 1.0) at adiponectin = 15 ng/mL, 1.1 (1.0, 1.2) at adiponectin = 30 ng/mL, and 1.3 (1.0, 1.7) at adiponectin = 45 ng/mL. Associations of adipokines with cognitive impairment varied across levels of other risk factors.ConclusionsAdipokines, in concert with body mass index, play complex roles in cognitive health, with many avenues open for further investigation.

Lipopolysaccharides from indirectly induce neuronal GSK3β-dependent synaptic defects and cause cognitive decline in a low-amyloid-β-concentration environment in Alzheimer's disease. - Gui, Shuge; Zeng, Fan; Wu, Zhou; Nonaka, Saori; Sano, Tomomi; Ni, Junjun; Nakanishi, Hiroshi; Moriyama, Masafumi; Kanematsu, Takashi (J Alzheimers Dis, 2025)
BackgroundLipopolysaccharides from s (LPS) are involved in the pathology of Alzheimer's disease (AD). However, the effect of LPS on synaptic defects remains unclear.ObjectiveIn this study, we tested our hypothesis that LPS induces synaptic defects in a low-amyloid-beta (Aβ)-concentration environment.MethodsMG6 microglia or N2a neurons was treated with LPS (0.1 μg/mL), soluble Aβ (0.1 μM) or AL (combined LPS and soluble Aβ at 0.1 μM).ResultsIn cultured MG6 microglia, increased the mRNA expression of TNF-α, IL-1β and IL-6 and the TNF-α release in parallel with increased NF-κB activation. In cultured N2a neurons, treatment with Aβ, LPS, and AL did not affect the mRNA expression of synapsin1 (SYN1) or post-synaptic density protein-95 (PSD-95). However, the treatment with conditioned medium from AL-exposed MG6 microglia (AL-MCM) significantly reduced the mRNA and protein expression of SYN1, PSD-95, and nuclear translocation of repressor element-1 silencing transcription factor (REST) but significantly increased the mRNA expression of TNF receptor type I (at 48 h) and glycogen synthase kinase (GSK)3β (at 24 h). TWS119 pretreatment (5 μM), a GSK3β specific inhibitor, significantly reversed the AL-MCM-induced reduction in the mRNA expression of SYN1 and PSD-95 and nuclear translocation of REST in cultured N2a neurons. In APP mice, the immunofluorescence intensity of SYN1 and PSD-95 in cortical neurons was positively correlated with the index of the memory test but negatively correlated with that of TNF-α-positive microglia.ConclusionsThese observations demonstrate that LPS induces neuronal GSK3β-dependent synaptic defects in a low-Aβ concentration environment via microglial activation.

The potential impact of optimal blood pressure treatment intensity to reduce disparities in dementia between Black and White individuals. - Levine, Deborah A; Sussman, Jeremy B; Hayward, Rodney A; Gałecki, Andrzej T; Whitney, Rachael T; Briceño, Emily M; Gross, Alden L; Giordani, Bruno J; Elkind, Mitchell Sv; Gottesman, Rebecca F; Gaskin, Darrell J; Sidney, Stephen; et al. (J Alzheimers Dis, 2025)
BACKGROUND: Black adults have higher dementia risk than White adults. Whether tighter population-level blood pressure (BP) control reduces this disparity is unknown. OBJECTIVE: Estimate the impact of optimal BP treatment intensity on racial disparities in dementia. METHODS: A microsimulation study of US adults ≥18 across a life-time policy-planning horizon. BP treatment strategies were the Systolic Blood Pressure Intervention Trial (SPRINT) protocol, the Eighth Joint National Committee (JNC-8) recommendations, and usual care (non-intervention control). Outcomes were all-cause dementia, atherosclerotic cardiovascular disease (ASCVD), stroke, myocardial infarction, non-ASCVD death, global cognitive performance, and optimal brain health (being free of dementia, cognitive impairment, or stroke). Population-level and individual-level effects stratified by race were estimated. RESULTS: Optimal population-level implementation of a SPRINT-based BP treatment strategy, compared to usual care, would average annual dementia incidence in White, but not Black, adults (1% versus 0%), due to hypertensive individuals' greater survival, and reduce annual ASCVD events more in Black than White adults (13% versus 5%). Under a SPRINT-based strategy, individuals with hypertension gained more years lived without dementia, ASCVD, myocardial infarction, or stroke and more years lived in optimal brain health. A SPRINT-based strategy did not attenuate individual-level race disparities in outcomes, except stroke. Due to longer life expectancy, a SPRINT-based strategy did not substantially reduce lifetime dementia risk in either group. The JNC-8-based strategy had similar but smaller effects as the SPRINT-based strategy. CONCLUSIONS: Our results suggest that tighter population-level BP control would not reduce population-level disparities in dementia between US Black and White adults.

Semaglutide improves cognitive function and neuroinflammation in APP/PS1 transgenic mice by activating AMPK and inhibiting TLR4/NF-κB pathway. - Zhai, Yanyu; Lu, Kaili; Yuan, Yuan; Zhang, Ziyao; Xue, Lixia; Zhao, Fei; Xu, Xiaofeng; Wang, Hongmei (J Alzheimers Dis, 2025)
BackgroundAlzheimer's disease (AD) causes cognitive function disorder and has become the preeminent cause of dementia. Glucagon-like peptide-1 (GLP-1) receptor agonists, semaglutide, have shown positive effects on promoting the cognitive function. However, research about the mechanism of semaglutide as a therapeutic intervention in AD is sparse.ObjectiveThis study was to investigate the therapeutic efficacy of semaglutide in a transgenic mouse model of AD pathology and explored the detailed mechanism by semaglutide modulated neuroinflammatory processes.MethodsMale amyloid precursor protein/presenilin 1 (APP/PS1) transgenic mice were treated with semaglutide or vehicle for 8 weeks. Morris water maze test was used to assess the therapeutic efficacy of semaglutide on recognition function. Pathology analysis was performed to detect the deposition of amyloid plaques. High-throughput sequencing analysis was applied to specify the mechanism. Microglia and astrocyte activation were assessed with immunofluorescent staining. Inflammation cytokine levels were evaluated with enzyme-linked immunosorbent assay (ELISA). Related proteins and pathway were evaluated with western blot.ResultsSemaglutide treatment attenuated Aβ accumulation and enhanced cognitive function in APP/PS1 transgenic mice. Through transcriptomic profiling, immunohistochemical staining, and ELISA, semaglutide was substantiated to inhibit the overactivation of microglia and astrocytes, as well as to curtail the secretion of inflammatory mediators. Furthermore, semaglutide robustly activated AMP-activated protein kinase (AMPK) and suppressed the toll-like receptor 4 (TLR4)/nuclear factor-kappa B (NF-κB) signaling cascade, thus reducing the Aβ deposition and dampening the inflammatory cascade.ConclusionsThe results demonstrated that semaglutide mitigated neuroinflammation and decelerated the advance of AD in APP/PS1 transgenic mice.

African Ancestry Individuals with Higher Educational Attainment Are Resilient to Alzheimer's Disease Measured by pTau181. - Rajabli, Farid; Seixas, Azizi A; Akgun, Bilcag; Adams, Larry D; Inciute, Jovita; Hamilton, Kara L; Whithead, Patrice G; Konidari, Ioanna; Gu, Tianjie; Arvizu, Jamie; Golightly, Charles G; Starks, Takiyah D; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Cognitive and functional abilities in individuals with Alzheimer's disease (AD) pathology (ADP) are highly variable. Factors contributing to this variability are not well understood. Previous research indicates that higher educational attainment (EA) correlates with reduced cognitive impairments among those with ADP. While cognitive and functional impairments are correlated, they are distinguishable in their manifestations. OBJECTIVE: To investigate whether levels of education are associated with functional impairments among those with ADP. METHODS: This research involved 410 African American (AA) individuals (Institutional Review Boards 20070307, 01/27/2023) to ascertain whether EA correlates with functional resilience and if this effect varies between APOE ɛ4 carriers and non-carriers. Utilizing EA as a cognitive reserve proxy, CDR-FUNC as a functional difficulties measure, and blood pTau181 as an ADP proxy, the non-parametric Mann-Whitney U test assessed the relationship between EA and CDR-FUNC in individuals with advanced pTau181 levels. RESULTS: The results showed that EA correlated with functional difficulties in AA individuals with high levels of pTau181, such that individuals with high EA are more likely to have better functional ability compared to those with lower EA (W = 730.5, p = 0.0007). Additionally, we found that the effect of high EA on functional resilience was stronger in ɛ4 non-carriers compared to ɛ4 carriers (W = 555.5, p = 0.022). CONCLUSION: This study extends the role of cognitive reserve and EA to functional performance showing that cognitive reserve influences the association between ADP burden and functional difficulties. Interestingly, this protective effect seems less pronounced in carriers of the strong genetic risk allele ɛ4.
Keywords: Alzheimer Disease; Apolipoprotein E4; Cognitive Dysfunction; Educational Status; Humans; Resilience, Psychological

Alterations in Synaptic Connectivity and Synaptic Transmission in Alzheimer's Disease with High Physical Activity. - Wu, Can; Ruan, Tingting; Yuan, Yalan; Xu, Chunshuang; Du, Lijuan; Wang, Fang; Xu, Shujun (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is a progressive neurodegeneration disease. Physical activity is one of the most promising modifiable lifestyles that can be effective in slowing down the progression of AD at an early stage. OBJECTIVE: Explore the molecular processes impaired in AD that were conversely preserved and enhanced by physical activity. METHODS: Integrated transcriptomic analyses were performed in datasets that contain AD patients and elders with different degrees of physical activity. The changes of the hub genes were validated through analyzing another two datasets. The expression of the hub genes was further detected in the hippocampus and cortexes of APP/PS1 transgenic mice with or without physical activity by Quantitative polymerase chain reaction (qPCR). RESULTS: Cross-comparison highlighted 195 DEGs displaying opposed regulation patterns between AD and high physical activity (HPA). The common DEGs were predominantly involved in synaptic vesicle recycling and synaptic transmission, largely downregulated in AD patients but upregulated in the elders with HPA. Two key modules and four hub genes that were related to synaptic vesicle turnover were obtained from the PPI network. The expression of these hub genes (SYT1, SYT4, SH3GL2, and AP2M1) was significantly decreased in AD transgenic mice and was reversed by HPA training. CONCLUSIONS: HPA may reverse AD pathology by upregulating a range of synaptic vesicle transport related proteins which might improve the efficiency of synaptic vesicle turnover and facilitate inter-neuronal information transfer. The study provides novel insights into the mechanisms underlining the protective effects of HPA on AD.

Altered Neuronal Activity Patterns of the Prefrontal Cortex in Alzheimer's Disease After Transcranial Alternating Current Stimulation: A Resting-State fMRI Study. - Wang, Tao; Yan, Shaozhen; Shan, Yi; Xing, Yi; Bi, Sheng; Chen, Zhigeng; Xi, Hanyu; Xue, Hanxiao; Qi, Zhigang; Tang, Yi; Lu, Jie (J Alzheimers Dis, 2024)
BACKGROUND: Transcranial alternating current stimulation (tACS) could improve cognition in patients with Alzheimer's disease (AD). However, the effects of tACS on brain activity remain unclear. OBJECTIVE: The purpose is to investigate the change in regional neuronal activity after tACS in AD patients employing resting-state functional magnetic resonance imaging (rs-fMRI). METHODS: A total of 46 patients with mild AD were enrolled. Each patient received 30 one-hour sessions of real or sham tACS for three weeks (clinical trial: NCT03920826). The fractional amplitude of low-frequency fluctuations (fALFF) and the regional homogeneity (ReHo) measured by rs-fMRI were calculated to evaluate the regional brain activity. RESULTS: Compared to baseline, AD patients in the real group exhibited increased fALFF in the left middle frontal gyrus-orbital part and right inferior frontal gyrus-orbital part, as well as increased ReHo in the left precentral gyrus and right middle frontal gyrus at the end of intervention. At the 3-month follow-up, fALFF increased in the left superior parietal lobule and right inferior temporal gyrus, as well as ReHo, in the left middle frontal gyrus and right superior medial frontal gyrus. A higher fALFF in the right lingual gyrus and ReHo in the right parahippocampal gyrus were observed in the response group than in the nonresponse group. CONCLUSIONS: The findings demonstrated the beneficial effects of tACS on the neuronal activity of the prefrontal cortex and even more extensive regions and provided a neuroimaging biomarker of treatment response in AD patients.

Association Between Urinary Glyphosate Exposure and Cognitive Impairment in Older Adults from NHANES 2013-2014. - Ren, Jiawen; Yu, Yongquan; Wang, Yucheng; Dong, Yu; Shen, Xiaobing (J Alzheimers Dis, 2024)
BACKGROUND: Glyphosate is the most commonly used herbicide with potential neurotoxicity. However, limited epidemical evidence is found in the relationship between glyphosate and cognitive impairment, especially in the cognitive-disrupting sensitive elderly populations. OBJECTIVE: This study aimed to examine the association of urinary glyphosate exposure with cognitive impairment in the United State (US) older adults. METHODS: Cognitive impairment was determined by the following four tests: the Consortium to Establish a Registry for Alzheimer's disease (CERAD) Immediate Recall test (IR), the CERAD Delayed Recall tests (DR), the Animal Fluency (AF) test and the Digit Substitution test (DSST). Survey weighted logistic regression and restricted cubic splines were applied to evaluate and visualize the association between glyphosate and cognitive impairment. RESULTS: A total of 465 elderly adults were identified in the National Health and Nutrition Examination Survey (NHANES) 2013-2014 cycle, and among them, 83.87% individuals had detectable urinary levels of glyphosate (0.628 ng/mL in average). After adjusting for the potential covariates, glyphosate was significantly linked to increased DR and AF impairment, and the corresponding ORs were 1.52 (1.01 to 2.30, p = 0.049) and 1.69 (1.11 to 2.59, p = 0.019), respectively. No significant association was identified between glyphosate and IR or DSST impairment. The RCS plot further confirmed the linear and positive relationships between glyphosate and DR and AF impairment. CONCLUSIONS: These findings suggested that exposure to glyphosate might be associated with declined cognitive function in the elderly, and it might be prudent to evaluate cognitive outcomes for aged individuals with glyphosate exposures.
Keywords: Aged; Alzheimer Disease; Cognition; Cognition Disorders; Cognitive Dysfunction; Glyphosate; Humans; Nutrition Surveys

Association of Plastic Exposure with Cognitive Function Among Chinese Older Adults. - Zhu, Yongbin; Wu, Yueping; Shi, Liping; Yang, Yue; Wang, Yanrong; Pan, Degong; He, Shulan; Wang, Liqun; Li, Jiangping (J Alzheimers Dis, 2024)
BACKGROUND: The widespread exposure to plastic products and the increasing number of individuals with cognitive impairments have imposed a heavy burden on society. OBJECTIVE: This study aims to investigate the relationship between plastic product exposure in daily life and cognitive function in older Chinese individuals. METHODS: Data were obtained from the 2023 Ningxia Older Psychological Health Cohort, comprising 4045 participants aged 60 and above. Cognitive function was assessed using the Mini-Mental State Examination scale. A population-based plastic exposure questionnaire was used to calculate plastic exposure scores (PES). Binary logistic regression was employed to analyze the relationship between PES and cognitive function, while restricted cubic splines were used to examine the dose-response relationship between PES and cognitive function. Latent profile analysis (LPA) was employed to explore the potential patterns of plastic exposure, and logistic regression was used to investigate the relationship between different exposure patterns and cognitive function. A linear regression model was utilized to investigate the relationship between PES and different dimensions of cognitive function. RESULTS: Among the 4045 participants, 1915 individuals were assessed with mild cognitive impairment (MCI). After adjusting for all covariates, PES (OR = 1.04, 95% CI 1.02-1.06) was significantly associated with the risk of MCI and exhibited a dose-response relationship. LPA identified two potential categories of plastic exposure, with a higher risk of MCI observed in the group using plastic utensils. CONCLUSIONS: This study indicates a positive correlation between plastic exposure levels and MCI risk, particularly among individuals who frequently use plastic tableware.
Keywords: Aged; Aged, 80 and over; China; Cognition; Cognitive Dysfunction; Cohort Studies; East Asian People; Environmental Exposure; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Plastics; Surveys and Questionnaires

Association of Vitamin D Levels with Risk of Cognitive Impairment and Dementia: A Systematic Review and Meta-Analysis of Prospective Studies. - Zhang, Xiao-Xue; Wang, He-Ran; Hu, Ya-Zhuo; Sun, Hong-Mei; Feng, Yu-Xin; Jia, Jian-Jun (J Alzheimers Dis, 2024)
BACKGROUND: Emerging evidence suggests the potential relationship between vitamin D deficiency and risk of cognitive impairment or dementia. To what extent the excess risk of dementia conferred by vitamin D deficiency is less clear. OBJECTIVE: We summarized the current evidence from several aspects and further quantified these associations. METHODS: We collected relevant prospective cohort studies by searching PubMed, Embase and Cochrane up to July 2023. The pooled relative risks (RR) were evaluated by random-effects models. Dose-response analyses were conducted by the method of two-stage generalized least squares regression. RESULTS: Of 9,267 identified literatures, 23 were eligible for inclusion in the meta-analyses, among which 9 and 4 literatures were included in the dose-response analyses for the risk of dementia and Alzheimer's disease (AD). Vitamin D deficiency exhibited a 1.42 times risk for dementia (95% confidence interval (CI) = 1.21-1.65) and a 1.57-fold excess risk for AD (95% CI = 1.15-2.14). And vitamin D deficiency was associated with 34% elevated risk with cognitive impairment (95% CI = 1.19-1.52). Additionally, vitamin D was non-linearly related to the risk of dementia (pnonlinearity = 0.0000) and AD (pnonlinearity = 0.0042). The approximate 77.5-100 nmol/L 25-hydroxyvitamin D [25(OH)D] was optimal for reducing dementia risk. And the AD risk seemed to be decreased when the 25(OH)D level >40.1 nmol/L. CONCLUSIONS: Vitamin D deficiency was a risk factor for dementia, AD, and cognitive impairment. The nonlinear relationships may further provide the optimum dose of 25(OH)D for dementia prevention.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Dementia; Humans; Prospective Studies; Risk Factors; Vitamin D; Vitamin D Deficiency

Bisecting N-Acetylglucosamine Correlates with Phospho-Tau181 in Subjective Cognitive Decline but not in Control Cases. - Egebäck Arulf, Sofia; Ziyue Zhou, Robin; Kirsebom, Bjørn-Eivind; Jejcic, Alenka; Fladby, Tormod; Winblad, Bengt; Tjernberg, Lars; Schedin-Weiss, Sophia (J Alzheimers Dis, 2024)
BACKGROUND: The N-glycan structure bisecting N-acetylglucosamine (bisecting GlcNAc) is present on several N-glycans that are elevated in Alzheimer's disease (AD), and previous studies have shown that bisecting GlcNAc levels correlate with total tau and phospho-tau181 in cerebrospinal fluid at early stages of AD. A recent population-based study showed that bisecting GlcNAc correlates with total tau also in blood and that this correlation could predict conversion to dementia. OBJECTIVE: In this study, we have further investigated how bisecting GlcNAc relates to total tau and phospho-tau 181 in cerebrospinal fluid samples from controls and cases with early cognitive deficits, stratified by amyloid/tau status and gender. METHODS: Relative levels of bisecting GlcNAc in cerebrospinal fluid were measured by an enzyme-linked lectin assay in individuals with subjective cognitive decline, mild cognitive impairment and controls from the Norwegian Dementia Disease Initiation cohort. RESULTS: As in our previous study, the correlation between bisecting GlcNAc and total tau or phospho-tau181 was particularly strong in the subjective cognitive decline group. The correlation was observed in amyloid negative and tau negative as well as amyloid positive and tau positive individuals, both in females and in males. Interestingly, among the amyloid negative and tau negative individuals, the correlation was observed in individuals with subjective cognitive decline but not in the controls. CONCLUSIONS: Thus, bisecting GlcNAc could be a biomarker for early cognitive decline.

Cerebrospinal Fluid Proteomics Identifies Potential Biomarkers for Early-Onset Alzheimer's Disease. - Li, Dazhi; Xie, Qiang; Xie, Jikui; Ni, Ming; Wang, Jinliang; Gao, Yuru; Wang, Yaxin; Tang, Qiqiang (J Alzheimers Dis, 2024)
BACKGROUND: Early-onset Alzheimer's disease (EOAD) exhibits a notable degree of heterogeneity as compared to late-onset Alzheimer's disease (LOAD). The proteins and pathways contributing to the pathophysiology of EOAD still need to be completed and elucidated. OBJECTIVE: Using correlation network analysis and machine learning to analyze cerebrospinal fluid (CSF) proteomics data to identify potential biomarkers and pathways associated with EOAD. METHODS: We employed mass spectrometry to conduct CSF proteomic analysis using the data-independent acquisition method in a Chinese cohort of 139 CSF samples, including 40 individuals with normal cognition (CN), 61 patients with EOAD, and 38 patients with LOAD. Correlation network analysis of differentially expressed proteins was performed to identify EOAD-associated pathways. Machine learning assisted in identifying crucial proteins differentiating EOAD. We validated the results in an Western cohort and examined the proteins expression by enzyme-linked immunosorbent assay (ELISA) in additional 9 EOAD, 9 LOAD, and 9 CN samples from our cohort. RESULTS: We quantified 2,168 CSF proteins. Following adjustment for age and sex, EOAD exhibited a significantly greater number of differentially expressed proteins than LOAD compared to CN. Additionally, our data indicates that EOAD may exhibit more pronounced synaptic dysfunction than LOAD. Three potential biomarkers for EOAD were identified: SH3BGRL3, LRP8, and LY6 H, of which SH3BGRL3 also accurately classified EOAD in the Western cohort. LY6 H reduction was confirmed via ELISA, which was consistent with our proteomic results. CONCLUSIONS: This study provides a comprehensive profile of the CSF proteome in EOAD and identifies three potential EOAD biomarker proteins.

Characterizing Gut Microbiota in Older Chinese Adults with Cognitive Impairment: A Cross-Sectional Study. - Wang, Jing; Zhang, Gong; Lai, Hao; Li, Zengbin; Shen, Mingwang; Li, Chao; Kwan, Patrick; O'Brien, Terence J; Wu, Ting; Yang, Siyu; Zhang, Xueli; Zhang, Lei (J Alzheimers Dis, 2024)
BACKGROUND: Cognitive impairment is a clinical manifestation that occurs in the course of dementia like Alzheimer's disease. The association between cognitive impairment and gut microbiota is unclear. OBJECTIVE: We aimed to identify gut microbiota characteristics and key gut microbiota biomarkers associated with cognitive impairment in a relatively large cohort of older adults in China. METHODS: A total of 229 adults aged ≥60 years from Shenzhen, China were recruited into this cross-sectional study. Participants were divided into cognitive impairment (CI) and no cognitive impairment (NCI) groups according to the results of the Mini-Mental State Examination. Diversity analysis and network analysis were used to characterize the gut microbiota between the two groups. The linear discriminant analysis effect size method and machine learning approaches were sequentially performed to identify gut microbiota biomarkers. The relationship between biomarkers and lifestyle factors was explored using Transformation-based redundancy analysis (tb-RDA). RESULTS: A total of 74 CI participants and 131 NCI participants were included in the analysis. The CI group demonstrated lower α-diversity compared to the NCI group (Shannon: 2.798 versus 3.152, p < 0.001). The density of the gut microbiota interaction network was lower in the CI group (0.074) compared to the NCI group (0.081). Megamonas, Blautia, Pseudomonas, Stenotrophomonas, and Veillonella were key biomarkers for CI. The tb-RDA revealed that increased fruit intake and exercise contribute to a higher abundance of Megamonas, Blautia, and Veillonella. CONCLUSIONS: We identified a significantly reduced abundance of certain beneficial gut microbiota in older Chinese adults with cognitive impairment.
Keywords: Aged; Aged, 80 and over; Biomarkers; China; Cognitive Dysfunction; Cross-Sectional Studies; East Asian People; Female; Gastrointestinal Microbiome; Humans; Machine Learning; Male; Middle Aged

Effect of Metformin on Plasma and Cerebrospinal Fluid Biomarkers in Non-Diabetic Older Adults with Mild Cognitive Impairment Related to Alzheimer's Disease. - Weinberg, Marc S; He, Yingnan; Kivisäkk, Pia; Arnold, Steven E; Das, Sudeshna (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is a complicated condition involving multiple metabolic and immunologic pathophysiological processes that can occur with the hallmark pathologies of amyloid-β, tau, and neurodegeneration. Metformin, an anti-diabetes drug, targets several of these disease processes in in vitro and animal studies. However, the effects of metformin on human cerebrospinal fluid (CSF) and plasma proteins as potential biomarkers of treatment remain unexplored. OBJECTIVE: Using proteomics data from a metformin clinical trial, identify the impact of metformin on plasma and CSF proteins. METHODS: We analyzed plasma and CSF proteomics data collected previously (ClinicalTrials.gov identifier: NCT01965756, conducted between 2013 and 2015), and conduced bioinformatics analyses to compare the plasma and CSF protein levels after 8 weeks of metformin or placebo use to their baseline levels in 20 non-diabetic patients with mild cognitive impairment (MCI) and positive AD biomarkers participants. RESULTS: 50 proteins were significantly (unadjusted p < 0.05) altered in plasma and 26 in CSF after 8 weeks of metformin use, with 7 proteins in common (AZU1, CASP-3, CCL11, CCL20, IL32, PRTN3, and REG1A). The correlation between changes in plasma and CSF levels of these 7 proteins after metformin use relative to baseline levels was high (r = 0.98). The proteins also demonstrated temporal stability. CONCLUSIONS: Our pilot study is the first to investigate the effect of metformin on plasma and CSF proteins in non-diabetic patients with MCI and positive AD biomarkers and identifies several candidate plasma biomarkers for future clinical trials after confirmatory studies.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Cognitive Dysfunction; Double-Blind Method; Female; Humans; Hypoglycemic Agents; Male; Metformin; Middle Aged; Proteomics

Enhancing Rab7 Activity by Inhibiting TBC1D5 Expression Improves Mitophagy in Alzheimer's Disease Models. - Liang, Xiao; Wang, Yangyang; Li, Siyu; Fan, Jianing; Zhou, Fanlin; Li, Xiaoju; Li, Shijie; Li, Yu (J Alzheimers Dis, 2024)
BACKGROUND: Mitochondrial dysfunction exists in Alzheimer's disease (AD) brain, and damaged mitochondria need to be removed by mitophagy. Small GTPase Rab7 regulates the fusion of mitochondria and lysosome, while TBC1D5 inhibits Rab7 activation. However, it is not clear whether the regulation of Rab7 activity by TBC1D5 can improve mitophagy and inhibit AD progression. OBJECTIVE: To investigate the role of TBC1D5 in mitophagy and its regulatory mechanism for Rab7, and whether activation of mitophagy can inhibit the progression of AD. METHODS: Mitophagy was determined by western blot and immunofluorescence. The morphology and quantity of mitochondria were tracked by TEM. pCMV-Mito-AT1.03 was employed to detect the cellular ATP. Amyloid-β secreted by AD cells was detected by ELISA. Co-immunoprecipitation was used to investigate the binding partner of the target protein. Golgi-cox staining was applied to observe neuronal morphology of mice. The Morris water maze test and Y-maze were performed to assess spatial learning and memory, and the open field test was measured to evaluate motor function and anxiety-like phenotype of experimental animals. RESULTS: Mitochondrial morphology was impaired in AD models, and TBC1D5 was highly expressed. Knocking down TBC1D5 increased the expression of active Rab7, promoted the fusion of lysosome and autophagosome, thus improving mitophagy, and improved the morphology of hippocampal neurons and the impaired behavior in AD mice. CONCLUSIONS: Knocking down TBC1D5 increased Rab7 activity and promoted the fusion of autophagosome and lysosome. Our study provided insights into the mechanisms that bring new possibilities for AD therapy targeting mitophagy.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Disease Models, Animal; GTPase-Activating Proteins; Humans; Male; Mice; Mice, Transgenic; Mitochondria; Mitophagy; Neurons; rab GTP-Binding Proteins; rab7 GTP-Binding Proteins

Epistatic Features and Machine Learning Improve Alzheimer's Disease Risk Prediction Over Polygenic Risk Scores. - Hermes, Stephen; Cady, Janet; Armentrout, Steven; O'Connor, James; Holdaway, Sarah Carlson; Cruchaga, Carlos; Wingo, Thomas; Greytak, Ellen McRae (J Alzheimers Dis, 2024)
BACKGROUND: Polygenic risk scores (PRS) are linear combinations of genetic markers weighted by effect size that are commonly used to predict disease risk. For complex heritable diseases such as late-onset Alzheimer's disease (LOAD), PRS models fail to capture much of the heritability. Additionally, PRS models are highly dependent on the population structure of the data on which effect sizes are assessed and have poor generalizability to new data. OBJECTIVE: The goal of this study is to construct a paragenic risk score that, in addition to single genetic marker data used in PRS, incorporates epistatic interaction features and machine learning methods to predict risk for LOAD. METHODS: We construct a new state-of-the-art genetic model for risk of Alzheimer's disease. Our approach innovates over PRS models in two ways: First, by directly incorporating epistatic interactions between SNP loci using an evolutionary algorithm guided by shared pathway information; and second, by estimating risk via an ensemble of non-linear machine learning models rather than a single linear model. We compare the paragenic model to several PRS models from the literature trained on the same dataset. RESULTS: The paragenic model is significantly more accurate than the PRS models under 10-fold cross-validation, obtaining an AUC of 83% and near-clinically significant matched sensitivity/specificity of 75%. It remains significantly more accurate when evaluated on an independent holdout dataset and maintains accuracy within APOE genotype strata. CONCLUSIONS: Paragenic models show potential for improving disease risk prediction for complex heritable diseases such as LOAD over PRS models.
Keywords: Aged; Alzheimer Disease; Apolipoproteins E; Epistasis, Genetic; Female; Genetic Predisposition to Disease; Genetic Risk Score; Genome-Wide Association Study; Humans; Machine Learning; Male; Models, Genetic; Multifactorial Inheritance; Polymorphism, Single Nucleotide

Herpes Simplex Viral Infection Doubles the Risk of Dementia in a Contemporary Cohort of Older Adults: A Prospective Study. - Vestin, Erika; Boström, Gustaf; Olsson, Jan; Elgh, Fredrik; Lind, Lars; Kilander, Lena; Lövheim, Hugo; Weidung, Bodil (J Alzheimers Dis, 2024)
BACKGROUND: Evidence indicates that herpes simplex virus (HSV) participates in the pathogenesis of Alzheimer's disease (AD). OBJECTIVE: We investigated AD and dementia risks according to the presence of herpesvirus antibodies in relation to anti-herpesvirus treatment and potential APOE ɛ4 carriership interaction. METHODS: This study was conducted with 1002 dementia-free 70-year-olds living in Sweden in 2001-2005 who were followed for 15 years. Serum samples were analyzed to detect anti-HSV and anti-HSV-1 immunoglobulin (Ig) G, anti-cytomegalovirus (CMV) IgG, anti-HSV IgM, and anti-HSV and anti-CMV IgG levels. Diagnoses and drug prescriptions were collected from medical records. Cox proportional-hazards regression models were applied. RESULTS: Cumulative AD and all-cause dementia incidences were 4% and 7%, respectively. Eighty-two percent of participants were anti-HSV IgG carriers, of whom 6% received anti-herpesvirus treatment. Anti-HSV IgG was associated with a more than doubled dementia risk (fully adjusted hazard ratio = 2.26, p = 0.031). No significant association was found with AD, but the hazard ratio was of the same magnitude as for dementia. Anti-HSV IgM and anti-CMV IgG prevalence, anti-herpesvirus treatment, and anti-HSV and -CMV IgG levels were not associated with AD or dementia, nor were interactions between anti-HSV IgG and APOE ɛ4 or anti-CMV IgG. Similar results were obtained for HSV-1. CONCLUSIONS: HSV (but not CMV) infection may be indicative of doubled dementia risk. The low AD incidence in this cohort may have impaired the statistical power to detect associations with AD.

Hypertension, Cognitive Decline, and Mild Cognitive Impairment Among Diverse Hispanics/Latinos: Study of Latinos-Investigation of Neurocognitive Aging Results (SOL-INCA). - Márquez, Freddie; Tarraf, Wassim; Stickel, Ariana M; Gonzalez, Kevin A; Testai, Fernando D; Cai, Jianwen; Gallo, Linda C; Talavera, Gregory A; Daviglus, Martha L; Wassertheil-Smoller, Sylvia; DeCarli, Charles; Schneiderman, Neil; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Hypertension can have deleterious effects on cognitive function; however, few studies have examined its effects on cognition among Hispanics/Latinos. OBJECTIVE: To assess associations between hypertension status with 1) change in cognitive performance, and 2) having mild cognitive impairment (MCI) among diverse Hispanics/Latinos. METHODS: This population-based, prospective cohort, multisite study included Hispanic/Latino adults aged 45 to 72 years in enrolled in the Hispanic Community Health Study/Study of Latinos at Visit 1 (2008-2011; mean age of 63.40±8.24 years), and the Study of Latinos-Investigation of Neurocognitive Aging at Visit 2 (2016-2018), with a mean follow-up duration of 7 years (n = 6,173). Hypertension status was assessed at both visits: normotension (no hypertension), incident hypertension (only at Visit 2), and persistent hypertension (at both visits). We examined change in cognitive performance and having MCI (only assessed at Visit 2) relative to hypertension status and adjusted for demographics and cardiovascular disease risk factors. RESULTS: Compared to normotension, persistent hypertension was associated with significantly increased decline in verbal fluency (β= -0.08; CI = [-0.16;-0.01]; p < 0.05), and processing speed (β= -0.11; CI = [-0.20;-0.02]; p < 0.05). Incident hypertension was not associated with significant change in cognitive performance. Both incident (OR = 1.70; CI = [1.16;2.50]; p < 0.01) and persistent hypertension (OR = 2.13; CI = [1.57;2.88]; p < 0.001) were associated with significantly higher odds ratios of having MCI. CONCLUSIONS: These findings indicate that persistent hypertension is associated with clinical impairment and domain-specific cognitive decline in middle-aged and older Hispanics/Latinos. It underscores the importance of monitoring blood pressure in routine healthcare visits beginning at midlife in this population to reduce the burden of cognitive decline.

Improving Healthcare Quality and Clinical Outcomes for Persons with Dementia in the Sub-Acute Hospital Through Person-Centered Care Practice. - Chenoweth, Lynn; Burley, Claire; Cook, Jacquelene; Cheah, Seong-Leang; Reyes, Patricia; Maiden, Genevieve; McGuire, Jane; McCade, Donna; Brodaty, Henry; Sukhapure, Mayouri; Harrison, Fleur; Williams, Anna (J Alzheimers Dis, 2024)
BACKGROUND: Person-centered care is considered beneficial for persons with dementia. OBJECTIVE: To evaluate the impact of a person-centered knowledge translation intervention on the quality of healthcare and outcomes for persons with dementia. METHODS: Over nine months, sub-acute hospital nursing, allied health, and medical staff (n = 90) participated in online and/or face-to-face person-centered education and were supported by senior nursing, allied health, and medical staff champions (n = 8) to implement person-centered healthcare. The quality of healthcare service, ward climate and care delivery were evaluated pre/post study intervention. In the week following hospital admission (Time 1) and week of discharge (Time 3), agitation incidence (co-primary outcome) was assessed in participants with dementia (n = 80). Participant delirium (co-primary outcome), accidents/injuries, psychotropic medicines, length of stay, readmission and discharge destination (secondary outcomes) were compared with a retrospective group (n = 77) matched on demographics, cognition and function in activities of daily living. RESULTS: Improvements occurred post-intervention in service quality by 17.5% (p = 0.369, phi = 0.08), ward climate by 18.1% (p = 0.291, phi = 0.08), and care quality by 50% (p = 0.000, phi = 0.37). Participant agitation did not change from Time 1 to Time 3 (p = 0.223). Relative to the retrospective group, significant reductions occurred in participant delirium (p = 0.000, phi = 0.73), incidents/injuries (p = 0.000, phi = 0.99), psychotropic medicine use (p = 0.030, phi = 0.09), and hospital readmissions within 30 days (p = 0.002, phi = 0.25), but not in discharge to home (p = 0.171). CONCLUSIONS: When person-centered healthcare knowledge is translated through staff education and practice support, persons with dementia can experience improved healthcare services and clinical outcomes, while healthcare services can benefit through reductions in unplanned service use.

Interaction Between Arteriosclerosis and Amyloid-β on Cognitive Function. - Frentz, Ingeborg; van Arendonk, Joyce; Leeuwis, Anna E; Vernooij, Meike W; van der Flier, Wiesje M; Bos, Daniel; De Deyn, Peter Paul; Wolters, Frank J; Ikram, M Arfan (J Alzheimers Dis, 2024)
BACKGROUND: Dementia is a multifactorial disease, with Alzheimer's disease (AD) and vascular pathology often co-occurring in many individuals with dementia. Yet, the interplay between AD and vascular pathology in cognitive decline is largely undetermined. OBJECTIVE: The aim of the present study was to examine the joint effect of arteriosclerosis and AD pathology on cognition in the general population without dementia. METHODS: We determined the interaction between blood-based AD biomarkers and CT-defined arteriosclerosis on cognition in 2,229 dementia-free participants of the population-based Rotterdam Study (mean age: 68.9 years, 52% women) cross-sectionally. RESULTS: Amyloid-β (Aβ)42 and arterial calcification were associated with cognitive performance. After further adjustment for confounders in a model that combined all biomarkers, only arterial calcification remained independently associated with cognition. There was a significant interaction between arterial calcification and Aβ42 and between arterial calcification and the ratio of Aβ42/40. Yet, estimates attenuated, and interactions were no longer statistically significant after adjustment for cardio metabolic risk factors. CONCLUSIONS: Arteriosclerosis and AD display additive interaction-effects on cognition in the general population, that are due in part to cardio metabolic risk factors. These findings suggest that joint assessment of arteriosclerosis and AD pathology is important for understanding of disease etiology in individuals with cognitive impairment.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Arteriosclerosis; Biomarkers; Cognition; Cognitive Dysfunction; Female; Humans; Male; tau Proteins

Long-Term Safety of Gantenerumab in Participants with Alzheimer's Disease: A Phase III, Double-Blind, and Open-Label Extension Study (Marguerite RoAD). - Neve, Anuja; Das, Bibha; Wojtowicz, Jakub; Huang, Zhiyue; Bullain, Szofia; Watkin, Michelle; Lott, Dominik; Bittner, Tobias; Delmar, Paul; Klein, Gregory; Hofmann, Carsten; Kerchner, Geoffrey A; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Gantenerumab is an anti-amyloid-β immunoglobulin G1 monoclonal antibody for subcutaneous (SC) administration. The efficacy and safety of low-dose (105 mg or 225 mg) gantenerumab were investigated in Marguerite RoAD (MR; NCT02051608), a Phase III, double-blind (DB), placebo-controlled study in participants with mild Alzheimer's disease (AD) dementia. Following a preplanned futility analysis of the SCarlet RoAD study (NCT01224106), MR was converted into an open-label extension (OLE). OBJECTIVE: The DB study aimed to assess the efficacy of gantenerumab compared with placebo from baseline to Week 104 in participants with mild AD dementia. Following conversion to an OLE, this objective became exploratory, as the OLE assessed the long-term safety and tolerability of SC gantenerumab at doses of up to 1,200 mg every 4 weeks (Q4W) in OLE participants. METHODS: Eligible DB study participants were offered the opportunity to receive gantenerumab up-titrated to 1,200 mg Q4W. Safety and tolerability were assessed using magnetic resonance imaging (MRI), physical and neurologic examinations, and adverse event monitoring. RESULTS: Overall, 225 participants were rolled over from the DB part of MR and received ≥1 gantenerumab dose in the OLE. The median treatment duration was 123 weeks. Fifty-nine (26.2%) and 41 (18.2%) participants had amyloid-related imaging abnormality (ARIA)-edema and ARIA-hemorrhage MRI findings, respectively. ARIA findings were manageable with MRI monitoring and dose intervention; most were asymptomatic. There were no unexpected safety findings. CONCLUSIONS: SC gantenerumab at doses of up to 1,200 mg Q4W were well tolerated in participants with mild AD dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Antibodies, Monoclonal, Humanized; Double-Blind Method; Female; Humans; Male; Middle Aged; Treatment Outcome

Loss of Adaptive DNA Breaks in Alzheimer's Disease Brains. - Zhang, Xiaoyu; Haeri, Mohammad; Swerdlow, Russell H; Wang, Ning (J Alzheimers Dis, 2024)
BACKGROUND: DNA breaks accumulate in Alzheimer's disease (AD) brains. While their role as true genomic lesions is recognized, DNA breaks also support cognitive function by facilitating the expression of activity-dependent immediate early genes. This process involves TOP2B, a DNA topoisomerase that catalyzes the formation of DNA double-strand breaks. OBJECTIVE: To characterize how AD impacts adaptive DNA breaks at nervous system genes. METHODS: We leveraged the ability of DNA single- and double-strand breaks to activate poly(ADP-ribose) polymerases (PARPs) that conjugate poly(ADP-ribose) (PAR) to adjacent proteins. To characterize the genomic sites harboring DNA breaks in AD brains, nuclei extracted from 3 AD and 3 non-demented autopsy brains (frontal cortex, all male donors, age 78 to 91 years of age) were analyzed through CUT&RUN in which we targeted PAR with subsequent DNA sequencing. RESULTS: Although the AD brains contained 19.9 times more PAR peaks than the non-demented brains, PAR peaks at nervous system genes were profoundly lost in AD brains, and the expression of these genes was downregulated. This result is consistent with our previous CUT&RUN targeting γH2AX, which marks DNA double-strand breaks. In addition, TOP2B expression was significantly decreased in the AD brains. CONCLUSIONS: Although AD brains contain a net increase in DNA breaks, adaptive DNA breaks at nervous system genes are lost in AD brains. This could potentially reflect diminished TOP2B expression and contribute to impaired neuron function and cognition in AD patients.

Memory consolidation, temporal and parietal atrophy, and metabolism in amyloid-β positive and negative mild cognitive impairment. - Keith, Cierra M; Haut, Marc W; Vieira Ligo Teixeira, Camila; Mehta, Rashi I; Phelps, Holly; Ward, Melanie; Miller, Mark; Navia, R Osvaldo; Coleman, Michelle M; Marano, Gary; Wang, Xiaofei; Pockl, Stephanie; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is classically characterized by alterations in memory consolidation. With the advent of diagnostic biomarkers, some patients clinically diagnosed with AD display biomarkers inconsistent with the diagnosis. OBJECTIVE: We aimed to explore differences in memory consolidation and neurodegeneration of the temporal and parietal lobes as a function of amyloid-β status in amnestic mild cognitive impairment (aMCI). METHODS: We examined differences in memory consolidation and neurodegeneration between patients diagnosed with amyloid-β positive aMCI (Aβ+ N = 78), amyloid-β negative aMCI (Aβ- N = 48), and healthy participants (HP; N = 41), within a well-characterized clinical cohort. RESULTS: Aβ+ exhibited more pronounced consolidation impairments compared to Aβ-, while Aβ- faced more consolidation challenges than HP. Both Aβ+ and Aβ- were similar in hippocampal volume and entorhinal thickness, but Aβ+ had thinner inferior parietal cortex than Aβ-. Using F-fluoro-deoxyglucose-positron emission tomography, metabolism in both temporal and parietal regions was lower in Aβ+ relative to Aβ-. CONCLUSIONS: These findings suggest pathologies other than AD likely contribute to memory consolidation difficulties in aMCI, and neurodegeneration of the parietal cortex in combination with hypometabolism may contribute to more pronounced consolidation problems in Aβ+.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Atrophy; Cognitive Dysfunction; Female; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Memory Consolidation; Middle Aged; Neuropsychological Tests; Parietal Lobe; Positron-Emission Tomography; Temporal Lobe

A Metabolomics Analysis of a Novel Phenotype of Older Adults at Higher Risk of Dementia. - Sultana, Munira; Camicioli, Richard; Dixon, Roger A; Whitehead, Shawn; Pieruccini-Faria, Frederico; Petrotchenko, Evgeniy; Speechley, Mark; Borchers, Christoph H; Montero-Odasso, Manuel (J Alzheimers Dis, 2024)
BACKGROUND: Older adults presenting with dual-decline in cognition and walking speed face a 6-fold higher risk for dementia compared with those showing no decline. We hypothesized that the metabolomics profile of dual-decliners would be unique even before they show signs of decline in cognition and gait speed. OBJECTIVE: The objective of this study was to determine if plasma metabolomics signatures can discriminate dual-decliners from no decliners, purely cognitive decliners, and purely motor decliners prior to decline. METHODS: A retrospective cross-sectional study using baseline plasma for untargeted metabolomics analyses to investigate early signals of later dual-decline status in study participants (n = 76) with convenient sampling. Dual-decline was operationalized as decline in gait speed (>10 cm/s) and cognition (>2 points decline in Montreal Cognitive Assessment score) on at least two consecutive 6-monthly assessments. The participants' decliner status was evaluated 3 years after the blood sample was collected. Pair-wise comparison of detected compounds was completed using principal components and hierarchical clustering analyses. RESULTS: Analyses did not detect any cluster separation in untargeted metabolomes across baseline groups. However, follow-up analyses of specific molecules detected 4 compounds (17-Hydroxy-12-(hydroxymethyl)-10-oxo-8 oxapentacyclomethyl hexopyranoside, Fleroxacin, Oleic acid, and 5xi-11,12-Dihydroxyabieta-8(14),9(11),12-trien-20-oic acid) were at significantly higher concentration among the dual-decliners compared to non-decliners. The pure cognitive decliner group had significantly lower concentration of six compounds (1,3-nonanediol acetate, 4-(2-carboxyethyl)-2-methoxyphenyl beta-D-glucopyranosiduronic acid, oleic acid, 2E-3-[4-(sulfo-oxy)phenyl] acrylic acid, palmitelaidic acid, and myristoleic acid) compared to the non-decliner group. CONCLUSIONS: The unique metabolomics profile of dual-decliners warrants follow-up metabolomics analysis. Results may point to modifiable pathways.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Cross-Sectional Studies; Dementia; Female; Humans; Male; Metabolomics; Phenotype; Retrospective Studies

Microglial TLR4/NLRP3 Inflammasome Signaling in Alzheimer's Disease. - Li, Yunfeng; Chen, Xiongjin; Zhou, Mulan; Feng, Sifan; Peng, Xiaoping; Wang, Yan (J Alzheimers Dis, 2024)
Alzheimer's disease is a pervasive neurodegenerative disease that is estimated to represent approximately 70% of dementia cases worldwide, and the molecular complexity that has been highlighted remains poorly understood. The accumulation of extracellular amyloid-β (Aβ), intracellular neurofibrillary tangles formed by tau hyperphosphorylation, and neuroinflammation are the major pathological features of Alzheimer's disease (AD). Over the years, there has been no apparent breakthrough in drug discovery based on the Aβ and tau hypotheses. Neuroinflammation has gradually become a hot spot in AD treatment research. As the primary cells of innate immunity in the central nervous system, microglia play a key role in neuroinflammation. Toll-like receptor 4 (TLR4) and nucleotide-binding oligomerization domain-like receptor 3 (NLRP3) inflammasomes are vital molecules in neuroinflammation. In the pathological context of AD, the complex interplay between TLR4 and the NLRP3 inflammasomes in microglia influences AD pathology via neuroinflammation. In this review, the effect of the activation and inhibition of TLR4 and NLRP3 in microglia on AD pathology, as well as the cross-talk between TLR4 and the NLRP3 inflammasome, and the influence of essential molecules in the relevant signaling pathway on AD pathology, were expounded. In addition, the feasibility of these factors in representing a potential treatment option for AD has been clarified.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Humans; Inflammasomes; Microglia; Neurodegenerative Diseases; Neuroinflammatory Diseases; NLR Family, Pyrin Domain-Containing 3 Protein; Signal Transduction; Toll-Like Receptor 4

Mitochondria-Related Candidate Genes and Diagnostic Model to Predict Late-Onset Alzheimer's Disease and Mild Cognitive Impairment. - Yan, Ran; Wang, Wenjing; Yang, Wen; Huang, Masha; Xu, Wei (J Alzheimers Dis, 2024)
BACKGROUND: Late-onset Alzheimer's disease (LOAD) is the most common type of dementia, but its pathogenesis remains unclear, and there is a lack of simple and convenient early diagnostic markers to predict the occurrence. OBJECTIVE: Our study aimed to identify diagnostic candidate genes to predict LOAD by machine learning methods. METHODS: Three publicly available datasets from the Gene Expression Omnibus (GEO) database containing peripheral blood gene expression data for LOAD, mild cognitive impairment (MCI), and controls (CN) were downloaded. Differential expression analysis, the least absolute shrinkage and selection operator (LASSO), and support vector machine recursive feature elimination (SVM-RFE) were used to identify LOAD diagnostic candidate genes. These candidate genes were then validated in the validation group and clinical samples, and a LOAD prediction model was established. RESULTS: LASSO and SVM-RFE analyses identified 3 mitochondria-related genes (MRGs) as candidate genes, including NDUFA1, NDUFS5, and NDUFB3. In the verification of 3 MRGs, the AUC values showed that NDUFA1, NDUFS5 had better predictability. We also verified the candidate MRGs in MCI groups, the AUC values showed good performance. We then used NDUFA1, NDUFS5 and age to build a LOAD diagnostic model and AUC was 0.723. Results of qRT-PCR experiments with clinical blood samples showed that the three candidate genes were expressed significantly lower in the LOAD and MCI groups when compared to CN. CONCLUSION: Two mitochondrial-related candidate genes, NDUFA1 and NDUFS5, were identified as diagnostic markers for LOAD and MCI. Combining these two candidate genes with age, a LOAD diagnostic prediction model was successfully constructed.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Female; Humans; Male; Mitochondria; Support Vector Machine

A Novel Score to Predict Individual Risk for Future Alzheimer's Disease: A Longitudinal Study of the ADNI Cohort. - Guo, Hongxiu; Sun, Shangqi; Yang, Yang; Ma, Rong; Wang, Cailin; Zheng, Siyi; Wang, Xiufeng; Li, Gang (J Alzheimers Dis, 2024)
BACKGROUND: Identifying high-risk individuals with mild cognitive impairment (MCI) who are likely to progress to Alzheimer's disease (AD) is crucial for early intervention. OBJECTIVE: This study aimed to develop and validate a novel clinical score for personalized estimation of MCI-to-AD conversion. METHODS: The data from the Alzheimer's Disease Neuroimaging Initiative (ADNI) study were analyzed. Two-thirds of the MCI patients were randomly assigned to a training cohort (n = 478), and the remaining one-third formed the validation cohort (n = 239). Multivariable logistic regression was performed to identify factors associated with MCI-to-AD progression within 4 years. A prediction score was developed based on the regression coefficients derived from the logistic model and tested in the validation cohort. RESULTS: A lipidomics-signature was obtained that showed a significant association with disease progression. The MCI conversion scoring system (ranged from 0 to 14 points), consisting of the lipidomics-signature and five other significant variables (Apolipoprotein ɛ4, Rey Auditory Verbal Learning Test immediate and delayed recall, Alzheimer's Disease Assessment Scale delayed recall test, Functional Activities Questionnaire, and cortical thickness of the AD signature), was constructed. Higher conversion scores were associated with a higher proportion of patients converting to AD. The scoring system demonstrated good discrimination and calibration in both the training cohort (AUC = 0.879, p of Hosmer-Lemeshow test = 0.597) and the validation cohort (AUC = 0.915, p of Hosmer-Lemeshow test = 0.991). The risk classification achieved excellent sensitivity (0.84) and specificity (0.75). CONCLUSIONS: The MCI-to-AD conversion score is a reliable tool for predicting the risk of disease progression in individuals with MCI.

Parkinson's Disease and Other Alzheimer's Disease and Related Dementia Pathologies and the Progression of Parkinsonism in Older Adults. - Buchman, Aron S; Yu, Lei; Oveisgharan, Shahram; Zammit, Andrea R; Wang, Tianhao; Shulman, Joshua M; VanderHorst, Veronique; Nag, Sukrit; Bennett, David A (J Alzheimers Dis, 2024)
BACKGROUND: The interrelationship of parkinsonism, Parkinson's disease (PD) and other Alzheimer's disease (AD) and Alzheimer's disease and related dementias (ADRD) pathologies is unclear. OBJECTIVE: We examined the progression of parkinsonian signs in adults with and without parkinsonism, and their underlying brain pathologies. METHODS: Annual parkinsonian signs were based on a modified Unified Parkinson's Disease Rating Scale. We used linear mixed effects models to compare the progression of parkinsonian signs in 3 groups categorized based on all available clinical evaluations: Group1 (never parkinsonism or clinical PD), Group2 (ever parkinsonism, but never clinical PD), Group3 (ever clinical PD). In decedents, we examined the progression of parkinsonian signs with PD and eight other AD/ADRD pathologies. RESULTS: During average follow-up of 8 years, parkinsonian signs on average increased by 7.3% SD/year (N = 3,807). The progression of parkinsonian signs was slowest in Group1 (never parkinsonism or clinical PD), intermediate in Group2, and fastest in Group3. In decedents (n = 1,717) pathologic PD and cerebrovascular (CVD) pathologies were associated with a faster rate of progressive parkinsonian signs (all p values <0.05). However, pathologic PD was rare in adults without clinical PD (Group1, 5%; Group2, 7% versus Group3, 55%). Yet, 70% of adults in Group2 without pathologic PD showed one or more CVD pathologies. In Group2, adults with pathologic PD showed faster progression of parkinsonian signs compared with those without evidence of pathologic PD and their rate of progression was indistinguishable from adults with clinical PD. CONCLUSIONS: Parkinsonism in old age is more commonly related to cerebrovascular pathologies relative to pathologic PD and only a minority manifest prodromal PD.

Pharmacologic and Nutritional Interventions for Early Alzheimer's Disease: A Systematic Review and Network Meta-Analysis of Randomized Controlled Trials. - Zeng, Baoqi; Tang, Chunbian; Wang, Junjian; Yang, Qingqing; Ren, Qingcuo; Liu, Xiaozhi (J Alzheimers Dis, 2024)
BACKGROUND: Early intervention is essential for meaningful disease modification in Alzheimer's disease (AD). OBJECTIVE: We aimed to determine the efficacy and safety of pharmacologic and nutritional interventions for early AD. METHODS: PubMed, Embase, the Cochrane Library, and ClinicalTrials.gov were searched from database inception until 1 September 2023. We included randomized controlled trials that evaluated the efficacy of interventions in early AD. Only interventions that demonstrated efficacy compared to placebo were included in the network meta-analysis (NMA). Then we performed frequentist fixed-effects NMA to rank the interventions. GRADE criteria were used to evaluate the level of evidence. RESULTS: Fifty-eight trials including a total of 33,864 participants and 48 interventions were eligible for inclusion. Among the 48 interventions analyzed, only 6 (12.5%) treatments- ranging from low to high certainty- showed significant improvement in cognitive decline compared to placebo. High certainty evidence indicated that donanemab (standardized mean difference [SMD] -0.239, 95% confidence interval [CI] -0.343 to -0.134) and lecanemab (SMD -0.194, 95% CI -0.279 to -0.108) moderately slowed the clinical progression in patients with amyloid pathology. Additionally, methylphenidate, donepezil, LipiDiDiet, and aducanumab with low certainty showed significant improvement in cognitive decline compared to placebo. However, there was no significant difference in serious adverse events as reported between the six interventions and placebo. CONCLUSIONS: Only 12.5% of interventions studied demonstrated efficacy in reducing cognitive impairment in early AD. Donanemab and lecanemab have the potential to moderately slow the clinical progression in patients with amyloid pathology. Further evidence is required for early intervention in AD.
Keywords: Alzheimer Disease; Humans; Network Meta-Analysis; Randomized Controlled Trials as Topic

Plasma BDNF/Irisin Ratio Associates with Cognitive Function in Older People. - Huang, Xiuxiu; Wang, Jiaxin; Zhang, Shifang; Zhao, Xiaoyan; An, Ran; Lan, Yue; Yi, Ming; Wan, Qiaoqin (J Alzheimers Dis, 2024)
BACKGROUND: Reliable blood biomarkers are crucial for early detection and treatment evaluation of cognitive impairment, including Alzheimer's disease and other dementias. OBJECTIVE: To examine whether plasma biomarkers and their combination are different between older people with mild cognitive impairment (MCI) and cognitively normal individuals, and to explore their relations with cognitive performance. METHODS: This cross-sectional study included 250 older adults, including 124 participants with MCI, and 126 cognitively normal participants. Plasma brain-derived neurotrophic factor (BDNF), irisin and clusterin were measured, and BDNF/irisin ratio was calculated. Global cognition was evaluated by the Montreal Cognitive Assessment. RESULTS: Plasma irisin levels, but not BDNF, were significantly different between MCI group and cognitively normal group. Higher irisin concentration was associated with an increased probability for MCI both before and after controlling covariates. By contrast, plasma BDNF concentration, but not irisin, was linearly correlated with cognitive performance after adjusting for covariates. Higher BDNF/irisin ratios were not only correlated with better cognitive performance, but also associated with lower risks of MCI, no matter whether we adjusted for covariates. Plasma BDNF and irisin concentrations increased with aging, whereas BDNF/irisin ratios remained stable. No significant results of clusterin were observed. CONCLUSIONS: Plasma BDNF/irisin ratio may be a reliable indicator which not only reflects the odds of the presence of MCI but also directly associates with cognitive performance.
Keywords: Aged; Aged, 80 and over; Aging; Biomarkers; Brain-Derived Neurotrophic Factor; Clusterin; Cognition; Cognitive Dysfunction; Cross-Sectional Studies; Female; Fibronectins; Humans; Male; Mental Status and Dementia Tests; Neuropsychological Tests

Pre-existing dementia is associated with 2-3 folds risk for in-hospital mortality and complications after intracerebral hemorrhage stroke. - Zuo, Lijun; Hu, Yang; Dong, YanHong; Seet, Raymond Cs; Li, Zixiao; Wang, Yongjun; Zhao, Xingquan (J Alzheimers Dis, 2024)
BACKGROUND: Pre-existing dementia was related to poor functional outcome after intracerebral hemorrhage (ICH), and its commonly underlying pathologies were considered as cerebral amyloid angiopathy. But the impact of pre-existing dementia on in-hospital mortality in Chinese ICH patients has not been well characterized. OBJECTIVE: To investigate the association between pre-existing dementia and in-hospital mortality after ICH. METHODS: Data were extracted from the China Stroke Center Alliance database. Information about the existence of prior to stroke dementia was obtained from next of kin informants and registered in clinical charts. Patients' characteristics, in-hospital mortality, home discharge and complications were compared between ICH patients with and without pre-existing dementia. RESULTS: Out of the 72,318 ICH patients, we identified 328 patients with pre-existing dementia. Patients with pre-existing dementia were more likely to experience greater stroke severity as measured by the National Institute of Health Stroke Scale and Glasgow Coma Scale. In the adjusted models, the presence of pre-existing dementia was associated with an increased risk of in-hospital mortality (OR 2.31, 95% CI 1.12-4.77), more frequent in-hospital complications of pulmonary embolism (OR 5.41, 95% CI 1.16-25.14), pneumonia (OR 1.58, 95% CI 1.08-2.33), urinary tract infection (OR 2.37, 95% CI 1.21-4.64), gastrointestinal bleeding (OR 2.39, 95% CI 1.27-4.49) and lower home discharge (OR 0.59, 95% CI 0.38∼0.93). CONCLUSIONS: ICH patients with pre-existing dementia are more likely to suffer from greater stroke severity, poorer outcomes and lower home discharge. Future studies should evaluate the value of intensive risk factor control among individuals with pre-existing dementia for stroke prevention.
Keywords: Aged; Aged, 80 and over; Cerebral Hemorrhage; China; Dementia; Female; Hemorrhagic Stroke; Hospital Mortality; Humans; Male; Middle Aged; Risk Factors; Stroke

A Scoping Review of Alzheimers Disease Hypotheses: An Array of Uni- and Multi-Factorial Theories. - Duchesne, Simon; Rousseau, Louis-Simon; Belzile-Marsolais, Florence; Welch, Laurie-Ann; Cournoyer, Béatrice; Arseneau, Marianne; Lapierre, Véronick; Poulin, Sara-Maude; Potvin, Olivier; Hudon, Carol (J Alzheimers Dis, 2024)
BACKGROUND: There is a common agreement that Alzheimers disease (AD) is inherently complex; otherwise, a general disagreement remains on its etiological underpinning, with numerous alternative hypotheses having been proposed. OBJECTIVE: To perform a scoping review of original manuscripts describing hypotheses and theories of AD published in the past decades. RESULTS: We reviewed 131 original manuscripts that fulfilled our inclusion criteria out of more than 13,807 references extracted from open databases. Each entry was characterized as having a single or multifactorial focus and assigned to one of 15 theoretical groupings. Impact was tracked using open citation tools. RESULTS: Three stages can be discerned in terms of hypotheses generation, with three quarter of studies proposing a hypothesis characterized as being single-focus. The most important theoretical groupings were the Amyloid group, followed by Metabolism and Mitochondrial dysfunction, then Infections and Cerebrovascular. Lately, evidence towards Genetics and especially Gut/Brain interactions came to the fore. CONCLUSIONS: When viewed together, these multi-faceted reports reinforce the notion that AD affects multiple sub-cellular, cellular, anatomical, and physiological systems at the same time but at varying degree between individuals. The challenge of providing a comprehensive view of all systems and their interactions remains, alongside ways to manage this inherent complexity.
Keywords: Alzheimer Disease; Brain; Humans

Small RNA Profiles of Brain Tissue-Derived Extracellular Vesicles in Alzheimer's Disease. - Huang, Yiyao; Driedonks, Tom A P; Cheng, Lesley; Turchinovich, Andrey; Pletniková, Olga; Redding-Ochoa, Javier; Troncoso, Juan C; Hill, Andrew F; Mahairaki, Vasiliki; Zheng, Lei; Witwer, Kenneth W (J Alzheimers Dis, 2024)
BACKGROUND: Extracellular vesicles (EVs) and non-coding RNAs (ncRNAs) are emerging contributors to Alzheimer's disease (AD) pathophysiology. Differential abundance of ncRNAs carried by EVs may provide valuable insights into underlying disease mechanisms. Brain tissue-derived EVs (bdEVs) are particularly relevant, as they may offer valuable insights about the tissue of origin. However, there is limited research on diverse ncRNA species in bdEVs in AD. OBJECTIVE: This study explored whether the non-coding RNA composition of EVs isolated from post-mortem brain tissue is related to AD pathogenesis. METHODS: bdEVs from age-matched late-stage AD patients (n = 23) and controls (n = 10) that had been separated and characterized in our previous study were used for RNA extraction, small RNA sequencing, and qPCR verification. RESULTS: Significant differences of non-coding RNAs between AD and controls were found, especially for miRNAs and tRNAs. AD pathology-related miRNA and tRNA differences of bdEVs partially matched expression differences in source brain tissues. AD pathology had a more prominent association than biological sex with bdEV miRNA and tRNA components in late-stage AD brains. CONCLUSIONS: Our study provides further evidence that EV non-coding RNAs from human brain tissue, including but not limited to miRNAs, may be altered and contribute to AD pathogenesis.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Extracellular Vesicles; Female; Humans; Male; MicroRNAs; RNA, Small Untranslated; RNA, Transfer; RNA, Untranslated

Space-Like Irradiation Exacerbated Cognitive Deficits and Amyloid Pathology in CRND8 Mouse Model of Alzheimer's Disease. - Wang, Wenzhang; Zhao, Fanpeng; Torres, Sandy; Harris, Peggy L R; Wang, Xinglong; Peng, Lihua; Siedlak, Sandra L; Zhu, Xiongwei (J Alzheimers Dis, 2024)
BACKGROUND: Space radiation was linked to neurological damage and behavioral deficits which raised concerns of increased degenerative risk on the brain and development of Alzheimer's disease following space travel. OBJECTIVE: In this study, we investigated the effects of irradiation by 56Fe and 28Si in CRND8 mice, an Alzheimer's disease mouse model. METHODS: Six-month-old CRND8 mice were exposed to whole body irradiation by 56Fe and 28Si at 0.5 Gy and 2 Gy doses. Behavior tests were administered 1-month to 3-months post-irradiation. Amyloid deposition and other pathological changes were analyzed 3-months and/or 6-months post-irradiatio. RESULTS: The Novel Object Recognition test showed some decline in 8-month-old mice compared to non-irradiated CRND8 mice. Male mice also showed a loss of freezing behavior in the fear conditioning contextual test following irradiation. Golgi staining revealed a loss of spines in hippocampal neurons after irradiation. Total amyloid immunohistochemistry showed a robust increase in 3-months post-irradiation 56Fe groups which became normalized to non-irradiated group by 6-months post-irradiation. However, 2 Gy 28Si caused a trend towards increased plaque load at 3-months post-irradiation which became significant at 6-months post irradiation only in male CRND8 mice. While 0.5 Gy Fe did not induce obvious changes in the total number of iba-1 positive microglia, more hippocampal microglia were found to express PCNA after 0.5 Gy Fe treatment, suggesting potential involvement of microglial dysfunction. CONCLUSIONS: Overall, our study provides new evidence of gender-specific and ion-dependent effects of space radiation on cognition and amyloid pathology in AD models.

Substantial Doubt Remains about the Efficacy of Anti-Amyloid Antibodies. - Digma, Leonardino A; Winer, Joseph R; Greicius, Michael D (J Alzheimers Dis, 2024)
With the FDA approval of aducanumab and lecanemab, and with the recent statistically significant phase 3 clinical trial for donanemab, there is growing enthusiasm for anti-amyloid antibodies in the treatment of Alzheimer's disease. Here, we discuss three substantial limitations regarding recent anti-amyloid clinical trials: 1) there is little evidence that amyloid reduction correlates with clinical outcome, 2) the reported efficacy of anti-amyloid therapies may be explained by functional unblinding, and 3) donanemab had no effect on tau burden in its phase 3 trial. Taken together, these observations call into question the efficacy of anti-amyloid therapies.
Keywords: Alzheimer Disease; Amyloidogenic Proteins; Antibodies, Monoclonal, Humanized; Emotions; Humans

Symptomatic Clusters Related to Amyloid Positivity in Cognitively Unimpaired Individuals. - Sannemann, Lena; Bartels, Claudia; Brosseron, Frederic; Buerger, Katharina; Fliessbach, Klaus; Freiesleben, Silka Dawn; Frommann, Ingo; Glanz, Wenzel; Heneka, Michael T; Janowitz, Daniel; Kilimann, Ingo; Kleineidam, Luca; et al. (J Alzheimers Dis, 2024)
BACKGROUND: The NIA-AA Research Framework on Alzheimer's disease (AD) proposes a transitional stage (stage 2) characterized by subtle cognitive decline, subjective cognitive decline (SCD) and mild neurobehavioral symptoms (NPS). OBJECTIVE: To identify participant clusters based on stage 2 features and assess their association with amyloid positivity in cognitively unimpaired individuals. METHODS: We included baseline data of N = 338 cognitively unimpaired participants from the DELCODE cohort with data on cerebrospinal fluid biomarkers for AD. Classification into the AD continuum (i.e., amyloid positivity, A+) was based on Aβ42/40 status. Neuropsychological test data were used to assess subtle objective cognitive dysfunction (OBJ), the subjective cognitive decline interview (SCD-I) was used to detect SCD, and the Neuropsychiatric Inventory Questionnaire (NPI-Q) was used to assess NPS. A two-step cluster analysis was carried out and differences in AD biomarkers between clusters were analyzed. RESULTS: We identified three distinct participant clusters based on presented symptoms. The highest rate of A+ participants (47.6% ) was found in a cluster characterized by both OBJ and SCD. A cluster of participants that presented with SCD and NPS (A+:26.6% ) and a cluster of participants with overall few symptoms (A+:19.7% ) showed amyloid positivity in a range that was not higher than the expected A+ rate for the age group. Across the full sample, participants with a combination of SCD and OBJ in the memory domain showed a lower Aβ42/ptau181 ratio compared to those with neither SCD nor OBJ. CONCLUSIONS: The cluster characterized by participants with OBJ and concomitant SCD was enriched for amyloid pathology.

There are dementia patients in Gaza too. - Irfan, Bilal; Abu Shammala, Abdallah; Alshaer, Nour; Nasser, Elias; Wajahath, Muaaz; Hamawy, Adam; Tahir, Mohammed; Khawaja, Haseeb; Khan, Osaama; Fikry, Karim; Kaleem, Arshad; Nasser, Mosab; et al. (J Alzheimers Dis, 2024)
This editorial highlights the devastating impact of the ongoing Israeli military assault in Gaza on dementia patients, whose fragile care systems have collapsed, leaving them vulnerable and without essential medical support. Through harrowing stories of displacement, medication shortages, and tragic deaths, the piece underscores the profound moral failure in protecting Gaza's most vulnerable, calling for urgent global action to address the humanitarian crisis and ensure dignity and healthcare for all affected individuals.
Keywords: Dementia; Humans; Middle East

A 19-Year-Old Adolescent with Probable Alzheimer's Disease. - Jia, Jianping; Zhang, Yue; Shi, Yuqing; Yin, Xuping; Wang, Shiyuan; Li, Yan; Zhao, Tan; Liu, Wenying; Zhou, Aihong; Jia, Longfei (J Alzheimers Dis, 2023)
Alzheimer's disease (AD) primarily affects older adults. In this report, we present the case of a 19-year-old male with gradual memory decline for 2 years and World Health Organization-University of California Los Angeles Auditory Verbal Learning Test (WHO-UCLA AVLT) results also showing memory impairment. Positron emission tomography-magnetic resonance imaging with 18F fluorodeoxyglucose revealed atrophy of the bilateral hippocampus and hypometabolism in the bilateral temporal lobe. Examination of the patient's cerebrospinal fluid showed an increased concentration of p-tau181 and a decreased amyloid-β 42/40 ratio. However, through whole-genome sequencing, no known gene mutations were identified. Considering the above, the patient was diagnosed with probable AD.
Keywords: Adolescent; Aged; Alzheimer Disease; Amyloid beta-Peptides; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Positron-Emission Tomography

Activation of TNF Receptor 2 Improves Synaptic Plasticity and Enhances Amyloid-β Clearance in an Alzheimer's Disease Mouse Model with Humanized TNF Receptor 2. - Ortí-Casañ, Natalia; Wajant, Harald; Kuiperij, H Bea; Hooijsma, Annelien; Tromp, Leon; Poortman, Isabelle L; Tadema, Norick; de Lange, Julia H E; Verbeek, Marcel M; De Deyn, Peter P; Naudé, Petrus J W; Eisel, Ulrich L M (J Alzheimers Dis, 2023)
BACKGROUND: Tumor necrosis factor-alpha (TNF-α) is a master cytokine involved in a variety of inflammatory and neurological diseases, including Alzheimer's disease (AD). Therapies that block TNF-α proved ineffective as therapeutic for neurodegenerative diseases, which might be explained by the opposing functions of the two receptors of TNF (TNFRs): while TNFR1 stimulation mediates inflammatory and apoptotic pathways, activation of TNFR2 is related to neuroprotection. Despite the success of targeting TNFR2 in a transgenic AD mouse model, research that better mimics the human context is lacking. OBJECTIVE: The aim of this study is to investigate whether stimulation of TNFR2 with a TNFR2 agonist is effective in activating human TNFR2 and attenuating AD neuropathology in the J20xhuTNFR2-k/i mouse model. METHODS: Transgenic amyloid-β (Aβ)-overexpressing mice containing a human extracellular TNFR2 domain (J20xhuTNFR2-k/i) were treated with a TNFR2 agonist (NewStar2). After treatment, different behavioral tests and immunohistochemical analysis were performed to assess different parameters, such as cognitive functions, plaque deposition, synaptic plasticity, or microglial phagocytosis. RESULTS: Treatment with NewStar2 in J20xhuTNFR2-k/i mice resulted in a drastic decrease in plaque load and beta-secretase 1 (BACE-1) compared to controls. Moreover, TNFR2 stimulation increased microglial phagocytic activity, leading to enhanced Aβ clearance. Finally, activation of TNFR2 rescued cognitive impairments and improved synaptic plasticity. CONCLUSION: Our findings demonstrate that activation of human TNFR2 ameliorates neuropathology and improves cognitive functions in an AD mouse model. Moreover, our study confirms that the J20xhuTNFR2-k/i mouse model is suitable for testing human TNFR2-specific compounds.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Humans; Mice; Mice, Transgenic; Neuronal Plasticity; Receptors, Tumor Necrosis Factor, Type II; Tumor Necrosis Factor-alpha

Age-Related Association Between APOE ɛ4 and Cognitive Progression in de novo Parkinson's Disease. - Liu, Jia-Yao; Ma, Ling-Zhi; Wang, Jun; Cui, Xin-Jing; Sheng, Ze-Hu; Fu, Yan; Li, Meng; Ou, Ya-Nan; Yu, Jin-Tai; Tan, Lan; Lian, Yan (J Alzheimers Dis, 2023)
BACKGROUND: APOE ɛ4 genotype was correlated with exacerbation of pathology and higher risk of dementia in Parkinson's disease (PD). Meanwhile, the differential influence of APOE ɛ4 on cognition in young and old individuals interpreted as antagonistic pleiotropy. OBJECTIVE: To examine whether the effect of APOE ɛ4 on cognitive progression in de novo PD is age dependent. METHODS: In this study, 613 de novo PD patients were recruited from Parkinson's Progression Markers Initiative (PPMI). To examine the age-dependent relationship between APOE ɛ4 and cognitive changes, we added 3-way interaction of APOE ɛ4*baseline age*time to the linear mixed-effect (LME) models and evaluated the specific roles of APOE ɛ4 in the middle age group and elderly group separately. Cox regression was utilized to examine the progression of cognition in age-stratified PD participants. RESULTS: Age significantly modified relationship between APOE ɛ4 and cognitive changes in most cognitive domains (pinteraction <0.05). In the elderly group, APOE ɛ4 carriers showed steeper decline in global cognition (p = 0.001) as well as in most cognitive domains, and they had a greater risk of cognitive progression (adjusted HR 1.625, 95% CI 1.143-2.310, p = 0.007), compared with non-carriers. However, in the middle age group, no significant relationships between APOE ɛ4 and cognitive decline can be detected. CONCLUSION: Our results indicated that the APOE ɛ4 allele has an age-dependent effect on cognitive decline in PD patients. The underlying mechanisms need to be investigated in the future.
Keywords: Aged; Apolipoprotein E4; Cognition; Cognitive Dysfunction; Disease Progression; Genotype; Heterozygote; Humans; Parkinson Disease

Association of Sarcopenia and Its Defining Components with the Degree of Cognitive Impairment in a Memory Clinic Population. - Larsson, LE; Wang, Rui; Cederholm, Tommy; Wiggenraad, Fleur; Rydén, Marie; Hagman, Göran; Hellénius, Mai-Lis; Kivipelto, Miia; Thunborg, Charlotta (J Alzheimers Dis, 2023)
BACKGROUND: Sarcopenia and cognitive impairment are two leading causes of disabilities. OBJECTIVE: The objective was to examine the prevalence of sarcopenia and investigate the association between sarcopenia diagnostic components (muscle strength, muscle mass, and physical performance) and cognitive impairment in memory clinic patients. METHODS: 368 patients were included (age 59.0±7.25 years, women: 58.7%), displaying three clinical phenotypes of cognitive impairments, i.e., subjective cognitive impairment (SCI, 57%), mild cognitive impairment (MCI, 26%), and Alzheimer's disease (AD, 17%). Sarcopenia was defined according to diagnostic algorithm recommended by the European Working Group on Sarcopenia in Older People. Components of sarcopenia were grip strength, bioelectrical impedance analysis, and gait speed. They were further aggregated into a score (0-3 points) by counting the numbers of limited components. Multi-nominal logistic regression was applied. RESULTS: Probable sarcopenia (i.e., reduced grip strength) was observed in 9.6% of the patients, and 3.5% were diagnosed with sarcopenia. Patients with faster gait speed showed less likelihood of MCI (odds ratio [OR]: 0.24, 95% confidence interval [CI]: 0.06-0.90) and AD (OR: 0.12, 95% CI: 0.03-0.60). One or more limited sarcopenia components was associated with worse cognitive function. After adjusting for potential confounders, the association remained significant only for AD (OR 4.29, 95% CI 1.45-11.92). CONCLUSION: The results indicate a connection between the sarcopenia components and cognitive impairments. Limitations in the sarcopenia measures, especially slow walking speed, were related to poorer cognitive outcomes. More investigationsare required to further verify the causal relationship between sarcopenia and cognitive outcomes.

Associations Between Ambient Air Pollution and Cognitive Abilities from Midlife to Early Old Age: Modification by APOE Genotype. - Franz, Carol E; Gustavson, Daniel E; Elman, Jeremy A; Fennema-Notestine, Christine; Hagler, Donald J; Baraff, Aaron; Tu, Xin M; Wu, Tsung-Chin; De Anda, Jaden; Beck, Asad; Kaufman, Joel D; Whitsel, Nathan; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Fine particulate matter (PM2.5) and nitrogen dioxide (NO2) measures of ambient air pollution are associated with accelerated age-related cognitive impairment, and Alzheimer's disease and related dementias (ADRD). OBJECTIVE: We examined associations between air pollution, four cognitive factors, and the moderating role of apolipoprotein E (APOE) genotype in the understudied period of midlife. METHODS: Participants were ∼1,100 men in the Vietnam Era Twin Study of Aging. Baseline cognitive assessments were from 2003 to 2007. Measures included past (1993-1999) and recent (3 years prior to baseline assessment) PM2.5 and NO2 exposure, in-person assessment of episodic memory, executive function, verbal fluency, and processing speed, and APOE genotype. Average baseline age was 56 years with a 12-year follow-up. Analyses adjusted for health and lifestyle covariates. RESULTS: Performance in all cognitive domains declined from age 56 to 68. Higher PM2.5 exposures were associated with worse general verbal fluency. We found significant exposure-by-APOE genotype interactions for specific cognitive domains: PM2.5 with executive function and NO2 with episodic memory. Higher PM2.5 exposure was related to worse executive function in APOE ɛ4 carriers, but not in non-carriers. There were no associations with processing speed. CONCLUSION: These results indicate negative effects of ambient air pollution exposure on fluency alongside intriguing differential modifications of cognitive performance by APOE genotype. APOE ɛ4 carriers appeared more sensitive to environmental differences. The process by which air pollution and its interaction with genetic risk for ADRD affects risk for later life cognitive decline or progression to dementia may begin in midlife.

Associations of the Harvard Automated Phone Task and Alzheimer's Disease Pathology in Cognitively Normal Older Adults: Preliminary Findings. - Gonzalez, Christopher; Mimmack, Kayden J; Amariglio, Rebecca E; Becker, J Alex; Chhatwal, Jasmeer P; Fitzpatrick, Colleen D; Gatchel, Jennifer R; Johnson, Keith A; Katz, Zoe S; Kuppe, Madeline K; Locascio, Joseph J; Udeogu, Onyinye J; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Detecting clinically meaningful changes in instrumental activities of daily living (IADL) at the earliest stages of Alzheimer's disease (AD) is critical. OBJECTIVE: The objective of this exploratory study was to examine the cross-sectional relationship between a performance-based IADL test, the Harvard Automated Phone Task (APT), and cerebral tau and amyloid burden in cognitively normal (CN) older adults. METHODS: Seventy-seven CN participants underwent flortaucipir tau and Pittsburgh Compound B amyloid PET. IADL were assessed using the three Harvard APT tasks: prescription refill (APT-Script), health insurance company call (APT-PCP), and bank transaction (APT-Bank). Linear regression models were used to determine associations between each APT task and entorhinal cortex, inferior temporal, or precuneus tau with or without an interaction with amyloid. RESULTS: Significant associations were found between APT-Bank task rate and interaction between amyloid and entorhinal cortex tau, and APT-PCP task and interactions between amyloid and inferior temporal and precuneus tau. No significant associations were found between the APT tasks and tau or amyloid alone. CONCLUSION: Our preliminary findings suggest an association between a simulated real-life IADL test and interactions of amyloid and several regions of early tau accumulation in CN older adults. However, some analyses were underpowered due to the small number of participants with elevated amyloid, and findings should be interpreted with caution. Future studies will further explore these associations cross-sectionally and longitudinally in order to determine whether the Harvard APT can serve as a reliable IADL outcome measure for preclinical AD prevention trials and ultimately in the clinic setting.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Amyloidogenic Proteins; Cognitive Dysfunction; Entorhinal Cortex; Humans; Positron-Emission Tomography; tau Proteins

Cognitive and Neuropsychological Profiles in Alzheimer's Disease and Primary Age-Related Tauopathy and the Influence of Comorbid Neuropathologies. - Walker, Jamie M; Gonzales, Mitzi M; Goette, William; Farrell, Kurt; White Iii, Charles L; Crary, John F; Richardson, Timothy E (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease neuropathologic change (ADNC) is defined by the progression of both hyperphosphorylated-tau (p-tau) and amyloid-β (Aβ) and is the most common underlying cause of dementia worldwide. Primary age-related tauopathy (PART), an Aβ-negative tauopathy largely confined to the medial temporal lobe, is increasingly being recognized as an entity separate from ADNC with diverging clinical, genetic, neuroanatomic, and radiologic profiles. OBJECTIVE: The specific clinical correlates of PART are largely unknown; we aimed to identify cognitive and neuropsychological differences between PART, ADNC, and subjects with no tauopathy (NT). METHODS: We compared 2,884 subjects with autopsy-confirmed intermediate-high stage ADNC to 208 subjects with definite PART (Braak stage I-IV, Thal phase 0, CERAD NP score "absent") and 178 NT subjects from the National Alzheimer's Coordinating Center dataset. RESULTS: PART subjects were older than either ADNC or NT patients. The ADNC cohort had more frequent neuropathological comorbidities as well as APOE ɛ4 alleles than the PART or NT cohort, and less frequent APOE ɛ2 alleles than either group. Clinically, ADNC patients performed significantly worse than NT or PART subjects across cognitive measures, but PART subjects had selective deficits in measures of processing speed, executive function, and visuospatial function, although additional cognitive measures were further impaired in the presence of neuropathologic comorbidities. In isolated cases of PART with Braak stage III-IV, there are additional deficits in measures of language. CONCLUSION: Overall, these findings demonstrate underlying cognitive features specifically associated with PART, and reinforce the concept that PART is a distinct entity from ADNC.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Cognition; Executive Function; Humans; Tauopathies

COVID-19 as a Risk Factor for Alzheimer's Disease. - Golzari-Sorkheh, Mahdieh; Weaver, Donald F; Reed, Mark A (J Alzheimers Dis, 2023)
Severe acute respiratory disease coronavirus 2 (SARS-CoV-2) is responsible for the coronavirus disease 2019 (COVID-19) pandemic. Although a primarily respiratory disease, recent reports indicate that it also affects the central nervous system (CNS). Over 25% of COVID-19 patients report neurological symptoms such as memory loss, anosmia, hyposmia, confusion, and headaches. The neurological outcomes may be a result of viral entry into the CNS and/or resulting neuroinflammation, both of which underlie an elevated risk for Alzheimer's disease (AD). Herein, we ask: Is COVID-19 a risk factor for AD? To answer, we identify the literature and review mechanisms by which COVID-19-mediated neuroinflammation can contribute to the development of AD, evaluate the effects of acute versus chronic phases of infection, and lastly, discuss potential therapeutics to address the rising rates of COVID-19 neurological sequelae.
Keywords: Alzheimer Disease; COVID-19; Humans; Nervous System Diseases; Neuroinflammatory Diseases; Risk Factors; SARS-CoV-2

Is Dementia Associated with COVID-19 Mortality? A Multicenter Retrospective Cohort Study Conducted in 50 Hospitals in Germany. - Kostev, Karel; Gessler, Nele; Wohlmuth, Peter; Arnold, Dirk; Bein, Berthold; Bohlken, Jens; Herrlinger, Klaus; Jacob, Louis; Koyanagi, Ai; Nowak, Lorenz; Smith, Lee; Wesseler, Claas; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Dementia has been identified as a major predictor of mortality associated with COVID-19. OBJECTIVE: The objective of this study was to investigate the association between dementia and mortality in COVID-19 inpatients in Germany across a longer interval during the pandemic. METHODS: This retrospective study was based on anonymized data from 50 hospitals in Germany and included patients with a confirmed COVID-19 diagnosis hospitalized between March 11, 2020 and July, 20, 2022. The main outcome of the study was the association of mortality during inpatient stays with dementia diagnosis, which was studied using multivariable logistic regression adjusted for age, sex, and comorbidities as well as univariate logistic regression for matched pairs. RESULTS: Of 28,311 patients diagnosed with COVID-19, 11.3% had a diagnosis of dementia. Prior to matching, 26.5% of dementia patients and 11.5% of non-dementia patients died; the difference decreased to 26.5% of dementia versus 21.7% of non-dementia patients within the matched pairs (n = 3,317). This corresponded to an increase in the risk of death associated with dementia (OR = 1.33; 95% CI: 1.16-1.46) in the univariate regression conducted for matched pairs. CONCLUSION: Although dementia was associated with COVID-19 mortality, the association was weaker than in previously published studies. Further studies are needed to better understand whether and how pre-existing neuropsychiatric conditions such as dementia may impact the course and outcome of COVID-19.
Keywords: COVID-19; COVID-19 Testing; Dementia; Germany; Hospitalization; Hospitals; Humans; Mortality; Retrospective Studies

Diagnostic Performance of Cerebrospinal Fluid Neurofilament Light Chain and Soluble Amyloid-β Protein Precursor β in the Subcortical Small Vessel Type of Dementia. - Axelsson Andrén, Elin; Kettunen, Petronella; Bjerke, Maria; Rolstad, Sindre; Zetterberg, Henrik; Blennow, Kaj; Wallin, Anders; Svensson, Johan (J Alzheimers Dis, 2023)
BACKGROUND: The subcortical small vessel type of dementia (SSVD) is a common subtype of vascular dementia, but there is a lack of disease-specific cerebrospinal fluid (CSF) biomarkers. OBJECTIVE: We investigated whether CSF concentrations of neurofilament light chain (NFL), soluble amyloid-β protein precursor α (sAβPPα), sAβPPβ, and CSF/serum albumin ratio could separate SSVD from healthy controls, Alzheimer's disease (AD), and mixed dementia (combined AD and SSVD). METHODS: This was a mono-center study of patients with SSVD (n = 38), AD (n = 121), mixed dementia (n = 62), and controls (n = 96). The CSF biomarkers were measured using immunoassays, and their independent contribution to the separation between groups were evaluated using the Wald test. Then, the area under the receiver operating characteristics curve (AUROC) and 95% confidence intervals (CIs) were calculated. RESULTS: Elevated neurofilament light chain (NFL) and decreased sAβPPβ independently separated SSVD from controls, and sAβPPβ also distinguished SSVD from AD and mixed dementia. The combination of NFL and sAβPPβ discriminated SSVD from controls with high accuracy (AUROC 0.903, 95% CI: 0.834-0.972). Additionally, sAβPPβ combined with the core AD biomarkers (amyloid-β42, total tau, and phosphorylated tau181) had a high ability to separate SSVD from AD (AUROC 0.886, 95% CI: 0.830-0.942) and mixed dementia (AUROC 0.903, 95% CI: 0.838-0.968). CONCLUSIONS: The high accuracy of NFL and sAβPPβ to separate SSVD from controls supports that SSVD is a specific diagnostic entity. Moreover, SSVD was distinguished from AD and mixed dementia using sAβPPβ in combination with the core AD biomarkers.

Different Trajectories of Apathy and Depression Among Subjective Cognitive Impairment Individuals with or without Conversion to Dementia: Results from the Memento Cohort in France. - Bogdan, Anamaria; Fabre, Roxane; Desmidt, Thomas; Golebiowski, Jérôme; Topin, Jérémie; Bethus, Ingrid; Hanon, Olivier; Boutoleau-Bretonnière, Claire; Wagemann, Nathalie; Annweiler, Cedric; Ousset, Pierre-Jean; Godefroy, Olivier; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Apathy and depression are two early behavioral symptoms in Alzheimer's disease (AD) and related disorders that often occur prior to the onset of cognitive decline and memory disturbances. Both have been associated with an increased risk of conversion to dementia, with a distinct neuropathology. OBJECTIVE: The assessment of the trajectories of apathy and depression and their independent impact on dementia conversion. METHODS: Apathy and Depression were measured using the Neuropsychiatric Inventory for caregiver (NPI) and clinician (NPI-C), among the nondemented individuals reporting subjective cognitive decline (SCD) at baseline. They were followed up over a 60-month period. Some converted to dementia, according to the methodology carried out by the French Memento Cohort. RESULTS: Among individuals with SCD (n = 2,323), the levels of apathy and depression were low and did not evolve significantly over the 60-month period, despite a trend in apathy increasing as of month 24. Regarding SCD individuals who converted to dementia within the 60-month period (n = 27), the prevalence of depression remained globally steady, while the levels of apathy increased over time. CONCLUSION: Apathy and depression have different trajectories among individuals with SCD and apathy alone is more likely-compared to depression-to be associated with conversion to dementia.

Disrupted excitation-inhibition balance in cognitively normal individuals at risk of Alzheimer's disease. - Fortel, Igor; Zhan, Liang; Ajilore, Olusola; Wu, Yichao; Mackin, Scott; Leow, Alex (bioRxiv, 2023)
BACKGROUND: Sex differences impact Alzheimer's disease (AD) neuropathology, but cell-to-network level dysfunctions in the prodromal phase are unclear. Alterations in hippocampal excitation-inhibition balance (EIB) have recently been linked to early AD pathology. OBJECTIVE: Examine how AD risk factors (age, APOE-ɛ4, amyloid-β) relate to hippocampal EIB in cognitively normal males and females using connectome-level measures. METHODS: Individuals from the OASIS-3 cohort (age 42-95) were studied (N = 437), with a subset aged 65+ undergoing neuropsychological testing (N = 231). RESULTS: In absence of AD risk factors (APOE-ɛ4/Aβ+), whole-brain EIB decreases with age more significantly in males than females (p = 0.021, β = -0.007). Regression modeling including APOE-ɛ4 allele carriers (Aβ-) yielded a significant positive AGE-by-APOE interaction in the right hippocampus for females only (p = 0.013, β = 0.014), persisting with inclusion of Aβ+ individuals (p = 0.012, β = 0.014). Partial correlation analyses of neuropsychological testing showed significant associations with EIB in females: positive correlations between right hippocampal EIB with categorical fluency and whole-brain EIB with the trail-making test (p < 0.05). CONCLUSION: Sex differences in EIB emerge during normal aging and progresses differently with AD risk. Results suggest APOE-ɛ4 disrupts hippocampal balance more than amyloid in females. Increased excitation correlates positively with neuropsychological performance in the female group, suggesting a duality in terms of potential beneficial effects prior to cognitive impairment. This underscores the translational relevance of APOE-ɛ4 related hyperexcitation in females, potentially informing therapeutic targets or early interventions to mitigate AD progression in this vulnerable population.

Early Life Stress Enhances Cognitive Decline and Alters Synapse Function and Interneuron Numbers in Young Male APP/PS1 Mice. - Brosens, Niek; Samouil, Dimitris; Stolker, Sabine; Katsika, Efthymia Vasilina; Weggen, Sascha; Lucassen, Paul J; Krugers, Harm J (J Alzheimers Dis, 2023)
BACKGROUND: Exposure to stress early in life increases the susceptibility to Alzheimer's disease (AD) pathology in aged AD mouse models. So far, the underlying mechanisms have remained elusive. OBJECTIVE: To investigate 1) effects of early life stress (ELS) on early functional signs that precede the advanced neuropathological changes, and 2) correlate synaptosomal protein content with cognition to identify neural correlates of AD. METHODS: APPswe/PS1dE9 mice and littermates were subjected to ELS by housing dams and pups with limited bedding and nesting material from postnatal days 2-9. At 3 months of age, an age where no cognitive loss or amyloid-β (Aβ) pathology is typically reported in this model, we assessed hippocampal Aβ pathology, synaptic strength and synapse composition and interneuron populations. Moreover, cognitive flexibility was assessed and correlated with synaptosomal protein content. RESULTS: While ELS did not affect Aβ pathology, it increased synaptic strength and decreased the number of calretinin+ interneurons in the hippocampal dentate gyrus. Both genotype and condition further affected the level of postsynaptic glutamatergic protein content. Finally, APP/PS1 mice were significantly impaired in cognitive flexibility at 3 months of age, and ELS exacerbated this impairment, but only at relatively high learning criteria. CONCLUSIONS: ELS reduced cognitive flexibility in young APP/PS1 mice and altered markers for synapse and network function. These findings at an early disease stage provide novel insights in AD etiology and in how ELS could increase AD susceptibility.
Keywords: Adverse Childhood Experiences; Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cognitive Dysfunction; Disease Models, Animal; Interneurons; Male; Mice; Mice, Transgenic; Plaque, Amyloid; Presenilin-1; Synapses

Effect of Metabolic Syndrome Risk Factors on Processing Speed and Executive Function in Three Racialized Groups. - Bouges, Shenikqua; Fischer, Barbara; Norton, Derek L; Wyman, Mary F; Lambrou, Nickolas; Zuelsdorff, Megan; Van Hulle, Carol A; Ennis, Gilda E; James, Taryn T; Johnson, Adrienne L; Chin, Nathaniel; Carlsson, Cynthia M; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Metabolic syndrome (MetS) has been associated with increased risk for Alzheimer's disease and related dementias (ADRD). Understanding the association of MetS risk factors to processing speed and executive function in the pre-clinical stages of ADRD in under-represented groups would offer insight on potential mechanisms through which MetS associates with ADRD risk. OBJECTIVE: Examine association of MetS features and processing speed and executive function across three racial groups. METHODS: Cognitively unimpaired adults from the Wisconsin Alzheimer's Disease Research Center and the Wisconsin Registry for Alzheimer's Disease Prevention completed blood-draws and neuropsychological testing. Six cognitive outcomes were assessed in association to MetS risk factors: Trailmaking Tests A and B, Animal Fluency, Digit Symbol, and composite scores for Processing Speed and Executive Function. Linear mixed effect models were used to assess the relationship between MetS risk factor count and longitudinal cognitive performance across three racialized groups. RESULTS: Participant sample sizes varied by outcome analyzed (N = 714-1,088). African American and Native American groups exhibited higher rates of MetS than non-Hispanic Whites. MetS was associated with processing speed and executive function across all racialized groups. Three-way interaction by racialized group was limited to one cognitive outcome: Trailmaking Test A. CONCLUSION: Metabolic dysfunction incrementally affects cognitive trajectory, with generally similar associations across racial groups. Since racialized groups exhibit higher levels of both MetS and ADRD, MetS may represent a driving factor for increased ADRD risk experience by racialized group and an important and modifiable target through which to reduce risk of ADRD.

Effect of Pathway-Specific Polygenic Risk Scores for Alzheimer's Disease (AD) on Rate of Change in Cognitive Function and AD-Related Biomarkers Among Asymptomatic Individuals. - Xu, Yuexuan; Vasiljevic, Eva; Deming, Yuetiva K; Jonaitis, Erin M; Koscik, Rebecca L; Van Hulle, Carol A; Lu, Qiongshi; Carboni, Margherita; Kollmorgen, Gwendlyn; Wild, Norbert; Carlsson, Cynthia M; Johnson, Sterling C; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Genetic scores for late-onset Alzheimer's disease (LOAD) have been associated with preclinical cognitive decline and biomarker variations. Compared with an overall polygenic risk score (PRS), a pathway-specific PRS (p-PRS) may be more appropriate in predicting a specific biomarker or cognitive component underlying LOAD pathology earlier in the lifespan. OBJECTIVE: In this study, we leveraged longitudinal data from the Wisconsin Registry for Alzheimer's Prevention and explored changing patterns in cognition and biomarkers at various age points along six biological pathways. METHODS: PRS and p-PRSs with and without APOE were constructed separately based on the significant SNPs associated with LOAD in a recent genome-wide association study meta-analysis and compared to APOE alone. We used a linear mixed-effects model to assess the association between PRS/p-PRSs and cognitive trajectories among 1,175 individuals. We also applied the model to the outcomes of cerebrospinal fluid biomarkers in a subset. Replication analyses were performed in an independent sample. RESULTS: We found p-PRSs and the overall PRS can predict preclinical changes in cognition and biomarkers. The effects of PRS/p-PRSs on rate of change in cognition, amyloid-β, and tau outcomes are dependent on age and appear earlier in the lifespan when APOE is included in these risk scores compared to when APOE is excluded. CONCLUSION: In addition to APOE, the p-PRSs can predict age-dependent changes in amyloid-β, tau, and cognition. Once validated, they could be used to identify individuals with an elevated genetic risk of accumulating amyloid-β and tau, long before the onset of clinical symptoms.

Elevated Pure Tone Thresholds Are Associated with Altered Microstructure in Cortical Areas Related to Auditory Processing and Attentional Allocation. - McEvoy, Linda K; Bergstrom, Jaclyn; Hagler, Donald J; Wing, David; Reas, Emilie T (J Alzheimers Dis, 2023)
BACKGROUND: Hearing loss is associated with cognitive decline and increased risk for Alzheimer's disease, but the basis of this association is not understood. OBJECTIVE: To determine whether hearing impairment is associated with advanced brain aging or altered microstructure in areas involved with auditory and cognitive processing. METHODS: 130 participants, (mean 76.4±7.3 years; 65% women) of the Rancho Bernardo Study of Healthy Aging had a screening audiogram in 2003-2005 and brain magnetic resonance imaging in 2014-2016. Hearing ability was defined as the average pure tone threshold (PTA) at 500, 1000, 2000, and 4000 Hz in the better-hearing ear. Brain-predicted age difference (Brain-pad) was calculated as the difference between brain-predicted age based on a validated structural imaging biomarker of brain age, and chronological age. Regional diffusion metrics in temporal and frontal cortex regions were obtained from diffusion-weighted MRIs. Linear regression analyses adjusted for age, gender, education, and health-related measures. RESULTS: PTAs were not associated with brain-PAD (β= 0.09; 95% CI: -0.084 to 0.243; p = 0.34). PTAs were associated with reduced restricted diffusion and increased free water diffusion primarily in right hemisphere temporal and frontal areas (restricted diffusion: βs = -0.21 to -0.30; 95% CIs from -0.48 to -0.02; ps <  0.03; free water: βs = 0.18 to 0.26; 95% CIs 0.01 to 0.438; ps <  0.04). CONCLUSIONS: Hearing impairment is not associated with advanced brain aging but is associated with differences in brain regions involved with auditory processing and attentional control. It is thus possible that increased dementia risk associated with hearing impairment arises, in part, from compensatory brain changes that may decrease resilience.

Evaluation of Blood-Based Plasma Biomarkers as Potential Markers of Amyloid Burden in Preclinical Alzheimer's Disease. - Winston, Charisse N; Langford, Oliver; Levin, Natalie; Raman, Rema; Yarasheski, Kevin; West, Tim; Abdel-Latif, Sara; Donohue, Michael; Nakamura, Akinori; Toba, Kenji; Masters, Colin L; Doecke, James; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Participant eligibility for the A4 Study was determined by amyloid PET imaging. Given the disadvantages of amyloid PET imaging in accessibility and cost, blood-based biomarkers may serve as a sufficient biomarker and more cost-effective screening tool for patient enrollment into preclinical AD trials. OBJECTIVE: To determine if a blood-based screening test can adequately identify amyloid burden in participants screened into a preclinical AD trial. METHODS: In this cross-sectional study, 224 participants from the A4 Study received an amyloid PET scan (18Florbetapir) within 90 days of blood sample collection. Blood samples from all study participants were processed within 2 h after phlebotomy. Plasma amyloid measures were quantified by Shimazdu and C2 N Diagnostics using mass spectrometry-based platforms. A corresponding subset of blood samples (n = 100) was processed within 24 h after phlebotomy and analyzed by C2 N. RESULTS: Plasma Aβ42/Aβ40 demonstrated the highest association for Aβ accumulation in the brain with an AUC 0.76 (95%CI = 0.69, 0.82) at C2 N and 0.80 (95%CI = 0.75, 0.86) at Shimadzu. Blood samples processed to plasma within 2 h after phlebotomy provided a better prediction of amyloid PET status than blood samples processed within 24 h (AUC 0.80 versus 0.64; p < 0.001). Age, sex, and APOE ɛ4 carrier status did not the diagnostic performance of plasma Aβ42/Aβ40 to predict amyloid PET positivity in A4 Study participants. CONCLUSION: Plasma Aβ42/Aβ40 may serve as a potential biomarker for predicting elevated amyloid in the brain. Utilizing blood testing over PET imaging may improve screening efficiency into clinical trials.
Keywords: Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Amyloidogenic Proteins; Biomarkers; Cross-Sectional Studies; Humans; Peptide Fragments; Positron-Emission Tomography

Excessive Sedentary Time Is Associated with Cognitive Decline in Older Patients with Minor Ischemic Stroke. - Liang, Hongtao; Yin, Xiang; Chen, Tian; Zhang, Yan; Zhang, Qin; Lin, Jie; Yin, Huan; Tang, Jinghua; He, Yingyi; Xia, Ping; Zhu, Yongping; Li, Haihua; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Cognitive impairment is commonly seen after acute ischemic stroke (AIS). Sedentary behaviors increase the risk of dementia among community dwelling population. OBJECTIVE: This study aims to investigate the association of sedentary behaviors with poststroke cognitive impairment among older adults of minor AIS. METHODS: This cohort study recruited 594 older subjects with minor AIS from three hospitals in China during February 1, 2016, and December 31, 2018. Participants were followed up for two years and the sedentary time per day was self-reported at the endpoint of follow-up. Cognitive functions were assessed by Mini-Mental State Examination (MMSE). Participants were categorized into the high and low sedentary time group according to the median sedentary time of the participants. RESULTS: At two years of follow-up, the long sedentary time group had significantly lower MMSE scores than the short sedentary time group [median, (95% CI): 21 (18 to 25) versus 22 (18 to 25), p = 0.368]. The long sedentary time group had a higher speed of cognitive decline than the short sedentary time group. Excessive sedentary time was associated with a higher risk of longitudinal cognitive decline (OR: 2.267, 95% CI: 1.594 to 3.225), adjusting for age, sex, education, body mass index, APOE genotype, comorbidities, symptoms of depression, anxiety, and insomnia, baseline MMSE scores and National Institute of Health Stroke Scale scores, cognitive therapy, and TOAST ischemic stroke subtypes. CONCLUSIONS: This study identified a possible link between sedentary behaviors and longitudinal cognitive decline among older patients with minor AIS, suggesting that reducing sedentary time might be helpful for preventing poststroke dementia.

Extracellular Tau Oligomers Damage the Axon Initial Segment. - Best, Merci N; Lim, Yunu; Ferenc, Nina N; Kim, Nayoung; Min, Lia; Wang, Dora Bigler; Sharifi, Kamyar; Wasserman, Anna E; McTavish, Sloane A; Siller, Karsten H; Jones, Marieke K; Jenkins, Paul M; et al. (J Alzheimers Dis, 2023)
BACKGROUND: In Alzheimer's disease (AD) brain, neuronal polarity and synaptic connectivity are compromised. A key structure for regulating polarity and functions of neurons is the axon initial segment (AIS), which segregates somatodendritic from axonal proteins and initiates action potentials. Toxic tau species, including extracellular oligomers (xcTauOs), spread tau pathology from neuron to neuron by a prion-like process, but few other cell biological effects of xcTauOs have been described. OBJECTIVE: Test the hypothesis that AIS structure is sensitive to xcTauOs. METHODS: Cultured wild type (WT) and tau knockout (KO) mouse cortical neurons were exposed to xcTauOs, and quantitative western blotting and immunofluorescence microscopy with anti-TRIM46 monitored effects on the AIS. The same methods were used to compare TRIM46 and two other resident AIS proteins in human hippocampal tissue obtained from AD and age-matched non-AD donors. RESULTS: Without affecting total TRIM46 levels, xcTauOs reduce the concentration of TRIM46 within the AIS and cause AIS shortening in cultured WT, but not TKO neurons. Lentiviral-driven tau expression in tau KO neurons rescues AIS length sensitivity to xcTauOs. In human AD hippocampus, the overall protein levels of multiple resident AIS proteins are unchanged compared to non-AD brain, but TRIM46 concentration within the AIS and AIS length are reduced in neurons containing neurofibrillary tangles. CONCLUSION: xcTauOs cause partial AIS damage in cultured neurons by a mechanism dependent on intracellular tau, thereby raising the possibility that the observed AIS reduction in AD neurons in vivo is caused by xcTauOs working in concert with endogenous neuronal tau.

Helicobacter pylori Infection Is Associated with Long-Term Cognitive Decline in Older Adults: A Two-Year Follow-Up Study. - Wang, Jian; Yu, Neng-Wei; Wang, Duo-Zi; Guo, Lei; Yang, Shu; Zheng, Bo; Guo, Fu-Qiang; Wang, Jian-Hong (J Alzheimers Dis, 2023)
BACKGROUND: Previous cross-sectional studies have identified a possible link between Helicobacter pylori (H. pylori) infection and dementia. However, the association of H. pylori infection with longitudinal cognitive decline has rarely been investigated. OBJECTIVE: This cohort study aims to demonstrate the effects of H. pylori infection on longitudinal cognitive decline. METHODS: This cohort study recruited 268 subjects with memory complaints. Among these subjects, 72 had a history of H. pylori infection, and the rest 196 subjects had no H. pylori infection. These subjects were followed up for 24 months and received cognitive assessment in fixed intervals of 12 months. RESULTS: At baseline, H. pylori infected, and uninfected participants had no difference in MMSE scores. At 2 years of follow-up, H. pylori infected participants had lower MMSE scores than uninfected participants. H. pylori infection was associated with an increased risk of longitudinal cognitive decline, as defined by a decrease of MMSE of 3 points or more during follow-up, adjusting for age, sex, education, APOEɛ4 genotype, hypertension, diabetes, hyperlipidemia, and smoking history (HR: 2.701; 95% CI: 1.392 to 5.242). H. pylori infection was associated with larger cognitive decline during follow-up, adjusting for the above covariates (standardized coefficient: 0.282, p < 0.001). Furthermore, H. pylori infected subjects had significantly higher speed of cognitive decline than uninfected subjects during follow-up, adjusting for the above covariates. CONCLUSION: H. pylori infection increases the risk of longitudinal cognitive decline in older subjects with memory complaints. This study is helpful for further understanding the association between infection and dementia.

Insights into the Pathophysiology of Alzheimer's Disease and Potential Therapeutic Targets: A Current Perspective. - Rajah Kumaran, Kesevan; Yunusa, Suleiman; Perimal, Enoch; Wahab, Habibah; Müller, Christian P; Hassan, Zurina (J Alzheimers Dis, 2023)
The aging population increases steadily because of a healthy lifestyle and medical advancements in healthcare. However, Alzheimer's disease (AD) is becoming more common and problematic among older adults. AD-related cases show an increasing trend annually, and the younger age population may also be at risk of developing this disorder. AD constitutes a primary form of dementia, an irreversible and progressive brain disorder that steadily damages cognitive functions and the ability to perform daily tasks. Later in life, AD leads to death as a result of the degeneration of specific brain areas. Currently, the cause of AD is poorly understood, and there is no safe and effective therapeutic agent to cure or slow down its progression. The condition is entirely preventable, and no study has yet demonstrated encouraging findings in terms of treatment. Identifying this disease's pathophysiology can help researchers develop safe and efficient therapeutic strategies to treat this ailment. This review outlines and discusses the pathophysiology that resulted in the development of AD including amyloid-β plaques, tau neurofibrillary tangles, neuroinflammation, oxidative stress, cholinergic dysfunction, glutamate excitotoxicity, and changes in neurotrophins level may sound better based on the literature search from Scopus, PubMed, ScienceDirect, and Google Scholar. Potential therapeutic strategies are discussed to provide more insights into AD mechanisms by developing some possible pharmacological agents for its treatment.
Keywords: Aged; Aging; Alzheimer Disease; Amyloid beta-Peptides; Humans; Neurofibrillary Tangles; Oxidative Stress; Plaque, Amyloid; tau Proteins

Landscape of Double-Stranded DNA Breaks in Postmortem Brains from Alzheimer's Disease and Non-Demented Individuals. - Zhang, Xiaoyu; Liu, Yan; Huang, Ming; Gunewardena, Sumedha; Haeri, Mohammad; Swerdlow, Russell H; Wang, Ning (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) brains accumulate DNA double-strand breaks (DSBs), which could contribute to neurodegeneration and dysfunction. The genomic distribution of AD brain DSBs is unclear. OBJECTIVE: To map genome-wide DSB distributions in AD and age-matched control brains. METHODS: We obtained autopsy brain tissue from 3 AD and 3 age-matched control individuals. The donors were men between the ages of 78 to 91. Nuclei extracted from frontal cortex tissue were subjected to Cleavage Under Targets & Release Using Nuclease (CUT&RUN) assay with an antibody against γH2AX, a marker of DSB formation. γH2AX-enriched chromatins were purified and analyzed via high-throughput genomic sequencing. RESULTS: The AD brains contained 18 times more DSBs than the control brains and the pattern of AD DSBs differed from the control brain pattern. In conjunction with published genome, epigenome, and transcriptome analyses, our data revealed aberrant DSB formation correlates with AD-associated single-nucleotide polymorphisms, increased chromatin accessibility, and upregulated gene expression. CONCLUSION: To our knowledge, this study is the first to characterize the AD brain DSB landscape. Our data suggest in AD, an accumulation of DSBs at ectopic genomic loci could contribute to an aberrant upregulation of gene expression.

Lithium Provides Broad Therapeutic Benefits in an Alzheimer's Disease Mouse Model. - Wiseman, Alyssa L; Briggs, Clark A; Peritt, Ariel; Kapecki, Nicolas; Peterson, Daniel A; Shim, Seong S; Stutzmann, Grace E (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) is a chronic neurodegenerative disorder with a progressive loss of cognitive function. Currently, no effective treatment regimen is available. Lithium, a mood stabilizer for bipolar disorder, exerts broad neuroprotective and neurotrophic actions and improves cognitive function. OBJECTIVE: The study investigated if lithium stabilizes Ca2+ signaling abnormalities in hippocampal neurons and subsequently normalize downstream effects on AD neuropathology and synaptic plasticity in young AD mice. METHODS: Four-month-old 3xTg-AD mice were treated with a LiCl diet chow for 30 days. At the end of the lithium treatment, a combination of two-photon Ca2+ imaging, electrophysiology, and immunohistochemistry assays were used to assess the effects of the LiCl treatment on inositol trisphosphate receptor (IP3R)-dependent endoplasmic reticulum (ER) Ca2+ and voltage-gated Ca2+ channel (VGCC)-mediated Ca2+ signaling in CA1 neurons, neuronal nitric oxide synthase (nNOS) and hyperphosphorylated tau (p-tau) levels and synaptic plasticity in the hippocampus and overlying cortex from 3xTg-ADmice. RESULTS: Thirty-day LiCl treatment reduced aberrant IP3R-dependent ER Ca2+ and VGCC-mediated Ca2+ signaling in CA1 pyramidal neurons from 3xTg-AD mice and restored neuronal nitric oxide synthase (nNOS) and hyperphosphorylated tau (p-tau) levels to control levels in the hippocampal subfields and overlying cortex. The LiCl treatment enhanced post-tetanic potentiation (PTP), a form of short-term plasticity in the hippocampus. CONCLUSION: The study found that lithium exerts therapeutic effects across several AD-associated early neuronal signaling abnormalities including aberrant Ca2+ signaling, nNOS, and p-tau formation and enhances short-term synaptic plasticity. Lithium could serve as an effective treatment or co-therapeutic for AD.
Keywords: Alzheimer Disease; Animals; Calcium; Disease Models, Animal; Hippocampus; Lithium; Mice; Mice, Transgenic; Nitric Oxide Synthase Type I; tau Proteins

Longitudinal Effects of Herpesviruses on Multiple Cognitive Outcomes in Healthy Elderly Adults. - Weidung, Bodil; Josefsson, Maria; Lyttkens, Peter; Olsson, Jan; Elgh, Fredrik; Lind, Lars; Kilander, Lena; Lövheim, Hugo (J Alzheimers Dis, 2023)
BACKGROUND: Herpesviruses have been proposed to be involved in Alzheimer's disease development as potentially modifiable pathology triggers. OBJECTIVE: To investigate associations of serum antibodies for herpes simplex virus (HSV)-1 and cytomegalovirus (CMV) and anti-herpesvirus treatment with cognitive outcomes in relation to interactions with APOE ɛ4. METHODS: The study included 849 participants in the population-based Prospective Investigation of the Vasculature in Uppsala Seniors study. Cognitive performance at the ages of 75 and 80 years was assessed using the Mini-Mental State Examination (MMSE), trail-making test (TMT) A and B, and 7-minute screening test (7MS). RESULTS: Anti- HSV-1 IgG positivity was associated cross-sectionally with worse performance on the MMSE, TMT-A, TMT-B, 7MS, enhanced free recall, and verbal fluency tests (p = 0.016, p = 0.016, p <  0.001, p = 0.001, p = 0.033, and p <  0.001, respectively), but not orientation or clock drawing. Cognitive scores did not decline over time and longitudinal changes did not differ according to HSV-1 positivity. Anti- CMV IgG positivity was not associated cross-sectionally with cognition, but TMT-B scores declined more in anti- CMV IgG carriers. Anti- HSV-1 IgG interacted with APOE ɛ4 in association with worse TMT-A and better enhanced cued recall. Anti- HSV IgM interacted with APOE ɛ4 and anti-herpesvirus treatment in association with worse TMT-A and clock drawing, respectively. CONCLUSION: These findings indicate that HSV-1 is linked to poorer cognition in cognitively healthy elderly adults, including impairments in executive function, memory, and expressive language. Cognitive performance did not decline over time, nor was longitudinal decline associated with HSV-1.

Mediation Effect of Brain Volume on the Relationship Between Peripheral Inflammation and Cognitive Decline. - Zhuo, Bingting; Zheng, Dashan; Cai, Miao; Wang, Chongjian; Zhang, Shiyu; Zhang, Zilong; Tian, Fei; Wang, Xiaojie; Lin, Hualiang (J Alzheimers Dis, 2023)
BACKGROUND: Studies have reported the associations between inflammation, brain volume, and cognition separately. It is reasonable to assume peripheral inflammation may contribute to cognitive decline through brain volume atrophy. OBJECTIVE: To examine the associations between peripheral inflammation, brain volume, and cognition among adults, and to investigate whether brain volume atrophy mediates the inflammation-cognition relationshipMethods:We retrieved 20,381 participants with available data on peripheral inflammation, brain volume, and cognition from the UK Biobank cohort. Cognitive function was assessed by performance on cognitive tasks probing various cognitive domains. Brain volumes were measured by magnetic resonance imaging (MRI). Multivariable linear models were used to investigate the associations between three peripheral inflammatory indexes (C-reactive protein, systemic immune-inflammatory index, neutrophil-to-lymphocyte ratio), brain volume, and cognition. Mediation analyses were conducted to assess the potential mediating effect of brain volume atrophy. All results were corrected for multiple comparisons using the false-discovery rate (FDR). RESULTS: Peripheral inflammation was inversely associated with grey matter volume (GMV), white matter volume (WMV), and cognition after adjusting for potential covariates. For instance, CRP was associated with the GMV of left parahippocampal gyrus (β= -0.05, 95% confidence interval [CI]: -0.06 to -0.04, pFDR =1.07×10-16) and general cognitive factor (β= -0.03, 95% CI: -0. -0.04 to -0.01, pFDR = 0.001). Brain volume atrophy mediated the inflammation-cognitive decline relationship, accounting for 15-29% of the overall impact. CONCLUSION: In this cohort study, peripheral inflammation was associated with brain volume atrophy and cognitive decline. Brain atrophy may mediate the inflammation-cognitive decline relationship.
Keywords: Atrophy; Brain; Cognition; Cognitive Dysfunction; Cohort Studies; Encephalitis; Humans; Inflammation; Magnetic Resonance Imaging

Mediation of Reduced Hippocampal Volume by Cerebral Amyloid Angiopathy in Pathologically Confirmed Patients with Alzheimer's Disease. - Nagaraja, Nandakumar; Wang, Wei-En; Duara, Ranjan; DeKosky, Steven T; Vaillancourt, David (J Alzheimers Dis, 2023)
BACKGROUND: Hippocampal atrophy in cerebral amyloid angiopathy (CAA) has been reported to be similar to that in Alzheimer's disease (AD). OBJECTIVE: To evaluate if CAA pathology partly mediates reduced hippocampal volume in patients with AD. METHODS: Patients with a clinical diagnosis of AD and neuropathological confirmation of AD+/-CAA in the National Alzheimer's Coordinating Center database were included in the study. The volumes of temporal lobe structures were calculated on T1-weighted imaging (T1-MRI) using automated FreeSurfer software, from images acquired on average 5 years prior to death. Multivariate regression analysis was performed to compare brain volumes in four CAA groups. The hippocampal volume on T1-MRI was correlated with Clinical Dementia Rating sum of boxes (CDRsb) score, apolipoprotein E (APOE) genotype, and hippocampal atrophy at autopsy. RESULTS: The study included 231 patients with no (n = 45), mild (n = 70), moderate (n = 67), and severe (n = 49) CAA. Among the four CAA groups, patients with severe CAA had a smaller mean left hippocampal volume (p = 0.023) but this was not significant when adjusted for APOE ɛ4 (p = 0.07). The left hippocampal volume on MRI correlated significantly with the hippocampal atrophy grading on neuropathology (p = 0.0003). Among patients with severe CAA, the left hippocampal volume on T1-MRI: (a) decreased with an increase in the number of APOE ɛ4 alleles (p = 0.04); but (b) had no evidence of correlation with CDRsb score (p = 0.57). CONCLUSION: Severe CAA was associated with smaller left hippocampal volume on T1-MRI up to five years prior to death among patients with neuropathologically confirmed AD. This relationship was dependent on APOE ɛ4 genotype.

Microglia-Astrocyte Communication in Alzheimer's Disease. - Wu, Yingying; Eisel, Ulrich L M (J Alzheimers Dis, 2023)
Microglia and astrocytes are regarded as active participants in the central nervous system under various neuropathological conditions, including Alzheimer's disease (AD). Both microglia and astrocyte activation have been reported to occur with a spatially and temporarily distinct pattern. Acting as a double-edged sword, glia-mediated neuroinflammation may be both detrimental and beneficial to the brain. In a variety of neuropathologies, microglia are activated before astrocytes, which facilitates astrocyte activation. Yet reactive astrocytes can also prevent the activation of adjacent microglia in addition to helping them become activated. Studies describe changes in the genetic profile as well as cellular and molecular responses of these two types of glial cells that contribute to dysfunctional immune crosstalk in AD. In this paper, we construct current knowledge of microglia-astrocyte communication, highlighting the multifaceted functions of microglia and astrocytes and their role in AD. A thorough comprehension of microglia-astrocyte communication could hasten the creation of novel AD treatment approaches.
Keywords: Alzheimer Disease; Astrocytes; Central Nervous System; Communication; Humans; Microglia

Microglial Imaging in Alzheimer's Disease and Its Relationship to Brain Amyloid: A Human 18F-GE180 PET Study. - Yang, Zhengshi; Banks, Sarah J; Ritter, Aaron R; Cummings, Jeffrey L; Sreenivasan, Karthik; Kinney, Jefferson W; Caldwell, Jessica K; Wong, Christina G; Miller, Justin B; Cordes, Dietmar (J Alzheimers Dis, 2023)
BACKGROUND: Emerging evidence suggests a potential causal role of neuroinflammation in Alzheimer's disease (AD). Using positron emission tomography (PET) to image overexpressed 18 kDA translocator protein (TSPO) by activated microglia has gained increasing interest. The uptake of 18F-GE180 TSPO PET was observed to co-localize with inflammatory markers and have a two-stage association with amyloid PET in mice. Very few studies evaluated the diagnostic power of 18F-GE180 PET in AD population and its interpretation in human remains controversial about whether it is a marker of microglial activation or merely reflects disrupted blood-brain barrier integrity in humans. OBJECTIVE: The goal of this study was to study human GE180 from the perspective of the previous animal observations. METHODS: With data from twenty-four participants having 18F-GE180 and 18F-AV45 PET scans, we evaluated the group differences of 18F-GE180 uptake between participants with and without cognitive impairment. An association analysis of 18F-GE180 and 18F-AV45 was then conducted to test if the relationship in humans is consistent with the two-stage association in AD mouse model. RESULTS: Elevated 18F-GE180 was observed in participants with cognitive impairment compared to those with normal cognition. No regions showed reduced 18F-GE180 uptake. Consistent with mouse model, a two-stage association between 18F-GE180 and 18F-AV45 was observed. CONCLUSIONS: 18F-GE180 PET imaging showed promising utility in detecting pathological alterations in a symptomatic AD population. Consistent two-stage association between 18F-GE180 and amyloid PET in human and mouse suggested that 18F-GE180 uptake in human might be considerably influenced by microglial activation.

Microglia-Mediated Neurovascular Unit Dysfunction in Alzheimer's Disease. - Huang, Wenhao; Xia, Qing; Zheng, Feifei; Zhao, Xue; Ge, Fangliang; Xiao, Jiaying; Liu, Zijie; Shen, Yingying; Ye, Ke; Wang, Dayong; Li, Yanze (J Alzheimers Dis, 2023)
The neurovascular unit (NVU) is involved in the pathological changes in Alzheimer's disease (AD). The NVU is a structural and functional complex that maintains microenvironmental homeostasis and metabolic balance in the central nervous system. As one of the most important components of the NVU, microglia not only induce blood-brain barrier breakdown by promoting neuroinflammation, the infiltration of peripheral white blood cells and oxidative stress but also mediate neurovascular uncoupling by inducing mitochondrial dysfunction in neurons, abnormal contraction of cerebral vessels, and pericyte loss in AD. In addition, microglia-mediated dysfunction of cellular components in the NVU, such as astrocytes and pericytes, can destroy the integrity of the NVU and lead to NVU impairment. Therefore, we review the mechanisms of microglia-mediated NVU dysfunction in AD. Furthermore, existing therapeutic advancements aimed at restoring the function of microglia and the NVU in AD are discussed. Finally, we predict the role of pericytes in microglia-mediated NVU dysfunction in AD is the hotspot in the future.
Keywords: Alzheimer Disease; Astrocytes; Blood-Brain Barrier; Humans; Microglia; Neurons

Mitochondria Profoundly Influence Apolipoprotein E Biology. - Gabrielli, Alexander P; Weidling, Ian; Ranjan, Amol; Wang, Xiaowan; Novikova, Lesya; Chowdhury, Subir Roy; Menta, Blaise; Berkowicz, Alexandra; Wilkins, Heather M; Peterson, Kenneth R; Swerdlow, Russell H (J Alzheimers Dis, 2023)
BACKGROUND: Mitochondria can trigger Alzheimer's disease (AD)-associated molecular phenomena, but how mitochondria impact apolipoprotein E (APOE; apoE) is not well known. OBJECTIVE: Consider whether and how mitochondrial biology influences APOE and apoE biology. METHODS: We measured APOE expression in human SH-SY5Y neuronal cells with different forms of mitochondrial dysfunction including total, chronic mitochondrial DNA (mtDNA) depletion (ρ0 cells); acute, partial mtDNA depletion; and toxin-induced mitochondrial dysfunction. We further assessed intracellular and secreted apoE protein levels in the ρ0 cells and interrogated the impact of transcription factors and stress signaling pathways known to influence APOE expression. RESULTS: SH-SY5Y ρ0 cells exhibited a 65-fold increase in APOE mRNA, an 8-fold increase in secreted apoE protein, and increased intracellular apoE protein. Other models of primary mitochondrial dysfunction including partial mtDNA-depletion, toxin-induced respiratory chain inhibition, and chemical-induced manipulations of the mitochondrial membrane potential similarly increased SH-SY5Y cell APOE mRNA. We explored potential mediators and found in the ρ0 cells knock-down of the C/EBPα and NFE2L2 (Nrf2) transcription factors reduced APOE mRNA. The activity of two mitogen-activated protein kinases, JNK and ERK, also strongly influenced ρ0 cell APOE mRNA levels. CONCLUSION: Primary mitochondrial dysfunction either directly or indirectly activates APOE expression in a neuronal cell model by altering transcription factors and stress signaling pathways. These studies demonstrate mitochondrial biology can influence the biology of the APOE gene and apoE protein, which are implicated in AD.
Keywords: Alzheimer Disease; Apolipoproteins E; Biology; Cell Line, Tumor; DNA, Mitochondrial; Humans; Mitochondria; Neuroblastoma; RNA, Messenger; Transcription Factors

Multi-Site Cross-Site Inter-Rater and Test-Retest Reliability and Construct Validity of the MarkVCID White Matter Hyperintensity Growth and Regression Protocol. - Bahrani, Ahmed A; Abner, Erin L; DeCarli, Charles S; Barber, Justin M; Sutton, Abigail C; Maillard, Pauline; Sandoval, Francisco; Arfanakis, Konstantinos; Yang, Yung-Chuan; Evia, Arnold M; Schneider, Julie A; Habes, Mohamad; et al. (J Alzheimers Dis, 2023)
BACKGROUND: White matter hyperintensities (WMH) that occur in the setting of vascular cognitive impairment and dementia (VCID) may be dynamic increasing or decreasing volumes or stable over time. Quantifying such changes may prove useful as a biomarker for clinical trials designed to address vascular cognitive-impairment and dementia and Alzheimer's Disease. OBJECTIVE: Conducting multi-site cross-site inter-rater and test-retest reliability of the MarkVCID white matter hyperintensity growth and regression protocol. METHODS: The NINDS-supported MarkVCID Consortium evaluated a neuroimaging biomarker developed to track WMH change. Test-retest and cross-site inter-rater reliability of the protocol were assessed. Cognitive test scores were analyzed in relation to WMH changes to explore its construct validity. RESULTS: ICC values for test-retest reliability of WMH growth and regression were 0.969 and 0.937 respectively, while for cross-site inter-rater ICC values for WMH growth and regression were 0.995 and 0.990 respectively. Word list long-delay free-recall was negatively associated with WMH growth (p < 0.028) but was not associated with WMH regression. CONCLUSIONS: The present data demonstrate robust ICC validity of a WMH growth/regression protocol over a one-year period as measured by cross-site inter-rater and test-retest reliability. These data suggest that this approach may serve an important role in clinical trials of disease-modifying agents for VCID that may preferentially affect WMH growth, stability, or regression.

Neural Stem Cells in the Treatment of Alzheimer's Disease: Current Status, Challenges, and Future Prospects. - Chen, Xiaokun; Jiang, Shenzhong; Wang, Renzhi; Bao, Xinjie; Li, Yongning (J Alzheimers Dis, 2023)
Alzheimer's disease (AD), a progressive dementia, is one of the world's most dangerous and debilitating diseases. Clinical trial results of amyloid-β (Aβ) and tau regulators based on the pretext of straightforward amyloid and tau immunotherapy were disappointing. There are currently no effective strategies for slowing the progression of AD. Further understanding of the mechanisms underlying AD and the development of novel therapeutic options are critical. Neurogenesis is impaired in AD, which contributes to memory deficits. Transplanted neural stem cells (NSCs) can regenerate degraded cholinergic neurons, and new neurons derived from NSCs can form synaptic connections with neighboring neurons. In theory, employing NSCs to replace and restore damaged cholinergic neurons and brain connections may offer new treatment options for AD. However there remain barriers to surmount before NSC-based therapy can be used clinically. The objective of this article is to describe recent advances in the treatment of AD models and clinical trials involving NSCs. In addition, we discuss the challenges and prospects associated with cell transplant therapy for AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Cholinergic Neurons; Disease Models, Animal; Humans; Neural Stem Cells

Neuropathologic Changes of Alzheimer's Disease and Related Dementias: Relevance to Future Prevention. - White, Lon R; Corrada, Maria M; Kawas, Claudia H; Cholerton, Brenna A; Edland, Steve E; Flanagan, Margaret E; Montine, Thomas J (J Alzheimers Dis, 2023)
BACKGROUND: Decedents with late-life dementia are often found at autopsy to have vascular pathology, cortical Lewy bodies, hippocampal sclerosis, and/or TDP-43 encephalopathy alone or with concurrent Alzheimer's disease (AD) lesions. Nonetheless, it is commonly believed that AD neuropathologic changes (NC) are the dominant or exclusive drivers of late-life dementia. OBJECTIVE: Assess associations of end-of-life cognitive impairment with any one or any combination of five distinct NC. Assess impairment prevalence among subjects having natural resistance to each type of NC. METHODS: Brains from 1,040 autopsied participants of the Honolulu-Asia Study, the Nun Study, and the 90 + Study were examined for NC of AD, Lewy body dementia, microvascular brain injury, hippocampal sclerosis, and limbic predominate TDP-43 encephalopathy. Associations with impairment were assessed for each NC and for NC polymorbidity (variable combinations of 2-5 concurrent NC). RESULTS: Among 387 autopsied decedents with severe cognitive impairment, 20.4% had only AD lesions (ADNC), 25.3% had ADNC plus 1 other NC, 11.1% had ADNC plus 2 or more other NC, 28.7% had no ADNC but 1-4 other NC, and 14.5% had no/negligible NC. Combinations of any two, three, or four NC were highly frequent among the impaired. Natural resistance to ADNC or any other single NC had a modest impact on overall cohort impairment levels. CONCLUSION: Polymorbidity involving 1-5 types of concurrent NC is a dominant neuropathologic feature of AD and related dementias. This represents a daunting challenge to future prevention and could explain failures of prior preventive intervention trials and of efforts to identify risk factors.

Neuroprotective Properties of Eudesmin on a Cellular Model of Amyloid-β Peptide Toxicity. - Castillo, Carolina; Bravo-Arrepol, Gastón; Wendt, Aline; Saez-Orellana, Francisco; Millar, Camila; Burgos, Carlos F; Gavilán, Javiera; Pacheco, Carla; Ahumada-Rudolph, Ramón; Napiórkowska, Mariola; Pérez, Claudia; Becerra, José; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by progressive cognitive impairment and memory loss. One of the hallmarks in AD is amyloid-β peptide (Aβ) accumulation, where the soluble oligomers of Aβ (AβOs) are the most toxic species, deteriorating the synaptic function, membrane integrity, and neuronal structures, which ultimately lead to apoptosis. Currently, there are no drugs to arrest AD progression, and current scientific efforts are focused on searching for novel leads to control this disease. Lignans are compounds extracted from conifers and have several medicinal properties. Eudesmin (Eu) is an extractable lignan from the wood of Araucaria araucana, a native tree from Chile. This metabolite has shown a range of biological properties, including the ability to control inflammation and antibacterial effects. OBJECTIVE: In this study, the neuroprotective abilities of Eu on synaptic failure induced by AβOs were analyzed. METHODS: Using neuronal models, PC12 cells, and in silico simulations we evaluated the neuroprotective effect of Eu (30 nM) against the toxicity induced by AβOs. RESULTS: In primary cultures from mouse hippocampus, Eu preserved the synaptic structure against AβOs toxicity, maintaining stable levels of the presynaptic protein SV2 at the same concentration. Eu also averted synapsis failure from the AβOs toxicity by sustaining the frequencies of cytosolic Ca2+ transients. Finally, we found that Eu (30 nM) interacts with the Aβ aggregation process inducing a decrease in AβOs toxicity, suggesting an alternative mechanism to explain the neuroprotective activity of Eu. CONCLUSION: We believe that Eu represents a novel lead that reduces the Aβ toxicity, opening new research venues for lignans as neuroprotective agents.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Lignans; Mice; Neuroprotective Agents; PC12 Cells; Rats

Non-Pharmacological Interventions for Feeding and Eating Disorders in Persons with Dementia: Systematic Review and Evidence Summary. - Chen, Hong-Li; Li, Cheng; Wang, Jing; Fei, Yang; Min, Min; Zhao, Yue; Shan, En-Fang; Yin, Yue-Heng; Liu, Chong-Yuan; Li, Xian-Wen (J Alzheimers Dis, 2023)
BACKGROUND: Feeding and eating disorders related to cognitive and psycho-behavioral symptoms are strongly associated with health status in persons with dementia (PWD). Non-pharmacological interventions have been the priority selection to address this significant issue. However, the direct targets of non-pharmacological interventions are unclear and there is no consistent evidence of recommendations on the intervention of different dementia stages and the settings of intervention practice. OBJECTIVE: To provide caregivers with a set of self-help non-pharmacological interventions for feeding and eating disorders in PWD. METHODS: Based on the process of evidence summary, a systematic literature search was performed on dementia websites and seven databases. Two researchers screened the studies independently and appraise the quality. The evidence was graded by Joanna Briggs Institute Grades of Recommendation. RESULTS: Twenty-eight articles were included. Twenty-three non-pharmacological intervention recommendations were categorized into six themes containing oral nutritional supplementation, assistance with eating and drinking, person-centered mealtime care, environmental modification, education or training, and multi-component intervention. These interventions corresponded to three direct targets including improving engagement, making up for loss ability, and increasing food intake directly. They were applied to different stages of dementia and most interventions were targeted at PWD in long-term care institutions. CONCLUSION: This article summarized the direct targets and the specific implementation of recommendations at different stages of dementia to provide caregivers with self-help non-pharmacological interventions. The practice of recommendations was more applicable to institutionalized PWD. When applied to PWD at home, caregivers need to identify the specific feeding and eating conditions at different stages and adopted the interventions in conjunction with the wishes of the PWD and professional advice.
Keywords: Caregivers; Dementia; Feeding and Eating Disorders; Health Status; Humans; Nutritional Status

A Novel Strategy for Alzheimer's Disease Based on the Regulatory Effect of Amyloid-β on Gut Flora. - Huang, Li; Lu, Zhaogang; Zhang, Hexin; Wen, Hongyong; Li, Zongji; Liu, Qibing; Wang, Rui (J Alzheimers Dis, 2023)
Alzheimer's disease (AD) is one of the most common neurodegenerative diseases worldwide. The accumulation of amyloid-β (Aβ) protein and plaque formation in the brain are two major causes of AD. Interestingly, growing evidence demonstrates that the gut flora can alleviate AD by affecting amyloid production and metabolism. However, the underlying mechanism remains largely unknown. This review will discuss the possible association between the gut flora and Aβ in an attempt to provide novel therapeutic directions for AD treatment based on the regulatory effect of Aβ on the gut flora.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloidogenic Proteins; Brain; Gastrointestinal Microbiome; Humans

Pathogenesis, Animal Models, and Drug Discovery of Alzheimer's Disease. - Xia, Zhao-Di; Ma, Ruo-Xin; Wen, Jin-Feng; Zhai, Yu-Fei; Wang, Yu-Qi; Wang, Feng-Yun; Liu, Dan; Zhao, Xiao-Long; Sun, Bao; Jia, Pu; Zheng, Xiao-Hui (J Alzheimers Dis, 2023)
Alzheimer's disease (AD), the most common cause of dementia, is a chronic neurodegenerative disease induced by multiple factors. The high incidence and the aging of the global population make it a growing global health concern with huge implications for individuals and society. The clinical manifestations are progressive cognitive dysfunction and lack of behavioral ability, which not only seriously affect the health and quality of life of the elderly, but also bring a heavy burden to the family and society. Unfortunately, almost all the drugs targeting the classical pathogenesis have not achieved satisfactory clinical effects in the past two decades. Therefore, the present review provides more novel ideas on the complex pathophysiological mechanisms of AD, including classical pathogenesis and a variety of possible pathogenesis that have been proposed in recent years. It will be helpful to find out the key target and the effect pathway of potential drugs and mechanisms for the prevention and treatment of AD. In addition, the common animal models in AD research are outlined and we examine their prospect for the future. Finally, Phase I, II, III, and IV randomized clinical trials or on the market of drugs for AD treatment were searched in online databases (Drug Bank Online 5.0, the U.S. National Library of Medicine, and Alzforum). Therefore, this review may also provide useful information in the research and development of new AD-based drugs.
Keywords: Alzheimer Disease; Animals; Drug Discovery; Models, Animal; Neurodegenerative Diseases; Quality of Life

Patterns of Aging Changes in Bodyweight May Predict Alzheimer's Disease. - Ukraintseva, Svetlana; Duan, Hongzhe; Holmes, Rachel; Bagley, Olivia; Wu, Deqing; Yashkin, Arseniy; Kulminski, Alexander; Akushevich, Igor; Whitson, Heather; Stallard, Eric; Yashin, Anatoliy; Arbeev, Konstantin (J Alzheimers Dis, 2023)
Relationships between patterns of aging-changes in bodyweight and AD are not fully understood. We compared mean age-trajectories of weight between those who did and did not develop late-onset-AD, and evaluated impact of age at maximum weight (AgeMax), and slope of decline in weight, on AD risk. Women with late-onset-AD had lower weight three or more decades before AD onset, and ∼10 years younger AgeMax, compared to AD-free women. APOE4 carriers had younger AgeMax and steeper slope. Older AgeMax and flatter slope predicted lower AD risk. Premature decline in weight could be a sign of accelerated physical aging contributing to AD.

Physical Activity for Cognitive Health: A Model for Intervention Design for People Experiencing Cognitive Concerns and Symptoms of Depression or Anxiety. - Curran, Eleanor; Palmer, Victoria J; Ellis, Kathryn A; Chong, Terence W H; Rego, Thomas; Cox, Kay L; Anstey, Kaarin J; Westphal, Alissa; Moorhead, Rebecca; Southam, Jenny; Lai, Rhoda; You, Emily; et al. (J Alzheimers Dis, 2023)
BACKGROUND: People experiencing cognitive concerns and symptoms of depression or anxiety are at risk for Alzheimer's disease and dementia. We know physical activity can benefit cognition but understanding how to best support engagement is an ongoing challenge. Evidence-based conceptual models of factors underpinning physical activity engagement in target populations can inform intervention tailoring to address this challenge. OBJECTIVE: This study (part of a pragmatic physical activity implementation trial) aimed to develop a specified model of physical activity engagement in people experiencing depressive or anxiety symptoms and cognitive concerns, to enable optimized dementia risk reduction intervention tailoring. METHODS: We employed a qualitative design, triangulating data from three sources: semi-structured individual interviews with people experiencing cognitive concerns and mild to moderate depressive or anxiety symptoms; review of published evidence; and the Capability, Opportunity and Motivation system of behavior, an existing behavioral science model. Findings were integrated to develop a contextualized model of mechanisms of action for optimizing engagement. RESULTS: Twenty-one participants were interviewed, and 24 relevant papers included. Convergent and complementary themes extended understanding of intervention needs. Findings highlighted emotional regulation, capacities to enact intentions despite barriers, and confidence in existing skills as areas of population-specific need that have not previously been emphasized. The final model provides specificity, directionality, and linked approaches for intervention tailoring. CONCLUSION: This study demonstrated that people experiencing cognitive concerns and symptoms of depression or anxiety require different interventions to improve physical activity engagement. The novel model can enable more precise intervention tailoring, and, ultimately, benefits for a key at-risk population.

Plasma Amyloid-β Homeostasis Is Associated with Body Mass Index and Weight Loss in People with Overweight and Obesity. - Brook, Emily S; D'Alonzo, Zachary J; Lam, Virginie; Chan, Dick; Dhaliwal, Satvinder Singh; Watts, Geraldb F; Mamo, John C L; Takechi, Ryusuke (J Alzheimers Dis, 2023)
BACKGROUND: Obesity is linked to a higher incidence of Alzheimer's disease (AD). Studies show that plasma amyloid-β (Aβ) dyshomeostasis, particularly low 42/40 ratio indicates a heightened risk for developing AD. However, the relationship between body mass index (BMI) and circulating plasma Aβ has not been extensively studied. OBJECTIVE: We hypothesized that people with a high BMI have altered plasma Aβ homeostasis compared with people with a lower BMI. We also tested whether reducing BMI by calorie-restriction could normalize plasma concentrations of Aβ. METHODS: Plasma concentrations of Aβ 40, Aβ 42, and Aβ 42/40 ratio were measured in 106 participants with BMIs classified as lean, overweight, or obese. From this cohort, twelve participants with overweight or obese BMIs entered a 12-week calorie-restriction weight loss program. We then tested whether decreasing BMI affected plasma Aβ concentrations. RESULTS: Plasma Aβ 42/40 ratio was 17.54% lower in participants with an obese BMI compared to lean participants (p <  0.0001), and 11.76% lower compared to participants with an overweight BMI (p <  0.0001). The weight loss regimen decreased BMI by an average of 4.02% (p = 0.0005) and was associated with a 6.5% decrease in plasma Aβ 40 (p = 0.0425). However, weight loss showed negligible correlations with plasma Aβ 40, Aβ 42, and Aβ 42/40 ratio. CONCLUSION: Obesity is associated with aberrant plasma Aβ homeostasis which may be associated with an increased risk for AD. Weight loss appears to lower Aβ 40, but large-scale longitudinal studies in addition to molecular studies are required to elucidate the underlying mechanisms of how obesity and weight loss influence plasma Aβ homeostasis.

Preventing Neurocognitive Decline in Adults Aging with HIV: Implications for Practice and Research. - Cody, Shameka L; Miller, Gabe H; Fazeli, Pariya L; Wang, Ge; Li, Wei; Goodin, Burel R; Vance, David E (J Alzheimers Dis, 2023)
Mild to moderate forms of neurocognitive impairment persist among people living with HIV (PLWH), despite being virally suppressed on antiretroviral therapy. PLWH are disproportionally impacted by physiological and psychosocial comorbidities compared to those without HIV. As adults live longer with HIV, the neurocognitive burden of physiological and psychosocial stressors can impair everyday functioning and may contribute to the development of neurodegenerative diseases such as Alzheimer's disease. This article outlines neurocognitive consequences of everyday stressors in PLWH. While some lifestyle factors can exacerbate inflammatory processes and promote negative neurocognitive health, novel interventions including the use of cannabinoids may be neuroprotective for aging PLWH who are at risk for elevated levels of inflammation from comorbidities. Studies of integrated neurocognitive rehabilitation strategies targeting lifestyle factors are promising for improving neurocognitive health, and may over time, reduce the risk of Alzheimer's disease in PLWH.
Keywords: Aging; Alzheimer Disease; Comorbidity; HIV Infections; Humans

Refining Risk for Alzheimer's Disease Among Heterozygous APOEɛ4 Carriers. - Patel, Smita; Wei, Jun; Shi, Zhuqing; Rifkin, Andrew S; Zheng, S Lilly; Gelfman, Elizabeth; Duggan, David; Helfand, Brian T; Hulick, Peter J; Xu, Jianfeng (J Alzheimers Dis, 2023)
In a large population-based cohort, we show not all heterozygous APOEɛ4 carriers are at increased risk for Alzheimer's disease (AD); a significantly higher AD proportion was only found for ɛ3/ɛ4, not ɛ2/ɛ4. Among ɛ3/ɛ4 carriers (24% in the cohort), the AD proportion differed considerably by polygenic risk score (PRS). In particular, the AD proportion was lower than the entire cohort for subjects in the bottom 20-percentile PRS and was higher than that of homozygous ɛ4 carriers for subjects at the top 5th-percentile PRS. Family history was no longer a significant predictor of AD risk after adjusting APOE and PRS.
Keywords: Alzheimer Disease; Apolipoprotein E4; Apolipoproteins E; Heterozygote; Homozygote; Humans

Retinal Functional and Structural Neural Indices: Potential Biomarkers for the Monitoring of Cerebral Neurodegeneration: The Maastricht Study. - van der Heide, Frank C T; Mokhtar, Sara; Khanna, Anjani; Said, Mozhda; Henry, Ronald M A; Kroon, Abraham A; Dagnelie, Pieter C; Eussen, Simone J P M; Berendschot, Tos T J M; Schouten, Jan S A G; Schram, Miranda T; van der Kallen, Carla J H; et al. (J Alzheimers Dis, 2023)
BACKGROUND: If retinal indices of neurodegeneration are to be biomarkers for the monitoring of cerebral neurodegeneration, it is important to establish whether potentially modifiable risk factors for dementia are associated with retinal neurodegenerative changes. OBJECTIVE: To study associations of dementia risk factors with retinal sensitivity, an index of retinal neural function, and retinal nerve fiber layer (RNFL) thickness, an index of retinal neural structure. METHODS: We used cross-sectional data from The Maastricht Study (up to 5,666 participants, 50.5% men, mean age 59.7), and investigated associations with regression analyses (adjusted for potential confounders). RESULTS: Most risk factors under study (i.e., hyperglycemia, unhealthy diet, lower cardiorespiratory fitness, smoking, alcohol consumption, and hypertension) were significantly associated with lower retinal sensitivity and lower RNFL thickness. CONCLUSION: Findings of this population-based study support the concept that retinal neural indices may be biomarkers for the monitoring of therapeutic strategies that aim to prevent early-stage cerebral neurodegeneration and, ultimately, dementia.

S1PR2 Regulates Autophagy Through the AKT/mTOR Pathway to Promote Pathological Damage in Alzheimer's Disease. - Wang, Xiaoping; Huang, Rui; Huang, Bin; Li, Xiaojia (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) is a fatal and debilitating neurodegenerative disease. Sphingosine-1-phosphate receptor 2 (S1PR2), one of the receptors of S1P, is a key regulatory factor for various diseases. OBJECTIVE: This study aimed to explore the role and possible mechanism of S1PR2 in AD. METHODS: S1PR2 expression in the AD mice was detected, and after intervening S1PR2 expression with sh-S1PR2 in AD mice, the behavioral changes, pathological lesions of the hippocampus, autophagy level, and AKT/mTOR pathway activation were analyzed. Furthermore, SH-SY5Y cells were induced by Aβ25-35 to construct an AD cell model, and the effects of sh-S1PR2 on proliferation, apoptosis, autophagy, and AKT/mTOR pathway of AD cells were investigated. In addition, the effects of pathway inhibitor rapamycin on model cells were further analyzed. RESULTS: The expression of S1PR2 was significantly increased in AD mice, the sh-S1PR2 significantly improved behavioral dysfunction, alleviated pathological injury of the hippocampus, increased the number of neurons, and inhibited Aβ production and p-tau expression, showing a positive effect on the AD pathology. In addition, silencing of S1PR2 expression significantly promoted the autophagy level and inhibited the activation of the AKT/mTOR pathway in AD model mice. In vitro experiments further confirmed that sh-S1PR2 promoted cell proliferation, inhibited apoptosis, relieved cytopathology, promoted autophagy, and inhibited the activation of the AKT/mTOR pathway in the cell model. The use of rapamycin further confirmed the role of AKT/mTOR pathway-mediated autophagy in the regulation of AD by S1PR2. CONCLUSION: S1PR2 promoted AD pathogenesis by inhibiting autophagy through the activation of AKT/mTOR pathway.

Soluble TREM2, Alzheimer's Disease Pathology, and Risk for Progression of Cerebral Small Vessel Disease: A Longitudinal Study. - Wu, Chao; Ma, Ya-Hui; Hu, Hao; Zhao, Bing; Tan, Lan (J Alzheimers Dis, 2023)
BackgroundUntil recently, studies on associations between neuroinflammation in vivo and cerebral small vessel disease (CSVD) are scarce. Cerebrospinal fluid (CSF) levels of soluble triggering receptor expressed on myeloid cells 2 (sTREM2), a candidate biomarker of microglial activation and neuroinflammation, were found elevated in Alzheimer's disease (AD), but they have not been fully explored in CSVD.ObjectiveTo determine whether CSF sTREM2 levels are associated with the increased risk of CSVD progression.MethodsA total of 426 individuals from the Alzheimer's Disease Neuroimaging Initiative (ADNI) database were included in this study. All participants underwent measurements of CSF sTREM2 and AD pathology (Aβ1-42, P-tau181P). The progression of CSVD burden and imaging markers, including cerebral microbleeds (CMBs), white matter hyperintensities and lacunes, were estimated based on neuroimaging changes. Logistic regression and moderation effect models were applied to explore associations of sTREM2 with CSVD progression and AD pathology.Results Higher CSF sTREM2 levels at baseline were associated with increased CSVD burden (OR = 1.28 [95% CI, 1.01-1.62]) and CMBs counts (OR = 1.32 [95% CI, 1.03-1.68]). Similarly, increased change rates of CSF sTREM2 might predict elevated CMBs counts (OR = 1.44 [95% CI, 1.05-1.98]). Participants with AD pathology (Aβ1-42 and P-tau181P) showed a stronger association between CSF sTREM2 and CSVD progression.ConclusionThis longitudinal study found a positive association between CSF sTREM2 and CSVD progression, suggesting that neuroinflammation might promote CSVD. Furthermore, neuroinflammation could be a shared pathogenesis of CSVD and AD at the early stage. Targeting neuroinflammation to intervene the progression of CSVD and AD warrants further investigation.
Keywords: Alzheimer Disease; Biomarkers; Cerebral Small Vessel Diseases; Humans; Longitudinal Studies; Membrane Glycoproteins; Myeloid Cells; Neuroinflammatory Diseases; Receptors, Immunologic

Two-Year Changes in Physical Activity and Concurrent Changes in Cognitive Function in a Cohort of Adults with Metabolic Syndrome. - Rognoni, Teresa; Fernández-Matarrubia, Marta; Martínez-González, Miguel Ángel; Salas-Salvadó, Jordi; Corella, Dolores; Castañer, Olga; Martínez, J Alfredo; Alonso-Gómez, Ángel M; Gómez-Gracia, Enrique; Vioque, Jesús; Romaguera, Dora; López-Miranda, José; et al. (J Alzheimers Dis, 2023)
BACKGROUND: It has been proposed that physical activity (PA) could prevent cognitive decline. OBJECTIVE: To evaluate the association between changes in PA and changes in cognitive function in a cohort of adults with metabolic syndrome. METHODS: Longitudinal observational study including 5,500 adults (mean age 65 years, SD = 5; women = 49.3%) with metabolic syndrome. Participants underwent physical activity measurements and cognitive evaluation at baseline and at two-years of follow-up. PA was quantified using the Minnesota questionnaire-shortened version. Cognitive function was evaluated using a battery of tests: Mini-Mental Test Examination, Clock Drawing Test, Trail Making Test A and B, Verbal Fluency Test, and Digit Span. The primary outcome was change in cognition at two-year follow-up, as measured through the Global Composite Score (GCS) of all neuropsychological tests. Multivariable-adjusted linear regression models were fitted with baseline PA and their changes as the main exposures and changes in cognitive function as the outcome. RESULTS: No significant association was found between PA levels (or their changes) and changes in cognitive function, as measured by the GCS. A greater increase in PA levels was associated with a more favorable two-year change in performance on the Trail Making Test A (Q4 versus Q1: b = -2.15, 95% CI -4.25 to -0.05; p-trend = 0.024). No significant association was found for other neuropsychological test. CONCLUSION: Our results do not support an association between increases in PA and the evolution of the global cognitive function at two-year follow-up, but they suggested a possible beneficial effect of PA on attentional function in older adults.

Urinary Amino Acid-Conjugated Acrolein and Taurine as New Biomarkers for Detection of Dementia. - Yoshida, Madoka; Uemura, Takeshi; Mizoi, Mutsumi; Waragai, Masaaki; Sakamoto, Akihiko; Terui, Yusuke; Kashiwagi, Keiko; Igarashi, Kazuei (J Alzheimers Dis, 2023)
BACKGROUND: Dementia, including Alzheimer's disease (AD), is one of the serious diseases at advanced age, and its early detection is important for maintaining quality of life (QOL). OBJECTIVE: In this study, we sought novel biomarkers for dementia in urine. METHODS: Samples of urine were collected from 57 control subjects without dementia, 62 mild cognitive impairment (MCI) patients, and 42 AD patients. Mini-Mental State Examination (MMSE) was evaluated when subjects were examined by medical doctors. Urinary amino acid (lysine)-conjugated acrolein (AC-Acro) was measured using N ɛ -(3-formyl-3, 4-dehydropiperidine) lysine (FDP-Lys) ELISA kit, and taurine content was measured using a taurine assay kit. Values were normalized by creatinine content which was measured with the colorimetric assay kit. RESULTS: We found that urinary amino acid (lysine)-conjugated acrolein (AC-Acro) and taurine negatively correlated with MMSE score and are significantly lower in dementia patients compared to the normal subjects. When AC-Acro and taurine were evaluated together with age using an artificial neural network model, median relative risk values for subjects with AD, subjects with mild cognitive impairment, and control subjects were 0.96, 0.53, and 0.06, respectively. CONCLUSION: Since urine is relatively easy to collect, our findings provide a novel biomarker for dementia without invasiveness.

5-Hydroxymethylcytosine Signatures in Circulating Cell-Free DNA as Diagnostic Biomarkers for Late-Onset Alzheimer's Disease. - Chen, Lei; Shen, Qianqian; Xu, Shunliang; Yu, Hongzhuan; Pei, Shengjie; Zhang, Yangting; He, Xin; Wang, QiuZhen; Li, Duo (J Alzheimers Dis, 2022)
BACKGROUND: 5-Hydroxymethylcytosine (5hmC) is an epigenetic DNA modification that is highly abundant in central nervous system. It has been reported that DNA 5hmC dysregulation play a critical role in Alzheimer's disease (AD) pathology. Changes in 5hmC signatures can be detected in circulating cell-free DNA (cfDNA), which has shown potential as a non-invasive liquid biopsy material. OBJECTIVE: However, the genome-wide profiling of 5hmC in cfDNA and its potential for the diagnosis of AD has not been reported to date. METHODS: We carried out a case-control study and used a genome-wide chemical capture followed by high-throughput sequencing to detect the genome-wide profiles of 5hmC in human cfDNA and identified differentially hydroxymethylated regions (DhMRs) in late-onset AD patients and the control. RESULTS: We discovered significant differences of 5hmC enrichment in gene bodies which were linked to multiple AD pathogenesis-associated signaling pathways in AD patients compared with cognitively normal controls, indicating they can be well distinguished from normal controls by DhMRs in cfDNA. Specially, we identified 7 distinct genes (RABEP1, CPNE4, DNAJC15, REEP3, ROR1, CAMK1D, and RBFOX1) with predicting diagnostic potential based on their significant correlations with MMSE and MoCA scores of subjects. CONCLUSION: The present results suggest that 5hmC markers derived from plasma cfDNA can served as an effective, minimally invasive biomarkers for clinical auxiliary diagnosis of late-onset AD.
Keywords: 5-Methylcytosine; Aged; Alzheimer Disease; Biomarkers; Case-Control Studies; Cell-Free Nucleic Acids; DNA Methylation; DNA, Neoplasm; Epigenesis, Genetic; Female; High-Throughput Nucleotide Sequencing; Humans; Male; Middle Aged

Analysis and Identification Genetic Effect of SARS-CoV-2 Infections to Alzheimer's Disease Patients by Integrated Bioinformatics. - Wang, Fang; Xu, Jia; Xu, Shu-Jun; Guo, Jie-Jie; Wang, Feiming; Wang, Qin-Wen (J Alzheimers Dis, 2022)
BACKGROUND: COVID-19 pandemic is a global crisis which results in millions of deaths and causes long-term neurological sequelae, such as Alzheimer's disease (AD). OBJECTIVE: We aimed to explore the interaction between COVID-19 and AD by integrating bioinformatics to find the biomarkers which lead to AD occurrence and development with COVID-19 and provide early intervention. METHODS: The differential expressed genes (DEGs) were found by GSE147507 and GSE132903, respectively. The common genes between COVID-19 and AD were identified. Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and protein-protein interactions (PPI) network analysis were carried out. Hub genes were found by cytoscape. A multivariate logistic regression model was constructed. NetworkAnalyst was used for the analysis of TF-gene interactions, TF-miRNA coregulatory network, and Protein-chemical Interactions. RESULTS: Forty common DEGs for AD and COVID-19 were found. GO and KEGG analysis indicated that the DEGs were enriched in the calcium signal pathway and other pathways. A PPI network was constructed, and 5 hub genes were identified (ITPR1, ITPR3, ITPKB, RAPGEF3, MFGE8). Four hub genes (ITPR1, ITPR3, ITPKB, RAPGEF3) which were considered as important factors in the development of AD that were affected by COVID-19 were shown by nomogram. Utilizing NetworkAnalyst, the interaction network of 4 hub genes and TF, miRNA, common AD risk genes, and known compounds is displayed, respectively. CONCLUSION: COVID-19 patients are at high risk of developing AD. Vaccination is required. Four hub genes can be considered as biomarkers for prediction and treatment of AD development caused by COVID-19. Compounds with neuroprotective effects can be used as adjuvant therapy for COVID-19 patients.
Keywords: Alzheimer Disease; Computational Biology; COVID-19; Databases, Genetic; Gene Expression Profiling; Humans; Protein Interaction Maps; SARS-CoV-2

Association Between High Serum Tetrahydrofolate and Low Cognitive Functions in the United States: A Cross-Sectional Study. - Fan, Yaohua; Liu, Wen; Chen, Si; Li, Mengzhu; Zhao, Lijun; Wu, Chunxiao; Liu, Helu; Zhu, Meiling (J Alzheimers Dis, 2022)
BACKGROUND: The relationship between serum folate status and cognitive functions is still controversial. OBJECTIVE: To evaluate the association between serum tetrahydrofolate and cognitive functions. METHODS: A total of 3,132 participants (60-80 years old) from the 2011-2014 NHANES were included in this cross-sectional study. The primary outcome measure was cognitive function assessment, determined by the Consortium to Establish a Registry for Alzheimer's Disease Word Learning Test (CERAD-WL), CERAD-Delayed Recall Test (CERAD-DR), Animal Fluency Test (AF), Digit Symbol Substitution Test (DSST), and global cognitive score. Generalized linear model (GLM), multivariate logistic regression models, weighted generalized additive models (GAM), and subgroup analyses were performed to evaluate the association between serum tetrahydrofolate and low cognitive functions. RESULTS: In GLM, and the crude model, model 1, model 2 of multivariate logistic regression models, increased serum tetrahydrofolate was associated with reduced cognitive functions via AF, DSST, CERAD-WL, CERAD-DR, and global cognitive score (p <  0.05). In GAM, the inflection points were 1.1, 2.8, and 2.8 nmol/L tetrahydrofolate, determined by a two-piece wise linear regression model of AF, DSST, and global cognitive score, respectively. Also, in GAM, there were no non-linear relationship between serum tetrahydrofolate and low cognitive functions, as determined by CERAD-WL or CERAD-DR. The results of subgroup analyses found that serum tetrahydrofolate levels and reduced cognitive functions as determined by AF had significant interactions for age and body mass index. The association between high serum tetrahydrofolate level and reduced cognitive functions as determined using DSST, CERAD-WL, CERAD-DR, or global cognitive score had no interaction with the associations between cognition and gender, or age, or so on. CONCLUSION: High serum tetrahydrofolate level is associated with significantly reduced cognitive function.

Association Between Serum Vitamins and the Risk of Alzheimer's Disease in Chinese Population. - Liu, Xi-Xi; Wu, Peng-Fei; Liu, Ying-Zi; Jiang, Ya-Ling; Wan, Mei-Dan; Xiao, Xue-Wen; Yang, Qi-Jie; Jiao, Bin; Liao, Xin-Xin; Wang, Jun-Ling; Liu, Shao-Hui; Zhang, Xuewei; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Alzheimer's disease (AD) is a chronic and fatal neurodegenerative disease; accumulating evidence suggests that vitamin deficiency is associated with the risk of AD. However, studies attempting to elucidate the relationship between vitamins and AD varied widely. OBJECTIVE: This study aimed to investigate the relationship between serum vitamin levels and AD in a cohort of the Chinese population. METHODS: A total of 368 AD patients and 574 healthy controls were recruited in this study; serum vitamin A, B1, B6, B9, B12, C, D, and E were measured in all participants. RESULTS: Compared with the controls, vitamin B2, B9, B12, D, and E were significantly reduced in AD patients. Lower levels of vitamin B2, B9, B12, D, and E were associated with the risk of AD. After adjusting for age and gender, low levels of vitamin B2, B9, and B12 were still related to the risk of AD. In addition, a negative correlation was determined between vitamin E concentration and Activity of Daily Living Scale score while no significant association was found between serum vitamins and age at onset, disease duration, Mini-Mental State Examination, and Neuropsychiatric Inventory Questionnaire score. CONCLUSION: We conclude that lower vitamin B2, B9, B12, D, and E might be associated with the risk of AD, especially vitamin B2, B9, and B12. And lower vitamin E might be related to severe ability impairment of daily activities.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Case-Control Studies; China; Female; Folic Acid; Humans; Logistic Models; Male; Mental Status and Dementia Tests; Middle Aged; Riboflavin; Risk; Vitamin B 12; Vitamin D; Vitamin E

Association of Brain Volume and Retinal Thickness in the Early Stages of Alzheimer's Disease. - Mathew, Sunu; WuDunn, Darrell; Mackay, Devin D; Vosmeier, Aaron; Tallman, Eileen F; Deardorff, Rachael; Harris, Alon; Farlow, Martin R; Brosch, Jared R; Gao, Sujuan; Apostolova, Liana G; Saykin, Andrew J; et al. (J Alzheimers Dis, 2022)
BACKGROUND: The eye has been considered a 'window to the brain,' and several neurological diseases including neurodegenerative conditions like Alzheimer's disease (AD) also show changes in the retina. OBJECTIVE: To investigate retinal nerve fiber layer (RNFL) thickness and its association with brain volume via magnetic resonance imaging (MRI) in older adults with subjective or objective cognitive decline. METHODS: 75 participants underwent ophthalmological and neurological evaluation including optical coherence tomography and MRI (28 cognitively normal subjects, 26 with subjective cognitive decline, 17 patients diagnosed with mild cognitive impairment, and 4 with AD). Differences in demographics, thickness of RNFL, and brain volume were assessed using ANCOVA, while partial Pearson correlations, covaried for age and sex, were used to compare thickness of the peripapillary RNFL with brain volumes, with p < 0.05 considered statistically significant. RESULTS: Mean RNFL thickness was significantly correlated with brain volumes, including global volume (right eye r = 0.235 p = 0.046, left eye r = 0.244, p = 0.037), temporal lobe (right eye r = 0.242 p = 0.039, left eye r = 0.290, p = 0.013), hippocampal (right eye r = 0.320 p = 0.005, left eye r = 0.306, p = 0.008), amygdala (left eye r = 0.332, p = 0.004), and occipital lobe (right eye r = 0.264 p = 0.024) volumes. CONCLUSION: RNFL thickness in both eyes was positively associated with brain volumes in subjects with subjective and objective cognitive decline. The RNFL, however, did not correlate with the disease, but the small sample number makes it important to conduct larger studies. RNFL thickness may be a useful non-invasive and inexpensive tool for detection of brain neurodegeneration and may assist with diagnosis and monitoring of progression and treatment in AD.

Association of Cholinergic Basal Forebrain Volume and Functional Connectivity with Markers of Inflammatory Response in the Alzheimer's Disease Spectrum. - Teipel, Stefan J; Dyrba, Martin; Ballarini, Tommaso; Brosseron, Frederic; Bruno, Davide; Buerger, Katharina; Cosma, Nicoleta-Carmen; Dechent, Peter; Dobisch, Laura; Düzel, Emrah; Ewers, Michael; Fliessbach, Klaus; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Inflammation has been described as a key pathogenic event in Alzheimer's disease (AD), downstream of amyloid and tau pathology. Preclinical and clinical data suggest that the cholinergic basal forebrain may moderate inflammatory response to different pathologies. OBJECTIVE: To study the association of cholinergic basal forebrain volume and functional connectivity with measures of neuroinflammation in people from the AD spectrum. METHODS: We studied 261 cases from the DELCODE cohort, including people with subjective cognitive decline, mild cognitive impairment, AD dementia, first degree relatives, and healthy controls. Using Bayesian ANCOVA, we tested associations of MRI indices of cholinergic basal forebrain volume and functional connectivity with cerebrospinal fluid (CSF) levels of sTREM2 as a marker of microglia activation, and serum levels of complement C3. Using Bayesian elastic net regression, we determined associations between basal forebrain measures and a large inflammation marker panel from CSF and serum. RESULTS: We found anecdotal to moderate evidence in favor of the absence of an effect of basal forebrain volume and functional connectivity on CSF sTREM2 and serum C3 levels both in Aβ42/ptau-positive and negative cases. Bayesian elastic net regression identified several CSF and serum markers of inflammation that were associated with basal forebrain volume and functional connectivity. The effect sizes were moderate to small. CONCLUSION: Our data-driven analyses generate the hypothesis that cholinergic basal forebrain may be involved in the neuroinflammation response to Aβ42 and phospho-tau pathology in people from the AD spectrum. This hypothesis needs to be tested in independent samples.
Keywords: Aged; Alzheimer Disease; Basal Forebrain; Biomarkers; Cholinergic Agents; Cognitive Dysfunction; Cohort Studies; Female; Humans; Inflammation; Magnetic Resonance Imaging; Male

Association of COVID-19 with New-Onset Alzheimer's Disease. - Wang, Lindsey; Davis, Pamela B; Volkow, Nora D; Berger, Nathan A; Kaelber, David C; Xu, Rong (J Alzheimers Dis, 2022)
An infectious etiology of Alzheimer's disease has been postulated for decades. It remains unknown whether SARS-CoV-2 viral infection is associated with increased risk for Alzheimer's disease. In this retrospective cohort study of 6,245,282 older adults (age ≥65 years) who had medical encounters between 2/2020-5/2021, we show that people with COVID-19 were at significantly increased risk for new diagnosis of Alzheimer's disease within 360 days after the initial COVID-19 diagnosis (hazard ratio or HR:1.69, 95% CI: 1.53-1.72), especially in people age ≥85 years and in women. Our findings call for research to understand the underlying mechanisms and for continuous surveillance of long-term impacts of COVID-19 on Alzheimer's disease.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; COVID-19; COVID-19 Testing; Female; Humans; Retrospective Studies; SARS-CoV-2

Associations of Pulmonary Function with MRI Brain Volumes: A Coordinated Multi-Study Analysis. - Frenzel, Stefan; Bis, Josh C; Gudmundsson, Elias F; O'Donnell, Adrienne; Simino, Jeannette; Yaqub, Amber; Bartz, Traci M; Brusselle, Guy G O; Bülow, Robin; DeCarli, Charles S; Ewert, Ralf; Gharib, Sina A; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Previous studies suggest poor pulmonary function is associated with increased burden of cerebral white matter hyperintensities and brain atrophy among elderly individuals, but the results are inconsistent. OBJECTIVE: To study the cross-sectional associations of pulmonary function with structural brain variables. METHODS: Data from six large community-based samples (N = 11,091) were analyzed. Spirometric measurements were standardized with respect to age, sex, height, and ethnicity using reference equations of the Global Lung Function Initiative. Associations of forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), and their ratio FEV1/FVC with brain volume, gray matter volume, hippocampal volume, and volume of white matter hyperintensities were investigated using multivariable linear regressions for each study separately and then combined using random-effect meta-analyses. RESULTS: FEV1 and FVC were positively associated with brain volume, gray matter volume, and hippocampal volume, and negatively associated with white matter hyperintensities volume after multiple testing correction, with little heterogeneity present between the studies. For instance, an increase of FVC by one unit was associated with 3.5 ml higher brain volume (95% CI: [2.2, 4.9]). In contrast, results for FEV1/FVC were more heterogeneous across studies, with significant positive associations with brain volume, gray matter volume, and hippocampal volume, but not white matter hyperintensities volume. Associations of brain variables with both FEV1 and FVC were consistently stronger than with FEV1/FVC, specifically with brain volume and white matter hyperintensities volume. CONCLUSION: In cross-sectional analyses, worse pulmonary function is associated with smaller brain volumes and higher white matter hyperintensities burden.

B Vitamin Supplementation Slows Cognitive Decline in Mild Cognitive Impairment Patients with Frontal Lobe Atrophy. - Gong, Xianmin; Shi, Lin; Wu, Yuanyuan; Luo, Yishan; Kwok, Timothy (J Alzheimers Dis, 2022)
BACKGROUND: The effects of B vitamins on mild cognitive impairment (MCI) patients' cognition have been mixed, suggesting the existence of moderating factors. OBJECTIVE: A post hoc analysis of a negative B vitamin trial was performed to examine the potential modulating effect of regional brain atrophy on the cognitive response to B vitamins in MCI patients. METHODS: In the 24-month randomized trial, 279 MCI outpatients took 500μ#x03BC;g methylcobalamin and 400μ#x03BC;g folic acid once per day or placebo tablets once per day. Sixty-four aspirin users were excluded from analysis as aspirin use has been found to have significant negative interaction effects. Subjects were followed up at months 12 and 24. The primary cognitive outcome was clinical dementia rating scale sum of boxes (CDR_SOB). In a subgroup of 83 subjects, MRI brain scans were performed at baseline to estimate regional brain atrophy ratios. RESULTS: Among the trial subjects who had MRI data, B vitamin supplementation had no significant effect on CDR_SOB, despite having significant homocysteine lowering effects. The atrophy ratio of the left frontal lobe significantly moderated the effect of B vitamin supplementation on CDR_SOB, after adjusting for confounders, in that B vitamin supplementation was associated with lower CDR_SOB scores (i.e., better cognitive function) at the 24th month among those patients with above median atrophy ratios, but not among those with lower atrophy ratios, in the left frontal lobe. CONCLUSION: B vitamins may be more effective in slowing down cognitive decline in MCI patients with atrophy in the left frontal lobe.

Behavioral and Psychological Symptoms of Dementia in Different Dementia Disorders: A Large-Scale Study of 10,000 Individuals. - Schwertner, Emilia; Pereira, Joana B; Xu, Hong; Secnik, Juraj; Winblad, Bengt; Eriksdotter, Maria; Nägga, Katarina; Religa, Dorota (J Alzheimers Dis, 2022)
BACKGROUND: The majority of individuals with dementia will suffer from behavioral and psychological symptoms of dementia (BPSD). These symptoms contribute to functional impairment and caregiver burden. OBJECTIVE: To characterize BPSD in Alzheimer's disease (AD), vascular dementia (VaD), mixed (Mixed) dementia, Parkinson's disease dementia (PDD), dementia with Lewy bodies (DLB), frontotemporal dementia (FTD), and unspecified dementia in individuals residing in long-term care facilities. METHODS: We included 10,405 individuals with dementia living in long-term care facilities from the Swedish registry for cognitive/dementia disorders (SveDem) and the Swedish BPSD registry. BPSD was assessed with the Neuropsychiatric Inventory - Nursing Home Version (NPI-NH). Multivariate logistic regression models were used to evaluate the associations between dementia diagnoses and different BPSDs. RESULTS: The most common symptoms were aberrant motor behavior, agitation, and irritability. Compared to AD, we found a lower risk of delusions (in FTD, unspecified dementia), hallucinations (FTD), agitation (VaD, PDD, unspecified dementia), elation/euphoria (DLB), anxiety (Mixed, VaD, unspecified dementia), disinhibition (in PDD), irritability (in DLB, FTD, unspecified dementia), aberrant motor behavior (Mixed, VaD, unspecified dementia), and sleep and night-time behavior changes (unspecified dementia). Higher risk of delusions (DLB), hallucinations (DLB, PDD), apathy (VaD, FTD), disinhibition (FTD), and appetite and eating abnormalities (FTD) were also found in comparison to AD. CONCLUSION: Although individuals in our sample were diagnosed with different dementia disorders, they all exhibited aberrant motor behavior, agitation, and irritability. This suggests common underlying psychosocial or biological mechanisms. We recommend prioritizing these symptoms while planning interventions in long-term care facilities.
Keywords: Alzheimer Disease; Behavioral Symptoms; Dementia, Vascular; Frontotemporal Dementia; Hallucinations; Humans; Parkinson Disease

Blood Pressure and Later-Life Cognition in Hispanic and White Adults (BP-COG): A Pooled Cohort Analysis of ARIC, CARDIA, CHS, FOS, MESA, and NOMAS. - Levine, Deborah A; Gross, Alden L; Briceño, Emily M; Tilton, Nicholas; Whitney, Rachael; Han, Dehua; Giordani, Bruno J; Sussman, Jeremy B; Hayward, Rodney A; Burke, James F; Elkind, Mitchell S V; Moran, Andrew E; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Ethnic differences in cognitive decline have been reported. Whether they can be explained by differences in systolic blood pressure (SBP) is uncertain. OBJECTIVE: Determine whether cumulative mean SBP levels explain differences in cognitive decline between Hispanic and White individuals. METHODS: Pooled cohort study of individual participant data from six cohorts (1971-2017). The present study reports results on SBP and cognition among Hispanic and White individuals. Outcomes were changes in global cognition (GC) (primary), executive function (EF) (secondary), and memory standardized as t-scores (mean [SD], 50 [10]); a 1-point difference represents a 0.1 SD difference in cognition. Median follow-up was 7.7 (Q1-Q3, 5.2-20.1) years. RESULTS: We included 24,570 participants free of stroke and dementia: 2,475 Hispanic individuals (median age, cumulative mean SBP at first cognitive assessment, 67 years, 132.5 mmHg; 40.8% men) and 22,095 White individuals (60 years,134 mmHg; 47.3% men). Hispanic individuals had slower declines in GC, EF, and memory than White individuals when all six cohorts were examined. Two cohorts recruited Hispanic individuals by design. In a sensitivity analysis, Hispanic individuals in these cohorts had faster decline in GC, similar decline in EF, and slower decline in memory than White individuals. Higher time-varying cumulative mean SBP was associated with faster declines in GC, EF, and memory in all analyses. After adjusting for time-varying cumulative mean SBP, differences in cognitive slopes between Hispanic and White individuals did not change. CONCLUSION: We found no evidence that cumulative mean SBP differences explained differences in cognitive decline between Hispanic and White individuals.

Brain Tissue-Derived Extracellular Vesicles in Alzheimer's Disease Display Altered Key Protein Levels Including Cell Type-Specific Markers. - Huang, Yiyao; Driedonks, Tom A P; Cheng, Lesley; Rajapaksha, Harinda; Routenberg, David A; Nagaraj, Rajini; Redding, Javier; Arab, Tanina; Powell, Bonita H; Pletniková, Olga; Troncoso, Juan C; Zheng, Lei; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Brain tissue-derived extracellular vesicles (bdEVs) play neurodegenerative and protective roles, including in Alzheimer's disease (AD). Extracellular vesicles (EVs) may also leave the brain to betray the state of the CNS in the periphery. Only a few studies have profiled the proteome of bdEVs and source brain tissue. Additionally, studies focusing on bdEV cell type-specific surface markers are rare. OBJECTIVE: We aimed to reveal the pathological mechanisms inside the brain by profiling the tissue and bdEV proteomes in AD patients. In addition, to indicate targets for capturing and molecular profiling of bdEVs in the periphery, CNS cell-specific markers were profiled on the intact bdEV surface. METHODS: bdEVs were separated and followed by EV counting and sizing. Brain tissue and bdEVs from age-matched AD patients and controls were then proteomically profiled. Total tau (t-tau), phosphorylated tau (p-tau), and antioxidant peroxiredoxins (PRDX) 1 and 6 were measured by immunoassay in an independent bdEV separation. Neuron, microglia, astrocyte, and endothelia markers were detected on intact EVs by multiplexed ELISA. RESULTS: Overall, concentration of recovered bdEVs was not affected by AD. Proteome differences between AD and control were more pronounced for bdEVs than for brain tissue. Levels of t-tau, p-tau, PRDX1, and PRDX6 were significantly elevated in AD bdEVs compared with controls. Release of certain cell-specific bdEV markers was increased in AD. CONCLUSION: Several bdEV proteins are involved in AD mechanisms and may be used for disease monitoring. The identified CNS cell markers may be useful tools for peripheral bdEV capture.

Can Diet Supplements of Macular Pigment of Lutein, Zeaxanthin, and Meso-zeaxanthin Affect Cognition? - Wang, Hongwei; Wang, Ge; Billings, Rebecca; Li, Daniel; Haase, Shakaye R; Wheeler, Pariya F; Vance, David E; Li, Wei (J Alzheimers Dis, 2022)
BACKGROUND: Lutein (L), zeaxanthin (Z), and meso-zeaxanthin (MZ) are collectively called macular pigment. MZ can be converted from L in the macula. In the recent decade, many studies have been performed to investigate the effects for taking carotenoids, especially L and Z or L, Z, and MZ, as diet supplements on human health. OBJECTIVE: We examined if diet supplements of L + Z or L + Z + MZ have effects on cognitive function in adults. METHODS: A systemic literature search was performed in March 2021 with the following keywords: lutein, zeaxanthin, meso-zeaxanthin, cognition, cognitive, and macular pigment. The searched databases included Medline EBSCOhost, Scopus, Elsevier, Cochrane Library, ProQuest, and ClinicalTrials.gov. Findings from eight clinical trials were presented as the strongest evidence on the studied topic. RESULTS: Most studies have found that macular pigments (L + Z) in blood or macula are positively correlated with cognitive performance. As an index of the amount of macular pigments in the brain, macular pigment optical density is related to cognitive performance in adults. In addition, there is an inverse relationship between a higher amount of macular pigment in the blood and lower risk of mild cognitive impairments or Alzheimer's disease. Based on the findings from the clinical trials, diet supplements of L + Z or L + Z + MZ are associated with improved cognition in adults. CONCLUSION: The diet supplements of L + Z or L + Z+MZ are associated with better cognitive functioning, which may be via their beneficial effects on the vision.

"Captive by the Uncertainty"-Experiences with Anticipatory Guidance for People Living with Dementia and Their Caregivers at a Specialty Dementia Clinic. - Shafir, Adi; Ritchie, Christine S; Garrett, Sarah B; Bernstein Sideman, Alissa; Naasan, Georges; Merrilees, Jennifer; Widera, Eric; Flint, Lynn; Harrison, Krista L (J Alzheimers Dis, 2022)
BACKGROUND: After a diagnosis of Alzheimer's disease and related disorders, people living with dementia (PWD) and caregivers wonder what disease trajectory to expect and how to plan for functional and cognitive decline. This qualitative study aimed to identify patient and caregiver experiences receiving anticipatory guidance about dementia from a specialty dementia clinic. OBJECTIVE: To examine PWD and caregiver perspectives on receiving anticipatory guidance from a specialty dementia clinic. METHODS: We conducted semi-structured interviews with PWD, and active and bereaved family caregivers, recruited from a specialty dementia clinic. Interviews were recorded, transcribed, and systematically summarized. Thematic analysis identified anticipatory guidance received from clinical or non-clinical sources and areas where respondents wanted additional guidance. RESULTS: Of 40 participants, 9 were PWD, 16 were active caregivers, and 15 were bereaved caregivers. PWD had a mean age of 75 and were primarily male (n = 6/9); caregivers had a mean age of 67 and were primarily female (n = 21/31). Participants felt they received incomplete or "hesitant" guidance on prognosis and expected disease course via their clinicians and filled the gap with information they found via the internet, books, and support groups. They appreciated guidance on behavioral, safety, and communication issues from clinicians, but found more timely and advance guidance from other non-clinical sources. Guidance on legal and financial planning was primarily identified through non-clinical sources. CONCLUSION: PWD and caregivers want more information about expected disease course, prognosis, and help planning after diagnosis. Clinicians have an opportunity to improve anticipatory guidance communication and subsequent care provision.
Keywords: Aged; Alzheimer Disease; Caregivers; Dementia; Female; Humans; Male; Qualitative Research; Uncertainty

Circulating Cell-Free Genomic DNA Is Associated with an Increased Risk of Dementia and with Change in Cognitive and Physical Function. - Nidadavolu, Lolita S; Feger, Danielle; Wu, Yuqiong; Grodstein, Francine; Gross, Alden L; Bennett, David A; Walston, Jeremy D; Oh, Esther S; Abadir, Peter M (J Alzheimers Dis, 2022)
BACKGROUND: Altered cell homeostasis, seen in cognitive decline and frailty, leads to cell death and turnover, releasing circulating cell-free DNA (ccf-DNA). OBJECTIVE: The goal of this study is to determine if serum genomic cell-free DNA (ccf-gDNA) is associated with physical and cognitive decline in older adults. METHODS: We used serum from 631 community-dwelling individuals from the Religious Orders Study or Rush Memory and Aging Project who were without cognitive impairment at baseline. ccf-gDNA fragments in serum were quantified using digital PCR. An array of cognitive and physical traits, risk of dementia, global cognition, and frailty at or nearest the time of blood draw were regressed on ccf-DNA, with adjustment for age, sex, race, and education. RESULTS: Cross-sectionally, higher ccf-gDNA levels were associated with lower global cognition score and slower gait speed at the evaluation nearest to blood draw. Higher ccf-gDNA levels were associated with increased odds of incident dementia (OR 1.27, 95% CI 1.05, 1.54). Longitudinally, higher levels of ccf-gDNA were associated with steeper general cognitive decline and worsening frailty over eight years of follow up. CONCLUSION: This study demonstrates that ccf-gDNA fragments have utility for identifying persons at higher risk of developing dementia and worsening cognition and frailty.

Comparative Analysis of Alzheimer's Disease Cerebrospinal Fluid Biomarkers Measurement by Multiplex SOMAscan Platform and Immunoassay-Based Approach. - Timsina, Jigyasha; Gomez-Fonseca, Duber; Wang, Lihua; Do, Anh; Western, Dan; Álvarez, Ignacio; Aguilar, Miquel; Pastor, Pau; Henson, Rachel L; Herries, Elizabeth; Xiong, Chengjie; Schindler, Suzanne E; et al. (J Alzheimers Dis, 2022)
BACKGROUND: The SOMAscan assay has an advantage over immunoassay-based methods because it measures a large number of proteins in a cost-effective manner. However, the performance of this technology compared to the routinely used immunoassay techniques needs to be evaluated. OBJECTIVE: We performed comparative analyses of SOMAscan and immunoassay-based protein measurements for five cerebrospinal fluid (CSF) proteins associated with Alzheimer's disease (AD) and neurodegeneration: NfL, Neurogranin, sTREM2, VILIP-1, and SNAP-25. METHODS: We compared biomarkers measured in ADNI (N = 689), Knight-ADRC (N = 870), DIAN (N = 115), and Barcelona-1 (N = 92) cohorts. Raw protein values were transformed using z-score in order to combine measures from the different studies. sTREM2 and VILIP-1 had more than one analyte in SOMAscan; all available analytes were evaluated. Pearson's correlation coefficients between SOMAscan and immunoassays were calculated. Receiver operating characteristic curve and area under the curve were used to compare prediction accuracy of these biomarkers between the two platforms. RESULTS: Neurogranin, VILIP-1, and NfL showed high correlation between SOMAscan and immunoassay measures (r >  0.9). sTREM2 had a fair correlation (r >  0.6), whereas SNAP-25 showed weak correlation (r = 0.06). Measures in both platforms provided similar predicted performance for all biomarkers except SNAP-25 and one of the sTREM2 analytes. sTREM2 showed higher AUC for SOMAscan based measures. CONCLUSION: Our data indicate that SOMAscan performs as well as immunoassay approaches for NfL, Neurogranin, VILIP-1, and sTREM2. Our study shows promise for using SOMAscan as an alternative to traditional immunoassay-based measures. Follow-up investigation will be required for SNAP-25 and additional established biomarkers.

The Correlation of Tau Levels with Blood Monocyte Count in Patients with Alzheimer's Disease. - Sun, Hao-Lun; Zhou, Fa-Ying; Chen, Dong-Wan; Tan, Cheng-Rong; Zeng, Gui-Hua; Liu, Yu-Hui; Wang, Jun; Bu, Xian-Le; Wang, Yan-Jiang; Li, Hui-Yun; Jin, Wang-Sheng (J Alzheimers Dis, 2022)
BACKGROUND: Recent studies have shown that monocytes can phagocytize the tau protein, which may ameliorate tau-type pathology in Alzheimer's disease (AD). However, there are few clinical studies on the relationship between monocytes and tau-type pathology in AD patients. OBJECTIVE: We aimed to explore changes in peripheral monocytes and their association with tau protein in AD patients. METHODS: A total of 127 clinically diagnosed AD patients and 100 age- and sex-matched cognitively normal controls were recruited for analysis of the correlation of plasma tau levels with the blood monocyte count. Cerebrospinal fluid (CSF) samples from 46 AD patients and 88 controls were further collected to analyze the correlation of CSF tau and amyloid-β (Aβ) levels with the blood monocyte count. 105 clinically diagnosed mild cognitive impairment (MCI) patients and 149 age- and sex-matched cognitively normal controls were recruited from another cohort for verification. RESULTS: Compared to normal controls, AD patients showed a significant reduction in the blood monocyte count. In addition, the monocyte count of AD patients was negatively correlated with CSF t-tau and p-tau levels but not with plasma tau levels. In normal people, monocyte count lack correlation with tau levels both in plasma and CSF. Monocyte count were not correlated with CSF Aβ levels in either group but were negatively correlated with CSF tau/Aβ42 levels in the AD group. We had further verified the correlations of monocyte count with CSF tau levels in another cohort. CONCLUSION: This study suggests that monocytes may play an important role in the clearance of tau protein in the brain.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Brain; Cognitive Dysfunction; Cohort Studies; Female; Humans; Male; Monocytes; tau Proteins

Demonstration of Clinical Meaningfulness of the Integrated Alzheimer's Disease Rating Scale (iADRS): Association Between Change in iADRS Scores and Patient and Caregiver Health Outcomes. - Wessels, Alette M; Belger, Mark; Johnston, Joseph A; Yu, Youying; Rentz, Dorene M; Dowsett, Sherie A; Chandler, Julie (J Alzheimers Dis, 2022)
BACKGROUND: The integrated Alzheimer's Disease Rating Scale (iADRS) is a validated cognitive/functional composite that effectively captures cognitive and functional decline over a broad spectrum of disease. The clinical meaningfulness of change on iADRS can be supported by establishing an association with changes on important health outcome measures. OBJECTIVE: To evaluate the relationship between change on the iADRS and changes in health outcomes in individuals with mild cognitive impairment (MCI) due to Alzheimer's disease (AD), or mild or moderate AD dementia using placebo data from four AD clinical trials and data from one AD observational study. METHODS: Analysis of covariate (ANCOVA) models were used to estimate the relationship between 18-month change on the iADRS and changes on health outcome measures (related to cost, quality of life, and caregiver burden). The regression coefficients for the iADRS were used to compute impact of natural disease progression and disease-modifying treatment on health outcomes. Additional ANCOVAs were conducted to understand whether cognition and/or function was the underlying explanation of any association between iADRS and health outcome change. RESULTS: Across datasets and disease stages, a worsening on the iADRS was significantly associated with increased societal costs, caregiver burden (time and distress) and worsening in measures of patient quality of life. CONCLUSION: Decline on the iADRS was associated with worsening in health outcome measures. These findings suggest that the iADRS can be used in clinical trials as a proxy measure of clinically meaningful outcomes of AD progression.
Keywords: Alzheimer Disease; Caregivers; Clinical Trials as Topic; Cognitive Dysfunction; Humans; Observational Studies as Topic; Outcome Assessment, Health Care; Quality of Life

DNA Damage Increases Secreted Aβ40 and Aβ42 in Neuronal Progenitor Cells: Relevance to Alzheimer's Disease. - Welty, Starr; Thathiah, Amantha; Levine, Arthur Samuel (J Alzheimers Dis, 2022)
BACKGROUND: Recent studies suggest a strong association between neuronal DNA damage, elevated levels of amyloid-β (Aβ), and regions of the brain that degenerate in Alzheimer's disease (AD). OBJECTIVE: To investigate the nature of this association, we tested the hypothesis that extensive DNA damage leads to an increase in Aβ40 and Aβ42 generation. METHODS: We utilized an immortalized human neuronal progenitor cell line (NPCs), ReN VM GA2. NPCs or 20 day differentiated neurons were treated with hydrogen peroxide or etoposide and allowed to recover for designated times. Sandwich ELISA was used to assess secreted Aβ40 and Aβ42. Western blotting, immunostaining, and neutral comet assay were used to evaluate the DNA damage response and processes indicative of AD pathology. RESULTS: We determined that global hydrogen peroxide damage results in increased cellular Aβ40 and Aβ42 secretion 24 h after treatment in ReN GA2 NPCs. Similarly, DNA double strand break (DSB)-specific etoposide damage leads to increased Aβ40 and Aβ42 secretion 2 h and 4 h after treatment in ReN GA2 NPCs. In contrast, etoposide damage does not increase Aβ40 and Aβ42 secretion in post-mitotic ReN GA2 neurons. CONCLUSION: These findings provide evidence that in our model, DNA damage is associated with an increase in Aβ secretion in neuronal progenitors, which may contribute to the early stages of neuronal pathology in AD.

Does Loss of Integrity of the Cingulum Bundle Link Amyloid-β Accumulation and Neurodegeneration in Alzheimer's Disease? - Vlegels, Naomi; Ossenkoppele, Rik; van der Flier, Wiesje M; Koek, Huiberdina L; Reijmer, Yael D; Wisse, Laura Em; Biessels, Geert Jan (J Alzheimers Dis, 2022)
BACKGROUND: Alzheimer's disease is characterized by the accumulation of amyloid-β (Aβ) into plaques, aggregation of tau into neurofibrillary tangles, and neurodegenerative processes including atrophy. However, there is a poorly understood spatial discordance between initial Aβ deposition and local neurodegeneration. OBJECTIVE: Here, we test the hypothesis that the cingulum bundle links Aβ deposition in the cingulate cortex to medial temporal lobe (MTL) atrophy. METHODS: 21 participants with mild cognitive impairment (MCI) from the UMC Utrecht memory clinic (UMCU, discovery sample) and 37 participants with MCI from Alzheimer's Disease Neuroimaging Initiative (ADNI, replication sample) with available Aβ-PET scan, T1-weighted and diffusion-weighted MRI were included. Aβ load of the cingulate cortex was measured by the standardized uptake value ratio (SUVR), white matter integrity of the cingulum bundle was assessed by mean diffusivity and atrophy of the MTL by normalized MTL volume. Relationships were tested with linear mixed models, to accommodate multiple measures for each participant. RESULTS: We found at most a weak association between cingulate Aβ and MTL volume (added R2 <0.06), primarily for the posterior hippocampus. In neither sample, white matter integrity of the cingulum bundle was associated with cingulate Aβ or MTL volume (added R2 <0.01). Various sensitivity analyses (Aβ-positive individuals only, posterior cingulate SUVR, MTL sub region volume) provided similar results. CONCLUSION: These findings, consistent in two independent cohorts, do not support our hypothesis that loss of white matter integrity of the cingulum is a connecting factor between cingulate gyrus Aβ deposition and MTL atrophy.

Evaluation of the Accuracy of Cognitive Screening Tests in Detecting Dementia Associated with Alzheimer's Disease: A Hierarchical Bayesian Latent Class Meta-Analysis. - Wang, Xiaonan; Li, Fengjie; Gao, Qi; Jiang, Zhen; Abudusaimaiti, Xiayidanmu; Yao, Jiangyue; Zhu, Huiping (J Alzheimers Dis, 2022)
BACKGROUND: Montreal Cognitive Assessment (MoCA) and Mini-Mental State Examination (MMSE) are neuropsychological tests commonly used by physicians for screening cognitive dysfunction of Alzheimer's disease (AD). Due to different imperfect reference standards, the performance of MoCA and MMSE do not reach consensus. It is necessary to evaluate the consistence and differentiation of MoCA and MMSE in the absence of a gold standard for AD. OBJECTIVE: We aimed to assess the accuracy of MoCA and MMSE in screening AD without a gold standard reference test. METHODS: Studies were identified from PubMed, Web of Science, CNKI, Chinese Wanfang Database, China Science and Technology Journal Database, and Cochrane Library. Our search was limited to studies published in English and Chinese before August 2021. A hierarchical Bayesian latent class model was performed in meta-analysis when the gold standard was absent. RESULTS: A total of 67 studies comprising 5,554 individuals evaluated for MoCA and 76,862 for MMSE were included in this meta-analysis. The pooled sensitivity was 0.934 (95% CI 0.905 to 0.954) for MoCA and 0.883 (95% CI 0.859 to 0.903) for MMSE, while the pooled specificity was 0.899 (95% CI 0.859 to 0.928) for MoCA and 0.903 (95% CI 0.879 to 0.923) for MMSE. MoCA was useful to rule out dementia associated with AD with lower negative likelihood ratio (LR-) (0.074, 95% CI 0.051 to 0.108). MoCA showed better performance with higher diagnostic odds ratio (DOR) (124.903, 95% CI 67.459 to 231.260). CONCLUSION: MoCA had better performance than MMSE in screening dementia associated with AD from patients with mild cognitive impairment or healthy controls.
Keywords: Alzheimer Disease; Bayes Theorem; Cognition; Cognitive Dysfunction; Humans; Mental Status and Dementia Tests; Neuropsychological Tests

Excretion of Amyloid-β in the Gastrointestinal Tract and Regulation by the Gut Microbiota. - Wu, Shijing; Hu, Li; Lin, Jiajing; Li, Kanglan; Ye, Shicai; Zhu, Shaoping; Liu, Zhou (J Alzheimers Dis, 2022)
BACKGROUND: Amyloid-β (Aβ) is important in the etiology of Alzheimer's disease (AD). Removal of Aβ from the brain is a major strategy for the prevention and treatment of AD. OBJECTIVE: To clarify whether Aβ 42 can be cleared by intestinal excretion and whether the gut microbiota (GM) can affect the excretory clearance of Aβ 42 in the peripheral blood and intestines. METHODS: Male 8-month-old C57BL6 mice were maintained on either normal chow or received broad-spectrum antibiotics in their drinking water for one week. Sterile saline, fluorescein isothiocyanate (FITC), or FITC-Aβ 42 (fluorescein isothiocyanate-labeled amyloid-β 42 peptides) was injected 1 h before FITC, or FITC-Aβ 42 was injected 1 h before sampling. Related changes of Aβ 42 before and after injection were evaluated. RESULTS: FITC-Aβ 42 was injected into mice through the tail vein and could later be detected in feces. Furthermore, the fecal concentrations of FITC-Aβ 42 were higher in mice that had been fed antibiotics to alter their GM than in normal mice. However, the FITC-Aβ 42 concentrations in blood showed the opposite pattern. CONCLUSION: Aβ 42 can be excreted into the intestinal lumen and is regulated by the GM.

High Soluble Amyloid-β42 Predicts Normal Cognition in Amyloid-Positive Individuals with Alzheimer's Disease-Causing Mutations. - Sturchio, Andrea; Dwivedi, Alok K; Malm, Tarja; Wood, Matthew J A; Cilia, Roberto; Sharma, Jennifer S; Hill, Emily J; Schneider, Lon S; Graff-Radford, Neill R; Mori, Hiroshi; Nübling, Georg; El Andaloussi, Samir; et al. (J Alzheimers Dis, 2022)
BACKGROUND: In amyloid-positive individuals at risk for Alzheimer's disease (AD), high soluble 42-amino acid amyloid-β (Aβ42) levels are associated with normal cognition. It is unknown if this relationship applies longitudinally in a genetic cohort. OBJECTIVE: To test the hypothesis that high Aβ42 preserves normal cognition in amyloid-positive individuals with Alzheimer's disease (AD)-causing mutations (APP, PSEN1, or PSEN2) to a greater extent than lower levels of brain amyloid, cerebrospinal fluid (CSF) phosphorylated tau (p-tau), or total tau (t-tau). METHODS: Cognitive progression was defined as any increase in Clinical Dementia Rating (CDR = 0, normal cognition; 0.5, very mild dementia; 1, mild dementia) over 3 years. Amyloid-positivity was defined as a standard uptake value ratio (SUVR) ≥1.42 by Pittsburgh compound-B positron emission tomography (PiB-PET). We used modified Poisson regression models to estimate relative risk (RR), adjusted for age at onset, sex, education, APOE4 status, and duration of follow-up. The results were confirmed with multiple sensitivity analyses, including Cox regression. RESULTS: Of 232 mutation carriers, 108 were PiB-PET-positive at baseline, with 43 (39.8% ) meeting criteria for progression after 3.3±2.0 years. Soluble Aβ42 levels were higher among CDR non-progressors than CDR progressors. Higher Aβ42 predicted a lower risk of progression (adjusted RR, 0.36; 95% confidence interval [CI], 0.19-0.67; p = 0.002) better than lower SUVR (RR, 0.81; 95% CI, 0.68-0.96; p = 0.018). CSF Aβ42 levels predicting lower risk of progression increased with higher SUVR levels. CONCLUSION: High CSF Aβ42 levels predict normal cognition in amyloid-positive individuals with AD-causing genetic mutations.

HMGCS2-Induced Autophagic Degradation of Tau Involves Ketone Body and ANKRD24. - Hu, Li-Tian; Xie, Xiao-Yong; Zhou, Gui-Feng; Wen, Qi-Xin; Song, Li; Luo, Biao; Deng, Xiao-Juan; Pan, Qiu-Ling; Chen, Guo-Jun (J Alzheimers Dis, 2022)
BACKGROUND: Accumulation of hyperphosphorylated Tau (pTau) contributes to the formation of neurofibrillary tangles in Alzheimer's disease (AD), and targeting Tau/pTau metabolism has emerged as a therapeutic approach. We have previously reported that mitochondrial 3-hydroxy-3-methylglutaryl-COA synthase 2 (HMGCS2) is involved in AD by promoting autophagic clearance of amyloid-β protein precursor via ketone body-associated mechanism, whether HMGCS2 may also regulate Tau metabolism remains elusive. OBJECTIVE: The present study was to investigate the role of HMGCS2 in Tau/p degradation. METHODS: The protein levels of Tau and pTau including pT217 and pT181, as well as autophagic markers LAMP1 and LC3-II were assessed by western blotting. The differentially regulated genes by HMGCS2 were analyzed by RNA sequencing. Autophagosomes were assessed by transmission electron microscopy. RESULTS: HMGCS2 significantly decreased Tau/pTau levels, which was paralleled by enhanced formation of autophagic vacuoles and prevented by autophagic regulators chloroquine, bafilomycin A1, 3-methyladenine, and rapamycin. Moreover, HMGCS2-induced alterations of LAMP1/LC3-II and Tau/pTau levels were mimicked by ketone body acetoacetate or β-hydroxybutyrate. Further RNA-sequencing identified ankyrin repeat domain 24 (ANKRD24) as a target gene of HMGCS2, and silencing of ANKRD24 reduced LAMP1/LC3-II levels, which was accompanied by the altered formation of autophagic vacuoles, and diminished the effect of HMGCS2 on Tau/pTau. CONCLUSION: HMGCS2 promoted autophagic clearance of Tau/pTau, in which ketone body and ANKRD24 played an important role.

Improved Alzheimer's Disease versus Frontotemporal Lobar Degeneration Differential Diagnosis Combining EEG and Neurochemical Biomarkers: A Pilot Study. - Laton, Jorne; Van Schependom, Jeroen; Goossens, Joery; Wiels, Wietse; Sieben, Anne; De Deyn, Peter Paul; Goeman, Johan; Streffer, Johannes; van der Zee, Julie; Martin, Jean-Jacques; Van Broeckhoven, Christine; De Vos, Maarten; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Distinguishing between Alzheimer's disease (AD) and frontotemporal lobar degeneration (FTLD) results in poor diagnostic accuracy. OBJECTIVE: To investigate the utility of electroencephalography (EEG)-based biomarkers in comparison and in addition to established cerebrospinal fluid (CSF) biomarkers in the AD versus FTLD differential diagnosis. METHODS: The study cohort comprised 37 AD and 30 FTLD patients, of which 17 AD and 9 FTLD patients had definite diagnoses. All participants had CSF neurochemical (NCM) biomarker analyses (Aβ1-42, T-tau, P-tau181, and Nf-L) and underwent 19-channel resting-state EEG. From the EEG spectra, dominant frequency peaks were extracted in four regions resulting in four dominant frequencies. This produced eight features (4 NCM + 4 EEG). RESULTS: When NCM and EEG markers were combined, the diagnostic accuracy increased significantly. In the whole group, the accuracy went up from 79% (NCM) to almost 82%, while in the definite group only, it went up from around 85% to almost 95% . Two differences in the occurrence of the dominant EEG frequency were discovered: people lacking a clear dominant peak almost all had definite AD, while people with two peaks more often had FTLD. CONCLUSION: Combining EEG with NCM biomarkers resulted in differential diagnostic accuracies of 82% in clinically diagnosed AD and FTD patients and of 95% in patients having a definite diagnosis, which was significantly better than with EEG or NCM biomarkers alone. This suggests that NCM and EEG markers are complementary, revealing different aspects of the disease and therefore confirms again their relevance in developing additional diagnosis tools.

Improved Prediction of Amyloid-β and Tau Burden Using Hippocampal Surface Multivariate Morphometry Statistics and Sparse Coding. - Wu, Jianfeng; Su, Yi; Zhu, Wenhui; Jalili Mallak, Negar; Lepore, Natasha; Reiman, Eric M; Caselli, Richard J; Thompson, Paul M; Chen, Kewei; Wang, Yalin (J Alzheimers Dis, 2022)
BACKGROUND: Amyloid-β (Aβ) plaques and tau protein tangles in the brain are the defining 'A' and 'T' hallmarks of Alzheimer's disease (AD), and together with structural atrophy detectable on brain magnetic resonance imaging (MRI) scans as one of the neurodegenerative ('N') biomarkers comprise the "ATN framework" of AD. Current methods to detect Aβ/tau pathology include cerebrospinal fluid (invasive), positron emission tomography (PET; costly and not widely available), and blood-based biomarkers (promising but mainly still in development). OBJECTIVE: To develop a non-invasive and widely available structural MRI-based framework to quantitatively predict the amyloid and tau measurements. METHODS: With MRI-based hippocampal multivariate morphometry statistics (MMS) features, we apply our Patch Analysis-based Surface Correntropy-induced Sparse coding and max-pooling (PASCS-MP) method combined with the ridge regression model to individual amyloid/tau measure prediction. RESULTS: We evaluate our framework on amyloid PET/MRI and tau PET/MRI datasets from the Alzheimer's Disease Neuroimaging Initiative. Each subject has one pair consisting of a PET image and MRI scan, collected at about the same time. Experimental results suggest that amyloid/tau measurements predicted with our PASCP-MP representations are closer to the real values than the measures derived from other approaches, such as hippocampal surface area, volume, and shape morphometry features based on spherical harmonics. CONCLUSION: The MMS-based PASCP-MP is an efficient tool that can bridge hippocampal atrophy with amyloid and tau pathology and thus help assess disease burden, progression, and treatment effects.

Insulin-Like Growth Factor, Inflammation, and MRI Markers of Alzheimer's Disease in Predominantly Middle-Aged Adults. - Wittfeld, Katharina; Raman, Mekala R; Conner, Sarah C; Aslam, Asra; Teumer, Alexander; Nauck, Matthias; Hosten, Norbert; Habes, Mohamad; DeCarli, Charles; Vasan, Ramachandran S; Beiser, Alexa S; Himali, Jayandra J; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Insulin-like growth factor 1 (IGF-1) signaling has been implicated in Alzheimer's disease pathogenesis, and further evidence suggests inflammation can be a moderator of this association. However, most research to date has been conducted on older adults. OBJECTIVE: To investigate the association of serum IGF-1 and IGF binding protein 3 (IGFBP-3) concentrations with MRI markers of Alzheimer's disease in predominantly middle-aged adults, and further assess moderation by chronic inflammation. METHODS: We included participants from the Framingham Heart Study (n = 1,852, mean age 46±8, 46% men) and the Study of Health in Pomerania (n = 674, mean age 50±13, 42% men) with available serum IGF-1, IFGBP-3, as well as brain MRI. IGF-1 and IFGBP-3 were related to MRI outcomes (i.e., total brain, cortical gray matter, white matter, white matter hyperintensities (WMH), and hippocampal volumes) using multivariable regression models adjusting for potential confounders. Subgroup analyses by C-reactive protein (CRP) concentrations were also performed. Cohort-specific summary statistics were meta-analyzed using random-effects models and corrected for multiple comparisons. RESULTS: Meta-analysis results revealed that higher IGF-1 concentrations were associated with lower WMH (estimate [β] [95% CI], -0.05 [-0.09, -0.02], p = 0.006) and larger hippocampal volumes (0.07 [0.02, 0.12], p = 0.01), independent of vascular risk factors. These associations occurred predominantly in individuals with CRP concentrations < 75th percentile. We did not observe associations between IGFBP-3 and MRI outcomes. CONCLUSION: Our findings suggest that IGF-1-related signaling may be implicated in brain health as early as midlife.

Lipid Peroxidation as a Marker of Apathy and Executive Dysfunction in Patients at Risk for Vascular Cognitive Impairment. - Bawa, Kritleen K; Ba, Joycelyn; Kiss, Alex; Wang, RuoDing; Feng, Vivian; Swardfager, Walter; Andreazza, Ana; Gallagher, Damien; Marotta, Giovanni; Herrmann, Nathan; Lanctôt, Krista L (J Alzheimers Dis, 2022)
BACKGROUND: The co-occurrence of apathy and executive dysfunction, a correlate of vascular cognitive impairment (VCI), is highly prevalent, yet facilitating factors are largely unknown. OBJECTIVE: This study investigates the relationship between lipid peroxidation, apathy, and executive dysfunction in patients at risk for VCI. METHODS: In participants with coronary artery disease, who are at a high risk of VCI, apathy (Apathy Evaluation Scale), and executive function (composite z-score based on age and education population norms from trails making test B, animal naming, and phonemic fluency tests) were assessed. Serum concentrations of an early (lipid hydroperoxide (LPH)) and late (8-isoprostane (8-ISO)) lipid peroxidation marker, were measured and the 8-ISO/LPH ratio was calculated. RESULTS: Participants (n = 206, age±SD = 63.0±7.5, 80% men, total years of education = 15.9±3.4, AES score = 28.3±8.8, executive function = 0±1) demonstrated significantly different 8-ISO/LPH ratios between groups (F(3, 202) = 10.915, p <  0.001) with increasing levels in the following order: no apathy or executive dysfunction, only executive dysfunction (executive function composite score≤-1), only apathy (AES≥28), and both apathy and executive dysfunction. A model adjusting for demographics showed that lipid peroxidation was associated with both apathy (B(SE) = 4.63 (0.954), t = 4.852, p <  0.001) and executive function (B(SE) = -0.19 (0.079), t = -2.377, p = 0.018). However, when controlling for both demographics and vascular risk factors, lipid peroxidation was associated with only apathy (B(SE) = 3.11 (0.987), t = 3.149, p = 0.002). CONCLUSION: The results highlight a potentially important involvement of lipid peroxidation in the co-occurrence of apathy and executive dysfunction in those at risk for VCI.

Lipid Rafts Act as a Common Platform for Amyloid-β Oligomer-Induced Alzheimer's Disease Pathology. - Kawarabayashi, Takeshi; Nakamura, Takumi; Sato, Kaoru; Seino, Yusuke; Ichii, Sadanobu; Nakahata, Naoko; Takatama, Masamitsu; Westaway, David; George-Hyslop, Peter St; Shoji, Mikio (J Alzheimers Dis, 2022)
BACKGROUND: Amyloid-β (Aβ) oligomers induce the overproduction of phosphorylated tau and neurodegeneration. These cascades gradually cause cognitive impairment in Alzheimer's disease (AD). While each pathological event in AD has been studied in detail separately, the spatial and temporal relationships between pathological events in AD remain unclear. OBJECTIVE: We demonstrated that lipid rafts function as a common platform for the pathological cascades of AD. METHODS: Cellular and synaptosomal lipid rafts were prepared from the brains of Aβ amyloid model mice (Tg2576 mice) and double transgenic mice (Tg2576 x TgTauP301L mice) and longitudinally analyzed. RESULTS: Aβ dimers, the cellular prion protein (PrPc), and Aβ dimer/PrPc complexes were detected in the lipid rafts. The levels of Fyn, the phosphorylated NR2B subunit of the N-methyl-D-aspartate receptor, glycogen synthase kinase 3β, total tau, phosphorylated tau, and tau oligomers increased with Aβ dimer accumulation in both the cellular and synaptosomal lipid rafts. Increases in the levels of these molecules were first seen at 6 months of age and corresponded with the early stages of Aβ accumulation in the amyloid model mice. CONCLUSION: Lipid rafts act as a common platform for the progression of AD pathology. The findings of this study suggest a novel therapeutic approach to AD, involving the modification of lipid raft components and the inhibition of their roles in the sequential pathological events of AD.

Medial Temporal Atrophy in Posterior Cortical Atrophy and Its Relationship to the Cingulate Island Sign. - Josephs, Kennedy A; Pham, Nha Trang Thu; Graff-Radford, Jonathan; Machulda, Mary M; Lowe, Val J; Whitwell, Jennifer L (J Alzheimers Dis, 2022)
BACKGROUND: It has been hypothesized that medial temporal sparing may be related to preserved posterior cingulate metabolism and the cingulate island sign (CIS) on [18F]fluorodeoxyglucose (FDG) PET in posterior cortical atrophy (PCA). OBJECTIVE: To assess the severity of medial temporal atrophy in PCA and determine whether the presence of a CIS is related to medial temporal sparing. METHODS: Fifty-five PCA patients underwent MRI and FDG-PET. The degree and symmetry of medial temporal atrophy on MRI was visually assessed using a five-point scale for both hemispheres. Visual assessments of FDG-PET coded the presence/absence of a CIS and whether the CIS was symmetric or asymmetric. Hippocampal volumes and a quantitative CIS were also measured. RESULTS: Medial temporal atrophy was most commonly mild or moderate, was symmetric in 55% of patients, and when asymmetric was most commonly worse on the right (76%). Older age and worse memory performance were associated with greater medial temporal atrophy. The CIS was observed in 44% of the PCA patients and was asymmetric in 50% of these. The patients with a CIS showed greater medial temporal asymmetry, but did not show lower medial temporal atrophy scores, compared to those without a CIS. Hippocampal volumes were not associated with quantitative CIS. CONCLUSION: Mild medial temporal atrophy is a common finding in PCA and is associated with memory impairment. However, medial temporal sparing was not related to the presence of a CIS in PCA.
Keywords: Alzheimer Disease; Atrophy; Fluorodeoxyglucose F18; Humans; Lewy Body Disease; Magnetic Resonance Imaging; Positron-Emission Tomography

A Mitochondrial DNA Haplogroup Defines Patterns of Five-Year Cognitive Change. - Watts, Amber; Chalise, Prabhakar; Hu, Jinxiang; Hui, Dongwei; Pa, Judy; Andrews, Shea J; Michaelis, Elias K; Swerdlow, Russell H (J Alzheimers Dis, 2022)
BACKGROUND: Mitochondrial DNA (mtDNA) may play a role in Alzheimer's disease (AD) and cognitive decline. A particular haplogroup of mtDNA, haplogroup J, has been observed more commonly in patients with AD than in cognitively normal controls. OBJECTIVE: We used two mtDNA haplogroups, H and J, to predict change in cognitive performance over five years. We hypothesized that haplogroup J carriers would show less cognitive resilience. METHODS: We analyzed data from 140 cognitively normal older adults who participated in the University of Kansas Alzheimer's Disease Research Center clinical cohort between 2011 and 2020. We used factor analysis to create three composite scores (verbal memory, attention, and executive function) from 11 individual cognitive tests. We performed latent growth curve modeling to describe trajectories of cognitive performance and change adjusting for age, sex, years of education, and APOE ɛ4 allele carrier status. We compared haplogroup H, the most common group, to haplogroup J, the potential risk group. RESULTS: Haplogroup J carriers had significantly lower baseline performance and slower rates of improvement on tests of verbal memory compared to haplogroup H carriers. We did not observe differences in executive function or attention. CONCLUSION: Our results reinforce the role of mtDNA in changes to cognitive function in a domain associated with risk for dementia, verbal memory, but not with other cognitive domains. Future research should investigate the distinct mechanisms by which mtDNA might affect performance on verbal memory as compared to other cognitive domains across haplogroups.

Mitochondrial Targeting of Amyloid-β Protein Precursor Intracellular Domain Induces Hippocampal Cell Death via a Mechanism Distinct from Amyloid-β. - Sandberg, Alexandra A; Manning, Evan; Wilkins, Heather M; Mazzarino, Randall; Minckley, Taylor; Swerdlow, Russell H; Patterson, David; Qin, Yan; Linseman, Daniel A (J Alzheimers Dis, 2022)
BACKGROUND: Amyloid-β (Aβ) is a principal cleavage product of amyloid-β protein precursor (AβPP) and is widely recognized as a key pathogenic player in Alzheimer's disease (AD). Yet, there is increasing evidence of a neurotoxic role for the AβPP intracellular domain (AICD) which has been proposed to occur through its nuclear function. Intriguingly, there is a γ-secretase resident at the mitochondria which could produce AICD locally. OBJECTIVE: We examined the potential of AICD to induce neuronal apoptosis when targeted specifically to the mitochondria and compared its mechanism of neurotoxicity to that of Aβ. METHODS: We utilized transient transfection of HT22 neuronal cells with bicistronic plasmids coding for DsRed and either empty vector (Ires), Aβ, AICD59, or mitochondrial-targeted AICD (mitoAICD) in combination with various inhibitors of pathways involved in apoptosis. RESULTS: AICD induced significant neuronal apoptosis only when targeted to the mitochondria. Apoptosis required functional mitochondria as neither Aβ nor mitoAICD induced significant toxicity in cells devoid of mitochondrial DNA. Both glutathione and a Bax inhibitor protected HT22 cells from either peptide. However, inhibition of the mitochondrial permeability transition pore only protected from Aβ, while pan-caspase inhibitors uniquely rescued cells from mitoAICD. CONCLUSION: Our results show that AICD displays a novel neurotoxic function when targeted to mitochondria. Moreover, mitoAICD induces apoptosis via a mechanism that is distinct from that of Aβ. These findings suggest that AICD produced locally at mitochondria via organelle-specific γ-secretase could act in a synergistic manner with Aβ to cause mitochondrial dysfunction and neuronal death in AD.

Non-Alcoholic Fatty Liver Disease, Liver Fibrosis, and Regional Amyloid-β and Tau Pathology in Middle-Aged Adults: The Framingham Study. - Weinstein, Galit; O'Donnell, Adrienne; Davis-Plourde, Kendra; Zelber-Sagi, Shira; Ghosh, Saptaparni; DeCarli, Charles S; Thibault, Emma G; Sperling, Reisa A; Johnson, Keith A; Beiser, Alexa S; Seshadri, Sudha (J Alzheimers Dis, 2022)
BACKGROUND: Liver steatosis and fibrosis are emerging as risk factors for multiple extrahepatic health conditions; however, their relationship with Alzheimer's disease pathology is unclear. OBJECTIVE: To examine whether non-alcoholic fatty liver disease (NAFLD) and FIB-4, a non-invasive index of advanced fibrosis, are associated with brain amyloid-β (Aβ) and tau pathology. METHODS: The study sample included Framingham Study participants from the Offspring and Third generation cohorts who attended exams 9 (2011-2014) and 2 (2008-2011), respectively. Participants underwent 11C-Pittsburgh Compound-B amyloid and 18F-Flortaucipir tau positron emission tomography (PET) imaging and abdomen computed tomography, or had information on all components of the FIB-4 index. Linear regression models were used to assess the relationship of NAFLD and FIB-4 with regional tau and Aβ, adjusting for potential confounders and multiple comparisons. RESULTS: Of the subsample with NAFLD information (N = 169; mean age 52±9 y; 57% males), 57 (34%) had NAFLD. Of the subsample with information on liver fibrosis (N = 177; mean age 50±10 y; 51% males), 34 (19%) had advanced fibrosis (FIB-4 >  1.3). Prevalent NAFLD was not associated with Aβ or tau PET. However, FIB-4 index was significantly associated with increased rhinal tau (β= 1.03±0.33, p = 0.002). Among individuals with prevalent NAFLD, FIB-4 was related to inferior temporal, parahippocampal gyrus, entorhinal and rhinal tau (β= 2.01±0.47, p <  0.001; β= 1.60±0.53, p = 0.007, and β= 1.59±0.47, p = 0.003 and β= 1.60±0.42, p = 0.001, respectively) and to Aβ deposition overall and in the inferior temporal and parahippocampal regions (β= 1.93±0.47, p <  0.001; β= 1.59±0.38, p <  0.001, and β= 1.52±0.54, p = 0.008, respectively). CONCLUSION: This study suggests a possible association between liver fibrosis and early Alzheimer's disease pathology, independently of cardio-metabolic risk factors.

Peptidylarginine Deiminase and Alzheimer's Disease. - Wang, Lai; Chen, Hongyang; Tang, Jing; Guo, Zhengwei; Wang, Yanming (J Alzheimers Dis, 2022)
Peptidylarginine deiminases (PADs) are indispensable enzymes for post-translational modification of proteins, which can convert Arg residues on the surface of proteins to citrulline residues. The PAD family has five isozymes, PAD1, 2, 3, 4, and 6, which have been found in multiple tissues and organs. PAD2 and PAD4 were detected in cerebral cortex and hippocampus from human and rodent brain. In the central nervous system, abnormal expression and activation of PADs are involved in the pathological changes and pathogenesis of Alzheimer's disease (AD). This article reviews the classification, distribution, and function of PADs, with an emphasis on the relationship between the abnormal activation of PADs and AD pathogenesis, diagnosis, and the therapeutic potential of PADs as drug targets for AD.
Keywords: Alzheimer Disease; Animals; Cerebral Cortex; Citrulline; Hippocampus; Humans; Isoenzymes; Protein Processing, Post-Translational; Protein-Arginine Deiminases

Perivascular Space Predicts Brain Hypometabolism of Individuals with Underlying Amyloid Pathology. - Shi, Xiaolei; Zhou, Nan; Sun, Bin; Wu, Yongshun; Hu, Yachun; Ning, Yuping (J Alzheimers Dis, 2022)
BACKGROUND: Reduced signal on fluorodeoxyglucose-positron emission tomography (FDG-PET) is a valid proxy for neurodegeneration in Alzheimer's disease (AD). Perivascular space (PVS) is believed to be associated with AD pathology and cognitive decline. OBJECTIVE: This study aimed to investigate the associations of PVS with FDG-PET and cognitive performance based on the burden of amyloid pathology. METHODS: We used magnetic resonance imaging (MRI) data from the Alzheimer's Disease Neuroimaging Initiative (ADNI). MRI-visible PVS in basal ganglia (BG) and centrum semi-oval (CSO) were visually classified as: none/mild, moderate or frequent/severe. The association of PVS with brain FDG-PET was explored based on the burden of amyloid pathology, where a cerebrospinal fluid (CSF) t-tau/Aβ42 with the ratio≥0.27 was defined as high amyloid pathology. Moreover, the relationships between PVS and cognitive performance variables (ADNI-MEM and ADNI-EF) were studied. RESULTS: For participants with higher tau/Aβ42 ratio, CSO-PVS severity was independently associated with lower FDG-PET. There were significant interaction effects between moderate or frequent/severe CSO-PVS and time on FDG decline in people with high amyloid pathology. The interaction between CSO-PVS and time (follow-up) was consistently associated with ADNI-MEM and ADNI-EF decline in individuals with high amyloid pathology. CONCLUSION: The study established the differential utility of PVS in BG and CSO for predicting brain metabolism. These findings suggest that CSO-PVS serves as a contributing factor to brain metabolism and cognitive decline associated with amyloid pathology.

Plasma Cholesterol Levels as Potential Nutritional Biomarkers for Lewy Body Dementia. - Dou, Yuchao; Liu, Shuai; Li, Yuqing; Wu, Hao; Chen, Hui; Ji, Yong (J Alzheimers Dis, 2022)
BACKGROUND: The relationship between cholesterol level and the risk of developing Alzheimer's disease has been well established, but the relationship between cholesterol level and Lewy body dementia (LBD) is still not well known. OBJECTIVE: The aim of this case-control study was to explore the association between blood cholesterol levels and LBD in Chinese older adults. METHODS: A total of 65 patients with LBD and 110 older adult controls were enrolled during the study period. The levels of triglyceride, total cholesterol, low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and fasting glucose were measured separately. The associations between LBD, blood cholesterol levels, and fasting glucose levels were assessed using multiple binary logistic regression analyses adjusted for multiple covariates. RESULTS: Increased plasma LDL-C levels and lower HDL-C levels were independently associated with the risk of LBD in models adjusted for age, sex, education, alcohol use status, smoking status, and vascular disorders. Higher fasting glucose levels may be associated with the risk of LBD. CONCLUSION: The results of this study suggest that elevated levels of LDL-C and reduced levels of HDL-C were associated with LBD development and therefore are potential nutritional risk factors for LBD. Adjusting diet and individualized and effective cholesterol-lowering therapy in high-risk adults may aid in the prevention or management of LBD.

Plasma Myeloperoxidase as a Potential Biomarker of Patient Response to Anti-Dementia Treatment in Alzheimer's Disease. - Wright, Joy R; Deen, Quazi Fahm E; Stevenson, Anna; Telford-Cooke, Leolie; Parker, Craig; Martin-Ruiz, Carmen; Steinert, Joern R; Kalaria, Raj N; Mukaetova-Ladinska, Elizabeta B (J Alzheimers Dis, 2022)
BACKGROUND: Myeloperoxidase (MPO), a neutrophil-derived pro-inflammatory protein, co-localizes with amyloid-β (Aβ) plaques in Alzheimer's disease (AD). Anti-dementia treatment may facilitate efflux of Aβ and associated plaque proteins from the brain to the peripheral circulation, therefore providing potential biomarkers for the monitoring of donor response to drug treatment. OBJECTIVE: We investigated the diagnostic utility of MPO as a biomarker of AD, and how anti-dementia treatment alters plasma MPO concentration. METHODS: Thirty-two AD patients were recruited, and plasma collected pre-drug administration (baseline), and 1- and 6-months post-treatment. All patients received cholinesterase inhibitors (ChEIs). At baseline and 6 months, patients underwent neuropsychological assessment. Forty-nine elderly healthy individuals with normal cognitive status served as controls. Plasma MPO concentration was measured by ELISA. RESULTS: AD drug naïve patients had similar plasma MPO concentration to their control counterparts (p >  0.05). Baseline MPO levels positively correlated with Neuropsychiatric Inventory score (r = 0.5080; p = 0.011) and carer distress (r = 0.5022; p = 0.012). Following 1-month ChEI treatment, 84.4% of AD patients exhibited increased plasma MPO levels (p <  0.001), which decreased at 6 months (p <  0.001). MPO concentration at 1 month was greatest in AD patients whose memory deteriorated during the study period (p = 0.028), and for AD patients with deterioration in Cornell assessment score (p = 0.044). CONCLUSION: Whereas baseline MPO levels did not differentiate between healthy and AD populations, baseline MPO positively correlated with initial Neuropsychiatric Inventory evaluation. Post-treatment, transient MPO upregulation in ChEI-treated patients may reflect worse therapeutic outcome. Further studies are required to assess the potential of plasma MPO as an AD therapeutic biomarker.

Post-Stroke Cognitive Impairment: Epidemiology, Risk Factors, and Management. - Huang, Yu-Yuan; Chen, Shi-Dong; Leng, Xin-Yi; Kuo, Kevin; Wang, Zuo-Teng; Cui, Mei; Tan, Lan; Wang, Kai; Dong, Qiang; Yu, Jin-Tai (J Alzheimers Dis, 2022)
Stroke, characterized as a neurological deficit of cerebrovascular cause, is very common in older adults. Increasing evidence suggests stroke contributes to the risk and severity of cognitive impairment. People with cognitive impairment following stroke often face with quality-of-life issues and require ongoing support, which have a profound effect on caregivers and society. The high morbidity of post-stroke cognitive impairment (PSCI) demands effective management strategies, in which preventive strategies are more appealing, especially those targeting towards modifiable risk factors. In this review article, we attempt to summarize existing evidence and knowledge gaps on PSCI: elaborating on the heterogeneity in current definitions, reporting the inconsistent findings in PSCI prevalence in the literature, exploring established or less established predictors, outlining prevention and treatment strategies potentially effective or currently being tested, and proposing promising directions for future research.
Keywords: Aged; Cognitive Dysfunction; Humans; Prevalence; Risk Factors; Stroke

Prevalence of Depressive Symptoms in a Memory Clinic Cohort: A Retrospective Study. - Loreto, Flavia; Fitzgerald, Anna; Golemme, Mara; Gunning, Stephen; Win, Zarni; Patel, Neva; Carswell, Christopher; Perry, Richard; Kennedy, Angus; Edison, Paul; Malhotra, Paresh (J Alzheimers Dis, 2022)
BACKGROUND: Depression has been suggested to be a cause of reversible cognitive impairment but also a risk factor for neurodegenerative disease. Studies suggest that depression prevalence may be high in early onset dementia, particularly Alzheimer's disease, but this has not been systematically assessed in a biomarker-validated clinical dementia cohort to date. OBJECTIVE: To examine the prevalence, features, and association with amyloid pathology of lifetime depressive symptoms in a memory clinic cohort meeting appropriate use criteria for amyloid PET imaging. METHODS: We included 300 patients from a single-center memory clinic cohort that received diagnostic biomarker evaluation with amyloid PET imaging according to appropriate use criteria. History of lifetime depressive symptoms was retrospectively assessed through structured review of clinical correspondence. RESULTS: One hundred forty-two (47%) patients had a history of significant depressive symptoms ('D+'). Of these, 89% had ongoing symptoms and 60% were on antidepressants at the time of presentation to our Clinic. Depressive symptoms were equally highly prevalent in the amyloid-positive and the heterogeneous group of amyloid-negative patients. CONCLUSION: Approximately half of patients who meet appropriate use criteria for amyloid PET had a history of depressive symptoms. We suggest that depression is an important feature of both neurodegenerative and non-neurodegenerative cognitive impairment and may contribute to the diagnostic uncertainty behind referral to amyloid PET.

Psychosis as a Treatment Target in Dementia: A Roadmap for Designing Interventions. - Agüera-Ortiz, Luis; Babulal, Ganesh M; Bruneau, Marie-Andrée; Creese, Byron; D'Antonio, Fabrizia; Fischer, Corinne E; Gatchel, Jennifer R; Ismail, Zahinoor; Kumar, Sanjeev; McGeown, William J; Mortby, Moyra E; Nuñez, Nicolas A; et al. (J Alzheimers Dis, 2022)
Psychotic phenomena are among the most severe and disruptive symptoms of dementias and appear in 30% to 50% of patients. They are associated with a worse evolution and great suffering to patients and caregivers. Their current treatments obtain limited results and are not free of adverse effects, which are sometimes serious. It is therefore crucial to develop new treatments that can improve this situation. We review available data that could enlighten the future design of clinical trials with psychosis in dementia as main target. Along with an explanation of its prevalence in the common diseases that cause dementia, we present proposals aimed at improving the definition of symptoms and what should be included and excluded in clinical trials. A review of the available information regarding the neurobiological basis of symptoms, in terms of pathology, neuroimaging, and genomics, is provided as a guide towards new therapeutic targets. The correct evaluation of symptoms is transcendental in any therapeutic trial and these aspects are extensively addressed. Finally, a critical overview of existing pharmacological and non-pharmacological treatments is made, revealing the unmet needs, in terms of efficacy and safety. Our work emphasizes the need for better definition and measurement of psychotic symptoms in dementias in order to highlight their differences with symptoms that appear in non-dementing diseases such as schizophrenia. Advances in neurobiology should illuminate the development of new, more effective and safer molecules for which this review can serve as a roadmap in the design of future clinical trials.
Keywords: Caregivers; Dementia; Hallucinations; Humans; Psychotic Disorders; Schizophrenia

The Relationship Between Prior Cancer Diagnosis and All-Cause Dementia Progression Among US Adults. - Fowler, Mackenzie E; Wright, Nicole C; Triebel, Kristen; Rocque, Gabrielle B; Irvin, Ryan; Kennedy, Richard E (J Alzheimers Dis, 2022)
BACKGROUND: Cancer-related cognitive impairment (CRCI), a frequent effect of cancer and its treatments, shares common cognitive symptoms with dementia syndromes. Cross-sectional studies demonstrate an inverse relationship between cancer and dementia. However, the longitudinal relationship between dementia decline and cancer has not been investigated. OBJECTIVE: To evaluate the association between cancer and longitudinal progression of dementia. METHODS: We extracted electronic health record data from July 2003 to February 2020 from a single academic medical center. We identified dementia and cancer history prior to dementia using ICD-9/10 codes. We measured cognitive decline with the Alabama Brief Cognitive Screener (ABCs). We used adjusted linear mixed models to estimate baseline cognition and rate of progression by cancer history, including differences by race. RESULTS: The study included 3,809 participants with dementia, of which 672 (17.6%) had cancer history. Those with cancer history had higher baseline cognition (β: 0.62, 95% CI: -0.02-1.25), but similar rate of decline. Non-Hispanic Blacks had lower cognitive scores at baseline and throughout follow-up regardless of cancer status compared to non-Hispanic Whites and other races/ethnicities with and without cancer history. CONCLUSION: In this longitudinal retrospective study, participants with cancer history demonstrate better cognition at dementia diagnosis and no difference in cognitive decline than those without cancer history. Smoking and comorbidities attenuate this association and results indicate non-Hispanic Blacks have worse cognitive outcomes in dementia regardless of cancer history than other race/ethnicity groups. Further exploration of the role of smoking, comorbidities, and race/ethnicity on cancer and dementia-related cognitive decline is needed.

Risk of Dementia in Cancer Survivors: A Meta-Analysis of Population-Based Cohort Studies. - Zhang, Dan-Dan; Ou, Ya-Nan; Fu, Yan; Wang, Zhi-Bo; Huang, Liang-Yu; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2022)
BACKGROUND: A negative association between cancer and Alzheimer's disease (AD) was revealed. OBJECTIVE: We aimed to further explore the dementia risk among cancer survivors and then among cancer survivors who received cancer treatment in subsequent subgroup analyses. METHODS: Databases of PubMed, Embase, and Cochrane Library were systematically searched from inception to April 1, 2021, following PRISMA and MOOSE guidelines. Relative risks (RR) of dementia were pooled by a random-effects model stratifying the data by potential confounding factors to explore the heterogeneity. This study is registered with PROSPERO, number CRD42021250654. RESULTS: A total of 36 studies were included in this meta-analysis, of which 16 studies were about the risk of dementia in cancer survivors, and 20 studies were about the risk of dementia in survivors who accepted cancer treatment. The pooled RR reached 0.89 ([95% CI = 0.82-0.97], I2 = 97.9%) for dementia and 0.89 ([0.83-0.95], I2 = 92.6%) for AD in cancer survivors compared with non-cancer controls. Notably, both dementia risk and AD risk significantly decreased in survivors of colon, leukemia, small intestine, and thyroid cancers (RR ranged from 0.64 to 0.92). Furthermore, prostate cancer patients treated with androgen deprivation therapy exhibited a significantly increased risk of dementia (RR:1.18 [1.09-1.27], I2 = 89.5%) and AD (RR:1.17 [1.08-1.25], I2 = 81.3%), with evidence of between-study heterogeneity. CONCLUSION: Currently, available evidence suggests that the risk of dementia among cancer survivors is decreased. However, large-scale prospective cohort studies are warranted to further prove the association.

Safety, Tolerability, Pharmacokinetics, and Pharmacodynamics of the Positive Modulator of HGF/MET, Fosgonimeton, in Healthy Volunteers and Subjects with Alzheimer's Disease: Randomized, Placebo-Controlled, Double-Blind, Phase I Clinical Trial. - Hua, Xue; Church, Kevin; Walker, William; L'Hostis, Philippe; Viardot, Geoffrey; Danjou, Philippe; Hendrix, Suzanne; Moebius, Hans J (J Alzheimers Dis, 2022)
BACKGROUND: Fosgonimeton (ATH-1017) is being developed as a first-in-class regenerative therapy for people with Alzheimer's disease (AD) and dementia; potentially improving dementia symptoms and altering disease progression by reversing synaptic disconnection and neuronal loss. OBJECTIVE: This randomized, double-blind, placebo-controlled phase I trial (NCT03298672) evaluated the safety, tolerability, pharmacokinetics, and pharmacodynamics of fosgonimeton. METHODS: Fosgonimeton was administered once daily via subcutaneous injection to 88 subjects. The single ascending dose study enrolled healthy young male subjects (n = 48; age, 33.4±6.3 years; dose, 2, 6, 20, 40, 60, or 90 mg); the multiple ascending dose study enrolled healthy elderly subjects (n = 29; age, 63.8±4.0 years; dose, 20, 40, 60, or 80 mg; 9-day duration); and the fixed-dose study enrolled AD subjects (n = 11; age, 69.2±7.1 years; dose, 40 mg; 9-day duration). Quantitative electroencephalogram (qEEG) and event-related potential (ERP) P300 measured neurophysiological signals following fosgonimeton treatment, supporting brain penetration and target engagement. RESULTS: Fosgonimeton and placebo were shown to be safe and well-tolerated across all doses. Pharmacokinetic results for fosgonimeton were dose-proportional, with no sex effect or accumulation over 9 days. The main effect of fosgonimeton on qEEG was acute and sustained gamma power induction. In AD subjects, there was a significant effect toward ERP P300 latency normalization compared with placebo (p = 0.027; n = 7 at 40 mg fosgonimeton versus n = 4 placebo). CONCLUSION: These results support the continued development of fosgonimeton as a novel therapeutic for people with AD and dementia. The fast-onset normalization of ERP P300 latency in AD subjects suggests enhancement of synaptic function and potential procognitive effects.
Keywords: Aged; Alzheimer Disease; Area Under Curve; Dose-Response Relationship, Drug; Double-Blind Method; Healthy Volunteers; Hepatocyte Growth Factor; Humans; Male

Scavenging Reactive Oxygen Species Decreases Amyloid-β Levels via Activation of PI3K/Akt/GLUT1 Pathway in N2a/APP695swe Cells. - Peng, Yan; Zhang, Li; Zhou, Fanlin; Wang, Yangyang; Zhang, Xiong; Fan, Jianing; Li, Shijie; Li, Xiaoju; Li, Yu (J Alzheimers Dis, 2022)
BACKGROUND: Dysregulated glucose metabolism in the brain is considered to be one of the key causes of Alzheimer's disease (AD). Abnormal glucose uptake in AD is tightly associated with decreased levels of glucose transporter 1 (GLUT1) and GLUT3 in the brain, but the underlying mechanisms remain unclear. OBJECTIVE: We aimed to explore the cause and mechanism of impaired glucose uptake in AD. METHODS: N2a/WT and N2a/APP695swe cells were cultured in vitro, and cellular glucose uptake and ATP content, as well as the expression of GLUT1, GLUT3, and PI3K/Akt pathway members, were detected. Intracellular reactive oxygen species (ROS) levels were detected by flow cytometry. After treatment with the ROS scavenger N-acetyl-L-cysteine (NAC), the above indicators were detected again. RESULTS: GLUT1 expression was significantly decreased (p = 0.0138) in N2a/APP695swe cells, while GLUT3 expression was no statistical difference (p >  0.05). After NAC treatment, PI3K and Akt phosphorylation levels, GLUT1 expression, glucose uptake and ATP levels were remarkably increased (p = 0.0006, p = 0.0008, p = 0.0009, p = 0.0001, p = 0.0013), while Aβ levels were significantly decreased (p = 0.0058, p = 0.0066). After addition of the PI3K inhibitor LY29004, GLUT1 expression was reduced (p = 0.0008), and Aβ levels were increased (p = 0.0009, p = 0.0117). In addition, increases in glucose uptake and ATP levels induced by the Akt activator SC79 were hindered by the GLUT1 inhibitor WZB117 (p = 0.0002, p = 0.0005). Aβ levels were decreased after SC79 treatment and increased after WZB117 treatment (p = 0.0212, p = 0.0006). CONCLUSION: Taken together, scavenging of ROS prevents from Aβ deposition via activation of the PI3K/Akt/GLUT1 pathway, and improved the impaired glucose uptake in N2a/APP695swe cells.

Serum Levels of α-Klotho Are Correlated with Cerebrospinal Fluid Levels and Predict Measures of Cognitive Function. - Kundu, Payel; Zimmerman, Benjamin; Quinn, Joseph F; Kaye, Jeffrey; Mattek, Nora; Westaway, Shawn K; Raber, Jacob (J Alzheimers Dis, 2022)
BACKGROUND: α-klotho might play a role in neurodegenerative diseases. OBJECTIVE: To determine levels of α-klotho and apoE in serum and cerebrospinal fluid (CSF) samples and their relationship with the Mini-Mental State Examination (MMSE) and Clinical Dementia Rating (CDR). METHODS: All subjects were between age 39 to 83+ (n = 94). CDR and MMSE were administered to all participants. CSF was collected in the early afternoon by lumbar puncture. RESULTS: Serum and CSF levels of α-klotho are positively correlated and both predict scores on the MMSE and CDR, regardless of sex or apoE4 status. CONCLUSION: Our results demonstrate that α-klotho may be an important biomarker of cognitive health and neurodegeneration, and that relatively non-invasive sampling of α-klotho from serum is likely highly reflective of CSF levels.

Sex-Specific Patterns of Body Mass Index Relationship with White Matter Connectivity. - Rahmani, Farzaneh; Wang, Qing; McKay, Nicole S; Keefe, Sarah; Hantler, Nancy; Hornbeck, Russ; Wang, Yong; Hassenstab, Jason; Schindler, Suzanne; Xiong, Chengjie; Morris, John C; Benzinger, Tammie L S; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Obesity is an increasingly recognized modifiable risk factor for Alzheimer's disease (AD). Increased body mass index (BMI) is related to distinct changes in white matter (WM) fiber density and connectivity. OBJECTIVE: We investigated whether sex differentially affects the relationship between BMI and WM structural connectivity. METHODS: A cross-sectional sample of 231 cognitively normal participants were enrolled from the Knight Alzheimer Disease Research Center. Connectome analyses were done with diffusion data reconstructed using q-space diffeomorphic reconstruction to obtain the spin distribution function and tracts were selected using a deterministic fiber tracking algorithm. RESULTS: We identified an inverse relationship between higher BMI and lower connectivity in the associational fibers of the temporal lobe in overweight and obese men. Normal to overweight women showed a significant positive association between BMI and connectivity in a wide array of WM fibers, an association that reversed in obese and morbidly obese women. Interaction analyses revealed that with increasing BMI, women showed higher WM connectivity in the bilateral frontoparietal and parahippocampal parts of the cingulum, while men showed lower connectivity in right sided corticostriatal and corticopontine tracts. Subgroup analyses demonstrated comparable results in participants with and without positron emission tomography or cerebrospinal fluid evidence of brain amyloidosis, indicating that the relationship between BMI and structural connectivity in men and women is independent of AD biomarker status. CONCLUSION: BMI influences structural connectivity of WM differently in men and women across BMI categories and this relationship does not vary as a function of preclinical AD.

Single Nucleus Transcriptome Data from Alzheimer's Disease Mouse Models Yield New Insight into Pathophysiology. - Weller, Andrew E; Ferraro, Thomas N; Doyle, Glenn A; Reiner, Benjamin C; Crist, Richard C; Berrettini, Wade H (J Alzheimers Dis, 2022)
BACKGROUND: 5XFAD humanized mutant mice and Trem2 knockout (T2KO) mice are two mouse models relevant to the study of Alzheimer's disease (AD)-related pathology. OBJECTIVE: To determine hippocampal transcriptomic and polyadenylation site usage alterations caused by genetic mutations engineered in 5XFAD and T2KO mice. METHODS: Employing a publicly available single-nucleus RNA sequencing dataset, we used Seurat and Sierra analytic programs to identify differentially expressed genes (DEGs) and differential transcript usage (DTU), respectively, in hippocampal cell types from each of the two mouse models. We analyzed cell type-specific DEGs further using Ingenuity Pathway Analysis (IPA). RESULTS: We identified several DEGs in both neuronal and glial cell subtypes in comparisons of wild type (WT) versus 5XFAD and WT versus T2KO mice, including Ttr, Fth1, Pcsk1n, Malat1, Rpl37, Rtn1, Sepw1, Uba52, Mbp, Arl6ip5, Gm26917, Vwa1, and Pgrmc1. We also observed DTU in common between the two comparisons in neuronal and glial subtypes, specifically in the genes Prnp, Rbm4b, Pnisr, Opcml, Cpne7, Adgrb1, Gabarapl2, Ubb, Ndfip1, Car11, and Stmn4. IPA identified 3 statistically significant canonical pathways that appeared in multiple cell types and that overlapped between 5XFAD and T2KO comparisons to WT, including 'FXR/RXR Activation', 'LXR/RXR Activation', and 'Acute Phase Response Signaling'. CONCLUSION: DEG, DTU, and IPA findings, derived from two different mouse models of AD, highlight the importance of energy imbalance and inflammatory processes in specific hippocampal cell types, including subtypes of neurons and glial cells, in the development of AD-related pathology. Additional studies are needed to further characterize these findings.

The Spectrum of Alzheimer-Type Pathology in Cognitively Normal Individuals. - Walker, Jamie M; Dehkordi, Shiva Kazempour; Schaffert, Jeff; Goette, William; White Iii, Charles L; Richardson, Timothy E; Zare, Habil (J Alzheimers Dis, 2022)
BACKGROUND: The strongest risk factor for the development of Alzheimer's disease (AD) is age. The progression of Braak stage and Thal phase with age has been demonstrated. However, prior studies did not include cognitive status. OBJECTIVE: We set out to define normative values for Alzheimer-type pathologic changes in individuals without cognitive decline, and then define levels that would qualify them to be resistant to or resilient against these changes. METHODS: Utilizing neuropathology data obtained from the National Alzheimer's Coordinating Center (NACC), we demonstrate the age-related progression of Alzheimer-type pathologic changes in cognitively normal individuals (CDR = 0, n = 542). With plots generated from these data, we establish standard lines that may be utilized to measure the extent to which an individual's Alzheimer-type pathology varies from the estimated normal range of pathology. RESULTS: Although Braak stage and Thal phase progressively increase with age in cognitively normal individuals, the Consortium to Establish a Registry for Alzheimer's Disease neuritic plaque score and Alzheimer's disease neuropathologic change remain at low levels. CONCLUSION: These findings suggest that an increasing burden of neuritic plaques is a strong predictor of cognitive decline, whereas, neurofibrillary degeneration and amyloid-β (diffuse) plaque deposition, both to some degree, are normal pathologic changes of aging that occur in almost all individuals regardless of cognitive status. Furthermore, we have defined the amount of neuropathologic change in cognitively normal individuals that would qualify them to be "resilient" against the pathology (significantly above the normative values for age, but still cognitively normal) or "resistant" to the development of pathology (significantly below the normative values for age).

40 Hz Light Flicker Promotes Learning and Memory via Long Term Depression in Wild-Type Mice. - Tian, Tian; Qin, Xin; Wang, Yali; Shi, Yan; Yang, Xin (J Alzheimers Dis, 2021)
BACKGROUND: 40 Hz light flicker is a well-known non-invasive treatment that is thought to be effective in treating Alzheimer's disease. However, the effects of 40 Hz visual stimulation on neural networks, synaptic plasticity, and learning and memory in wild-type animals remain unclear. OBJECTIVE: We aimed to explore the impact of 40 Hz visual stimulation on synaptic plasticity, place cell, and learning and memory in wild-type mice. METHODS: c-Fos+ cell distribution and in vivo electrophysiology was used to explore the effects of 40 Hz chronic visual stimulation on neural networks and neuroplasticity in wild-type mice. The character of c-Fos+ distribution in the brain and the changes of corticosterone levels in the blood were used to investigate the state of animal. Place cell analysis and novel location test were utilized to examine the effects of 40 Hz chronic visual stimulation on learning and memory in wild-type mice. RESULTS: We found that 40 Hz light flicker significantly affected many brain regions that are related to stress. Also, 40 Hz induced gamma enrichment within 15 min after light flickers and impaired the expression of long-term potentiation (LTP), while facilitated the expression of long-term depression (LTD) in the hippocampal CA1. Furthermore, 40 Hz light flicker enhanced the expression of corticosterone, rendered well-formed place cells unstable and improved animal's learning and memory in novel local recognition test, which could be blocked by pre-treatment with the LTD specific blocker Glu2A-3Y. CONCLUSION: These finding suggested that 40 Hz chronic light flicker contains stress effects, promoting learning and memory in wild-type mice via LTD.

Accelerometer-Measured, Habitual Physical Activity and Circulating Brain-Derived Neurotrophic Factor: A Cross-Sectional Study. - Spartano, Nicole L; Himali, Jayandra J; Trinquart, Ludovic; Yang, Qiong; Weinstein, Galit; Satizabal, Claudia L; Dukes, Kimberly A; Beiser, Alexa S; Murabito, Joanne M; Vasan, Ramachandran S; Seshadri, Sudha (J Alzheimers Dis, 2021)
BACKGROUND: One of the mechanisms suggested to link physical activity (PA) to favorable brain health is through stimulation of neural growth factors such as brain-derived neurotrophic factor (BDNF). Acute bouts of PA stimulate circulating BDNF levels. OBJECTIVE: In this investigation, we assessed whether habitual, accelerometer-measured PA levels were related to circulating BDNF levels in a middle-aged cohort. METHODS: In the Framingham Heart Study Third Generation cohort, 1,769 participants provided reliable accelerometry data and were not missing BDNF measurement and platelet counts. In a cross-sectional analysis, using multivariable regression, we related PA measures to serum BDNF levels, adjusting for age, sex, smoking status, platelet count, depression status, and accelerometer wear time. RESULTS: Our study participants (mean age 47±9 years, 50.8% women) spent an average of 22.3 mins/day moderate-to-vigorous (MV)PA. Most PA variables (steps, MVPA, light activity, and sedentary time) were not related to BDNF levels (p > 0.05). We observed a non-linear trend, where 15-50 mins/week vigorous activity was associated with lower BDNF compared to those with 0 min vigorous activity (β= -0.049±0.024, p = 0.05), but with no significant associations at lower or higher vigorous activity levels. In smokers, MVPA was also associated with lower BDNF levels (β= -0.216±0.079, p = 0.01). CONCLUSION: Our study reveals that circulating BDNF is not chronically elevated in individuals with higher levels of habitual PA in middle-aged adults from the community and may even be chronically suppressed with higher PA in subgroups, including current smokers. These results do not contradict previous studies demonstrating that circulating BDNF rises acutely after PA.

Amyloid Deposition Is Greater in Cerebral Gyri than in Cerebral Sulci with Worsening Clinical Diagnosis Across the Alzheimer's Disease Spectrum. - Walden, Lucas M; Hu, Song; Madabhushi, Anant; Prescott, Jeffrey W (J Alzheimers Dis, 2021)
BACKGROUND: Histopathologic studies have demonstrated differential amyloid-β (Aβ) burden between cortical sulci and gyri in Alzheimer's disease (AD), with sulci having a greater Aβ burden. OBJECTIVE: To characterize Aβ deposition in the sulci and gyri of the cerebral cortex in vivo among subjects with normal cognition (NC), mild cognitive impairment (MCI), and AD, and to evaluate if these differences could improve discrimination between diagnostic groups. METHODS: T1-weighted 3T MR and florbetapir (amyloid) positron emission tomography (PET) data were obtained from the Alzheimer's Disease Neuroimaging Initiative (ADNI). T1 images were segmented and the cortex was separated into sulci/gyri based on pial surface curvature measurements. T1 images were registered to PET images and regional standardized uptake value ratios (SUVr) were calculated. A linear mixed effects model was used to analyze the relationship between clinical variables and amyloid PET SUVr measurements in the sulci/gyri. Receiver operating characteristic (ROC) analysis was performed to define amyloid positivity. Logistic models were used to evaluate predictive performance of clinical diagnosis using amyloid PET SUVr measurements in sulci/gyri. RESULTS: 719 subjects were included: 272 NC, 315 MCI, and 132 AD. Gyral and sulcal Aβ increased with worsening cognition, however there was a greater increase in gyral Aβ. Females had a greater gyral and sulcal Aβ burden. Focusing on sulcal and gyral Aβ did not improve predictive power for diagnostic groups. CONCLUSION: While there were significant differences in Aβ deposition in cerebral sulci and gyri across the AD spectrum, these differences did not translate into improved prediction of diagnosis. Females were found to have greater gyral and sulcal Aβ burden.

ANMerge: A Comprehensive and Accessible Alzheimer's Disease Patient-Level Dataset. - Birkenbihl, Colin; Westwood, Sarah; Shi, Liu; Nevado-Holgado, Alejo; Westman, Eric; Lovestone, Simon; Hofmann-Apitius, Martin (J Alzheimers Dis, 2021)
BACKGROUND: Accessible datasets are of fundamental importance to the advancement of Alzheimer's disease (AD) research. The AddNeuroMed consortium conducted a longitudinal observational cohort study with the aim to discover AD biomarkers. During this study, a broad selection of data modalities was measured including clinical assessments, magnetic resonance imaging, genotyping, transcriptomic profiling, and blood plasma proteomics. Some of the collected data were shared with third-party researchers. However, this data was incomplete, erroneous, and lacking in interoperability. OBJECTIVE: To provide the research community with an accessible, multimodal, patient-level AD cohort dataset. METHODS: We systematically addressed several limitations of the originally shared resources and provided additional unreleased data to enhance the dataset. RESULTS: In this work, we publish and describe ANMerge, a new version of the AddNeuroMed dataset. ANMerge includes multimodal data from 1,702 study participants and is accessible to the research community via a centralized portal. CONCLUSION: ANMerge is an information rich patient-level data resource that can serve as a discovery and validation cohort for data-driven AD research, such as, for example, machine learning and artificial intelligence approaches.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Datasets as Topic; Female; Gene Expression Profiling; Genotype; Humans; Magnetic Resonance Imaging; Male; Proteomics

Automatic Subtyping of Individuals with Primary Progressive Aphasia. - Themistocleous, Charalambos; Ficek, Bronte; Webster, Kimberly; den Ouden, Dirk-Bart; Hillis, Argye E; Tsapkini, Kyrana (J Alzheimers Dis, 2021)
BACKGROUND: The classification of patients with primary progressive aphasia (PPA) into variants is time-consuming, costly, and requires combined expertise by clinical neurologists, neuropsychologists, speech pathologists, and radiologists. OBJECTIVE: The aim of the present study is to determine whether acoustic and linguistic variables provide accurate classification of PPA patients into one of three variants: nonfluent PPA, semantic PPA, and logopenic PPA. METHODS: In this paper, we present a machine learning model based on deep neural networks (DNN) for the subtyping of patients with PPA into three main variants, using combined acoustic and linguistic information elicited automatically via acoustic and linguistic analysis. The performance of the DNN was compared to the classification accuracy of Random Forests, Support Vector Machines, and Decision Trees, as well as to expert clinicians' classifications. RESULTS: The DNN model outperformed the other machine learning models as well as expert clinicians' classifications with 80% classification accuracy. Importantly, 90% of patients with nfvPPA and 95% of patients with lvPPA was identified correctly, providing reliable subtyping of these patients into their corresponding PPA variants. CONCLUSION: We show that the combined speech and language markers from connected speech productions can inform variant subtyping in patients with PPA. The end-to-end automated machine learning approach we present can enable clinicians and researchers to provide an easy, quick, and inexpensive classification of patients with PPA.
Keywords: Acoustics; Aged; Aphasia, Primary Progressive; Decision Trees; Female; Humans; Linguistics; Machine Learning; Male; Models, Theoretical; Neural Networks, Computer; Primary Progressive Nonfluent Aphasia; Reproducibility of Results; Support Vector Machine

The Behavioral and Psychological Symptoms of Dementia in Down Syndrome Scale (BPSD-DS II): Optimization and Further Validation. - Dekker, Alain D; Ulgiati, Aurora M; Groen, Henk; Boxelaar, Vincent A; Sacco, Silvia; Falquero, Ségolène; Carfi, Angelo; di Paola, Antonella; Benejam, Bessy; Valldeneu, Silvia; Fopma, Roelie; Oosterik, Marjo; et al. (J Alzheimers Dis, 2021)
BACKGROUND: People with Down syndrome (DS) are at high risk to develop Alzheimer's disease dementia (AD). Behavioral and psychological symptoms of dementia (BPSD) are common and may also serve as early signals for dementia. However, comprehensive evaluation scales for BPSD, adapted to DS, are lacking. Therefore, we previously developed the BPSD-DS scale to identify behavioral changes between the last six months and pre-existing life-long characteristic behavior. OBJECTIVE: To optimize and further study the scale (discriminative ability and reliability) in a large representative DS study population. METHODS: Optimization was based on item irrelevance and clinical experiences obtained in the initial study. Using the shortened and refined BPSD-DS II, informant interviews were conducted to evaluate 524 individuals with DS grouped according to dementia status: no dementia (DS, N = 292), questionable dementia (DS + Q, N = 119), and clinically diagnosed dementia (DS + AD, N = 113). RESULTS: Comparing item change scores between groups revealed prominent changes in frequency and severity for anxious, sleep-related, irritable, restless/stereotypic, apathetic, depressive, and eating/drinking behavior. For most items, the proportion of individuals displaying an increased frequency was highest in DS + AD, intermediate in DS + Q, and lowest in DS. For various items within sections about anxious, sleep-related, irritable, apathetic, and depressive behaviors, the proportion of individuals showing an increased frequency was already substantial in DS + Q, suggesting that these changes may serve as early signals of AD in DS. Reliability data were promising. CONCLUSION: The optimized scale yields largely similar results as obtained with the initial version. Systematically evaluating BPSD in DS may increase understanding of changes among caregivers and (timely) adaptation of care/treatment.
Keywords: Adult; Aged; Anxiety; Dementia; Down Syndrome; Female; Humans; Irritable Mood; Male; Middle Aged; Reproducibility of Results; Symptom Assessment

Borrelia burgdorferi Co-Localizing with Amyloid Markers in Alzheimer's Disease Brain Tissues. - Senejani, Alireza G; Maghsoudlou, Jasmin; El-Zohiry, Dina; Gaur, Gauri; Wawrzeniak, Keith; Caravaglia, Cristina; Khatri, Vishwa A; MacDonald, Alan; Sapi, Eva (J Alzheimers Dis, 2021)
BACKGROUND: Infections by bacterial or viral agents have been hypothesized to influence the etiology of neurodegenerative diseases. OBJECTIVE: This study examined the potential presence of Borrelia burgdorferi spirochete, the causative agent of Lyme disease, in brain autopsy tissue of patients diagnosed with either Alzheimer's (AD) or Parkinson's diseases. METHODS: Brain tissue sections from patients with age-matched controls were evaluated for antigen and DNA presence of B. burgdorferi using various methods. Positive Borrelia structures were evaluated for co-localization with biofilm and AD markers such as amyloid and phospho-tau (p-Tau) using immunohistochemical methods. RESULTS: The results showed the presence of B. burgdorferi antigen and DNA in patients with AD pathology and among those, one of them was previously diagnosed with Lyme disease. Interestingly, a significant number of Borrelia-positive aggregates with a known biofilm marker, alginate, were found along with the spirochetal structures. Our immunohistochemical data also showed that Borrelia-positive aggregates co-localized with amyloid and anti-phospho-tau markers. To further prove the potential relationship of B. burgdorferi and amyloids, we infected two mammalian cell lines with B. burgdorferi which resulted in a significant increase in the expression of amyloid-β and p-Tau proteins in both cells lines post-infection. CONCLUSION: These results indicate that B. burgdorferi can be found in AD brain tissues, not just in spirochete but a known antibiotics resistant biofilm form, and its co-localized amyloid markers. In summary, this study provides evidence for a likely association between B. burgdorferi infections and biofilm formation, AD pathology, and chronic neurodegenerative diseases.

Cerebrospinal Fluid Sulfatide Levels Lack Diagnostic Utility in the Subcortical Small Vessel Type of Dementia. - Svensson, Johan; Blomqvist, Maria; Kettunen, Petronella; Eckerström, Carl; Henricsson, Marcus; Jonsson, Michael; Bjerke, Maria; Månsson, Jan-Eric; Wallin, Anders (J Alzheimers Dis, 2021)
BACKGROUND: Sulfatides (STs) in cerebrospinal fluid (CSF), as well as magnetic resonance imaging (MRI)-detected white matter hyperintensities (WMHs), may reflect demyelination. Here, we investigated the diagnostic utility of CSF ST levels in the subcortical small vessel type of dementia (SSVD), which is characterized by the presence of brain WMHs. OBJECTIVE: To study the diagnostic utility of CSF ST levels in SSVD. METHODS: This was a mono-center, cross-sectional study of SSVD (n = 16), Alzheimer's disease (n = 40), mixed dementia (n = 27), and healthy controls (n = 33). Totally, 20 ST species were measured in CSF by liquid chromatography-mass spectrometry (LC-MS/MS). RESULTS: CSF total ST levels, as well as CSF levels of hydroxylated and nonhydroxylated ST species, did not differ across the study groups. In contrast, CSF neurofilament light chain (NFL) levels separated the patient groups from the controls. CSF total ST level correlated with CSF/serum albumin ratio in the total study population (r = 0.64, p <  0.001) and in all individual study groups. Furthermore, CSF total ST level correlated positively with MRI-estimated WMH volume in the total study population (r = 0.30, p <  0.05), but it did not correlate with CSF NFL level. CONCLUSION: Although there was some relation between CSF total ST level and WMH volume, CSF ST levels were unaltered in all dementia groups compared to the controls. This suggests that CSF total ST level is a poor biomarker of demyelination in SSVD. Further studies are needed to investigate the mechanisms underlying the marked correlation between CSF total ST level and CSF/serum albumin ratio.

Cognitive Effects of Aerobic Exercise in Alzheimer's Disease: A Pilot Randomized Controlled Trial. - Yu, Fang; Vock, David M; Zhang, Lin; Salisbury, Dereck; Nelson, Nathaniel W; Chow, Lisa S; Smith, Glenn; Barclay, Terry R; Dysken, Maurice; Wyman, Jean F (J Alzheimers Dis, 2021)
BACKGROUND: Aerobic exercise has shown inconsistent cognitive effects in older adults with Alzheimer's disease (AD) dementia. OBJECTIVE: To examine the immediate and longitudinal effects of 6-month cycling on cognition in older adults with AD dementia. METHODS: This randomized controlled trial randomized 96 participants (64 to cycling and 32 to stretching for six months) and followed them for another six months. The intervention was supervised, moderate-intensity cycling for 20-50 minutes, 3 times a week for six months. The control was light-intensity stretching. Cognition was assessed at baseline, 3, 6, 9, and 12 months using the AD Assessment Scale-Cognition (ADAS-Cog). Discrete cognitive domains were measured using the AD Uniform Data Set battery. RESULTS: The participants were 77.4±6.8 years old with 15.6±2.9 years of education, and 55%were male. The 6-month change in ADAS-Cog was 1.0±4.6 (cycling) and 0.1±4.1 (stretching), which were both significantly less than the natural 3.2±6.3-point increase observed naturally with disease progression. The 12-month change was 2.4±5.2 (cycling) and 2.2±5.7 (control). ADAS-Cog did not differ between groups at 6 (p = 0.386) and 12 months (p = 0.856). There were no differences in the 12-month rate of change in ADAS-Cog (0.192 versus 0.197, p = 0.967), memory (-0.012 versus -0.019, p = 0.373), executive function (-0.020 versus -0.012, p = 0.383), attention (-0.035 versus -0.033, p = 0.908), or language (-0.028 versus -0.026, p = 0.756). CONCLUSION: Exercise may reduce decline in global cognition in older adults with mild-to-moderate AD dementia. Aerobic exercise did not show superior cognitive effects to stretching in our pilot trial, possibly due to the lack of power.

Cognitive Effects of the BET Protein Inhibitor Apabetalone: A Prespecified Montreal Cognitive Assessment Analysis Nested in the BETonMACE Randomized Controlled Trial. - Cummings, Jeffrey; Schwartz, Gregory G; Nicholls, Stephen J; Khan, Aziz; Halliday, Chris; Toth, Peter P; Sweeney, Michael; Johansson, Jan O; Wong, Norman C W; Kulikowski, Ewelina; Kalantar-Zadeh, Kamyar; Lebioda, Kenneth; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Epigenetic changes may contribute importantly to cognitive decline in late life including Alzheimer's disease (AD) and vascular dementia (VaD). Bromodomain and extra-terminal (BET) proteins are epigenetic "readers" that may distort normal gene expression and contribute to chronic disorders. OBJECTIVE: To assess the effects of apabetalone, a small molecule BET protein inhibitor, on cognitive performance of patients 70 years or older participating in a randomized trial of patients at high risk for major cardiovascular events (MACE). METHODS: The Montreal Cognitive Assessment (MoCA) was performed on all patients 70 years or older at the time of randomization. 464 participants were randomized to apabetalone or placebo in the cognition sub-study. In a prespecified analysis, participants were assigned to one of three groups: MoCA score≥26 (normal performance), MoCA score 25-22 (mild cognitive impairment), and MoCA score≤21 (dementia). Exposure to apabetalone was equivalent in the treatment groups in each MoCA-defined group. RESULTS: Apabetalone was associated with an increased total MoCA score in participants with baseline MoCA score of≤21 (p = 0.02). There was no significant difference in change from baseline in the treatment groups with higher MoCA scores. In the cognition study, more patients randomized to apabetalone discontinued study drug for adverse effects (11.3% versus 7.9%). CONCLUSION: In this randomized controlled study, apabetalone was associated with improved cognition as measured by MoCA scores in those with baseline scores of 21 or less. BET protein inhibitors warrant further investigation for late life cognitive disorders.
Keywords: Aged; Cardiovascular Diseases; Cognitive Dysfunction; Epigenesis, Genetic; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Quinazolinones

Copper Imbalance in Alzheimer's Disease and Its Link with the Amyloid Hypothesis: Towards a Combined Clinical, Chemical, and Genetic Etiology. - Squitti, Rosanna; Faller, Peter; Hureau, Christelle; Granzotto, Alberto; White, Anthony R; Kepp, Kasper P (J Alzheimers Dis, 2021)
The cause of Alzheimer's disease (AD) is incompletely defined. To date, no mono-causal treatment has so far reached its primary clinical endpoints, probably due to the complexity and diverse neuropathology contributing to the neurodegenerative process. In the present paper, we describe the plausible etiological role of copper (Cu) imbalance in the disease. Cu imbalance is strongly associated with neurodegeneration in dementia, but a complete biochemical etiology consistent with the clinical, chemical, and genetic data is required to support a causative association, rather than just correlation with disease. We hypothesize that a Cu imbalance in the aging human brain evolves as a gradual shift from bound metal ion pools, associated with both loss of energy production and antioxidant function, to pools of loosely bound metal ions, involved in gain-of-function oxidative stress, a shift that may be aggravated by chemical aging. We explain how this may cause mitochondrial deficits, energy depletion of high-energy demanding neurons, and aggravated protein misfolding/oligomerization to produce different clinical consequences shaped by the severity of risk factors, additional comorbidities, and combinations with other types of pathology. Cu imbalance should be viewed and integrated with concomitant genetic risk factors, aging, metabolic abnormalities, energetic deficits, neuroinflammation, and the relation to tau, prion proteins, α-synuclein, TAR DNA binding protein-43 (TDP-43) as well as systemic comorbidity. Specifically, the Amyloid Hypothesis is strongly intertwined with Cu imbalance because amyloid-β protein precursor (AβPP)/Aβ are probable Cu/Zn binding proteins with a potential role as natural Cu/Zn buffering proteins (loss of function), and via the plausible pathogenic role of Cu-Aβ.

A Cost-Consequence Analysis of Different Screening Procedures in Alzheimer's Disease: Results from the MOPEAD Project. - Wimo, Anders; Belger, Mark; Bon, Jaka; Jessen, Frank; Dumas, Annette; Kramberger, Milica G; Jamilis, Laura; Johansson, Gunilla; Rodrigo Salas, Adrián; Rodríguez Gómez, Octavio; Sannemann, Lena; Stoekenbroek, Malou; et al. (J Alzheimers Dis, 2021)
BACKGROUND: For care planning and support, under-detection and late diagnosis of Alzheimer's disease (AD) is a great challenge. Models of Patient-Engagement for Alzheimer's Disease (MOPEAD) is an EU-funded project aiming at testing different strategies to improve this situation. OBJECTIVE: To make a cost-consequence analysis of MOPEAD. METHODS: Four screening strategies were tested in five countries (Germany, the Netherlands, Slovenia, Spain, and Sweden): 1) a web-approach; 2) Open-House initiative; 3) in primary care; and 4) by diabetes specialists. Persons-at-risk of AD in all strategies were offered referral to a hospital-based specialist. The primary health-economic outcome was the cost per true-positive case (TP) of AD from the screened population. RESULTS: Of 2,847 screened persons, 1,121 screened positive (39%), 402 were evaluated at memory clinics (14%), and 236 got an AD diagnosis (8%). The cost per TP of those screened was 3,115€ with the web-approach, 2,722€ with the Open-House, 1,530€ in primary care, and 1,190€ by diabetes specialists. Sensitivity analyses that more likely reflect the real-world situation confirmed the results. The number-needed-to-screen was 30 with the web-approach, 8 with the Open-House and primary care, and 6 with the diabetes specialists.There were country differences in terms of screening rates, referrals to memory clinics, staff-types involved, and costs per TP. CONCLUSION: In primary care and by the diabetes specialist, the costs per TP/screened population were lowest, but the capacity of such settings to identify cases with AD-risk must be discussed. Hence new diagnostic strategies such as web-solutions and Open-House initiatives may be valuable after modifications.

Deaths with Dementia in Indigenous and Non-Indigenous Australians: A Nationwide Study. - Waller, Michael; Buckley, Rachel F; Masters, Colin L; Nona, Francis R; Eades, Sandra; Dobson, Annette J (J Alzheimers Dis, 2021)
BACKGROUND: The prevalence of dementia is generally reported to be higher among Indigenous peoples. OBJECTIVE: The rates and coding of dementia mortality were compared between Indigenous and non-Indigenous Australians. METHODS: De-identified individual records on causes of death for all people aged 40 years or more who died in Australia between 2006 and 2014 (n = 1,233,084) were used. There were 185,237 records with International Classification of Diseases, Tenth Revision, codes for dementia (Alzheimer's Disease, vascular dementia, or unspecified dementia) as the underlying cause of death or mentioned elsewhere on the death certificate. Death rates were compared using Poisson regression. Logistic regression was used to assess whether dementia was more likely to be classified as 'unspecified' type in Indigenous Australians. RESULTS: The rates of death with dementia were 57% higher in Indigenous Australians, compared to non-Indigenous, relative rate (RR) 1.57, 95% confidence interval (CI) (1.48, 1.66), p <  0.0001. This excess of deaths was highest at ages below 75 (RRs >  2, test for interaction p <  0.0001), and among men (test for interaction p <  0.0001). When the underreporting of Indigenous status on the death certificate was taken into account the relative rate increased to 2.17, 95% CI (2.07, 2.29). Indigenous Australians were also more likely to have their dementia coded as 'unspecified' on their death certificate (Odds Ratio 1.92, 95% CI (1.66, 2.21), p <  0.0001), compared to the non-Indigenous group. CONCLUSION: This epidemiological analysis based on population level mortality data demonstrates the higher dementia-related mortality rate for Indigenous Australians especially at younger ages.

Diagnosing Mild Cognitive Impairment Among Racially Diverse Older Adults: Comparison of Consensus, Actuarial, and Statistical Methods. - Devlin, Kathryn N; Brennan, Laura; Saad, Laura; Giovannetti, Tania; Hamilton, Roy H; Wolk, David A; Xie, Sharon X; Mechanic-Hamilton, Dawn (J Alzheimers Dis, 2021)
BACKGROUND: Actuarial and statistical methods have been proposed as alternatives to conventional methods of diagnosing mild cognitive impairment (MCI), with the aim of enhancing diagnostic and prognostic validity, but have not been compared in racially diverse samples. OBJECTIVE: We compared the agreement of consensus, actuarial, and statistical MCI diagnostic methods, and their relationship to race and prognostic indicators among diverse older adults. METHODS: Participants (N = 354; M age = 71; 68% White, 29% Black) were diagnosed with MCI or normal cognition (NC) according to clinical consensus, actuarial neuropsychological criteria (Jak/Bondi), and latent class analysis (LCA). We examined associations with race/ethnicity, longitudinal cognitive and functional change, and incident dementia. RESULTS: MCI rates by consensus, actuarial criteria, and LCA were 44%, 53%, and 41%, respectively. LCA identified three MCI subtypes (memory; memory/language; memory/executive) and two NC classes (low normal; high normal). Diagnostic agreement was substantial, but agreement of the actuarial method with consensus and LCA was weaker than the agreement between consensus and LCA. Among cases classified as MCI by actuarial criteria only, Black participants were over-represented, and outcomes were generally similar to those of NC participants. Consensus diagnoses best predicted longitudinal outcomes overall, whereas actuarial diagnoses best predicted longitudinal functional change among Black participants. CONCLUSION: Consensus diagnoses optimize specificity in predicting dementia, but among Black older adults, actuarial diagnoses may be more sensitive to early signs of decline. Results highlight the need for cross-cultural validity in MCI diagnosis and should be explored in community- and population-based samples.

Diet May Moderate the Relationship Between Arterial Stiffness and Cognitive Performance in Older Adults. - Gauci, Sarah; Young, Lauren M; White, David J; Reddan, Jeffery M; Lassemillante, Annie-Claude; Meyer, Denny; Pipingas, Andrew; Scholey, Andrew (J Alzheimers Dis, 2021)
BACKGROUND: Cognitive decline is influenced by various factors including diet, cardiovascular disease, and glucose control. However, the combined effect of these risk factors on cognitive performance is yet to be fully understood. OBJECTIVE: The current study aimed to explore the inter-relationship between these risk factors and cognitive performance in older adults at risk of future cognitive decline. METHODS: The sample comprised 163 (Age: M = 65.23 years, SD = 6.50) participants. Food Frequency Questionnaire data was used to score diet quality and adherence to the Western Style Diet (WSD) and Prudent Style Diet (PSD). Glucose control was gauged by serum levels of glycated hemoglobin (HbA1c) and arterial stiffness was measured using carotid to femoral pulse wave velocity. Cognitive performance was assessed using two subtests of the Swinburne University Computerized Cognitive Assessment Battery (SUCCAB) and Rey's Verbal Learning Test (RVLT). RESULTS: Diet quality, adherence to the WSD or PSD, and glucose control were not significantly related to cognitive outcomes. However, a significant negative association was found between arterial stiffness and the spatial working memory subtest of SUCCAB (β= -0.21, p <  0.05). Arterial stiffness also significantly interacted with the PSD to impact total recall (F change (1,134) = 5.37, p <  0.05) and the composite score of RVLT (F change (1,134) = 4.03, p <  0.05). CONCLUSION: In this sample of older adults at risk of cognitive decline, diet alone was not found to predict cognitive performance; however, it was found to moderate the relationship between arterial stiffness and cognition.

Droplet Degeneration of Hippocampal and Cortical Neurons Signifies the Beginning of Neuritic Plaque Formation. - Streit, Wolfgang J; Rotter, Jonas; Winter, Karsten; Müller, Wolf; Khoshbouei, Habibeh; Bechmann, Ingo (J Alzheimers Dis, 2021)
BACKGROUND: Neuritic plaques contain neural and microglial elements, and amyloid-β protein (Aβ), but their pathogenesis remains unknown. OBJECTIVE: Elucidate neuritic plaque pathogenesis. METHODS: Histochemical visualization of hyperphosphorylated-tau positive (p-tau+) structures, microglia, Aβ, and iron. RESULTS: Disintegration of large projection neurons in human hippocampus and neocortex presents as droplet degeneration: pretangle neurons break up into spheres of numerous p-tau+ droplets of various sizes, which marks the beginning of neuritic plaques. These droplet spheres develop in the absence of colocalized Aβ deposits but once formed become encased in diffuse Aβ with great specificity. In contrast, neurofibrillary tangles often do not colocalize with Aβ. Double-labelling for p-tau and microglia showed a lack of microglial activation or phagocytosis of p-tau+ degeneration droplets but revealed massive upregulation of ferritin in microglia suggesting presence of high levels of free iron. Perl's Prussian blue produced positive staining of microglia, droplet spheres, and Aβ plaque cores supporting the suggestion that droplet degeneration of pretangle neurons in the hippocampus and cortex represents ferroptosis, which is accompanied by the release of neuronal iron extracellularly. CONCLUSION: Age-related iron accumulation and ferroptosis in the CNS likely trigger at least two endogenous mechanisms of neuroprotective iron sequestration and chelation, microglial ferritin expression and Aβ deposition, respectively, both contributing to the formation of neuritic plaques. Since neurofibrillary tangles and Aβ deposits colocalize infrequently, tangle formation likely does not involve release of neuronal iron extracellularly. In human brain, targeted deposition of Aβ occurs specifically in response to ongoing ferroptotic droplet degeneration thereby producing neuritic plaques.

Economic Burden of Alzheimer's Disease Dementia in Japan. - Ikeda, Shunya; Mimura, Masaru; Ikeda, Manabu; Wada-Isoe, Kenji; Azuma, Mie; Inoue, Sachie; Tomita, Kiyoyuki (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease dementia (ADD) is the leading cause of long-term care in Japan. OBJECTIVE: This study estimates the annual healthcare and long-term care costs in fiscal year 2018 for adults over 65 years of age with ADD in Japan and the informal care costs and productivity loss for their families. METHODS: Healthcare and long-term care costs for ADD were estimated according to the disease severity classified by the clinical dementia rating (CDR) score, using reports from a literature review. For the costs of time spent on caregiving activities, productivity loss for ADD family caregivers aged 20-69 and informal care costs for all ADD family caregivers were estimated. RESULTS: The total healthcare cost of ADD was JPY 1,073 billion, of which 86% (JPY 923 billion) was attributed to healthcare costs other than ADD drug costs (JPY 151 billion). The healthcare costs other than ADD drug costs by severity were less than JPY 200 billion for CDR 0.5, CDR 1, and CDR 2, respectively, but increased to JPY 447 billion (48%) for CDR 3. The public long-term care costs were estimated to be JPY 4,783 billion, which increased according to the severity. Total productivity loss for ADD family caregivers aged 20-69 was JPY 1,547 billion and the informal care cost for all ADD family caregivers was JPY 6,772 billion. CONCLUSION: ADD costs have a significant impact on public-funded healthcare, long-term care systems, and families in Japan. To minimize the economic burden of ADD, prolonging healthy life expectancy is the key factor to address.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Caregivers; Female; Health Care Costs; Humans; Japan; Long-Term Care; Male

Effects of Peroral Omega-3 Fatty Acid Supplementation on Cerebrospinal Fluid Biomarkers in Patients with Alzheimer's Disease: A Randomized Controlled Trial-The OmegAD Study. - Tofiq, Avin; Zetterberg, Henrik; Blennow, Kaj; Basun, Hans; Cederholm, Tommy; Eriksdotter, Maria; Faxen-Irving, Gerd; Hjorth, Erik; Jernerén, Fredrik; Schultzberg, Marianne; Wahlund, Lars-Olof; Palmblad, Jan; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Studies have suggested a connection between a decrease in the levels of polyunsaturated fatty acids (PUFAs) and Alzheimer's disease (AD). We aimed to assess the effect of supplementation with omega-3 fatty acids (n-3 FAs) on biomarkers analyzed in the cerebrospinal fluid (CSF) of patients diagnosed with AD. OBJECTIVE: To investigate the effects of daily supplementation with 2.3 g of PUFAs in AD patients on the biomarkers in CSF described below. We also explored the possible correlation between these biomarkers and the performance in the cognitive test Mini-Mental State Examination (MMSE). METHODS: Thirty-three patients diagnosed with AD were randomized to either treatment with a daily intake of 2.3 g of n-3 FAs (n  =  18) or placebo (n  =  15). CSF samples were collected at baseline and after six months of treatment, and the following biomarkers were analyzed: Aβ 38, Aβ 40, Aβ 42, t-tau, p-tau, neurofilament light (NfL), chitinase-3-like protein 1 (YKL-40), acetylcholinesterase (AChE), butyrylcholinesterase (BuChE), soluble IL-1 receptor type II (sIL-1RII), and IL-6. RESULTS: There were no significant differences between the groups concerning the level of the different biomarkers in the CSF at baseline. Within the treatment group, there was a small but significant increase in both YKL-40 (p = 0.04) and NfL (p = 0.03), while the other CSF biomarkers remained stable. CONCLUSION: Supplementation with n-3 FAs had a statistically significant effect on NfL and YKL-40, resulting in an increase of both biomarkers, indicating a possible increase of inflammatory response and axonal damage. This increase in biomarkers did not correlate with MMSE score.

Entorhinal Perfusion Predicts Future Memory Decline, Neurodegeneration, and White Matter Hyperintensity Progression in Older Adults. - Bangen, Katherine J; Thomas, Kelsey R; Sanchez, Danielle L; Edmonds, Emily C; Weigand, Alexandra J; Delano-Wood, Lisa; Bondi, Mark W (J Alzheimers Dis, 2021)
BACKGROUND: Altered cerebral blood flow (CBF) has been linked to increased risk for Alzheimer's disease (AD). However, whether altered CBF contributes to AD risk by accelerating cognitive decline remains unclear. It also remains unclear whether reductions in CBF accelerate neurodegeneration and development of small vessel cerebrovascular disease. OBJECTIVE: To examine associations between CBF and trajectories of memory performance, regional brain atrophy, and global white matter hyperintensity (WMH) volume. METHOD: 147 Alzheimer's Disease Neuroimaging Initiative participants free of dementia underwent arterial spin labeling (ASL) magnetic resonance imaging (MRI) to measure CBF and serial neuropsychological and structural MRI examinations. Linear mixed effects models examined 5-year rate of change in memory and 4-year rate of change in regional brain atrophy and global WMH volumes as a function of baseline regional CBF. Entorhinal and hippocampal CBF were examined in separate models. RESULTS: Adjusting for demographic characteristics, pulse pressure, apolipoprotein E ɛ4 positivity, cerebrospinal fluid p-tau/Aβ ratio, and neuronal metabolism (i.e., fluorodeoxyglucose standardized uptake value ratio), lower baseline entorhinal CBF predicted faster rates of decline in memory as well as faster entorhinal thinning and WMH progression. Hippocampal CBF did not predict cognitive or brain structure trajectories. CONCLUSION: Findings highlight the importance of early cerebrovascular dysfunction in AD risk and suggest that entorhinal CBF as measured by noninvasive ASL MRI is a useful biomarker predictive of future cognitive decline and of risk of both.

Ethnic Differences in Dementia Risk: A Systematic Review and Meta-Analysis. - Shiekh, Suhail Ismail; Cadogan, Sharon Louise; Lin, Liang-Yu; Mathur, Rohini; Smeeth, Liam; Warren-Gash, Charlotte (J Alzheimers Dis, 2021)
BACKGROUND: Globally around 50 million people have dementia. Risk factors for dementia such as hypertension and diabetes are more common in Black, Asian, and other ethnic minorities. There are also marked ethnic inequalities in care seeking, likelihood of diagnosis, and uptake of treatments for dementia. Nevertheless, ethnic differences in dementia incidence and prevalence remain under-explored. OBJECTIVE: To examine published peer-reviewed observational studies comparing age-specific or age-adjusted incidence or prevalence rates of dementia between at least two ethnic groups. METHODS: We searched seven databases on 1 September 2019 using search terms for ethnicity, dementia, and incidence or prevalence. We included population-based studies comparing incidence or prevalence of dementia after accounting for age of at least two ethnic groups in adults aged 18 or more. Meta-analysis was conducted for eligible ethnic comparisons. RESULTS: We included 12 cohort studies and seven cross-sectional studies. Thirteen were from the US, and two studies each from the UK, Singapore, and Xinjiang Uyghur Autonomous Region in China. The pooled risk ratio for dementia incidence obtained from four studies comparing Black and White ethnic groups was 1.33 (95% CI 1.07-1.65; I-squared = 58.0%). The pooled risk ratio for dementia incidence comparing the Asian and White ethnic groups was 0.86 (95% CI 0.728-1.01; I-squared = 43.9%). There was no difference in the incidence of dementia for Latino ethnic group compared to the White ethnic group. CONCLUSION: Evidence to date suggest there are ethnic differences in risk of dementia. Better understanding of the drivers of these differences may inform efforts to prevent or treat dementia.

Five-Year Change in Body Mass Index Predicts Conversion to Mild Cognitive Impairment or Dementia Only in APOE ɛ4 Allele Carriers. - Kadey, Kylie R; Woodard, John L; Moll, Allison C; Nielson, Kristy A; Smith, J Carson; Durgerian, Sally; Rao, Stephen M (J Alzheimers Dis, 2021)
BACKGROUND: Body mass index (BMI) has been identified as an important modifiable lifestyle risk factor for dementia, but less is known about how BMI might interact with Apolipoprotein E ɛ4 (APOE ɛ4) carrier status to predict conversion to mild cognitive impairment (MCI) and dementia. OBJECTIVE: The aim of this study was to investigate the interaction between APOE ɛ4 status and baseline (bBMI) and five-year BMI change (ΔBMI) on conversion to MCI or dementia in initially cognitively healthy older adults. METHODS: The associations between bBMI, ΔBMI, APOE ɛ4 status, and conversion to MCI or dementia were investigated among 1,289 cognitively healthy elders from the National Alzheimer's Coordinating Center (NACC) database. RESULTS: After five years, significantly more carriers (30.6%) converted to MCI or dementia than noncarriers (17.6%), p <  0.001, OR = 2.06. Neither bBMI (OR = 0.99, 95%CI = 0.96-1.02) nor the bBMI by APOE interaction (OR = 1.02, 95%CI = 0.96-1.08) predicted conversion. Although ΔBMI also did not significantly predict conversion (OR = 0.90, 95%CI = 0.78-1.04), the interaction between ΔBMI and carrier status was significant (OR = 0.72, 95%CI = 0.53-0.98). For carriers only, each one-unit decline in BMI over five years was associated with a 27%increase in the odds of conversion (OR = 0.73, 95%CI = 0.57-0.94). CONCLUSION: A decline in BMI over five years, but not bBMI, was strongly associated with conversion to MCI or dementia only for APOE ɛ4 carriers. Interventions and behaviors aimed at maintaining body mass may be important for long term cognitive health in older adults at genetic risk for AD.

Gut Microbiota Changes and Their Correlation with Cognitive and Neuropsychiatric Symptoms in Alzheimer's Disease. - Zhou, Yunzhe; Wang, Yan; Quan, Meina; Zhao, Huiying; Jia, Jianping (J Alzheimers Dis, 2021)
BACKGROUND: Gut microbiota can influence human brain function and behavior. Recent studies showed that gut microbiota might play an important role in the pathogenesis of Alzheimer's disease (AD). OBJECTIVE: To investigate the composition of gut microbiota in AD patients and their association with cognitive function and neuropsychiatric symptoms (NPS). METHODS: The fecal samples from 60 AD patients (30 with NPS and 30 without NPS) and 32 healthy control subjects (HC) were collected and analyzed by 16S ribosomal RNA sequencing. The functional variations of gut microbiota were predicted using Phylogenetic Investigation of Communities by Reconstruction of Unobserved States. The correlation between different bacterial taxa and cognitive (Mini-Mental State Examination (MMSE), Clinical Dementia Rating (CDR)), and NPS measures were analyzed. RESULTS: The fecal microbial composition of AD patients was quite distinct from HC. Bifidobacterium, Sphingomonas, Lactobacillus, and Blautia were enriched, while Odoribacter, Anaerobacterium, and Papillibacter were reduced. AD patients with NPS showed decreased Chitinophagaceae, Taibaiella, and Anaerobacterium compared with those without NPS. Functional pathways were different between AD and HC, and between AD patients with and without NPS. Correlation analysis showed that Sphingomonas correlated negatively with MMSE; Anaerobacterium and Papillibacter correlated positively with MMSE and negatively with CDR. Cytophagia, Rhodospirillaceae, and Cellvibrio correlated positively with NPS, while Chitinophagaceae, Taibaiella, and Anaerobacterium correlated negatively with NPS. CONCLUSION: AD patients have gut microbiota alterations related to cognition, and differential taxa between AD patients with and without NPS associated differently with NPS domains, which helps further understand the pathogenesis of AD and explore potential therapeutic targets.

High Fat Diet Mediates Amyloid-β Cleaving Enzyme 1 Phosphorylation and SUMOylation, Enhancing Cognitive Impairment in APP/PS1 Mice. - Bao, Jian; Liang, Zheng; Gong, Xiaokang; Yu, Jing; Xiao, Yifan; Liu, Wei; Wang, Xiaochuan; Wang, Jian-Zhi; Shu, Xiji (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease (AD) is the most common form of dementia in older adults and extracellular accumulation of amyloid-β (Aβ) is one of the two characterized pathologies of AD. Obesity is significantly associated with AD developing factors. Several studies have reported that high fat diet (HFD) influenced Aβ accumulation and cognitive performance during AD pathology. However, the underlying neurobiological mechanisms have not yet been elucidated. OBJECTIVE: The objective of this study was to explore the underlying neurobiological mechanisms of HFD influenced Aβ accumulation and cognitive performance during AD pathology. METHODS: 2.5-month-old male APP/PS1 mice were randomly separated into two groups: 1) the normal diet (ND) group, fed a standard diet (10 kcal%fat); and 2) the HFD group, fed a high fat diet (40 kcal%fat, D12492; Research Diets). After 4 months of HFD or ND feeding, mice in the two groups were subjected for further ethological, morphological, and biochemical analyses. RESULTS: A long-term HFD diet significantly increased perirenal fat and impaired dendritic integrity and aggravated neurodegeneration, and augmented learning and memory deficits in APP/PS1 mice. Furthermore, the HFD increased beta amyloid cleaving enzyme 1 (BACE1) dephosphorylation and SUMOylation, resulting in enhanced enzyme activity and stability, which exacerbated the deposition of amyloid plaques. CONCLUSION: Our study demonstrates that long-term HFD consumption aggravates amyloid-β accumulation and cognitive impairments, and that modifiable lifestyle factors, such as obesity, can induce BACE1 post-modifications which may contribute to AD pathogenesis.

Hippocampal Functional Connectivity and Memory Performance After Exercise Intervention in Older Adults with Mild Cognitive Impairment. - Won, Junyeon; Callow, Daniel D; S Pena, Gabriel; Jordan, Leslie S; Arnold-Nedimala, Naomi A; Nielson, Kristy A; Smith, J Carson (J Alzheimers Dis, 2021)
BACKGROUND: Exercise training (ET) has neuroprotective effects in the hippocampus, a key brain region for memory that is vulnerable to age-related dysfunction. OBJECTIVE: We investigated the effects of ET on functional connectivity (FC) of the hippocampus in older adults with mild cognitive impairment (MCI) and a cognitively normal (CN) control group. We also assessed whether the ET-induced changes in hippocampal FC (Δhippocampal-FC) are associated with changes in memory task performance (Δmemory performance). METHODS: 32 older adults (77.0±7.6 years; 16 MCI and 16 CN) participated in the present study. Cardiorespiratory fitness tests, memory tasks (Rey Auditory Verbal Learning Test (RAVLT) and Logical Memory Test (LM)), and resting-state fMRI were administered before and after a 12-week walking ET intervention. We utilized a seed-based correlation analysis using the bilateral anterior and posterior hippocampi as priori seed regions of interest. The associations of residualized ET-induced Δhippocampal-FC and Δmemory performance were assessed using linear regression. RESULTS: There were significant improvements in RAVLT Trial 1 and LM test performance after ET across participants. At baseline, MCI, compared to CN, demonstrated significantly lower posterior hippocampal FC. ET was associated with increased hippocampal FC across groups. Greater ET-related anterior and posterior hippocampal FC with right posterior cingulate were associated with improved LM recognition performance in MCI participants. CONCLUSION: Our findings indicate that hippocampal FC is significantly increased following 12-weeks of ET in older adults and, moreover, suggest that increased hippocampal FC may reflect neural network plasticity associated with ET-related improvements in memory performance in individuals diagnosed with MCI.

In vivo Characterization of Biochemical Variants of Amyloid-β in Subjects with Idiopathic Normal Pressure Hydrocephalus and Alzheimer's Disease Neuropathological Change. - Libard, Sylwia; Walter, Jochen; Alafuzoff, Irina (J Alzheimers Dis, 2021)
BACKGROUND: Stepwise occurrence of biochemically modified amyloid-β (Aβ) in the brain of subjects with Alzheimer's disease (AD) has been suggested to be of significance for cognitive impairment. Our previous reports have shown that Aβ is observed in 63% of all subjects with idiopathic normal pressure hydrocephalus (iNPH) suggesting that the majority of iNPH subjects with Aβ are indeed also suffering from AD. OBJECTIVE: We assessed the occurrence of biochemically modified Aβ variants, in vivo, in subjects with iNPH and in a cohort of postmortem brain samples from patients with dementia. METHODS: We assessed Aβ proteins in 127 diagnostic brain biopsies obtained from subjects with iNPH and in a cohort of subjects with dementia by means of immunohistochemistry. RESULTS: The pyroglutamylated Aβ (pyAβ) precedes the aggregation of phosphorylated Aβ (pAβ) during the AD neuropathological change progression; moreover, these modified variants of Aβ correlate with hyperphosphorylated tau in the frontal cortical area of human brain. Our results confirm the existence of the suggested biochemical stages of Aβ aggregation that might be of significance for neurodegeneration leading to cognitive impairment. CONCLUSION: The observation that both pyAβ and pAβ are seen in vivo in iNPH subjects is intriguing. It has been reported that most of the iNPH subjects with Aβ in the brain biopsy indeed develop AD with time. Based on our current and previous results, it is clinically merited to obtain a diagnostic biopsy from a subject with iNPH. When Aβ is observed in the biopsy, the biochemical characterization is of interest.

Lipidomic Network of Mild Cognitive Impairment from the Mayo Clinic Study of Aging. - Wang, Xuewei; Bui, Hai; Vemuri, Prashanthi; Graff-Radford, Jonathan; Jack, Clifford R; Petersen, Ronald C; Mielke, Michelle M (J Alzheimers Dis, 2021)
BACKGROUND: Lipid alterations contribute to Alzheimer's disease (AD) pathogenesis. Lipidomics studies could help systematically characterize such alterations and identify potential biomarkers. OBJECTIVE: To identify lipids associated with mild cognitive impairment and amyloid-β deposition, and to examine lipid correlation patterns within phenotype groupsMethods:Eighty plasma lipids were measured using mass spectrometry for 1,255 non-demented participants enrolled in the Mayo Clinic Study of Aging. Individual lipids associated with mild cognitive impairment (MCI) were first identified. Correlation network analysis was then performed to identify lipid species with stable correlations across conditions. Finally, differential correlation network analysis was used to determine lipids with altered correlations between phenotype groups, specifically cognitively unimpaired versus MCI, and with elevated brain amyloid versus without. RESULTS: Seven lipids were associated with MCI after adjustment for age, sex, and APOE4. Lipid correlation network analysis revealed that lipids from a few species correlated well with each other, demonstrated by subnetworks of these lipids. 177 lipid pairs differently correlated between cognitively unimpaired and MCI patients, whereas 337 pairs of lipids exhibited altered correlation between patients with and without elevated brain amyloid. In particular, 51 lipid pairs showed correlation alterations by both cognitive status and brain amyloid. Interestingly, the lipids central to the network of these 51 lipid pairs were not significantly associated with either MCI or amyloid, suggesting network-based approaches could provide biological insights complementary to traditional association analyses. CONCLUSION: Our attempt to characterize the alterations of lipids at network-level provides additional insights beyond individual lipids, as shown by differential correlations in our study.

Loneliness, Not Social Support, Is Associated with Cognitive Decline and Dementia Across Two Longitudinal Population-Based Cohorts. - Freak-Poli, Rosanne; Wagemaker, Nina; Wang, Rui; Lysen, Thom S; Ikram, M Arfan; Vernooij, Meike W; Dintica, Christina S; Vernooij-Dassen, Myrra; Melis, Rene J M; Laukka, Erica J; Fratiglioni, Laura; Xu, Weili; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Poor social health is likely associated with cognitive decline and risk of dementia; however, studies show inconsistent results. Additionally, few studies separate social health components or control for mental health. OBJECTIVE: To investigate whether loneliness and social support are independently associated with cognitive decline and risk of dementia, and whether depressive symptoms confound the association. METHODS: We included 4,514 participants from the population-based Rotterdam Study (RS; aged 71±7SD years) followed up to 14 years (median 10.8, interquartile range 7.4-11.6), and 2,112 participants from the Swedish National Study on Aging and Care in Kungsholmen (SNAC-K; aged 72±10SD years) followed up to 10 years (mean 5.9±1.6SD). At baseline, participants were free of major depression and scored on the Mini-Mental State Examination (MMSE) ≥26 for RS and ≥25 for SNAC-K. We investigated loneliness, perceived social support, and structural social support (specifically marital status and number of children). In both cohorts, dementia was diagnosed and cognitive function was repeatedly assessed with MMSE and a global cognitive factor (g-factor). RESULTS: Loneliness was prospectively associated with a decline in the MMSE in both cohorts. Consistently, persons who were lonely had an increased risk of developing dementia (RS: HR 1.34, 95%CI 1.08-1.67; SNAC-K: HR 2.16, 95%CI 1.12-4.17). Adjustment for depressive symptoms and exclusion of the first 5 years of follow-up did not alter results. Neither perceived or structural social support was associated with cognitive decline or dementia risk. CONCLUSION: Loneliness, not social support, predicted cognitive decline and incident dementia independently of depressive symptoms.

Longitudinal Trajectories in Cortical Thickness and Volume Atrophy: Superior Cognitive Performance Does Not Protect Against Brain Atrophy in Older Adults. - Gardener, Samantha L; Weinborn, Michael; Sohrabi, Hamid R; Doecke, James D; Bourgeat, Pierrick; Rainey-Smith, Stephanie R; Shen, Kai-Kai; Fripp, Jurgen; Taddei, Kevin; Maruff, Paul; Salvado, Olivier; Savage, Greg; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Previous research has identified a small subgroup of older adults that maintain a high level of cognitive functioning well into advanced age. Investigation of those with superior cognitive performance (SCP) for their age is important, as age-related decline has previously been thought to be inevitable. OBJECTIVE: Preservation of cortical thickness and volume was evaluated in 76 older adults with SCP and 100 typical older adults (TOAs) assessed up to five times over six years. METHODS: Regions of interest (ROIs) found to have been associated with super-aging status (a construct similar to SCP status) in previous literature were investigated, followed by a discovery phase analyses of additional regions. SCPs were aged 70 + at baseline, scoring at/above normative memory (CVLT-II) levels for demographically similar individuals aged 30-44 years old, and in the unimpaired range for all other cognitive domains over the course of the study. RESULTS: In linear mixed models, following adjustment for multiple comparisons, there were no significant differences between rates of thinning or volume atrophy between SCPs and TOAs in previously identified ROIs, or the discovery phase analyses. With only amyloid-β negative individuals in the analyses, again there were no significant differences between SCPs and TOAs. CONCLUSION: The increased methodological rigor in classifying groups, together with the influence of cognitive reserve, are discussed as potential factors accounting for our findings as compared to the extant literature on those with superior cognitive performance for their age.

Longitudinally Increasing Elevated Asymmetric Flortaucipir Binding in a Cognitively Unimpaired Amyloid-Negative Older Individual. - Schwarz, Christopher G; Knopman, David S; Ramanan, Vijay K; Lowe, Val J; Wiste, Heather J; Cogswell, Petrice M; Utianski, Rene L; Senjem, Matthew L; Gunter, Jeffrey R; Vemuri, Prashanthi; Petersen, Ronald C; Jack, Clifford R (J Alzheimers Dis, 2021)
We present the case of a cognitively unimpaired 77-year-old man with elevated, asymmetric, and longitudinally increasing Flortaucipir tau PET despite normal (visually negative) amyloid PET. His atypical tau PET signal persisted and globally increased in a follow-up scan five years later. Across eight years of observations, temporoparietal atrophy was observed consistent with tau PET patterns, but he retained the cognitively unimpaired classification. Altogether, his atypical tau PET signal is not explained by any known risk factors or alternative pathologies, and other imaging findings were not remarkable. He remains enrolled for further observation.

Lung Function Impairment and the Risk of Incident Dementia: The Rotterdam Study. - Xiao, Tian; Wijnant, Sara R A; Licher, Silvan; Terzikhan, Natalie; Lahousse, Lies; Ikram, M Kamran; Brusselle, Guy G; Ikram, M Arfan (J Alzheimers Dis, 2021)
BACKGROUND: The etiology of dementia may partly be underpinned by impaired lung function via systemic inflammation and hypoxia. OBJECTIVE: To prospectively examine the association between chronic obstructive pulmonary disease (COPD) and subclinical impairments in lung function and the risk of dementia. METHODS: In the Rotterdam Study, we assessed the risk of incident dementia in participants with Preserved Ratio Impaired Spirometry (PRISm; FEV1/FVC≥0.7, FEV1 < 80% predicted) and in participants with COPD (FEV1/FVC < 0.7) compared to those with normal spirometry (controls; FEV1/FVC≥0.7, FEV1≥80% predicted). Hazard ratios (HRs) with 95% confidence intervals (CI) for dementia were adjusted for age, sex, education attainment, smoking status, systolic blood pressure, body mass index, triglycerides, comorbidities and Apolipoprotein E (APOE) genotype. RESULTS: Of 4,765 participants, 110 (2.3%) developed dementia after 3.3 years. Compared to controls, participants with PRISm, but not COPD, had an increased risk for all-type dementia (adjusted HRPRISm 2.70; 95% CI, 1.53-4.75; adjusted HRCOPD 1.03; 95% CI, 0.61-1.74). These findings were primarily driven by men and smokers. Similarly, participants with FVC% predicted values in the lowest quartile compared to those in the highest quartile were at increased risk of all-type dementia (adjusted HR 2.28; 95% CI, 1.31-3.98), as well as Alzheimer's disease (AD; adjusted HR 2.13; 95% CI, 1.13-4.02). CONCLUSION: Participants with PRISm or a low FVC% predicted lung function were at increased risk of dementia, compared to those with normal spirometry or a higher FVC% predicted, respectively. Further research is needed to elucidate whether this association is causal and how PRISm might contribute to dementia pathogenesis.

Mitochondrial Membrane Potential Influences Amyloid-β Protein Precursor Localization and Amyloid-β Secretion. - Wilkins, Heather M; Troutwine, Benjamin R; Menta, Blaise W; Manley, Sharon J; Strope, Taylor A; Lysaker, Colton R; Swerdlow, Russell H (J Alzheimers Dis, 2021)
BACKGROUND: Amyloid-β (Aβ), which derives from the amyloid-β protein precursor (AβPP), forms plaques and serves as a fluid biomarker in Alzheimer's disease (AD). How Aβ forms from AβPP is known, but questions relating to AβPP and Aβ biology remain unanswered. AD patients show mitochondrial dysfunction, and an Aβ/AβPP mitochondria relationship exists. OBJECTIVE: We considered how mitochondrial biology may impact AβPP and Aβ biology. METHODS: SH-SY5Y cells were transfected AβPP constructs. After treatment with FCCP (uncoupler), Oligomycin (ATP synthase inhibitor), or starvation Aβ levels were measured. β-secretase (BACE1) expression was measured. Mitochondrial localized full-length AβPP was also measured. All parameters listed were measured in ρ0 cells on an SH-SY5Y background. iPSC derived neurons were also used to verify key results. RESULTS: We showed that mitochondrial depolarization routes AβPP to, while hyperpolarization routes AβPP away from, the organelle. Mitochondrial AβPP and cell Aβ secretion inversely correlate, as cells with more mitochondrial AβPP secrete less Aβ, and cells with less mitochondrial AβPP secrete more Aβ. An inverse relationship between secreted/extracellular Aβ and intracellular Aβ was observed. CONCLUSION: Our findings indicate mitochondrial function alters AβPP localization and suggest enhanced mitochondrial activity promote Aβ secretion while depressed mitochondrial activity minimize Aβ secretion. Our data complement other studies that indicate a mitochondrial, AβPP, and Aβ nexus, and could help explain why cerebrospinal fluid Aβ is lower in those with AD. Our data further suggest Aβ secretion could serve as a biomarker of cell or tissue mitochondrial function.

Mortality After Ischemic Stroke in Patients with Alzheimer's Disease Dementia and Other Dementia Disorders. - Zupanic, Eva; von Euler, Mia; Winblad, Bengt; Xu, Hong; Secnik, Juraj; Kramberger, Milica Gregoric; Religa, Dorota; Norrving, Bo; Garcia-Ptacek, Sara (J Alzheimers Dis, 2021)
BACKGROUND: Stroke and dementia are interrelated diseases and risk for both increases with age. Even though stroke incidence and age-standardized death rates have decreased due to prevention of stroke risk factors, increased utilization of reperfusion therapies, and other changes in healthcare, the absolute numbers are increasing due to population growth and aging. OBJECTIVE: To analyze predictors of death after stroke in patients with dementia and investigate possible time and treatment trends. METHODS: A national longitudinal cohort study 2007-2017 using Swedish national registries. We compared 12,629 ischemic stroke events in patients with dementia with matched 57,954 stroke events in non-dementia controls in different aspects of patient care and mortality. Relationship between dementia status and dementia type (Alzheimer's disease and mixed dementia, vascular dementia, other dementias) and death was analyzed using Cox regressions. RESULTS: Differences in receiving intravenous thrombolysis between patients with and without dementia disappeared after the year 2015 (administered to 11.1% dementia versus 12.3% non-dementia patients, p = 0.117). One year after stroke, nearly 50% dementia and 30% non-dementia patients had died. After adjustment for demographics, mobility, nursing home placement, and comorbidity index, dementia was an independent predictor of death compared with non-dementia patients (HR 1.26 [1.23-1.29]). CONCLUSION: Dementia before ischemic stroke is an independent predictor of death. Over time, early and delayed mortality in patients with dementia remained increased, regardless of dementia type. Patients with≤80 years with prior Alzheimer's disease or mixed dementia had higher mortality rates after stroke compared to patients with prior vascular dementia.
Keywords: Aged; Aged, 80 and over; Comorbidity; Dementia; Female; Fibrinolytic Agents; Humans; Incidence; Ischemic Stroke; Male; Registries; Survival Rate; Sweden; Thrombolytic Therapy

Multiple Neurodegenerative Pathologies in an Alzheimer's Disease Patient Treated with Fornical Deep Brain Stimulation. - White, Bartholomew; Lyketsos, Constantine G; Rosenberg, Paul B; Oh, Esther S; Chen, Liam (J Alzheimers Dis, 2021)
As an established treatment for movement disorders, deep brain stimulation (DBS) has been adapted for the treatment of Alzheimer's disease (AD) by modulating fornix activity. Although it is generally regarded as a safe intervention in patients over 65 years of age, the complex neurophysiology and interconnection within circuits connected to the fornix warrants a careful ongoing evaluation of the true benefit and risk potential of DBS on slowing cognitive decline in AD patients. Here we report on a patient who died long after being implanted with a DBS device who donated her brain for neuropathologic study. The autopsy confirmed multiple proteinopathies including AD-related change, diffuse neocortical Lewy body disease, TDP-43 proteinopathy, and a nonspecific tauopathy. We discuss the possible mechanisms of these overlapping neurodegenerative disorders and caution that future studies of DBS for AD will need to take these findings into consideration.

Mutations in the Amyloid-β Protein Precursor Reduce Mitochondrial Function and Alter Gene Expression Independent of 42-Residue Amyloid-β Peptide. - Pope, Chad A; Wilkins, Heather M; Swerdlow, Russell H; Wolfe, Michael S (J Alzheimers Dis, 2021)
BACKGROUND: Dominant missense mutations in the amyloid-β protein precursor (AβPP) cause early-onset familial Alzheimer's disease (FAD) and are associated with changes in the production or properties of the amyloid-β peptide (Aβ), particularly of the 42-residue variant (Aβ 42) that deposits in the Alzheimer's disease (AD) brain. Recent findings, however, show that FAD mutations in AβPP also lead to increased production of longer Aβ variants of 45-49 residues in length. OBJECTIVE: We aimed to test neurotoxicity of Aβ 42 vis-á-vis longer variants, focusing specifically on mitochondrial function, as dysfunctional mitochondria are implicated in the pathogenesis of AD. METHODS: We generated SH-SY5Y human neuroblastoma cells stably expressing AβPP mutations that lead to increased production of long Aβ peptides with or without Aβ 42. These AβPP-expressing cells were tested for oxygen consumption rates (OCR) under different conditions designed to interrogate mitochondrial function. These cell lines were also examined for expression of genes important for mitochondrial or neuronal structure and function. RESULTS: The mutant AβPP-expressing cells showed decreased basal OCRs as well as decreased OCRs associated with mitochondrial ATP production, even more so in the absence of Aβ 42 production. Moreover, mutant AβPP-expressing cells producing longer forms of Aβ displayed altered expression of certain mitochondrial- and neuronal-associated genes, whether or not Aβ 42 was produced. CONCLUSION: These findings suggest that mutant AβPP can cause mitochondrial dysfunction that is associated with long Aβ but not with Aβ 42.

Neurotrophic Treatment Initiated During Early Postnatal Development Prevents the Alzheimer-Like Behavior and Synaptic Dysfunction. - Wei, Wei; Liu, Yinghua; Dai, Chunling; Baazaoui, Narjes; Tung, Yunn-Chyn; Liu, Fei; Iqbal, Khalid (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by impairments in synaptic plasticity and cognitive performance. Cognitive dysfunction and loss of neuronal plasticity are known to begin decades before the clinical diagnosis of the disease. The important influence of congenital genetic mutations on the early development of AD provides a novel opportunity to initiate treatment during early development to prevent the Alzheimer-like behavior and synaptic dysfunction. OBJECTIVE: To explore strategies for early intervention to prevent Alzheimer's disease. METHODS: In the present study, we investigated the effect of treatment during early development with a ciliary neurotrophic factor (CNTF) derived peptidergic compound, P021 (Ac-DGGLAG-NH2) on cognitive function and synaptic plasticity in 3xTg-AD transgenic mouse model of AD. 3xTg-AD and genetic background-matched wild type female mice were treated from birth to postnatal day 120 with P021 in diet or as a control with vehicle diet, and cognitive function and molecular markers of neuroplasticity were evaluated. RESULTS: P021 treatment during early development prevented cognitive impairment and increased expressions of pCREB and BDNF that activated downstream various signaling cascades such as PLC/PKC, MEK/ERK and PI3K/Akt, and ameliorated synaptic protein deficit in 4-month-old 3xTg-AD mice. CONCLUSION: These findings indicate that treatment with the neurotrophic peptide mimetic such as P021 during early development can be an effective therapeutic strategy to rescue synaptic deficit and cognitive impairment in familial AD and related tauopathies.

Paraoxonase 1, B Vitamins Supplementation, and Mild Cognitive Impairment. - Perła-Kaján, Joanna; Włoczkowska, Olga; Zioła-Frankowska, Anetta; Frankowski, Marcin; David Smith, A; de Jager, Celeste A; Refsum, Helga; Jakubowski, Hieronim (J Alzheimers Dis, 2021)
BACKGROUND: Identification of modifiable risk factors that affect cognitive decline is important for the development of preventive and treatment strategies. Status of paraoxonase 1 (PON1), a high-density lipoprotein-associated enzyme, may play a role in the development of neurological diseases, including Alzheimer's disease. OBJECTIVE: We tested a hypothesis that PON1 status predicts cognition in individuals with mild cognitive impairment (MCI). METHODS: Individuals with MCI (n = 196, 76.8-years-old, 60% women) participating in a randomized, double-blind placebo-controlled trial (VITACOG) were assigned to receive a daily dose of folic acid (0.8 mg), vitamin B12 (0.5 mg) and B6 (20 mg) (n = 95) or placebo (n = 101) for 2 years. Cognition was analyzed by neuropsychological tests. Brain atrophy was quantified in a subset of participants (n = 168) by MRI. PON1 status, including PON1 Q192R genotype, was determined by quantifying enzymatic activity of PON1 using paraoxon and phenyl acetate as substrates. RESULTS: In the placebo group, baseline phenylacetate hydrolase (PhAcase) activity of PON1 (but not paraoxonase activity or PON1 Q192R genotype) was significantly associated with global cognition (Mini-Mental State Examination, MMSE; Telephone Inventory for Cognitive Status-modified, TICS-m), verbal episodic memory (Hopkins Verbal Learning Test-revised: Total Recall, HVLT-TR; Delayed Recall, HVLT-DR), and attention/processing speed (Trail Making A and Symbol Digits Modalities Test, SDMT) at the end of study. In addition to PhAcase, baseline iron and triglycerides predicted MMSE, baseline fatty acids predicted SDMT, baseline anti-N-Hcy-protein autoantibodies predicted TICS-m, SDMT, Trail Making A, while BDNF V66M genotype predicted HVLT-TR and HVLT-DR scores at the end of study. B-vitamins abrogated associations of PON1 and other variables with cognition. CONCLUSION: PON1 is a new factor associated with impaired cognition that can be ameliorated by B-vitamins in individuals with MCI.

Physical Activity and Trajectory of Cognitive Change in Older Persons: Mayo Clinic Study of Aging. - Krell-Roesch, Janina; Syrjanen, Jeremy A; Bezold, Jelena; Trautwein, Sandra; Barisch-Fritz, Bettina; Boes, Klaus; Woll, Alexander; Forzani, Erica; Kremers, Walter K; Machulda, Mary M; Mielke, Michelle M; Knopman, David S; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Little is known about the association between physical activity (PA) and cognitive trajectories in older adults. OBJECTIVE: To examine the association between PA and change in memory, language, attention, visuospatial skills, and global cognition, and a potential impact of sex or Apolipoprotein E (APOE) ɛ4 status. METHODS: Longitudinal study derived from the population-based Mayo Clinic Study of Aging, including 2,060 cognitively unimpaired males and females aged ≥70 years. Engagement in midlife (ages 50-65) and late-life (last year) PA was assessed using a questionnaire. Neuropsychological testing was done every 15 months (mean follow-up 5.8 years). We ran linear mixed-effect models to examine whether mid- or late-life PA at three intensities (mild, moderate, vigorous) was associated with cognitive z-scores. RESULTS: Light intensity midlife PA was associated with less decline in memory function compared to the no-PA reference group (time x light PA; estimate [standard error] 0.047 [0.016], p = 0.004). Vigorous late-life PA was associated with less decline in language (0.033 [0.015], p = 0.030), attention (0.032 [0.017], p = 0.050), and global cognition (0.039 [0.016], p = 0.012). Females who were physically inactive in midlife experienced more pronounced cognitive decline than females physically active in midlife and males regardless of PA (p-values for time interaction terms with midlife PA levels and sex were all p <  0.05 for global cognition). APOE ɛ4 carriership did not moderate the association between PA and cognition. CONCLUSION: Engaging in PA, particularly of vigorous intensity in late-life, was associated with less pronounced decline in global and domain-specific cognition. This association may differ by sex.

Plasma Total-Tau and Neurofilament Light Chain as Diagnostic Biomarkers of Alzheimer's Disease Dementia and Mild Cognitive Impairment in Adults with Down Syndrome. - Petersen, Melissa E; Rafii, Michael S; Zhang, Fan; Hall, James; Julovich, David; Ances, Beau M; Schupf, Nicole; Krinsky-McHale, Sharon J; Mapstone, Mark; Silverman, Wayne; Lott, Ira; Klunk, William; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The need for diagnostic biomarkers of cognitive decline is particularly important among aging adults with Down syndrome (DS). Growing empirical support has identified the utility of plasma derived biomarkers among neurotypical adults with mild cognitive impairment (MCI) and Alzheimer's disease (AD); however, the application of such biomarkers has been limited among the DS population. OBJECTIVE: This study aimed to investigate the cross-sectional diagnostic performance of plasma neurofilament light chain (Nf-L) and total-tau, individually and in combination among a cohort of DS adults. METHODS: Plasma samples were analyzed from n = 305 (n = 225 cognitively stable (CS); n = 44 MCI-DS; n = 36 DS-AD) participants enrolled in the Alzheimer's Biomarker Consortium -Down Syndrome. RESULTS: In distinguishing DS-AD participants from CS, Nf-L alone produced an AUC of 90%, total-tau alone reached 74%, and combined reached an AUC of 86%. When age and gender were included, AUC increased to 93%. Higher values of Nf-L, total-tau, and age were all shown to be associated with increased risk for DS-AD. When distinguishing MCI-DS participants from CS, Nf-L alone produced an AUC of 65%, while total-tau alone reached 56%. A combined model with Nf-L, total-tau, age, and gender produced an AUC of 87%. Both higher values in age and total-tau were found to increase risk for MCI-DS; Nf-L levels were not associated with increased risk for MCI-DS. CONCLUSION: Advanced assay techniques make total-tau and particularly Nf-L useful biomarkers of both AD pathology and clinical status in DS and have the potential to serve as outcome measures in clinical trials for future disease-modifying drugs.

Porphyromonas Gingivalis Infection Induces Synaptic Failure via Increased IL-1β Production in Leptomeningeal Cells. - Huang, Wanyi; Zeng, Fan; Gu, Yebo; Jiang, Muzhou; Zhang, Xinwen; Yan, Xu; Kadowaki, Tomoko; Mizutani, Shinsuke; Kashiwazaki, Haruhiko; Ni, Junjun; Wu, Zhou (J Alzheimers Dis, 2021)
BACKGROUND: Studies have reported that synaptic failure occurs before the Alzheimer's disease (AD) onset. The systemic Porphyromonas gingivalis (P. gingivalis) infection is involved in memory decline. We previously showed that leptomeningeal cells, covering the brain, activate glial cells by releasing IL-1β in response to systemic inflammation. OBJECTIVE: In the present study, we focused on the impact of leptomeningeal cells on neurons during systemic P. gingivalis infection. METHODS: The responses of leptomeningeal cells and cortical neurons to systemic P. gingivalis infection were examined in 15-month-old mice. The mechanism of IL-1β production by P. gingivalis infected leptomeningeal cells was examined, and primary cortical neurons were treated with P. gingivalis infected leptomeningeal cells condition medium (Pg LCM). RESULTS: Systemic P. gingivalis infection increased the expression of IL-1β in leptomeninges and reduced the synaptophysin (SYP) expression in leptomeninges proximity cortex in mice. Leptomeningeal cells phagocytosed P. gingivalis resulting in lysosomal rupture and Cathepsin B (CatB) leakage. Leaked CatB mediated NLRP3 inflammasome activation inducing IL-1β secretion in leptomeningeal cells. Pg LCM decreased the expression of synaptic molecules, including SYP, which was inhibited by an IL-1 receptor antagonist pre-treatment. CONCLUSION: These observations demonstrate that P. gingivalis infection is involved in synaptic failure by inducing CatB/NLRP3 inflammasome-mediated IL-1β production in leptomeningeal cells. The periodontal bacteria-induced synaptic damage may accelerate the onset and cognitive decline of AD.

Porphyromonas gingivalis (W83) Infection Induces Alzheimer's Disease-Like Pathophysiology in Obese and Diabetic Mice. - Bahar, Bojlul; Kanagasingam, Shalini; Tambuwala, Murtaza M; Aljabali, Alaa A A; Dillon, Stephanie A; Doaei, Saeid; Welbury, Richard; Chukkapalli, Sasanka S; Singhrao, Sim K (J Alzheimers Dis, 2021)
BACKGROUND: Periodontal disease(s) and metabolic illnesses negatively impact the quality of life and, eventually mental health. OBJECTIVE: This study investigated the effect of Porphyromonas gingivalis (W83) oral infection on the development of Alzheimer's disease (AD) pathophysiology in a wild-type obese, diabetic (db/db) mouse model. METHODS: The db/db mice were either orally infected with P. gingivalis and Fusobacterium nucleatum or sham infected for 16 weeks. The presence of amyloid-β (Aβ) and neurofibrillary tangles (NFTs) were assessed using a silver impregnation technique and subsequently by immunohistochemistry for tau and neuroinflammation. The mRNA abundance of a panel of 184 genes was performed using quantitative real-time PCR, and the differentially expressed genes were analyzed by Ingenuity Pathway Analysis. RESULTS: While no Aβ plaques and NFTs were evident by silver impregnation, immunohistochemistry (glial cell markers) of the P. gingivalis-infected mice tissue sections exhibited neuroinflammation in the form of reactive microglia and astrocytes. Anti-tau immunopositivity, in addition to cells, was prominent in thickened axons of hippocampal CA neurons. The mRNA abundance of crucial genes in the insulin signaling pathway (INSR, IGF1, IRS, IDE, PIK3R, SGK1, GYS, GSK3B, AKT1) were upregulated, potentially exacerbating insulin resistance in the brain by P. gingivalis oral infection. Increased mRNA abundance of several kinases, membrane receptors, transcription factors, and pro-inflammatory mediators indicated hyperactivation of intracellular cascades with potential for tau phosphorylation and Aβ release in the same infection group. CONCLUSION: P. gingivalis W83 infection of db/db mice provides a disease co-morbidity model with the potential to reproduce AD pathophysiology with induced periodontal disease.

Possible Role of Activin in the Adiponectin Paradox-Induced Progress of Alzheimer's Disease. - Hashimoto, Makoto; Ho, Gilbert; Sugama, Shuei; Takenouchi, Takato; Waragai, Masaaki; Sugino, Hiromu; Inoue, Satoshi; Masliah, Eliezer (J Alzheimers Dis, 2021)
Accumulating evidence suggests that the adiponectin (APN) paradox might be involved in promoting aging-associated chronic diseases such as Alzheimer's disease (AD). In human brain, APN regulation of the evolvability of amyloidogenic proteins (APs), including amyloid-β (Aβ) and tau, in developmental/reproductive stages, might be paradoxically manifest as APN stimulation of AD through antagonistic pleiotropy in aging. The unique mechanisms underlying APN activity remain unclear, a better understanding of which might provide clues for AD therapy. In this paper, we discuss the possible relevance of activin, a member of transforming growth factor β (TGFβ) superfamily of peptides, to antagonistic pleiotropy effects of APN. Notably, activin, a multiple regulator of cell proliferation and differentiation, as well as an endocrine modulator in reproduction and an organizer in early development, might promote aging-associated disorders, such as inflammation and cancer. Indeed, serum activin, but not serum TGFβ increases during aging. Also, activin/TGFβ signal through type II and type I receptors, both of which are transmembrane serine/threonine kinases, and the serine/threonine phosphorylation of APs, including Aβ 42 serine 8 and αS serine 129, may confer pathological significance in neurodegenerative diseases. Moreover, activin expression is induced by APN in monocytes and hepatocytes, suggesting that activin might be situated downstream of the APN paradox. Finally, a meta-analysis of genome-wide association studies demonstrated that two SNPs relevant to the activin/TGFβ receptor signaling pathways conferred risk for major aging-associated disease. Collectively, activin might be involved in the APN paradox of AD and could be a significant therapeutic target.

The Potential Role of Ferroptosis in Alzheimer's Disease. - Zhang, Guimei; Zhang, Yaru; Shen, Yanxin; Wang, Yongchun; Zhao, Meng; Sun, Li (J Alzheimers Dis, 2021)
Alzheimer's disease (AD) is the most prevalent cause of dementia, accounting for approximately 60%-80%of all cases. Although much effort has been made over the years, the precise mechanism of AD has not been completely elucidated. Recently, great attention has shifted to the roles of iron metabolism, lipid peroxidation, and oxidative stress in AD pathogenesis. We also note that these pathological events are the vital regulators of a novel regulatory cell death, termed ferroptosis-an iron-dependent, oxidative, non-apoptotic cell death. Ferroptosis differs from apoptosis, necrosis, and autophagy with respect to morphology, biochemistry, and genetics. Mounting evidence suggests that ferroptosis may be involved in neurological disorders, including AD. Here, we review the underlying mechanisms of ferroptosis; discuss the potential interaction between AD and ferroptosis in terms of iron metabolism, lipid peroxidation, and the glutathione/glutathione peroxidase 4 axis; and describe some associated studies that have explored the implication of ferroptosis in AD.
Keywords: Alzheimer Disease; Animals; Ferroptosis; Humans

Predictors of Mild Cognitive Impairment Stability, Progression, or Reversion in the Lothian Birth Cohort 1936. - Welstead, Miles; Luciano, Michelle; Muniz-Terrera, Graciela; Saunders, Stina; Mullin, Donncha S; Russ, Tom C (J Alzheimers Dis, 2021)
BACKGROUND: Mild cognitive impairment (MCI) describes a borderland between healthy cognition and dementia. Progression to and reversion from MCI is relatively common but more research is required to understand the factors affecting this fluidity and improve clinical care interventions. OBJECTIVE: We explore these transitions in MCI status and their predictive factors over a six-year period in a highly-phenotyped longitudinal study, the Lothian Birth Cohort 1936. METHODS: MCI status was derived in the LBC1936 at ages 76 (n = 567) and 82 years (n = 341) using NIA-AA diagnostic guidelines. Progressions and reversions between healthy cognition and MCI over the follow-up period were assessed. Multinomial logistic regression assessed the effect of various predictors on the likelihood of progressing, reverting, or maintaining cognitive status. RESULTS: Of the 292 participants who completed both time points, 41 (14%) participants had MCI at T1 and 56 (19%) at T2. Over the follow-up period, 74%remained cognitively healthy, 12%transitioned to MCI, 7%reverted to healthy cognition, and 7%maintained their baseline MCI status. Findings indicated that membership of these transition groups was affected by age, cardiovascular disease, and number of depressive symptoms. CONCLUSION: Findings that higher baseline depressive symptoms increase the likelihood of reverting from MCI to healthy cognition indicate that there may be an important role for the treatment of depression for those with MCI. However, further research is required to identify prevention strategies for those at high risk of MCI and inform effective interventions that increase the likelihood of reversion to, and maintenance of healthy cognition.

Proteome Profiling Identified Amyloid-β Protein Precursor as a Novel Binding Partner and Modulator of VGLUT1. - Zhou, Jin-Wu; Zhao, Man; Rang, Wen-Liang; Zhang, Xiao-Yan; Liu, Zhen-Ming; Zhang, Liang-Ren; Wang, Tong-Xing; Wu, Chu-Tse; Cheng, Xiao-Rui; Zhou, Wen-Xia (J Alzheimers Dis, 2021)
BACKGROUND: The toxicity of excessive glutamate release has been implicated in various acute and chronic neurodegenerative conditions. Vesicular glutamate transporters (VGLUTs) are the major mediators for the uptake of glutamate into synaptic vesicles. However, the dynamics and mechanism of this process in glutamatergic neurons are still largely unknown. OBJECTIVE: This study aimed to investigate the candidate protein partners of VGLUT1 and their regulatory roles in the vesicles in rat brain. METHODS: Pull down assay, co-immunoprecipitation assay, or split-ubiquitin membrane yeast two hybrid screening coupled with nanoRPLC-MS/MS were used to identify the candidate protein partners of VGLUT1 in the vesicles in rat brain. The in vitro and in vivo models were used to test effects of AβPP, Atp6ap2, Gja1, and Synataxin on VGLUT1 expression. RESULTS: A total of 255 and 225 proteins and 172 known genes were identified in the pull down assay, co-immunoprecipitation assay, or split-ubiquitin yeast two-hybrid screening respectively. The physiological interactions of SV2A, Syntaxin 12, Gja1, AβPP, and Atp6ap2 to VGLUT1 were further confirmed. Knockdown of Atp6ap2, Gja1, and Synataxin increased VGLUT1 mRNA expression and only knockdown of AβPP increased both mRNA and protein levels of VGLUT1 in PC12 cells. The regulatory function of AβPP on VGLUT1 expression was further confirmed in the in vitro and in vivo models. CONCLUSION: These results elucidate that the AβPP and VGLUT1 interacts at vesicular level and AβPP plays a role in the regulation of VGLUT1 expression which is essential for maintaining vesicular activities.

Quantifying and Examining Reserve in Symptomatic Former National Football League Players. - Foley, Éimear M; Tripodis, Yorghos; Yhang, Eukyung; Koerte, Inga K; Martin, Brett M; Palmisano, Joseph; Makris, Nikos; Schultz, Vivian; Lepage, Chris; Muehlmann, Marc; Wróbel, Paweł P; Guenette, Jeffrey P; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Repetitive head impacts (RHI) from contact sports have been associated with cognitive and neuropsychiatric disorders. However, not all individuals exposed to RHI develop such disorders. This may be explained by the reserve hypothesis. It remains unclear if the reserve hypothesis accounts for the heterogenous symptom presentation in RHI-exposed individuals. Moreover, optimal measurement of reserve in this population is unclear and likely unique from non-athlete populations. OBJECTIVE: We examined the association between metrics of reserve and cognitive and neuropsychiatric functioning in 89 symptomatic former National Football League players. METHODS: Individual-level proxies (e.g., education) defined reserve. We additionally quantified reserve as remaining residual variance in 1) episodic memory and 2) executive functioning performance, after accounting for demographics and brain pathology. Associations between reserve metrics and cognitive and neuropsychiatric functioning were examined. RESULTS: Higher reading ability was associated with better attention/information processing (β=0.25; 95% CI, 0.05-0.46), episodic memory (β=0.27; 95% CI, 0.06-0.48), semantic and phonemic fluency (β=0.24; 95% CI, 0.02-0.46; β=0.38; 95% CI, 0.17-0.59), and behavioral regulation (β=-0.26; 95% CI, -0.48, -0.03) performance. There were no effects for other individual-level proxies. Residual episodic memory variance was associated with better attention/information processing (β=0.45; 95% CI, 0.25, 0.65), executive functioning (β=0.36; 95% CI, 0.15, 0.57), and semantic fluency (β=0.38; 95% CI, 0.17, 0.59) performance. Residual executive functioning variance was associated with better attention/information processing (β=0.44; 95% CI, 0.24, 0.64) and episodic memory (β=0.37; 95% CI, 0.16, 0.58) performance. CONCLUSION: Traditional reserve proxies (e.g., years of education, occupational attainment) have limitations and may be unsuitable for use in elite athlete samples. Alternative approaches of reserve quantification may prove more suitable for this population.

Race/Ethnic Disparities in Mild Cognitive Impairment and Dementia: The Northern Manhattan Study. - Wright, Clinton B; DeRosa, Janet T; Moon, Michelle P; Strobino, Kevin; DeCarli, Charles; Cheung, Ying Kuen; Assuras, Stephanie; Levin, Bonnie; Stern, Yaakov; Sun, Xiaoyan; Rundek, Tatjana; Elkind, Mitchell S V; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Variability in dementia rates across racial and ethnic groups has been estimated at 60%. Studies suggest disparities in Caribbean Hispanic and Black populations, but community-based data are limited. OBJECTIVE: Estimate the prevalence of mild cognitive impairment (MCI) and dementia in the racially and ethnically diverse community-based Northern Manhattan Study cohort and examine sociodemographic, vascular risk factor, and brain imaging correlates. METHODS: Cases of MCI and dementia were adjudicated by a team of neuropsychologists and neurologists and prevalence was estimated across race/ethnic groups. Ordinal proportional odds models were used to estimate race/ethnic differences in the prevalence of MCI or dementia adjusting for sociodemographic variables (model 1), model 1 plus potentially modifiable vascular risk factors (model 2), and model 1 plus structural imaging markers of brain integrity (model 3). RESULTS: There were 989 participants with cognitive outcome determinations (mean age 69±9 years; 68% Hispanic, 16% Black, 14% White; 62% women; mean (±SD) follow-up five (±0.6) years). Hispanic and Black participants had greater likelihood of MCI (20%) and dementia (5%) than White participants accounting for age and education differences. Hispanic participants had greater odds of MCI or dementia than both White and Black participants adjusting for sociodemographic variables, vascular risk factors, and brain imaging factors. White matter hyperintensity burden was significantly associated with greater odds of MCI or dementia (OR = 1.3, 1.1 to 1.6), but there was no significant interaction by race/ethnicity. CONCLUSION: In this diverse community-based cohort, cross-sectional data revealed significant race/ethnic disparities in the prevalence of MCI and dementia. Longer follow-up and incidence data are needed to further clarify these relationships.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Cohort Studies; Cross-Sectional Studies; Dementia; Ethnicity; Female; Humans; Male; Middle Aged; New York City; Prevalence

Race-Related Association between APOE Genotype and Alzheimer's Disease: A Systematic Review and Meta-Analysis. - Qin, Wei; Li, Wenwen; Wang, Qi; Gong, Min; Li, Tingting; Shi, Yuqing; Song, Yang; Li, Ying; Li, Fangyu; Jia, Jianping (J Alzheimers Dis, 2021)
BACKGROUND: The global race-dependent association of Alzheimer's disease (AD) and apolipoprotein E (APOE) genotype is not well understood. Transethnic analysis of APOE could clarify the role of genetics in AD risk across populations. OBJECTIVE: This study aims to determine how race and APOE genotype affect the risks for AD. METHODS: We performed a systematic search of PubMed, Embase, Web of Science, and the Cochrane Library since 1993 to Aug 25, 2020. A total of 10,395 reports were identified, and 133 were eligible for analysis with data on 77,402 participants. Studies contained AD clinical diagnostic and APOE genotype data. Homogeneous data sets were pooled in case-control analyses. Odds ratios and 95% confidence intervals for developing AD were calculated for populations of different races and APOE genotypes. RESULTS: The proportion of APOE genotypes and alleles differed between populations of different races. Results showed that APOEɛ4 was a risk factor for AD, whereas APOEɛ2 protected against it. The effects of APOEɛ4 and ɛ2 on AD risk were distinct in various races, and they were substantially attenuated among Black people. Sub-group analysis found a higher frequency of APOEɛ4/ɛ4 and lower frequency of APOEɛ3/ɛ3 among early-onset AD than late-onset AD in a combined group and different races. CONCLUSION: Our meta-analysis suggests that the association of APOE genotypes and AD differ among races. These results enhance our understanding of APOE-related risk for AD across race backgrounds and provide new insights into precision medicine for AD.
Keywords: Alleles; Alzheimer Disease; Apolipoprotein E2; Apolipoprotein E4; Apolipoproteins E; Genotype; Humans; Racial Groups

Relation of Literacy and Music Literacy to Dementia in Older Black and White Brazilians. - Capuano, Ana W; Wilson, Robert S; Leurgans, Sue E; Sampaio, Carolina; Farfel, Jose M; Barnes, Lisa L; Bennett, David A (J Alzheimers Dis, 2021)
BACKGROUND: Literacy is more consistently reported than education as protective against dementia in developing regions. OBJECTIVE: To study the association of verbal literacy, numeracy, and music literacy with dementia in older Black and White Brazilians with a broad spectrum of education. METHODS: We studied 1,818 Black, Mixed-race, and White deceased Brazilians 65 years or older at death (mean = 79.64). Data were retrospectively obtained within 36 hours after death in a face-to-face interview with an informant, usually a family member. Dementia was classified using the Clinical Dementia Rating (CDR) scale. Three forms of literacy were ascertained: verbal literacy (10 questions: reading and writing), numeracy (3 questions: multiplication, percentages, and use of a calculator), and music literacy (1 question: reading music). Black (11%) and Mixed-race (23%) older adults were combined in analyses. Models adjusted for age and sex. RESULTS: Dementia was identified in 531 people. Participants had 0 to 25 years of education (median = 4). More literacy was associated with lower odds of dementia (all p≤0.039). Participants that read music had about half the odds of having dementia. Participants in the highest quartile of numeracy and verbal literacy had respectively 27%and 15%lower odds of having dementia compared to the lowest quartile. Literacy was lower in Blacks (p <  0.001, except music p = 0.894) but the effect of literacy on dementia was similar (interaction p >  0.237). In secondary analyses, playing instruments without reading music was not associated with dementia (p = 0.887). CONCLUSION: In a large sample of Brazilians, verbal literacy, numeracy, and music literacy were associated with lower odds of dementia. The effect was similar across races.

The Relationship Between Cardiovascular Health and Rate of Cognitive Decline in Young-Old and Old-Old Adults: A Population-Based Study. - Speh, Andreja; Wang, Rui; Winblad, Bengt; Kramberger, Milica G; Bäckman, Lars; Qiu, Chengxuan; Laukka, Erika J (J Alzheimers Dis, 2021)
BACKGROUND: Modifiable vascular risk factors have been associated with late-life cognitive impairment. The Life Simple 7 (LS7) score comprises seven cardiovascular health metrics: smoking, diet, physical activity, body mass index, plasma glucose, total serum cholesterol, and blood pressure. OBJECTIVE: To investigate the association between individual and composite LS7 metrics and rate of cognitive decline, and potential differences in these associations between young-old and old-old individuals. METHODS: This cohort study included 1,950 participants aged≥60 years (M = 70.7 years) from the Swedish National Study on Aging and Care-Kungsholmen (SNAC-K), who underwent repeated neuropsychological testing (episodic and semantic memory, verbal fluency, processing speed, global cognition) across 12 years. The LS7 score was assessed at baseline and categorized as poor, intermediate, or optimal. Level and change in cognitive performance as a function LS7 categories were estimated using linear mixed-effects models. RESULTS: Having an optimal LS7 total score was associated with better performance (expressed in standard deviation units) at baseline for perceptual speed (β= 0.21, 95%CI 0.12-0.29), verbal fluency (β= 0.08, 0.00-0.16), and global cognition (β= 0.06, 0.00-0.12) compared to the poor group. Age-stratified analyses revealed associations for cognitive level and change only in the young-old (<  78 years) group. For the specific metrics, diverging patterns were observed for young-old and old-old individuals. CONCLUSION: Meeting the LS7 criteria for ideal cardiovascular health in younger old age is associated with slower rate of cognitive decline. However, the LS7 criteria may have a different meaning for cognitive function in very old adults.

Relevance of a Truncated PRESENILIN 2 Transcript to Alzheimer's Disease and Neurodegeneration. - Moussavi Nik, Seyyed Hani; Porter, Tenielle; Newman, Morgan; Bartlett, Benjamin; Khan, Imran; Sabale, Miheer; Eccles, Melissa; Woodfield, Amy; Groth, David; Doré, Vincent; Villemagne, Victor L; Masters, Colin L; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The PRESENILIN genes (PSEN1, PSEN2) encoding for their respective proteins have critical roles in many aspects of Alzheimer's disease (AD) pathogenesis. The PS2V transcript of PSEN2 encodes a truncated protein and is upregulated in AD brains; however, its relevance to AD and disease progression remains to be determined. OBJECTIVE: Assess transcript levels in postmortem AD and non-AD brain tissue and in lymphocytes collected under the Australian Imaging Biomarker and Lifestyle (AIBL) study. METHODS: Full length PSEN2 and PS2V transcript levels were assessed by quantitative digital PCR in postmortem brain tissue (frontal cortex and hippocampus) from control, AD, frontotemporal dementia (FTD), and Lewy body dementia (LBD). Transcript levels were also assessed in lymphocytes obtained from the Perth subset of the AIBL study (n = 160). Linear regression analysis was used to assess correlations between transcript copy number and brain volume and neocortical amyloid load. RESULTS: PS2V levels increased in AD postmortem brain but PS2V was also present at significant levels in FTD and LBD brains. PS2V transcript was detected in lymphocytes and PS2V/PSEN2 ratios were increased in mild cognitive impairment (p = 0.024) and AD (p = 0.019) groups compared to control group. Increased ratios were significantly correlated with hippocampal volumes only (n = 62, β= -0.269, p = 0.03). CONCLUSION: Taken together, these results suggest that PS2V may be a marker of overall neurodegeneration.

The Retinal Vessel Density Can Reflect Cognitive Function in Patients with Alzheimer's Disease: Evidence from Optical Coherence Tomography Angiography. - Yan, Yibing; Wu, Xingqi; Wang, Xiaojing; Geng, Zhi; Wang, Lu; Xiao, Guixian; Wu, Yue; Zhou, Shanshan; Liao, Rongfeng; Wei, Ling; Tian, Yanghua; Wang, Kai (J Alzheimers Dis, 2021)
BACKGROUND: There is increasing evidence that Alzheimer's disease (AD) patients may present decreased cerebral blood perfusion before pathological brain changes. Using the retina as a window to the brain, we can study disorders of the central nervous system through the eyes. OBJECTIVE: This study aimed to investigate differences in retinal structure and vessel density (VD) between patients with mild AD and healthy controls (HCs). Furthermore, we explored the relationship between retinal VD and cognitive function. METHODS: We enrolled 37 patients with AD and 29 age-matched HCs who underwent standard ophthalmic optical coherence tomography angiography (OCTA) for evaluation of the retinal layer thickness and VD parameters. Cognitive function was evaluated using a battery of neuropsychological assessments. Finally, the correlations among retinal layer thickness, VD parameters, and cognitive function were evaluated. RESULTS: The retinal fiber layer thickness and retinal VD of patients with AD were significantly reduced compared with HCs. The retinal VD was significantly correlated with overall cognition, memory, executive, and visual-spatial perception functions. However, there was no significant between-group difference in the macular thickness. CONCLUSION: Our findings indicate a positive correlation between retinal VD and some, but not all, cognitive function domains. Most importantly, we demonstrated the role of OCTA in detecting early capillary changes, which could be a noninvasive biomarker for early AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cognition; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Retinal Vessels; Tomography, Optical Coherence

Site-Specific Cerebrospinal Fluid Tau Hyperphosphorylation in Response to Alzheimer's Disease Brain Pathology: Not All Tau Phospho-Sites are Hyperphosphorylated. - Barthélemy, Nicolas R; Toth, Balazs; Manser, Paul T; Sanabria-Bohórquez, Sandra; Teng, Edmond; Keeley, Michael; Bateman, Randall J; Weimer, Robby M; Wildsmith, Kristin R (J Alzheimers Dis, 2021)
BACKGROUND: Understanding patterns of association between CSF phosphorylated tau (p-tau) species and clinical disease severity will aid Alzheimer's disease (AD) diagnosis and treatment. OBJECTIVE: To evaluate changes in tau phosphorylation ratios to brain imaging (amyloid PET, [18F]GTP1 PET, and MRI) and cognition across clinical stages of AD in two different cohorts. METHODS: A mass spectrometry (MS)-based method was used to evaluate the relationship between p-tau/tau phosphorylation ratios on 11 sites in CSF and AD pathology measured by tau PET ([18F]GTP1) and amyloid PET ([18F]florbetapir or [18F]florbetaben). Cohort A included cognitively normal-amyloid negative (n = 6) and positive (n = 5) individuals, and amyloid positive prodromal (n = 13), mild (n = 12), and moderate AD patients (n = 10); and Cohort B included amyloid positive prodromal (n = 24) and mild (n = 40) AD patients. RESULTS: In this cross-sectional analysis, we identified clusters of phosphosites with different profiles of phosphorylation ratios across stages of disease. Eight of 11 investigated sites were hyperphosphorylated and associated with the SUVR measures from [18F]GTP1 and amyloid PET. Novel sites 111, 153, and 208 may be relevant biomarkers for AD diagnosis to complement tau hyperphosphorylation measures on previously established sites 181, 205, 217, and 231. Hypophosphorylation was detected on residues 175, 199, and 202, and was inversely associated with [18F]GTP1 and amyloid PET. CONCLUSION: Hyperphosphorylated and hypophosphorylated forms of tau are associated with AD pathologies, and due to their different site-specific profiles, they may be used in combination to assist with staging of disease.

A Super-Resolved View of the Alzheimer's Disease-Related Amyloidogenic Pathway in Hippocampal Neurons. - Yu, Yang; Gao, Yang; Winblad, Bengt; Tjernberg, Lars O; Schedin-Weiss, Sophia (J Alzheimers Dis, 2021)
BACKGROUND: Processing of the amyloid-β protein precursor (AβPP) is neurophysiologically important due to the resulting fragments that regulate synapse biology, as well as potentially harmful due to generation of the 42 amino acid long amyloid β-peptide (Aβ42), which is a key player in Alzheimer's disease. OBJECTIVE: Our aim was to clarify the subcellular locations of the fragments involved in the amyloidogenic pathway in primary neurons with a focus on Aβ42 and its immediate substrate AβPP C-terminal fragment (APP-CTF). To overcome the difficulties of resolving these compartments due to their small size, we used super-resolution microscopy. METHODS: Mouse primary hippocampal neurons were immunolabelled and imaged by stimulated emission depletion (STED) microscopy, including three-dimensional three-channel imaging, and quantitative image analyses. RESULTS: The first (β-secretase) and second (γ-secretase) cleavages of AβPP were localized to functionally and distally distinct compartments. The β-secretase cleavage was observed in early endosomes in soma, where we were able to show that the liberated N- and C-terminal fragments were sorted into distinct vesicles budding from the early endosomes. Lack of colocalization of Aβ42 and APP-CTF in soma suggested that γ-secretase cleavage occurs in neurites. Indeed, APP-CTF was, in line with Aβ42 in our previous study, enriched in the presynapse but absent from the postsynapse. In contrast, full-length AβPP was not detected in either the pre- or the postsynaptic side of the synapse. Furthermore, we observed that endogenously produced and endocytosed Aβ42 were localized in different compartments. CONCLUSION: These findings provide critical super-resolved insight into amyloidogenic AβPP processing in primary neurons.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Amyloidogenic Proteins; Animals; Cells, Cultured; Hippocampus; Humans; Mice; Mice, Inbred C57BL; Microscopy; Neurons; Peptide Fragments; Protein Transport

Synaptic Molecular and Neurophysiological Markers Are Independent Predictors of Progression in Alzheimer's Disease. - Smailovic, Una; Kåreholt, Ingemar; Koenig, Thomas; Ashton, Nicholas J; Winblad, Bengt; Höglund, Kina; Nilsson, Per; Zetterberg, Henrik; Blennow, Kaj; Jelic, Vesna (J Alzheimers Dis, 2021)
BACKGROUND: Cerebrospinal fluid (CSF) neurogranin and quantitative electroencephalography (qEEG) are potential molecular and functional markers of synaptic pathology in Alzheimer's disease (AD). Synaptic markers have emerged as candidate prognostic indicators of AD since synaptic degeneration was shown to be an early event and the best correlate of cognitive deficits in patients along the disease continuum. OBJECTIVE: The present study investigated the association between CSF neurogranin and qEEG measures as well as their potential to predict clinical deterioration in mild cognitive impairment (MCI) patients. METHODS: Patients diagnosed with MCI (n = 99) underwent CSF conventional AD biomarkers and neurogranin analysis and resting-state EEG recordings. The study population was further stratified into stable (n = 41) and progressive MCI (n = 31), based on the progression to AD dementia during two years follow-up. qEEG analysis included computation of global field power and global field synchronization in four conventional frequency bands. RESULTS: CSF neurogranin levels were associated with theta power and synchronization in the progressive MCI group. CSF neurogranin and qEEG measures were significant predictors of progression to AD dementia, independent of baseline amyloid status in MCI patients. A combination of CSF neurogranin with global EEG power in theta and global EEG synchronization in beta band exhibited the highest classification accuracy as compared to either of these markers alone. CONCLUSION: qEEG and CSF neurogranin are independent predictors of progression to AD dementia in MCI patients. Molecular and neurophysiological synaptic markers may have additive value in a multimodal diagnostic and prognostic approach to dementia.

TAR DNA-Binding Protein 43 Is Associated with Rate of Memory and Functional and Global Cognitive Decline in the Decade Prior to Death. - Buciuc, Marina; Tosakulwong, Nirubol; Machulda, Mary M; Whitwell, Jennifer L; Weigand, Stephen D; Murray, Melissa E; Ross Reichard, R; Parisi, Joseph E; Dickson, Dennis W; Boeve, Bradley F; Knopman, David S; Petersen, Ronald C; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Transactive response DNA-binding protein of 43 kDa (TDP-43) is associated with memory impairment and overall cognitive decline. It is unclear how TDP-43 contributes to the rate of clinical decline. OBJECTIVE: To determine whether cross-sectional and longitudinal cognitive and functional decline are associated with anatomical distribution of TDP-43 in the brain. METHODS: Longitudinal clinical-neuropathologic autopsy cohort study of 385 initially cognitively normal/mildly impaired older adults prospectively followed until death. We investigated how TDP-43, amyloid-β (Aβ), tau neurofibrillary tangles (NFT), Lewy body disease (LBD), age, sex, and genetics are associated with clinical scores and rates of their longitudinal decline. RESULTS: Of 385 participants, 260 (68%) had no TDP-43, 32 (8%) TDP-43 limited to amygdala, and 93 (24%) TDP-43 in the hippocampus and beyond. Higher TDP-43 and Braak NFT stages independently were associated with faster decline in global cognition, functional performance measured by Clinical Dementia Rating scale, and naming and episodic memory, whereas older age was associated with slower rate of cognitive, psychiatric, and functional decline. Cross-sectionally the following associations were found: higher TDP-43 and Braak NFT - worse performance; higher Aβ burden - worse global cognition, more behavioral changes, the latter also with higher LBD; older age - worse naming, lower frequency of behavioral changes; female sex - more impaired naming and better preserved episodic memory. There were no genetic associations. CONCLUSION: The association of TDP-43 distribution with decline in cognitive and functional performance suggests that TDP-43 is playing a role in the clinical progression to dementia. Further characterization of clinical features associated with TDP-43 can facilitate establishment of antemortem diagnosis.

tRNA-Derived Fragments in Alzheimer's Disease: Implications for New Disease Biomarkers and Neuropathological Mechanisms. - Wu, Wenzhe; Lee, Inhan; Spratt, Heidi; Fang, Xiang; Bao, Xiaoyong (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease (AD) is the most common type of dementia caused by irreversible neurodegeneration, with the onset mechanisms elusive. tRNA-derived RNA fragments (tRFs), a recently discovered family of small non-coding RNAs (sncRNAs), have been found to associate with many human diseases, including infectious, metabolic, and neurological diseases. However, whether tRFs play a role in human AD development is not known. OBJECTIVE: This study aimed to explore whether tRFs are involved in human AD. METHODS: Thirty-four postmortem human hippocampus samples were used. The expression of Drosha, Dicer, and angiogenin (ANG), three ribonucleases responsible for the biogenesis of sncRNAs, was determined by qRT-PCR and western blot. The tRFs in the hippocampus was detected by qRT-PCR or northern blot. We also used qRT-PCR to quantify NOP2/Sun RNA methyltransferase 2 (NSun2) and polyadenylation factor I subunit 1 (CLP1), two tRNA modification enzymes. RESULTS: tRFs derived from a subset of tRNAs are significantly altered in the hippocampus of AD patients. The expression change of some tRFs showed age- and disease stage-dependent. ANG is significantly enhanced in AD, suggesting its role in inducing tRFs in AD. The expression of NSun2 in AD patients younger than 65 was significantly decreased. According to a previous report supporting NSun2-mediated tRNA methylation modification making tRNA less susceptible to ANG-mediated cleavage, our results suggested that the decrease in NSun2 may make tRNAs less methylated and subsequently enhanced tRF production from ANG-mediated tRNA cleavage. CONCLUSION: Our studies demonstrated for the first time the involvement of tRFs in human AD.
Keywords: Aged; Alzheimer Disease; Biomarkers; Blotting, Northern; Case-Control Studies; Hippocampus; Humans; Polymerase Chain Reaction; RNA, Small Untranslated; RNA, Transfer

Upregulation of Local Hepcidin Contributes to Iron Accumulation in Alzheimer's Disease Brains. - Chaudhary, Suman; Ashok, Ajay; McDonald, Dallas; Wise, Aaron S; Kritikos, Alexander E; Rana, Neil A; Harding, Clifford V; Singh, Neena (J Alzheimers Dis, 2021)
BACKGROUND: Accumulation of iron is a consistent feature of Alzheimer's disease (AD) brains. The underlying cause, however, remains debatable. OBJECTIVE: To explore whether local hepcidin synthesized by brain cells contributes to iron accumulation in AD brains. METHODS: Brain tissue from the cingulate cortex of 33 cases of AD pre-assigned to Braak stage I-VI, 6 cases of non-dementia, and 15 cases of non-AD dementia were analyzed for transcriptional upregulation of hepcidin by RT-qPCR and RT-PCR. Change in the expression of ferritin, ferroportin (Fpn), microglial activation marker Iba1, IL-6, and TGFβ2 was determined by western blotting. Total tissue iron was determined by colorimetry. RESULTS: Significant transcriptional upregulation of hepcidin was observed in Braak stage III-VI relative to Braak stage I and II, non-AD dementia, and non-dementia samples. Ferritin was increased in Braak stage V, and a significant increase in tissue iron was evident in Braak stage III-VI. The expression of Iba1 and IL-6 was also increased in Braak stage III-VI relative to Braak stage I and II and non-AD dementia samples. Amyloid-β plaques were absent in most Braak stage I and II samples, and present in Braak stage III-VI samples with few exceptions. CONCLUSION: These observations suggest that upregulation of brain hepcidin is mediated by IL-6, a known transcriptional activator of hepcidin. The consequent downregulation of Fpn on neuronal and other cells results in accumulation of iron in AD brains. The increase in hepcidin is disease-specific, and increases with disease progression, implicating AD-specific pathology in the accumulation of iron.

Adiponectin Paradox as a Therapeutic Target in Alzheimer's Disease. - Waragai, Masaaki; Ho, Gilbert; Takamatsu, Yoshiki; Wada, Ryoko; Sugama, Shuei; Takenouchi, Takato; Masliah, Eliezer; Hashimoto, Makoto (J Alzheimers Dis, 2020)
Despite the apparent neurotoxicity of amyloid-β (Aβ), recent clinical trials of Aβ immunotherapy have not shown any clinical benefit in Alzheimer's disease (AD). Given this, clarification of the next generation therapeutic strategy in AD is warranted. Hypothetically, adiponectin might be involved in promoting amyloidogenic evolvability in reproduction, which may result in the adiponectin paradox through antagonistic pleiotropy mechanism in aging, leading to AD. Accordingly, preventing the adiponectin paradox by suppressing adiponectin signaling might prove therapeutic in AD.

Aggregates of RNA Binding Proteins and ER Chaperones Linked to Exosomes in Granulovacuolar Degeneration of the Alzheimer's Disease Brain. - Yamoah, Alfred; Tripathi, Priyanka; Sechi, Antonio; Köhler, Christoph; Guo, Haihong; Chandrasekar, Akila; Nolte, Kay Wilhelm; Wruck, Christoph Jan; Katona, Istvan; Anink, Jasper; Troost, Dirk; Aronica, Eleonora; et al. (J Alzheimers Dis, 2020)
Granulovacuolar degeneration (GVD) occurs in Alzheimer's disease (AD) brain due to compromised autophagy. Endoplasmic reticulum (ER) function and RNA binding protein (RBP) homeostasis regulate autophagy. We observed that the ER chaperones GRP78/BiP, Sigma receptor 1 (SigR1), and VAPB were elevated in many AD patients' subicular neurons. However, those neurons which were affected by GVD showed lower chaperone levels, and there was only minor co-localization of chaperones with GVD bodies (GVBs), suggesting that neurons lacking sufficient chaperone-mediated proteostasis enter the GVD pathway. Consistent with this notion, granular, incipient pTau aggregates in human AD and pR5 tau transgenic mouse neurons were regularly co-localized with increased chaperone immunoreactivity, whereas neurons with mature neurofibrillary tangles lacked both the chaperone buildup and significant GVD. On the other hand, APP/PS1 (APPswe/PSEN1dE9) transgenic mouse hippocampal neurons that are devoid of pTau accumulation displayed only few GVBs-like vesicles, which were still accompanied by prominent chaperone buildup. Identifying a potential trigger for GVD, we found cytoplasmic accumulations of RBPs including Matrin 3 and FUS as well as stress granules in GVBs of AD patient and pR5 mouse neurons. Interestingly, we observed that GVBs containing aggregated pTau and pTDP-43 were consistently co-localized with the exosomal marker Flotillin 1 in both AD and pR5 mice. In contrast, intraneuronal 82E1-immunoreactive amyloid-β in human AD and APP/PS1 mice only rarely co-localized with Flotillin 1-positive exosomal vesicles. We conclude that altered chaperone-mediated ER protein homeostasis and impaired autophagy manifesting in GVD are linked to both pTau and RBP accumulation and that some GVBs might be targeted to exocytosis.

Alzheimer's/Vascular Spectrum Dementia: Classification in Addition to Diagnosis. - Emrani, Sheina; Lamar, Melissa; Price, Catherine C; Wasserman, Victor; Matusz, Emily; Au, Rhoda; Swenson, Rodney; Nagele, Robert; Heilman, Kenneth M; Libon, David J (J Alzheimers Dis, 2020)
Alzheimer's disease (AD) and vascular dementia (VaD) are the two most common types of dementia. Although the combination of these disorders, called 'mixed' dementia, is recognized, the prevailing clinical and research perspective continues to consider AD and VaD as independent disorders. A review of recent neuropathological and neuropsychological literature reveals that these two disorders frequently co-occur and so-called 'pure' AD or VaD is comparatively rare. In addition, recent research shows that vascular dysfunction not only potentiates AD pathology, but that pathological changes in AD may subsequently induce vascular disorders. On the basis of these data, we propose that the neurobiological underpinnings underlying AD/VaD dementia and their neuropsychological phenotypes are best understood as existing along a clinical/pathological continuum or spectrum. We further propose that in conjunction with current diagnostic criteria, statistical modeling techniques using neuropsychological test performance should be leveraged to construct a system to classify AD/VaD spectrum dementia in order to test hypotheses regarding how mechanisms related to AD and VaD pathology interact and influence each other.

Amyloid Hypothesis: The Emperor's New Clothes? - Høilund-Carlsen, Poul F; Barrio, Jorge R; Werner, Tom J; Newberg, Andrew; Alavi, Abass (J Alzheimers Dis, 2020)
The lengthy debate on the validity of the amyloid hypothesis and the usefulness of amyloid imaging and anti-amyloid therapeutic interventions in dementia continues unabated, even though none of them have been able to convince the medical world of their correctness and clinical value. There are huge financial interests associated with promoting both, but in spite of the large sums of money in their support, no effective anti-amyloid treatments or diagnostic use of amyloid imaging have emerged. There are solid scientific reasons that explain these negative results, and it is time to move forward to other promising options for the benefit of the patients.

The Amyloid, Tau, and Neurodegeneration (A/T/N) Classification Applied to a Clinical Research Cohort with Long-Term Follow-Up. - Grøntvedt, Gøril Rolfseng; Lauridsen, Camilla; Berge, Guro; White, Linda R; Salvesen, Øyvind; Bråthen, Geir; Sando, Sigrid Botne (J Alzheimers Dis, 2020)
BACKGROUND: The unbiased amyloid, tau, and neurodegeneration (A/T/N) classification is designed to characterize individuals in the Alzheimer continuum and is currently little explored in clinical cohorts. OBJECTIVE: A retrospective comparison of the A/T/N classification system with the results of a two-year clinical study, with extended follow-up up to 10 years after inclusion. METHODS: Patients (n = 102) clinically diagnosed as Alzheimer's disease (AD) with dementia or amnestic mild cognitive impairment (MCI), and 61 cognitively healthy control individuals were included. Baseline cerebrospinal fluid core biomarkers for AD (Aβ42, phosphorylated tau, and total tau) were applied to the A/T/N classification using the final clinical diagnosis at extended follow-up as the gold standard. RESULTS: A + T + N+ was a strong predictor for AD dementia, even among cognitively healthy individuals. Amnestic MCI was heterogenous, considering both clinical outcome and distribution within A/T/N. Some individuals with amnestic MCI progressed to clinical AD dementia within all four major A/T/N groups. The highest proportion of progression was among triple positive cases, but progression was also common in individuals with suspected non-Alzheimer pathophysiology (A-T + N+), and those with triple negative status. A-T-N- individuals who were cognitively healthy overwhelmingly remained cognitively intact over time, but in amnestic MCI the clinical outcome was heterogenous, including AD dementia, other dementias, and recovery. CONCLUSION: The A/T/N framework accentuates biomarkers over clinical status. However, when selecting individuals for research, a combination of the two may be necessary since the prognostic value of the A/T/N framework depends on clinical status.

Anterior Cingulate Structure and Perfusion Is Associated with Cerebrospinal Fluid Tau Among Cognitively Normal Older Adult APOEɛ4 Carriers. - Hays, Chelsea C; Zlatar, Zvinka Z; Meloy, M J; Osuna, Jessica; Liu, Thomas T; Galasko, Douglas R; Wierenga, Christina E (J Alzheimers Dis, 2020)
Evidence suggests the ɛ4 allele of the apolipoprotein E gene (APOE) may accelerate an age-related process of cortical thickening and cerebral blood flow (CBF) reduction in the anterior cingulate cortex (ACC). Although the neural basis of this association remains unclear, evidence suggests it might reflect early neurodegenerative processes. However, to date, associations between cerebrospinal fluid (CSF) biomarkers of neurodegeneration, such as CSF tau, and APOE-related alterations in ACC cortical thickness (CTH) and CBF have yet to be explored. The current study explored the interaction of CSF tau and APOE genotype (ɛ4+, ɛ4-) on FreeSurfer-derived CTH and arterial spin labeling MRI-measured resting CBF in the ACC (caudal ACC [cACC] and rostral ACC [rACC]) among a sample of 45 cognitively normal older adults. Secondary analyses also examined associations between APOE, CTH/CBF, and cognitive performance. In the cACC, higher CSF tau was associated with higher CTH and lower CBF in ɛ4+, whereas these relationships were not evident in ɛ4-. In the rACC, higher CSF tau was associated with higher CTH for both ɛ4+ and ɛ4-, and with lower CBF only in ɛ4+. Significant interactions of CSF tau and APOE on CTH/CBF were not observed in two posterior reference regions implicated in Alzheimer's disease. Secondary analyses revealed a negative relationship between cACC CTH and executive functioning in ɛ4+ and a positive relationship in ɛ4-. Findings suggest the presence of an ɛ4-related pattern of increased CTH and CBF reduction in the ACC that is associated with biomarkers of neurodegeneration and subtle decrements in cognition.

The Association of Post-Stroke Cognitive Impairment and Gut Microbiota and its Corresponding Metabolites. - Liu, Yongqiang; Kong, Cheng; Gong, Li; Zhang, Xiaohui; Zhu, Yuefei; Wang, Haichao; Qu, Xiao; Gao, Renyuan; Yin, Fang; Liu, Xueyuan; Qin, Huanlong (J Alzheimers Dis, 2020)
BACKGROUND: Post-stroke cognitive impairment (PSCI) is an important factor causing disabilities after acute ischemic stroke (AIS). Emerging evidence suggested that gut microbiota play an important role in cognitive impairment. OBJECTIVE: This study aimed to explore the association between PSCI and gut microbiota. METHOD: 65 patients with newly diagnostic AIS finished the fecal collection on admission and cognitive assessment 3 months later in the clinic. Fecal samples were subjected to 16SrRNA gene sequencing and gas chromatography-mass spectrometry analysis. Additionally, we enrolled new 18 AIS patients, whose treatment was supplemented by probiotics, to assess the potential of microbial treatment in PSCI. RESULTS: PSCI patients were characterized by the significantly decreased alpha-diversity, disturbed microbial composition, and corresponding metabolites compared with non-PSCI patients. Increased Fusobacterium and deficiency of microbial metabolized short-chain fatty acids (SCFAs) were significantly associated with PSCI. A model based on gut microbiota and SCFAs could predict 3 months or longer PSCI early and accurately after stroke onset. While traditional probiotic administration had little effect on PSCI, it could ameliorate patients' mood, including depression and anxiety in the 3 months after stroke. CONCLUSION: Our study revealed the association between PSCI and gut microbiota and its corresponding metabolites for the first time, suggesting the potential for applying microbiota and its corresponding metabolites to early clinical diagnosis and treatment of PSCI.

Cerebrospinal Fluid Metals and the Association with Cerebral Small Vessel Disease. - Shams, Mana; Martola, Juha; Charidimou, Andreas; Granberg, Tobias; Ferreira, Daniel; Westman, Eric; Wintermark, Max; Iv, Michael; Larvie, Mykol; Kristoffersen Wiberg, Maria; Kaijser, Magnus; Forsgard, Niklas; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Brain metal homeostasis is essential for brain health, and deregulation can result in oxidative stress on the brain parenchyma. OBJECTIVE: Our objective in this study was to focus on two hemorrhagic MRI manifestations of small vessel disease [cerebral microbleeds (CMBs) and cortical superficial siderosis (cSS)] and associations with cerebrospinal fluid (CSF) iron levels. In addition, we aimed to analyze CSF biomarkers for dementia and associations with CSF metal levels. METHODS: This is a cross-sectional study of 196 patients who underwent memory clinic investigation, including brain MRI. CSF was collected and analyzed for metals, amyloid-β (Aβ) 42, total tau (T-tau), and phosphorylated tau (P-tau), and CSF/serum albumin ratios. Statistical analyses were performed using generalized linear models. RESULTS: No significant difference was found between CSF metal levels across diagnostic groups. Higher iron and copper levels were associated with higher CSF levels of Aβ42, T-tau, P-tau, and CSF/serum albumin ratios (p < 0.05). Zinc was associated with higher CSF/serum albumin ratios. There was no significant association between CMBs or cSS and CSF iron levels. An increase in CSF iron with the number of CMBs was seen in APOEɛ4 carriers. CONCLUSION: CSF iron levels are elevated with cerebral microbleeds in APOEɛ4 carriers, with no other association seen with hemorrhagic markers of small vessel disease. The association of elevated CSF iron and copper with tau could represent findings of increased neurodegeneration in these patients.

Circulating Vitamin D Levels and Alzheimer's Disease: A Mendelian Randomization Study in the IGAP and UK Biobank. - Wang, Longcai; Qiao, Yanchun; Zhang, Haihua; Zhang, Yan; Hua, Jiao; Jin, Shuilin; Liu, Guiyou (J Alzheimers Dis, 2020)
Observational studies strongly supported the association of low levels of circulating 25-hydroxyvitamin D (25OHD) and cognitive impairment or dementia in aging populations. However, randomized controlled trials have not shown clear evidence that vitamin D supplementation could improve cognitive outcomes. In fact, some studies reported the association between vitamin D and cognitive impairment based on individuals aged 60 years and over. However, it is still unclear that whether vitamin D levels are causally associated with Alzheimer's disease (AD) risk in individuals aged 60 years and over. Here, we performed a Mendelian randomization (MR) study to investigate the causal association between vitamin D levels and AD using a large-scale vitamin D genome-wide association study (GWAS) dataset and two large-scale AD GWAS datasets from the IGAP and UK Biobank with individuals aged 60 years and over. Our results showed that genetically increased 25OHD levels were significantly associated with reduced AD risk in individuals aged 60 years and over. Hence, our findings in combination with previous literature indicate that maintaining adequate vitamin D status in older people especially aged 60 years and over, may contribute to slow down cognitive decline and forestall AD. Long-term randomized controlled trials are required to test whether vitamin D supplementation may prevent AD in older people especially those aged 60 years and may be recommended as preventive agents.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biological Specimen Banks; Cognition Disorders; Databases, Factual; Female; Genome-Wide Association Study; Humans; Hydroxycholecalciferols; Male; Mendelian Randomization Analysis; Middle Aged; Nutritional Status; United Kingdom; Vitamin D; Vitamin D Deficiency

Clinical and Bacterial Markers of Periodontitis and Their Association with Incident All-Cause and Alzheimer's Disease Dementia in a Large National Survey. - Beydoun, May A; Beydoun, Hind A; Hossain, Sharmin; El-Hajj, Ziad W; Weiss, Jordan; Zonderman, Alan B (J Alzheimers Dis, 2020)
Microbial agents including periodontal pathogens have recently appeared as important actors in Alzheimer's disease (AD) pathology. We examined associations of clinical periodontal and bacterial parameters with incident all-cause and AD dementia as well as AD mortality among US middle-aged and older adults. Clinical [Attachment Loss (AL); probing pocket depth (PPD)] and bacterial [pathogen immunoglobulin G (IgG)] periodontal markers were investigated in relation to AD and all-cause dementia incidence and to AD mortality, using data from the third National Health and Nutrition Examination Surveys (NHANES III, 1988-1994) linked longitudinally with National Death Index and Medicare data through January 1, 2014, with up to 26 years of follow-up. Sex- and age-specific multivariable-adjusted Cox proportional hazards models were conducted. Among those ≥65 years, AD incidence and mortality were consistently associated with PPD, two factors and one cluster comprised of IgG titers against Porphyromonas gingivalis (P. gingivalis), Prevotella melaninogenica (P. melaninogenica) and Campylobacter rectus (C. rectus) among others. Specifically, AD incidence was linked to a composite of C. rectus and P. gingivalis titers (per SD, aHR = 1.22; 95% CI, 1.04-1.43, p = 0.012), while AD mortality risk was increased with another composite (per SD, aHR = 1.46; 95% CI, 1.09-1.96, p = 0.017) loading highly on IgG for P. gingivalis, Prevotella intermedia, Prevotella nigrescens, Fusobacterium nucleatum, C. rectus, Streptococcus intermedius, Capnocylophaga Ochracea, and P. melaninogenica. This study provides evidence for an association between periodontal pathogens and AD, which was stronger for older adults. Effectiveness of periodontal pathogen treatment on reducing sequelae of neurodegeneration should be tested in randomized controlled trials.

Common Bacterial Infections and Risk of Dementia or Cognitive Decline: A Systematic Review. - Muzambi, Rutendo; Bhaskaran, Krishnan; Brayne, Carol; Davidson, Jennifer A; Smeeth, Liam; Warren-Gash, Charlotte (J Alzheimers Dis, 2020)
BACKGROUND: Bacterial infections may be associated with dementia, but the temporality of any relationship remains unclear. OBJECTIVES: To summarize existing literature on the association between common bacterial infections and the risk of dementia and cognitive decline in longitudinal studies. METHODS: We performed a comprehensive search of 10 databases of published and grey literature from inception to 18 March 2019 using search terms for common bacterial infections, dementia, cognitive decline, and longitudinal study designs. Two reviewers independently performed the study selection, data extraction, risk of bias and overall quality assessment. Data were summarized through a narrative synthesis as high heterogeneity precluded a meta-analysis. RESULTS: We identified 3,488 studies. 9 met the eligibility criteria; 6 were conducted in the United States and 3 in Taiwan. 7 studies reported on dementia and 2 investigated cognitive decline. Multiple infections were assessed in two studies. All studies found sepsis (n = 6), pneumonia (n = 3), urinary tract infection (n = 1), and cellulitis (n = 1) increased dementia risk (HR 1.10; 95% CI 1.02-1.19) to (OR 2.60; 95% CI 1.84-3.66). The range of effect estimates was similar when limited to three studies with no domains at high risk of bias. However, the overall quality of evidence was rated very low. Studies on cognitive decline found no association with infection but had low power. CONCLUSION: Our review suggests common bacterial infections may be associated with an increased risk of subsequent dementia, after adjustment for multiple confounders, but further high-quality, large-scale longitudinal studies, across different healthcare settings, are recommended to further explore this association.

Concentration-Dependent Activity of Hydromethylthionine on Clinical Decline and Brain Atrophy in a Randomized Controlled Trial in Behavioral Variant Frontotemporal Dementia. - Shiells, Helen; Schelter, Bjoern O; Bentham, Peter; Baddeley, Thomas C; Rubino, Christopher M; Ganesan, Harish; Hammel, Jeffrey; Vuksanovic, Vesna; Staff, Roger T; Murray, Alison D; Bracoud, Luc; Wischik, Damon J; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Hydromethylthionine is a potent inhibitor of pathological aggregation of tau and TDP-43 proteins. OBJECTIVE: To compare hydromethylthionine treatment effects at two doses and to determine how drug exposure is related to treatment response in bvFTD. METHODS: We undertook a 52-week Phase III study in 220 bvFTD patients randomized to compare hydromethylthionine at 200 mg/day and 8 mg/day (intended as a control). The principal outcomes were change on the Addenbrookes Cognitive Examination - Revised (ACE-R), the Functional Activities Questionnaire (FAQ), and whole brain volume. Secondary outcomes included Modified Clinical Global Impression of Change (Modified-CGIC). A population pharmacokinetic exposure-response analysis was undertaken in 175 of the patients with available blood samples and outcome data using a discriminatory plasma assay for the parent drug. RESULTS: There were no significant differences between the two doses as randomized. There were steep concentration-response relationships for plasma levels in the range 0.3-0.6 ng/ml at the 8 mg/day dose on clinical and MRI outcomes. There were significant exposure-dependent differences at 8 mg/day for FAQ, Modified-CGIC, and whole brain atrophy comparing patients with plasma levels greater than 0.346 ng/ml with having minimal drug exposure. The exposure-response is biphasic with worse outcomes at the high concentrations produced by 200 mg/day. CONCLUSIONS: Hydromethylthionine has a similar concentration-response profile for effects on clinical decline and brain atrophy at the 8 mg/day dose in bvFTD as recently reported in AD. Treatment responses in bvFTD are predicted to be maximal at doses in the range 20-60 mg/day. A confirmatory placebo-controlled trial is now planned.

COVID-19: Review of a 21st Century Pandemic from Etiology to Neuro-psychiatric Implications. - Yamamoto, Vicky; Bolanos, Joe F; Fiallos, John; Strand, Susanne E; Morris, Kevin; Shahrokhinia, Sanam; Cushing, Tim R; Hopp, Lawrence; Tiwari, Ambooj; Hariri, Robert; Sokolov, Rick; Wheeler, Christopher; et al. (J Alzheimers Dis, 2020)
COVID-19 is a severe infectious disease that has claimed >150,000 lives and infected millions in the United States thus far, especially the elderly population. Emerging evidence has shown the virus to cause hemorrhagic and immunologic responses, which impact all organs, including lungs, kidneys, and the brain, as well as extremities. SARS-CoV-2 also affects patients', families', and society's mental health at large. There is growing evidence of re-infection in some patients. The goal of this paper is to provide a comprehensive review of SARS-CoV-2-induced disease, its mechanism of infection, diagnostics, therapeutics, and treatment strategies, while also focusing on less attended aspects by previous studies, including nutritional support, psychological, and rehabilitation of the pandemic and its management. We performed a systematic review of >1,000 articles and included 425 references from online databases, including, PubMed, Google Scholar, and California Baptist University's library. COVID-19 patients go through acute respiratory distress syndrome, cytokine storm, acute hypercoagulable state, and autonomic dysfunction, which must be managed by a multidisciplinary team including nursing, nutrition, and rehabilitation. The elderly population and those who are suffering from Alzheimer's disease and dementia related illnesses seem to be at the higher risk. There are 28 vaccines under development, and new treatment strategies/protocols are being investigated. The future management for COVID-19 should include B-cell and T-cell immunotherapy in combination with emerging prophylaxis. The mental health and illness aspect of COVID-19 are among the most important side effects of this pandemic which requires a national plan for prevention, diagnosis and treatment.
Keywords: Coronavirus Infections; COVID-19; Humans; Immunotherapy; Mental Health; Nutritional Support; Pandemics; Pneumonia, Viral

Dickkopf-1 Overexpression in vitro Nominates Candidate Blood Biomarkers Relating to Alzheimer's Disease Pathology. - Shi, Liu; Winchester, Laura M; Liu, Benjamine Y; Killick, Richard; Ribe, Elena M; Westwood, Sarah; Baird, Alison L; Buckley, Noel J; Hong, Shengjun; Dobricic, Valerija; Kilpert, Fabian; Franke, Andre; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Previous studies suggest that Dickkopf-1 (DKK1), an inhibitor of Wnt signaling, plays a role in amyloid-induced toxicity and hence Alzheimer's disease (AD). However, the effect of DKK1 expression on protein expression, and whether such proteins are altered in disease, is unknown. OBJECTIVE: We aim to test whether DKK1 induced protein signature obtained in vitro were associated with markers of AD pathology as used in the amyloid/tau/neurodegeneration (ATN) framework as well as with clinical outcomes. METHODS: We first overexpressed DKK1 in HEK293A cells and quantified 1,128 proteins in cell lysates using aptamer capture arrays (SomaScan) to obtain a protein signature induced by DKK1. We then used the same assay to measure the DKK1-signature proteins in human plasma in two large cohorts, EMIF (n = 785) and ANM (n = 677). RESULTS: We identified a 100-protein signature induced by DKK1 in vitro. Subsets of proteins, along with age and apolipoprotein E ɛ4 genotype distinguished amyloid pathology (A + T-N-, A+T+N-, A+T-N+, and A+T+N+) from no AD pathology (A-T-N-) with an area under the curve of 0.72, 0.81, 0.88, and 0.85, respectively. Furthermore, we found that some signature proteins (e.g., Complement C3 and albumin) were associated with cognitive score and AD diagnosis in both cohorts. CONCLUSIONS: Our results add further evidence for a role of DKK regulation of Wnt signaling in AD and suggest that DKK1 induced signature proteins obtained in vitro could reflect theATNframework as well as predict disease severity and progression in vivo.

Dyadic Group Exercises for Persons with Memory Deficits and Care Partners: Mixed-Method Findings from the Paired Preventing Loss of Independence through Exercise (PLIÉ) Randomized Trial. - Mehling, E Wolf; Scott, M Travis; Duffy, James; Whitmer, A Rachel; Chesney, A Margaret; Boscardin, W John; Barnes, E Deborah (J Alzheimers Dis, 2020)
BACKGROUND: Non-pharmacological therapies for persons with dementia (PWD) are needed. OBJECTIVE: To develop and test the Paired Preventing Loss of Independence through Exercise (PLIÉ) program, an integrative group movement program for PWD and care partners (CPs). METHODS: Participants were randomized to immediate or delayed start to Paired PLIÉ in community-based classes (1 hour, 2 days/week, 12 weeks, 3 home visits). Co-primary outcomes included standard measures of cognition, physical function,and quality of life (PWD) and caregiver burden (CPs) assessed by blinded assessors, analyzed using linear mixed models to calculate effect sizes for outcome changes during Paired PLIÉ, controlling for randomization group. Anonymous satisfaction surveys included satisfaction ratings and thematic analysis of open-ended responses. RESULTS: Thirty dyads enrolled, 24 (80%) completed. PWD (mean age 80; 55% female) experienced significant improvement in self-rated quality of life (Effect Size+0.23; p = 0.016) when participating in Paired PLIÉ, while CPs experienced a non-significant increase in burden (-0.23, p = 0.079). Changes in physical and cognitive function in PWD were not significant. All CPs returning the satisfaction survey (n = 20) reported being moderately-to-highly satisfied with the program. Thematic analyses identified physical (e.g., sit-to-stand, more energy), emotional (enjoyment), and social benefits (peer-to-peer interaction) for PWD and CPs; challenges were primarily related to getting to the in-person classes. CONCLUSION: Paired PLIÉ is a promising integrative group movement program that warrants further study. It is feasible and may improve self-rated quality of life in PWD. Although CPs may experience increased burden due to logistical challenges, most reported high satisfaction and physical, emotional, and social benefits.

Effect of Mentally Challenging Occupations on Incident Dementia Differs Between African Americans and Non-Hispanic Whites. - Hyun, Jinshil; Hall, Charles B; Sliwinski, Martin J; Katz, Mindy J; Wang, Cuiling; Ezzati, Ali; Lipton, Richard B (J Alzheimers Dis, 2020)
BACKGROUND: Engaging in mentally challenging activities may protect against dementia in late life. However, little is known whether the association between mentally challenging activities and dementia risk varies with race/ethnicity. OBJECTIVE: The current study investigates whether having jobs with higher mental stimulation is differentially associated with a decreased risk of dementia between African Americans (AAs) and non-Hispanic Whites (nHWs). METHODS: The sample consisted of 1,079 individuals (66% nHWs, 28% AAs; age = 78.6±5.3) from the longitudinal Einstein Aging Study. Occupation information of each participant was collected retrospectively at baseline and was linked to the substantive complexity of work score from the Dictionary of Occupational Titles. Cox proportional hazards models were used to evaluate the associations of occupational complexity with risk of dementia. RESULTS: Individuals whose jobs had moderate-to-high levels of complexity, compared to those with the lowest complexity, were at modestly decreased risk for incident dementia. When stratified by race, moderate-to-high levels of occupational complexity were significantly associated with lower risk of developing dementia for AAs (HR = 0.35). When risk of dementia was evaluated based on the combinations of race×occupational complexity, AAs with lowest occupational complexity showed the highest risk of developing dementia, while other combinations exhibited lower risk of developing dementia (HRs = 0.36 0.43). CONCLUSION: Our results suggest that moderate-to-high levels of complexity at work are associated with a decreased risk of incident dementia in AAs. Understanding the differential effects of mentally challenging occupations across race/ethnicity may suggest important intervention strategies that could mitigate racial disparities in dementia rates.

Effects of LDL Cholesterol and Statin Use on Verbal Learning and Memory in Older Adults at Genetic Risk for Alzheimer's Disease. - Wroolie, Tonita; Roat-Shumway, Siena; Watson, Katie; Reiman, Eric; Rasgon, Natalie (J Alzheimers Dis, 2020)
BACKGROUND: The apolipoprotein epsilon 4 (APOE4) allele is a well-established genetic risk factor for Alzheimer's disease (AD). However, there are mixed findings as to how the APOE4 allele modifies the effects of both higher low-density lipoprotein cholesterol (LDL) and statin use on cognitive functioning. OBJECTIVE: This study sought to examine the effects of LDL levels and statin use on verbal learning and memory, as modified by the presence of the APOE4 allele, in a sample of cognitively unimpaired, older adults at risk for AD. METHODS: Neuropsychological, LDL, statin use, and APOE4 data were extracted from an ongoing longitudinal study at the Banner Alzheimer's Institute in Arizona. Participants were cognitively unimpaired based on Mini-Mental State Examination scores within a normal range, aged 47-75, with a family history of probable AD in at least one first-degree relative. RESULTS: In the whole sample, higher LDL was associated with worse immediate verbal memory in APOE4 non-carriers, but did not have an effect on immediate verbal memory in APOE4 carriers. In APOE4 non-carriers, statin use was associated with better verbal learning, but did not have an effect on verbal learning in APOE4 carriers. Among women, higher LDL in APOE4 carriers was associated with worse verbal learning than in APOE4 non-carriers, and statin use in APOE4 non-carriers was associated with better verbal learning and immediate and delayed verbal memory but worse performances on these tasks in APOE4 carriers. CONCLUSION: LDL and statin use may have differential effects on verbal learning and/or memory depending on genetic risk for AD. Women appear to be particularly vulnerable to statin use depending on their APOE4 status.

Falls Associate with Neurodegenerative Changes in ATN Framework of Alzheimer's Disease. - Keleman, Audrey; Wisch, Julie K; Bollinger, Rebecca M; Grant, Elizabeth A; Benzinger, Tammie L; Morris, John C; Ances, Beau M; Stark, Susan L (J Alzheimers Dis, 2020)
BACKGROUND: Behavioral markers for Alzheimer's disease (AD) are not included within the widely used amyloid-tau-neurodegeneration framework. OBJECTIVE: To determine when falls occur among cognitively normal (CN) individuals with and without preclinical AD. METHODS: This cross-sectional study recorded falls among CN participants (n = 83) over a 1-year period. Tailored calendar journals recorded falls. Biomarkers including amyloid positron emission tomography (PET) and structural and functional magnetic resonance imaging were acquired within 2 years of fall evaluations. CN participants were dichotomized by amyloid PET (using standard cutoffs). Differences in amyloid accumulation, global resting state functional connectivity (rs-fc) intra-network signature, and hippocampal volume were compared between individuals who did and did not fall using Wilcoxon rank sum tests. Among preclinical AD participants (amyloid-positive), the partial correlation between amyloid accumulation and global rs-fc intra-network signature was compared for those who did and did not fall. RESULTS: Participants who fell had smaller hippocampal volumes (p = 0.04). Among preclinical AD participants, those who fell had a negative correlation between amyloid uptake and global rs-fc intra-network signature (R = -0.75, p = 0.012). A trend level positive correlation was observed between amyloid uptake and global rs-fc intra-network signature (R = 0.70, p = 0.081) for preclinical AD participants who did not fall. CONCLUSION: Falls in CN older adults correlate with neurodegeneration biomarkers. Participants without falls had lower amyloid deposition and preserved global rs-fc intra-network signature. Falls most strongly correlated with presence of amyloid and loss of brain connectivity and occurred in later stages of preclinical AD.

Functional Connectivity Alterations of the Temporal Lobe and Hippocampus in Semantic Dementia and Alzheimer's Disease. - Schwab, Simon; Afyouni, Soroosh; Chen, Yan; Han, Zaizhu; Guo, Qihao; Dierks, Thomas; Wahlund, Lars-Olof; Grieder, Matthias (J Alzheimers Dis, 2020)
BACKGROUND: Semantic memory impairments in semantic dementia are attributed to atrophy and functional disruption of the anterior temporal lobes. In contrast, the posterior medial temporal neurodegeneration found in Alzheimer's disease is associated with episodic memory disturbance. The two dementia subtypes share hippocampal deterioration, despite a relatively spared episodic memory in semantic dementia. OBJECTIVE: To unravel mutual and divergent functional alterations in Alzheimer's disease and semantic dementia, we assessed functional connectivity between temporal lobe regions in Alzheimer's disease (n = 16), semantic dementia (n = 23), and healthy controls (n = 17). METHODS: In an exploratory study, we used a functional parcellation of the temporal cortex to extract time series from 66 regions for correlation analysis. RESULTS: Apart from differing connections between Alzheimer's disease and semantic dementia that yielded reduced functional connectivity, we identified a common pathway between the right anterior temporal lobe and the right orbitofrontal cortex in both dementia subtypes. This disconnectivity might be related to social knowledge deficits as part of semantic memory decline. However, such interpretations are preferably made in a holistic context of disease-specific semantic impairments and functional connectivity changes. CONCLUSION: Despite a major limitation owed to unbalanced databases between study groups, this study provides a preliminary picture of the brain's functional disconnectivity in Alzheimer's disease and semantic dementia. Future studies are needed to replicate findings of a common pathway with consistent diagnostic criteria and neuropsychological evaluation, balanced designs, and matched data MRI acquisition procedures.

Functional Integrity of Synapses in the Central Nervous System of Cognitively Intact Individuals with High Alzheimer's Disease Neuropathology is Associated with Absence of Synaptic Tau Oligomers. - Singh, Ayush; Allen, Dyron; Fracassi, Anna; Tumurbaatar, Batbayar; Natarajan, Chandramouli; Scaduto, Pietro; Woltjer, Randy; Kayed, Rakez; Limon, Agenor; Krishnan, Balaji; Taglialatela, Giulio (J Alzheimers Dis, 2020)
BACKGROUND: Certain individuals, here referred to as Non-Demented with Alzheimer Neuropathology (NDAN), do not show overt neurodegeneration (N - ) and remain cognitively intact despite the presence of plaques (A+) and tangles (T+) that would normally be consistent with fully symptomatic Alzheimer's disease (AD). OBJECTIVE: The existence of NDAN (A + T +N - ) subjects suggests that the human brain utilizes intrinsic mechanisms that can naturally evade cognitive decline normally associated with the symptomatic stages of AD (A + T +N +). Deciphering the underlying mechanisms would prove relevant to develop complementing therapeutics to prevent progression of AD-related cognitive decline. METHODS: Previously, we have reported that NDAN present with preserved neurogenesis and synaptic integrity paralleled by absence of amyloid oligomers at synapses. Using postmortem brain samples from age-matched control subjects, demented AD patients and NDAN individuals, we performed immunofluorescence, western blots, micro transplantation of synaptic membranes in Xenopus oocytes followed by twin electrode voltage clamp electrophysiology and fluorescence assisted single synaptosome-long term potentiation studies. RESULTS: We report decreased tau oligomers at synapses in the brains of NDAN subjects. Furthermore, using novel approaches we report, for the first time, that such absence of tau oligomers at synapses is associated with synaptic functional integrity in NDAN subjects as compared to demented AD patients. CONCLUSION: Overall, these results give further credence to tau oligomers as primary actors of synaptic destruction underscoring cognitive demise in AD and support their targeting as a viable therapeutic strategy for AD and related tauopathies.

Generation of Transgenic Cynomolgus Monkeys Overexpressing the Gene for Amyloid-β Precursor Protein. - Seita, Yasunari; Morimura, Toshifumi; Watanabe, Naoki; Iwatani, Chizuru; Tsuchiya, Hideaki; Nakamura, Shinichiro; Suzuki, Toshiharu; Yanagisawa, Daijiro; Tsukiyama, Tomoyuki; Nakaya, Masataka; Okamura, Eiichi; Muto, Masanaga; et al. (J Alzheimers Dis, 2020)
Alzheimer's disease (AD) is the most common cause of dementia and understanding its pathogenesis should lead to improved therapeutic and diagnostic methods. Although several groups have developed transgenic mouse models overexpressing the human amyloid-β precursor protein (APP) gene with AD mutations, with and without presenilin mutations, as well as APP gene knock-in mouse models, these animals display amyloid pathology but do not show neurofibrillary tangles or neuronal loss. This presumably is due to differences between the etiology of the aged-related human disease and the mouse models. Here we report the generation of two transgenic cynomolgus monkeys overexpressing the human gene for APP with Swedish, Artic, and Iberian mutations, and demonstrated expression of gene tagged green fluorescent protein marker in the placenta, amnion, hair follicles, and peripheral blood. We believe that these nonhuman primate models will be very useful to study the pathogenesis of dementia and AD. However, generated Tg monkeys still have some limitations. We employed the CAG promoter, which will promote gene expression in a non-tissue specific manner. Moreover, we used transgenic models but not knock-in models. Thus, the inserted transgene destroys endogenous gene(s) and may affect the phenotype(s). Nevertheless, it will be of great interest to determine whether these Tg monkeys will develop tauopathy and neurodegeneration similar to human AD.

The GSM BPN-15606 as a Potential Candidate for Preventative Therapy in Alzheimer's Disease. - Prikhodko, Olga; Rynearson, Kevin D; Sekhon, Travis; Mante, Mike M; Nguyen, Phuong D; Rissman, Robert A; Tanzi, Rudolph E; Wagner, Steven L (J Alzheimers Dis, 2020)
BACKGROUND: In the amyloid hypothesis of Alzheimer's disease (AD), the dysregulation of amyloid-β protein (Aβ) production and clearance leads to amyloid deposits, tau tangles, neuronal loss, and cognitive dysfunction. Thus far, therapies targeting the enzymes responsible for Aβ production have been found ineffective or having significant side effects. OBJECTIVE: To test whether a γ-secretase modulator, BPN-15606, is an effective disease-modifying or preventative treatment in the PSAPP mouse model of AD. METHODS: We treated pre-plaque (3-month-old) and post-plaque (6-month-old) PSAPP AD transgenic mice for 3 months and examined behavioral, biochemical, and pathological end points. RESULTS: BPN-15606 attenuated cognitive impairment and reduced amyloid plaque load, microgliosis, and astrogliosis associated with the AD phenotype of PSAPP mice when administered to pre-plaque (3-month-old) but was ineffective when administered to post-plaque (6-month-old) mice. No treatment-related toxicity was observed. CONCLUSION: BPN-15606 appears efficacious when administered prior to significant pathology.

Impact of APOE and BDNF Val66Met Gene Polymorphisms on Cognitive Functions in Patients with Amnestic Mild Cognitive Impairment. - Cechova, Katerina; Andel, Ross; Angelucci, Francesco; Chmatalova, Zuzana; Marková, Hana; Laczó, Jan; Vyhnálek, Martin; Matoska, Vaclav; Kaplan, Vojtech; Nedelska, Zuzana; Ward, David D; Hort, Jakub (J Alzheimers Dis, 2020)
Apolipoprotein (APOE) ɛ4 is a well-known risk factor for late-onset Alzheimer's disease (AD), but other AD-related gene polymorphisms might also be important, such as the polymorphism within the brain-derived neurotrophic factor (BDNF) gene. Carriage of BDNF Val66Met has been associated with faster cognitive decline and greater hippocampal atrophy in cognitively normal elderly. Thus, we examined the effects of the concurrent presence of APOE and BDNF polymorphisms on cognitive functions and brain morphometry in amnestic mild cognitive impairment (aMCI) patients. 107 aMCI patients (mean age = 72.2) were recruited from the Czech Brain Aging Study and, based on APOE and BDNF genes polymorphisms, were divided into four groups: ɛ4-BDNFVal/Val (n = 37), ɛ4-BDNFMet (n = 19), ɛ4+BDNFVal/Val (n = 35), and ɛ4+BDNFMet (n = 16). All patients underwent clinical examination, magnetic resonance imaging, and complex neuropsychological battery. The combination of APOEɛ4+ and BDNF Met was associated with significantly worse memory performance in immediate and delayed recall compared to other polymorphism groups. We did not observe increased atrophy in areas related to memory function in the ɛ4+BDNFMet group. Our findings suggest that carriage of ɛ4+BDNFMet is associated with more pronounced memory dysfunction, a typical feature of early AD, but not with structural brain changes in aMCI patients. These findings suggest that in APOEɛ4/BDNF Met carriers, synaptic dysfunction affecting memory may precede pronounced structural changes.

Inflammation in Traumatic Brain Injury. - Postolache, Teodor T; Wadhawan, Abhishek; Can, Adem; Lowry, Christopher A; Woodbury, Margaret; Makkar, Hina; Hoisington, Andrew J; Scott, Alison J; Potocki, Eileen; Benros, Michael E; Stiller, John W (J Alzheimers Dis, 2020)
There is an increasing evidence that inflammation contributes to clinical and functional outcomes in traumatic brain injury (TBI). Many successful target-engaging, lesion-reducing, symptom-alleviating, and function-improving interventions in animal models of TBI have failed to show efficacy in clinical trials. Timing and immunological context are paramount for the direction, quality, and intensity of immune responses to TBI and the resulting neuroanatomical, clinical, and functional course. We present components of the immune system implicated in TBI, potential immune targets, and target-engaging interventions. The main objective of our article is to point toward modifiable molecular and cellular mechanisms that may modify the outcomes in TBI, and contribute to increasing the translational value of interventions that have been identified in animal models of TBI.

Influence of Comorbidity of Cerebrovascular Disease and Amyloid-β on Alzheimer's Disease. - Yassi, Nawaf; Hilal, Saima; Xia, Ying; Lim, Yen Ying; Watson, Rosie; Kuijf, Hugo; Fowler, Christopher; Yates, Paul; Maruff, Paul; Martins, Ralph; Ames, David; Chen, Christopher; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Quantifying the contribution of cerebrovascular disease to the clinical and pathological profile of Alzheimer's disease is challenging. OBJECTIVE: We aimed to determine the influence of cerebrovascular disease, amyloid-β (Aβ), and their comorbidity on cognitive decline, hippocampal atrophy, and Aβ deposition, by evaluating data from the Australian Imaging, Biomarker and Lifestyle Study of Ageing. METHODS: Two-hundred and eighteen participants underwent Aβ PET, MRI, and cognitive assessment at 18-month intervals for up to 90 months. Aβ status was determined on baseline PET. Participants were also classified as V + on baseline MRI if they had≥1 large cortical infarcts, subcortical infarcts, or cortical cerebral microinfarcts; or white matter hyperintensity volume greater than the 90th percentile of healthy controls. Linear mixed models were conducted comparing slopes of change in cognition, hippocampal volume, and Aβ load between the four resultant groups. RESULTS: Mean age at baseline was 74 years (range 59-96). One-hundred and fifteen participants were cognitively normal, 54 had mild cognitive impairment, and 49 had Alzheimer's disease. Compared to the Aβ-/V- group, the Aβ+/V- and Aβ+/V+groups showed significantly faster cognitive decline and hippocampal atrophy over 90 months. V + status was associated with greater cognitive decline (Cohen's d = 0.85, p < 0.001) and hippocampal atrophy (d = 2.05, p < 0.001) in the Aβ+group but not in the Aβ- group. V + status was not associated with Aβ accumulation in any group. CONCLUSION: Comorbidity of cerebrovascular disease and Aβ was associated with cognitive decline and neurodegeneration. Cerebrovascular disease was not associated with the rate of Aβ accumulation.

Levels of Retinal Amyloid-β Correlate with Levels of Retinal IAPP and Hippocampal Amyloid-β in Neuropathologically Evaluated Individuals. - Schultz, Nina; Byman, Elin; Wennström, Malin (J Alzheimers Dis, 2020)
BACKGROUND: Previous studies have used immunohistology to demonstrate Alzheimer's disease (AD) characteristic accumulation of amyloid-β (Aβ) in the retina of AD patients, a finding indicating retina examination as a potential diagnostic tool for AD pathology. OBJECTIVE: To further explore this idea by investigating whether levels of Aβ42 and Aβ40 in retina are associated with corresponding levels in hippocampus, neuropathological assessments, apolipoprotein E (APOE) genotype, and levels of islet amyloid polypeptide (IAPP). METHODS: Levels of high molecular weight (HMW) Aβ42, Aβ40, and IAPP in ultra-centrifuged homogenates of retina and hippocampus from patients with AD, multiple sclerosis, AD with Lewy bodies, and non-demented controls were analyzed using Mesoscale Discovery electrochemiluminescence technology employing immunoassay and enzyme-linked immunosorbent assay. RESULTS: Higher levels of retinal and hippocampal Aβ42-HMW, Aβ40-HMW, and IAPP-HMW were found in individuals with high neuropathological scores of Aβ plaques and in individuals carrying the APOEɛ4 allele. The retinal levels of Aβ42-HMW and Aβ40-HMW correlated with corresponding levels in hippocampus as well as with neurofibrillary tangles (NFT) and Aβ scores. Retinal IAPP-HMW correlated with retinal levels of Aβ42-HMW and with NFT and Aβ scores. CONCLUSION: These results show that different isoforms of Aβ can be detected in the human retina and moreover support the growing number of studies indicating that AD-related pathological changes occurring in the brain could be reflected in the retina.

Metabolic Changes Detected by 18F-FDG PET in the Preclinical Stage of Familial Creutzfeldt-Jakob Disease. - Lu, Hui; Jing, Donglai; Chen, Yaojing; Cui, Chunlei; Gao, Ran; Wang, Lin; Liang, Zhigang; Chen, Kewei; Wu, Liyong (J Alzheimers Dis, 2020)
BACKGROUND: Pathologic processes in Creutzfeldt-Jakob disease (CJD) are not fully understood. Familial CJD (fCJD) gives opportunities to discover pathologic changes in the preclinical stage. OBJECTIVE: To investigate cerebral glucose metabolism in the preclinical stage via 18F-fluorodeoxyglucose positron emission tomography (18F-FDG PET) in fCJD. METHODS: Seven asymptomatic carriers of G114V mutation and six family members without PRNP mutation from the same fCJD kindred were included, and were followed for 2 years. Ten symptomatic CJD patients were also recruited. All subjects underwent standardized clinical examinations and 18F-FDG PET scans. Results were compared in three groups: baseline carriers against non-carriers (baseline analysis), changes after 2 years in carriers (follow-up analysis), and differences between symptomatic CJD patients and healthy controls (CJD patients analysis). RESULTS: No carriers developed any neurological symptoms during 2-year follow-up. Baseline analysis: carriers demonstrates decreased metabolism (p < 0.001) in left and right postcentral, left fusiform, left superior temporal, left lingual, left superior parietal, and left Heschl gyrus. Follow-up analysis shows metabolic decline (p < 0.001) in right inferior temporal, left supra-marginal and left postcentral lobe, and increased metabolism (p < 0.001) in left fusiform, left angular, left thalamus, left Heschl's, right Rolandic operculum, and left superior parietal gyrus. CJD patients demonstrates decreased metabolism in right inferior triangularis frontal gyrus, right middle occipital gyrus, right putamen, right thalamus, and right middle temporal gyrus. CONCLUSION: Hypo-metabolism of parietal and temporal lobe can be detected by 18F-FDG PET in the preclinical stage of CJD. Subcortical area might compensate in the preclinical stage and decompensate in the symptomatic stage.

Mitochondrial DNA Manipulations Affect Tau Oligomerization. - Weidling, Ian W; Wilkins, Heather M; Koppel, Scott J; Hutfles, Lewis; Wang, Xiaowan; Kalani, Anuradha; Menta, Blaise W; Ryan, Benjamin; Perez-Ortiz, Judit; Gamblin, T Chris; Swerdlow, Russell H (J Alzheimers Dis, 2020)
BACKGROUND: Mitochondrial dysfunction and tau aggregation occur in Alzheimer's disease (AD), and exposing cells or rodents to mitochondrial toxins alters their tau. OBJECTIVE: To further explore how mitochondria influence tau, we measured tau oligomer levels in human neuronal SH-SY5Y cells with different mitochondrial DNA (mtDNA) manipulations. METHODS: Specifically, we analyzed cells undergoing ethidium bromide-induced acute mtDNA depletion, ρ0 cells with chronic mtDNA depletion, and cytoplasmic hybrid (cybrid) cell lines containing mtDNA from AD subjects. RESULTS: We found cytochrome oxidase activity was particularly sensitive to acute mtDNA depletion, evidence of metabolic re-programming in the ρ0 cells, and a relatively reduced mtDNA content in cybrids generated through AD subject mitochondrial transfer. In each case tau oligomer levels increased, and acutely depleted and AD cybrid cells also showed a monomer to oligomer shift. CONCLUSION: We conclude a cell's mtDNA affects tau oligomerization. Overlapping tau changes across three mtDNA-manipulated models establishes the reproducibility of the phenomenon, and its presence in AD cybrids supports its AD-relevance.

A New Serum Biomarker Set to Detect Mild Cognitive Impairment and Alzheimer's Disease by Peptidome Technology. - Abe, Koji; Shang, Jingwei; Shi, Xiaowen; Yamashita, Toru; Hishikawa, Nozomi; Takemoto, Mami; Morihara, Ryuta; Nakano, Yumiko; Ohta, Yasuyuki; Deguchi, Kentaro; Ikeda, Masaki; Ikeda, Yoshio; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Because dementia is an emerging problem in the world, biochemical markers of cerebrospinal fluid (CSF) and radio-isotopic analyses are helpful for diagnosing Alzheimer's disease (AD). Although blood sample is more feasible and plausible than CSF or radiological biomarkers for screening potential AD, measurements of serum amyloid- β (Aβ), plasma tau, and serum antibodies for Aβ1 - 42 are not yet well established. OBJECTIVE: We aimed to identify a new serum biomarker to detect mild cognitive impairment (MCI) and AD in comparison to cognitively healthy control by a new peptidome technology. METHODS: With only 1.5μl of serum, we examined a new target plate "BLOTCHIP®" plus a matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF/MS) to discriminate control (n = 100), MCI (n = 60), and AD (n = 99). In some subjects, cognitive Mini-Mental State Examination (MMSE) were compared to positron emission tomography (PET) with Pittsburgh compound B (PiB) and the serum probability of dementia (SPD). The mother proteins of candidate serum peptides were examined in autopsied AD brains. RESULTS: Apart from Aβ or tau, the present study discovered a new diagnostic 4-peptides-set biomarker for discriminating control, MCI, and AD with 87% of sensitivity and 65% of specificity between control and AD (***p < 0.001). MMSE score was well correlated to brain Aβ deposition and to SPD of AD. The mother proteins of the four peptides were upregulated for coagulation, complement, and plasticity (three proteins), and was downregulated for anti-inflammation (one protein) in AD brains. CONCLUSION: The present serum biomarker set provides a new, rapid, non-invasive, highly quantitative and low-cost clinical application for dementia screening, and also suggests an alternative pathomechanism of AD for neuroinflammation and neurovascular unit damage.

Older Patients with Alzheimer's Disease-Related Cortical Atrophy Who Develop Post-Operative Delirium May Be at Increased Risk of Long-Term Cognitive Decline After Surgery. - Racine, Annie M; Touroutoglou, Alexandra; Abrantes, Tatiana; Wong, Bonnie; Fong, Tamara G; Cavallari, Michele; Travison, Thomas G; Gou, Yun; Marcantonio, Edward R; Alsop, David C; Jones, Richard N; Inouye, Sharon K; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Older surgical patients with Alzheimer's disease (AD) dementia and delirium are at increased risk for accelerated long-term cognitive decline. OBJECTIVE: Investigate associations between a probabilistic marker of preclinical AD, delirium, and long-term cognitive decline. METHODS: The Successful Aging after Elective Surgery cohort includes older adults (≥70 years) without dementia who underwent elective surgery. 140 patients underwent preoperative magnetic resonance imaging and had≥6 months cognitive follow-up. Cortical thickness was measured in 'AD-Signature' regions. Delirium was evaluated each postoperative day by the Confusion Assessment Method. Cognitive performance was assessed using a detailed neuropsychological battery at baseline; months 1, 2, and 6; and every 6 months thereafter until 36 months. Using either a General Cognitive Performance composite (GCP) or individual test scores as outcomes, we performed linear mixed effects models to examine main effects of AD-signature atrophy and the interaction of AD-signature atrophy and delirium on slopes of cognitive change from post-operative months 2-36. RESULTS: Reduced baseline AD-signature cortical thickness was associated with greater 36-month cognitive decline in GCP (standardized beta coefficient, β = -0.030, 95% confidence interval [-0.060, -0.001]). Patients who developed delirium who also had thinner AD signature cortex showed greater decline on a verbal learning test (β = -0.100 [-0.192, -0.007]). CONCLUSION: Patients with the greatest baseline AD-related cortical atrophy who develop delirium after elective surgery appear to experience the greatest long-term cognitive decline. Thus, atrophy suggestive of preclinical AD and the development of delirium may be high-risk indicators for long-term cognitive decline following surgery.

Oxidized Products of Omega-6 and Omega-3 Long Chain Fatty Acids Are Associated with Increased White Matter Hyperintensity and Poorer Executive Function Performance in a Cohort of Cognitively Normal Hypertensive Older Adults. - Shinto, Lynne; Lahna, David; Murchison, Charles F; Dodge, Hiroko; Hagen, Kirsten; David, Jason; Kaye, Jeffrey; Quinn, Joseph F; Wall, Rachel; Silbert, Lisa C (J Alzheimers Dis, 2020)
BACKGROUND: Cerebrovascular disease is a common cause of dementia in older adults, and potentially preventable with early intervention. Oxylipins are produced from the oxidation of long-chain polyunsaturated fatty acids (PUFA) possessing potent vascular effects. Oxylipins generated from the cytochrome P450 pathway are enzymatically converted to diols by soluble epoxide hydrolase (sEH); sEH products have been associated with small vessel ischemic disease. Little is known about oxylipins' impact on markers of dementia risk. OBJECTIVE: An exploratory examination of the association between omega-6 and omega-3 derived oxylipins, brain MRI, and cognition. METHODS: Thirty-seven non-demented participants with controlled hypertension (mean age 65.6 years) were enrolled in a dementia prevention study investigating fish oil and lipoic acid on preserving cognitive function. Baseline associations between plasma oxylipins, white matter hyperintensity (WMH), and Trails-B were examined using linear regression. P450-derived diol/epoxide ratio was an indirect measure of sEH activity. RESULTS: Omega-6 derived 9-HODE was associated with increased WMH (p = 0.017) and reduced grey matter volume (p = 0.02). Omega-6 P450-derived diol/epoxide ratio 9,10-DiHOME/9,10-EpOME was associated with increased WMH (p = 0.035) and poorer performance on Trails-B (p = 0.05); ratio14,15-DHET/14,15-EET was associated with increased WMH (p = 0.045). Omega-3 P450-derived diol/epoxide ratio 19,20-DiHDPE/19,20-EpDPE was associated with increased WMH (p = 0.04) and poorer performance on Trails-B (p = 0.04). Arachidonic acid was associated with better performance on Trails-B (p = 0.012); Omega-3 derived 16,17-EpDPE was associated with decreased WMH (p = 0.005). CONCLUSIONS: With the exception of arachidonic acid, it was specific oxylipin products, not their parent PUFAs, that were associated with unfavorable and favorable MRI and cognitive markers of dementia risk.

Patterns of Regional Cerebral Blood Flow as a Function of Obesity in Adults. - Amen, Daniel G; Wu, Joseph; George, Noble; Newberg, Andrew (J Alzheimers Dis, 2020)
BACKGROUND: While obesity has been shown to be a risk factor for Alzheimer's disease, the potential mechanisms underlying this risk may be clarified with better understanding of underlying physiology in obese persons. OBJECTIVE: To identify patterns of cerebral perfusion abnormality in adults as a function of body mass index (BMI) defined weight categories, including overweight or obese status. METHODS: A large psychiatric cohort of 35,442 brain scans across 17,721 adults (mean age 40.8±16.2 years, range 18-94 years) were imaged with SPECT during baseline and concentration scans, the latter done after each participant completed the Connors Continuous Performance Test II. ANOVA was done to identify patterns of perfusion abnormality in this cohort across BMI designations of underweight (BMI < 18.5), normal weight (BMI = 18.5 to 24.9), overweight (BMI 24.9 to 29.9), obesity (BMI≥30), and morbid obesity (BMI≥40). This analysis was done for 128 brain regions quantifying SPECT perfusion using the automated anatomical labeling (AAL) atlas. RESULTS: Across adulthood, higher BMI correlated with decreased perfusion on both resting and concentration brain SPECT scans. These are seen in virtually all brain regions, including those influenced by AD pathology such as the hippocampus. CONCLUSION: Greater BMI is associated with cerebral perfusion decreases in both resting and concentration SPECT scans across adulthood.

Performance of Validated MicroRNA Biomarkers for Alzheimer's Disease in Mild Cognitive Impairment. - Sandau, Ursula S; Wiedrick, Jack T; Smith, Sierra J; McFarland, Trevor J; Lusardi, Theresa A; Lind, Babett; Harrington, Christina A; Lapidus, Jodi A; Galasko, Douglas R; Quinn, Joseph F; Saugstad, Julie A (J Alzheimers Dis, 2020)
BACKGROUND: Cerebrospinal fluid (CSF) microRNA (miRNA) biomarkers of Alzheimer's disease (AD) have been identified, but have not been evaluated in prodromal AD, including mild cognitive impairment (MCI). OBJECTIVE: To assess whether a set of validated AD miRNA biomarkers in CSF are also sensitive to early-stage pathology as exemplified by MCI diagnosis. METHODS: We measured the expression of 17 miRNA biomarkers for AD in CSF samples from AD, MCI, and cognitively normal controls (NC). We then examined classification performance of the miRNAs individually and in combination. For each miRNA, we assessed median expression in each diagnostic group and classified markers as trending linearly, nonlinearly, or lacking any trend across the three groups. For trending miRNAs, we assessed multimarker classification performance alone and in combination with apolipoprotein E ɛ4 allele (APOEɛ4) genotype and amyloid-β42 to total tau ratio (Aβ42:T-Tau). We identified predicted targets of trending miRNAs using pathway analysis. RESULTS: Five miRNAs showed a linear trend of decreasing median expression across the ordered diagnoses (control to MCI to AD). The trending miRNAs jointly predicted AD with area under the curve (AUC) of 0.770, and MCI with AUC of 0.705. Aβ42:T-Tau alone predicted MCI with AUC of 0.758 and the AUC improved to 0.813 (p = 0.051) after adding the trending miRNAs. Multivariate correlation of the five trending miRNAs with Aβ42:T-Tau was weak. CONCLUSION: Selected miRNAs combined with Aβ42:T-Tau improved classification performance (relative to protein biomarkers alone) for MCI, despite a weak correlation with Aβ42:T-Tau. Together these data suggest that that these miRNAs carry novel information relevant to AD, even at the MCI stage. Preliminary target prediction analysis suggests novel roles for these biomarkers.

Plasma High Density Lipoprotein Small Subclass is Reduced in Alzheimer's Disease Patients and Correlates with Cognitive Performance. - Pedrini, Steve; Hone, Eugene; Gupta, Veer B; James, Ian; Teimouri, Elham; Bush, Ashley I; Rowe, Christopher C; Villemagne, Victor L; Ames, David; Masters, Colin L; Rainey-Smith, Stephanie; Verdile, Giuseppe; et al. (J Alzheimers Dis, 2020)
BACKGROUND: The link between cholesterol and Alzheimer's disease (AD) has received much attention, as evidence suggests high levels of cholesterol might be an AD risk factor. The carriage of cholesterol and lipids through the body is mediated via lipoproteins, some of which, particularly apolipoprotein E (ApoE), are intimately linked with AD. In humans, high density lipoprotein (HDL) is regarded as a "good" lipid complex due to its ability to enable clearance of excess cholesterol via 'cholesterol reverse transport', although its activities in the pathogenesis of AD are poorly understood. There are several subclasses of HDL; these range from the newly formed small HDL, to much larger HDL. OBJECTIVE: We examined the major subclasses of HDL in healthy controls, mild cognitively impaired, and AD patients who were not taking statins to determine whether there were HDL profile differences between the groups, and whether HDL subclass levels correlated with plasma amyloid-β (Aβ) levels or brain Aβ deposition. METHODS: Samples from AIBL cohort were used in this study. HDL subclass levels were assessed by Lipoprint while Aβ1-42 levels were assessed by ELISA. Brain Aβ deposition was assessed by PET scan. Statistical analysis was performed using parametric and non-parametric tests. RESULTS: We found that small HDL subclass is reduced in AD patients and it correlates with cognitive performance while plasma Aβ concentrations do not correlate with lipid profile or HDL subfraction levels. CONCLUSION: Our data indicate that AD patients exhibit altered plasma HDL profile and that HDL subclasses correlate with cognitive performances.

Potential of FTIR Spectroscopy Applied to Exosomes for Alzheimer's Disease Discrimination: A Pilot Study. - Martins, Tânia Soares; Magalhães, Sandra; Rosa, Ilka Martins; Vogelgsang, Jonathan; Wiltfang, Jens; Delgadillo, Ivonne; Catita, José; da Cruz E Silva, Odete A B; Nunes, Alexandra; Henriques, Ana Gabriela (J Alzheimers Dis, 2020)
Alzheimer's disease (AD) diagnosis is based on psychological and imaging tests but can also include monitoring cerebrospinal fluid (CSF) biomarkers. However, CSF based-neurochemical approaches are expensive and invasive, limiting their use to well-equipped settings. In contrast, blood-based biomarkers are minimally invasive, cost-effective, and a widely accessible alternative. Blood-derived exosomes have recently emerged as a reliable AD biomarker source, carrying disease-specific cargo. Fourier-transformed infrared (FTIR) spectroscopy meets the criteria for an ideal diagnostic methodology since it is rapid, easy to implement, and has high reproducibility. This metabolome-based technique is useful for diagnosing a broad range of diseases, although to our knowledge, no reports for FTIR spectroscopy applied to exosomes in AD exist. In this ground-breaking pilot study, FTIR spectra of serum and serum-derived exosomes from two independent cohorts were acquired and analyzed using multivariate analysis. The regional UA-cohort includes 9 individuals, clinically diagnosed with AD, mean age of 78.7 years old; and the UMG-cohort comprises 12 individuals, clinically diagnosed with AD (based on molecular and/or imaging data), mean age of 73.2 years old. Unsupervised principal component analysis of FTIR spectra of serum-derived exosomes revealed higher discriminatory value for AD cases when compared to serum as a whole. Consistently, the partial least-squares analysis revealed that serum-derived exosomes present higher correlations than serum. In addition, the second derivative peak area calculation also revealed significant differences among Controls and AD cases. The results obtained suggest that this methodology can discriminate cases from Controls and thus be potential useful to assist in AD clinical diagnosis.

Reduced Hippocampal Glutamate and Posterior Cingulate N-Acetyl Aspartate in Mild Cognitive Impairment and Alzheimer's Disease Is Associated with Episodic Memory Performance and White Matter Integrity in the Cingulum: A Pilot Study. - Wong, Dickson; Atiya, Samir; Fogarty, Jennifer; Montero-Odasso, Manuel; Pasternak, Stephen H; Brymer, Chris; Borrie, Michael J; Bartha, Robert (J Alzheimers Dis, 2020)
Identification of biological changes underlying the early symptoms of Alzheimer's disease (AD) will help to identify and stage individuals prior to symptom onset. The limbic system, which supports episodic memory and is impaired early in AD, is a primary target. In this study, brain metabolism and microstructure evaluated by high field (7 Tesla) proton magnetic resonance spectroscopy (1H-MRS) and diffusion tensor imaging (DTI) were evaluated in the limbic system of eight individuals with mild cognitive impairment (MCI), nine with AD, and sixteen normal elderly controls (NEC). Left hippocampal glutamate and posterior cingulate N-acetyl aspartate concentrations were reduced in MCI and AD compared to NEC. Differences in DTI metrics indicated volume and white matter loss along the cingulum in AD compared to NEC. Metabolic and microstructural changes were associated with episodic memory performance assessed using Craft Story 21 Recall and Benson Complex Figure Copy. The current study suggests that metabolite concentrations measured using 1H-MRS may provide insight into the underlying metabolic and microstructural processes of episodic memory impairment.

Resilience of Alzheimer's Disease to COVID-19. - Li, Jingwen; Long, Xi; Huang, Heqing; Tang, Jine; Zhu, Chunli; Hu, Shaoping; Wu, Jing; Li, Jinghong; Lin, Zhicheng; Xiong, Nian (J Alzheimers Dis, 2020)
BACKGROUND: Facing the novel coronavirus disease 2019 (COVID-19), most vulnerable individuals are seniors, especially those with comorbidities. More attention needs to been paid to the COVID-19 patients with Alzheimer's disease (AD), which is the top age-related neurodegenerative disease. OBJECTIVE: Since it is unclear whether AD patients are prone to COVID-19 infection and progression to severe stages, we report for the first time a retrospective analysis of the clinical characteristics of AD patients with COVID-19 pneumonia. METHODS: We conducted a retrospective cohort study of the clinical data of 19 AD patients with COVID-19 pneumonia, compared with 23 non-AD COVID-19 patients admitted at the same time to our hospital. Demographic, clinical, laboratory, radiological, and treatment data were collected and analyzed. RESULTS: Between AD patients and non-AD patients with COVID-19 pneumonia, the pneumonia severity was not significantly different. AD patients had a higher clustering onset than non-AD patients. The median duration from symptom onset to hospitalization were shorter in AD patients than non-AD patients, indicating the former were sent to the hospital by their family or from nursing home earlier than the later. The median duration from hospitalization to discharge seemed shorter in AD patients than non-AD patients. Dementia patients seemed less likely to report fatigue. It is noticed that more AD patients might have pericardial effusion than the non-AD patients. CONCLUSION: AD patients with COVID-19 were in milder conditions with a better prognosis than non-AD patients. AD patients who had adequate access to healthcare showed resilience to COVID-19 with shorter hospital stays.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cluster Analysis; Cohort Studies; Coronavirus Infections; COVID-19; Disease Progression; Fatigue; Female; Humans; Length of Stay; Male; Middle Aged; Pandemics; Patient Discharge; Pleural Effusion; Pneumonia; Pneumonia, Viral; Prognosis; Resilience, Psychological

A Review of the Brain-Gut-Microbiome Axis and the Potential Role of Microbiota in Alzheimer's Disease. - Sun, Miao; Ma, Kai; Wen, Jie; Wang, Guangxian; Zhang, Changliang; Li, Qi; Bao, Xiaofeng; Wang, Hui (J Alzheimers Dis, 2020)
Alzheimer's disease (AD) is a neurodegenerative process characterized by loss of neurons in the hippocampus and cerebral cortex, leading to progressive cognitive decline. Pathologically, the hallmark of AD is accumulation of "senile" plaques composed of amyloid-β (Aβ) protein surrounding neurons in affected regions. Despite extensive research into AD pathogenesis and therapeutic targets, there remains no breakthroughs in its management. In recent years, there has been a spark of interest in the connection between the brain and gastrointestinal tract, referred to as the brain-gut axis, and its potential implications for both metabolic and neurologic disease. Moreover, the gastrointestinal flora, referred to as the microbiome, appears to exert significant influence over the brain-gut axis. With the need for expanded horizons in understanding and treating AD, many have turned to the brain-gut-microbiome axis for answers. Here we provide a review of the brain-gut-microbiome axis and discuss the evidence supporting alterations of the axis in the pathogenesis of AD. Specifically, we highlight the role for the microbiome in disruption of Aβ metabolism/clearance, increased permeability of the blood-brain barrier and modulation of the neuroinflammatory response, and inhibition of hippocampal neurogenesis. The majority of the above described findings are the result of excellent, albeit basic and pre-clinical studies. Therefore, we conclude with a brief description of documented clinical support for brain-gut-microbiome axis alteration in AD, including potential microbiome-based therapeutics for AD. Collectively, these findings suggest that the brain-gut-microbiome axis may be a "lost link" in understanding and treating AD and call for future work.

Selective Peripheral Taste Dysfunction in APP/PS1 Mutant Transgenic Mice. - Wood, Ryan M; Garcia, Zacnite; Daniels, Nathan; Landon, Shannon M; Humayun, Saima; Lee, Hyoung-gon; Macpherson, Lindsey J (J Alzheimers Dis, 2020)
BACKGROUND: Previous studies indicate that taste dysfunction occurs early in the development of Alzheimer's disease. It is debatable whether the deficit in taste is due primarily to peripheral sensory mechanisms or to central processing, or a combination of the two. OBJECTIVE: The aim of our current study is to combine behavior and histological data in APP/PS1 transgenic mice to determine whether APP/PS1 transgenic mice show deficits in unconditioned taste preference and avoidance behaviors and whether taste impairments are due to defects in the peripheral taste system and/or problems with central processing of taste information. METHODS: The APP/PS1 transgenic mutant mice were used as a model of Alzheimer's disease. We employed a brief-access gustometer test to assess immediate orosensory taste responses of APP/PS1 mice. We used immunohistochemistry to examine tongue, gustatory ganglion, and brain tissues to determine a cytological basis for behavioral deficits. RESULTS: There is a significant, selective reduction of bitter taste sensitivity in APP/PS1 mice. These mice also have a loss of TRPM5-expressing taste receptor cells in the circumvallate papillae of the tongue. While we observed no overt loss of neuron cell bodies within the primary gustatory sensory neurons, degeneration of the neurons' peripheral axons innervating the taste bud may play a role in the observed loss of TRPM5-expressing taste receptor cells. CONCLUSION: This data supports a potential role for peripheral taste dysfunction in AD through the selective loss of taste receptor cells. Further study is necessary to delineate the mechanisms and pathological significance of this deficit in AD.

Structural Brain Changes in Pre-Clinical FTD MAPT Mutation Carriers. - Domínguez-Vivero, Clara; Wu, Liwen; Lee, Seonjoo; Manoochehri, Masood; Cines, Sarah; Brickman, Adam M; Rizvi, Batool; Chesebro, Anthony; Gazes, Yunglin; Fallon, Emer; Lynch, Timothy; Heidebrink, Judith L; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Frontotemporal dementia (FTD) is the second most common cause of early-onset neurodegenerative dementia. Several studies have focused on early imaging changes in FTD patients, but once subjects meet full criteria for the FTD diagnosis, structural changes are generally widespread. OBJECTIVE: This study aims to determine the earliest structural brain changes in asymptomatic MAPT MUTATION carriers. METHODS: This is a cross-sectional multicenter study comparing global and regional brain volume and white matter integrity in a group of MAPT mutation preclinical carriers and controls. Participants belong to multiple generations of six families with five MAPT mutations. All participants underwent a medical examination, neuropsychological tests, genetic analysis, and a magnetic resonance scan (3T, scout, T1-weighted image followed by EPI (BOLD), MPRAGE, DTI, FLAIR, and ASL sequences). RESULTS: Volumes of five cortical and subcortical areas were strongly correlated with mutation status: temporal lobe (left amygdala, left temporal pole), cingulate cortex (left rostral anterior cingulate gyrus, right posterior cingulate), and the lingual gyrus in the occipital lobe. We did not find significant differences in whole brain volume, white matter hyperintensities volume, and white matter integrity using DTI analysis. CONCLUSION: Temporal lobe, cingulate cortex and the lingual gyrus seem to be early targets of the disease and may serve as biomarkers for FTD prior to overt symptom onset.

Structural Brain Magnetic Resonance Imaging to Rule Out Comorbid Pathology in the Assessment of Alzheimer's Disease Dementia: Findings from the Ontario Neurodegenerative Disease Research Initiative (ONDRI) Study and Clinical Trials Over the Past 10 Years. - Kapoor, Arunima; Bartha, Robert; Black, Sandra E; Borrie, Michael; Freedman, Morris; Gao, Fuqiang; Herrmann, Nathan; Mandzia, Jennifer; Ozzoude, Miracle; Ramirez, Joel; Scott, Christopher J M; Symons, Sean; et al. (J Alzheimers Dis, 2020)
BACKGROUND/OBJECTIVE: Structural brain magnetic resonance imaging (MRI) is not mandatory in Alzheimer's disease (AD) research or clinical guidelines. We aimed to explore the use of structural brain MRI in AD/mild cognitive impairment (MCI) trials over the past 10 years and determine the frequency with which inclusion of standardized structural MRI acquisitions detects comorbid vascular and non-vascular pathologies. METHODS: We systematically searched ClinicalTrials.gov for AD clinical trials to determine their neuroimaging criteria and then used data from an AD/MCI cohort who underwent standardized MRI protocols, to determine type and incidence of clinically relevant comorbid pathologies. RESULTS: Of 210 AD clinical trials, 105 (50%) included structural brain imaging in their eligibility criteria. Only 58 (27.6%) required MRI. 16,479 of 53,755 (30.7%) AD participants were in trials requiring MRI. In the observational AD/MCI cohort, 141 patients met clinical criteria; 22 (15.6%) had relevant MRI findings, of which 15 (10.6%) were exclusionary for the study. DISCUSSION: In AD clinical trials over the last 10 years, over two-thirds of participants could have been enrolled without brain MRI and half without even a brain CT. In a study sample, relevant comorbid pathology was found in 15% of participants, despite careful screening. Standardized structural MRI should be incorporated into NIA-AA diagnostic guidelines (when available) and research frameworks routinely to reduce diagnostic heterogeneity.

Tau Acetylation in Entorhinal Cortex Induces its Chronic Hippocampal Propagation and Cognitive Deficits in Mice. - Wang, Xin; Liu, En-Jie; Liu, Qian; Li, Shi-Hong; Li, Ting; Zhou, Qiu-Zhi; Liu, Yan-Chao; Zhang, Huaqiu; Wang, Jian-Zhi (J Alzheimers Dis, 2020)
BACKGROUND: Increased tau acetylation at K174, K274, K280, and K281 has been observed in the brains of Alzheimer's disease (AD) patients or in transgenic mice, but the role of acetylation in tau propagation is elusive. OBJECTIVE: To study the effect of tau acetylation in entorhinal cortex on tau transmission and learning and memory. METHODS: Stereotactic brain injection, behavioral test, electrophysiological recording, immunohistochemistry, and immunofluorescence were used. RESULTS: We constructed the hyperacetylation mimics of tau (AAV-Tau-4Q), the non-acetylation tau mutant (AAV-Tau-4R), and the wild-type tau (AAV-Tau-WT). By overexpressing these different tau proteins in the entorhinal cortex (EC) of 2-month-old mice, we found that overexpressing Tau-4Q in EC for 3 or 6 months (to 5 or 8 months of age) neither induces tau propagation to dentate gyrus (DG) nor glial activation in DG, nor spatial memory deficit. However, overexpressing Tau-WT and Tau-4Q in EC for 13.5 months (15.5 months of age) at 2 months promoted tau propagation respectively to granulosa and hilus of DG with glial activation, synaptic dysfunction, and memory deficit, while overexpressing Tau-4R abolished tau propagation with improved cellular pathologies and cognitive functions. Furthermore, overexpressing Tau-4Q in unilateral DG of 2-month-old mice for 8 weeks also promoted its contralateral transmission with glial activation, and mice with tau (Tau-WT, Tau-4Q, and Tau-4R) overexpression in DG showed cognitive deficits compared with the empty vector controls. CONCLUSION: Tau acetylation induces a time-dependent propagation from EC to DG, and only hippocampus but not EC tau accumulation induces cognitive deficits.

Utility of MemTrax and Machine Learning Modeling in Classification of Mild Cognitive Impairment. - Bergeron, Michael F; Landset, Sara; Zhou, Xianbo; Ding, Tao; Khoshgoftaar, Taghi M; Zhao, Feng; Du, Bo; Chen, Xinjie; Wang, Xuan; Zhong, Lianmei; Liu, Xiaolei; Ashford, J Wesson (J Alzheimers Dis, 2020)
BACKGROUND: The widespread incidence and prevalence of Alzheimer's disease and mild cognitive impairment (MCI) has prompted an urgent call for research to validate early detection cognitive screening and assessment. OBJECTIVE: Our primary research aim was to determine if selected MemTrax performance metrics and relevant demographics and health profile characteristics can be effectively utilized in predictive models developed with machine learning to classify cognitive health (normal versus MCI), as would be indicated by the Montreal Cognitive Assessment (MoCA). METHODS: We conducted a cross-sectional study on 259 neurology, memory clinic, and internal medicine adult patients recruited from two hospitals in China. Each patient was given the Chinese-language MoCA and self-administered the continuous recognition MemTrax online episodic memory test on the same day. Predictive classification models were built using machine learning with 10-fold cross validation, and model performance was measured using Area Under the Receiver Operating Characteristic Curve (AUC). Models were built using two MemTrax performance metrics (percent correct, response time), along with the eight common demographic and personal history features. RESULTS: Comparing the learners across selected combinations of MoCA scores and thresholds, Naïve Bayes was generally the top-performing learner with an overall classification performance of 0.9093. Further, among the top three learners, MemTrax-based classification performance overall was superior using just the top-ranked four features (0.9119) compared to using all 10 common features (0.8999). CONCLUSION: MemTrax performance can be effectively utilized in a machine learning classification predictive model screening application for detecting early stage cognitive impairment.

Validation of Plasma Proteomic Biomarkers Relating to Brain Amyloid Burden in the EMIF-Alzheimer's Disease Multimodal Biomarker Discovery Cohort. - Westwood, Sarah; Baird, Alison L; Anand, Sneha N; Nevado-Holgado, Alejo J; Kormilitzin, Andrey; Shi, Liu; Hye, Abdul; Ashton, Nicholas J; Morgan, Angharad R; Bos, Isabelle; Vos, Stephanie J B; Baker, Susan; et al. (J Alzheimers Dis, 2020)
We have previously investigated, discovered, and replicated plasma protein biomarkers for use to triage potential trials participants for PET or cerebrospinal fluid measures of Alzheimer's disease (AD) pathology. This study sought to undertake validation of these candidate plasma biomarkers in a large, multi-center sample collection. Targeted plasma analyses of 34 proteins with prior evidence for prediction of in vivo pathology were conducted in up to 1,000 samples from cognitively healthy elderly individuals, people with mild cognitive impairment, and in patients with AD-type dementia, selected from the EMIF-AD catalogue. Proteins were measured using Luminex xMAP, ELISA, and Meso Scale Discovery assays. Seven proteins replicated in their ability to predict in vivo amyloid pathology. These proteins form a biomarker panel that, along with age, could significantly discriminate between individuals with high and low amyloid pathology with an area under the curve of 0.74. The performance of this biomarker panel remained consistent when tested in apolipoprotein E ɛ4 non-carrier individuals only. This blood-based panel is biologically relevant, measurable using practical immunocapture arrays, and could significantly reduce the cost incurred to clinical trials through screen failure.

Waist Circumference and Domain-Specific Cognitive Function Among Non-Demented Japanese Older Adults Stratified by Sex: Results from the Takashima Cognition Study. - Waki, Takashi; Tanaka-Mizuno, Sachiko; Takashima, Naoyuki; Takechi, Hajime; Hayakawa, Takehito; Miura, Katsuyuki; Ueshima, Hirotsugu; Kita, Yoshikuni; Dodge, Hiroko H (J Alzheimers Dis, 2020)
BACKGROUND: While being obese in mid-life is associated with an increased risk of dementia and cognitive decline in late-life, being obese in late-life is shown to be associated with a lower risk of these outcomes in some studies. This phenomenon is known as the "obesity paradox", but the underlying reasons and potential sex difference have not been well understood. OBJECTIVE: To investigate the association between cognition and waist circumference (WC), an alternative measure of body fat which can be measured easier than body mass index (BMI), among older adults in each generation of late-life for men and women separately. METHODS: Three hundred thirty-five participants were used in the current study who were identified by random sampling of residents aged 65-74, 75-84, and 85 + years in Takashima County, Shiga Prefecture, Japan during 2005-2006. Associations between WC and domain-specific cognitive functions measured by 12 neuropsychological tests were examined using multivariable linear regression models with covariates: age, education, and hypertension. RESULTS: Larger WC was associated with better attention/working memory among 65-74-year old women and with better learning/acquisition among 65-74-year-old men, while larger WC was associated with worse learning/acquisition, memory, attention/working memory, and language/fluency among 75-84-year old men. CONCLUSION: We found age and sex differences in the association between WC and domain-specific cognitive functions. Among older old men (age 75-84) larger WC had negative effects on various domains including memory, attention, language, and executive functions, while we did not find any negative effects of larger WC on cognition among women in any age groups.

18F-FDG Is a Superior Indicator of Cognitive Performance Compared to 18F-Florbetapir in Alzheimer's Disease and Mild Cognitive Impairment Evaluation: A Global Quantitative Analysis. - Khosravi, Mohsen; Peter, Jonah; Wintering, Nancy A; Serruya, Mijail; Shamchi, Sara Pourhassan; Werner, Thomas J; Alavi, Abass; Newberg, Andrew B (J Alzheimers Dis, 2019)
BACKGROUND: 18F-Fluorodeoxyglucose (18F-FDG) positron emission tomography (PET) and 18F-florbetapir PET are approved neuroimaging biomarkers for the Alzheimer's disease (AD) and mild cognitive impairment (MCI). OBJECTIVES: This study aims to compare the efficacy of 18F-FDG and 18F-florbetapir PET at evaluating the cognitive performance of patients with AD, MCI, and normal controls (NCs). METHODS: 63 subjects (36 male/27 female, mean age = 68.3) including 19 AD, 23 MCI, and 21 NCs underwent 18F-FDG and 18F-florbetapir PET imaging. A global quantification approach was applied on supra-tentorial, frontal, parieto-occipital, temporal, and cerebellar brain regions by calculating the global SUVmean ratios (GSUVr) as the weighted average of all regional SUVmean. 18F-FDG and 18F-florbetapir GSUVr of each region were subsequently correlated with the Mini-Mental Status Examination (MMSE). RESULTS: Subjects were studied in five categories as NC, MCI patients, AD patients, MCI and AD patients grouped together (MCI/AD), and a group including all the subjects (NC/MCI/AD). Both 18F-FDG and 18F-florbetapir could successfully detect subjects with dementia (p <  0.001). Studied in all regions and groups, the correlation analysis of 18F-FDG GSUVr with MMSE scores was significant in more regions and groups compared to that of 18F-florbetapir. We also demonstrated that the correlation of 18F-FDG GSUVr with MMSE is stronger than that of 18F-florbetapir in the supra-tentorial and temporal regions. CONCLUSIONS: This study reveals how 18F-FDG-PET global quantification is a superior indicator of cognitive performance in AD and MCI patients compared to 18F-florbetapir PET. Accordingly, we still recommend 18F-FDG-PET over amyloid imaging in the evaluation for AD and MCI.

APOE Effect on Amyloid-β PET Spatial Distribution, Deposition Rate, and Cut-Points. - Toledo, Jon B; Habes, Mohamad; Sotiras, Aristeidis; Bjerke, Maria; Fan, Yong; Weiner, Michael W; Shaw, Leslie M; Davatzikos, Christos; Trojanowski, John Q (J Alzheimers Dis, 2019)
There are conflicting results regarding how APOE genotype, the strongest genetic risk factor for Alzheimer's disease (AD), influences spatial and longitudinal amyloid-β (Aβ) deposition and its impact on the selection of biomarker cut-points. In our study, we sought to determine the impact of APOE genotype on cross-sectional and longitudinal florbetapir positron emission tomography (PET) amyloid measures and its impact in classification of patients and interpretation of clinical cohort results. We included 1,019 and 1,072 Alzheimer's Disease Neuroimaging Initiative participants with cerebrospinal fluid Aβ1 - 42 and florbetapir PET values, respectively. 623 of these subjects had a second florbetapir PET scans two years after the baseline visit. We evaluated the effect of APOE genotype on Aβ distribution pattern, pathological biomarker cut-points, cross-sectional clinical associations with Aβ load, and longitudinal Aβ deposition rate measured using florbetapir PET scans. 1) APOEɛ4 genotype influences brain amyloid deposition pattern; 2) APOEɛ4 genotype does not modify Aβ biomarker cut-points estimated using unsupervised mixture modeling methods if white matter and brainstem references are used (but not when cerebellum is used as a reference); 3) findings of large differences in Aβ biomarker value differences based on APOE genotype are due to increased probability of having AD neuropathology and are most significant in mild cognitive impairment subjects; and 4) APOE genotype and age (but not gender) were associated with increased Aβ deposition rate. APOEɛ4 carrier status affects rate and location of brain Aβ deposition but does not affect choice of biomarker cut-points if adequate references are selected for florbetapir PET processing.

APOE ɛ4 Carriers Show Delayed Recovery of Verbal Memory and Smaller Entorhinal Volume in the First Year After Ischemic Stroke. - Werden, Emilio; Khlif, Mohamed Salah; Bird, Laura J; Cumming, Toby; Bradshaw, Jennifer; Khan, Wasim; Pase, Matthew; Restrepo, Carolina; Veldsman, Michele; Egorova, Natalia; Patel, Sheila K; Gottlieb, Elie; et al. (J Alzheimers Dis, 2019)
BACKGROUND: The apolipoprotein E (APOE) gene ɛ4 allele is a risk factor for Alzheimer's disease and cardiovascular disease. However, its relationship with cognition and brain volume after stroke is not clear. OBJECTIVE: We compared cognition and medial temporal lobe volumes in APOEɛ4 carriers and non-carriers in the first year after ischemic stroke. METHODS: We sampled 20 APOEɛ4 carriers and 20 non-carriers from a larger cohort of 135 ischemic stroke participants in the longitudinal CANVAS study. Participants were matched on a range of demographic and stroke characteristics. We used linear mixed-effect models to compare cognitive domain z-scores (attention, processing speed, executive function, verbal and visual memory, language, visuospatial function) and regional medial temporal lobe volumes (hippocampal, entorhinal cortex) between groups at each time-point (three, 12-months post-stroke), and within groups across time-points. APOE gene single nucleotide polymorphisms (SNPs; rs7412, rs429358) were genotyped on venous blood. RESULTS: APOEɛ4 carriers and non-carriers did not differ on any demographic, clinical, or stroke variable. Carriers performed worse than non-carriers in verbal memory at three months post-stroke (p = 0.046), but were better in executive function at 12 months (p = 0.035). Carriers demonstrated a significant improvement in verbal memory (p = 0.012) and executive function (p = 0.015) between time-points. Non-carriers demonstrated a significant improvement in visual memory (p = 0.0005). Carriers had smaller bilateral entorhinal cortex volumes (p <  0.05), and larger-right-sided and contralesional hippocampal volumes, at both time-points (p <  0.05). CONCLUSION: APOE ɛ4 is associated with delayed recovery of verbal memory function and reduced entorhinal cortex volumes in the first year after ischemic stroke.

Association of Cognitive Function with Amyloid-β and Tau Proteins in the Vitreous Humor. - Wright, Lauren M; Stein, Thor D; Jun, Gyungah; Chung, Jaeyoon; McConnell, Kate; Fiorello, Marissa; Siegel, Nicole; Ness, Steven; Xia, Weiming; Turner, Kelley L; Subramanian, Manju L (J Alzheimers Dis, 2019)
BACKGROUND: The eye may serve as source for diagnostic testing for early detection of Alzheimer's disease (AD). Examination of amyloid-β (Aβ) and tau protein content in human vitreous and its correlation to neuro-cognition may improve ocular-based AD detection methods. OBJECTIVE: To evaluate levels of Aβ and tau protein in human vitreous humor and investigate the clinical predictive role of these proteins as early diagnostic markers of AD. METHODS: A prospective, single-center, multi-surgeon cohort study. Vitreous humor samples from 80 eyes were measured quantitatively for Aβ40-42, pTau, and tTau. Linear regression was used to test associations between AD biomarker levels, Mini-Mental State Exam (MMSE), and serum apolipoprotein E (APOE) allele status, with adjustment for age, sex, and education level of patients. RESULTS: Lower MMSE scores were significantly associated with lower levels of vitreous Aβ40 (p = 0.015), Aβ42 (p = 0.0066), and tTau (p = 0.0085), and these biomarkers were not associated with any pre-existing eye conditions. Presence of the ɛ4 allele and the ɛ2 allele approached significance with reduced Aβ40 level (p = 0.053) and increased p-Tau level (p = 0.056), respectively. CONCLUSION: Patients with poor cognitive function have significantly lower vitreous humor levels of AD-related biomarkers Aβ40, Aβ42, and tTau. These biomarkers do not correlate with underlying eye conditions, suggesting their specificity in association with cognitive change. This is the first study to our knowledge to correlate cognition with AD-related proteins in the vitreous humor. Results suggest ocular proteins may have a role for early dementia detection in individuals at risk for AD.

A Clinical Trial of Transcranial Electromagnetic Treatment in Alzheimer's Disease: Cognitive Enhancement and Associated Changes in Cerebrospinal Fluid, Blood, and Brain Imaging. - Arendash, Gary; Cao, Chuanhai; Abulaban, Haitham; Baranowski, Rob; Wisniewski, Gary; Becerra, Lino; Andel, Ross; Lin, Xiaoyang; Zhang, Xiaolin; Wittwer, David; Moulton, Jay; Arrington, John; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Small aggregates (oligomers) of the toxic proteins amyloid-β (Aβ) and phospho-tau (p-tau) are essential contributors to Alzheimer's disease (AD). In mouse models for AD or human AD brain extracts, Transcranial Electromagnetic Treatment (TEMT) disaggregates both Aβ and p-tau oligomers, and induces brain mitochondrial enhancement. These apparent "disease-modifying" actions of TEMT both prevent and reverse memory impairment in AD transgenic mice. OBJECTIVE: To evaluate the safety and initial clinical efficacy of TEMT against AD, a comprehensive open-label clinical trial was performed. METHODS: Eight mild/moderate AD patients were treated with TEMT in-home by their caregivers for 2 months utilizing a unique head device. TEMT was given for two 1-hour periods each day, with subjects primarily evaluated at baseline, end-of-treatment, and 2 weeks following treatment completion. RESULTS: No deleterious behavioral effects, discomfort, or physiologic changes resulted from 2 months of TEMT, as well as no evidence of tumor or microhemorrhage induction. TEMT induced clinically important and statistically significant improvements in ADAS-cog, as well as in the Rey AVLT. TEMT also produced increases in cerebrospinal fluid (CSF) levels of soluble Aβ1-40 and Aβ1-42, cognition-related changes in CSF oligomeric Aβ, a decreased CSF p-tau/Aβ1-42 ratio, and reduced levels of oligomeric Aβ in plasma. Pre- versus post-treatment FDG-PET brain scans revealed stable cerebral glucose utilization, with several subjects exhibiting enhanced glucose utilization. Evaluation of diffusion tensor imaging (fractional anisotropy) scans in individual subjects provided support for TEMT-induced increases in functional connectivity within the cognitively-important cingulate cortex/cingulum. CONCLUSION: TEMT administration to AD subjects appears to be safe, while providing cognitive enhancement, changes to CSF/blood AD markers, and evidence of stable/enhanced brain connectivity.

Clinico-Neuropathological Findings in the Oldest Old from the Georgia Centenarian Study. - Tanprasertsuk, Jirayu; Johnson, Elizabeth J; Johnson, Mary Ann; Poon, Leonard W; Nelson, Peter T; Davey, Adam; Martin, Peter; Barbey, Aron K; Barger, Kathryn; Wang, Xiang-Dong; Scott, Tammy M (J Alzheimers Dis, 2019)
BACKGROUND: Centenarian studies are important sources for understanding of factors that contribute to longevity and healthy aging. Clinico-neuropathological finding is a key in identifying pathology and factors contributing to age-related cognitive decline and dementia in the oldest old. OBJECTIVE: To characterize the cross-sectional relationship between neuropathologies and measures of premortem cognitive performance in centenarians. METHODS: Data were acquired from 49 centenarians (≥98 years) from the Georgia Centenarian Study. Cognitive assessment from the time point closest to mortality was used ( RESULTS: Wide ranges of AD-type neuropathological changes were observed in both non-demented and demented subjects. Neocortical NFT and Braak staging were related to clinical dementia rating. Neocortical NFT and NP, Braak and NIARI staging, cerebral and ventricular atrophy, HS, CAA, and TDP-43 proteinopathy were differentially associated with poor performance in multiple cognitive domains and activities of daily living. CONCLUSION: AD-type pathology was associated with severe dementia and poor cognition but was not the only variable that explained cognitive impairment, indicating the complexity and heterogeneity of pathophysiology of dementia in the oldest old.

A Comparison of Partial Volume Correction Techniques for Measuring Change in Serial Amyloid PET SUVR. - Schwarz, Christopher G; Gunter, Jeffrey L; Lowe, Val J; Weigand, Stephen; Vemuri, Prashanthi; Senjem, Matthew L; Petersen, Ronald C; Knopman, David S; Jack, Clifford R (J Alzheimers Dis, 2019)
Longitudinal PET studies in aging and Alzheimer's disease populations rely on accurate and precise measurements of change over time from serial PET scans. Various methods for partial volume correction (PVC) are commonly applied to such studies, but existing comparisons and validations of these PVC methods have focused on cross-sectional measurements. Rate of change measurements inherently have smaller magnitudes than cross-sectional measurements, so levels of noise amplification due to PVC must be smaller, and it is necessary to re-evaluate methods in this context. Here we compare the relative precision in longitudinal measurements from serial amyloid PET scans when using geometric transfer matrix (GTM) PVC versus the traditional two-compartment (Meltzer-style), three-compartment (Müller-Gärtner-style), and no-PVC approaches. We used two independent implementations of standardized uptake value ratio (SUVR) measurement and PVC (one in-house pipeline based on SPM12 and ANTs, and one using FreeSurfer 6.0). For each approach, we also tested longitudinal-specific variants. Overall, we found that measurements using GTM PVC had significantly worse relative precision (unexplained within-subject variability ≈4-8%) than those using two-compartment, three-compartment, or no PVC (≈2-4%). Longitudinally-stabilized approaches did not improve these properties. This data suggests that GTM PVC methods may be less suitable than traditional approaches when measuring within-person change over time in longitudinal amyloid PET.

Effect of Advanced Glycation End Products on the Progression of Alzheimer's Disease. - Chou, Ping-Song; Wu, Meng-Ni; Yang, Chen-Cheng; Shen, Cheng-Ting; Yang, Yuan-Han (J Alzheimers Dis, 2019)
BACKGROUND: Shared links between type 2 diabetes mellitus (T2DM) and Alzheimer's disease (AD) have been well-known. A high concentration of advanced glycation end products (AGEs) has been reported to contribute to impaired mobility in patients with AD, but there is limited understanding regarding the longitudinal impact of AGEs on cognitive performance. OBJECTIVE: This study aims to explore whether the concentrations of AGEs mediate the clinical progression of cognitive performance in patients with AD and T2DM. METHODS: Twenty-five patients aged 79.0±5.8 years who were diagnosed with probable AD with a Clinical Dementia Rating (CDR) of 0.5 or 1 and T2DM were enrolled in this study. When patients participated in the study, the concentration of plasma AGEs was tested. A series of neuropsychological tests, namely the Mini-Mental Status Examination (MMSE), Cognitive Assessment Screening Instrument (CASI), and CDR, were performed annually during follow-up. The association between the concentration of AGEs and changes in overall cognition and cognition related daily living performance was analyzed. RESULTS: After the mean 48.6±2.1 months of follow-up, AGEs were found to be significantly associated with a change in CDR. A total of 12 (48% ) patients experienced a decline in CDR; they had a significantly higher concentration of AGEs than did those whose CDR did not deteriorate (100.5 ± 14.2 versus 81.5 ± 17.7; p = 0.007). This difference in CDR remained significant after adjustment for age, sex, education level, and apolipoprotein E4 status (adjusted p = 0.020). CONCLUSION: In conclusion, this study indicates that a high concentration of AGEs may be a predictor of a long-term decline in cognition related daily living performance in patients with AD and T2DM.

Ethical Issues in the Treatment of Late-Stage Alzheimer's Disease. - Watt, Andrew D; Jenkins, Nicole L; McColl, Gawain; Collins, Steven; Desmond, Patricia M (J Alzheimers Dis, 2019)
There is hope that the continuing efforts of researchers will yield a disease-modifying drug for Alzheimer's disease. Such a drug is likely to be capable of halting, or significantly slowing, the underlying pathological processes driving cognitive decline; however, it is unlikely to be capable of restoring brain function already lost through the pathological process. A therapy capable of halting Alzheimer's disease, while not providing restoration of function, may prompt serious ethical questions. For example, is there a stage in the disease process when it becomes too late for therapeutic intervention to commence? And who bears the responsibility of making such a decision? Conversations regarding the ethics of treating neurodegenerative conditions with non-restorative drugs have been largely absent within both clinical and research communities. Such discussions are urgently required to ensure that patients' rights and well-being are protected when such therapeutic options become available.

Evaluation of Medicare Claims Data as a Tool to Identify Dementia. - Lee, Eunjung; Gatz, Margaret; Tseng, Chiuchen; Schneider, Lon S; Pawluczyk, Sonia; Wu, Anna H; Deapen, Dennis (J Alzheimers Dis, 2019)
BACKGROUND: Medicare claims record linkage has been used to identify diagnosed dementia cases in order to estimate dementia prevalence and cost of care. Claims records in the 1990 s and early 2000 s have been found to provide 85% - ∼90% sensitivity and specificity. OBJECTIVE: Considering that dementia awareness has improved over time, we sought to examine sensitivity and specificity of more recent Medicare claims records against a standard criterion, clinical diagnosis of dementia. METHODS: For a sample of patients evaluated at the University of Southern California Alzheimer Disease Research Center (ADRC), we performed database linkage with Medicare claims files for a six-year period, 2007-2012. We used clinical diagnosis at the ADRC as the criterion diagnosis in order to calculate sensitivity and specificity. RESULTS: Medicare claims correctly identified 85% of dementia patients and 77% of individuals with normal cognition. About half of patients clinically diagnosed with mild cognitive impairment had dementia diagnoses in Medicare claims. Misclassified dementia patients (i.e., missed diagnosis by Medicare claims) had more favorable Mini-Mental State Examination and Clinical Dementia Rating scores and were less likely to present behavioral symptoms than correctly-classified dementia patients. CONCLUSIONS: Database linkage to Medicare claims records is an efficient and reasonably accurate tool to identify dementia cases in a population-based cohort. However, possibilities of obtaining biased results due to misclassification of dementia status need to be carefully considered to use Medicare claims diagnosis for etiologic research studies. Additional confirmation of dementia diagnosis may also be considered. A larger study is warranted to confirm our findings.

Exercise Training in Amnestic Mild Cognitive Impairment: A One-Year Randomized Controlled Trial. - Tarumi, Takashi; Rossetti, Heidi; Thomas, Binu P; Harris, Thomas; Tseng, Benjamin Y; Turner, Marcel; Wang, Ciwen; German, Zohre; Martin-Cook, Kristin; Stowe, Ann M; Womack, Kyle B; Mathews, Dana; et al. (J Alzheimers Dis, 2019)
BACKGROUND: The current evidence is inconclusive to support the benefits of aerobic exercise training (AET) for preventing neurocognitive decline in patients with amnestic mild cognitive impairment (aMCI). OBJECTIVE: To examine the effect of a progressive, moderate-to-high intensity AET program on memory and executive function, brain volume, and cortical amyloid-β (Aβ) plaque deposition in aMCI patients. METHODS: This is a proof-of-concept trial that randomized 70 aMCI patients to 12 months of AET or stretching and toning (SAT, active control) interventions. Primary neuropsychological outcomes were assessed by using the California Verbal Learning Test-second edition (CVLT-II) and the Delis-Kaplan Executive Function System (D-KEFS). Secondary outcomes were the global and hippocampal brain volumes and the mean cortical and precuneus Aβ deposition. RESULTS: Baseline cognitive scores were similar between the groups. Memory and executive function performance improved over time but did not differ between the AET and SAT groups. Brain volume decreased and precuneus Aβ plaque deposition increased over time but did not differ between the groups. Cardiorespiratory fitness was significantly improved in the AET compared with SAT group. In amyloid positive patients, AET was associated with reduced hippocampal atrophy when compared with the SAT group. CONCLUSION: The AET and SAT groups both showed evidence of slightly improved neuropsychological scores in previously sedentary aMCI patients. However, these interventions did not prevent brain atrophy or increases in cortical Aβ deposition over 12 months. In amyloid positive patients, AET reduced hippocampal atrophy when compared with the SAT group.

A Fragment of S38AA is a Novel Plasma Biomarker of Alzheimer's Disease. - Hashimoto, Masakazu; Yamazaki, Akira; Ohno, Atsushi; Kimura, Toru; Winblad, Bengt; Tjernberg, Lars O (J Alzheimers Dis, 2019)
Alzheimer's disease (AD) is a progressive neurodegenerative disease without a cure. The pathological process starts decades before clinical onset, and thus clinical trials of drugs aimed at treating AD should start at a presymptomatic stage. Therefore, it is critical to diagnose AD at an early stage. Tau, phosphorylated tau, and amyloid-β peptide (Aβ) in cerebrospinal fluid (CSF), and positron emission tomography (PET) imaging of Aβ or tau accumulation are supportive biomarkers for AD diagnosis, but there is no reliable presymptomatic diagnostic marker. Since CSF sampling is invasive, and PET imaging is expensive and available only at specialized centers, a reliable blood biomarker has long been sought for. Here we describe a novel extramembrane fragment from solute carrier family 38 member 10 (SLC38A10, S38AA) that we found to be decreased in pyramidal neurons in AD cases by proteomics and immunohistochemical analysis. We detected a S38AA fragment in CSF and found the levels to correlate with severity of AD and APOE genotype. Importantly, the plasma levels of the fragment also showed a significant correlation with Mini-Mental State Examination scores in AD. Moreover, plasma from other neurodegenerative disease was analyzed and the fragment was found to be increased specifically in AD. Interestingly, the fragment is detected in mouse, rat, and monkey, and increases in amyloid precursor protein transgenic mice as the AD-like pathology progresses. We propose that the S38AA fragment in plasma could be a novel quantitative diagnostic marker for AD and potentially a marker of disease progression in AD.

Geographical Variation in the Diagnostic Rate and Quality of Dementia Diagnoses. - Zakarias, Johanne Købstrup; Jensen-Dahm, Christina; Nørgaard, Ane; Roos, Peter; Gasse, Christiane; Phung, Thien Kieu Thi; Waldemar, Gunhild (J Alzheimers Dis, 2019)
BACKGROUND: Early and accurate diagnosis of dementia opens the door to appropriate treatment, support, and counseling. Despite availability of evidence-based guidelines for diagnostic evaluation of dementia, the diagnostic rate in people with dementia is low and the quality of dementia diagnoses is unknown. OBJECTIVE: The overall aim of this register-based study was to analyze the quality of diagnostic evaluation of dementia by assessing nationwide geographical variations in a range of indicators. METHODS: A register-based cross-sectional study of the entire Danish population aged 65 years or older in 2015 was conducted. The surrogate indicators for diagnostic quality included 1) prevalence rates of dementia diagnoses, 2) incidence rates of dementia diagnoses, 3) age at first diagnosis of dementia, 4) medical specialty responsible for diagnosis, 5) diagnostic rate of dementia subtypes, and 6) use of anti-dementia medication. The indicators were compared across the five Danish regions. RESULTS: The national prevalence and incidence of registered dementia diagnoses was 3.0% and 0.5%, respectively. The proportion of patients diagnosed at a dementia specialist department ranged from 60.9% to 90.5% across the five regions, subtype specific diagnosis ranged from 45.3% to 75.5%, and use of anti-dementia medication ranged from 29.2% to 58.3%. CONCLUSION: The observed geographical variations in dementia diagnoses and treatment indicate inequality in the access to appropriate diagnostic evaluation and care for patients with dementia. Our findings call for more awareness of the benefits of timely diagnosis and for improvement in the quality of diagnostic evaluation of dementia.

Gut Microbiota Alteration and Its Time Course in a Tauopathy Mouse Model. - Sun, Bin-Lu; Li, Wei-Wei; Wang, Jun; Xu, Ya-Li; Sun, Hao-Lun; Tian, Ding-Yuan; Wang, Yan-Jiang; Yao, Xiu-Qing (J Alzheimers Dis, 2019)
Emerging evidence suggests that gut microbiota dysbiosis plays a role in neurodegenerative disorders. However, whether the composition and diversity of the gut microbiota are altered in tauopathies remains largely unknown. This study was aimed to examine the diversity and composition of the gut microbiota in tauopathies, as well as the correlation with pathological changes in the brain. We collected fecal samples from 32 P301L tau transgenic mice and 32 age- and gender-matched littermate mice at different ages. The 16S ribosomal RNA sequencing technique was used to analyze the microbiota composition in feces. Brain tau pathology levels were measured by immunohistochemistry. The diversity and composition of the gut microbiota significantly changed with aging. At the phylum level, the relative abundance of Bacteroidetes was increased, while Firmicutes were decreased in P301L mice compared with that in Wt mice after 3 months of age. In addition, Actinobacteria was decreased in P301L mice at 3 and 6 months of age, meanwhile Tenericutes was decreased in P301L mice at 10 months of age. Moreover, several specific macrobiota were highly associated with the levels of paired helical filament-tau or pT231-tau protein in the brain. Our findings suggest that gut microbiota changed with aging, as well as in the tauopathy mice model. Modulation of the gut microbiota may be a potential strategy for treatment of tauopathy.

Head Position During Sleep: Potential Implications for Patients with Neurodegenerative Disease. - Levendowski, Daniel J; Gamaldo, Charlene; St Louis, Erik K; Ferini-Strambi, Luigi; Hamilton, Joanne M; Salat, David; Westbrook, Philip R; Berka, Chris (J Alzheimers Dis, 2019)
BACKGROUND: The characterization of sleep in those with neurodegenerative disease (NDD) is essential in understanding the potential neurobiological mechanisms that underlie the connection between sleep disruption and NDD manifestations and progression. OBJECTIVE: Explore the inter-relationships between NDD and age, sex, diagnosis of obstructive sleep apnea, snoring, and duration of sleep time with the head in the supine and non-supine positions. METHODS: A case-control design was used to evaluate differences in sleep position obtained from multi-night, in-home Sleep Profiler recordings in 45 patients with diagnosed NDD (24 with mild cognitive impairment, 15 with Alzheimer's disease, and 6 with Lewy Body, Parkinson's, or other dementias) and 120 age-sex matched controls with normal cognition (NC). RESULTS: The frequency of supine sleep >2 h/night was significantly greater in the NDD than in the NC group (p < 0.001, odds ratio = 3.7), and remained significant after controlling for age, sex, snoring, and obstructive sleep apnea diagnosis (p = 0.01). There were no group differences in nocturnal mobility i.e., number of head position changes/h. CONCLUSION: This study demonstrates the utility of in-home measurements of sleep in defining the association of supine sleep position with neurodegenerative disorders. Our findings warrant further investigation, particularly in light of the recent evidence suggesting that sleep may an active role in the brain's ability to clear CNS neurotoxins and metabolites.

Herpes Simplex Virus, APOEɛ4, and Cognitive Decline in Old Age: Results from the Betula Cohort Study. - Lövheim, Hugo; Norman, Tove; Weidung, Bodil; Olsson, Jan; Josefsson, Maria; Adolfsson, Rolf; Nyberg, Lars; Elgh, Fredrik (J Alzheimers Dis, 2019)
BACKGROUND: Herpes simplex virus (HSV) has been suggested to play a role in Alzheimer's disease (AD) development. OBJECTIVE: The aim of the present study was to investigate the early AD-related symptom episodic memory decline in relation to HSV and carriage of allele 4 of the apolipoprotein E gene (APOEɛ4) in a large population-based cohort with a long follow-up time. METHODS: The study included 3,413 persons, with longitudinal data available for 1,293 persons with a mean follow-up time of 11.6 years. The associations between HSV carriage, APOEɛ4 carriage, and episodic memory was investigated at baseline, as well as in longitudinal analyses where individuals with and without HSV antibodies (HSV1/2 non-specific) were matched and episodic memory decline compared. RESULTS: Cross-sectional analyses revealed an age-dependent association of HSV carriage with lower episodic memory function, particularly among APOEɛ4 carriers (p = 0.008). Longitudinal analyses showed an increased risk of episodic memory decline in HSV carriers (≥65 years: p < 0.001, all ages: non-significant), and a significant interaction between HSV and APOEɛ4 for episodic memory decline (p < 0.001). CONCLUSION: In this large population-based cohort study, both cross-sectional and longitudinal results support an association between HSV carriage and declining episodic memory function, especially among APOEɛ4 carriers. The results strengthen the hypothesis that HSV is associated with AD development.

Identifying Unmet Needs of Family Dementia Caregivers: Results of the Baseline Assessment of a Cluster-Randomized Controlled Intervention Trial. - Zwingmann, Ina; Michalowsky, Bernhard; Esser, Alexander; Kaczynski, Anika; Monsees, Jessica; Keller, Armin; Hertel, Johannes; Wucherer, Diana; Thyrian, Jochen René; Eichler, Tilly; Kilimann, Ingo; Teipel, Stefan; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Caregivers providing informal care for people with dementia (PwD) often report unmet needs, burden, and health impairments. Optimal support for family dementia caregivers will likely benefit from better understanding and assessment of the prevalence and types of caregivers' unmet needs and associated socio-demographic and clinical characteristics. OBJECTIVE: The present study investigates 1) the number and types of caregivers' unmet needs, 2) socio-demographic and clinical characteristics of both PwD and caregivers, and 3) caregivers' burden and health-related outcomes that are related to caregivers' unmet needs. METHODS: The present analyses are based on cross-sectional data of n = 226 dyads of caregivers and their community-dwelling PwD participating in a comprehensive standardized, computer-based caregivers' needs assessment within a general practitioner (GP)-based, cluster-randomized intervention trial. RESULTS: A total of n = 505 unmet needs were identified for n = 171 caregivers from the intervention group at baseline. Only 24.3% caregivers reported no unmet need (n = 55), whereas 75.7% caregivers had at least one unmet need (n = 171). Caregivers had on average 2.19 unmet needs (mean = 2.19, SD = 2.15). Specifically, 53.1% of caregivers had one up to three unmet needs (n = 120), 18.6% (n = 42) had three up to six unmet needs, and 4.0% (n = 9) had more than six unmet needs. DISCUSSION: Our results underline the importance of a comprehensive needs assessment for family dementia caregivers to develop and implement concepts that can provide family dementia caregivers with optimal support.

Impacts of Overweight and Obesity in Older Age on the Risk of Dementia: A Systematic Literature Review and a Meta-Analysis. - Danat, Isaac M; Clifford, Angela; Partridge, Martin; Zhou, Weiju; Bakre, Aishat T; Chen, Anthony; McFeeters, Danielle; Smith, Tina; Wan, Yuhui; Copeland, John; Anstey, Kaarin J; Chen, Ruoling (J Alzheimers Dis, 2019)
BACKGROUND: It is unclear whether overweight and obesity in older age reduces or increases the risk of incident dementia. OBJECTIVE: To assess the impacts of overweight and obesity in older age on incident dementia. METHODS: We searched cohort studies reporting body weight measured in older age and dementia through PubMed, Embase, Medline, PyschInfo, and Cochrane library until July 2016. Sixteen articles were identified for the review. We pooled data from them and a new unpublished study from China, to calculate relative risk (RR) of incident dementia in relation to body mass index (BMI) and waist circumference (WC). RESULTS: All 16 cohort studies were undertaken in high income countries, with follow-up periods ranging between 3 to 18 years. Thirteen studies showed an inverse association between BMI and dementia, and three studies demonstrated a positive association. Pooled RR of dementia in relation to continuous BMI from 14 studied populations, including the new Chinese data, was 0.97 (95% CI 0.95-1.00); in those followed up CONCLUSION: The current evidence did not support a paradox on beneficial impacts of overweight and obesity in older age on incident dementia. More studies with long term follow up are needed to clarify the association of body weight in older age with dementia risk.

Inferring the Molecular Mechanisms of Noncoding Alzheimer's Disease-Associated Genetic Variants. - Amlie-Wolf, Alexandre; Tang, Mitchell; Way, Jessica; Dombroski, Beth; Jiang, Ming; Vrettos, Nicholas; Chou, Yi-Fan; Zhao, Yi; Kuzma, Amanda; Mlynarski, Elisabeth E; Leung, Yuk Yee; Brown, Christopher D; et al. (J Alzheimers Dis, 2019)
Most of the loci identified by genome-wide association studies (GWAS) for late-onset Alzheimer's disease (LOAD) are in strong linkage disequilibrium (LD) with nearby variants all of which could be the actual functional variants, often in non-protein-coding regions and implicating underlying gene regulatory mechanisms. We set out to characterize the causal variants, regulatory mechanisms, tissue contexts, and target genes underlying these associations. We applied our INFERNO algorithm to the top 19 non-APOE loci from the IGAP GWAS study. INFERNO annotated all LD-expanded variants at each locus with tissue-specific regulatory activity. Bayesian co-localization analysis of summary statistics and eQTL data was performed to identify tissue-specific target genes. INFERNO identified enhancer dysregulation in all 19 tag regions analyzed, significant enrichments of enhancer overlaps in the immune-related blood category, and co-localized eQTL signals overlapping enhancers from the matching tissue class in ten regions (ABCA7, BIN1, CASS4, CD2AP, CD33, CELF1, CLU, EPHA1, FERMT2, ZCWPW1). In several cases, we identified dysregulation of long noncoding RNA (lncRNA) transcripts and applied the lncRNA target identification algorithm from INFERNO to characterize their downstream biological effects. We also validated the allele-specific effects of several variants on enhancer function using luciferase expression assays. By integrating functional genomics with GWAS signals, our analysis yielded insights into the regulatory mechanisms, tissue contexts, genes, and biological processes affected by noncoding genetic variation associated with LOAD risk.

Inhibition of Calpain Protects Against Tauopathy in Transgenic P301S Tau Mice. - Liu, Mengyu; Wang, Luwen; Gao, Ju; Dong, Qing; Perry, George; Ma, Xuemei; Wang, Xinglong (J Alzheimers Dis, 2019)
Alzheimer's disease (AD) and other tauopathies are characterized by intracellular accumulation of microtubule-associated tau protein leading to neurodegeneration. Calpastatin is the endogenous inhibitor of calpain, a calcium-dependent cysteine protease that has been increasingly implicated in tauopathies. In this study, we generated a neuron specific calpastatin overexpressing knock-in transgenic mouse model and crossed it with the PS19 tauopathy mouse model expressing human P301S mutant tau protein. The forced expression of calpastatin in neurons significantly alleviated tau hyperphosphorylation measured by immunocytochemistry and immunoblot. The genetic inhibition of calpain by calpastatin also greatly suppressed characteristic hippocampal neuron loss and widespread astrogliosis and microgliosis in PS19 mice. Consistently, PS19 mice with neuronal calpastatin overexpression exhibited remarkably alleviated cognitive deficits, muscle weakness, skeletal muscle atrophy, and neuromuscular denervation, together implying the neuroprotective effects of neuronal calpastatin in PS19 mice of tauopathy. In sum, this study provides additional evidence supporting the pathological role of calpain in neurodegenerative diseases associated with tau pathology, and suggests that targeting calpain is likely a promising therapeutic approach for these devastating diseases.

Intraneuronal Tau Misfolding Induced by Extracellular Amyloid-β Oligomers. - Rudenko, Lauren K; Wallrabe, Horst; Periasamy, Ammasi; Siller, Karsten H; Svindrych, Zdenek; Seward, Matthew E; Best, Merci N; Bloom, George S (J Alzheimers Dis, 2019)
Abnormal folding and aggregation of the microtubule-associated protein, tau, is a hallmark of several neurodegenerative disorders, including Alzheimer's disease (AD). Although normal tau is an intrinsically disordered protein, it does exhibit tertiary structure whereby the N- and C-termini are often in close proximity to each other and to the contiguous microtubule-binding repeat domains that extend C-terminally from the middle of the protein. Unfolding of this paperclip-like conformation might precede formation of toxic tau oligomers and filaments, like those found in AD brain. While there are many ways to monitor tau aggregation, methods to monitor changes in tau folding are not well established. Using full length human 2N4R tau doubly labeled with the Förster resonance energy transfer (FRET) compatible fluorescent proteins, Venus and Teal, on the N- and C-termini, respectively (Venus-Tau-Teal), intensity and lifetime FRET measurements were able to distinguish folded from unfolded tau in living cells independently of tau-tau intermolecular interactions. When expression was restricted to low levels in which tau-tau aggregation was minimized, Venus-Tau-Teal was sensitive to microtubule binding, phosphorylation, and pathogenic oligomers. Of particular interest is our finding that amyloid-β oligomers (AβOs) trigger Venus-Tau-Teal unfolding in cultured mouse neurons. We thus provide direct experimental evidence that AβOs convert normally folded tau into a conformation thought to predominate in toxic tau aggregates. This finding provides further evidence for a mechanistic connection between Aβ and tau at seminal stages of AD pathogenesis.

Long-Term Trazodone Use and Cognition: A Potential Therapeutic Role for Slow-Wave Sleep Enhancers. - La, Alice L; Walsh, Christine M; Neylan, Thomas C; Vossel, Keith A; Yaffe, Kristine; Krystal, Andrew D; Miller, Bruce L; Karageorgiou, Elissaios (J Alzheimers Dis, 2019)
BACKGROUND: Recent studies reveal an association between slow-wave sleep (SWS), amyloid-β aggregation, and cognition. OBJECTIVE: This retrospective study examines whether long-term use of trazodone, an SWS enhancer, is associated with delayed cognitive decline. METHODS: We identified 25 regular trazodone users (mean age 75.4±7.5; 9 women, 16 men) who carried a diagnosis of Alzheimer's dementia, mild cognitive impairment, or normal cognition, and 25 propensity-matched trazodone non-users (mean age 74.5±8.0; 13 women, 12 men), accounting for age, sex, education, type of sleep deficit (hypersomnia, insomnia, parasomnia), diagnosis, and baseline Mini-Mental State Examination (MMSE). Longitudinal group differences in cognitive testing were evaluated through repeated measures tests over an average inter-evaluation interval of four years. RESULTS: Trazodone non-users had 2.6-fold faster decline MMSE (primary outcome) compared to trazodone users, 0.27 (95% confidence interval [CI]: 0.07-0.48) versus 0.70 (95% CI: 0.50-0.90) points per year (p = 0.023). The observed effects were especially associated with subjective improvement of sleep complaints in post-hoc analyses (p = 0.0006). Secondary outcomes of other cognitive and functional scores had variable worsening in non-users and varied in significance when accounting for co-administered medications and multiple comparisons. Trazodone effects on MMSE remained significant within participants with AD-predicted pathology, with 2.4-fold faster decline in non-users (p = 0.038). CONCLUSIONS: These results suggest an association between trazodone use and delayed cognitive decline, adding support for a potentially attractive and cost-effective intervention in dementia. Whether the observed relationship of trazodone to cognitive function is causal or an indirect marker of other effects, such as treated sleep disruption, and if such effects are mediated through SWS enhancement requires confirmation through prospective studies.

Maintain Your Brain: Protocol of a 3-Year Randomized Controlled Trial of a Personalized Multi-Modal Digital Health Intervention to Prevent Cognitive Decline Among Community Dwelling 55 to 77 Year Olds. - Heffernan, Megan; Andrews, Gavin; Fiatarone Singh, Maria A; Valenzuela, Michael; Anstey, Kaarin J; Maeder, Anthony J; McNeil, John; Jorm, Louisa; Lautenschlager, Nicola T; Sachdev, Perminder S; Ginige, Jeewani A; Hobbs, Megan J; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Maintain Your Brain (MYB) is a randomized controlled trial of an online multi-modal lifestyle intervention targeting modifiable dementia risk factors with its primary aim being to reduce cognitive decline in an older age cohort. METHODS: MYB aims to recruit 8,500 non-demented community dwelling 55 to 77 year olds from the Sax Institute's 45 and Up Study in New South Wales, Australia. Participants will be screened for risk factors related to four modules that comprise the MYB intervention: physical activity, nutrition, mental health, and cognitive training. Targeting risk factors will enable interventions to be personalized so that participants receive the most appropriate modules. MYB will run for three years and up to four modules will be delivered sequentially each quarter during year one. Upon completing a module, participants will continue to receive less frequent booster activities for their eligible modules (except for the mental health module) until the end of the trial. DISCUSSION: MYB will be the largest internet-based trial to attempt to prevent cognitive decline and potentially dementia. If successful, MYB will provide a model for not just effective intervention among older adults, but an intervention that is scalable for broad use.

Neuronal Exosome-Derived Human Tau is Toxic to Recipient Mouse Neurons in vivo. - Winston, Charisse N; Aulston, Brent; Rockenstein, Edward M; Adame, Anthony; Prikhodko, Olga; Dave, Kishan N; Mishra, Priyanka; Rissman, Robert A; Yuan, Shauna H (J Alzheimers Dis, 2019)
Progressive accumulation of aggregation-prone proteins, amyloid-β (Aβ) and hyperphosphorylated tau (p-tau), are the defining hallmarks of Alzheimer's disease (AD). The mechanisms by which Aβ and p-tau are transmitted throughout the diseased brain are not yet completely understood. Interest in exosome research has grown dramatically over the past few years, specifically due to their potential role as biomarkers for staging of neurodegenerative diseases, including AD. Despite their diagnostic utility, the pathogenic potential of exosomes has yet to be fully elucidated. In this study, we use a series of recombinant tau antibodies to characterize a new model of human tau in vivo. Exosome suspensions derived from neuronally-differentiated, human induced pluripotent stem cells that express the repeat domain of tau P301L and V337M mutations (NiPSCEs) were injected into the wild-type mouse brain and pathological changes were characterized by immunostaining at one- (1 m) and two-month (2 m) post-injection. We found that tau inclusions were present throughout the brain at 2 m post-injection, which were detectable using antibodies raised against full-length tau (K9JA) and misfolded tau (MC1). Furthermore, we found that phosphorylated tau immunoreactivity was elevated 1 m post-injection, which was surprisingly normalized after 2 m. Finally, we observed extensive degeneration of neuronal dendrites in both ipsilateral and contralateral hippocampi in NiPSCE treated mice. In summary, we demonstrate that exosomes are sufficient to cause long-distance propagation of tau pathology and neurodegeneration in vivo. These novel findings support an active role of exosomes in AD pathogenesis.

Neuron-Specific Apolipoprotein E4 (1-272) Fragment Induces Tau Hyperphosphorylation and Axonopathy via Triggering Endoplasmic Reticulum Stress. - Liang, Tao; Xue, Feixiao; Hang, Weijian; Wen, Bin; Zhang, Qianying; Chen, Jiehui; Liu, Xiaofeng; Chen, Juan (J Alzheimers Dis, 2019)
Apolipoprotein (apo) E4 is the major genetic risk factor for Alzheimer's disease (AD). It is shown that apoE4 preferentially undergoes aberrant cleavage in neurons, yielding neurotoxic C-terminal-truncated apoE4 fragment. Endoplasmic reticulum (ER) stress has also been known to be involved in the pathogenesis of AD. However, little is known about the contribution of ER stress to the neurotoxicity of apoE4 fragment. In the present study, we established the neuron-specific expression human C-terminal-truncated apoE4(1-272) fragment transgenic mice and also transfected apoE4(1-272) fragment in neuroblastoma N2a cells. We found that human apoE4(1-272) fragment could trigger ER stress as evidenced by increasing the expression of ER stress markers both in vivo and in vitro. Meanwhile, the apoE4(1-272) transgenic mice presented obviously AD-like neuropathological changes, including the impairment of spatial learning and memory, prominent axonal morphological changes, and hyperphosphorylation of tau. At the same time, we also found that glycogen synthase kinase-3 activities were significantly increased. Furthermore, these neuropathological changes, especially tau hyperphosphorylation and axonal transport impairment, were significantly rescued by the ER stress protector 4-phenylbutyric acid (4-PBA) in apoE4(1-272)-transfected N2a cells. Pretreatment with 4-PBA not only decreased the protein expression of immunoglobulin binding protein (BiP) and C/EBP-homologous protein (CHOP), but also significantly reversed these defects in axonal transport. These results suggested that the neurotoxic effects of apoE4(1-272) fragment found in AD subjects, at least in part, through triggering ER stress and inducing tau hyperphosphorylation, led to the enduring impairment of axonal transport.

Neuropsychological Deficit Profiles, Vascular Risk Factors, and Neuropathological Findings in Hispanic Older Adults with Autopsy-Confirmed Alzheimer's Disease. - Weissberger, Gali H; Gollan, Tamar H; Bondi, Mark W; Nation, Daniel A; Hansen, Lawrence A; Galasko, Douglas; Salmon, David P (J Alzheimers Dis, 2019)
This study aimed to determine if patterns of neuropsychological deficits, vascular risk factors, and neuropathology differ in Hispanic and Non-Hispanic patients with autopsy-confirmed Alzheimer's disease (AD). Participants were enrolled in a longitudinal study at the Shiley-Marcos AD Research Center at the University of California, San Diego. Hispanic (n = 14) and Non-Hispanic (n = 20) patients with autopsy-confirmed AD who scored ≥95 on the Dementia Rating Scale (DRS) were included. Patient groups were matched on age, education, global mental status, and severity of functional decline; they were compared to Hispanic (n = 14) or Non-Hispanic (n = 20) cognitively-normal controls of similar age and education. Ethnicity (Hispanic, Non-Hispanic) by disease state (autopsy-confirmed AD or cognitively normal) comparisons were made for cognitive test performance and vascular risk factors. Patient groups were further compared on measures of AD (Braak stage, neuritic plaques, neurofibrillary tangles), vascular neuropathology, and performance across cognitive domains of memory, language, attention, executive functions, and visuospatial abilities after scores were z-transformed based on respective culturally-appropriate control groups. Patient groups had similar overall AD pathology burden, whereas Hispanics with AD had more small parenchymal arteriolar disease and amyloid angiopathy than Non-Hispanics with AD. Despite largely similar pathology, Hispanics with AD were less cognitively impaired (relative to respective NC groups) than Non-Hispanics with AD, and exhibited a different pattern of deficits across cognitive domains. Findings suggest that cognitive deficits that are usually prominent in AD may be less salient in Hispanic patients and this may adversely impact the ability to clinically detect the disease in mild to moderate stages.

NP03, a Microdose Lithium Formulation, Blunts Early Amyloid Post-Plaque Neuropathology in McGill-R-Thy1-APP Alzheimer-Like Transgenic Rats. - Wilson, Edward N; Do Carmo, Sonia; Welikovitch, Lindsay A; Hall, Hélène; Aguilar, Lisi Flores; Foret, Morgan K; Iulita, M Florencia; Jia, Dan Tong; Marks, Adam R; Allard, Simon; Emmerson, Joshua T; Ducatenzeiler, Adriana; et al. (J Alzheimers Dis, 2019)
Epidemiological, preclinical, and clinical studies have suggested a role for microdose lithium in reducing Alzheimer's disease (AD) risk by modulating key mechanisms associated with AD pathology. The novel microdose lithium formulation, NP03, has disease-modifying effects in the McGill-R-Thy1-APP transgenic rat model of AD-like amyloidosis at pre-plaque stages, before frank amyloid-β (Aβ) plaque deposition, during which Aβ is primarily intraneuronal. Here, we are interested in determining whether the positive effects of microdose lithium extend into early Aβ post-plaque stages. We administered NP03 (40μg Li/kg; 1 ml/kg body weight) to McGill-R-Thy1-APP transgenic rats for 12 weeks spanning the transition phase from plaque-free to plaque-bearing. The effect of NP03 on remote working memory was assessed using the novel object recognition task. Levels of human Aβ38, Aβ40, and Aβ42 as well as levels of pro-inflammatory mediators were measured in brain-extracts and plasma using electrochemiluminescent assays. Mature Aβ plaques were visualized with a thioflavin-S staining. Vesicular acetylcholine transporter (VAChT) bouton density and levels of chemokine (C-X-C motif) ligand 1 (CXCL1), interleukin-6 (IL-6), and 4-hydroxynonenal (4-HNE) were probed using quantitative immunohistochemistry. During the early Aβ post-plaque stage, we find that NP03 rescues functional deficits in object recognition, reduces loss of cholinergic boutons in the hippocampus, reduces levels of soluble and insoluble cortical Aβ42 and reduces hippocampal Aβ plaque number. In addition, NP03 reduces markers of neuroinflammation and cellular oxidative stress. Together these results indicate that microdose lithium NP03 is effective at later stages of amyloid pathology, after appearance of Aβ plaques.

Porphyromonas gingivalis Infection Induces Amyloid-β Accumulation in Monocytes/Macrophages. - Nie, Ran; Wu, Zhou; Ni, Junjun; Zeng, Fan; Yu, Weixian; Zhang, Yufeng; Kadowaki, Tomoko; Kashiwazaki, Haruhiko; Teeling, Jessica L; Zhou, Yanmin (J Alzheimers Dis, 2019)
Abnormal accumulation of amyloid-β (Aβ) in the brain is the most significant pathological hallmark of Alzheimer's disease (AD). We have found that chronic systemic exposure to lipopolysaccharide of Porphyromonas gingivalis (P. gingivalis) induces the accumulation of Aβ in the brain of middle-aged mice. On the other hand, recent research has shown that circulating Aβ is transferred into the brain; however, the involvement of chronic systemic P. gingivalis infection in the peripheral Aβ metabolism is unknown. We hypothesized that chronic P. gingivalis infection expands Aβ pools in peripheral inflammatory tissues and thereby contributes to the accumulation of Aβ in the brain of patients with periodontitis. We showed that the increased expression of IL-1β, AβPP770, CatB, Aβ1-42, and Aβ3-42 was mainly co-localized with macrophages in the liver of P. gingivalis infected mice. Blocking CatB and NF-κB significantly inhibited the P. gingivalis-induced expression of IL-1β, AβPP770, Aβ1-42, and Aβ3-42 in RAW264.7 cells. Aβ3-42, but not Aβ1-42, induced the significant death of macrophages, and the reduction of phagocytic abilities induced by Aβ3-42 tended to be higher than that induced by Aβ1-42. Additionally, the expression of AβPP770, CatB, Aβ1-42, and Aβ3-42 was determined in the macrophages of gingival tissues from periodontitis patients. These findings indicate that chronic systemic P. gingivalis infection induces the Aβ accumulation in inflammatory monocytes/macrophages via the activation of CatB/NF-κB signaling, thus suggesting monocytes/macrophages serve as a circulating pool of Aβ in patients with periodontitis. Taken together, CatB may be a novel therapeutic target for preventing the periodontitis-related AD initiation and pathological progression.

The Prevalence and Subtypes of Young Onset Dementia in Central Norway: A Population-Based Study. - Kvello-Alme, Marte; Bråthen, Geir; White, Linda R; Sando, Sigrid Botne (J Alzheimers Dis, 2019)
BACKGROUND: Young onset dementia poses several challenges for the individual, health care, and society that are not normally relevant for late onset dementia, but is little researched. OBJECTIVE: To determine the prevalence and subtypes of young onset dementia in a defined catchment area in central Norway. METHODS: The main sources of patient identification were the databases at the Department of Neurology, University Hospital of Trondheim (St. Olav's Hospital), and Department of Psychiatry, Levanger Hospital. Both departments are the main sites for referral of young onset dementia (onset before age 65 years) in the county, covering approximately 90% of the catchment area of the study. Other sources included key persons in the communities, collaborating hospital departments examining dementia, and review of hospital records of all three hospitals in the area. Included patients met the DSM-IV criteria for dementia. The prevalence of dementias was calculated by sex and age. RESULTS: All patients identified with dementia and onset before 65 years on census date were included in the study (n = 390). Patients younger than 65 on census date were included in the calculation of prevalence, giving a result of 76.3 per 100 000 persons at risk in the age category of 30-65 years, and 163.1 per 100,000 for the category 45-64 years. Etiology was heterogeneous, but the main subtype of dementia was Alzheimer's disease. CONCLUSIONS: Young onset dementia affects a significant number of people in central Norway. Prevalence figures are higher than previously reported from England and Japan, but are similar to a more recent study from Australia.

A Randomized, Double-Blind, Placebo-Controlled, Phase II Study Assessing Safety, Tolerability, and Efficacy of Bryostatin in the Treatment of Moderately Severe to Severe Alzheimer's Disease. - Farlow, Martin R; Thompson, Richard E; Wei, Lee-Jen; Tuchman, Alan J; Grenier, Elaine; Crockford, David; Wilke, Susanne; Benison, Jeffrey; Alkon, Daniel L (J Alzheimers Dis, 2019)
BACKGROUND: Bryostatin-activated PKC epsilon pre-clinically induces synaptogenesis, anti-apoptosis, anti-amyloid-β oligomers, and anti-hyperphosphorylated tau. OBJECTIVES: To investigate bryostatin safety, tolerability, and efficacy to improve cognition in advanced Alzheimer's disease (AD) patients. METHODS: A double-blind, randomized, placebo-controlled Phase II, 12-week trial of i.v. bryostatin for 150 advanced AD patients (55-85) with MMSE-2 of 4-15, randomized 1:1:1 into 20 μg and 40 μg bryostatin, and placebo arms. The Full Analysis Set (FAS) and the Completer Analysis Set (CAS) were pre-specified alternative assessments (1-sided, p < 0.1 for primary efficacy, and 2-sided, p < 0.05 for pre-specified and post hoc exploratory analyses). RESULTS: The safety profile was similar for 20 μg treatment and placebo patients. The 40 μg patients showed safety and drop-out issues, but no efficacy. Primary improvement of Severe Impairment Battery (SIB) scores at 13 weeks was not significant (p = 0.134) in the FAS, although in the CAS, the SIB comparison favored 20 μg bryostatin compared to placebo patients (p < 0.07). Secondary analyses at weeks 5 and 15 (i.e., 30 days post-final dosing) also favored 20 μg bryostatin compared to placebo patients. A pre-specified ANCOVA for baseline memantine blocking bryostatin and positive post-hoc trend analyses were statistically significant (2-sided, p < 0.05). CONCLUSION: Although the primary endpoint was not significant in the FAS, primary and secondary analyses in the CAS, and pre-specified and post-hoc exploratory analyses did favor bryostatin 20 μg compared to the placebo cohort. These promising Phase II results support further trials of 20 μg bryostatin- without memantine- to treat AD.

Subjective Cognitive Decline May Be a Stronger Predictor of Incident Dementia in Women than in Men. - Heser, Kathrin; Kleineidam, Luca; Wiese, Birgitt; Oey, Anke; Roehr, Susanne; Pabst, Alexander; Kaduszkiewicz, Hanna; van den Bussche, Hendrik; Brettschneider, Christian; König, Hans-Helmut; Weyerer, Siegfried; Werle, Jochen; et al. (J Alzheimers Dis, 2019)
BACKGROUND/OBJECTIVE: Subjective cognitive decline (SCD) has often been associated with an increased risk for subsequent dementia. However, sex-specific associations are understudied until now. METHODS: Cross-sectional and longitudinal associations over a follow-up period of up to 13 years were investigated in a sample of participants without objective cognitive impairment at baseline (n = 2,422, mean age = 79.63 years). Logistic regression and Cox proportional hazards models were conducted. RESULTS: Women less frequently reported SCD without worries (p <  0.001), but tended to report more often SCD with worries (p = 0.082) at baseline compared to men. In models adjusted for age, education, cognitive status, and depressive symptoms, SCD at baseline increased the risk for subsequent dementia (p <  0.001), and this effect was less pronounced in males (interaction sex×SCD: p = 0.022). Stratified analyses showed that SCD increased the risk for subsequent dementia in women (HR = 1.77, p <  0.001), but not in men (HR = 1.07, p = 0.682). Similar results were found in analyses with SCD without and with worries, except that SCD with worries also predicted subsequent Alzheimer's disease (AD) in men (p = 0.037). CONCLUSION: At baseline, men reported more SCD without worries and women tended to report more SCD with worries. SCD in women was more strongly associated with subsequent dementia. SCD without and with worries was related to incident dementia and AD in women, whereas in men only SCD with worries increased the risk for AD, but not for all-cause dementia.

Telomere Shortening in the Alzheimer's Disease Neuroimaging Initiative Cohort. - Nudelman, Kelly N H; Lin, Jue; Lane, Kathleen A; Nho, Kwangsik; Kim, Sungeun; Faber, Kelley M; Risacher, Shannon L; Foroud, Tatiana M; Gao, Sujuan; Davis, Justin W; Weiner, Michael W; Saykin, Andrew J (J Alzheimers Dis, 2019)
BACKGROUND: Although shorter telomeres have been associated with Alzheimer's disease (AD), it is unclear whether longitudinal change in telomere length is associated with AD progression. OBJECTIVE: To investigate the association of telomere length change with AD diagnosis and progression. METHODS: In 653 individuals from the Alzheimer's Disease Neuroimaging Initiative (ADNI) cohort, T/S ratio (telomere versus single copy gene), a proxy of telomere length, was measured for up to five visits per participant (N = 1918 samples post-QC) using quantitative PCR (qPCR). T/S ratio was adjusted for batch effects and DNA storage time. A mixed effects model was used to evaluate association of telomere length with AD diagnostic group and interaction of age and diagnosis. Another mixed effects model was used to compare T/S ratio changes pre- to post-conversion to MCI or AD to telomere change in participants with stable diagnoses. RESULTS: Shorter telomeres were associated with older age (Effect Size (ES) = -0.23) and male sex (ES = -0.26). Neither baseline T/S ratio (ES = -0.036) nor T/S ratio change (ES = 0.046) differed significantly between AD diagnostic groups. MCI/AD converters showed greater, but non-significant, telomere shortening compared to non-converters (ES = -0.186). CONCLUSIONS: Although AD compared to controls showed small, non-significant effects for baseline T/S ratio and T/S ratio shortening, we did observe a larger, though still non-significant effect for greater telomere shortening in converters compared to non-converters. Although our results do not support telomere shortening as a robust biomarker of AD progression, further investigation in larger samples and for subgroups of participants may be informative.

Two Year Outcomes, Cognitive and Behavioral Markers of Decline in Healthy, Cognitively Normal Older Persons with Global Deterioration Scale Stage 2 (Subjective Cognitive Decline with Impairment). - Reisberg, Barry; Torossian, Carol; Shulman, Melanie B; Monteiro, Isabel; Boksay, Istvan; Golomb, James; Guillo Benarous, Francoise; Ulysse, Anaztasia; Oo, Thet; Vedvyas, Alok; Rao, Julia A; Marsh, Karyn; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Little is known with respect to behavioral markers of subjective cognitive decline (SCD), a condition initially described in association with Global Deterioration Scale (GDS) stage 2. OBJECTIVE: Two-year interval behavioral markers were investigated herein. METHODS: Subjects from a published 7-year outcome study of GDS stage 2 subjects were selected. This study had demonstrated a hazard ratio of 4.5 for progression of GDS stage 2, in comparison with GDS stage 1 (no subjective or objective cognitive decline) subjects, after controlling for demographic and temporal variables. Because GDS 2 subjects have previously demonstrated impairment in comparison with healthy persons free of complaints, we herein suggest the terminology "SCD(I)" for these persons. 98 SCD(I) persons, 63 women and 35 men, mean baseline age, 67.12±8.75 years, with a mean educational background of 15.55±2.60 years, and mean baseline MMSE scores of 28.9±1.24 were followed for 2.13±0.30 years. RESULTS: Observed annual decline on the GDS was 6.701% per annum, very close to a 1986 published estimate. At follow up, the MMSE, and 7 of 8 psychometric tests did not decline significantly. Of 21 Hamilton Depression Scale items, 2 improved and the remainder were unchanged. Anxieties declined from multiple perspectives. The Brief Cognitive Rating Scale (BCRS) declined significantly (p < 0.001), with component declines in Remote memory (p < 0.01), and Functioning/self-care (p = 0.01). CONCLUSION: SCD(I) persons decline at an annual rate of approximately 6.7% /year from several recent studies. The BCRS assessments and the Digit Symbol Substitution Test can be sensitive measures for future studies of progression mitigation.

An UNC5C Allele Predicts Cognitive Decline and Hippocampal Atrophy in Clinically Normal Older Adults. - Yang, Hyun-Sik; Chhatwal, Jasmeer P; Xu, Jishu; White, Charles C; Hanseeuw, Bernard; Rabin, Jennifer S; Papp, Kathryn V; Buckley, Rachel F; Schultz, Aaron P; Properzi, Michael J; Gatchel, Jennifer R; Amariglio, Rebecca E; et al. (J Alzheimers Dis, 2019)
BACKGROUND: The UNC5C rs3846455G allele has been linked to poor cognitive resilience against age-related neuropathologies, but this association remains to be replicated, and the allele's effect on hippocampal neurodegeneration needs to be examined. OBJECTIVE: To further validate the association between rs3846455G and faster cognitive decline, especially among cognitively normal older adults, and to assess whether rs3846455G predicts accelerated hippocampal volume loss in older adults. METHODS: We assessed participants in the Harvard Aging Brain Study (HABS), a longitudinal cohort study of older adults who were clinically normal at baseline. To avoid bias from population admixture, analyses were limited to participants of European descent with longitudinal neuroimaging data (n = 174). Linear mixed effect models were used to examine the effect of rs3846455G on longitudinal change of the Preclinical Alzheimer Cognitive Composite (PACC) and MRI-measured bilateral hippocampal volume, adjusting for baseline amyloid-β (Aβ) measured by the cortical Pittsburgh Compound B PET distributed volume ratio. We also tested whether hippocampal atrophy mediates the association between rs3846455G and greater PACC decline through a mediation analysis. RESULTS: rs3846455G was associated with greater PACC decline (β= -0.087/year, 95% CI -0.169 to -0.005, p = 0.039) after controlling for baseline Aβ. Further, rs3846455G predicted accelerated hippocampal atrophy after controlling for baseline Aβ (β= -57.3 mm3/year, 95% CI -102.8 to -11.9, p = 0.014). The association between rs3846455G and greater PACC decline was partially mediated by accelerated hippocampal atrophy (mediated effect (relative scale) = -0.014, 95% CI -0.032 to -6.0×10-4, p = 0.039). CONCLUSION: UNC5C rs3846455G predicts greater cognitive decline and accelerated hippocampal atrophy in clinically normal older adults.

Upregulation of Thioredoxin-Interacting Protein in Brain of Amyloid-β Protein Precursor/Presenilin 1 Transgenic Mice and Amyloid-β Treated Neuronal Cells. - Wang, Yiran; Wang, Ying; Bharti, Veni; Zhou, Hong; Hoi, Vanessa; Tan, Hua; Wu, Zijian; Nagakannan, Pandian; Eftekharpour, Eftekhar; Wang, Jun-Feng (J Alzheimers Dis, 2019)
Oxidative stress has been hypothesized to play a role in the pathophysiology of Alzheimer's disease (AD). Previously, we found that total nitrosylated protein levels were increased in the brain of amyloid-β protein precursor (AβPP) and presenilin 1 (PS1) double transgenic mice, an animal model for AD, suggesting that cysteine oxidative protein modification may contribute to this disease. Thioredoxin (Trx) is a major oxidoreductase that can reverse cysteine oxidative modifications such as sulfenylation and nitrosylation, and inhibit oxidative stress. Thioredoxin-interacting protein (Txnip) is an endogenous Trx inhibitor. To understand the involvement of Trx and Txnip in AD development, we investigated Trx and Txnip in the brain of AβPP/PS1 mice. Using immunoblotting analysis, we found that although Trx protein levels were not changed, Txnip protein levels were significantly increased in hippocampus and frontal cortex of 9- and 12-month-old AβPP/PS1 mice when compared to wild-type mice. Txnip protein levels were also increased by amyloid-β treatment in primary cultured mouse cerebral cortical neurons and HT22 mouse hippocampal cells. Using biotin switch and dimedone conjugation methods, we found that amyloid-β treatment increased protein nitrosylation and sulfenylation in HT22 cells. We also found that downregulation of Txnip, using CRISPR/Cas9 method in HT22 cells, attenuated amyloid-β-induced protein nitrosylation and sulfenylation. Our findings suggest that amyloid-β may increase Txnip levels, subsequently inhibiting Trx reducing capability and enhancing protein cysteine oxidative modification. Our findings also indicate that Txnip may be a potential target for the treatment of AD.

Vital Exhaustion and Incidence of Dementia: Results from the Copenhagen City Heart Study. - Islamoska, Sabrina; Ishtiak-Ahmed, Kazi; Hansen, Åse Marie; Grynderup, Matias Brødsgaard; Mortensen, Erik Lykke; Garde, Anne Helene; Gyntelberg, Finn; Prescott, Eva Irene Bossano; Török, Eszter; Waldemar, Gunhild; Nabe-Nielsen, Kirsten (J Alzheimers Dis, 2019)
BACKGROUND: Psychological distress is potentially linked to the risk of dementia through neurologic and cardiovascular mechanisms. Vital exhaustion (VE) is a mental state of psychological distress, which could be a risk factor for dementia. OBJECTIVE: To investigate whether VE is a risk factor for dementia in later life. METHODS: We used data from 6,807 participants attending the third survey of the Copenhagen City Heart Study in 1991-1994. VE was assessed by 17 symptoms (score: 0-17) from the Maastricht Questionnaire. Information on dementia was obtained from national registers. Risk time for dementia was counted from five years after VE assessment for participants > 55 years at the time of VE assessment. For younger participants, risk time for dementia was counted from the year they turned 60 years and onwards. Participants were followed until 2016. We used Poisson regression to calculate incidence rate ratios (IRR) and their 95% confidence intervals (CI). RESULTS: During an average follow-up of 10 years, 872 participants were registered with dementia. We found a dose-response relation between the number of VE symptoms and the incidence of dementia. For every additional VE symptom, the dementia incidence increased by 2% (IRR = 1.024; 95% CI: 1.004-1.043). Adjustment for socio-demographic and health-related factors did not change the results substantially. Neither did stratification by age, sex, educational level, and marital status. CONCLUSION: We found evidence that VE is a risk factor for dementia. Our sensitivity analyses supported that this association was not only due to VE being a potential prodromal sign of dementia.

Why Is Amyloid-β PET Requested After Performing Cerebrospinal Fluid Biomarkers? - Reimand, Juhan; Groot, Colin; Teunissen, Charlotte E; Windhorst, Albert D; Boellaard, Ronald; Barkhof, Frederik; Nazarenko, Sergei; van der Flier, Wiesje M; van Berckel, Bart N M; Scheltens, Philip; Ossenkoppele, Rik; Bouwman, Femke (J Alzheimers Dis, 2019)
BACKGROUND: Amyloid-β PET and cerebrospinal fluid (CSF) Aβ42 are considered interchangeable for clinical diagnosis of Alzheimer's disease. OBJECTIVE: To explore the clinical reasoning for requesting additional amyloid-β PET after performing CSF biomarkers. METHODS: We retrospectively identified 72 memory clinic patients who underwent amyloid-β PET after CSF biomarkers analysis for clinical diagnostic evaluation between 2011 and 2019. We performed patient chart reviews to identify factors which led to additional amyloid-β PET. Additionally, we assessed accordance with appropriate-use-criteria (AUC) for amyloid-β PET. RESULTS: Mean patient age was 62.0 (SD = 8.1) and mean Mini-Mental State Exam score was 23.6 (SD = 3.8). CSF analysis conflicting with the clinical diagnosis was the most frequent reason for requesting an amyloid-β PET scan (n = 53, 74%), followed by incongruent MRI (n = 16, 22%), unusual clinical presentation (n = 11, 15%) and young age (n = 8, 11%). An amyloid-β PET scan was rarely (n = 5, 7%) requested in patients with a CSF Aβ+/tau+ status. Fifteen (47%) patients with a post-PET diagnosis of AD had a predominantly non-amnestic presentation. In n = 11 (15%) cases, the reason that the clinician requested amyloid-β was not covered by AUC. This happened most often (n = 7) when previous CSF analysis did not support current clinical diagnosis, which led to requesting amyloid-β PET. CONCLUSION: In this single-center study, the main reason for requesting an amyloid-β PET scan after performing CSF biomarkers was the occurrence of a mismatch between the primary clinical diagnosis and CSF Aβ/tau results.

11C-CFT-PET in Presymptomatic FTDP-17: A Potential Biomarker Predicting Onset. - Wu, Liyong; Liu, Jia; Feng, Xueyan; Dong, Jing; Qin, Wei; Liu, Yang; Wang, Jingjuan; Lu, Jie; Chen, Kewei; Wang, Yuping; Jia, Jianping (J Alzheimers Dis, 2018)
Frontotemporal dementia with parkinsonism-linked to chromosome 17 (FTDP-17) is a rare autosomal dominant neurodegenerative disorder. Most patients with FTDP-17 carry the mutation in the microtubule-associated protein tau (MAPT) gene. Striatum is predominantly and early affected in FTDP-17. Five family members (two symptomatic patients and three presymptomatic mutation carriers) from a Chinese pedigree of FTDP-17 with N279K mutation in MAPT were enrolled. Parkinsonism was the initial symptom for symptomatic patients. 2b-carbomethoxy-3b-(4-trimethylstannylphenyl) tropane (11C-CFT) uptake was obviously affected in the putamen of two presymptomatic mutation carriers. Presymptomatic case 3, whose 11C-CFT uptake in the right putamen was normal at baseline, was still free of parkinsonism during follow-up. In conclusion, 11C-CFT-positron emission tomography could be a potential biomarker for the presymptomatic stage of FTDP-17 to predict the disease onset.
Keywords: Adult; Biomarkers; Brain; Carbon Radioisotopes; Female; Frontotemporal Dementia; Heterozygote; Humans; Male; Middle Aged; Mutation; Parkinsonian Disorders; Pedigree; Positron-Emission Tomography; tau Proteins

The 20-Year Voyage Aboard the Journal of Alzheimer's Disease: Docking at 'Type 3 Diabetes', Environmental/Exposure Factors, Pathogenic Mechanisms, and Potential Treatments. - de la Monte, Suzanne M; Tong, Ming; Wands, Jack R (J Alzheimers Dis, 2018)
The Journal of Alzheimer's Disease (JAD), founded in 1998, played a pivotal role in broadening the field of research on Alzheimer's disease (AD) by publishing a diverse range of clinical, pathological, molecular, biochemical, epidemiological, experimental, and review articles from its birth. This article recounts my own journey as an author who contributed articles to JAD over the 20 years of the journal's existence. In retrospect, it seems remarkable that a considerable body of work that originated from our group marks a trail that began with studies of vascular, stress, and mitochondrial factors in AD pathogenesis, exploded into the concept of 'Type 3 Diabetes', and continued with the characterization of how environmental, exposure, and lifestyle factors promote neurodegeneration and which therapeutic strategies could reverse the neurodegeneration cascade.

ABC Transporters Are Key Players in Alzheimer's Disease. - Pereira, Cátia D; Martins, Filipa; Wiltfang, Jens; da Cruz E Silva, Odete A B; Rebelo, Sandra (J Alzheimers Dis, 2018)
Human ATP-binding cassette (ABC) transporters mediate a critical function in the cell, namely the transport of molecules across lipid membranes. Associated to their ubiquitous tissue distribution, they are key players in cellular homeostasis but also potential causative or contributing factors for many pathologies, including Alzheimer's disease (AD). In the central nervous system (CNS), numerous ABC transporters are present throughout the brain parenchyma and especially at the blood-brain barrier (BBB). AD is a neurodegenerative disorder mainly characterized by extracellular deposition of amyloid-β (Aβ) peptides and intracellular accumulation of hyperphosphorylated forms of tau protein. Besides being degraded via proteolytic and phagocytic processes mediated by brain parenchymal cells, a major mechanism for eliminating cerebral Aβ is through its transport across the BBB into the peripheral blood. In fact, many AD cases are associated with impaired Aβ clearance. Consistently, several studies have recently uncovered important roles for ABC transporters in AD pathophysiology. Hence, this review focuses on the relevance of ABC transporters in CNS homeostasis by highlighting AD as a strong example of the deleterious consequences that might result from the former's altered expression and/or activity in the brain. The potentiality of human ABC transporters as novel pharmacological targets for both the diagnosis and therapeutics of AD is emphasized.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; ATP-Binding Cassette Transporters; Blood-Brain Barrier; Humans

Abnormal Functional Brain Networks in Mild Cognitive Impairment and Alzheimer's Disease: A Minimum Spanning Tree Analysis. - Wang, Bin; Miao, Liwen; Niu, Yan; Cao, Rui; Li, Dandan; Yan, Pengfei; Guo, Hao; Yan, Tianyi; Wu, Jinglong; Xiang, Jie (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) disrupts the topological architecture of whole-brain connectivity. Minimum spanning tree (MST), which captures the most important connections in a network, has been considered an unbiased method for brain network analysis. However, the alterations in the MST of functional brain networks during the progression of AD remain unclear. Here, we performed an MST analysis to examine the alterations in functional networks among normal controls (NCs), mild cognitive impairment (MCI) patients, and AD patients. We identified substantial differences in the connections among the three groups. The maximum betweenness centrality, leaf number, and tree hierarchy of the MSTs showed significant group differences, indicating a more star-like topology in the MCI patients and a more line-like topology in the NCs and AD patients. These findings may correspond to changes in the core of the functional brain networks. For nodal properties (degree and betweenness centrality), we determined that brain regions around the cingulate gyrus, occipital lobes, subcortex, and inferior temporal gyrus showed significant differences among the three groups and contributed to the global topological alterations. The leaf number and tree hierarchy, as well as the nodal properties, were significantly correlated with clinical features in the MCI and AD patients, which demonstrated that more star-to-line topology changes were associated with worse cognitive performance in these patients. These findings indicated that MST properties could capture slight alterations in network topology, particularly for the differences between NCs and MCI patients, and may be applicable as neuroimaging markers of the early stage of AD.

Accuracy of Inferred APOE Genotypes for a Range of Genotyping Arrays and Imputation Reference Panels. - Lupton, Michelle K; Medland, Sarah E; Gordon, Scott D; Goncalves, Tabatha; MacGregor, Stuart; Mackey, David A; Young, Terri L; Duffy, David L; Visscher, Peter M; Wray, Naomi R; Nyholt, Dale R; Bain, Lisa; et al. (J Alzheimers Dis, 2018)
Cohort studies investigating aging and dementia require APOE genotyping. We compared directly measured APOE genotypes to 'hard-call' genotypes derived from imputing genome-wide genotyping data from a range of platforms using several imputation panels. Older GWAS arrays imputed to 1000 Genomes Project (1KGP) phases and the Haplotype Reference Consortium (HRC) reference panels were able to achieve concordance rates of over 98% with stringent quality control (hard-call-threshold 0.8). However, this resulted in high levels of missingness (>12% with 1KGP and 5% with HRC). With recent GWAS arrays, concordance of 99% could be obtained with relatively lenient QC, resulting in no missingness.

Acute Stroke Care in Dementia: A Cohort Study from the Swedish Dementia and Stroke Registries. - Zupanic, Eva; Kåreholt, Ingemar; Norrving, Bo; Secnik, Juraj; von Euler, Mia; Winblad, Bengt; Religa, Dorota; Kramberger, Milica Gregoric; Johnell, Kristina; Eriksdotter, Maria; Garcia-Ptacek, Sara (J Alzheimers Dis, 2018)
BACKGROUND: Previous studies have shown that patients with dementia receive less testing and treatment for stroke. OBJECTIVES: Our aim was to investigate hospital management of acute ischemic stroke in patients with and without dementia. METHODS: Retrospective analysis of prospectively collected data 2010-2014 from the Swedish national dementia registry (SveDem) and the Swedish national stroke registry (Riksstroke). Patients with dementia who suffered an acute ischemic stroke (AIS) (n = 1,356) were compared with matched non-dementia AIS patients (n = 6,755). Outcomes included length of stay in a stroke unit, total length of hospitalization, and utilization of diagnostic tests and assessments. RESULTS: The median age at stroke onset was 83 years. While patients with dementia were equally likely to be directly admitted to a stroke unit as their non-dementia counterparts, their stroke unit and total hospitalization length were shorter (10.5 versus 11.2 days and 11.6 versus 13.5, respectively, p < 0.001). Dementia patients were less likely to receive carotid ultrasound (OR 0.36, 95% CI [0.30-0.42]) or undergo assessments by the interdisciplinary team members (physiotherapists, speech therapists, occupational therapists; p < 0.05 for all adjusted models). However, a similar proportion of patients received CT imaging (97.4% versus 98.6%, p = 0.001) and a swallowing assessment (90.7% versus 91.8%, p = 0.218). CONCLUSIONS: Patients with dementia who suffer an ischemic stroke have equal access to direct stroke unit care compared to non-dementia patients; however, on average, their stay in a stroke unit and total hospitalization are shorter. Dementia patients are also less likely to receive specific diagnostic tests and assessments by the interdisciplinary stroke team.

The Added Value of Diffusion-Weighted MRI-Derived Structural Connectome in Evaluating Mild Cognitive Impairment: A Multi-Cohort Validation1. - Wang, Qi; Guo, Lei; Thompson, Paul M; Jack, Clifford R; Dodge, Hiroko; Zhan, Liang; Zhou, Jiayu (J Alzheimers Dis, 2018)
T1-weighted MRI has been extensively used to extract imaging biomarkers and build classification models for differentiating Alzheimer's disease (AD) patients from healthy controls, but only recently have brain connectome networks derived from diffusion-weighted MRI been used to model AD progression and various stages of disease such as mild cognitive impairment (MCI). MCI, as a possible prodromal stage of AD, has gained intense interest recently, since it may be used to assess risk factors for AD. Little work has been done to combine information from both white matter and gray matter, and it is unknown how much classification power the diffusion-weighted MRI-derived structural connectome could provide beyond information available from T1-weighted MRI. In this paper, we focused on investigating whether diffusion-weighted MRI-derived structural connectome can improve differentiating healthy controls subjects from those with MCI. Specifically, we proposed a novel feature-ranking method to build classification models using the most highly ranked feature variables to classify MCI with healthy controls. We verified our method on two independent cohorts including the second stage of Alzheimer's Disease Neuroimaging Initiative (ADNI2) database and the National Alzheimer's Coordinating Center (NACC) database. Our results indicated that 1) diffusion-weighted MRI-derived structural connectome can complement T1-weighted MRI in the classification task; 2) the feature-rank method is effective because of the identified consistent T1-weighted MRI and network feature variables on ADNI2 and NACC. Furthermore, by comparing the top-ranked feature variables from ADNI2, NACC, and combined dataset, we concluded that cross-validation using independent cohorts is necessary and highly recommended.

Age-Related Changes in the Spatial Frequency Threshold of Male and Female 3xTg-AD Mice Using OptoMotry. - King, Jillian L; Wong, Aimée A; Brown, Richard E (J Alzheimers Dis, 2018)
Visual impairments and retinal abnormalities occur in patients with Alzheimer's disease (AD) and in mouse models of AD. It is important to know the visual ability of mouse models of AD to ensure that age-related cognitive deficits are not confounded by visual impairments. Using OptoMotry, the spatial frequency thresholds of male and female 3xTg-AD mice did not differ from their B6129SF2 wildtype controls between 1-18 months of age, but females had higher spatial frequency thresholds than males. However, the differences were quite small, and the visual ability of all mice was comparable to that of C57BL/6 mice.
Keywords: Aging; Alzheimer Disease; Animals; Disease Models, Animal; Female; Humans; Male; Maze Learning; Mice; Mice, Inbred C57BL; Mice, Transgenic; Sex Characteristics; tau Proteins; Vision, Ocular

Alterations in Acrolein Metabolism Contribute to Alzheimer's Disease. - Tsou, Han-Hsing; Hsu, Wen-Chin; Fuh, Jong-Ling; Chen, Shih-Pin; Liu, Tsung-Yun; Wang, Hsiang-Tsui (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a detrimental neurodegenerative disease, and early diagnosis appears to be the key to successful treatment. Acrolein, a byproduct of lipid peroxidation, has been shown to contribute to the pathological process of AD. This study recruited 118 elderly subjects consisting of 58 non-demented control subjects and 62 AD patients. We analyzed the acrolein-related metabolites in the plasma, cerebrospinal fluid (CSF), and urine of all subjects. We found that the levels of acrolein-conjugated protein (Acr-PC) in the plasma (p = 0.00012) and CSF (p = 0.00161) of AD patients were significantly higher than those of control subjects, whereas the levels of a urinary acrolein metabolite, 3-hydroxypropyl mercapturic acid (3-HPMA), were markedly decreased (p = 0.00882) in AD patients. These data suggest that deregulated acrolein metabolism may be correlated with neuronal damage in AD patients, which might provide further insights into the disease progression and early diagnosis of AD.
Keywords: Acetylcysteine; Acrolein; Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Case-Control Studies; Creatinine; Disease Progression; Early Diagnosis; Female; Humans; Male; Middle Aged

Alterations in the Plasma Levels of Specific Choline Phospholipids in Alzheimer's Disease Mimic Accelerated Aging. - Dorninger, Fabian; Moser, Ann B; Kou, Jianqiu; Wiesinger, Christoph; Forss-Petter, Sonja; Gleiss, Andreas; Hinterberger, Margareta; Jungwirth, Susanne; Fischer, Peter; Berger, Johannes (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is the most common neurodegenerative disease and of continuously rising prevalence. The identification of easy-to-measure biomarkers capable to assist in the prediction and early diagnosis of AD is currently a main research goal. Lipid metabolites in peripheral blood of human patients have recently gained major attention in this respect. Here, we analyzed plasma of 174 participants (not demented at baseline; mean age: 75.70±0.44 years) of the Vienna Transdanube Aging (VITA) study, a longitudinal, population-based birth cohort study, at baseline and after 90 months or at diagnosis of probable AD. We determined the levels of specific choline phospholipids, some of which have been suggested as potential biomarkers for the prediction of AD. Our results show that during normal aging the levels of lysophosphatidylcholine, choline plasmalogen, and lyso-platelet activating factor increase significantly. Notably, we observed similar but more pronounced changes in the group that developed probable AD. Thus, our results imply that, in terms of choline-containing plasma phospholipids, the conversion to AD mimics an accelerated aging process. We conclude that age, even in the comparatively short time frame between 75 and 82.5 years, is a crucial factor in the quest for plasma lipid biomarkers for AD that must be carefully considered in future studies and trials.

Altered Expression of Urea Cycle Enzymes in Amyloid-β Protein Precursor Overexpressing PC12 Cells and in Sporadic Alzheimer's Disease Brain. - Jęśko, Henryk; Lukiw, Walter J; Wilkaniec, Anna; Cieślik, Magdalena; Gąssowska-Dobrowolska, Magdalena; Murawska, Emilia; Hilgier, Wojciech; Adamczyk, Agata (J Alzheimers Dis, 2018)
Urea cycle enzymes may play important yet poorly characterized roles in Alzheimer's disease (AD). Our previous results showed that amyloid-β (Aβ) affects urea cycle enzymes in rat pheochromocytoma (PC12) cells. The aim of the present study was to investigate the changes in arginases, other urea cycle enzymes, and nitric oxide synthases (NOSs) in PC12 cells transfected with AβPP bearing the double 'Swedish' mutation (APPsw, K670M/N671L) and in postmortem sporadic AD brain hippocampus; the mutation intensifies Aβ production and strongly associates with AD neuropathology. mRNA expression was analyzed using real-time PCR in cell cultures and DNA microarrays in hippocampal CA1 area of human AD brains. Arginase activity was measured spectrophotometrically, and arginine, ornithine, and citrulline levels by high-performance liquid chromatography. Our data demonstrated that the expression and activity of arginases (Arg1 and Arg2), as well as the expression of argininosuccinate synthase (Ass) were significantly reduced in APPsw cells compared to control. However, argininosuccinate lyase (Asl) was upregulated in APPsw cells. Real-time PCR analysis revealed significant elevation of neuronal nitric oxide synthase (Nnos) mRNA in APPsw cells, without changes in the endothelial Enos, whereas inducible Inos was undetectable. The changes were found to follow closely those observed in the human hippocampal CA1 region of sporadic AD brains. The changes in enzyme expression were accompanied in APPsw cells by significantly elevated citrulline, ornithine, and arginine. Our findings demonstrate that AβPP/Aβ alters arginine metabolism and induces a shift of cellular homeostasis that may support the oxidative/nitrosative stress observed in AD.

Alzheimer's Disease: A Journey from Amyloid Peptides and Oxidative Stress, to Biomarker Technologies and Disease Prevention Strategies-Gains from AIBL and DIAN Cohort Studies. - Martins, Ralph N; Villemagne, Victor; Sohrabi, Hamid R; Chatterjee, Pratishtha; Shah, Tejal M; Verdile, Giuseppe; Fraser, Paul; Taddei, Kevin; Gupta, Veer B; Rainey-Smith, Stephanie R; Hone, Eugene; Pedrini, Steve; et al. (J Alzheimers Dis, 2018)
Worldwide there are over 46 million people living with dementia, and this number is expected to double every 20 years reaching about 131 million by 2050. The cost to the community and government health systems, as well as the stress on families and carers is incalculable. Over three decades of research into this disease have been undertaken by several research groups in Australia, including work by our original research group in Western Australia which was involved in the discovery and sequencing of the amyloid-β peptide (also known as Aβ or A4 peptide) extracted from cerebral amyloid plaques. This review discusses the journey from the discovery of the Aβ peptide in Alzheimer's disease (AD) brain to the establishment of pre-clinical AD using PET amyloid tracers, a method now serving as the gold standard for developing peripheral diagnostic approaches in the blood and the eye. The latter developments for early diagnosis have been largely achieved through the establishment of the Australian Imaging Biomarker and Lifestyle research group that has followed 1,100 Australians for 11 years. AIBL has also been instrumental in providing insight into the role of the major genetic risk factor apolipoprotein E ɛ4, as well as better understanding the role of lifestyle factors particularly diet, physical activity and sleep to cognitive decline and the accumulation of cerebral Aβ.

Alzheimer's Disease in Systemic Sclerosis Patients: A Nationwide Population-Based Cohort Study. - Watad, Abdulla; Bragazzi, Nicola L; Tiosano, Shmuel; Yavne, Yarden; Comaneshter, Doron; Cohen, Arnon D; Amital, Howard (J Alzheimers Dis, 2018)
BACKGROUND: Neurological features are often overlooked in systemic sclerosis (SSc) patients and little is known about the link between dementia and SSc. OBJECTIVES: We sought to investigate whether an association exists between Alzheimer's disease (AD) and SSc, as well as assess the impact of a dual diagnosis on mortality rates, by performing an extensive data analysis on a large subject sample. METHODS: We utilized the medical database of the Clalit-Health-Services in a case-control study. Patients with SSc were compared with age- and sex-matched controls with regard to the prevalence of AD and its impact on their mortality. RESULTS: Our study included 2,431 SSc patients and 12,377 age- and sex-matched controls. The mean age of the study population was 63.32±18.06 years and the female to male ratio was 4.5:1. 134 (5.5%) cases had AD as a co-morbidity in comparison with 749 (5.9%) of the controls. The mortality rate was 12.5% among controls and 26.2% among SSc cases. On the Cox multivariate survival analysis, diagnosis of SSc and AD demonstrated significant HRs (2.35 (95% CI 2.05-2.69, p < 0.0001) and 2.19 (95% CI 1.94-2.48, p < 0.0001), respectively). SSc patients with AD had a relative risk of death of 2.35 (95% CI: 1.44-3.83) in comparison with SSc patients without AD. CONCLUSION: AD is a predictor of death in SSc and therefore preemptive screening may be warranted. Further studies are needed to evaluate whether improvements in the medical regimen for SSc may lead to a reduction in AD development and possibly to increased survival as well.

Alzheimer's Disease rs11767557 Variant Regulates EPHA1 Gene Expression Specifically in Human Whole Blood. - Liu, Guiyou; Zhang, Yan; Wang, Longcai; Xu, Jianyong; Chen, Xiaoyun; Bao, Yunjuan; Hu, Yang; Jin, Shuilin; Tian, Rui; Bai, Weiyang; Zhou, Wenyang; Wang, Tao; et al. (J Alzheimers Dis, 2018)
Large-scale genome-wide association studies have reported EPHA1 rs11767557 variant to be associated with Alzheimer's disease (AD) risk in the European population. However, it is still unclear how this variant functionally contributes to the underlying disease pathogenesis. The rs11767557 variant is located approximately 3 kb upstream of EPHA1 gene. We think that rs11767557 may modify the expression of nearby genes such as EPHA1 and further cause AD risk. Until now, the potential association between rs11767557 and the expression of nearby genes has not been reported in previous studies. Here, we evaluate the potential expression association between rs11767557 and EPHA1 using multiple large-scale eQTLs datasets in human brain tissues and the whole blood. The results show that rs11767557 variant could significantly regulate EPHA1 gene expression specifically in human whole blood. These findings may further provide important supplementary information about the regulating mechanisms of rs11767557 variant in AD risk.
Keywords: Alzheimer Disease; Case-Control Studies; China; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Polymorphism, Single Nucleotide; Receptor, EphA1; Risk Assessment

Amyloid-β Induces AMPA Receptor Ubiquitination and Degradation in Primary Neurons and Human Brains of Alzheimer's Disease. - Zhang, Yanmin; Guo, Ouyang; Huo, Yuda; Wang, Guan; Man, Heng-Ye (J Alzheimers Dis, 2018)
As the primary mediator for synaptic transmission, AMPA receptors (AMPARs) are crucial for synaptic plasticity and higher brain functions. A downregulation of AMPAR expression has been indicated as one of the early pathological molecular alterations in Alzheimer's disease (AD), presumably via amyloid-β (Aβ). However, the molecular mechanisms leading to the loss of AMPARs remain less clear. We report that in primary neurons, application of Aβ triggers AMPAR internalization accompanied with a decrease in cell-surface AMPAR expression. Importantly, in both Aβ-treated neurons and human brain tissue from AD patients, we observed a significant decrease in total AMPAR amount and an enhancement in AMPAR ubiquitination. Consistent with facilitated receptor degradation, AMPARs show higher turnover rates in the presence of Aβ. Furthermore, AD brain lysates and Aβ-incubated neurons show increased expression of the AMPAR E3 ligase Nedd4 and decreased expression of AMPAR deubiquitinase USP46. Changes in these enzymes are responsible for the Aβ-dependent AMPAR reduction. These findings indicate that AMPAR ubiquitination acts as the key molecular event leading to the loss of AMPARs and thus suppressed synaptic transmission in AD.

Amyloid-β25-35 Upregulates Endogenous Neuroprotectant Neuroglobin via NFκB Activation in vitro. - Liu, Ning; Yu, Zhanyang; Xun, Yu; Shu, Pan; Yue, Yiwei; Yuan, Shishan; Jiang, Yinghua; Huang, Zixuan; Yang, Xiaoping; Feng, Xing; Xiang, Shuanglin; Wang, Xiaoying (J Alzheimers Dis, 2018)
Neuroglobin (Ngb) has been reported to be increased in early and moderately advanced Alzheimer's disease (AD) stages but declined in the severe stage. However, its regulatory mechanisms and pathophysiological roles in the disease remain to be defined. In this study, we found that Ngb expression was significantly upregulated by low dose Aβ25-35, the neurotoxic fragment of Aβ1 - 40 and Aβ1 - 42, but was not further increased by a higher dose of Aβ25-35. Mutation analysis and supershift assay demonstrated that transcription factor Nuclear Factor κB (NFκB), κB2 and κB3 sites located in mouse Ngb promoter region were involved in dynamic regulation of Ngb expression in response to different doses of Aβ25-35 stimulation. In addition, we found that suppression of endogenous Ngb expression exacerbated Aβ25-35-induced neuronal cell death and mitochondrial dysfunction. Our results indicate that endogenous Ngb expression may be upregulated by low dose Aβ25-35, which is responsible for protecting against Aβ25-35-mediated neurotoxicity. These experimental findings suggest that upregulation of endogenous Ngb expression might be an effective intervention approach for AD.

Analyses of Clinical Features and Investigations on Potential Mechanisms in Patients with Alzheimer's Disease and Olfactory Dysfunction. - Zuo, Li-Jun; Guo, Peng; Liu, Li; Yu, Shu-Yang; Lian, Teng-Hong; Yu, Qiu-Jin; Hu, Yang; Jin, Zhao; Wang, Rui-Dan; Piao, Ying-Shan; Li, Li-Xia; Wang, Ya-Jie; et al. (J Alzheimers Dis, 2018)
BACKGROUND: OD is common in patients with Alzheimer's disease (AD). However, the relationship between OD and clinical symptoms and the potential mechanisms of OD in AD patients are still unknown. OBJECTIVE: To explore the relationship between OD and clinical symptoms and the potential mechanisms of OD in AD patients. METHODS: We evaluated OD using the Hyposmia Rating Scale (HRS), classified patients into AD with OD (AD-OD) and AD with no OD (AD-NOD) groups, and detected the levels of free radicals and inflammatory factors, including hydroxyl radical (•OH), hydrogen peroxide (H2O2), nitric oxide, interleukin-1β, interleukin-6, tumor necrosis factor-α, and prostaglandin E2 in serum from AD patients. RESULTS: It was shown that the scores of the Mini-Mental State Examination, Animal Fluency Test, Boston Naming Test (BNT), and Auditory Verbal Learning Test-delayed recall were all significantly lower and the score of overall activity of daily living (ADL) and instrumental ADL were significantly higher in AD-OD group than those in AD-NOD group. Compared with AD-NOD group, •OH level in serum was prominently elevated, and H2O2 level was dramatically declined in AD-OD group. In the correlation analysis, HRS score was significantly and positively correlated with the score of BNT, and negatively correlated with •OH level in serum. CONCLUSIONS: AD-OD patients suffered from severe cognitive impairment in the domain of language. Oxidative stress might be correlated with AD-OD featured by the drastically increased •OH level in serum.

Analysis of Brain Donors' Demographic and Medical Characteristics to Facilitate the Construction of a Human Brain Bank in China. - Zhang, Hanlin; Chen, Kang; Wang, Naili; Zhang, Di; Yang, Qian; Zhang, Qing; Liu, Pan; Wan, Mengyao; Gong, Changlin; Hong, Xinyu; Qiu, Wenying; Qian, Xiaojing; et al. (J Alzheimers Dis, 2018)
The Chinese Academy of Medical Sciences and Peking Union Medical College (CAMS/PUMC) Human Brain Bank was established in December 2012 and had accomplished 197 brain donations by November 2017. The brain bank was based on a large-scale willed body donation program in CAMS/PUMC starting from 1999. Demographic and medical characteristic analysis of brain donors was conducted to facilitate the construction of the brain bank. The average postmortem delay of brain donors was 17.7 h and 77.7% of these donors died less than 15 km away from the brain bank. Donors were predominantly with higher-level education (p < 0.001) and at an older age when registration (p < 0.001) and donation (p < 0.001) occurred. Our results elucidated the characteristics of donors in the CAMS/PUMC Human Brain Bank, which may provide useful information to target potential donors and improve the quality and quantity of brain specimens. The current study may pave the way for the construction of a nationwide network of standardized human brain banks in China.

Anti-Tau Monoclonal Antibodies Derived from Soluble and Filamentous Tau Show Diverse Functional Properties in vitro and in vivo. - Vandermeeren, Marc; Borgers, Marianne; Van Kolen, Kristof; Theunis, Clara; Vasconcelos, Bruno; Bottelbergs, Astrid; Wintmolders, Cindy; Daneels, Guy; Willems, Roland; Dockx, Koen; Delbroek, Lore; Marreiro, André; et al. (J Alzheimers Dis, 2018)
The tau spreading hypothesis provides rationale for passive immunization with an anti-tau monoclonal antibody to block seeding by extracellular tau aggregates as a disease-modifying strategy for the treatment of Alzheimer's disease (AD) and potentially other tauopathies. As the biochemical and biophysical properties of the tau species responsible for the spatio-temporal sequences of seeding events are poorly defined, it is not yet clear which epitope is preferred for obtaining optimal therapeutic efficacy. Our internal tau antibody collection has been generated by immunizations with different tau species: aggregated- and non-aggregated tau and human postmortem AD brain-derived tau fibrils. In this communication, we describe and characterize a set of these anti-tau antibodies for their biochemical and biophysical properties, including binding, tissue staining by immunohistochemistry, and epitope. The antibodies bound to different domains of the tau protein and some were demonstrated to be isoform-selective (PT18 and hTau56) or phospho-selective (PT84). Evaluation of the antibodies in cellular- and in vivo seeding assays revealed clear differences in maximal efficacy. Limited proteolysis experiments support the hypothesis that some epitopes are more exposed than others in the tau seeds. Moreover, antibody efficacy seems to depend on the structural properties of fibrils purified from tau Tg mice- and postmortem human AD brain.

Application of Weighted Gene Co-Expression Network Analysis to Explore the Key Genes in Alzheimer's Disease. - Liang, Jia-Wei; Fang, Zheng-Yu; Huang, Yong; Liuyang, Zhen-Yu; Zhang, Xiao-Lin; Wang, Jing-Lin; Wei, Hui; Wang, Jian-Zhi; Wang, Xiao-Chuan; Zeng, Ji; Liu, Rong (J Alzheimers Dis, 2018)
BACKGROUND: Weighted co-expression network analysis (WGCNA) is a powerful systems biology method to describe the correlation of gene expression based on the microarray database, which can be used to facilitate the discovery of therapeutic targets or candidate biomarkers in diseases. OBJECTIVE: To explore the key genes in the development of Alzheimer's disease (AD) by using WGCNA. METHODS: The whole gene expression data GSE1297 from AD and control human hippocampus was obtained from the GEO database in NCBI. Co-expressed genes were clustered into different modules. Modules of interest were identified through calculating the correlation coefficient between the module and phenotypic traits. GO and pathway enrichment analyses were conducted, and the central players (key hub genes) within the modules of interest were identified through network analysis. The expression of the identified key genes was confirmed in AD transgenic mice through using qRT-PCR. RESULTS: Two modules were found to be associated with AD clinical severity, which functioning mainly in mineral absorption, NF-κB signaling, and cGMP-PKG signaling pathways. Through analysis of the two modules, we found that metallothionein (MT), Notch2, MSX1, ADD3, and RAB31 were highly correlated with AD phenotype. Increase in expression of these genes was confirmed in aged AD transgenic mice. CONCLUSION: WGCNA analysis can be used to analyze and predict the key genes in AD. MT1, MT2, MSX1, NOTCH2, ADD3, and RAB31 are identified to be the most relevant genes, which may be potential targets for AD therapy.

Association between Plasma Levels of PAI-1, tPA/PAI-1 Molar Ratio, and Mild Cognitive Impairment in Chinese Patients with Type 2 Diabetes Mellitus. - Wang, Jiaqi; Yuan, Yang; Cai, Rongrong; Huang, Rong; Tian, Sai; Lin, Hongyan; Guo, Dan; Wang, Shaohua (J Alzheimers Dis, 2018)
BACKGROUND: Plasminogen activator inhibitor 1 (PAI-1) and tissue plasminogen activator (tPA) are involved in the complications of type 2 diabetes mellitus (T2DM) and early pathology of Alzheimer's disease. OBJECTIVE: This study aimed to investigate the association between plasma PAI-1, tPA/PAI-1 molar ratio, and mild cognitive impairment (MCI) in Chinese T2DM patients. METHODS: A total of 162 Chinese T2DM patients were recruited and divided into two groups according to the Montreal Cognitive Assessment score. Demographic data were collected, plasma PAI-1 and tPA levels were measured through enzyme-linked immunosorbent assay, tPA/PAI-1 molar ratio was calculated, and neuropsychological test results were examined. The association between PAI-1, tPA/PAI-1 molar ratio, and cognition was analyzed. RESULTS: There were 66 diabetic MCI patients and 96 healthy cognition participants (controls). T2DM patients with MCI displayed significantly increased plasma PAI-1 levels (p = 0.016) and decreased tPA/PAI-1 molar ratio (p = 0.021) compared with the controls. High PAI-1 levels and low tPA/PAI-1 molar ratio were associated with MCI in T2DM patients, e.g., plasma level of PAI-1 were negatively correlated (r = -0.343, p = 0.007) with logic memory in T2DM patients with MCI. Linear regression analysis further revealed that PAI-1 concentration was an independent factor of diabetic MCI (p = 0.001). CONCLUSIONS: High PAI-1 levels and low tPA/PAI-1 molar ratio were significantly correlated with T2DM-associated cognitive impairment, especially memory function, in Chinese patients.

Association between α-Klotho and Deep White Matter Lesions in the Brain: A Pilot Case Control Study Using Brain MRI. - Kuriyama, Nagato; Ozaki, Etsuko; Mizuno, Toshiki; Ihara, Masafumi; Mizuno, Shigeto; Koyama, Teruhide; Matsui, Daisuke; Watanabe, Isao; Akazawa, Kentaro; Takeda, Kazuo; Takada, Akihiro; Inaba, Masaaki; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The anti-aging protein, α-Klotho, may be involved in cognitive decline and has potential as a surrogate marker that reflects dementia. However, the role of α-Klotho in the brain has not been sufficiently investigated. OBJECTIVE: Here, we investigated the association between α-Klotho and cognitive decline that is associated with cerebral deep white matter lesions (DWMLs). METHODS: Two hundred-eighty participants (187 males and 93 females, mean age: 70.8 years old) were evaluated for DWMLs, and the Fazekas scale (Grade) was assessed following brain magnetic resonance imaging. A questionnaire concerning lifestyle and neuropsychological tests was administered, and their associations with the blood α-Klotho level were retrospectively investigated. RESULTS: The α-Klotho level was 685.1 pg/mL in Grade 0 (68 subjects), 634.1 in G1 (134), 596.0 in G2 (62), and 571.6 in G3 (16), showing that the level significantly decreased with advanced grades. Significant correlations were noted between the α-Klotho level and higher brain function tests including the Mini-Mental State Examination and word fluency tests (p < 0.05). When a 90th percentile value of the level in the G0 group (400 pg/mL) or lower was defined as a low α-Klotho level, the odds ratio of the high-grade G3 group was 2.9 (95% confidence interval: 1.4-7.8) (after correction for age, sex, hypertension, and chronic kidney disease), which was significant. CONCLUSION: A reduced blood α-Klotho level was correlated with grading of cerebral DWMLs and was accompanied by cognitive decline as an independent risk factor. The α-Klotho level may serve as a useful clinical index of vascular cognitive impairment.
Keywords: Aged; Aged, 80 and over; Apolipoprotein E4; Brain; C-Reactive Protein; Case-Control Studies; Cognition Disorders; Female; Glucuronidase; Humans; Image Processing, Computer-Assisted; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Pilot Projects; Severity of Illness Index

The Association of Mid- and Late-Life Systemic Inflammation with Brain Amyloid Deposition: The ARIC-PET Study. - Walker, Keenan A; Windham, B Gwen; Brown, Charles H; Knopman, David S; Jack, Clifford R; Mosley, Thomas H; Selvin, Elizabeth; Wong, Dean F; Hughes, Timothy M; Zhou, Yun; Gross, Alden L; Gottesman, Rebecca F (J Alzheimers Dis, 2018)
BACKGROUND: Although inflammation has been implicated in the pathogenesis of Alzheimer's disease, the effects of systemic inflammation on brain amyloid deposition remain unclear. OBJECTIVE: We examined the association of midlife and late-life systemic inflammation with late-life brain amyloid levels in a community sample of non-demented older adults from the Atherosclerosis Risk in Communities (ARIC) - PET Study. METHODS: 339 non-demented participants (age: 75 [SD 5]) were recruited from the ARIC Study to undergo florbetapir PET (amyloid) imaging. Blood levels of high sensitivity C-reactive protein (CRP), a marker of systemic inflammation, were measured 22 years (Visit 2), 16 years (Visit 4), and up to 2 years before PET imaging (Visit 5). Elevated brain amyloid deposition (standardized uptake value ratio >1.2) was the primary outcome. RESULTS: Our primary analyses found no association of midlife and late-life CRP with late-life brain amyloid levels. However, in secondary stratified analyses, we found that higher midlife (Visit 2) CRP was associated with elevated amyloid among males (OR 1.65, 95% CI: 1.13-2.42), and among white (OR 1.33, 95% CI: 1.02-1.75), but not African American, participants (p-interactions<0.05). Among male participants, those who maintained high CRP levels (≥3 mg/L) throughout mid- and late-life were most likely to have elevated brain amyloid (OR, 8.81; 95% CI: 1.23, 62.91). CONCLUSIONS: Although our primary analysis does not support an association between systemic inflammation and brain amyloid deposition, we found evidence for sex- and race-dependent associations. However, findings from subgroup analyses should be interpreted with caution.

Associations between Use of Specific Analgesics and Concentrations of Amyloid-β 42 or Phospho-Tau in Regions of Human Cerebral Cortex. - Flanagan, Margaret E; Larson, Eric B; Walker, Rod L; Keene, C Dirk; Postupna, Nadia; Cholerton, Brenna; Sonnen, Joshua A; Dublin, Sascha; Crane, Paul K; Montine, Thomas J (J Alzheimers Dis, 2018)
Analgesics are commonly used by older adults, raising the question of whether their use might contribute to dementia risk and neuropathologic changes of Alzheimer's disease (AD). The Adult Changes in Thought (ACT) study is a population-based study of brain aging and incident dementia among people 65 years or older who are community dwelling and not demented at entry. Amyloid-β (Aβ)42 and phospho-tau were quantified using Histelide in regions of cerebral cortex from 420 brain autopsies. Total standard daily doses of prescription opioid and non-aspirin nonsteroidal anti-inflammatory drug (NSAID) exposure during a defined 10-year exposure window were identified using automated pharmacy dispensing data and used to classify people as having no/low, intermediate, or high exposure. People with high NSAID exposure had significantly greater Aβ42 concentration in middle frontal gyrus and superior and middle temporal gyri, but not inferior parietal lobule; no Aβ42 regional concentration was associated with prescription opioid usage. People with high opioid usage had significantly greater concentration of phospho-tau in middle frontal gyrus than people with little-to-no opioid usage. Consistent with our previous studies, findings suggest that high levels of NSAID use in older individuals may promote Aβ42 accumulation in cerebral cortex.
Keywords: Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Analgesics; Analgesics, Opioid; Anti-Inflammatory Agents, Non-Steroidal; Autopsy; Cerebral Cortex; Female; Humans; Logistic Models; Male; Peptide Fragments; Prospective Studies; tau Proteins

Associations of Dietary Protein and Fiber Intake with Brain and Blood Amyloid-β. - Fernando, W M A D Binosha; Rainey-Smith, Stephanie R; Gardener, Samantha L; Villemagne, Victor L; Burnham, Samantha C; Macaulay, S Lance; Brown, Belinda M; Gupta, Veer Bala; Sohrabi, Hamid R; Weinborn, Michael; Taddei, Kevin; Laws, Simon M; et al. (J Alzheimers Dis, 2018)
Accumulating evidence suggests a diet high in protein and fiber may confer some protection against Alzheimer's disease (AD). However, no human studies to-date have assessed the relationship between protein and fiber intake, and plasma and brain amyloid-β (Aβ). Consequently, this cross-sectional study, investigated the association of self-reported dietary intakes of protein and fiber, with plasma and brain Aβ burden (n = 541, and n = 162 respectively), in a well-characterized cohort of cognitively normal older adults, drawn from the larger Australian Imaging, Biomarkers and Lifestyle (AIBL) study of aging. We observed 12.59 and 8.43 higher odds of 'high' brain Aβ burden (PiB PET SUVR≥1.5) if protein intake fell in the lowest and middle tertile, respectively, compared to the highest tertile (p = 0.008; p = 0.013). Thus, in this cohort, the more protein consumed, the less likelihood of 'high' Aβ burden in the brain. No other significant associations were observed. The results of this study highlight the potentially protective impact of high dietary protein intake on brain Aβ burden in older adults, before objective memory decline is apparent. While longitudinal validation is required, these findings may assist in the development of dietary approaches aimed at preventing or delaying AD onset.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Australia; Biomarkers; Brain; Cognition; Cohort Studies; Cross-Sectional Studies; Dietary Fiber; Dietary Proteins; Female; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography

Atherosclerosis, Hypertension, and Diabetes in Alzheimer's Disease, Vascular Dementia, and Mixed Dementia: Prevalence and Presentation. - Javanshiri, Keivan; Waldö, Maria Landqvist; Friberg, Niklas; Sjövall, Fredrik; Wickerström, Karin; Haglund, Mattias; Englund, Elisabet (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is the most prevalent cause of dementia with vascular dementia (VaD) being second alongside with mixed AD and VaD, according to some. For some time, it has been proposed that cardiovascular disease (CaVD), hypertension, and diabetes mellitus (DM), which are known risk factors for VaD, also are associated with and contribute to the development of AD. OBJECTIVE: The aim of this study was to investigate the prevalence of these proposed general risk factors, and to document presence of CaVD as evidenced from clinical records or from autopsy findings, further to correlate these with the diagnoses AD, VaD and mixed AD-VaD (MD), respectively. METHODS: Autopsy reports at the Clinical Department of Pathology in Lund from 1992-2017 were analyzed. All cases with a complete autopsy report and a neuropathologically diagnosed dementia disorder (AD, VaD, or MD) were selected on the condition of a clinical diagnosis of dementia. Clinical data were retrieved through medical records and the Swedish National Diabetes Register (NDR). A total of 268 subjects were included. RESULTS: In AD, there was less CaVD as significantly less organ/tissue findings (p < 0.05), significantly less hypertension (p < 0.001), and likewise significantly less DM (p = 0.0014) than in VaD, with the MD group results being set between these two in all aspects studied. CONCLUSION: AD and VaD exhibit such different profiles of organ and vascular damage as well as of hypertension and DM that they clearly point toward different pathogenic origin with low likelihood of shared risk factors.

Automated Multi-Atlas Segmentation of Hippocampal and Extrahippocampal Subregions in Alzheimer's Disease at 3T and 7T: What Atlas Composition Works Best? - Xie, Long; Shinohara, Russell T; Ittyerah, Ranjit; Kuijf, Hugo J; Pluta, John B; Blom, Kim; Kooistra, Minke; Reijmer, Yael D; Koek, Huiberdina L; Zwanenburg, Jaco J M; Wang, Hongzhi; Luijten, Peter R; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Multi-atlas segmentation, a popular technique implemented in the Automated Segmentation of Hippocampal Subfields (ASHS) software, utilizes multiple expert-labelled images ("atlases") to delineate medial temporal lobe substructures. This multi-atlas method is increasingly being employed in early Alzheimer's disease (AD) research, it is therefore becoming important to know how the construction of the atlas set in terms of proportions of controls and patients with mild cognitive impairment (MCI) and/or AD affects segmentation accuracy. OBJECTIVE: To evaluate whether the proportion of controls in the training sets affects the segmentation accuracy of both controls and patients with MCI and/or early AD at 3T and 7T. METHODS: We performed cross-validation experiments varying the proportion of control subjects in the training set, ranging from a patient-only to a control-only set. Segmentation accuracy of the test set was evaluated by the Dice similarity coeffiecient (DSC). A two-stage statistical analysis was applied to determine whether atlas composition is linked to segmentation accuracy in control subjects and patients, for 3T and 7T. RESULTS: The different atlas compositions did not significantly affect segmentation accuracy at 3T and for patients at 7T. For controls at 7T, including more control subjects in the training set significantly improves the segmentation accuracy, but only marginally, with the maximum of 0.0003 DSC improvement per percent increment of control subject in the training set. CONCLUSION: ASHS is robust in this study, and the results indicate that future studies investigating hippocampal subfields in early AD populations can be flexible in the selection of their atlas compositions.

Behavioral Variant Frontotemporal Dementia Performance on a Range of Saccadic Tasks. - Douglass, Amanda; Walterfang, Mark; Velakoulis, Dennis; Abel, Larry (J Alzheimers Dis, 2018)
BACKGROUND: Saccadic paradigms display changes across a number of degenerative conditions reflecting changes in the oculomotor pathway which in some conditions have been linked to disease presentation. OBJECTIVE: To examine a novel range of saccadic paradigms in behavioral variant frontotemporal dementia (bvFTD). METHODS: Prosaccade, predictive, self-paced, memory-guided, and anti-saccade tasks were examined in bvFTD patients and controls. RESULTS: A significant increase in latency for the bvFTD group was seen in all tasks. Self-paced saccades are reduced in number, memory-guided saccades display an increase in errors. Predictive saccades show an increased latency that does not remain when prosaccade latency changes are accounted for. While changes were seen across a range of paradigms, no individual task completely separated bvFTD from control participants. CONCLUSION: bvFTD patients as a group display a number of changes on saccadic testing which may reflect the frontal lobe changes seen in this condition.

Berberine Alleviates Tau Hyperphosphorylation and Axonopathy-Associated with Diabetic Encephalopathy via Restoring PI3K/Akt/GSK3β Pathway. - Wang, Shanshan; He, Benhong; Hang, Weijian; Wu, NingHua; Xia, Liangtao; Wang, Xu; Zhang, Qianying; Zhou, Xinwen; Feng, Zuohua; Chen, Qingjie; Chen, Juan (J Alzheimers Dis, 2018)
BACKGROUND: Axonopathy is closely linked to the development of diabetic encephalopathy induced by type II diabetes (T2D). Berberine has been shown to cross the blood-brain barrier and holds promising effect for neuronal damage in diabetes. OBJECTIVE: The present study investigated the protective effect and the underlying mechanism of berberine on neuronal axonopathy in both in vitro and in vivo models. METHODS: High glucose/high fat diet and streptozotocin injection-induced T2D rat model was used. Berberine was administered p.o. to T2D rat model for 10 weeks. Morris water maze test, in vivo neuronal tracing, immunohistochemistry, and western blot analysis were performed to evaluate the protective effects of berberine in T2D-induced diabetic encephalopathy rats. Primary cultured neurons were used to further explore the underlying mechanisms in vitro. RESULTS: Berberine dramatically reduced blood glucose and serum insulin levels and alleviated insulin resistance. Berberine significantly attenuated memory impairment, axonopathy, and tau hyperphosphorylation, and also restored PI3K/Akt/GSK3β signaling pathway in T2D rats. In vitro, berberine induced an increase in the phosphorylation of PI3K/Akt as well as GSK3β in high glucose-treated primary neurons. Furthermore, berberine-induced PI3K/Akt activation also resulted in the dephosphorylation of tau protein, which could improve axonal transport impairment in high glucose-treated primary neurons. Pretreated neurons with LY294002, an inhibitor of PI3K, partially blocked berberine-inhibited tau phosphorylation and berberine-activated PI3K/Akt signaling pathway. CONCLUSIONS: Berberine exerts the protective effect against cognitive deficits by improving tau hyperphosphorylation and the axonal damage through restoring PI3K/Akt/GSK3β signaling pathway.

Biallelic Loss of Function of SORL1 in an Early Onset Alzheimer's Disease Patient. - Le Guennec, Kilan; Tubeuf, Hélène; Hannequin, Didier; Wallon, David; Quenez, Olivier; Rousseau, Stéphane; Richard, Anne-Claire; Deleuze, Jean-François; Boland, Anne; Frebourg, Thierry; Gaildrat, Pascaline; Campion, Dominique; et al. (J Alzheimers Dis, 2018)
Heterozygous SORL1 protein truncating variants (PTV) are a strong risk factor for early-onset Alzheimer's disease (EOAD). In case control studies performed at the genome-wide level, PTV definition is usually straightforward. Regarding splice site variants, only those affecting canonical sites are typically included. Some other variants, not annotated as PTV, could, however, affect splicing and hence result in a loss of SORL1 function. We took advantage of the whole exome sequencing data from the 9/484 patients with a previously reported SORL1 PTV in the French EOAD series and searched for a second variant which may affect splicing and eventually result in more than 50% loss of function overall. We found that one patient, known to carry a variant predicted to disrupt the canonical 5' splice site of exon 8, also carried a second novel intronic variant predicted to affect SORL1 splicing of exon 29. Segregation analysis showed that the second variant was located in trans from the known PTV. We performed ex vivo minigene splicing assays and showed that both variants led to the generation of transcripts containing a premature stop codon. This is therefore the first evidence of a human carrying biallelic SORL1 PTV. This patient had a family history of dementia in both maternal and paternal lineages with later ages of onset than the proband himself. However, his 55 years age at onset was in the same ranges as previously published SORL1 heterozygous PTV carriers. This suggests that biallelic loss of SORL1 function is an extremely rare event that was not associated with a dramatically earlier age at onset than heterozygous SORL1 loss-of-function variant carriers, in this single patient.
Keywords: Alzheimer Disease; Case-Control Studies; Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Humans; LDL-Receptor Related Proteins; Male; Membrane Transport Proteins; Middle Aged; Risk Factors

Bi-directional Association of Cerebrospinal Fluid Immune Markers with Stage of Alzheimer's Disease Pathogenesis. - Meyer, Pierre-François; Savard, Mélissa; Poirier, Judes; Labonte, Anne; Rosa-Neto, Pedro; Weitz, Tara M; Town, Terrence; Breitner, John (J Alzheimers Dis, 2018)
Immune mechanisms may be important in the pathogenesis of Alzheimer's disease (AD). Yet, studies comparing cerebrospinal fluid (CSF) and plasma immune marker levels of healthy and demented individuals have yielded conflicting results. We analyzed CSF from 101 members of the parental history-positive PREVENT-AD cohort of healthy aging adults, and 237 participants without dementia from the initial cohort of the Alzheimer's Disease Neuroimaging Initiative (ADNI-1). Following recent practice, we used the biomarkers total-tau and amyloid-β1-42 to allocate participants from each study into four stages of AD pathogenesis: Stage 0 (no abnormality), Stage 1 (reduced amyloid-β1-42), Stage 2 (reduced amyloid-β1-42 and increased total-tau), or "Suspected Non-Alzheimer Pathology" (elevated total-tau only). Investigating the PREVENT-AD participants' CSF assay results for 19 immune/inflammatory markers, we found six that showed a distinct bi-directional relationship with pathogenetic stage. Relative to Stage 0, these were diminished at Stage 1 but strongly increased at Stage 2. Among the ADNI participants (90 healthy controls and 147 with mild cognitive impairment), we found that 23 of 83 available CSF markers also showed this distinct pattern. These results support recent observations that immune activation may become apparent only after the onset of both amyloid and tau pathologies. Unexpectedly, they also suggest that immune marker activity may diminish along with earliest appearance of amyloid-β plaque pathology. These findings may explain discordant results from past studies, and suggest the importance of characterizing the extent of AD pathology when comparing clinical groups.

Brain Amyloid Contribution to Cognitive Dysfunction in Early-Stage Parkinson's Disease: The PPMI Dataset. - Fiorenzato, Eleonora; Biundo, Roberta; Cecchin, Diego; Frigo, Anna Chiara; Kim, Jinhee; Weis, Luca; Strafella, Antonio P; Antonini, Angelo (J Alzheimers Dis, 2018)
BACKGROUND: The pathological processes underlying cognitive impairment in Parkinson's disease (PD) are heterogeneous and the contribution of cerebral amyloid deposits is poorly defined, particularly in the early stages of the disease. OBJECTIVE: To investigate regional [18F]florbetaben binding to amyloid-β (Aβ) and its contribution to cognitive dysfunction in early stage PD. METHODS: A multicenter cohort of 48 PD patients from the Parkinson's Progression Marker Initiative (PPMI) underwent [18F]florbetaben positron emission tomography (PET) scanning. Clinical features, including demographic characteristics, motor severity, cerebrospinal fluid (CSF), and cognitive testing were systematically assessed according to the PPMI study protocol. For the purpose of this study, we analyzed various neuropsychological tests assessing all cognitive functions. RESULTS: There were 10/48 (21%) amyloid positive PD patients (PDAβ+). Increased [18F]florbetaben uptake in widespread cortical and subcortical regions was associated with poorer performance on global cognition, as assessed by Montreal Cognitive Assessment (MoCA), and impaired performance on Symbol Digit Modality test (SDMT). Further, we found that PDAβ+ patients had higher CSF total-tau/Aβ1 - 42 (p = 0.001) and phosphorylated-tau/Aβ1 - 42 in (p = 0.002) compared to amyloid-negative PD. CONCLUSION: These findings suggest that multiple disease processes are associated with PD cognitive impairment and amyloid deposits may be observed already in early stages. However, prevalence of amyloid positivity is in the range of literature age-matched control population. Increased cortical and subcortical amyloid is associated with poor performance in attentive-executive domains while cognitive deficits at MoCA and SDMT may identify amyloid-related dysfunction in early PD.

Brazilian Green Propolis Prevents Cognitive Decline into Mild Cognitive Impairment in Elderly People Living at High Altitude. - Zhu, Aiqin; Wu, Zhou; Zhong, Xin; Ni, Junjun; Li, Yinglan; Meng, Jie; Du, Can; Zhao, Xue; Nakanishi, Hiroshi; Wu, Shizheng (J Alzheimers Dis, 2018)
BACKGROUND: Systemic inflammation is known as a risk factor of cognitive decline. OBJECTIVE: To investigate the effects of propolis on cognitive decline and systemic inflammation in elderly people living at high altitude. METHODS: Sixty participants (average 72.8 years) living at altitude (2,260 meters) were randomized to receive propolis (0.83 g, n = 30) or placebo (n = 30) for 24 months. Cognitive outcomes were assessed using MMSE and serum cytokine levels were measured for 24 months in a double-blind study. RESULTS: MMSE scores were 26.17 at baseline and 23.87 at 24 months in placebo group. Compared to placebo group, improvements of MMSE scores were significant in propolis-treated subjects (p = 0.007) with a response emerging over time (time points×group interaction, p = 0.016). In addition, the serum IL-1β and IL-6 levels were significantly different across treatments (p < 0.0001) showing upward and downward trends in placebo- and propolis-treated subjects, respectively (p < 0.0001). Serum levels of TNF-α were not significantly different across treatment (p = 0.0528) but with a response emerging over time (time points×group interaction, p = 0.016). In contrast, serum levels of TGFβ1 were significantly different across treatments (p < 0.0001) showing downward and upward trends in placebo- and propolis-treated subjects, respectively. Serum levels of IL-10 were significant for the effect of groups (p = 0.0411). Furthermore, MMSE scores correlated with the decrease in IL-1β and the increase in TGFβ1 in serum. CONCLUSION: Elderly people living at high altitude developed to MCI in 24 months with exacerbation of systemic inflammation. Ingestion of propolis (>12 months) protected against cognitive decline after systemic inflammation was reduced.

Cardiorespiratory Fitness and White Matter Neuronal Fiber Integrity in Mild Cognitive Impairment. - Ding, Kan; Tarumi, Takashi; Zhu, David C; Tseng, Benjamin Y; Thomas, Binu P; Turner, Marcel; Repshas, Justin; Kerwin, Diana R; Womack, Kyle B; Lu, Hanzhang; Cullum, C Munro; Zhang, Rong (J Alzheimers Dis, 2018)
BACKGROUND: Mounting evidence showed the self-reported levels of physical activity are positively associated with white matter (WM) integrity and cognitive performance in normal adults and patients with mild cognitive impairment (MCI). However, the objective measure of cardiorespiratory fitness (CRF) was not used in these studies. OBJECTIVE: To determine the associations of CRF measured by maximal oxygen uptake (VO2max) with WM fiber integrity and neurocognitive performance in older adults with MCI. METHODS: Eighty-one participants (age = 65±7 years, 43 women), including 26 cognitively normal older adults and 55 amnestic MCI patients, underwent VO2max test to measure CRF, diffusion tensor imaging (DTI) to assess WM fiber integrity, and neurocognitive assessment focused on memory and executive function. DTI data were analyzed by the tract-based spatial statistics and region-of-interest approach. RESULTS: Cognitively normal older adults and MCI patients were not different in global WM fiber integrity and VO2max. VO2max was associated positively with DTI metrics of fractional anisotropy in ∼54% WM fiber tracts, and negatively with mean and radial diffusivities in ∼46% and ∼56% of the WM fiber tracts. The associations of VO2max with DTI metrics remained statistically significant after adjustment of age, sex, body mass index, WM lesion burden, and MCI status. The DTI metrics obtained from the area that correlated to VO2max were associated with executive function performance in MCI patients. CONCLUSIONS: Higher levels of CRF are associated with better WM fiber integrity, which in turn is correlated with better executive function performance in MCI patients.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Anisotropy; Cardiorespiratory Fitness; Case-Control Studies; Cognition; Cognitive Dysfunction; Diffusion Tensor Imaging; Executive Function; Female; Humans; Linear Models; Male; Memory; Middle Aged; Nerve Fibers, Myelinated; Neuropsychological Tests; Texas; White Matter

Cerebral Amyloid Angiopathy and Cerebral Amyloid Angiopathy-Related Inflammation: Comparison of Hemorrhagic and DWI MRI Features. - Renard, Dimitri; Tatu, Lavinia; Collombier, Laurent; Wacongne, Anne; Ayrignac, Xavier; Charif, Mahmoud; Boukriche, Yassine; Chiper, Laura; Fourcade, Genevieve; Azakri, Souhayla; Gaillard, Nicolas; Mercier, Erick; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Cerebral amyloid angiopathy (CAA) can be associated with primary vasculitis of small/medium-sized leptomeningeal and cortical arteries, called CAA-related inflammation (CAA-ri). OBJECTIVE: To compare hemorrhagic and diffusion-weighted imaging (DWI) MRI features in CAA and CAA-ri. METHODS: We prospectively scored in a consecutive CAA and CAA-ri cohort: presence/number of chronic intracerebral hemorrhage (ICH), cerebral microbleeds (CMB), and cortical superficial siderosis (CSS) on initial T2*-weighted imaging, and DWI lesions on both initial and follow-up imaging. In a subgroup, ApoE, CSF, and 18F-florbetaben-positron emission tomography (FBB-PET) were also analyzed. RESULTS: In CAA-ri, CMB presence was more frequent (100% versus 40%, p < 0.001) and CMB numbers higher (mean 137 versus 8, p < 0.001). No difference was observed for chronic ICH or CSS. DWI lesions were more frequent in acute compared to chronic CAA-ri (p = 0.025), whereas no such difference was observed between acute and chronic CAA (p = 0.18). Both ApoE4 (genotyping available in 22 CAA-ri and 48 CAA patients) carriers and homozygosity were more frequent in CAA-ri (48% versus 19% [p = 0.014] and 32% versus 2% [p < 0.001] respectively). CSF biomarker analyses (performed in 20 CAA-ri and 45 CAA patients) showed lower Aβ42 levels in CAA-ri compared to CAA (median 312 versus 422 pg/mL, p = 0.0032). FBB-PET (performed in 11 CAA-ri and 20 CAA patients) showed higher standardized uptake value ratios in CAA-ri compared with CAA, only significant when the pons was used as reference (p = 0.037). CONCLUSION: Compared to CAA, CAA-ri was associated with higher CMB numbers, more frequent ApoE4 carriers and homozygotes, lower CSF Aβ42 levels, and more severe amyloid load on FBB-PET.

Cerebral Amyloid Angiopathy: Similarity in African-Americans and Caucasians with Alzheimer's Disease. - Kamara, Dennis M; Gangishetti, Umesh; Gearing, Marla; Willis-Parker, Monica; Zhao, Liping; Hu, William T; Walker, Lary C (J Alzheimers Dis, 2018)
Cerebral amyloid angiopathy (CAA) of the Aβ type is variably present in the brains of patients with Alzheimer's disease (AD). CAA contributes to cognitive decline and increases the risk of lobar hemorrhage; because both AD-typical dementia and lobar hemorrhage are more common in African-Americans than in Caucasians, we postulated that African-Americans with AD might be particularly susceptible to CAA. To test this hypothesis, we analyzed CAA histopathologically in the large vessels and capillaries of autopsy-derived frontal, temporal, parietal, and occipital cortical samples from African-Americans (n = 18) and Caucasians (n = 19) with end-stage AD. In the combined cohort of 37 subjects, 22% of the subjects had severe CAA in large vessels, and 11% had severe CAA in capillaries. However, the prevalence and histopathologic characteristics of CAA were similar in the African-Americans and Caucasians. This conclusion was substantiated in an independent sample from the National Alzheimer's Coordinating Center database, in which the degree of CAA was comparable in 1,554 Caucasians and 68 African-Americans with end-stage AD. These findings support a growing consensus that the fundamental histopathologic features of AD are largely impartial to the race of the afflicted.

Cerebrospinal Fluid Amyloid-β Levels are Increased in Patients with Insomnia. - Chen, Dong-Wan; Wang, Jun; Zhang, Li-Li; Wang, Yan-Jiang; Gao, Chang-Yue (J Alzheimers Dis, 2018)
Previous studies demonstrate that patients with sleep disorders are at risk of developing Alzheimer's disease (AD), with the mechanism unknown. It is suggested that acute sleep deprivation induces an increase of amyloid-β (Aβ), the major pathological agent in AD, in the cerebrospinal fluid (CSF). In the present study, we recruited 23 patients with chronic insomnia aged between 46 to 67 years and 23 healthy controls aged between 43 to 67 years. We investigated the CSF levels of Aβ and tau, another pathological hallmark in the AD pathogenesis. We found that CSF Aβ42 levels were significantly increased in insomnia patients. However, no significant difference was found in Aβ40, total tau (t-Tau), and phosphorylated tau (p-Tau) between the two groups. Furthermore, we found that CSF Aβ40 and Aβ42 levels are significantly correlated with the sleep quality, as reflected by the Pittsburgh Sleep Quality Index (PSQI) scores. But no significant correlation was found in CSF t-Tau and p-Tau levels with PSQI. Our results indicate that chronic sleep disorders may induce the disruption of Aβ metabolism in the brain, thus increase the risk for developing AD.
Keywords: Adult; Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Female; Humans; Male; Middle Aged; Phosphorylation; Sleep Initiation and Maintenance Disorders; tau Proteins

Cerebrospinal Fluid, MRI, and Florbetaben-PET in Cerebral Amyloid Angiopathy-Related Inflammation. - Renard, Dimitri; Collombier, Laurent; Demattei, Christophe; Wacongne, Anne; Charif, Mahmoud; Ayrignac, Xavier; Azakri, Souhayla; Gaillard, Nicolas; Boudousq, Vincent; Lehmann, Sylvain; Menjot de Champfleur, Nicolas; Thouvenot, Eric (J Alzheimers Dis, 2018)
BACKGROUND: Cerebral amyloid angiopathy-related inflammation (CAA-ri) is associated with a cerebrospinal fluid (CSF) biomarker profile similar to that observed in CAA. Few CAA-ri patients have been studied by fibrillar amyloid-β (Aβ) imaging (using 11C-Pittsburgh compound B and 18F-florbetapir, but not 18F-florbetaben). OBJECTIVE: To describe CSF biomarkers, magnetic resonance imaging (MRI), and 18F-florbetaben (FBB)-positron emission tomography (PET) changes in CAA-ri patients. METHODS: CSF levels of total tau, phosphorylated tau, Aβ1-42, and Aβ1-40, MRI (cerebral microbleeds count on susceptibility-weighted imaging and semi-quantitative analysis of fluid-attenuation inversion recovery white matter hyperintensities), and FBB-PET (using both cerebellar cortex and pons to calculate standardized uptake value ratios) were analyzed in nine consecutive CAA-ri patients. RESULTS: A median number of 769 cerebral microbleeds/patient were counted on MRI. When using the pons as reference region, amyloid load on FBB-PET was very strongly correlated to CSF Aβ1-40 levels (rho = -0.83, p = 0.008) and moderately correlated to cerebral microbleed numbers in the occipital lobes (rho = 0.59, p = 0.001), while comparisons with other CSF biomarkers were not statistically significant (total tau, rho = -0.63, p = 0.076; phosphorylated tau, rho = -0.68, p = 0.05; Aβ1-42, rho = -0.59, p = 0.09). All correlations were weaker, and not statistically significant, when using the cerebellum as reference region. A non-significant correlation (rho = -0.50, p = 0.18) was observed between CSF Aβ1-40 levels and cerebral microbleed numbers. CONCLUSION: In CAA-ri, CSF Aβ1-40 levels correlated well with amyloid load assessed by FBB-PET when the pons was used as reference, and to a lesser degree with cerebral microbleeds count on MRI. This confirms earlier data on CSF Aβ1-40 as an in vivo marker for CAA and CAA-ri.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Aniline Compounds; Biomarkers; Brain; Cerebral Amyloid Angiopathy; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Multivariate Analysis; Positron-Emission Tomography; Prospective Studies; Stilbenes; tau Proteins; Vasculitis, Central Nervous System

Change in Fitness and the Relation to Change in Cognition and Neuropsychiatric Symptoms After Aerobic Exercise in Patients with Mild Alzheimer's Disease. - Sobol, Nanna A; Dall, Christian Have; Høgh, Peter; Hoffmann, Kristine; Frederiksen, Kristian Steen; Vogel, Asmus; Siersma, Volkert; Waldemar, Gunhild; Hasselbalch, Steen G; Beyer, Nina (J Alzheimers Dis, 2018)
BACKGROUND: Physical activity has the potential to improve physical function in patients with Alzheimer's disease (AD) and may contribute to modify disease processes and cognitive function. OBJECTIVE: The aim of this study was to investigate 1) the effect of moderate-high-intensity aerobic exercise on cardiorespiratory fitness, i.e., peak oxygen uptake (VO2peak) determined by direct breath-by-breath cardiopulmonary exercise test, and 2) the association between changes in VO2peak and changes in cognition and neuropsychiatric symptoms in patients with mild AD. METHODS: The study is based on secondary outcome analyses from the large single-blinded multi-center study ADEX (Preserving Cognition, Quality of Life, Physical Health and Functional Ability in Alzheimer's Disease: The Effect of Physical Exercise). A preselected sub-group of 55 participants (age 52-83 years), 29 from the intervention group (IG) and 26 from the control group (CG), was included. IG performed 16 weeks of supervised moderate-to-high intensity aerobic exercise. Assessments of VO2peak, mental speed and attention (Symbol Digit Modalities Test, SDMT), and neuropsychiatric symptoms (Neuropsychiatric Inventory, NPI) were performed at baseline and at 16 weeks. RESULT: VO2peak increased 13% in the IG and a between-group difference in mean change (3.92 ml/kg/min, 95% CI 6.34-1.51, p = 0.003) was present in favor of the IG. Combined data from IG and CG showed positive associations between changes in VO2peak and changes in NPI (Rho = - 0.41, p = 0.042) and changes in SDMT (Rho = 0.36, p = 0.010), respectively. CONCLUSION: Aerobic exercise improves VO2peak in community-dwelling patients with mild AD. Furthermore, changes in VO2peak appear to be associated to changes in cognition and neuropsychiatric symptoms.

Characteristics of Cognitively Normal Mexican-Americans with Cognitive Complaints. - Hall, James R; Wiechmann, April; Johnson, Leigh A; Edwards, Melissa; O'Bryant, Sid E (J Alzheimers Dis, 2018)
BACKGROUND: Subjective cognitive complaints in cognitively normal adults have been linked to later cognitive decline and dementia. Research on the characteristics of this group has been conducted on a variety of clinical and community-based populations. The current study focuses on the rapidly expanding population of Mexican-American elders. OBJECTIVE: The objective of the study is the determination of characteristics of cognitively normal Mexican-Americans with cognitive complaints. METHODS: Data on 319 cognitively normal participants in a large-scale community-based study of elderly Mexican-Americans (HABLE) were analyzed comparing those with cognitive complaints with those without on clinical characteristics, affective status, neuropsychological functioning, and proteomic markers. RESULTS: Those expressing concern about cognitive decline scored lower on the MMSE, were more likely to have significantly more affective symptoms, higher levels of diabetic markers, poorer performance on attention and executive functioning, and a different pattern of inflammatory markers. CONCLUSION: Although longitudinal research is needed to determine the impact of these differences on later cognition, possible targets for early intervention with Mexican-Americans were identified.
Keywords: Aged; Biomarkers; Cognition; Cognitive Dysfunction; Executive Function; Female; Humans; Male; Mexican Americans; Middle Aged; Neuropsychological Tests; Risk Factors; Texas

Chinese Herbal Medicine for Vascular Dementia: A Systematic Review and Meta-Analysis of High-Quality Randomized Controlled Trials. - Xu, Qing-Qing; Shan, Chun-Shuo; Wang, Yong; Shi, Yi-Hua; Zhang, Qi-Hao; Zheng, Guo-Qing (J Alzheimers Dis, 2018)
BACKGROUND: Vascular dementia (VaD) is the second common form of dementia and Chinese herbal medicine (CHM) has been used for aging-related disorders for thousands of years. However, there is still a lack of scientific evidence using CHM for VaD. OBJECTIVE: To conduct a systematic review to assess the current evidence available for the effectiveness and safety of CHM for VaD. METHODS: Six databases were searched for high-quality randomized-controlled clinical trials that met the requirements of at least 4 of the 7 domains of the Cochrane risk of bias tool from their inception to February 2017. RevMan 5.3 was applied for data analysis. RESULTS: Forty studies with 42 comparisons and 3,572 individuals were included. The studies investigated the CHM versus placebo (n = 4), CHM versus western conventional treatment (WCT) (n = 36), and CHM plus WCT versus WCT (n = 2). Meta-analysis showed that CHM for VaD could improve Mini-Mental State Examination (MMSE), the Activities of Daily Living, Hasegawa's dementia scale, and clinical effective rate but had statistically similar effect based on Blessed Behavior Scale (BBS) outcome when compared with WCTs. When compared with placebo, CHMs were more beneficial in improving MMSE but showed no significant difference in BBS scores. CHM as adjuvant therapy exerted an additive anti-VaD benefit on MMSE scores. The participants of CHM group had fewer adverse events than that of the placebo group or WCT group. CONCLUSION: The findings of the present study support, at least to an extent, that CHM can be recommended for routine use for treatment of VaD.

Circulating Plasma microRNAs are Altered with Amyloidosis in a Mouse Model of Alzheimer's Disease. - Ryan, Margaret M; Guévremont, Diane; Mockett, Bruce G; Abraham, Wickliffe C; Williams, Joanna M (J Alzheimers Dis, 2018)
Pathological changes underlying Alzheimer's disease (AD) begin decades before the classical symptoms of memory loss become evident. As microRNAs are released from neurons and enter the bloodstream, circulating microRNAs may be reflective of AD progression and are ideal candidates as biomarkers for early-stage disease detection. Here, we provide a novel, in-depth analysis of how plasma microRNAs alter with aging, the most prominent risk factor for AD, and with development of amyloid-β (Aβ) plaque deposition. We assessed the circulating microRNAs in APPswe/PSEN1dE9 transgenic mice and wild-type controls at 4, 8 and 15 m (n = 8-10) using custom designed Taqman arrays representing 185 neuropathology-related microRNAs. We performed a linear mixed-effects model to investigate the effects of age and genotype on plasma microRNAs expression. Following this analysis, we found 8 microRNAs were significantly affected by age alone in wild-type animals and 12 microRNAs altered in APPswe/PSEN1dE9 mice, either prior to Aβ plaque deposition (4 m) or during the development of AD-like pathogenesis (8 m or 15 m). Importantly, we found that differing sets of microRNAs were identified at each time point. Functional analysis of these data revealed that while common biological pathways, such as Inflammatory Response, were enriched throughout the disease process, Free Radical Scavenging, Immunological Disease, and Apoptosis Signaling were specifically enriched later in the disease process. Overall, this study reinforces that distinct biological processes underpin the early versus late stages of AD-like pathogenesis and highlights potential pre-symptomatic microRNAs biomarkers of neurodegeneration.

Circulatory Levels of Toxic Metals (Aluminum, Cadmium, Mercury, Lead) in Patients with Alzheimer's Disease: A Quantitative Meta-Analysis and Systematic Review. - Xu, Lin; Zhang, Wenchao; Liu, Xianchen; Zhang, Cuili; Wang, Pin; Zhao, Xiulan (J Alzheimers Dis, 2018)
BACKGROUND: Environmental exposure to toxic metals has been postulated to play a role in the pathophysiological processes of Alzheimer's disease (AD). However, the circulatory levels of toxic metals in AD patients are not consistent in previous studies. OBJECTIVE: To systematically assess levels of toxic metals (aluminum, mercury, cadmium, lead) in the circulation (blood, serum/plasma) of AD patients and controls. METHODS: PubMed, Web of Science, Science Direct, Cochrane Library, and the China National Knowledge Infrastructure (CNKI) were systematically searched to identify studies published up to January 1, 2017. Meta-analyses were performed using random-effects models and the pooled standardized mean difference (SMD) were reported with 95% confidence intervals (CI). RESULTS: We identified 17, 7, 8, and 10 studies for aluminum, mercury, cadmium, and lead, respectively. Meta-analyses showed significantly elevated circulatory levels of aluminum (SMD = 1.08, 95% CI: 0.66, 1.50), mercury (SMD = 0.55, 95% CI, 0.15, 0.95), and cadmium (SMD = 0.62, 95% CI: 0.12, 1.11), whereas lower levels of lead (SMD = -0.23, 95% CI: -0.38, -0.07) in AD patients than in controls. Publication bias was only observed for aluminum studies, but the "trim and fill" analysis showed that the publication bias did not alter the direction of the effect. Sensitivity analyses showed no studies from the pooled analysis changed the results. CONCLUSION: Compared to controls, circulatory levels of aluminum, mercury, and cadmium are significantly higher but the levels of lead were reduced in AD patients. These findings suggest that elevated aluminum, mercury, and cadmium in the circulation, especially in serum may play a role in the progression of AD.

Cognitive Function in Individuals with Normal Weight Obesity: Results from the Third National Health and Nutrition Examination Survey (NHANES III). - Malandrino, Noemi; Capristo, Esmeralda; Taveira, Tracey H; Mingrone, Geltrude; Wu, Wen-Chih (J Alzheimers Dis, 2018)
BACKGROUND/OBJECTIVE: Normal weight obesity (NWO) is associated with increased risk of metabolic syndrome, cardiovascular- and all-cause mortality. However, no data have been reported on the relationship between adiposity and cognitive performance in NWO. We therefore studied the association between cognitive function and body fat percentage (BF%) in NWO, using a representative sample of the United States population. METHODS: A cross-sectional study was performed using the nationwide 1988 to 1994 data set from the Third National Health and Nutrition Examination Survey. Cognitive function was measured by three validated cognitive tests: simple reaction time test (SRTT), symbol digit substitution test (SDST), and serial digit learning test (SDLT). The association between BF% and cognitive performance was evaluated in 2,039 adults aged 20-59 years and with a body mass index ranging from 18.5 to 24.9 kg/m2. Linear regression modeling was used to adjust for potential confounders. RESULTS: Increased BF% was significantly associated with poorer performance on SDLT in the entire study sample (coefficient [95% CI]: 0.15 [0.01, 0.29]) and with poorer performance on SDST in the age group 20-29 years (coefficient [95% CI]: 0.30 [0.10, 0.49]). Increased BF% did not significantly predict poorer performance on SRTT. CONCLUSION: Higher BF% is significantly associated with poorer cognitive function in a nationally representative sample of US adults with NWO. The identification of possible complications associated with increased adipose tissue underlines the need to measure body fat content in NWO individuals, whose metabolic and cognitive dysfunction could go undetected for years due to their young age and normal body weight.

Cognitive Variability Predicts Incident Alzheimer's Disease and Mild Cognitive Impairment Comparable to a Cerebrospinal Fluid Biomarker. - Gleason, Carey E; Norton, Derek; Anderson, Eric D; Wahoske, Michelle; Washington, Danielle T; Umucu, Emre; Koscik, Rebecca L; Dowling, N Maritza; Johnson, Sterling C; Carlsson, Cynthia M; Asthana, Sanjay (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) biomarkers are emerging as critically important for disease detection and monitoring. Most biomarkers are obtained through invasive, resource-intense procedures. A cognitive marker, intra-individual cognitive variability (IICV) may provide an alternative or adjunct marker of disease risk for individuals unable or disinclined to undergo lumbar puncture. OBJECTIVE: To contrast risk of incident AD and mild cognitive impairment (MCI) associated with IICV to risk associated with well-established biomarkers: cerebrospinal fluid (CSF) phosphorylated tau protein (p-tau181) and amyloid-β 42 (Aβ42) peptide. METHODS: Dispersion in cognitive performance, IICV, was estimated with a published algorithm, and included Trail Making Test A and B, Rey Auditory Verbal Learning Test (RAVLT), and the American National Adult Reading Test (ANART). CSF biomarkers were expressed as a ratio: p-tau181/Aβ42, wherein high values signified pathognomonic profiles. Logistic regression models included longitudinal data from 349 Alzheimer's Disease Neuroimaging Initiative (ADNI) participants who completed lumbar puncture. All subjects were cognitively healthy (n = 105) or diagnosed with MCI (n = 244) at baseline. We examined odds of conversion associated with baseline elevations in IICV and/or ratio of CSF p-tau181/Aβ42. RESULTS: When included in models alone or in combination with CSF p-tau181/Aβ42, one standard IICV unit higher was associated with an estimated odds ratio for incident AD or MCI of 2.81 (95% CI: 1.83-4.33) in the most inclusive sample, and an odds ratio of 3.41 (95% CI: 2.03-5.73) when restricted to participants with MCI. Iterative analyses suggested that IICV independently improved model fit even when individual index components were included in comparative models. CONCLUSIONS: These analyses provide preliminary support for IICV as a marker of incident AD and MCI. This easily-disseminated, non-invasive marker compared favorably to well-established CSF biomarkers.
Keywords: Aged; Aged, 80 and over; Algorithms; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Cross-Sectional Studies; Female; Humans; Incidence; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Peptide Fragments; Statistics, Nonparametric; tau Proteins

Common Variant in PLD3 Influencing Cerebrospinal Fluid Total Tau Levels and Hippocampal Volumes in Mild Cognitive Impairment Patients from the ADNI Cohort. - Tan, Meng-Shan; Wang, Ping; Ma, Fang-Chen; Li, Jie-Qiong; Tan, Chen-Chen; Yu, Jin-Tai; Tan, Lan (J Alzheimers Dis, 2018)
Recent studies found the variants in Alzheimer's disease (AD) risk gene PLD3 were associated with cognitive function, but its detailed mechanism before typical AD onset was unknown. Our current study examined the impact of PLD3 common variant rs11667768 on cerebrospinal fluid (CSF) total-tau and phosphorylated-tau levels and structural MRI from the ADNI database. We found rs11667768 was significantly associated with CSF total-tau levels and hippocampal volumes at baseline and six-year follow-up in the total non-demented elderly group and the mild cognitive impairment subgroup, indicating a potential role of PLD3 common variants in influencing cognitive function through changing CSF total-tau levels and hippocampal volumes.

Comprehensive Characterization of the Pyroglutamate Amyloid-β Induced Motor Neurodegenerative Phenotype of TBA2.1 Mice. - Dunkelmann, Tina; Schemmert, Sarah; Honold, Dominik; Teichmann, Kerstin; Butzküven, Elke; Demuth, Hans-Ulrich; Shah, Nadim Joni; Langen, Karl-Josef; Kutzsche, Janine; Willbold, Dieter; Willuweit, Antje (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is the most common neurodegenerative disorder and is being intensively investigated using a broad variety of animal models. Many of these models express mutant versions of human amyloid-β protein precursor (AβPP) that are associated with amyloid-β protein (Aβ)-induced early onset familial AD. Most of these models, however, do not develop bold neurodegenerative pathology and the respective phenotypes. Nevertheless, this may well be essential for their suitability to identify therapeutically active compounds that have the potential for a curative or at least disease-modifying therapy in humans. In this study, the new transgenic mouse model TBA2.1 was explored in detail to increase knowledge about the neurodegenerative process induced by the presence of pyroglutamate modified human Aβ3-42 (pEAβ3-42). Analysis of the sensorimotor phenotype, motor coordination, Aβ pathology, neurodegeneration, and gliosis revealed formation and progression of severe pathology and phenotypes including massive neuronal loss in homozygous TBA2.1 mice within a few months. In contrast, the start of a slight phenotype was observed only after 21 months in heterozygous mice. These data highlight the role of pEAβ3-42 in the disease development and progression of AD. Based on the findings of this study, homozygous TBA2.1 mice can be utilized to gain deeper understanding in the underlying mechanisms of pEAβ3-42 and might be suitable as an animal model for treatment studies targeting toxic Aβ species, complementary to the well described transgenic AβPP mouse models.

Constructing a Local Potential Participant Registry to Improve Alzheimer's Disease Clinical Research Recruitment. - Grill, Joshua D; Hoang, Dan; Gillen, Daniel L; Cox, Chelsea G; Gombosev, Adrijana; Klein, Kirsten; O'Leary, Steve; Witbracht, Megan; Pierce, Aimee (J Alzheimers Dis, 2018)
Potential participant registries are tools to address the challenge of slow recruitment to clinical research. In particular, registries may aid recruitment to secondary prevention clinical trials for Alzheimer's disease (AD), which enroll cognitively normal older individuals meeting specific genetic or biomarker criteria. Evidence of registry effectiveness is sparse, as is guidance on optimal designs or methods of conduct. We report our experiences of developing a novel local potential participant registry that implemented online enrollment and data collection. In the first year of operation, 957 individuals submitted email addresses to the registry, of whom 592 self-reported demographic, family history, and medical data. In addition, registrants provided information related to their interest and willingness to be contacted about studies. Local earned media and community education were the most effective methods of recruitment into the registry. Seventy-six (26%) of 298 registrants contacted about studies in the first year enrolled in those studies. One hundred twenty-nine registrants were invited to enroll in a preclinical AD trial, of whom 25 (18%) screened and 6 were randomized. These results indicate that registries can aid recruitment and provide needed guidance for investigators initiating new local registries.

Cysteine-Rich Repeat Domains 2 and 4 are Amyloid-β Binding Domains of Neurotrophin Receptor p75NTR and Potential Targets to Block Amyloid-β Neurotoxicity. - Wang, Ye-Ran; Wang, Jun; Liu, Yu-Hui; Hu, Gong-Ling; Gao, Chang-Yue; Wang, Yan-Jiang; Zhou, Xin-Fu; Zeng, Fan (J Alzheimers Dis, 2018)
The p75 neurotrophin receptor (p75NTR) is an amyloid-β (Aβ) receptor that both mediates Aβ neurotoxicity and regulates Aβ production and deposition, thus playing an important role in the pathogenesis of Alzheimer's disease (AD). The extracellular domain of p75NTR (p75ECD), consisting of four cysteine-rich repeat domains (CRDs), was recently reported to be an endogenous anti-Aβ scavenger to block p75NTR-mediated neuronal death and neurite degeneration signaling of Aβ and pro-neurotrophins. Identification of the specific Aβ binding domains of p75NTR is crucial for illuminating their interactions and the etiology of AD. CRDs of p75ECD were obtained by expression of recombinant plasmids or direct synthesis. Aβ aggregation inhibiting test and immunoprecipitation assay were applied to locate the specific binding domains of Aβ to p75ECD. The Aβ neurotoxicity antagonistic effects of different CRDs were examined by cytotoxicity experiments including neurite outgrowth assay, propidium iodide (PI) staining, and MTT assay. In the Aβ aggregation inhibiting test, the fluorescence intensity in the CRD2 and CRD4 treatment groups was significantly lower than that in the CRD1 and CRD3 treatment groups. Immunoprecipitation assay and western blot confirmed that Aβ could bind to CRD2 and CRD4. Besides, CRD2 and CRD4 antagonized Aβ neurotoxicity suggested by longer neurite length, less PI labelled cells, and higher cell viability than the control group. Our results indicate that CRD2 and CRD4 are Aβ binding domains of p75NTR and capable of antagonizing Aβ neurotoxicity, and therefore are potential therapeutic targets to block the interaction of Aβ and p75NTR in the pathogenesis of AD.

A Decade of Blood Biomarkers for Alzheimer's Disease Research: An Evolving Field, Improving Study Designs, and the Challenge of Replication. - Shi, Liu; Baird, Alison L; Westwood, Sarah; Hye, Abdul; Dobson, Richard; Thambisetty, Madhav; Lovestone, Simon (J Alzheimers Dis, 2018)
Blood-based biomarkers represent a less invasive and potentially cheaper approach for aiding Alzheimer's disease (AD) detection compared with cerebrospinal fluid and some neuroimaging biomarkers. Acknowledging that many in the field have made great progress, here we review some of the work that our group has pursued to identify and validate blood-based proteomic biomarkers through both case control and AD pathology endophenotype-based approaches. Our focus is primarily to identify a minimally invasive and hopefully cost-effective blood-based biomarker to reduce screen failure in clinical trials where participants have prodromal or even pre-clinical disease. We summarize some of the key findings and approaches taken in these biomarker studies, while addressing the main challenges, including that of limited replication in the field, and discuss opportunities for biomarker development.

Deep Brain Stimulation of Frontal Lobe Networks to Treat Alzheimer's Disease. - Scharre, Douglas W; Weichart, Emily; Nielson, Dylan; Zhang, Jun; Agrawal, Punit; Sederberg, Per B; Knopp, Michael V; Rezai, Ali R (J Alzheimers Dis, 2018)
The study objective was to evaluate the safety and efficacy of deep brain stimulation (DBS) at the ventral capsule/ventral striatum (VC/VS) region to specifically modulate frontal lobe behavioral and cognitive networks as a novel treatment approach for Alzheimer's disease (AD) patients. This is a non-randomized phase I prospective open label interventional trial of three subjects with matched comparison groups. AD participants given DBS for at least 18 months at the VC/VS target were compared on the Clinical Dementia Rating-Sum of Boxes (CDR-SB), our primary outcome clinical measure, to matched groups without DBS from the AD Neuroimaging Initiative (ADNI) cohort. Serial 2-Deoxy-2-[18F]fluoro-D-glucose (FDG) positron emission tomography (PET) images of AD participants were also compared longitudinally over time. Three AD DBS participants were matched to subjects from the ADNI cohort. All participants tolerated DBS well without significant adverse events. All three AD DBS participants had less performance decline and two of them meaningfully less decline over time on our primary outcome measure, CDR-SB, relative to matched comparison groups from the ADNI using score trajectory slopes. Minimal changes or increased metabolism on FDG-PET were seen in frontal cortical regions after chronic DBS at the VC/VS target. The first use of DBS in AD at a frontal lobe behavior regulation target (VC/VS) was well-tolerated and revealed less performance decline in CDR-SB. Frontal network modulation to improve executive and behavioral deficits should be furthered studied in AD.
Keywords: Aged; Alzheimer Disease; Deep Brain Stimulation; Female; Frontal Lobe; Humans; Male; Middle Aged; Ohio; Pilot Projects; Positron-Emission Tomography; Prospective Studies

Deep Brain Stimulation Targeting the Fornix for Mild Alzheimer Dementia (the ADvance Trial): A Two Year Follow-up Including Results of Delayed Activation. - Leoutsakos, Jeannie-Marie S; Yan, Haijuan; Anderson, William S; Asaad, Wael F; Baltuch, Gordon; Burke, Anna; Chakravarty, M Mallar; Drake, Kristen E; Foote, Kelly D; Fosdick, Lisa; Giacobbe, Peter; Mari, Zoltan; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Given recent challenges in developing new treatments for Alzheimer dementia (AD), it is vital to explore alternate treatment targets, such as neuromodulation for circuit dysfunction. We previously reported an exploratory Phase IIb double-blind trial of deep brain stimulation targeting the fornix (DBS-f) in mild AD (the ADvance trial). We reported safety but no clinical benefits of DBS-f versus the delayed-on (sham) treatment in 42 participants after one year. However, secondary post hoc analyses of the one-year data suggested a possible DBS-f benefit for participants≥65 years. OBJECTIVE: To examine the long-term safety and clinical effects of sustained and delayed-on DBS-f treatment of mild AD after two years. METHODS: 42 participants underwent implantation of DBS-f electrodes, with half randomized to active DBS-f stimulation (early on) for two years and half to delayed-on (sham) stimulation after 1 year to provide 1 year of active DBS-f stimulation (delayed on). We evaluated safety and clinical outcomes over the two years of the trial. RESULTS: DBS-f had a favorable safety profile with similar rates of adverse events across both trial phases (years 1 and 2) and between treatment arms. There were no differences between treatment arms on any primary clinical outcomes. However, post-hoc age group analyses suggested a possible benefit among older (>65) participants. CONCLUSION: DBS-f was safe. Additional study of mechanisms of action and methods for titrating stimulation parameters will be needed to determine if DBS has potential as an AD treatment. Future efficacy studies should focus on patients over age 65.

Depression and Alzheimer's Disease Biomarkers Predict Driving Decline. - Babulal, Ganesh M; Chen, Suzie; Williams, Monique M; Trani, Jean-Francois; Bakhshi, Parul; Chao, Grace L; Stout, Sarah H; Fagan, Anne M; Benzinger, Tammie L S; Holtzman, David M; Morris, John C; Roe, Catherine M (J Alzheimers Dis, 2018)
BACKGROUND: Symptomatic Alzheimer's disease (AD) and depression independently increase crash risk. Additionally, depression is both a risk factor for and a consequence of AD. OBJECTIVE: To examine whether a depression diagnosis, antidepressant use, and preclinical AD are associated with driving decline among cognitively normal older adults. METHODS: Cognitively normal participants, age ≥65, were enrolled. Cox proportional hazards models evaluated whether a depression diagnosis, depressive symptoms (Geriatric Depression Scale), antidepressant use, cerebrospinal fluid (amyloid-β42 [Aβ42], tau, phosphorylated tau181 [ptau181]), and amyloid imaging biomarkers (Pittsburgh Compound B and Florbetapir) were associated with time to receiving a rating of marginal/fail on a road test. Age was adjusted for in all models. RESULTS: Data were available from 131 participants with age ranging from 65.4 to 88.2 years and mean follow up of 2.4 years (SD = 1.0). A depression diagnosis was associated with a faster time to receiving a marginal/fail rating on a road test and antidepressant use (p = 0.024, HR = 2.62). Depression diagnosis and CSF and amyloid PET imaging biomarkers were associated with driving performance on the road test (p≤0.05, HR = 2.51-3.15). In the CSF ptau181 model, depression diagnosis (p = 0.031, HR = 2.51) and antidepressant use (p = 0.037, HR = 2.50) were statistically significant predictors. There were no interaction effects between depression diagnosis, antidepressant use, and biomarker groups. Depressive symptomology was not a statistically significant predictor of driving performance. CONCLUSIONS: While, as previously shown, preclinical AD alone predicts a faster time to receiving a marginal/fail rating, these results suggest that also having a diagnosis of depression accelerates the onset of driving problems in cognitively normal older adults.

Diagnostic Value of Diffusion Tensor Imaging and Positron Emission Tomography in Early Stages of Frontotemporal Dementia. - Krämer, Julia; Lueg, Gero; Schiffler, Patrick; Vrachimis, Alexis; Weckesser, Matthias; Wenning, Christian; Pawlowski, Matthias; Johnen, Andreas; Teuber, Anja; Wersching, Heike; Meuth, Sven G; Duning, Thomas (J Alzheimers Dis, 2018)
BACKGROUND: Due to suboptimal sensitivity and specificity of structural and molecular neuroimaging tools, the diagnosis of behavioral variant frontotemporal dementia (bvFTD) remains challenging. OBJECTIVE: Investigation of the sensitivity of diffusion tensor imaging (DTI) and fluorodeoxyglucose positron emission tomography (FDG-PET) to detect cerebral alterations in early stages of bvFTD despite inconspicuous conventional MRI. METHODS: Thirty patients with early stages of bvFTD underwent a detailed neuropsychological examination, cerebral 3T MRI with DTI analysis, and FDG-PET. After 12 months of follow-up, all patients finally fulfilled the diagnosis of bvFTD. Individual FDG-PET data analyses showed that 20 patients exhibited a "typical" pattern for bvFTD with bifrontal and/or temporal hypometabolism (bvFTD/PET+), and that 10 patients showed a "non-typical"/normal pattern (bvFTD/PET-). DTI data were compared with 42 healthy controls in an individual and voxel-based group analysis. To examine the clinical relevance of the findings, associations between pathologically altered voxels of DTI or FDG-PET results and behavioral symptoms were estimated by linear regression analyses. RESULTS: DTI voxel-based group analyses revealed microstructural degeneration in bifrontal and bitemporal areas in bvFTD/PET+ and bvFTD/PET- groups. However, when comparing the sensitivity of individual DTI data analysis with FDG-PET, DTI appeared to be less sensitive. Neuropsychological symptoms were considerably related to neurodegeneration within frontotemporal areas identified by DTI and FDG-PET. CONCLUSION: DTI seems to be an interesting tool for detection of functionally relevant neurodegenerative alterations in early stages of bvFTD, even in bvFTD/PET- patients. However, at a single subject level, it seems to be less sensitive than FDG-PET. Thus, improvement of individual DTI analysis is necessary.

Differential Effect of APOE ɛ4 Status and Elevated Pulse Pressure on Functional Decline in Cognitively Normal Older Adults. - Werhane, Madeleine L; Thomas, Kelsey R; Edmonds, Emily C; Bangen, Katherine J; Tran, My; Clark, Alexandra L; Nation, Daniel A; Gilbert, Paul E; Bondi, Mark W; Delano-Wood, Lisa (J Alzheimers Dis, 2018)
BACKGROUND/OBJECTIVE: The APOE ɛ4 allele and increased vascular risk have both been independently linked to cognitive impairment and dementia. Since few studies have characterized how these risk factors affect everyday functioning, we investigated the relationship between APOE ɛ4 genotype and elevated pulse pressure (PP) on functional change in cognitively normal participants from the Alzheimer's Disease Neuroimaging Initiative (ADNI). METHODS: 738 normally aging participants underwent APOE genotyping, and baseline PP was calculated from blood pressure indices. The Functional Activities Questionnaire (FAQ) was completed by participants' informant at baseline and 6, 12, 24, 36, and 48-month follow-up visits. Multiple linear regression and multilevel modeling were used to examine the effects of PP and APOE ɛ4 genotype on cross-sectional and longitudinal FAQ scores, respectively. RESULTS: Adjusting for demographic and clinical covariates, results showed that both APOE ɛ4 status and elevated PP predicted greater functional difficulty trajectories across four years of follow-up. Interestingly, however, elevated PP was associated with greater functional decline over time in ɛ4 non-carriers versus carriers. CONCLUSION: Results show that, although APOE ɛ4 status is the prominent predictor of functional difficulty for ɛ4 carriers, an effect of arterial stiffening on functional difficulty was observed in non-carriers. Future studies are needed in order to clarify the etiology of the association between PP and different brain aging processes, and further explore its utility as a marker of dementia risk. The present study underscores the importance of targeting modifiable risk factors such as elevated PP to prevent or slow functional decline and pathological brain aging.

Diffuse Amyloid-β Plaques, Neurofibrillary Tangles, and the Impact of APOE in Elderly Persons' Brains Lacking Neuritic Amyloid Plaques. - Abner, Erin L; Neltner, Janna H; Jicha, Gregory A; Patel, Ela; Anderson, Sonya L; Wilcock, Donna M; Van Eldik, Linda J; Nelson, Peter T (J Alzheimers Dis, 2018)
Data from a large autopsy series were analyzed to address questions pertinent to primary age-related tauopathy (PART) and Alzheimer's disease (AD): what factors are associated with increased severity of neurofibrillary degeneration in brains that lack neuritic amyloid plaques?; is there an association between Apolipoprotein E (APOE) alleles and PART pathologic severity independent of amyloid-β (Aβ) deposits?; and, how do the stains used to detect plaques and tangles impact the experimental results? Neuropathologic data were evaluated from elderly research volunteers whose brain autopsies were performed at University of Kentucky Alzheimer's Disease Center (UK-ADC; N = 145 subjects). All of the included subjects' brains lacked neuritic amyloid plaques according to the CERAD diagnostic criteria and the average final MMSE score before death was 26.8±4.6 stdev. The study incorporated evaluation of tissue with both silver histochemical stains and immunohistochemical stains to compare results; the immunohistochemical stains (Aβ and phospho-tau) were scanned and quantified using digital pathologic methods. Immunohistochemical stains provided important advantages over histochemical stains due to sensitivity and detectability via digital methods. When AD-type pathology was in its presumed earliest phases, neocortical parenchymal Aβ deposits were associated with increased medial temporal lobe neurofibrillary tangles. The observation supports the NIA-AA consensus recommendation for neuropathologic diagnoses, because even these "diffuse" Aβ deposits signal that AD pathobiologic mechanisms are occurring. Further, the data were most compatible with the hypothesis that the APOEɛ4 allele exerts its effect(s) via driving Aβ deposition, i.e., an "upstream" influence, rather than being associated directly with Aβ- independent PART pathology.

Diosgenin Attenuates Lipopolysaccharide-Induced Parkinson's Disease by Inhibiting the TLR/NF-κB Pathway. - Li, Bingyu; Xu, Pengli; Wu, Shuyan; Jiang, Zhixian; Huang, Zhijian; Li, Qian; Chen, Danhong (J Alzheimers Dis, 2018)
BACKGROUND: Parkinson's disease (PD) is a neurodegenerative disease characterized by loss of dopaminergic neurons in the substantia nigra. Diosgenin is a natural steroid saponin which was shown to play a beneficial role in Alzheimer's disease. OBJECTIVE: This study sought to investigate the potential effect of diosgenin on a rat model of PD. METHODS: Sprague Dawley rats were subjected to intra-striatal injection of lipopolysaccharide (LPS) and treated with diosgenin. Stepping, Whisker, and Cylinder tests were carried out to determine the motor function, and the expression of tyrosine hydroxylase was detected by immunohistochemistry. The levels of multiple proinflammatory cytokines, oxidative stress related factors and proteins involved in Toll-like receptor (TLR)/nuclear factor kappa B (NF-κB) pathway were measured. The synergistic effect of environment enrichment on diosgenin was also investigated. RESULTS: Intra-striatal injection of LPS caused motor deficits in rats, induced inflammatory response and oxidative stress response, and activated the TLR/NF-κB pathway both in vivo and in vitro. Diosgenin could attenuate the LPS-induced alterations. Enriched environment enhanced the effect of diosgenin to ameliorate the LPS-induced motor deficits in rats and decreased the protein levels of TLR2, TLR4, and nuclear NF-κB in diosgenin treated PD rats. CONCLUSION: Diosgenin had a beneficial effect in LPS-induced rat PD models, by suppressing the TLR/NF-κB signaling pathway. Environmental enrichment could play a synergistic effect with diosgenin, by enhancing the inhibitory effect of diosgenin on the TLR/ NF-κB signaling pathway.

Dipeptidyl-Peptidase Activity of Meprin β Links N-truncation of Aβ with Glutaminyl Cyclase-Catalyzed pGlu-Aβ Formation. - Schlenzig, Dagmar; Cynis, Holger; Hartlage-Rübsamen, Maike; Zeitschel, Ulrike; Menge, Katja; Fothe, Anja; Ramsbeck, Daniel; Spahn, Claudia; Wermann, Michael; Roßner, Steffen; Buchholz, Mirko; Schilling, Stephan; et al. (J Alzheimers Dis, 2018)
The formation of amyloid-β (Aβ) peptides is causally involved in the development of Alzheimer's disease (AD). A significant proportion of deposited Aβ is N-terminally truncated and modified at the N-terminus by a pGlu-residue (pGlu-Aβ). These forms show enhanced neurotoxicity compared to full-length Aβ. Although the truncation may occur by aminopeptidases after formation of Aβ, recently discovered processing pathways of amyloid-β protein precursor (AβPP) by proteases such as meprin β may also be involved. Here, we assessed a role of meprin β in forming Aβ3-40/42, which is the precursor of pGlu-Aβ3-40/42 generated by glutaminyl cyclase (QC). Similar to QC, meprin β mRNA is significantly upregulated in postmortem brain from AD patients. A histochemical analysis supports the presence of meprin β in neurons and astrocytes in the vicinity of pGlu-Aβ containing deposits. Cleavage of AβPP-derived peptides by meprin β in vitro results in peptides Aβ1-x, Aβ2-x, and Aβ3-x. The formation of N-truncated Aβ by meprin β was also corroborated in cell culture. A subset of the generated peptides was converted into pGlu-Aβ3-40 by an addition of glutaminyl cyclase, supporting the preceding formation of Aβ3-40. Further analysis of the meprin β cleavage revealed a yet unknown dipeptidyl-peptidase-like activity specific for the N-terminus of Aβ1-x. Thus, our data suggest that meprin β contributes to the formation of N-truncated Aβ by endopeptidase and exopeptidase activity to generate the substrate for QC-catalyzed pGlu-Aβ formation.

Disease Course Varies According to Age and Symptom Length in Alzheimer's Disease. - Barnes, Josephine; Bartlett, Jonathan W; Wolk, David A; van der Flier, Wiesje M; Frost, Chris (J Alzheimers Dis, 2018)
Health-care professionals, patients, and families seek as much information as possible about prognosis for patients with Alzheimer's disease (AD); however, we do not yet have a robust understanding of how demographic factors predict prognosis. We evaluated associations between age at presentation, age of onset, and symptom length with cognitive decline as measured using the Mini-Mental State Examination (MMSE) and Clinical Dementia Rating sum-of-boxes (CDR-SOB) in a large dataset of AD patients. Age at presentation was associated with post-presentation decline in MMSE (p < 0.001), with younger patients showing faster decline. There was little evidence of an association with change in CDR-SOB. Symptom length, rather than age, was the strongest predictor of MMSE and CDR-SOB at presentation, with increasing symptom length associated with worse outcomes. The evidence that younger AD patients have a more aggressive disease course implies that early diagnosis is essential.

Distinct Neuroanatomical Correlates of Neuropsychiatric Symptoms in the Three Main Forms of Genetic Frontotemporal Dementia in the GENFI Cohort. - Sellami, Leila; Bocchetta, Martina; Masellis, Mario; Cash, David M; Dick, Katrina M; van Swieten, John; Borroni, Barbara; Galimberti, Daniela; Tartaglia, Maria Carmela; Rowe, James B; Graff, Caroline; Tagliavini, Fabrizio; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The overlap between frontotemporal dementia (FTD) and primary psychiatric disorders has been brought to light by reports of prominent neuropsychiatric symptoms (NPS) in FTD-related genetic mutations, particularly among C9orf72 and GRN carriers. It has been recently demonstrated that early neuroanatomical changes in genetic FTD may be different across the major disease-causing mutations. OBJECTIVE: We aimed to identify whether NPS could be driven by distinct structural correlates. METHODS: One hundred and sixty-seven mutation carriers (75 GRN, 60 C9orf72, and 32 MAPT) were included from the Genetic FTD Initiative (GENFI) study, a large international cohort of genetic FTD. Neuropsychiatric symptoms including delusions, hallucinations (visual, auditory, and tactile), depression, and anxiety were investigated using a structured interview. Voxel-based morphometry was performed to identify neuroanatomical correlates of NPS. RESULTS: Psychotic symptoms correlated mainly with grey matter (GM) atrophy in the anterior insula, left thalamus, cerebellum, and cortical regions including frontal, parietal, and occipital lobes in GRN mutations carriers. GM atrophy in posterior structures of the default-mode network was associated with anxiety in the GRN group. Delusions in C9orf72 expansion carriers were mainly associated with left frontal cortical atrophy. Cerebellar atrophy was found to be correlated only with anxiety in C9orf72 carriers. NPS in the MAPT group were mainly associated with volume loss in the temporal lobe. CONCLUSION: Neuroanatomical correlates of NPS appear to be distinct across the main forms of genetic FTD. Overall, our findings support overlapping brain structural changes between FTD and primary psychiatric disorders.

Distinct White Matter Changes Associated with Cerebrospinal Fluid Amyloid-β1-42 and Hypertension. - Al-Janabi, Omar M; Brown, Christopher A; Bahrani, Ahmed A; Abner, Erin L; Barber, Justin M; Gold, Brian T; Goldstein, Larry B; Murphy, Ronan R; Nelson, Peter T; Johnson, Nathan F; Shaw, Leslie M; Smith, Charles D; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) pathology and hypertension (HTN) are risk factors for development of white matter (WM) alterations and might be independently associated with these alterations in older adults. OBJECTIVE: To evaluate the independent and synergistic effects of HTN and AD pathology on WM alterations. METHODS: Clinical measures of cerebrovascular disease risk were collected from 62 participants in University of Kentucky Alzheimer's Disease Center studies who also had cerebrospinal fluid (CSF) sampling and MRI brain scans. CSF Aβ1-42 levels were measured as a marker of AD, and fluid-attenuated inversion recovery imaging and diffusion tensor imaging were obtained to assess WM macro- and microstructural properties. Linear regression analyses were used to assess the relationships among WM alterations, cerebrovascular disease risk, and AD pathology. Voxelwise analyses were performed to examine spatial patterns of WM alteration associated with each pathology. RESULTS: HTN and CSF Aβ1-42 levels were each associated with white matter hyperintensities (WMH). Also, CSF Aβ1-42 levels were associated with alterations in normal appearing white matter fractional anisotropy (NAWM-FA), whereas HTN was marginally associated with alterations in NAWM-FA. Linear regression analyses demonstrated significant main effects of HTN and CSF Aβ1-42 on WMH volume, but no significant HTN×CSF Aβ1-42 interaction. Furthermore, voxelwise analyses showed unique patterns of WM alteration associated with hypertension and CSF Aβ1-42. CONCLUSION: Associations of HTN and lower CSF Aβ1-42 with WM alteration were statistically and spatially distinct, suggesting independent rather than synergistic effects. Considering such spatial distributions may improve diagnostic accuracy to address each underlying pathology.

The Distribution of Urinary Alzheimer-Associated Neuronal Thread Protein and Its Association with Common Chronic Diseases in the General Population. - Jin, He; Guan, Shaochen; Wang, Rong; Fang, Xianghua; Liu, Hongjun; Wu, Yanchuan; Zhang, Yanlei; Liu, Chunxiao (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer-associated neuronal thread protein (AD7c-NTP) has been found to be a biomarker for Alzheimer's disease (AD). OBJECTIVE: The aim of the present study was to investigate the distribution of Alzheimer-associated neuronal thread protein and its relationship to common chronic diseases in the general population. METHODS: Urine samples of 1,805 participants were collected from four districts (Xi Cheng, Fang Shan, Tong Zhou, and Yan Qing) in Beijing. The assessment in this study included a questionnaire that captured participants' demographic information, use of medication and histories of disease, neurological examinations, psychometric evaluations, physical and clinical examinations, and laboratory tests. RESULTS: Urine AD7c-NTP level was increased among the population over 60 years old and females exhibited higher levels than males. These results controlled for other demographic factors such as education levels, employment status, body mass index and current residence. The urine AD7c-NTP levels exhibited no association with non-neurological diseases (0.3346±0.4482 ng/ml), such as hypertension (0.3445±0.4187), stroke (0.3652±0.4010), diabetes (0.3319±0.4371), dyslipidemia (0.3440±0.4314), renal insufficiency (0.3223±0.3909), cancer (0.5055±1.0006), chronic lung disease (0.2911±0.2852), chronic liver disease (0.5579±0.6726), severe depression symptoms (0.5186±0.7040), and mild depression symptoms (0.3669±0.3811). CONCLUSIONS: Cut-off values for urine AD7c-NTP levels for different age groups and genders should be established. AD7c-NTP levels proved relatively stable in the body and were not impacted by demographic factors or common chronic diseases.

DJ-1 Suppresses Cytoplasmic TDP-43 Aggregation in Oxidative Stress-Induced Cell Injury. - Lei, Yang; Zhang, Zhi-Feng; Lei, Rui-Xue; Wang, Shu; Zhuang, Yang; Liu, An-Chun; Wu, Yan; Chen, Juan; Tang, Jun-Chun; Pan, Meng-Xian; Liu, Rui; Liao, Wei-Jing; et al. (J Alzheimers Dis, 2018)
DJ-1 (also called PARK7) is a multifunctional redox-sensitive protein that is protective against oxidative stress-induced cell death. TAR DNA-binding protein 43 (TDP-43) is a major protein component of pathological inclusions in amyotrophic lateral sclerosis and frontotemporal dementia. Reducing aberrant aggregation of TDP-43 is a potential approach to prevent cell death. To investigate whether DJ-1 might inhibit TDP-43 aggregation to exert a protective effect in oxidative stress-induced injury, we tested the protein level and subcellular localization of TDP-43 and DJ-1 in SH-SY5Y cells transfected with wild-type DJ-1, DJ-1 mutant (L166P) cDNA, or DJ-1 siRNA. We show that oxidative stress induced by paraquat leads to the formation of cytosolic TDP-43 aggregation in SH-SY5Y cells. DJ-1 overexpression decreases paraquat-induced cytoplasmic accumulation of TDP-43 in SH-SY5Y cells and protects against paraquat-induced cell death. Transfection of DJ-1 L166P mutant or DJ-1 siRNA leads to increased cytosolic aggregation of TDP-43 in paraquat-treated SH-SY5Y cells and promotes cell death. These data suggest that DJ-1 may protect against oxidative stress-induced cell death through the suppression of cytoplasmic TDP-43 aggregation.

Does Fatty Acid Composition in Subcutaneous Adipose Tissue Differ between Patients with Alzheimer's Disease and Cohabiting Proxies? - Faxen-Irving, Gerd; Falahati, Farshad; Basun, Hans; Eriksdotter, Maria; Vedin, Inger; Wahlund, Lars-Olof; Schultzberg, Marianne; Hjorth, Erik; Palmblad, Jan; Cederholm, Tommy; Freund-Levi, Yvonne (J Alzheimers Dis, 2018)
Low tissue levels of the major marine ω3 fatty acids (FAs) DHA and EPA are found in Alzheimer's disease (AD). We investigated if healthy proxies to AD patients have higher levels of these ω3 FAs. We observed lower levels of EPA and DHA in subcutaneous adipose tissue biopsies from 64 AD patients compared with 16 cognitively healthy proxies. No significant difference was observed when pairwise comparisons were made between a subset of 16 AD patients and their co-habiting proxies. Larger studies are needed to replicate these findings and to determine if they could depend on FA intake or differences in metabolism.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Dietary Supplements; Fatty Acids, Omega-3; Female; Humans; Male; Regression Analysis; Subcutaneous Fat

Does the Genetic Feature of the Chinese Tree Shrew (Tupaia belangeri chinensis) Support Its Potential as a Viable Model for Alzheimer's Disease Research? - Fan, Yu; Luo, Rongcan; Su, Ling-Yan; Xiang, Qun; Yu, Dandan; Xu, Ling; Chen, Jia-Qi; Bi, Rui; Wu, Dong-Dong; Zheng, Ping; Yao, Yong-Gang (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a neurodegenerative disease with increasing incidence across the world and no cure at the present time. An ideal animal model would facilitate the understanding of the pathogenesis of AD and discovery of potential therapeutic targets. The Chinese tree shrew (Tupaia belangeri chinensis) has a closer genetic affinity to primates relative to rodents, and can attain ages of 8 years or older, which represents another advantage for the study of neurodegenerative diseases such as AD compared to primates. Here, we analyzed 131 AD-related genes in the Chinese tree shrew brain tissues based on protein sequence identity, positive selection, mRNA, and protein expression by comparing with those of human, rhesus monkey, and mouse. In particular, we focused on the Aβ and neurofibrillary tangles formation pathways, which are crucial to AD pathogenesis. The Chinese tree shrew had a generally higher sequence identity with human than that of mouse versus human for the AD pathway genes. There was no apparent selection on the tree shrew lineage for the AD-related genes. Moreover, expression pattern of the Aβ and neurofibrillary tangle formation pathway genes in tree shrew brain tissues resembled that of human brain tissues, with a similar aging-dependent effect. Our results provided an essential genetic basis for future AD research using the tree shrew as a viable model.
Keywords: Alzheimer Disease; Amino Acid Sequence; Animals; Biomedical Research; Disease Models, Animal; Gene Expression Profiling; Humans; Male; Mice; Tupaia

The Down-Expression of ACE and IDE Exacerbates Exogenous Amyloid-β Neurotoxicity in CB2R-/- Mice. - Wang, Lin; Shi, Fang-Xiao; Xu, Wei-Qi; Cao, Yun; Li, Na; Li, Man; Wang, Qun; Wang, Jian-Zhi; Tian, Qing; Yu, Li-Kai; Zhou, Xin-Wen (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is characterized by neuritic plaques and neurofibrillary tangles. It is reported that enzymatic degradation of amyloid-β (Aβ) plays a pivotal role in Aβ accumulation and type-2 cannabinoid receptor (CB2R) participates in Aβ processing in the brain; however, the underlying mechanisms remain unclear. We determined that Aβ degradation-related proteins are significantly different between CB2R-/- mice and wild-type (WT) mice via proteomic analysis. Moreover, the data demonstrated that the angiotensin converting enzyme (ACE) and insulin-degrading enzyme (IDE) levels are substantially attenuated, and the Aβ level is significantly enhanced in CB2R-/--Aβ1 - 42 mice compared with that of WT-Aβ1 - 42 mice. Furthermore, Aβ-mediated synaptic dysfunction, the loss of memory associated proteins, and the suppression of glutamatergic transmission are more severe in CB2R-/--Aβ1 - 42 mice than that in WT-Aβ1 - 42 mice. CB2R activation could decrease Aβ1 - 40 and Aβ1 - 42 levels and enhance ACE and IDE levels with its selective agonist JWH133; however, AM630 (CB2R antagonist) abrogates all changes induced by JWH133 in N2a cells with AβPP overexpression. Taken together, our study demonstrated that the deletion of CB2R reduces exogenous Aβ degradation and aggravates the toxicity of Aβ via the reduction of ACE and IDE, which suggests that CB2R is involved in the onset of AD and a potential therapeutic target for AD.

Dual-Task Gait and Alzheimer's Disease Genetic Risk in Cognitively Normal Adults: A Pilot Study. - Whitson, Heather E; Potter, Guy G; Feld, Jody A; Plassman, Brenda L; Reynolds, Kelly; Sloane, Richard; Welsh-Bohmer, Kathleen A (J Alzheimers Dis, 2018)
BACKGROUND: Dual-task paradigms, in which an individual performs tasks separately and then concurrently, often demonstrate that people with neurodegenerative disorders experience more dual-task interference, defined as worse performance in the dual-task condition compared to the single-task condition. OBJECTIVE: To examine how gait-cognition dual-task performance differs between cognitively normal older adults with and without an APOE ɛ4 allele. METHODS: Twenty-nine individuals ages 60 to 72 with normal cognition completed a dual-task protocol in which walking and cognitive tasks (executive function, memory) were performed separately and concurrently. Fourteen participants carried APOE ɛ4 alleles (ɛ3/ɛ4 or ɛ2/ɛ4); fifteen had APOE genotypes (ɛ2/ɛ2, ɛ2/ɛ3, or ɛ3/ɛ3) associated with lower risk of Alzheimer's disease (AD). RESULTS: The two risk groups did not differ by age, sex, race, education, or gait or cognitive measures under single-task conditions. Compared to low risk participants, APOE ɛ4 carriers tended to exhibit greater dual-task interference. Both the memory and executive function tasks resulted in dual-task interference on gait, but effect sizes for a group difference were larger when the cognitive task was executive function. In the dual-task protocol that combined walking and the executive function task, effect sizes for group difference in gait interference were larger (0.62- 0.70) than for cognitive interference (0.45- 0.47). DISCUSSION: Dual-task paradigms may reveal subtle changes in brain function in asymptomatic individuals at heightened risk of AD.

Early Candidate Urine Biomarkers for Detecting Alzheimer's Disease Before Amyloid-β Plaque Deposition in an APP (swe)/PSEN1dE9 Transgenic Mouse Model. - Zhang, Fanshuang; Wei, Jing; Li, Xundou; Ma, Chao; Gao, Youhe (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is an incurable age-associated neurodegenerative disorder that is characterized by irreversible progressive cognitive deficits and extensive brain damage. The identification of candidate biomarkers before amyloid-β plaque deposition occurs is therefore of great importance for the early intervention of AD. Urine, which is not regulated by homeostatic mechanisms, theoretically accumulates changes associated with AD earlier than cerebrospinal fluid and blood. In this study, an APP (swe)/PSEN1dE9 transgenic mouse model was used to identify candidate biomarkers for early AD. Urine samples were collected from 4-, 6-, and 8-month-old transgenic mouse models, and the urinary proteomes were profiled using liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS). The levels of 29 proteins differed significantly between wild type and 4-month-old mice, which had not started to accumulate amyloid-β plaques. Among these proteins, 13 have been associated with the mechanisms of AD, while 9 have been suggested as AD biomarkers. Our results indicated that urine proteins enable detection of AD before amyloid-β plaque deposition, which may present an opportunity for intervention.

Early Intervention with a Multi-Ingredient Dietary Supplement Improves Mood and Spatial Memory in a Triple Transgenic Mouse Model of Alzheimer's Disease. - Hutton, Craig P; Lemon, Jennifer A; Sakic, Boris; Rollo, C David; Boreham, Douglas R; Fahnestock, Margaret; Wojtowicz, J Martin; Becker, Suzanna (J Alzheimers Dis, 2018)
The increasing global burden of Alzheimer's disease (AD) and failure of conventional treatments to stop neurodegeneration necessitates an alternative approach. Evidence of inflammation, mitochondrial dysfunction, and oxidative stress prior to the accumulation of amyloid-β in the prodromal stage of AD (mild cognitive impairment; MCI) suggests that early interventions which counteract these features, such as dietary supplements, may ameliorate the onset of MCI-like behavioral symptoms. We administered a polyphenol-containing multiple ingredient dietary supplement (MDS), or vehicle, to both sexes of triple transgenic (3xTg-AD) mice and wildtype mice for 2 months from 2-4 months of age. We hypothesized that the MDS would preserve spatial learning, which is known to be impaired in untreated 3xTg-AD mice by 4 months of age. Behavioral phenotyping of animals was done at 1-2 and 3-4 months of age using a comprehensive battery of tests. As previously reported in males, both sexes of 3xTg-AD mice exhibited increased anxiety-like behavior at 1-2 months of age, prior to deficits in learning and memory, which did not appear until 3-4 months of age. The MDS did not reduce this anxiety or prevent impairments in novel object recognition (both sexes) or on the water maze probe trial (females only). Strikingly, the MDS specifically prevented 3xTg-AD mice (both sexes) from developing impairments (exhibited by untreated 3xTg-AD controls) in working memory and spatial learning. The MDS also increased sucrose preference, an indicator of hedonic tone. These data show that the MDS can prevent some, but not all, psychopathology in an AD model.

Early Tau Burden Correlates with Higher Rate of Atrophy in Transentorhinal Cortex. - Xie, Long; Das, Sandhitsu R; Wisse, Laura E M; Ittyerah, Ranjit; Yushkevich, Paul A; Wolk, David A (J Alzheimers Dis, 2018)
Neurofibrillary tangle (NFT) pathology is linked to neurodegeneration in the medial temporal lobe (MTL). Using a tailored pipeline, we correlated atrophy rate, as measured from retrospective longitudinal MRI, with NFT burden, measured from 18F-AV-1451 PET, within MTL regions of earliest NFT pathology. In amyloid-β positive but not amyloid-β negative individuals, we found significant correlation between 18F-AV-1451 uptake and atrophy rate that was strongest in the transentorhinal cortex, the first region with NFT pathology. This supports the role of NFTs in driving neurodegeneration and the utility of 18F-AV-1451 PET and structural measurement of transentorhinal cortex in tracking early tau-mediated disease progression.

EEG Theta Power Is an Early Marker of Cognitive Decline in Dementia due to Alzheimer's Disease. - Musaeus, Christian Sandøe; Engedal, Knut; Høgh, Peter; Jelic, Vesna; Mørup, Morten; Naik, Mala; Oeksengaard, Anne-Rita; Snaedal, Jon; Wahlund, Lars-Olof; Waldemar, Gunhild; Andersen, Birgitte Bo (J Alzheimers Dis, 2018)
BACKGROUND: Quantitative EEG (qEEG) power could potentially be used as a diagnostic tool for Alzheimer's disease (AD) and may further our understanding of the pathophysiology. However, the early qEEG power changes of AD are not well understood. OBJECTIVE: To investigate the early changes in qEEG power and the possible correlation with memory function and cerebrospinal fluid biomarkers. In addition, whether qEEG power could discriminate between AD, mild cognitive impairment (MCI), and older healthy controls (HC) at the individual level. METHODS: Standard EEGs from 138 HC, 117 MCI, and 117 AD patients were included from six Nordic memory clinics. All EEGs were recorded consecutively before the diagnosis and were not used for the consensus diagnosis. Absolute and relative power was calculated for both eyes closed and open condition. RESULTS: At group level using relative power, we found significant increases globally in the theta band and decreases in high frequency power in the temporal regions for eyes closed for AD and, to a lesser extent, for MCI compared to HC. Relative theta power was significantly correlated with multiple neuropsychological measures and had the largest correlation coefficient with total tau. At the individual level, the classification rate for AD and HC was 72.9% for relative power with eyes closed. CONCLUSION: Our findings suggest that the increase in relative theta power may be the first change in patients with dementia due to AD. At the individual level, we found a moderate classification rate for AD and HC when using EEGs alone.

The Effect of Chronic Cerebral Hypoperfusion on Amyloid-β Metabolism in a Transgenic Mouse Model of Alzheimer's Disease (PS1V97L). - Yang, Heyun; Hou, Tingting; Wang, Wei; Luo, Yumin; Yan, Feng; Jia, Jianping (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) and cerebrovascular disease often coexist. However, it is difficult to determine how chronic cerebral hypoperfusion affects the metabolism of amyloid-β peptides (Aβ) in a living patient with AD. Thus, we developed an animal model of this condition, using transgenic mice (PS1V97L) and right common carotid artery ligation to create chronic cerebral hypoperfusion. The metabolic processes associated with amyloid-β peptide (Aβ) were observed and evaluated in this PS1V97L plus hypoperfusion model. Compared with control mice, the model revealed significantly upregulated expression of Aβ (including Aβ oligomers), with decreased α-secretase activity and expression and increased β-secretase activity and expression. Furthermore, the model revealed increased mRNA and protein expression of the receptor for advanced glycation end products (RAGE) and decreased mRNA and protein expression of low-density lipoprotein receptor-related protein 1 (LRP-1); both these are Aβ transporters. Moreover, the model revealed decreased activity and expression of neprilysin, which is a peripheral Aβ degrading enzyme. These findings suggest that hypoperfusion may magnify the effect of AD on Aβ metabolism by aggravating its abnormal production, transport, and clearance.

Effect of Education on Alzheimer's Disease-Related Neuroimaging Biomarkers in Healthy Controls, and Participants with Mild Cognitive Impairment and Alzheimer's Disease: A Cross-Sectional Study. - Wada, Masataka; Noda, Yoshihiro; Shinagawa, Shunichiro; Chung, Jun Ku; Sawada, Kyosuke; Ogyu, Kamiyu; Tarumi, Ryosuke; Tsugawa, Sakiko; Miyazaki, Takahiro; Yamagata, Bun; Graff-Guerrero, Ariel; Mimura, Masaru; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Cognitive reserve is the acquired capacity reflecting a functional brain adaptability/flexibility in the context of aging. Educational attainment is thought to be among the most important factors that contribute to cognitive reserve. OBJECTIVE: The aim of this study is to investigate the relationships among duration of education and Alzheimer's disease (AD) related neuroimaging biomarkers such as amyloid-β deposition, glucose metabolism, and brain volumes in each stage of AD. METHODS: We reanalyzed a part of the datasets of the Alzheimer's Disease Neuroimaging Initiative. Participants were between 55 and 90 years of age and diagnosed as one of the following: healthy controls (HC), mild cognitive impairment (MCI), or AD. Multiple regression analyses were conducted to examine the relationships among duration of education and amyloid-β deposition (n = 825), brain metabolism (n = 1,304), and brain volumes (n = 1,606) among three groups using data for 18F-Florbetapir (AV-45) imaging, fludeoxyglucose (FDG) positron emission tomography, and T1-weighted magnetic resonance imaging. RESULTS: Duration of education had no correlations with amyloid-β deposition or brain metabolism in any groups. However, duration of education was positively associated with the total brain volume only in participants with MCI. CONCLUSIONS: Our findings suggest that education may exert a protective effect on total brain volume in the MCI stage but not in HC or AD. Thus, education may play an important role in preventing the onset of dementia through brain reserve in MCI.

Effectiveness of a Personalized Brain-Computer Interface System for Cognitive Training in Healthy Elderly: A Randomized Controlled Trial. - Yeo, Si Ning; Lee, Tih Shih; Sng, Wei Theng; Heo, Min Quan; Bautista, Dianne; Cheung, Yin Bun; Zhang, Hai Hong; Wang, Chuanchu; Chin, Zheng Yang; Feng, Lei; Zhou, Juan; Chong, Mei Sian; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Cognitive training has been demonstrated to improve cognitive performance in older adults. To date, no study has explored personalized training that targets the brain activity of each individual. OBJECTIVE: This is the first large-scale trial that examines the usefulness of personalized neurofeedback cognitive training. METHODS: We conducted a randomized-controlled trial with participants who were 60-80 years old, with Clinical Dementia Rating (CDR) score of 0-0.5, Mini-Mental State Examination (MMSE) score of 24 and above, and with no neuropsychiatric diagnosis. Participants were randomly assigned to the Intervention or Waitlist-Control group. The training system, BRAINMEM, has attention, working memory, and delayed recall game components. The intervention schedule comprised 24 sessions over eight weeks and three monthly booster sessions. The primary outcome was the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) total score after the 24-session training. RESULTS: There were no significant between-subjects differences in overall cognitive performance post-intervention. However, a sex moderation effect (p = 0.014) was present. Men in the intervention group performed better than those in the waitlist group (mean difference, +4.03 (95% CI 0.1 to 8.0), p = 0.046. Among females, however, both waitlist-control and intervention participants improved from baseline, although the between-group difference in improvement did not reach significance. BRAINMEM also received positive appraisal and intervention adherence from the participants. CONCLUSION: A personalized neurofeedback intervention is potentially feasible for use in cognitive training for older males. The sex moderation effect warrants further investigation and highlights the importance of taking sex into account during cognitive training.

The Effectiveness of Psychosocial and Behavioral Interventions for Informal Dementia Caregivers: Meta-Analyses and Meta-Regressions. - Jütten, Linda Helena; Mark, Ruth Elaine; Wicherts, Jelte Michiel; Sitskoorn, Margriet Maria (J Alzheimers Dis, 2018)
BACKGROUND: Many psychosocial and behavioral interventions have been developed for informal dementia caregivers. Because existing meta-analyses only focused on a limited number of interventions and outcomes, how effective these interventions are overall and which interventions components are associated with larger effects has yet to be explored. OBJECTIVE: To provide a comprehensive meta-analysis of the effectiveness of psychosocial and behavioral interventions on burden, depression, anxiety, quality of life, stress, and sense of competence in informal dementia caregivers. In addition, we examined if interventions which utilized more sessions and/or were delivered personally (face-to-face) had larger effect sizes. In exploratory meta-regressions, we examined seven additional moderators. METHODS: The protocol was registered with PROSPERO, number CRD42017062555. We systematically searched the literature to identify controlled trials assessing the effect of psychosocial and behavioral interventions on the six outcome measures, for informal dementia caregivers. We performed six random effects meta-analyses, to assess the pooled effect sizes of the interventions. In addition, we performed separate meta-regressions, for each outcome, for each moderator. RESULTS: The sample consisted of 60 studies. For all outcomes except anxiety, the pooled effects were small and in favor of the intervention group. No moderator was found to systematically predict these effects. There were no indications for publication bias or selection bias based on significance. CONCLUSION: Overall, the interventions yield significant (small) effects, independent of intervention characteristics. Future research should explore options to enhance the effectiveness of interventions aimed at assisting informal caregivers.

Effects of Meditation and Music-Listening on Blood Biomarkers of Cellular Aging and Alzheimer's Disease in Adults with Subjective Cognitive Decline: An Exploratory Randomized Clinical Trial. - Innes, Kim E; Selfe, Terry Kit; Brundage, Kathleen; Montgomery, Caitlin; Wen, Sijin; Kandati, Sahiti; Bowles, Hannah; Khalsa, Dharma Singh; Huysmans, Zenzi (J Alzheimers Dis, 2018)
BACKGROUND: Telomere length (TL), telomerase activity (TA), and plasma amyloid-β (Aβ) levels have emerged as possible predictors of cognitive decline and dementia. OBJECTIVE: To assess the: 1) effects of two 12-week relaxation programs on TL, TA, and Aβ levels in adults with subjective cognitive decline; and 2) relationship of biomarker changes to those in cognitive function, psychosocial status, and quality of life (QOL). METHODS: Participants were randomized to a 12-week Kirtan Kriya meditation (KK) or music listening (ML) program and asked to practice 12 minutes/day. Plasma Aβ(38/40/42) and peripheral blood mononuclear cell TL and TA were measured at baseline and 3 months. Cognition, stress, sleep, mood, and QOL were assessed at baseline, 3 months, and 6 months. RESULTS: Baseline blood samples were available for 53 participants (25 KK, 28 ML). The KK group showed significantly greater increases in Aβ40 than the ML group. TA rose in both groups, although increases were significant only among those with higher practice adherence and lower baseline TA. Changes in both TL and TA varied by their baseline values, with greater increases among participants with values ≤50th percentile (ps-interaction <0.006). Both groups improved in cognitive and psychosocial status (ps ≤0.05), with improvements in stress, mood, and QOL greater in the KK group. Rising Aβ levels were correlated with gains in cognitive function, mood, sleep, and QOL at both 3 and 6 months, associations that were particularly pronounced in the KK group. Increases in TL and TA were also correlated with improvements in certain cognitive and psychosocial measures. CONCLUSION: Practice of simple mind-body therapies may alter plasma Aβ levels, TL, and TA. Biomarker increases were associated with improvements in cognitive function, sleep, mood, and QOL, suggesting potential functional relationships.

Effects of Physical Exercise on Alzheimer's Disease Biomarkers: A Systematic Review of Intervention Studies. - Frederiksen, Kristian Steen; Gjerum, Le; Waldemar, Gunhild; Hasselbalch, Steen Gregers (J Alzheimers Dis, 2018)
Physical exercise may be an important adjunct to pharmacological treatment of Alzheimer's disease (AD). Animal studies indicate that exercise may be disease modifying through several mechanisms including reduction of AD pathology. We carried out a systematic review of intervention studies of physical exercise with hippocampal volume (on MRI), amyloid-β, total tau, phosphorylated tau in cerebrospinal fluid (CSF), 18F-FDG-PET or amyloid PET as outcome measures in healthy subjects, patients with subjective memory complaints, mild cognitive impairment, or AD. We identified a total of 8 studies of which 6 investigated the effects of exercise on hippocampal volume in healthy subjects and 1 on CSF biomarkers and 1 on hippocampal volume in AD, and none investigating the remaining outcome measures or patient groups. Methodological quality of identified studies was generally low. One study found a detrimental effect on hippocampal volume and one found a positive effect, whereas the remaining studies did not find an effect of exercise on outcome measures. The present systematic study identified a relatively small number of studies, which did not support an effect of exercise on hippocampal volume. Methodological issues such small to moderate sample sizes and inadequate ramdomization procedures further limits conclusions. Our findings highlight the difficulties in conducting high quality studies of exercise and further studies are needed before definite conclusions may be reached.
Keywords: Alzheimer Disease; Biomarkers; Exercise; Hippocampus; Humans; Outcome Assessment (Health Care); Physical Therapy Modalities

Elevation of Plasma Amyloid-β Level is More Significant in Early Stage of Cognitive Impairment: A Population-Based Cross-Sectional Study. - Wang, Jin; Qiao, Fan; Shang, Suhang; Li, Pei; Chen, Chen; Dang, Liangjun; Jiang, Yu; Huo, Kang; Deng, Meiying; Wang, Jingyi; Qu, Qiumin (J Alzheimers Dis, 2018)
BACKGROUND: Aggregation and deposition of amyloid-β (Aβ) in the brain is the main pathological change of Alzheimer's disease (AD). Decreased Aβ42 in the cerebrospinal fluid has been confirmed as a biomarker of AD; however, the relationship between plasma Aβ and cognitive impairment is currently unclear. OBJECTIVE: The aim was to explore the relationship between plasma Aβ and cognitive impairment in a cross-sectional study. METHODS: A total of 1,314 subjects (age above 40) from a village in the suburbs of Xi'an, China were enrolled between October 8, 2014 and March 30, 2015. A validated Chinese version of the Mini-Mental State Examination and neuropsychological battery were used to assess cognition. Levels of plasma Aβ42 and Aβ40 were tested using commercial enzyme-linked immunosorbent assay. Relationship of plasma Aβ and cognitive impairment was analyzed using logistic regression analysis. RESULTS: Of the enrolled subjects, 1,180 (89.80%) had normal cognition, 85 (6.47%) had possible cognitive impairment and 49 (3.73%) had probable cognitive impairment. Logistic regression analysis showed that the Aβ42/Aβ40 ratio (OR = 4.042, 95% CI: 1.248-11.098, p = 0.012) and plasma Aβ42 (OR = 1.036, 95% CI: 1.003-1.071, p = 0.031) was higher in the possible cognitive impairment than that in the normal cognition group. Furthermore, the plasma Aβ42/Aβ40 ratio was higher in the possible cognitive impairment group than that in the probable cognitive impairment group (OR = 0.029, 95% CI: 0.002-0.450, p = 0.011). CONCLUSIONS: Levels of plasma Aβ42 and Aβ42/Aβ40 ratio were elevated in patients with possible cognitive impairment, indicating that plasma Aβ42 and Aβ42/Aβ40 ratio increases may be more pronounced in early stage of cognitive impairment.

The End of the Beginning of the Alzheimer's Disease Nightmare: A Devil's Advocate's View. - Wimo, Anders (J Alzheimers Dis, 2018)
Although there have been so many failures in Alzheimer's disease (AD) modifying trials, there are still many compounds in the pipeline and the hope still remains that the entrance of disease-modifying treatment (DMT) for AD will positively and dramatically change the whole situation of AD treatment. However, if DMT does enter the market, it will be the beginning of a great number of challenges and problems. The current infrastructure for diagnostics of early (pre-dementia) AD does not have the capacity to meet the demands and expectations of the population. Neither is there capacity for treatment monitoring and follow-ups. If screening is considered, there will be a great risk for false positive cases and a great number of people who will have to undergo diagnostics. There will be high costs for diagnostics and treatment initially, while potential benefits will occur much later in other sectors than where the payers for treatment are. Although there are great hopes that prevention of cardiovascular risk factors and changes in lifestyle might impact the risk for dementia, there is still no consensus that this is the case. Finally, the relevance of different AD paradigms such as amyloid and tau is still a matter of discussion, particularly regarding the oldest old.

Erythromyeloid-Derived TREM2: A Major Determinant of Alzheimer's Disease Pathology in Down Syndrome. - Raha-Chowdhury, Ruma; Henderson, James W; Raha, Animesh Alexander; Stott, Simon R W; Vuono, Romina; Foscarin, Simona; Wilson, Liam; Annus, Tiina; Fincham, Robert; Allinson, Kieren; Devalia, Vinod; Friedland, Robert P; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Down syndrome (DS; trisomy 21) individuals have a spectrum of hematopoietic and neuronal dysfunctions and by the time they reach the age of 40 years, almost all develop Alzheimer's disease (AD) neuropathology which includes senile plaques and neurofibrillary tangles. Inflammation and innate immunity are key players in AD and DS. Triggering receptor expressed in myeloid cells-2 (TREM2) variants have been identified as risk factors for AD and other neurodegenerative diseases. OBJECTIVE: To investigate the effects of TREM2 and the AD-associated R47H mutation on brain pathology and hematopoietic state in AD and DS. METHODS: We analyzed peripheral blood, bone marrow, and brain tissue from DS, AD, and age-matched control subjects by immunohistochemistry and western blotting. TREM2-related phagocytosis was investigated using a human myeloid cell line. RESULTS: TREM2 protein levels in brain and sera declined with age and disease progression in DS. We observed soluble TREM2 in brain parenchyma that may be carried by a subset of microglia, macrophages, or exosomes. Two DS cases had the AD-associated TREM2-R47H mutation, which manifested a morphologically extreme phenotype of megakaryocytes and erythrocytes in addition to impaired trafficking of TREM2 to the erythroid membrane. TREM2 was shown to be involved in phagocytosis of red blood cells. TREM2 was seen in early and late endosomes. Silencing TREM2 using siRNA in THP1 cells resulted in significant cell death. CONCLUSION: We provide evidence that peripheral TREM2 originating from erythromyeloid cells significantly determines AD neuropathology in DS subjects. Understanding the molecular signaling pathways mediated by TREM2 may reveal novel therapeutic targets.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Cell Line; Disease Progression; Down Syndrome; Exosomes; Female; Humans; Immunity, Innate; Macrophages; Male; Membrane Glycoproteins; Microglia; Middle Aged; Phagocytosis; Polymorphism, Single Nucleotide; Receptors, Immunologic

Evolvability of Amyloidogenic Proteins in Human Brain. - Hashimoto, Makoto; Ho, Gilbert; Sugama, Shuei; Takamatsu, Yoshiki; Shimizu, Yuka; Takenouchi, Takato; Waragai, Masaaki; Masliah, Eliezer (J Alzheimers Dis, 2018)
Currently, the physiological roles of amyloidogenic proteins (APs) in human brain, such as amyloid-β and α-synuclein, are elusive. Given that many APs arose by gene duplication and have been resistant against the pressures of natural selection, APs may be associated with some functions that are advantageous for survival of offspring. Nonetheless, evolvability is the sole physiological quality of APs that has been characterized in microorganisms such as yeast. Since yeast and human brain may share similar strategies in coping with diverse range of critical environmental stresses, the objective of this paper was to discuss the potential role of evolvability of APs in aging-associated neurodegenerative disorders, including Alzheimer's disease and Parkinson's disease. Given the heterogeneity of APs in terms of structure and cytotoxicity, it is argued that APs might be involved in preconditioning against diverse stresses in human brain. It is further speculated that these stress-related APs, most likely protofibrillar forms, might be transmitted to offspring via the germline, conferring preconditioning against forthcoming stresses. Thus, APs might represent a vehicle for the inheritance of the acquired characteristics against environmental stresses. Curiously, such a characteristic of APs is reminiscent of Charles Darwin's 'gemmules', imagined molecules of heritability described in his pangenesis theory. We propose that evolvability might be a physiological function of APs during the reproductive stage and neurodegenerative diseases could be a by-product effect manifested later in aging. Collectively, our evolvability hypothesis may play a complementary role in the pathophysiology of APs with the conventional amyloid cascade hypothesis.

Exposure to Strong Anticholinergic Medications and Dementia-Related Neuropathology in a Community-Based Autopsy Cohort. - Gray, Shelly L; Anderson, Melissa L; Hanlon, Joseph T; Dublin, Sascha; Walker, Rod L; Hubbard, Rebecca A; Yu, Onchee; Montine, Thomas J; Crane, Paul K; Sonnen, Josh A; Keene, C Dirk; Larson, Eric B (J Alzheimers Dis, 2018)
BACKGROUND: Anticholinergic medication exposure has been associated with increased risk for dementia. No study has examined the association between anticholinergic medication use and neuropathologic lesions in a community-based sample. OBJECTIVE: To examine the relationship between anticholinergic exposure and dementia-related neuropathologic changes. METHODS: Within a community-based autopsy cohort (N = 420), we ascertained use of anticholinergic medications over a 10-year period from automated pharmacy data and calculated total standardized daily doses (TSDD). We used modified Poisson regression to calculate adjusted relative risks (RRs) and 95% confidence intervals (CIs) for the association between anticholinergic exposure and dementia-associated neuropathology. Inverse probability weighting was used to account for selection into the autopsy cohort. RESULTS: Heavy anticholinergic exposure (≥1,096 TSDD) was not associated with greater neuropathologic changes of Alzheimer's disease; the adjusted RRs for heavy use of anticholinergics (≥1,096 TSDD) compared to no use were 1.22 (95% CI 0.81-1.88) for neuritic plaque scores and 0.89 (0.47-1.66) for extent of neurofibrillary degeneration. Moderate (91-1,095 TSDD) and heavy use of anticholinergics was associated with a significantly lower cerebral microinfarct burden compared with no use with adjusted RRs of 0.44 (0.21-0.89) and 0.24 (0.09-0.62), respectively. Anticholinergic exposure was not associated with macroscopic infarcts or atherosclerosis. CONCLUSIONS: Use of anticholinergic medications is not associated with Alzheimer's disease-related neuropathologic changes but is associated with lower cerebral microinfarct burden. Further research into biological mechanisms underlying the anticholinergic-dementia link is warranteds.

FDDNP-PET Tau Brain Protein Binding Patterns in Military Personnel with Suspected Chronic Traumatic Encephalopathy1. - Chen, Stephen T; Siddarth, Prabha; Merrill, David A; Martinez, Jacqueline; D Emerson, Natacha; Liu, Jie; Wong, Koon-Pong; Satyamurthy, Nagichettiar; Giza, Christopher C; Huang, Sung-Cheng; Fitzsimmons, Robert P; Bailes, Julian; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Our group has shown that in vivo tau brain binding patterns from FDDNP-PET scans in retired professional football players with suspected chronic traumatic encephalopathy differ from those of tau and amyloid aggregate binding observed in Alzheimer's disease (AD) patients and cognitively-intact controls. OBJECTIVE: To compare these findings with those from military personnel with histories of mild traumatic brain injury(mTBI). METHODS: FDDNP-PET brain scans were compared among 7 military personnel and 15 retired players with mTBI histories and cognitive and/or mood symptoms, 24 AD patients, and 28 cognitively-intact controls. Nonparametric ANCOVAs with Tukey-Kramer adjusted post-hoc comparisons were used to test for significant differences in regional FDDNP binding among subject groups. RESULTS: FDDNP brain binding was higher in military personnel compared to controls in the amygdala, midbrain, medial thalamus, pons, frontal and anterior and posterior cingulate regions (p < 0.01-0.0001). Binding patterns in the military personnel were similar to those of the players except for the amygdala and striatum (binding higher in players; p = 0.02-0.003). Compared with the AD group, the military personnel showed higher binding in the midbrain (p = 0.0008) and pons (p = 0.002) and lower binding in the medial temporal, lateral temporal, and parietal regions (all p = 0.02). CONCLUSION: This first study of in vivo tau and amyloid brain signals in military personnel with histories of mTBI shows binding patterns similar to those of retired football players and distinct from the binding patterns in AD and normal aging, suggesting the potential value of FDDNP-PET for early detection and treatment monitoring in varied at-risk populations.

GDF11 Rejuvenates Cerebrovascular Structure and Function in an Animal Model of Alzheimer's Disease. - Zhang, Wei; Guo, Yi; Li, Bo; Zhang, Qi; Liu, Jian-Hui; Gu, Guo-Jun; Wang, Jin-Hong; Bao, Rui-Kang; Chen, Yu-Jie; Xu, Jian-Rong (J Alzheimers Dis, 2018)
Cerebral amyloid angiopathy (CAA) is present in up to 90% of patients with Alzheimer's disease (AD), and may interact with classical neuropathology to exacerbate cognitive decline. Since growth differentiation factor 11 (GDF11) can activate vascular remodeling, we tested its effects on cognitive function and neuroinflammatory changes of AD model mice. We intravenously administered GDF11 or vehicle daily to 12-month-old transgenic mice overexpressing the amyloid-β protein precursor (AβPP)/PS1). Cognitive function was monitored using the Morris water maze, and after conclusion of the treatment, we assessed the morphology and presence of inflammatory markers in the cerebral vasculature. Subchronic treatment of adult AβPP/PS1 mice with GDF11 rescued cognitive function and ameliorated cerebrovascular function. In particular, the de novo genesis of small blood vessels and the expression of vascular-related proteins were significantly higher than in the vehicle-treated AβPP/PS1 mice, whereas the expressions of the inflammatory markers Iba-1 and GFAP significantly decreased in proportion to the lower ratio of two forms of amyloid-β (Aβ40/42). Daily intravenous treatment with GDF11-injection can rejuvenate respects of cognition and cerebrovascular changes in AD mice.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Behavior, Animal; Cerebral Amyloid Angiopathy; Disease Models, Animal; Growth Differentiation Factors; Maze Learning; Mice; Mice, Transgenic; Prefrontal Cortex; Presenilin-1

Gene Transfer Induced Hypercholesterolemia in Amyloid Mice. - Grames, Mychal S; Dayton, Robert D; Lu, Xiaohong; Schilke, Robert M; Alexander, J Steven; Orr, A Wayne; Barmada, Sami J; Woolard, Matthew D; Klein, Ronald L (J Alzheimers Dis, 2018)
A risk factor for cardiovascular disease (CVD), mutant PCSK9, was expressed in APP/PS1 mice to study the CVD-Alzheimer's disease inter-relationship. Cholesterol levels were elevated by 5-6-fold from 3 to 13 weeks after PCSK9 gene transfer. We tested whether hypercholesterolemia would increase amyloid-β plaques at a relatively early stage of plaque deposition. Plaque burden was increased in the hippocampus of PCSK9 treated mice though the increase was modest compared to the large elevation in cholesterol. Elevating cholesterol via gene transfer could be valuable in a variety of disease models compared to making crosses with germ-line transgenic mouse models of CVD.

General Practice Clinical Data Help Identify Dementia Hotspots: A Novel Geospatial Analysis Approach. - Bagheri, Nasser; Wangdi, Kinley; Cherbuin, Nicolas; Anstey, Kaarin J (J Alzheimers Dis, 2018)
We have a poor understanding of whether dementia clusters geographically, how this occurs, and how dementia may relate to socio-demographic factors. To shed light on these important questions, this study aimed to compute a dementia risk score for individuals to assess spatial variation of dementia risk, identify significant clusters (hotspots), and explore their association with socioeconomic status. We used clinical records from 16 general practices (468 Statistical Area level 1 s, N = 14,746) from the city of west Adelaide, Australia for the duration of 1 January 2012 to 31 December 2014. Dementia risk was estimated using The Australian National University-Alzheimer's Disease Risk Index. Hotspot analyses were applied to examine potential clusters in dementia risk at small area level. Significant hotspots were observed in eastern and southern areas while coldspots were observed in the western area within the study perimeter. Additionally, significant hotspots were observed in low socio-economic communities. We found dementia risk scores increased with age, sex (female), high cholesterol, no physical activity, living alone (widow, divorced, separated, or never married), and co-morbidities such as diabetes and depression. Similarly, smoking was associated with a lower dementia risk score. The identification of dementia risk clusters may provide insight into possible geographical variations in risk factors for dementia and quantify these risks at the community level. As such, this research may enable policy makers to tailor early prevention strategies to the correct individuals within their precise locations.
Keywords: Age Factors; Aged; Aged, 80 and over; Australia; Dementia; Demography; Epidemiological Monitoring; Female; General Practice; Humans; Male; Retrospective Studies; Sex Factors; Topography, Medical

Generation and Partial Characterization of Rabbit Monoclonal Antibody to Pyroglutamate Amyloid-β3-42 (pE3-Aβ). - Mehta, Pankaj D; Patrick, Bruce A; Barshatzky, Marc; Mehta, Sangita P; Frackowiak, Janusz; Mazur-Kolecka, Bozena; Wegiel, Jerzy; Wisniewski, Thomas; Miller, David L (J Alzheimers Dis, 2018)
N-terminally truncated pyroglutamate amyloid-β (Aβ) peptide starting at position 3 represents a significant fraction of Aβ peptides (pE3-Aβ) in amyloid plaques of postmortem brains from patients with Alzheimer's disease (AD) and older persons with Down syndrome (DS). Studies in transgenic mouse models of AD also showed that pE3-Aβ is a major component of plaques, and mouse monoclonal antibody to pE3-Aβ appears to be a desirable therapeutic agent for AD. Since small peptides do not typically elicit a good immune response in mice, but do so favorably in rabbits, our aims were to generate and partially characterize a rabbit monoclonal antibody (RabmAb) to pE3-Aβ. The generated RabmAb was found to be specific for pE3-Aβ, since it showed no reactivity with Aβ16, Aβ40, Aβ42, Aβ3-11, and pE11-17 Aβ peptides in an enzyme linked immunosorbent assay (ELISA). The isotype of the antibody was found to be IgG class. The antibody possesses high affinity to pE3-Aβ with dissociation constant (KD) for the antibody of 1 nM. The epitope of the antibody lies within the sequence of pE3-FRHD. In dot blotting, the optimal detection of pE3-Aβ was at an antibody concentration of 0.5 μg/ml. The threshold of pE3-Aβ detection was 2 fmol. The antibody was sensitive enough to detect 10 pg/ml of pE3-Aβ in sandwich ELISA. pE3-Aβ was detected in AD and DS brain extracts in ELISA and immunoblotting. Immunohistological studies showed immunolabeling of plaques and blood vessels in brains from patients with AD, and DS showing AD pathology. Thus, the antibody can be widely applied in AD and DS research, and therapeutic applications.

Genotyping of the Alzheimer's Disease Genome-Wide Association Study Index Single Nucleotide Polymorphisms in the Brains for Dementia Research Cohort. - Brookes, Keeley J; McConnell, George; Williams, Kirsty; Chaudhury, Sultan; Madhan, Gaganjit; Patel, Tulsi; Turley, Christopher; Guetta-Baranes, Tamar; Bras, Jose; Guerreiro, Rita; Hardy, John; Francis, Paul T; et al. (J Alzheimers Dis, 2018)
The Brains for Dementia Research project is a recently established longitudinal cohort which aims to provide brain tissue for research purposes from neuropathologically defined samples. Here we present the findings from our analysis on the 19 established GWAS index SNPs for Alzheimer's disease, in order to demonstrate if the BDR sample also displays association to these variants. A highly significant association of the APOEɛ4 allele was identified (p = 3.99×10-12). Association tests for the 19 GWAS SNPs found that although no SNPs survive multiple testing, nominal significant findings were detected and concordance with the Lambert et al. GWAS meta-analysis was observed.

Growth Hormone-Releasing Hormone Modulation of Neuronal Exosome Biomarkers in Mild Cognitive Impairment. - Winston, Charisse N; Goetzl, Edward J; Baker, Laura D; Vitiello, Michael V; Rissman, Robert A (J Alzheimers Dis, 2018)
Age-related changes in cognition are linked to decreased expression of somatotropins, GHRH and IGF-1. Mild cognitive impairment (MCI) and Alzheimer's disease (AD) are heterogeneous conditions. The loss of GHRH signaling in the brain may be mechanistically involved in AD pathogenesis. The consequent need to identify AD at an early and perhaps more treatable stage has fueled research into blood-based, exosome biomarkers. Plasma exosomes from participants enrolled in a randomized, double-blind, placebo-controlled 20-week trial of GHRH administration, were isolated, precipitated, and enriched by immuno-absorption with anti-L1CAM antibody (neural adhesion protein) from adults with MCI and age-matched, cognitively normal controls (CNC). Extracted protein cargo from neuronally-derived exosomes (NDEs) were assessed by ELISAs for protein levels implicated in AD neuropathology and for synaptic proteins altered by AD. Plasma NDE concentrations of Aβ1-42 were significantly increased while plasma NDE concentrations of NRGN, synaptophysin, synaptotagmin, and synaptopodin were significantly decreased in patients with MCI, independent of GHRH treatment. Plasma NDE concentrations of ptau-S396 and GAP43 were not affected by cognitive status (CNC versus MCI) or by GHRH treatment. Aβ1-42, neurogranin (NRGN), synaptophysin, synaptotagmin, and synaptopodin demonstrated the highest diagnostic accuracy for distinguishing between CNC and MCI patients, while synaptophysin and synaptotagmin demonstrated moderate accuracy in distinguishing between placebo-treated and GHRH-treated, MCI patients.

Gut Microbiome is Altered in Patients with Alzheimer's Disease. - Zhuang, Zhen-Qian; Shen, Lin-Lin; Li, Wei-Wei; Fu, Xue; Zeng, Fan; Gui, Li; Lü, Yang; Cai, Min; Zhu, Chi; Tan, Yin-Ling; Zheng, Peng; Li, Hui-Yun; et al. (J Alzheimers Dis, 2018)
Previous studies suggest that gut microbiota is associated with neuropsychiatric disorders, such as Parkinson's disease, amyotrophic lateral sclerosis, and depression. However, whether the composition and diversity of gut microbiota is altered in patients with Alzheimer's disease (AD) remain largely unknown. In the present study, we collected fecal samples from 43 AD patients and 43 age- and gender-matched cognitively normal controls. 16S ribosomal RNA sequencing technique was used to analyze the microbiota composition in feces. The composition of gut microbiota was different between the two groups. Several bacteria taxa in AD patients were different from those in controls at taxonomic levels, such as Bacteroides, Actinobacteria, Ruminococcus, Lachnospiraceae, and Selenomonadales. Our findings suggest that gut microbiota is altered in AD patients and may be involved in the pathogenesis of AD.

Harpagoside Rescues the Memory Impairments in Chronic Cerebral Hypoperfusion Rats by Inhibiting PTEN Activity. - Chen, Chen; Zhang, Haifeng; Xu, Hongliang; Xue, Rui; Zheng, Yake; Wu, Tianwen; Lian, Yajun (J Alzheimers Dis, 2018)
Vascular dementia (VaD) is the second most common dementia worldwide. Unlike Alzheimer's disease, VaD does not yet have effective therapeutic drugs. Harpagoside is the most important component extracted from Harpagophytum procumbens, a traditional Chinese medicine that has been widely used. The neuroprotective effects of harpagoside have been studied in Aβ- and MPTP-induced neurotoxicity. However, whether harpagoside is protective against VaD is not clear. In this study, with the use of chronic cerebral hypoperfusion rats, a well-known VaD model, we demonstrated that chronic administration (two months) of harpagoside was able to restore both the spatial learning/memory and fear memory impairments. Importantly, the protective effects of harpagoside were not due to alterations in the physiological conditions, metabolic parameters, or locomotor abilities of the rats. Meanwhile, we found that harpagoside suppressed the overactivation of PTEN induced by CCH by enhancing PTEN phosphorylation. Furthermore, harpagoside elevated the activity of Akt and inhibited the activity of GSK-3β, downstream effectors of PTEN. Overall, our study suggested that harpagoside treatment might be a potential therapeutic drug targeting the cognitive impairments of VaD.

Heme Oxygenase 1 Induces Tau Oligomer Formation and Synapse Aberrations in Hippocampal Neurons. - Si, Zizhen; Wang, Xidi; Zhang, Zhujun; Wang, Jinxin; Li, Jihong; Li, Jing; Li, Ling; Li, Yuanxin; Peng, Yahui; Sun, Chongran; Hui, Yang; Gao, Xu (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by behavioral changes and cognitive decline. Recent evidence suggests that it is the soluble forms of tau oligomers (Tau-O) and Aβ oligomers (oAβ) rather than the well-studied insoluble protein aggregates that possess the neurotoxicity, infectivity, and amplification underlying disease progression. Heme oxygenase 1 (HO-1), an inducible enzyme upregulated in the cortex and hippocampus of AD brains, was reported to damage neural structures and disrupt brain function, suggesting possible contributions to Tau-O-mediated neurodegeneration. In this study, we focused on the effects of HO-1 on Tau-O formation. In hippocampus of HO-1-overexpressing transgenic mice and neural 2a (N2a) cells, Tau-O was co-localized with HO-1 as visualized by immunofluorescence staining. Furthermore, primary cultured hippocampal neurons from HO-1 transgenic mice showed elevated Tau-O and concomitant reductions in spine density and length as well as dendritic length, diameter, and arborization. Blocking Tau-O formation by isoprenaline reversed these HO-1-induced morphological changes. These results indicated that HO-1 contributes to Tau-O formation and ensuing synaptic damage. Thus, HO-1 is a promising target for AD drug development.

Hippocampal Stratum Radiatum, Lacunosum, and Moleculare Sparing in Mild Cognitive Impairment. - Su, Li; Hayes, Lawrence; Soteriades, Soteris; Williams, Guy; Brain, Susannah A E; Firbank, Michael J; Longoni, Giulia; Arnold, Robert J; Rowe, James B; O'Brien, John T (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is associated with atrophy in entorhinal cortex (ERC), the hippocampus, and its subfields Cornu Ammonis 1 (CA1) and subiculum, which predict conversion from mild cognitive impairment (MCI) to clinical AD. The stratum radiatum, lacunosum, and moleculare (SRLM) are also important gateways involving ERC and CA1, which are affected by early AD pathology. OBJECTIVE: To assess whether the SRLM is affected in MCI and AD. METHODS: In this proof-of-concept study, 27 controls, 13 subjects with AD, and 22 with MCI underwent 3T MRI. T1 maps were used for whole-hippocampal volumetry, T2 maps were segmented for hippocampal subfield areas, entorhinal cortex and subiculum thickness, and evaluated for SRLM integrity. RESULTS: Significant CA1 atrophy and subiculum thinning were found in both AD and MCI compared to similarly aged controls. However, SRLM integrity was only significantly reduced in AD but not in MCI compared to controls. There were no significant differences in other hippocampal subfields (CA2, CA3/dentate gyrus) or ERC thickness between the groups. Finally, CA1 and CA3/DG areas and SRLM clarity were correlated with clinical and cognitive measurements of disease severity. CONCLUSION: Although this study was cross sectional, it suggests a progression of specific subfield changes from MCI to established AD that is associated with the reduced integrity of SRLM, which may reflect more widespread hippocampal involvement as the disease progresses and the relative preservation of SRLM in MCI. These results provide new MRI biomarkers for disease staging and understanding of the neurobiology in AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Atrophy; Cognitive Dysfunction; Disease Progression; Entorhinal Cortex; Female; Hippocampus; Humans; Imaging, Three-Dimensional; Magnetic Resonance Imaging; Male; Middle Aged; Reproducibility of Results

Hippocampal Subfield Volumetry: Differential Pattern of Atrophy in Different Forms of Genetic Frontotemporal Dementia. - Bocchetta, Martina; Iglesias, Juan Eugenio; Scelsi, Marzia A; Cash, David M; Cardoso, M Jorge; Modat, Marc; Altmann, Andre; Ourselin, Sebastien; Warren, Jason D; Rohrer, Jonathan D (J Alzheimers Dis, 2018)
BACKGROUND: Frontotemporal dementia (FTD) is a heterogeneous neurodegenerative disorder, with a strong genetic component. Previous research has shown that medial temporal lobe atrophy is a common feature of FTD. However, no study has so far investigated the differential vulnerability of the hippocampal subfields in FTD. OBJECTIVES: We aimed to investigate hippocampal subfield volumes in genetic FTD. METHODS: We in6/2/2018vestigated hippocampal subfield volumes in a cohort of 75 patients with genetic FTD (age: mean (standard deviation) 59.3 (7.7) years; disease duration: 5.1 (3.4) years; 29 with MAPT, 28 with C9orf72, and 18 with GRN mutations) compared with 97 age-matched controls (age: 62.1 (11.1) years). We performed a segmentation of their volumetric T1-weighted MRI scans to extract hippocampal subfields volumes. Left and right volumes were summed and corrected for total intracranial volumes. RESULTS: All three groups had smaller hippocampi than controls. The MAPT group had the most atrophic hippocampi, with the subfields showing the largest difference from controls being CA1-4 (24-27%, p < 0.0005). For C9orf72, the CA4, CA1, and dentate gyrus regions (8-11%, p < 0.0005), and for GRN the presubiculum and subiculum (10-14%, p < 0.0005) showed the largest differences from controls. CONCLUSIONS: The hippocampus was affected in all mutation types but a different pattern of subfield involvement was found in the three genetic groups, consistent with differential cortical-subcortical network vulnerability.

Homocysteine and Cerebral Atrophy: The Epidemiology of Dementia in Singapore Study. - Tan, Bryce; Venketasubramanian, Narayanaswamy; Vrooman, Henri; Cheng, Ching-Yu; Wong, Tien Yin; Ikram, Mohammad Kamran; Chen, Christopher; Hilal, Saima (J Alzheimers Dis, 2018)
BACKGROUND: Plasma homocysteine levels are increasingly studied as a potential risk factor for dementia. Elevated homocysteine levels have been linked with gray and white matter volume reduction among individuals with mild cognitive impairment and Alzheimer's disease. However, the effects of homocysteine on brain changes in preclinical stages of dementia remain unexplored. OBJECTIVE: To examine the association of elevated homocysteine levels with markers of neurodegeneration, i.e., white and gray matter volume in an elderly population. METHODS: The study included 768 participants (mean age: 69.6±6.5 years, 51.3% women) from the Epidemiology of Dementia In Singapore study. Participants underwent a brain MRI scan and blood tests. Serum homocysteine was measured using competitive immunoassay. Cortical thickness and subcortical structural volume were quantified using FreeSurfer whereas white matter volume was quantified using a previous validated method. RESULTS: Higher homocysteine levels were significantly associated with decreased global white matter volume [mean difference (β) in volume (ml) per micromole per liter (μmol/l) increase in homocysteine levels: - 0.555, 95% Confidence Interval (CI): - 0.873; - 0.237], decreased parietal cortical thickness [β in thickness (μm) per μmol/l increase in homocysteine levels:- 1.429, 95% CI: - 2.781; - 0.077], and smaller volumes of the thalamus [β: - 0.017, 95% CI: - 0.026; - 0.008], brainstem [β: - 0.037, 95% CI: - 0.058; - 0.016], and accumbens [β: - 0.004, 95% CI: - 0.006; - 0.002]. CONCLUSION: Higher homocysteine levels were associated with cerebral atrophy. Further studies are required to assess whether lowering plasma homocysteine levels may prevent neurodegenerative changes or delay progression of clinical symptoms before the development of dementia.
Keywords: Aged; Atrophy; Biomarkers; Dementia; Female; Homocysteine; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Organ Size; Risk Factors; Singapore; White Matter

Honokiol Alleviates Cognitive Deficits of Alzheimer's Disease (PS1V97L) Transgenic Mice by Activating Mitochondrial SIRT3. - Li, Haitao; Jia, Jianping; Wang, Wei; Hou, Tingting; Tian, Yuanruhua; Wu, Qiaoqi; Xu, Lingzhi; Wei, Yiping; Wang, Xiu (J Alzheimers Dis, 2018)
Accumulating evidence has demonstrated that mitochondrial dysfunction is a prominent early event in the progression of Alzheimer's disease (AD). Whether protecting mitochondrial function can reduce amyloid-β oligomer (AβO)-induced neurotoxicity in PS1V97L transgenic mice remains unknown. In this study, we examined the possible protective effects of honokiol (HKL) on mitochondrial dysfunction induced by AβOs in neurons, and cognitive function in AD PS1V97Ltransgenic mice. We determined that HKL increased mitochondrial sirtuin 3 (SIRT3) expression levels and activity, which in turn markedly improved ATP production and weakened mitochondrial reactive oxygen species production. We demonstrated that the enhanced energy metabolism and attenuated oxidative stress of HKL restores AβO-mediated mitochondrial dysfunction in vitro and in vivo. Consequently, memory deficits in the PS1V97L transgenic mice were rescued by HKL in the early stages. These results suggest that HKL has therapeutic potential for delaying the onset of AD symptoms by alleviating mitochondrial impairment and increasing hyperactivation of SIRT3 in the pathogenesis of preclinical AD.

How Does Utilization of Health Care Services Change in People with Dementia Served by Dementia Care Networks? Results of the Longitudinal, Observational DemNet-D-Study. - Thyrian, Jochen René; Michalowsky, Bernhard; Hertel, Johannes; Wübbeler, Markus; Gräske, Johannes; Holle, Bernhard; Schäfer-Walkmann, Susanne; Wolf-Ostermann, Karin; Hoffmann, Wolfgang (J Alzheimers Dis, 2018)
BACKGROUND: There is no common definition for the Dementia Care Network (DCN). They are heterogeneous and there is no general, longitudinal evidence for the effects of DCN. OBJECTIVE: We describe changes in utilization of health services by people served by dementia care networks in Germany and factors associated with those changes over time. METHODS: Primary data was assessed in 560 people with dementia (PwD) and their caregivers supported by DCN in Germany; sociodemographic and clinical variables, utilization of services; DCN were characterized according to governance. The design: observational study with face-to-face interviews at two time points over a period of one year. Data was assessed via semi-structured interviews at the participants' homes. RESULTS: Utilization of health services in this study is consistently higher than reported for the general population and does not significantly change over time. The strongest predictor of utilization of any service after one year was the use of this service at baseline (OR from 3.23 to 44.16). Higher activities of daily functioning increased the chances to utilize specialist physicians (OR = 1.32; 95% -CI: 1.08-1.63) or occupational therapy (OR = 1.24; 95% -CI: 1.02-1.50) significantly. Being a female decreased chances to utilize specialist physicians (OR = 0.57; 95% -CI: 0.37-0.87) and increased the chances to utilize no services (OR = 2.08; 95% -CI: 1.29-3.33). CONCLUSION: While health care acknowledges the importance and benefits of dementia care networks (i.e., in Germany, the results were considered in new German legislation (SGB XI)), further research is needed to define this kind of service delivery to facilitate comparison as well as promote evidence-based implementation.

Impact of a Virtual Dementia Experience on Medical and Pharmacy Students' Knowledge and Attitudes Toward People with Dementia: A Controlled Study. - Gilmartin-Thomas, Julia F-M; McNeil, John; Powell, Anne; Malone, Daniel T; Wolfe, Rory; Larson, Ian C; O'Reilly, Claire L; Kirkpatrick, Carl M; Kipen, Eva; Petrovich, Tanya; Bell, J Simon (J Alzheimers Dis, 2018)
BACKGROUND: Clinical practice guidelines for dementia highlight the importance of providing patient-centered care. This can be achieved by improving health professionals' attitudes and knowledge toward people with dementia. OBJECTIVE: Quantitatively evaluate the impact of a virtual dementia experience on medical and pharmacy students' knowledge and attitudes toward people with dementia. METHODS: A non-randomized controlled study from September-October 2016. The intervention group received a 1.5-hour multisensory, virtual simulation of light, sound, color, and visual content to experience the cognitive and perceptual difficulties faced by people with dementia. Controls participated in the standard curriculum only. All students were invited to complete the 20-item Dementia Attitudes Scale (DAS) pre- and post-intervention. RESULTS: A total of 278 students (n = 64 medical, n = 214 pharmacy) were analyzed (n = 80 intervention, n = 198 control). The majority of students were female (n = 184, 66.2%), with an average age of 22.5 years. The intervention improved the DAS total score and subdomains of comfort and knowledge (p < 0.001). CONCLUSION: The intervention had a positive impact on medical and pharmacy students' knowledge and attitudes toward people with dementia.
Keywords: Australia; Curriculum; Dementia; Female; Health Knowledge, Attitudes, Practice; Humans; Male; Students, Medical; Students, Pharmacy; Virtual Reality; Young Adult

The Impact of Creative Arts in Alzheimer's Disease and Dementia Public Health Education. - Burns, Nicole C; Watts, Amber; Perales, Jaime; Montgomery, Robert Neal; Morris, Jill K; Mahnken, Jonathan D; Lowther, Johnna; Vidoni, Eric D (J Alzheimers Dis, 2018)
Previous research involving dramatic performances about Alzheimer's disease and dementia perception have targeted health care workers or caretakers. We examined the influence of a theater performance on the emotional affect of a general audience to determine the utility of this type of theater in large-scale public health education efforts. Our study included 147 participants that attended a self-revelatory theater performance based on the social/relationship experiences of those with dementia and those who care for them. This type of theater engages the audience and actors in a dual transformative process, supporting the emotional growth of all involved. Participants completed pre- and post-performance questionnaires regarding their beliefs and feelings surrounding the topic of dementia and the importance of the Arts for educating on issues surrounding dementia care. We tested for change in emotional affect pre- and post-performance using sensitivity and center of gravity statistical analyses. We found a significant change in emotional affect from an initial strong negative affect to slightly more positive/relaxed view after viewing the performance. Findings support self-revelatory theater as a resource to destigmatize preconceived notions of dementia. Large-scale community health education efforts could benefit from using this style of theater to elicit a change in audience perception of disease realities.

Impact of Untimely Access to Formal Care on Costs and Quality of Life in Community Dwelling People with Dementia. - Janssen, Niels; Handels, Ron L; Sköldunger, Anders; Woods, Bob; Jelley, Hannah; Edwards, Rhiannon Tudor; Orrell, Martin; Selbæk, Geir; Røsvik, Janne; Gonçalves-Pereira, Manuel; Marques, Maria J; Zanetti, Orazio; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Access to formal care is not always timely and a better understanding on the impact of untimely access is needed. OBJECTIVE: To examine, from a societal perspective, the impact of untimely access to formal care in terms of total costs and quality of life over one year in community dwelling people with dementia. METHODS: Within the Actifcare study, needs, resource use, and quality of life were observed for one year in a cohort of 451 community dwelling people with dementia in 8 European countries. Untimely access to care was operationalized as having at least one unmet need for care identified by the Camberwell Assessment of Need for the Elderly (CANE) instrument. Two regression models were built for both total costs and quality of life measured by the EQ-5D-5L, one using sum of unmet needs and one using a predefined selection of need items. RESULTS: Unmet needs were not associated with higher total costs but they were associated with a lower quality of life of people with dementia. Of all CANE items, only an unmet need for "company" was significantly related to lower total costs. CONCLUSION: Total costs did not seem to differ between participants with unmet and met needs. Only few associations between specific unmet needs and costs and quality of life were found. Furthermore, quality of life of people with dementia decreases when multiple unmet needs are experienced, indicating that assessing and meeting needs is important to improve quality of life.

In Vitro Potency and Preclinical Pharmacokinetic Comparison of All-D-Enantiomeric Peptides Developed for the Treatment of Alzheimer's Disease. - Schartmann, Elena; Schemmert, Sarah; Niemietz, Nicole; Honold, Dominik; Ziehm, Tamar; Tusche, Markus; Elfgen, Anne; Gering, Ian; Brener, Oleksandr; Shah, Nadim Joni; Langen, Karl-Josef; Kutzsche, Janine; et al. (J Alzheimers Dis, 2018)
Diffusible amyloid-β (Aβ) oligomers are currently presumed to be the most cytotoxic Aβ assembly and held responsible to trigger the pathogenesis of Alzheimer's disease (AD). Thus, Aβ oligomers are a prominent target in AD drug development. Previously, we reported on our solely D-enantiomeric peptide D3 and its derivatives as AD drug candidates. Here, we compare one of the most promising D3 derivatives, ANK6, with its tandem version (tANK6), and its head-to-tail cyclized isoform (cANK6r). In vitro tests investigating the D-peptides' potencies to inhibit Aβ aggregation, eliminate Aβ oligomers, and reduce Aβ-induced cytotoxicity revealed that all three D-peptides efficiently target Aβ. Subsequent preclinical pharmacokinetic studies of the three all-D-peptides in wildtype mice showed promising blood-brain barrier permeability with cANK6r yielding the highest levels in brain. The peptides' potencies to lower Aβ toxicity and their remarkable brain/plasma ratios make them promising AD drug candidates.

Increased Foxo3a Nuclear Translocation and Activity is an Early Neuronal Response to βγ-Secretase-Mediated Processing of the Amyloid-β Protein Precursor: Utility of an AβPP-GAL4 Reporter Assay. - Law, Bernard M; Guest, Amy L; Pullen, Matthew W J; Perkinton, Michael S; Williams, Robert J (J Alzheimers Dis, 2018)
Sequential cleavage of the amyloid-β protein precursor (AβPP) by BACE1 (β-secretase) followed by theγ-secretase complex, is strongly implicated in Alzheimer's disease (AD) but the initial cellular responses to these cleavage events are not fully defined. β-secretase-mediated AβPP processing yields an extracellular domain (sAβPPβ) and a C-terminal fragment of AβPP of 99 amino acids (C99). Subsequent cleavage by γ-secretase produces amyloid-β (Aβ) and an AβPP intracellular domain (AICD). A cellular screen based on the generation of AICD from an AβPP-Gal4 fusion protein was adapted by introducing familial AD (FAD) mutations into the AβPP sequence and linking the assay to Gal4-UAS driven luciferase and GFP expression, to identify responses immediately downstream of AβPP processing in neurons with a focus on the transcription factor Foxo3a which has been implicated in neurodegeneration. The K670N/M671L, E682K, E693G, and V717I FAD mutations and the A673T protective mutation, were introduced into the AβPP sequence by site directed mutagenesis. When expressed in mouse cortical neurons, AβPP-Gal4-UAS driven luciferase and GFP expression was substantially reduced by γ-secretase inhibitors, lowered by β-secretase inhibitors, and enhanced by α-secretase inhibitors suggesting that AICD is a product of the βγ-secretase pathway. AβPP-Gal4-UAS driven GFP expression was exploited to identify individual neurons undergoing amyloidogenic AβPP processing, revealing increased nuclear localization of Foxo3a and enhanced Foxo3a-mediated transcription downstream of AICD production. Foxo3a translocation was not driven by AICD directly but correlated with reduced Akt phosphorylation. Collectively this suggests that βγ-secretase-mediated AβPP processing couples to Foxo3a which could be an early neuronal signaling response in AD.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Disease Models, Animal; Forkhead Box Protein O3; Mice; Mutagenesis, Site-Directed; Mutation; Neurons; Phosphorylation; Protein Transport; Signal Transduction

Increasing Diagnostic Accuracy of Mild Cognitive Impairment due to Alzheimer's Disease by User-Independent, Web-Based Whole-Brain Volumetry. - Hedderich, Dennis M; Spiro, Judith E; Goldhardt, Oliver; Kaesmacher, Johannes; Wiestler, Benedikt; Yakushev, Igor; Zimmer, Claus; Boeckh-Behrens, Tobias; Grimmer, Timo (J Alzheimers Dis, 2018)
BACKGROUND: Volumetric quantification of structural MRI has been shown to increase the diagnostic accuracy of patients with mild cognitive impairment (MCI); however, its implementation in clinical routine is usually technically difficult and time-consuming. OBJECTIVE: The purpose of this study was to investigate whether volumetric information obtained from the free and easy-to-use online tool volBrain can improve correct identification of MCI patients with Alzheimer's disease (AD) compared to visual reading. METHODS: The study cohort consisted of 27 patients with MCI due to AD (AD positive) as determined by biomarker information and 26 cognitively normal controls (CN). Three blinded readers, 2 radiologists and 1 clinical dementia expert, assessed the patients' MRI regarding brain atrophy and probability of underlying AD two times, without and with supporting volumetric information from volBrain. To assess diagnostic accuracy of volBrain measures alone, a simple sum score based on basic volumetric measures was developed and tested. RESULTS: Correct patient classification by readers 1, 2, and 3 without a volumetric report was 73.6%, 77.4%, and 83.0%. With a volumetric report, correct classification increased for the radiological readers to 77.4% and 81.1%, respectively and decreased to 77.4% for reader 3. Usage of the volumetric report alone yielded the highest diagnostic accuracy of 84.9%. Diagnostic confidence increased significantly for radiological readers. CONCLUSION: Volumetric information from volBrain increases the radiologist's diagnostic performance and confidence in identifying MCI patients with AD. We propose that such tools may be implemented in the routine diagnostic work-up of patients with suspected AD.

Inhibition of Histone Acetylation by ANP32A Induces Memory Deficits. - Chai, Gao-Shang; Feng, Qiong; Ma, Rong-Hong; Qian, Xiao-Hang; Luo, Dan-Ju; Wang, Zhi-Hao; Hu, Yu; Sun, Dong-Sheng; Zhang, Jun-Fei; Li, Xiao; Li, Xiao-Guang; Ke, Dan; et al. (J Alzheimers Dis, 2018)
There is accumulating evidence that decreased histone acetylation is involved in normal aging and neurodegenerative diseases. Recently, we found that ANP32A, a key component of INHAT (inhibitor of acetyltransferases) that suppresses histone acetylation, increased in aged and cognitively impaired C57 mice and expressing wild-type human full length tau (htau) transgenic mice. Downregulating ANP32A restored cognitive function and synaptic plasticity through upregulation of the expressions of synaptic-related proteins via increasing histone acetylation. However, there is no direct evidence that ANP32A can induce neurodegeneration and memory deficits. In the present study, we overexpressed ANP32A in the hippocampal CA3 region of C57 mice and found that ANP32A overexpression induced cognitive abilities and synaptic plasticity deficits, with decreased synaptic-related protein expression and histone acetylation. Combined with our recent studies, our findings reveal that upregulated ANP32A induced-suppressing histone acetylation may underlie the cognitive decline in neurodegenerative disease, and suppression of ANP32A may represent a promising therapeutic approach for neurodegenerative diseases including Alzheimer's disease.

Interaction between Cytomegalovirus and Herpes Simplex Virus Type 1 Associated with the Risk of Alzheimer's Disease Development. - Lövheim, Hugo; Olsson, Jan; Weidung, Bodil; Johansson, Anders; Eriksson, Sture; Hallmans, Göran; Elgh, Fredrik (J Alzheimers Dis, 2018)
BACKGROUND: Several environmental factors, including infectious agents, have been suggested to cause Alzheimer's disease (AD). Cytomegalovirus (CMV) has been associated with AD in several recent studies. OBJECTIVE: To investigate whether carriage of CMV, alone or in combination with Herpes simplex virus (HSV), increased the risk of developing AD. METHODS: Plasma samples from 360 AD cases (75.3% women, mean age 61.2 years), taken an average of 9.6 years before AD diagnosis, and 360 age-, sex-, cohort-, and sampling date matched dementia-free controls were analyzed to detect anti-CMV (immunoglobulin [Ig] G and IgM), group-specific anti-HSV (IgG and IgM), and specific anti-HSV1 and HSV2 IgG antibodies by enzyme-linked immunosorbent assays. AD cases and dementia-free controls were compared using conditional logistic regression analyses. RESULTS: The presence of anti-CMV IgG antibodies did not increase the risk of AD (odds ratio [OR], 0.857; p = 0.497). Among AD cases, an association between CMV and HSV1 carriage was detected (OR 7.145, p < 0.001); in a conditional logistic regression model, the interaction between CMV and HSV1 was associated with AD development (OR 5.662; p = 0.007). CONCLUSION: The present findings do not support a direct relationship between CMV infection and the development of AD; however, an interaction between CMV and HSV1 was found to be associated significantly with AD development. These findings suggest that CMV infection facilitates the development of HSV1-associated AD, possibly via its effects on the immune system.
Keywords: Aged; Alzheimer Disease; Antibodies, Viral; Case-Control Studies; Cytomegalovirus; Cytomegalovirus Infections; Enzyme-Linked Immunosorbent Assay; Female; Herpes Simplex; Herpesvirus 1, Human; Humans; Immunoglobulin G; Immunoglobulin M; Logistic Models; Male; Middle Aged

Interactive Effect of Depression and Cognitive Impairment on Olfactory Identification in Elderly People. - Chen, Ben; Zhong, Xiaomei; Mai, Naikeng; Peng, Qi; Zhang, Min; Chen, Xinru; Wu, Zhangying; Zou, Laiquan; Liang, Wanyuan; Ouyang, Cong; Wu, Yujie; Ning, Yuping (J Alzheimers Dis, 2018)
Olfactory identification (OI) deficits have been regarded as an indicator of cognitive impairment in the elderly, but few studies have analyzed the mixed effect of depression on OI. Since depression is common in the elderly and strongly associated with OI, we aimed to explore whether the comorbidity of depression and cognitive impairment may be associated with worse outcomes. In total, 153 elderly patients with depression and 154 normal elderly were recruited. Subjects underwent assessments of depression, cognitive function, and OI. Information on the factors that may affect OI performance was collected (age, sex, smoking history, diabetes, etc.). Correlation analysis showed that several factors had a significant influence on OI performance in the elderly, including severity of depression, cognitive scores, age, sex, and years of education (p < 0.05). Among the different cognitive domains, OI was positively associated with global cognition, memory, language, executive function, and attention performance (p < 0.05). The multiple linear regression analysis indicated that memory scores, age, HAMD scores, and sex were the most relevant factors to OI scores across all elderly participants. The factorial analysis suggested that elderly with comorbidity of depression and cognitive impairment (memory deficits or language deficits) had worse OI impairment, and there was an interactive effect of depression and memory deficits on OI in elderly people. The present study suggested that the coexistence of depressive symptoms and cognitive impairment was associated with worse OI in the elderly. Studies exploring the association between OI and cognitive function should include an assessment of depression and adjust the interactive effects of depression.

Intracranial Transplantation of Pancreatic Islets Attenuates Cognitive and Peripheral Metabolic Dysfunctions in a Rat Model of Sporadic Alzheimer's Disease. - Bloch, Konstantin; Gil-Ad, Irit; Vanichkin, Alexey; Hornfeld, Shay Henry; Taler, Michal; Dar, Shira; Azarov, Dmitry; Vardi, Pnina; Weizman, Abraham (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is often associated with brain insulin resistance and peripheral metabolic dysfunctions. Recently, we developed a model of sporadic AD associated with obesity-related peripheral metabolic abnormalities in Lewis rats using intracerebroventricular administration of streptozotocin (icv-STZ). OBJECTIVE: We aimed to assess the effect of intracranially grafted pancreatic islets on cognitive and peripheral metabolic dysfunctions in the icv-STZ Lewis rats. METHODS: AD-like dementia associated with obesity was induced in inbred Lewis rats using a single icv-STZ. Two months after icv-STZ, syngeneic islets (100 islets per recipient) were implanted in the cranial subarachnoid cavity of icv-STZ rats. Morris water maze and marble burying tests were used for studying cognitive and behavioral functions. Central and peripheral metabolic alterations were assessed by histological and biochemical assays. RESULTS: The icv-STZ induced increases in food intake, body weight, and blood levels of insulin and leptin without alteration of glucose homeostasis. Grafted islets reduced body weight gain, food consumption, peripheral insulin resistance, and hyperleptinemia. Biochemical and histological analysis of the brain revealed viable grafted islets expressing insulin and glucagon. The grafted islets did not affect expression of brain insulin receptors and peripheral glucose homeostasis. Two months after islet transplantation, cognitive and behavioral functioning in transplanted rats were significantly better than the sham-operated icv-STZ rats. No significant differences in the locomotor activity between transplanted and non-transplanted icv-STZ rats were found. CONCLUSIONS: Intracranial islet transplantation attenuates cognitive decline and peripheral metabolic dysfunctions providing a novel therapeutic approach for sporadic AD associated with peripheral metabolic dysfunctions.

Kainic Acid Impairs the Memory Behavior of APP23 Mice by Increasing Brain Amyloid Load through a Tumor Necrosis Factor-α-Dependent Mechanism. - Ruan, Yang; Guo, Shi-Jie; Wang, Xu; Dong, Dong; Shen, Dong-Hui; Zhu, Jie; Zheng, Xiang-Yu (J Alzheimers Dis, 2018)
Kainic acid (KA) was recently identified as an epileptogenic and neuroexcitotoxic agent that is responsible for inducing learning and memory deficits in various neurodegenerative diseases, such as Alzheimer's disease (AD). However, the mechanism by which KA acts upon AD remains unclear. To this end, we presently investigated the roles of KA in processing amyloid-β protein precursor (AβPP) and amyloid-β protein (Aβ) loads during the course of AD development and progression. Specifically, KA treatment clearly caused the upregulation of tumor necrosis factor α (TNF-α) via activation of the PI3-K/AKT, ERK1/2, and p65 pathways in glial cells. TNF-α secreted from glial cells was then found to be responsible for stimulating the expression of BACE-1 and PS1/2, which resulted in the production and deposition of Aβ in neurons. Finally, the accumulation and aggregation of Aβ lead to the cognitive decline of APP23 mice. These results indicate that KA accelerates the progression of AD by inducing the crosstalk between glial cells and neurons.

Ketogenic Medium Chain Triglycerides Increase Brain Energy Metabolism in Alzheimer's Disease. - Croteau, Etienne; Castellano, Christian-Alexandre; Richard, Marie Anne; Fortier, Mélanie; Nugent, Scott; Lepage, Martin; Duchesne, Simon; Whittingstall, Kevin; Turcotte, Éric E; Bocti, Christian; Fülöp, Tamás; Cunnane, Stephen C (J Alzheimers Dis, 2018)
BACKGROUND: In Alzheimer's disease (AD), it is unknown whether the brain can utilize additional ketones as fuel when they are derived from a medium chain triglyceride (MCT) supplement. OBJECTIVE: To assess whether brain ketone uptake in AD increases in response to MCT as it would in young healthy adults. METHODS: Mild-moderate AD patients sequentially consumed 30 g/d of two different MCT supplements, both for one month: a mixture of caprylic (55%) and capric acids (35%) (n = 11), followed by a wash-out and then tricaprylin (95%; n = 6). Brain ketone (11C-acetoacetate) and glucose (FDG) uptake were quantified by PET before and after each MCT intervention. RESULTS: Brain ketone consumption doubled on both types of MCT supplement. The slope of the relationship between plasma ketones and brain ketone uptake was the same as in healthy young adults. Both types of MCT increased total brain energy metabolism by increasing ketone supply without affecting brain glucose utilization. CONCLUSION: Ketones from MCT compensate for the brain glucose deficit in AD in direct proportion to the level of plasma ketones achieved.

The Level of Plasma Amyloid-β40 Is Correlated with Peripheral Transport Proteins in Cognitively Normal Adults: A Population-Based Cross-Sectional Study. - Gao, Ling; Jiang, Yu; Wei, Shan; Shang, Suhang; Li, Pei; Chen, Chen; Dang, Liangjun; Wang, Jin; Huo, Kang; Deng, Meiying; Wang, Jingyi; Zhang, Rong; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Transport proteins, soluble low-density lipoprotein receptor-related protein-1 (sLRP1), and soluble receptor of advanced glycation end products (sRAGE), play an important role in the clearance of plasma amyloid-β (Aβ). However, their relationship is not clear. OBJECTIVE: The aim was to explore the relationship between plasma levels of sLRP1, sRAGE, and Aβ in a cross-sectional study. METHODS: A total of 1,185 cognitively normal participants (age above 40) from a village in the suburbs of Xi'an, China were enrolled from October 8, 2014 to March 30, 2015. Plasma Aβ40, Aβ42, sLRP1, and sRAGE were tested using a commercial ELISA. Apolipoprotein E (APOE) genotyping was conducted using PCR and sequencing. The relationship between plasma levels of sLRP1, sRAGE, and Aβ was analyzed using Pearson's correlation analysis and multiple linear regression. RESULTS: In the total population, Log sLRP1 and Log sRAGE were positively correlated with plasma Aβ40 (r= 0.103, p < 0.001; r= 0.064, p = 0.027, respectively), but neither were associated with plasma Aβ42. After multivariable adjustment in the regression model, Log sLRP1 and Log sRAGE were still positively related with plasma Aβ40 (β= 2.969, p < 0.001; β= 1.936, p = 0.017, respectively) but not Aβ42. Furthermore, the positive correlations between transport proteins and plasma Aβ40 remained significant only in APOEɛ4 non-carriers after Pearson's analysis and multiple regression analysis after stratification by gene status. CONCLUSION: The concentrations of plasma sLRP1 and sRAGE had a significant impact on the level of plasma Aβ40 in cognitively normal adults, especially in APOEɛ4 non-carriers. However, the mechanism by which the transport proteins are involved in peripheral Aβ clearance and the relationship between transporters and amyloid burden in the brain needs further validation.

Linking Atrial Fibrillation with Alzheimer's Disease: Epidemiological, Pathological, and Mechanistic Evidence. - Ihara, Masafumi; Washida, Kazuo (J Alzheimers Dis, 2018)
Many studies have shown a relationship between atrial fibrillation (AF) and vascular dementia. AF is a major risk factor for stroke, and stroke is the greatest risk factor for vascular dementia. However, the relationship between Alzheimer's disease (AD), the leading cause of dementia, and AF remains unclear. At least four epidemiological studies have reported AF significantly raises the risk of AD 1.5- to 2.5-fold. Chronic cerebral hypoperfusion, resulting from persistent AF, could explain the link as hypoperfusion may mechanistically exacerbate amyloid-β (Aβ) neuropathology, such as senile plaques and amyloid angiopathy, by upregulating Aβ-producing enzymes and lowering Aβ clearance efficiency. In addition, hypoperfusion may exacerbate tau pathology directly through upregulation of tau-phosphorylating enzymes and indirectly via the amyloid cascade. However, most neuropathological studies do not support the direct link between AD pathology and AF but rather suggests vascular neuropathology is related to, or coexistent with, AF and lowers the threshold for clinically-evident AD. Vascular neuropathology may thus mediate the link between AD and AF. From a treatment perspective, an observational study has shown that catheter ablation is associated with less incidence of AD in AF patients, suggesting rhythm-control suppresses hypoperfusion-induced AD neuropathology. In addition, rate-control may lower the rate of cognitive decline in cognitively impaired elderly subjects with AF. Further studies are warranted to clarify the mechanisms underlying the linkage between AF and AD. However, anticoagulation and rhythm-/rate-control against AF may hold promise even for AD patients.

Longitudinal Modeling of Functional Decline Associated with Pathologic Alzheimer's Disease in Older Persons without Cognitive Impairment. - Wang, Dai; Schultz, Tim; Novak, Gerald P; Baker, Susan; Bennett, David A; Narayan, Vaibhav A (J Alzheimers Dis, 2018)
BACKGROUND: Therapeutic research on Alzheimer's disease (AD) has moved to intercepting the disease at the preclinical phase. Most drugs in late development have focused on the amyloid hypothesis. OBJECTIVE: To understand the magnitude of amyloid-related functional decline and to identify the functional domains sensitive to decline in a preclinical AD population. METHODS: Data were from the Religious Orders Study and the Rush Memory and Aging Project. Cognitive decline was measured by a modified version of the Alzheimer's Disease Cooperative Study Preclinical Alzheimer Cognitive Composite. The trajectories of functional decline, as measured by the instrumental and basic activities of daily living, were longitudinally modeled in 484 participants without cognitive impairment at baseline and having both a final clinical and a postmortem neuropathology assessment of AD. RESULTS: Individuals with different final clinical diagnoses had different trajectories of cognitive and functional decline. Individuals with AD dementia, minor cognitive impairment, and no cognitive impairment had the most, intermediate, and least declines. While individuals with pathologic AD had significantly more cognitive decline over time than those without, the magnitude of difference in functional decline between these two groups was small. Functional domains such as handling finance and handling medications were more sensitive to decline. CONCLUSION: Demonstrating the functional benefit of an amyloid-targeting drug represents a significant challenge as elderly people experience functional decline due to a wide range of reasons with limited manifestation attributable to AD neuropathology. More sensitive functional scales focusing on the functional domains sensitive to decline in preclinical AD are needed.

A Longitudinal Study of Total and Phosphorylated α-Synuclein with Other Biomarkers in Cerebrospinal Fluid of Alzheimer's Disease and Mild Cognitive Impairment. - Wang, Hua; Stewart, Tessandra; Toledo, Jon B; Ginghina, Carmen; Tang, Lu; Atik, Anzari; Aro, Patrick; Shaw, Leslie M; Trojanowski, John Q; Galasko, Douglas R; Edland, Steven; Jensen, Poul H; et al. (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) features a dynamic sequence of amyloid deposition, neurodegeneration, and cognitive impairment. A significant fraction of AD brains also displays Lewy body pathology, suggesting that addition of classically Parkinson's disease-related proteins to the AD biomarker panel may be of value. To determine whether addition of cerebrospinal fluid (CSF) total α-synuclein and its form phosphorylated at S129 (pS129) to the AD biomarker panel [Amyloid-β1-42 (Aβ42), tau, and phosphorylated tau (p-tau181)] improves its performance, we examined CSF samples collected longitudinally up to 7 years as part of the Alzheimer's Disease Neuroimaging Initiative. From 87 AD, 177 mild cognitive impairment (MCI), and 104 age-matched healthy controls, 792 baseline and longitudinal CSF samples were tested for total α-synuclein, pS129, Aβ42, tau, and p-tau181. pS129, but not total α-synuclein, was weakly associated with diagnosis at baseline when t-tau/Aβ42 was included in the statistical model (β= 0.0026, p = 0.041, 95% CI [(0.0001)-(0.005)]). CSF α-synuclein predicted Alzheimer's Disease Assessment Scale-Cognitive (β= -0.59, p = 0.0015, 95% CI [(-0.96)-(-0.23)]), memory (β= 0.4, p = 0.00025, 95% CI [(0.16)-(0.59)]), and executive (0.62,<0.0001, 95% CI [(0.31)-(0.93)]) function composite scores, and progression from MCI to AD (β= 0.019, p = 0.0011, 95% CI [(0.002)-(0.20)]). pS129 was associated with executive function (β= -2.55, p = 0.0085, 95% CI [(-4.45)-(-0.66)]). Lower values in the mismatch between α-synuclein and p-tau181 predicted faster cognitive decline (β= 0.64, p = 0.0012, 95% CI [(0.48)-(0.84)]). Longitudinal biomarker changes did not differ between groups, and may not reflect AD progression. The α-synuclein-p-tau181-Mismatch could better predict longitudinal cognitive changes than classical AD markers alone, and its pathological correlates should be investigated further.
Keywords: Aged; Aged, 80 and over; alpha-Synuclein; Alzheimer Disease; Biomarkers; Cognitive Dysfunction; Cross-Sectional Studies; Disease Progression; Executive Function; Female; Humans; Linear Models; Longitudinal Studies; Male; Memory Disorders; Multivariate Analysis; Neuropsychological Tests; Phosphorylation; tau Proteins

Long-Term Follow Up of Patients with Mild-to-Moderate Alzheimer's Disease Treated with Bapineuzumab in a Phase III, Open-Label, Extension Study. - Salloway, Stephen P; Sperling, Reisa; Fox, Nick C; Sabbagh, Marwan N; Honig, Lawrence S; Porsteinsson, Anton P; Rofael, Hany; Ketter, Nzeera; Wang, Daniel; Liu, Enchi; Carr, Stephen; Black, Ronald S; et al. (J Alzheimers Dis, 2018)
BACKGROUND: A 3-year extension of two Phase III parent studies of intravenous (IV) bapineuzumab in patients with mild-to-moderate Alzheimer's disease dementia (apolipoprotein (APOE) ɛ4 carriers and noncarriers) is summarized. OBJECTIVES: The primary and secondary objectives were to evaluate the long-term safety, tolerability, and maintenance of efficacy of bapineuzumab. METHODS: A multicenter study in patients who had participated in double-blind placebo-controlled parent studies. Patients enrolled in the extension study were assigned to receive IV infusions of bapineuzumab (0.5 or 1.0 mg/kg) every 13 weeks until termination but were blinded to whether they had received bapineuzumab or placebo in the parent studies. RESULTS: A total of 1,462 (688 were APOEɛ4 carriers and 774 were noncarriers) patients were enrolled. Extension-onset adverse events occurred in >81% of the patients in each dose group. Fall, urinary tract infection, agitation, and ARIA-E occurred in ≥10% of participants. The incidence proportion of ARIA-E was higher among carriers and noncarriers who received bapineuzumab for the first time in the extension study (11.8% and 5.4%, respectively) versus those who were previously exposed in the parent studies (5.1% and 1.3%, respectively). After 6 to 12 months exposure to bapineuzumab IV in the extension study, similar deterioration of cognition and function occurred with no significant differences between the dose groups. CONCLUSIONS: Infusion of bapineuzumab 0.5 or 1.0 mg/kg every 13 weeks for up to 3 years was generally well tolerated, with a safety and tolerability profile similar to that in previous studies.

Medical Comorbidity in Alzheimer's Disease: A Nested Case-Control Study. - Wang, Jen-Hung; Wu, Ya-Ju; Tee, Boon Lead; Lo, Raymond Y (J Alzheimers Dis, 2018)
BACKGROUND: Little is known about the distribution of medical comorbidities in Alzheimer's disease (AD). OBJECTIVE: We aimed to describe the comorbidity pattern of AD in a nested case-control study. METHODS: Incident AD cases were identified by International Classification of Diseases codes in a random sample of 2 million individuals in Taiwan National Health Insurance program during 2001-2011. We further restricted cases to those treated with AD drugs of approved reimbursement. We sampled a set of age- and sex-matched control subjects (2:1 ratio) and employed conditional logistic regression to estimate the associations between pre-specified 14 comorbidities and AD. The clusters of multiple chronic diseases were then identified by exploratory factor analysis. RESULTS: A total of 2,618 AD cases were identified during 2001-2011 with a mean age of 76.1 years and female preponderance (59%). The most common 5 comorbidities in AD were hypertension (55.1%), osteoarthritis (38.2%), depression (32.3%), diabetes mellitus (DM) (25.7%), and cerebrovascular disease (CVD) (22.7%). After adjusting for age and sex, DM, osteoporosis, depression, and CVD were significantly associated with AD. The number of comorbidity was 3-fold greater in the AD group. The cluster of hypertension, DM, and hyperlipidemia was the most common combination in old age, whereas the cluster osteoarthritis and osteoporosis was the only multimorbidity pattern significantly associated with AD. CONCLUSION: Multimorbidity is common in AD. Depression, CVD, osteoporosis, and DM are associated with incident AD, supporting that their co-existence is a typical feature of AD at old age. Comorbidity care should be integrated into current management for patients with AD.

Melatonin in Synaptic Impairments of Alzheimer's Disease. - Shi, Yan; Fang, Ying-Yan; Wei, Yu-Ping; Jiang, Qian; Zeng, Peng; Tang, Na; Lu, Youming; Tian, Qing (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) underlies dementia for millions of people worldwide with no effective treatment. The dementia of AD is thought stem from the impairments of the synapses because of their critical roles in cognition. Melatonin is a neurohormone mainly released by the pineal gland in a circadian manner and it regulates brain functions in various manners. It is reported that both the melatonin deficit and synaptic impairments are present in the very early stage of AD and strongly contribute to the progress of AD. In the mammalian brains, the effects of melatonin are mainly relayed by two of its receptors, melatonin receptor type 1a (MT1) and 1b (MT2). To have a clear idea on the roles of melatonin in synaptic impairments of AD, this review discussed the actions of melatonin and its receptors in the stabilization of synapses, modulation of long-term potentiation, as well as their contributions in the transmissions of glutamatergic, GABAergic and dopaminergic synapses, which are the three main types of synapses relevant to the synaptic strength. The synaptic protective roles of melatonin in AD treatment were also summarized. Regarding its protective roles against amyloid-β neurotoxicity, tau hyperphosphorylation, oxygenation, inflammation as well as synaptic dysfunctions, melatonin may be an ideal therapeutic agent against AD at early stage.

Mesenchymal Stem Cell-Derived Extracellular Vesicles Suppresses iNOS Expression and Ameliorates Neural Impairment in Alzheimer's Disease Mice. - Wang, Shan-Shan; Jia, Jianjun; Wang, Zhenfu (J Alzheimers Dis, 2018)
BACKGROUND: Mesenchymal stem cells (MSCs)-derived extracellular vesicles (EVs) have been reported to exhibit therapeutic effects in various animal models of neurological diseases, such as stroke and hypoxic-ischemic brain injury. OBJECTIVE: The present study investigated the potential beneficial effect of MSC-derived EVs in an animal model of Alzheimer's disease (AD). METHODS: APP/PS1 mice and their non-transgenic littermates (WT) received intracerebroventricle injection of MSC-derived EVs once per two days for two weeks. Then novel object recognition and water maze tasks were carried out to measure the cognitive behaviors. Electrophysiological tests were carried out to measure hippocampal synaptic plasticity. Inducible nitric oxide synthase (iNOS) mRNA and protein levels were measured by qRT-PCR and western blotting in primary cultured neurons treated with amyloid-β peptide (Aβ) or prepared from APP/PS1 mice. RESULTS: Treatment with MSC-derived EVs alleviates exogenous Aβ-induced iNOS mRNA and protein expression. In cultured primary neurons prepared from APP/PS1 pups, iNOS mRNA and protein levels were significantly reduced when treated with MSC-derived EVs. MSC-derived EVs improved cognitive behavior, rescued impairment of CA1 synaptic transmission, and long-term potentiation in APP/PS1 mice. CONCLUSION: MSC-derived EVs possessed beneficial effects in a mouse model of AD, probably by suppressing Aβ induced iNOS expression.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Cells, Cultured; Disease Models, Animal; Extracellular Vesicles; Humans; Male; Mesenchymal Stem Cells; Mice; Mice, Transgenic; Neuronal Plasticity; Neurons; Nitric Oxide Synthase Type II; Synaptic Transmission

Meta-Analysis of the Association between Variants in ABCA7 and Alzheimer's Disease. - Ma, Fang-Chen; Wang, Hui-Fu; Cao, Xi-Peng; Tan, Chen-Chen; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2018)
The ATP-binding cassette transporter A7 (ABCA7) was identified as a known risk factor for Alzheimer's disease (AD). However, the relation between ABCA7 and AD was still inconsistent across these studies. Here, our meta-analysis aimed at confirming the association of ABCA7 with AD. Finally, 16 case-control studies (63747 versus 85833) were retrieved from PubMed and other databases. Three common loci were confirmed to increase the risk of AD (rs3764650: OR = 1.20, 95% CI = 1.16-1.24; rs3752246: OR = 1.13,95% CI = 1.08-1.19; rs4147929: OR = 1.17, 95% CI = 1.10-1.24), but the associations varied among the different races. Furthermore, ABCA7 loss-of-function (LOF) mutations conferred a higher risk for AD than did the above variants (LOF: OR = 1.78, 95%  = 1.43-2.22). In conclusion, ABCA7 genetic variants, especially the LOF mutations, were significantly associated with the risk of AD.

Metabolic Syndrome and Amyloid Accumulation in the Aging Brain. - Gomez, Gabriela; Beason-Held, Lori L; Bilgel, Murat; An, Yang; Wong, Dean; Studenski, Stephanie; Ferrucci, Luigi; Resnick, Susan M (J Alzheimers Dis, 2018)
BACKGROUND: Recent studies show links between metabolic syndrome and Alzheimer's disease (AD) neuropathology. Understanding the link between vascular-related health conditions and dementia will help target at risk populations and inform clinical strategies for early detection and prevention of AD. OBJECTIVE: To determine whether metabolic syndrome is associated with global cerebral amyloid-β (Aβ) positivity and longitudinal Aβ accumulation. METHODS: Prospective study of 165 participants who underwent (11)C-Pittsburgh compound B (PiB) PET neuroimaging to measure Aβ, from June 2005 to May 2016. Metabolic syndrome was defined using the revised Third Adults Treatment Panel of the National Cholesterol Education Program criteria. Participants were classified as PiB+/- . Linear mixed effects models assessed the relationships between baseline metabolic syndrome and PiB status and regional Aβ change over time. RESULTS: A total of 165 cognitively normal participants of the Baltimore Longitudinal Study of Aging (BLSA) Neuroimaging substudy, aged 55-92 years (mean baseline age = 76.4 years, 85 participants were male), received an average of 2.5 PET-PiB scans over an average interval of 2.6 (3.08 SD) years between first and last visits. Metabolic syndrome was not associated with baseline PiB positivity or concurrent regional Aβ. Metabolic syndrome was associated with increased rates of Aβ accumulation in superior parietal and precuneus regions over time in the PiB+ group. Elevated fasting glucose and blood pressure showed individual associations with accelerated Aβ accumulation. CONCLUSION: Metabolic syndrome was associated with accelerated Aβ accumulation in PiB+ individuals and may be an important factor in the progression of AD pathology.

Methylenetetrahydrofolate Reductase Deficiency Deregulates Regional Brain Amyloid-β Protein Precursor Expression and Phosphorylation Levels. - Hoffman, Alexander; Taleski, Goce; Qian, Helena; Wasek, Brandi; Arning, Erland; Bottiglieri, Teodoro; Sontag, Jean-Marie; Sontag, Estelle (J Alzheimers Dis, 2018)
Deregulation of the amyloid-β protein precursor (AβPP) plays a critical role in the neurodegenerative cascade of Alzheimer's disease (AD). Significantly, common functional polymorphisms in the 5,10-methylenetetrahydrofolate reductase (MTHFR) gene are a risk factor for the development of late-onset AD. Reduced MTHFR activity is associated with alterations in folate and homocysteine metabolism. Here, we first show that in young MTHFR knockout mice, mild and severe MTHFR deficiency markedly increase cortical and hippocampal AβPP phosphorylation at the regulatory Thr668 site. However, the hippocampus is especially vulnerable to the effects of aging and mild MTHFR deficiency. Notably, the effects of severe MTHFR deficiency in young mice are recapitulated by prolonged dietary folate deficiency in old mice, which leads to regional brain accumulation of cystathionine due to impaired methylation of homocysteine. The incremental AβPP phosphorylation at Thr668 mediated by severe genetic-or diet-induced impairment of the folate cycle correlates with enhanced accumulation of demethylated protein phosphatase 2A (PP2A), and activation of glycogen synthase kinase-3β (GSK-3β). Lastly, we show that severe disturbances in folate metabolism can also affect AβPP expression levels in a brain region specific manner. Together our findings identify a novel link between genetic MTHFR deficiency, activation of GSK-3β, demethylation of PP2A, and enhanced phosphorylation of AβPP at Thr668, which is known to critically influence neuronal AβPP function and pathological amyloidogenic processing. Deregulation of AβPP provides a novel mechanism by which common human MTHFR polymorphisms may interact with dietary folate deficiency to alter neuronal homeostasis and increase the risk for sporadic AD.

Microglia CREB-Phosphorylation Mediates Amyloid-β-Induced Neuronal Toxicity. - Gao, Yuan; Liu, En-Jie; Wang, Wei-Jin; Wang, Ya-Li; Li, Xiao-Guang; Wang, Xin; Li, Shi-Hong; Zhang, Shu-Juan; Li, Meng-Zhu; Zhou, Qiu-Zhi; Long, Xiao-Bing; Zhang, Hua-Qiu; et al. (J Alzheimers Dis, 2018)
Extracellular accumulation of amyloid-β (Aβ) forming senile plaques is one of the hallmark pathologies in Alzheimer's disease (AD), while the mechanisms underlying the neuronal toxic effect of Aβ are not fully understood. Here, we found that intracerebroventricular infusion of the aged Aβ42 in mice only induces memory deficit at 24 h but not at 7 days. Interestingly, a remarkably increased CREB (cAMP response element-binding protein) Ser133-phosphorylation (pS133-CREB) with microglial activation was detected at 24 h but not at 7 days after Aβ infusion. Aβ treatment for 24 h increased pS133-CREB level in microglia of the hippocampal non-granular cell layers with remarkably decreased pS133-CREB immunoreactivity in neurons of the hippocampal granular cell layers, including CA1, CA3, and DG subsets. Inhibition of microglia activation by minocycline or CREB phosphorylation by H89, an inhibitor of protein kinase A (PKA), abolished Aβ-induced microglia CREB hyperphosphorylation with restoration of neuronal function and attenuation of inflammatory response, i.e., reduced levels of interleukin-6 (IL6) and pCREB binding of matrix metalloproteinase-9 (MMP9) DNA. Finally, treatment of the primary hippocampal neurons with Aβ-potentiated microglia media decreased neuronal GluN1 and GluA2 levels, while simultaneous inhibition of PKA restored the levels. These novel findings reveal that intracerebroventricular infusion of Aβ only induces transient memory deficit in mice and the molecular mechanisms involve a stimulated microglial CREB phosphorylation.

Modeling Prion-Like Processing of Tau Protein in Alzheimer's Disease for Pharmaceutical Development. - Wischik, Claude M; Schelter, Björn O; Wischik, Damon J; Storey, John M D; Harrington, Charles R (J Alzheimers Dis, 2018)
Following our discovery of a fragment from the repeat domain of tau protein as a structural constituent of the PHF-core in Alzheimer's disease (AD), we developed an assay that captured several key features of the aggregation process. Tau-tau binding through the core tau fragment could be blocked by the same diaminophenothiazines found to dissolve proteolytically stable PHFs isolated from AD brain. We found that the PHF-core tau fragment is inherently capable of auto-catalytic self-propagation in vitro, or "prion-like processing", that has now been demonstrated for several neurodegenerative disorders. Here we review the findings that led to the first clinical trials to test tau aggregation inhibitor therapy in AD as a way to block this cascade. Although further trials are still needed, the results to date suggest that a treatment targeting the prion-like processing of tau protein may have a role in both prevention and treatment of AD.

Moringa Oleifera Alleviates Homocysteine-Induced Alzheimer's Disease-Like Pathology and Cognitive Impairments. - Mahaman, Yacoubou Abdoul Razak; Huang, Fang; Wu, Mengjuan; Wang, Yuman; Wei, Zhen; Bao, Jian; Salissou, Maibouge Tanko Mahamane; Ke, Dan; Wang, Qun; Liu, Rong; Wang, Jian-Zhi; Zhang, Bin; et al. (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is multifactorial with unclear etiopathology. Due to the complexity of AD, many attempted single therapy treatments, like Aβ immunization, have generally failed. Therefore, there is a need for drugs with multiple benefits. Naturally occurring phytochemicals with neuroprotective, anti-amyloidogenic, antioxidative, and anti-inflammatory properties could be a possible way out. In this study, the effect of Moringa oleifera (MO), a naturally occurring plant with high antioxidative, anti-inflammatory, and neuroprotective effects, was evaluated on hyperhomocysteinemia (HHcy) induced AD-like pathology in rats. Homocysteine (Hcy) injection for 14 days was used to induce AD-like pathology. Simultaneous MO extract gavage followed the injection as a preventive treatment or, after injection completion, MO gavage was performed for another 14 days as a curative treatment. MO was found to not only prevent but also rescue the oxidative stress and cognitive impairments induced by Hcy treatment. Moreover, MO recovered the decreased synaptic proteins PSD93, PSD95, Synapsin 1 and Synaptophysin, and improved neurodegeneration. Interestingly, MO decreased the Hyc-induced tau hyperphosphorylation at different sites including S-199, T-231, S-396, and S-404, and at the same time decreased Aβ production through downregulation of BACE1. These effects in HHcy rats were accompanied by a decrease in calpain activity under MO treatment, supporting that calpain activation might be involved in AD pathogenesis in HHcy rats. Taken together, our data, for the first time, provided evidence that MO alleviates tau hyperphosphorylation and Aβ pathology in a HHcy AD rat model. This and previous other studies support MO as a good candidate for, and could provide new insights into, the treatment of AD and other tauopathies.

Multicenter Resting State Functional Connectivity in Prodromal and Dementia Stages of Alzheimer's Disease. - Teipel, Stefan J; Metzger, Coraline D; Brosseron, Frederic; Buerger, Katharina; Brueggen, Katharina; Catak, Cihan; Diesing, Dominik; Dobisch, Laura; Fliebach, Klaus; Franke, Christiana; Heneka, Michael T; Kilimann, Ingo; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Alterations of intrinsic networks from resting state fMRI (rs-fMRI) have been suggested as functional biomarkers of Alzheimer's disease (AD). OBJECTIVE: To determine the diagnostic accuracy of multicenter rs-fMRI for prodromal and preclinical stages of AD. METHODS: We determined rs-fMRI functional connectivity based on Pearson's correlation coefficients and amplitude of low-frequency fluctuation in people with subjective cognitive decline, people with mild cognitive impairment, and people with AD dementia compared with healthy controls. We used data of 247 participants of the prospective DELCODE study, a longitudinal multicenter observational study, imposing a unified fMRI acquisition protocol across sites. We determined cross-validated discrimination accuracy based on penalized logistic regression to account for multicollinearity of predictors. RESULTS: Resting state functional connectivity reached significant cross-validated group discrimination only for the comparison of AD dementia cases with healthy controls, but not for the other diagnostic groups. AD dementia cases showed alterations in a large range of intrinsic resting state networks, including the default mode and salience networks, but also executive and language networks. When groups were stratified according to their CSF amyloid status that was available in a subset of cases, diagnostic accuracy was increased for amyloid positive mild cognitive impairment cases compared with amyloid negative controls, but still inferior to the accuracy of hippocampus volume. CONCLUSION: Even when following a strictly harmonized data acquisition protocol and rigorous scan quality control, widely used connectivity measures of multicenter rs-fMRI do not reach levels of diagnostic accuracy sufficient for a useful biomarker in prodromal stages of AD.

Multivariate Approach for Alzheimer's Disease Detection Using Stationary Wavelet Entropy and Predator-Prey Particle Swarm Optimization. - Zhang, Yudong; Wang, Shuihua; Sui, Yuxiu; Yang, Ming; Liu, Bin; Cheng, Hong; Sun, Junding; Jia, Wenjuan; Phillips, Preetha; Górriz, Juan Manuel (J Alzheimers Dis, 2018)
BACKGROUND: The number of patients with Alzheimer's disease is increasing rapidly every year. Scholars often use computer vision and machine learning methods to develop an automatic diagnosis system. OBJECTIVE: In this study, we developed a novel machine learning system that can make diagnoses automatically from brain magnetic resonance images. METHODS: First, the brain imaging was processed, including skull stripping and spatial normalization. Second, one axial slice was selected from the volumetric image, and stationary wavelet entropy (SWE) was done to extract the texture features. Third, a single-hidden-layer neural network was used as the classifier. Finally, a predator-prey particle swarm optimization was proposed to train the weights and biases of the classifier. RESULTS: Our method used 4-level decomposition and yielded 13 SWE features. The classification yielded an overall accuracy of 92.73±1.03%, a sensitivity of 92.69±1.29%, and a specificity of 92.78±1.51%. The area under the curve is 0.95±0.02. Additionally, this method only cost 0.88 s to identify a subject in online stage, after its volumetric image is preprocessed. CONCLUSION: In terms of classification performance, our method performs better than 10 state-of-the-art approaches and the performance of human observers. Therefore, this proposed method is effective in the detection of Alzheimer's disease.

Mutation Screening of the CHCHD2 Gene for Alzheimer's Disease and Frontotemporal Dementia in Chinese Mainland Population. - Che, Xiang-Qian; Zhao, Qian-Hua; Huang, Yue; Li, Xia; Ren, Ru-Jing; Chen, Sheng-Di; Guo, Qi-Hao; Wang, Gang (J Alzheimers Dis, 2018)
As an important multifunctional protein involved in regulation of mitochondrial metabolism, CHCHD2 was identified as a causative gene for Parkinson's disease (PD), yet the relationship between CHCHD2 and neurodegenerative dementia is not well understood. We directly sequenced the entire coding region of CHCHD2 gene in 150 AD patients, 84 FTD patients, and 417 controls. Four rare putative pathogenic variants of CHCHD2, including rs142444896 (c.5C>T, p.P2L), rs752705344 (c.15C>G, p.S5R), rs145190179 (c.94G>A, p.A32T), and rs182992574 (c.255T>A, p.S85R) were identified from a cohort composed of 150 AD and 84 FTD patients. These results suggest that CH CHD2 gene play an important role in other neurodegenerative disorders from our dementia study in China.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Asian Continental Ancestry Group; Case-Control Studies; China; Female; Frontotemporal Dementia; Genetic Association Studies; Humans; Male; Middle Aged; Mitochondrial Proteins; Mutation; Transcription Factors

Nature of Tau-Associated Neurodegeneration and the Molecular Mechanisms. - Yang, Ying; Wang, Jian-Zhi (J Alzheimers Dis, 2018)
Neurodegeneration is defined as the progressive loss of structure or function of the neurons. As the nature of degenerative cell loss is currently not clear, there is no specific molecular marker to measure neurodegeneration. Therefore, researchers have been using apoptotic markers to measure neurodegeneration. However, neurodegeneration is completely different from apoptosis by morphology and time course. Lacking specific molecular marker has been the major hindrance in research of neurodegenerative disorders. Alzheimer's disease (AD) is the most common neurodegenerative disorder, and tau accumulation forming neurofibrillary tangles is a hallmark pathology in the AD brains, suggesting that tau must play a critical role in AD neurodegeneration. Here we review part of our published papers on tau-related studies, and share our thoughts on the nature of tau-associated neurodegeneration in AD.

Neuroprotective Effects of Ginsenoside Rf on Amyloid-β-Induced Neurotoxicity in vitro and in vivo. - Du, Yehong; Fu, Min; Wang, Yu Tian; Dong, Zhifang (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a neurodegenerative disease characterized by the deposition of amyloid-β peptides (Aβ). Aβ accumulation leads to the formation of neurofibrillary tangles, inflammation, axonal injury, synapse loss, and neuronal apoptosis. Thus, reducing Aβ levels should exert a neuroprotective effect against AD. Ginsenoside Rf, an extract from Panax notoginseng, has potent anti-fatigue, anti-nociception, anti-oxidation, and anti-inflammation properties. However, it is unclear whether ginsenoside Rf is effective in the treatment of AD. Here, we reported that ginsenoside Rf could significantly attenuate Aβ-induced apoptosis in N2A cells, as reflected by a dramatic increase in mitochondrial membrane potential and decrease in Ca2 + concentration, reactive oxygen species, and active caspase-3 expression. Meanwhile, ginsenoside Rf could alleviate the Aβ-induced inflammation reaction, such as the decrease of interferon-gamma (IFN-γ) and active caspase-1 expression and the increase of interleukin-13. Furthermore, we also found that Rf is able to accelerate Aβ clearance and subsequently reduces Aβ level in N2A cells stably transfected with human Swedish mutant APP695 (N2A-APP). More importantly, daily Rf treatment (20 mg/kg, i.p.) throughout the experiment dramatically improved spatial learning and memory in Aβ42-induced mouse model of AD. Taken together, these results indicate that ginsenoside Rf may decrease Aβ-induced neurotoxicity and memory decline via anti-inflammatory response during AD development, suggesting that Rf may be a potential therapeutic agent for treating AD.

A Nomogram for Predicting Amyloid PET Positivity in Amnestic Mild Cognitive Impairment. - Kim, Si Eun; Woo, Sookyoung; Kim, Seon Woo; Chin, Juhee; Kim, Hee Jin; Lee, Byung In; Park, Jinse; Park, Kyung Won; Kang, Do-Young; Noh, Young; Ye, Byoung Seok; Yoo, Han Soo; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Most clinical trials focus on amyloid-β positive (Aβ+) amnestic mild cognitive impairment (aMCI), but screening failures are high because only a half of patients with aMCI are positive on Aβ PET. Therefore, it becomes necessary for clinicians to predict which patients will have Aβ biomarker. OBJECTIVE: We aimed to compare clinical factors, neuropsychological (NP) profiles, and apolipoprotein E (APOE) genotype between Aβ+ aMCI and Aβ-aMCI and to develop a clinically useful prediction model of Aβ positivity on PET (PET-Aβ+) in aMCI using a nomogram. METHODS: We recruited 523 aMCI patients who underwent Aβ PET imaging in a nation-wide multicenter cohort. The results of NP measures were divided into following subgroups: 1) Stage (Early and Late-stage), 2) Modality (Visual, Verbal, and Both), 3) Recognition failure, and 4) Multiplicity (Single and Multiple). A nomogram for PET-Aβ+ in aMCI patients was constructed using a logistic regression model. RESULTS: PET-Aβ+ had significant associations with NP profiles for several items, including high Clinical Dementia Rating Scale Sum of Boxes score (OR 1.47, p = 0.013) and impaired memory modality (impaired both visual and verbal memories compared with visual only, OR 3.25, p = 0.001). Also, presence of APOEɛ4 (OR 4.14, p < 0.001) was associated with PET-Aβ+. These predictors were applied to develop the nomogram, which showed good prediction performance (C-statistics = 0.79). Its prediction performances were 0.77/0.74 in internal/external validation. CONCLUSIONS: The nomogram consisting of NP profiles, especially memory domain, and APOEɛ4 genotype may provide a useful predictive model of PET-Aβ+ in patients with aMCI.

Non-Genetic Risk Factors for Degenerative and Vascular Young Onset Dementia: Results from the INSPIRED and KGOW Studies. - Cations, Monica; Draper, Brian; Low, Lee-Fay; Radford, Kylie; Trollor, Julian; Brodaty, Henry; Sachdev, Perminder; Gonski, Peter; Broe, Gerald Anthony; Withall, Adrienne (J Alzheimers Dis, 2018)
BACKGROUND: Several brain reserve, vascular risk, and other modifiable factors have been associated with late-onset dementia, but their association with young onset dementia (YOD) has not been adequately explored. OBJECTIVE: To examine the association of cognitive reserve enhancing factors, cardiovascular risk factors (including smoking), depression, alcohol use, and traumatic brain injury (TBI) with non-autosomal dominant degenerative and/or vascular YOD. METHODS: Data for this matched case-control study were taken from two larger studies conducted in NSW, Australia. One comprised all people with YOD within a geographical region, while the other exclusively included Aboriginal and Torres Strait Islander participants. Dementia diagnosis was confirmed by clinical consensus, and risk exposure was retrospectively self- and/or informant-reported. RESULTS: Participants were 96 people with YOD (58.4% with probable Alzheimer's disease) and 175 age-group, sex, and sample matched control participants. Poor educational attainment, low participation in cognitive leisure activity, stroke, transient ischemic attack, and self-reported very heavy alcohol use were related to the risk of primary degenerative and/or vascular YOD. The effect of hypertension and depression varied depending on when they occurred relative to dementia onset. Current smoking was significantly associated with risk in univariate analyses but did not retain significance in multivariate modelling. There was no association with hypercholesterolemia, diabetes, or TBI of any kind. Some compensation for low educational attainment was possible via a complex occupation later in life. CONCLUSION: Non-genetic factors have a role in YOD, though the relative importance of each factor may be different to late onset dementia. The timing and severity of exposure, as well as the potential for compensation with later protective exposures, are important considerations for potential prevention strategies.

Non-Phosphorylated Tau in Cerebrospinal Fluid is a Marker of Alzheimer's Disease Continuum in Young Urbanites Exposed to Air Pollution. - Calderón-Garcidueñas, Lilian; Mukherjee, Partha S; Waniek, Katharina; Holzer, Max; Chao, Chih-Kai; Thompson, Charles; Ruiz-Ramos, Rubén; Calderón-Garcidueñas, Ana; Franco-Lira, Maricela; Reynoso-Robles, Rafael; González-Maciel, Angelica; Lachmann, Ingolf (J Alzheimers Dis, 2018)
Long-term exposure to fine particulate matter (PM2.5) and ozone (O3) above USEPA standards is associated with Alzheimer's disease (AD) risk. Metropolitan Mexico City (MMC) children exhibit subcortical pretangles in infancy and cortical tau pre-tangles, NFTs, and amyloid phases 1-2 by the 2nd decade. Given their AD continuum, we measured in 507 normal cerebrospinal fluid (CSF) samples (MMC 354, controls 153, 12.82±6.73 y), a high affinity monoclonal non-phosphorylated tau antibody (non-P-Tau), as a potential biomarker of AD and axonal damage. In 81 samples, we also measured total tau (T-Tau), tau phosphorylated at threonine 181 (P-Tau), amyloid-β1-42, BDNF, and vitamin D. We documented by electron microscopy myelinated axonal size and the pathology associated with combustion-derived nanoparticles (CDNPs) in anterior cingulate cortex white matter in 6 young residents (16.25±3.34 y). Non-P-Tau showed a strong increase with age significantly faster among MMC versus controls (p = 0.0055). Aβ1 - 42 and BDNF concentrations were lower in MMC children (p = 0.002 and 0.03, respectively). Anterior cingulate cortex showed a significant decrease (p = <0.0001) in the average axonal size and CDNPs were associated with organelle pathology. Significant age increases in non-P-Tau support tau changes early in a population with axonal pathology and evolving AD hallmarks in the first two decades of life. Non-P-Tau is an early biomarker of axonal damage and potentially valuable to monitor progressive longitudinal changes along with AD multianalyte classical CSF markers. Neuroprotection of young urbanites with PM2.5 and CDNPs exposures ought to be a public health priority to halt the development of AD in the first two decades of life.

Olfactory Function is Associated with Cognitive Performance: Results of the Heinz Nixdorf Recall Study. - Tebrügge, Sarah; Winkler, Angela; Gerards, Diana; Weimar, Christian; Moebus, Susanne; Jöckel, Karl-Heinz; Erbel, Raimund; Jokisch, Martha (J Alzheimers Dis, 2018)
BACKGROUND: There is strong evidence for an association of olfactory dysfunction and neurodegenerative diseases. Studies on the association of olfaction and cognition in the general population are rare. OBJECTIVE: To evaluate gender- and age-specific associations of olfactory function and cognitive performance in a well characterized population-based study sample. METHODS: At the third examination of the Heinz Nixdorf Recall study (n = 3,087), 2,640 participants (48% men; 68.2±7.2 years) underwent Sniffin' Sticks Screening Test measuring olfactory function on a scale of 0-12 points. Olfactory function was rated as anosmic, hyposmic, or normosmic (≤6, 7-10 or ≥11 points, respectively). All participants performed eight validated cognitive subtests. Age- (55-64 years, 65-74 years, 75-86 years) and gender-stratified multivariate analysis of covariance was used to evaluate group differences in cognitive performance. RESULTS: Women showed better olfactory function than men (p < 0.001). For middle-aged participants, olfactory groups differed in almost all cognitive subtests. The analyses revealed no gender effects, although associations were slightly greater for women than for men. Anosmics showed the worst cognitive performance and normosmics showed the best cognitive performance. In the young- and old-aged groups, a quantitative association was found for anosmics in all subtests and for normosmics and hyposmics in almost all subtests. CONCLUSION: This is the first study reporting on age-specific associations of olfactory function and cognitive performance in the general population. The association found in middle-aged participants (65-74 years) may serve as a marker to improve identification of persons at high risk for cognitive decline and dementia.

Optical Depolarization of DCX-Expressing Cells Promoted Cognitive Recovery and Maturation of Newborn Neurons via the Wnt/β-Catenin Pathway. - Zhao, Ming-Liang; Chen, Shi-Jin; Li, Xiao-Hong; Wang, Li-Na; Chen, Feng; Zhong, Shi-Jiang; Yang, Cheng; Sun, Sheng-Kai; Li, Jian-Jun; Dong, Hua-Jiang; Dong, Yue-Qing; Wang, Yi; et al. (J Alzheimers Dis, 2018)
Electrical excitability by membrane depolarization is crucial for survival and maturation of newborn cells in the dentate gyrus of the hippocampus. However, traditional technology for membrane depolarization lacks temporal and spatial precision. Optogenetics can be used to activate channelrhodopsin-2 (ChR2), allowing cationic current to depolarize genetically targeted cells. In this study, we used ChR2-EGFP driven by doublecortin (DCX) to promote survival and maturation of newborn cells in the dentate gyrus after traumatic brain injury (TBI). C57BL/6 mice underwent lateral fluid percussion TBI. TBI mice were transfected with a lentivirus carrying the DCX-ChR2-EGFP gene. We observed that not only immature neurons but also type-2b intermediate progenitor (IPs) and neuroblasts expressed DCX-EGFP, indicating that DCX-expressing newborn cells could provide a long time window for electrical activity regulation. Quantitative results showed that the number of EGFP-expressing cells began to rise at 3 days after TBI and peaked at 9 days after TBI. By optical depolarization of DCX-EGFP-expressing cells between 3 and 12 days, we observed significantly improved cognitive deficits after TBI with enhanced survival and maturation of newborn cells in the dentate gyrus. We also investigated the role of optical depolarization in neural stem cells transfected with a lentivirus carrying the ChR2-DCX-EGFP gene in vitro. By administrating verapamil to block L-type calcium channels, we verified that the up-regulation of MAP2, NeuN, Neurog2, NeuroD1 and GluR2 in newborn cells was mediated by ChR2-elicted depolarization. By using β-catenin inhibitor Dkk1, we demonstrated that optical depolarization of DCX-EGFP-expressing cells facilitated survival and maturation probably through the Wnt/β-catenin signaling cascade.

Outcomes for Hospitalized Older Adults with Down Syndrome in the United States. - Mendiratta, Priya; Wei, Jeanne Y; Dayama, Neeraj; Li, Xiaocong (J Alzheimers Dis, 2018)
BACKGROUND: Patients with Down syndrome (DS) often survive into adulthood. Relatively little information is currently available regarding hospitalization outcomes among mature, older adults with DS. OBJECTIVE: To identify risk factors associated with hospital mortality rates and increased costs for hospitalized older adults with DS. METHODS: Data on hospitalized older adults with DS (≥65 years) were identified from the Nationwide Inpatient Sample database (6) from 2002 through 2012. Multivariate analyses were performed to evaluate risk factors associated with hospital mortality and hospitalization cost in these patients. RESULTS: A total of 2,134 older adults with DS were identified. A temporal increase over the 11-year period was observed in the number of older adults with DS who were hospitalized (trend p < 0.0001). However, the hospital mortality rate and post-hospital discharge to skilled nursing facilities have decreased during the same time period. Risk factors associated with increased hospital mortality included advanced age (70-79 years), female gender, admissions in the western United States, and presence of comorbid conditions (ischemic heart disease, Alzheimer's disease, and cerebrovascular accident). The mean cost was $18,241 (SD $56,105) over the 11-year period. However, no significant temporal changes in costs were noted (trend p = 0.14). CONCLUSIONS: The number of hospitalized elderly Americans with DS has increased over the 11-year period. However, hospital mortality and discharge to skilled nursing facilities have decreased during the same time period. Several demographic and co-morbid factors are associated with increased mortality. No significant differences in temporal trends in costs were noted.

Overactive BRCA1 Affects Presenilin 1 in Induced Pluripotent Stem Cell-Derived Neurons in Alzheimer's Disease. - Wezyk, Michalina; Szybinska, Aleksandra; Wojsiat, Joanna; Szczerba, Marcelina; Day, Kelly; Ronnholm, Harriet; Kele, Malin; Berdynski, Mariusz; Peplonska, Beata; Fichna, Jakub Piotr; Ilkowski, Jan; Styczyńska, Maria; et al. (J Alzheimers Dis, 2018)
The BRCA1 protein, one of the major players responsible for DNA damage response has recently been linked to Alzheimer's disease (AD). Using primary fibroblasts and neurons reprogrammed from induced pluripotent stem cells (iPSC) derived from familial AD (FAD) patients, we studied the role of the BRCA1 protein underlying molecular neurodegeneration. By whole-transcriptome approach, we have found wide range of disturbances in cell cycle and DNA damage response in FAD fibroblasts. This was manifested by significantly increased content of BRCA1 phosphorylated on Ser1524 and abnormal ubiquitination and subcellular distribution of presenilin 1 (PS1). Accordingly, the iPSC-derived FAD neurons showed increased content of BRCA1(Ser1524) colocalized with degraded PS1, accompanied by an enhanced immunostaining pattern of amyloid-β. Finally, overactivation of BRCA1 was followed by an increased content of Cdc25C phosphorylated on Ser216, likely triggering cell cycle re-entry in FAD neurons. This study suggests that overactivated BRCA1 could both influence PS1 turnover leading to amyloid-β pathology and promote cell cycle re-entry-driven cell death of postmitotic neurons in AD.

Patients with Dementia in Primary Care: Who Is Referred to a Neurologist/Psychiatrist and What Patient-Oriented Factors Are Associated with the Visit? - Strohmaier, Urs; Keller, Felix; Kilimann, Ingo; Michalowsky, Bernhard; Wucherer, Diana; Zwingmann, Ina; Teipel, Stefan; Hoffmann, Wolfgang; Thyrian, Jochen René (J Alzheimers Dis, 2018)
BACKGROUND: The current guidelines imply that basic medical diagnostics for dementia should be provided by general practitioners in cooperation with other specialists such as neurologists and psychiatrists. OBJECTIVES: The aims of this paper were to 1) compare the dementia patients of general practice residents whose care is co-managed by neurology/psychiatry residents with those whose care is not; 2) identify the patient variables associated with the utilization of neurological and psychiatric specialists; and 3) describe the frequency of imaging used for dementia patients in primary care. METHODS: The analyses utilized data from 485 individuals who screened positive for dementia in primary care (PWD). Clinical variables and the utilization of specialists were assessed via medical records and face-to-face interviews. The factors associated with the utilization of specialists were assessed using multivariate linear regression and included age, sex, relationship status, cognitive impairment, depression, activities of daily living, and formal diagnosis of dementia. RESULTS: Our results show that 89 out of 485 study participants (18.4%) were referred to specialists 12 months prior to assessment. Of these 89 individuals, 14.6% (n = 13) did not receive imaging diagnostics, while 39.3% (n = 35) received brain imaging by CT scan and 46.1% (n = 41) by MRI. PWD referred to specialists differed from those not referred, in age, relationship status, and the presence of a formal diagnosis. Our multivariate analysis revealed that younger age (OR = 0.95; 95% -confidence interval 0.90-0.99; p = 0.04) and higher functional impairment (OR = 1.15; 95% -confidence interval 1.02-1.30; p = 0.02) were associated with a visit to a specialist. DISCUSSION: Only 1 out of every 4 to 5 individuals who have screened positive for dementia have visited a specialist in psychiatry or neurology. While in general, women utilized specialists less often than men, younger and more functionally impaired patients were more likely to be sent to a specialist by their treating general practitioner. Almost 90% of the patients sent to a specialist received cranial neuroimaging, suggesting high adherence to diagnostic guidelines in specialized care.

Patterns of Neuropsychological Dysfunction and Cortical Volume Changes in Logopenic Aphasia. - Owens, Tyler E; Machulda, Mary M; Duffy, Joseph R; Strand, Edythe A; Clark, Heather M; Boland, Sarah; Martin, Peter R; Lowe, Val J; Jack, Clifford R; Whitwell, Jennifer L; Josephs, Keith A (J Alzheimers Dis, 2018)
BACKGROUND: Neuropsychological assessment can add essential information to the characterization of individuals presenting with the logopenic variant of primary progressive aphasia (lvPPA). OBJECTIVE: This study examined the neuropsychological characteristics of lvPPA patients. We also examined differences in regional and whole brain atrophy based on neuropsychological profiles. METHODS: We conducted a hierarchical cluster analysis on memory, executive functioning, and visuospatial neuropsychological test data for 56 individuals with lvPPA. We then compared resultant clusters to left middle temporal, inferior parietal, and superior parietal regions-of-interest using multivariate analysis of covariance. We also performed voxel-level analyses. RESULTS: We identified three clusters characterized as lvPPA with no neurocognitive impairment (n = 5), lvPPA with mild neurocognitive deficits (n = 23), and lvPPA with marked cognitive deficits (n = 28). WAB-AQ was associated with left middle temporal volume. Superior parietal volumes were smaller for the lvPPA group with marked cognitive symptoms compared to the less severe groups. Voxel-level analyses showed greater atrophy in temporal, parietal, lateral occipital, and frontal regions, left worse than right. Age, disease duration, gender, WAB-AQ, and PiB-PET did not account for differences between groups. CONCLUSIONS: LvPPA patients without cognitive deficits in other domains were relatively uncommon while 50% of our sample exhibited pronounced neurocognitive deficits outside the language domain. Pronounced cognitive deficits in lvPPA are associated with widespread atrophy, left worse than right. Our study underscores the importance of examining neuropsychological function in addition to language in patients with lvPPA.

Perspectives on Communicating Biomarker-Based Assessments of Alzheimer's Disease to Cognitively Healthy Individuals. - Milne, Richard; Bunnik, Eline; Diaz, Ana; Richard, Edo; Badger, Shirlene; Gove, Dianne; Georges, Jean; Fauria, Karine; Molinuevo, Jose-Luis; Wells, Katie; Ritchie, Craig; Brayne, Carol (J Alzheimers Dis, 2018)
In clinical trials which target pathophysiological mechanisms associated with Alzheimer's disease, research participants who are recruited based on biomarker test results should be informed about their increased risk of developing Alzheimer's dementia. This paper presents the results of a qualitative focus group study of attitudes and concerns toward learning information about biomarker-based risk status among healthy research participants in the United Kingdom and Spain and people with dementia and their supporters/caregivers from countries represented in the European Working Group of People with Dementia of Alzheimer Europe. The study identified expectations related to learning risk status and preferences related to the content, quality, and follow-up of the disclosure process. The latter emphasize distinctions between risk and diagnoses, the importance of clear information about risk, and suggestions for risk reduction, as well as expectations for follow up and support. The implications of these preferences for practice are discussed. Providing details of research participants' experience and views may serve as a guide for the development of processes for the responsible disclosure of Alzheimer's disease biomarkers.
Keywords: Adult; Aged; Alzheimer Disease; Biomarkers; Caregivers; Disclosure; Female; Focus Groups; Humans; Male; Middle Aged; Qualitative Research; Risk Factors; Spain; United Kingdom

Plasma Antioxidant Status in Patients with Alzheimer's Disease and Cognitively Intact Elderly: A Meta-Analysis of Case-Control Studies. - Mullan, Kathryn; Cardwell, Chris R; McGuinness, Bernadette; Woodside, Jayne V; McKay, Gareth J (J Alzheimers Dis, 2018)
Serum antioxidants may afford neuroprotection against Alzheimer's disease (AD) via correction of the pro-oxidative imbalance but findings reported have been inconsistent. We compared the pooled mean difference in serum levels of ten dietary antioxidants between patients with AD and cognitively intact controls from 52 studies in meta-analyses using random-effects models. Patients with AD had significantly lower plasma levels of α-carotene, β-carotene, lycopene, lutein, vitamin A, C, and E, and uric acid. No significant difference was observed for plasma levels of β-cryptoxanthin and zeaxanthin. Considerable heterogeneity was detected across studies. The lower serum levels of dietary antioxidants from the carotene and vitamin subclasses observed in individuals with AD suggest reduced systemic availability of these subclasses in this prevalent form of dementia. To our knowledge, these are the first meta-analyses to demonstrate lower serum lycopene and to evaluate β-cryptoxanthin, lutein, and zeaxanthin levels in AD. In light of the significant heterogeneity detected across studies, caution should be exercised in the interpretation of the data and therapeutic intervention approaches considered through supplementation measures. Our data may better inform interventions to improve antioxidant status in a condition of major public health importance.

Polypharmacy and Potentially Inappropriate Medication in People with Dementia: A Nationwide Study. - Kristensen, Rachel Underlien; Nørgaard, Ane; Jensen-Dahm, Christina; Gasse, Christiane; Wimberley, Theresa; Waldemar, Gunhild (J Alzheimers Dis, 2018)
BACKGROUND: Polypharmacy (use of ≥5 different medications) and potentially inappropriate medication (PIM) are well-known risk factors for numerous negative health outcomes. However, the use of polypharmacy and PIM in people with dementia is not well-described. OBJECTIVE: To examine the prevalence of polypharmacy and PIM in older people with and without dementia in a nationwide population. METHODS: Cross-sectional study of the Danish population aged ≥65 in 2014 (n = 1,032,120) based on register data, including information on diagnoses and dispensed prescriptions. Polypharmacy and PIM use among people with (n = 35,476) and without dementia (n = 994,231) were compared, stratified by living situation and adjusted for age, sex, and comorbidity. The red-yellow-green list from the Danish Institute for Rational Pharmacotherapy and the German PRISCUS list were used to define PIM. RESULTS: People with dementia were more frequently exposed to polypharmacy (dementia: 62.6% versus no-dementia: 35.1%, p < 0.001) and likewise PIM (red-yellow-green: 45.0% versus 29.7%, p < 0.001; PRISCUS: 24.4% versus 13.2%, p < 0.001). After adjustments for age, sex, and comorbidity, the likelihood of polypharmacy and PIM was higher for community-dwelling people with dementia than without dementia (odds ratio (OR); [95% confidence interval (CI)] polypharmacy: 1.50 [1.45-1.55]; red-yellow-green: 1.27 [1.23-1.31]; PRISCUS: 1.25 [1.20-1.30]). In contrast, dementia slightly decreased the odds of polypharmacy and PIM in nursing home residents. CONCLUSION: Use of polypharmacy and PIM were widespread in the older population and more so in people with dementia. This could have negative implications for patient-safety and demonstrates the need for interventions to improve drug therapy in people with dementia.

Postsynaptic Proteome of Non-Demented Individuals with Alzheimer's Disease Neuropathology. - Zolochevska, Olga; Bjorklund, Nicole; Woltjer, Randall; Wiktorowicz, John E; Taglialatela, Giulio (J Alzheimers Dis, 2018)
Some individuals, here referred to as Non-Demented with Alzheimer's Neuropathology (NDAN), retain their cognitive function despite the presence of amyloid plaques and tau tangles typical of symptomatic Alzheimer's disease (AD). In NDAN, unlike AD, toxic amyloid-β oligomers do not localize to the postsynaptic densities (PSDs). Synaptic resistance to amyloid-β in NDAN may thus enable these individuals to remain cognitively intact despite the AD-like pathology. The mechanism(s) responsible for this resistance remains unresolved and understanding such protective biological processes could reveal novel targets for the development of effective treatments for AD. The present study uses a proteomic approach to compare the hippocampal postsynaptic densities of NDAN, AD, and healthy age-matched persons to identify protein signatures characteristic for these groups. Subcellular fractionation followed by 2D gel electrophoresis and mass spectrometry were used to analyze the PSDs. We describe fifteen proteins which comprise the unique proteomic signature of NDAN PSDs, thus setting them apart from control subjects and AD patients.

Potential Novel Approaches to Understand the Pathogenesis and Treat Alzheimer's Disease. - Drummond, Eleanor; Goñi, Fernando; Liu, Shan; Prelli, Frances; Scholtzova, Henrieta; Wisniewski, Thomas (J Alzheimers Dis, 2018)
There is growing genetic and proteomic data highlighting the complexity of Alzheimer's disease (AD) pathogenesis. Greater use of unbiased "omics" approaches is being increasingly recognized as essential for the future development of effective AD research, that need to better reflect the multiple distinct pathway abnormalities that can drive AD pathology. The track record of success in AD clinical trials thus far has been very poor. In part, this high failure rate has been related to the premature translation of highly successful results in animal models that mirror only limited aspects of AD pathology to humans. We highlight our recent efforts to increase use of human tissue to gain a better understanding of the AD pathogenesis subtype variety and to develop several distinct therapeutic approaches tailored to address this diversity. These therapeutic approaches include the blocking of the Aβ/apoE interaction, stimulation of innate immunity, and the simultaneous blocking of Aβ/tau oligomer toxicity. We believe that future successful therapeutic approaches will need to be combined to better reflect the complexity of the abnormal pathways triggered in AD pathogenesis.

Potential of Low Dose Leuco-Methylthioninium Bis(Hydromethanesulphonate) (LMTM) Monotherapy for Treatment of Mild Alzheimer's Disease: Cohort Analysis as Modified Primary Outcome in a Phase III Clinical Trial. - Wilcock, Gordon K; Gauthier, Serge; Frisoni, Giovanni B; Jia, Jianping; Hardlund, Jiri H; Moebius, Hans J; Bentham, Peter; Kook, Karin A; Schelter, Bjoern O; Wischik, Damon J; Davis, Charles S; Staff, Roger T; et al. (J Alzheimers Dis, 2018)
BACKGROUND: LMTM is being developed as a treatment for AD based on inhibition of tau aggregation. OBJECTIVES: To examine the efficacy of LMTM as monotherapy in non-randomized cohort analyses as modified primary outcomes in an 18-month Phase III trial in mild AD. METHODS: Mild AD patients (n = 800) were randomly assigned to 100 mg twice a day or 4 mg twice a day. Prior to unblinding, the Statistical Analysis Plan was revised to compare the 100 mg twice a day as monotherapy subgroup (n = 79) versus 4 mg twice a day as randomized (n = 396), and 4 mg twice a day as monotherapy (n = 76) versus 4 mg twice a day as add-on therapy (n = 297), with strong control of family-wise type I error. RESULTS: The revised analyses were statistically significant at the required threshold of p < 0.025 in both comparisons for change in ADAS-cog, ADCS-ADL, MRI atrophy, and glucose uptake. The brain atrophy rate was initially typical of mild AD in both add-on and monotherapy groups, but after 9 months of treatment, the rate in monotherapy patients declined significantly to that reported for normal elderly controls. Differences in severity or diagnosis at baseline between monotherapy and add-on patients did not account for significant differences in favor of monotherapy. CONCLUSIONS: The results are consistent with earlier studies in supporting the hypothesis that LMTM might be effective as monotherapy and that 4 mg twice a day may serve as well as higher doses. A further suitably randomized trial is required to test this hypothesis.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Antipsychotic Agents; Cohort Studies; Double-Blind Method; Female; Humans; International Cooperation; Male; Mental Status and Dementia Tests; Methylene Blue; Middle Aged; Treatment Outcome

Predicting and Tracking Short Term Disease Progression in Amnestic Mild Cognitive Impairment Patients with Prodromal Alzheimer's Disease: Structural Brain Biomarkers. - Marizzoni, Moira; Ferrari, Clarissa; Jovicich, Jorge; Albani, Diego; Babiloni, Claudio; Cavaliere, Libera; Didic, Mira; Forloni, Gianluigi; Galluzzi, Samantha; Hoffmann, Karl-Titus; Molinuevo, José Luis; Nobili, Flavio; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Early Alzheimer's disease (AD) detection using cerebrospinal fluid (CSF) biomarkers has been recommended as enrichment strategy for trials involving mild cognitive impairment (MCI) patients. OBJECTIVE: To model a prodromal AD trial for identifying MRI structural biomarkers to improve subject selection and to be used as surrogate outcomes of disease progression. METHODS: APOE ɛ4 specific CSF Aβ42/P-tau cut-offs were used to identify MCI with prodromal AD (Aβ42/P-tau positive) in the WP5-PharmaCog (E-ADNI) cohort. Linear mixed models were performed 1) with baseline structural biomarker, time, and biomarker×time interaction as factors to predict longitudinal changes in ADAS-cog13, 2) with Aβ42/P-tau status, time, and Aβ42/P-tau status×time interaction as factors to explain the longitudinal changes in MRI measures, and 3) to compute sample size estimation for a trial implemented with the selected biomarkers. RESULTS: Only baseline lateral ventricle volume was able to identify a subgroup of prodromal AD patients who declined faster (interaction, p = 0.003). Lateral ventricle volume and medial temporal lobe measures were the biomarkers most sensitive to disease progression (interaction, p≤0.042). Enrichment through ventricular volume reduced the sample size that a clinical trial would require from 13 to 76%, depending on structural outcome variable. The biomarker needing the lowest sample size was the hippocampal subfield GC-ML-DG (granule cells of molecular layer of the dentate gyrus) (n = 82 per arm to demonstrate a 20% atrophy reduction). CONCLUSION: MRI structural biomarkers can enrich prodromal AD with fast progressors and significantly decrease group size in clinical trials of disease modifying drugs.

Prediction and Early Detection of Alzheimer's Dementia: Professional Disclosure Practices and Ethical Attitudes. - Schweda, Mark; Kögel, Anna; Bartels, Claudia; Wiltfang, Jens; Schneider, Anja; Schicktanz, Silke (J Alzheimers Dis, 2018)
BACKGROUND: Biomarker-supported testing for preclinical and prodromal Alzheimer's disease (AD) finds its way into clinical practice. Professional attitudes and practices regarding disclosure and ethical issues are controversial in many countries. OBJECTIVES: Against this background, the objective was to survey the actual practice and the attitudes of physicians in German hospitals and memory clinics in order to explore possible practical insecurities and ethical concerns. METHODS: A detailed survey with 37 items was conducted among medical professionals at German hospitals and memory clinics (n = 108). Analyses were performed using SPSS 21.0 (IBM). Findings were based on frequency and percentage distribution. RESULTS: Nearly half of the respondents stated that persons with mild cognitive impairment and pathological cerebrospinal fluid biomarkers were informed they had or would soon develop AD. While 81% acknowledged a 'right not to know', 75% said that results were always communicated. A majority agreed there was a benefit of prediction or later life planning [end-of-life, financial, family, housing (73-75%)] but also expected high psychological stress (82%) and self-stigmatization (70%) for those tested. CONCLUSIONS: There is considerable heterogeneity and insecurity regarding prediction and early detection in the context of AD in Germany. Information of professionals and standardization of professional testing and disclosure practices are needed.

Predictors of Age of Diagnosis and Survival of Alzheimer's Disease in Down Syndrome. - Sinai, Amanda; Mokrysz, Claire; Bernal, Jane; Bohnen, Ingrid; Bonell, Simon; Courtenay, Ken; Dodd, Karen; Gazizova, Dina; Hassiotis, Angela; Hillier, Richard; McBrien, Judith; McCarthy, Jane; et al. (J Alzheimers Dis, 2018)
BACKGROUND: People with Down syndrome (DS) are an ultra-high risk population for Alzheimer's disease (AD). Understanding the factors associated with age of onset and survival in this population could highlight factors associated with modulation of the amyloid cascade. OBJECTIVE: This study aimed to establish the typical age at diagnosis and survival associated with AD in DS and the risk factors associated with these. METHODS: Data was obtained from the Aging with Down Syndrome and Intellectual Disabilities (ADSID) research database, consisting of data extracted from clinical records of patients seen by Community Intellectual Disability Services (CIDS) in England. Survival times when considering different risk factors were calculated. RESULTS: The mean age of diagnosis was 55.80 years, SD 6.29. Median survival time after diagnosis was 3.78 years, and median age at death was approximately 60 years. Survival time was associated with age of diagnosis, severity of intellectual disability, living status, anti-dementia medication status, and history of epilepsy. Age at diagnosis and treatment status remained predictive of survival time following adjustment. CONCLUSION: This study provides the best estimate of survival in dementia within the DS population to date, and is in keeping with previous estimates from smaller studies in the DS population. This study provides important estimates and insights into possible predictors of survival and age of diagnosis of AD in adults with DS, which will inform selection of participants for treatment trials in the future.
Keywords: Age of Onset; Alzheimer Disease; Down Syndrome; England; Female; Humans; Male; Middle Aged; Risk Factors; Survival Analysis

Preserved Structural Network Organization Mediates Pathology Spread in Alzheimer's Disease Spectrum Despite Loss of White Matter Tract Integrity. - Powell, Fon; Tosun, Duygu; Sadeghi, Roksana; Weiner, Michael; Raj, Ashish (J Alzheimers Dis, 2018)
Models of Alzheimer's disease (AD) hypothesize stereotyped progression via white matter (WM) fiber connections, most likely via trans-synaptic transmission of toxic proteins along neuronal pathways. An important question in the field is whether and how organization of fiber pathways is affected by disease. It remains unknown whether fibers act as conduits of degenerative pathologies, or if they also degenerate with the gray matter network. This work uses graph theoretic modeling in a longitudinal design to investigate the impact of WM network organization on AD pathology spread. We hypothesize if altered WM network organization mediates disease progression, then a previously published network diffusion model will yield higher prediction accuracy using subject-specific connectomes in place of a healthy template connectome. Neuroimaging data in 124 subjects from ADNI were assessed. Graph topology metrics show preserved network organization in patients compared to controls. Using a published diffusion model, we further probe the effect of network alterations on degeneration spread in AD. We show that choice of connectome does not significantly impact the model's predictive ability. These results suggest that, despite measurable changes in integrity of specific fiber tracts, WM network organization in AD is preserved. Further, there is no difference in the mediation of putative pathology spread between healthy and AD-impaired networks. This conclusion is somewhat at variance with previous results, which report global topological disturbances in AD. Our data indicates the combined effect of edge thresholding, binarization, and inclusion of subcortical regions to network graphs may be responsible for previously reported effects.

Prevalence, Safety, and Effectiveness of Oral Anticoagulant Use in People with and without Dementia or Cognitive Impairment: A Systematic Review and Meta-Analysis. - Fanning, Laura; Ryan-Atwood, Taliesin E; Bell, J Simon; Meretoja, Atte; McNamara, Kevin P; Dārziņš, Pēteris; Wong, Ian C K; Ilomäki, Jenni (J Alzheimers Dis, 2018)
BACKGROUND: Differences in management and outcomes of oral anticoagulant (OAC) use may exist for people with and without dementia or cognitive impairment (CI). OBJECTIVE: To systematically review the prevalence and safety and effectiveness outcomes of OAC use in people with and without dementia or CI. METHODS: MEDLINE, EMBASE, and CINAHL were searched for studies reporting prevalence or safety and effectiveness outcomes of OAC use for people with and without dementia, published between 2000 to September 2017. Study selection, data extraction, and quality assessment were performed by two reviewers. RESULTS: studies met pre-specified inclusion criteria (21 prevalence studies, 6 outcomes studies). People with dementia had 52% lower odds of receiving OAC compared to people without dementia. Mean OAC prevalence was 32% for people with dementia, compared to 48% without dementia. There was no difference in the composite outcome of embolic events, myocardial infarction, and all-cause death between dementia and non-dementia groups (adjusted hazard ratio (HR) 0.72, 95% CI, 0.45-1.14, p = 0.155). Bleeding rate was lower for people without dementia (HR 0.56, 95% CI, 0.37-0.85). Adverse warfarin events were more common for residents of long-term care with dementia (adjusted incidence rate ratio 1.48, 95% CI, 1.20-1.82). Community-dwelling people with dementia treated with warfarin had poorer anticoagulation control than those without dementia (mean time in therapeutic range (TTR) % ±SD, 38±26 (dementia), 61±27 (no dementia), p < 0.0001). CONCLUSION: A lower proportion of people with dementia received oral anticoagulation compared with people without dementia. People with dementia had higher bleeding risk and poorer anticoagulation control when treated with warfarin.

Progress of Brain Amyloid Deposition in Familial Alzheimer's Disease with Taiwan D678H APP Mutation. - Weng, Yi-Ching; Hsiao, Ing-Tsung; Huang, Chu-Yun; Huang, Kuo-Lun; Liu, Chi-Hung; Chang, Ting-Yu; Yen, Tzu-Chen; Lin, Kun-Ju; Huang, Chin-Chang (J Alzheimers Dis, 2018)
BACKGROUND: The amyloid AV-45 (florbetapir) positron emission tomography (PET) has been used in the study of the familial Alzheimer's disease (FAD) with the D678H amyloid precursor protein (APP) mutation. In addition, the progress of the disease remains unknown. OBJECTIVE: We aim to investigate the progression rate of amyloid accumulation in FAD patients with this mutation by neuroimages analysis. METHODS: The clinical course, changes in cognitive function, brain magnetic resonance imaging (MRI) and 18F-AV-45 PET scan were investigated in FAD patients and sporadic AD (sAD) patients. We compared the amyloid deposition pattern in serial brain 18F-AV-45 PET scan among the FAD, familial mild cognitive impairment (FMCI), and sMCI and sAD patients. RESULTS: Seven familial patients received a follow-up survey. The follow up duration for brain AV-45 PET was from 1.54 to 3.61 years. In 4 FMCI patients, an increased regional SUVR was noted, and the annual change rates were increased from 1.03% to 18.82%. However, a decreased regional SUVR was noted in 3 FAD patients and the annual change rates were from -2.62% to -16.03%. As compared with the sAD and sMCI patients, the annual change rate is statistically significant in FAD and FMCI patients respectively. CONCLUSIONS: The data indicate a biphasic course with an initial increase and then a decrease of SUVR in brain amyloid PET scan in familial APP mutation patients. The data also reveal that the novel Taiwan APP (D678H) mutation has a more amyloid burden than the sAD patients, particularly in an MCI stage.

Prominent Non-Memory Deficits in Alzheimer's Disease Are Associated with Faster Disease Progression. - Scheltens, Nienke M E; Tijms, Betty M; Heymans, Martijn W; Rabinovici, Gil D; Cohn-Sheehy, Brendan I; Miller, Bruce L; Kramer, Joel H; Wolfsgruber, Steffen; Wagner, Michael; Kornhuber, Johannes; Peters, Oliver; Scheltens, Philip; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is a heterogeneous disorder. OBJECTIVE: To investigate whether cognitive AD subtypes are associated with different rates of disease progression. METHODS: We included 1,066 probable AD patients from the Amsterdam Dementia Cohort (n = 290), Alzheimer's Disease Neuroimaging Initiative (n = 268), Dementia Competence Network (n = 226), and University of California, San Francisco (n = 282) with available follow-up data. Patients were previously clustered into two subtypes based on their neuropsychological test results: one with most prominent memory impairment (n = 663) and one with most prominent non-memory impairment (n = 403). We examined associations between cognitive subtype and disease progression, as measured with repeated Mini-Mental State Examination (MMSE) and Clinical Dementia Rating scale sum of boxes (CDR sob), using linear mixed models. Furthermore, we investigated mortality risk associated with subtypes using Cox proportional hazard analyses. RESULTS: Patients were 71±9 years old; 541 (51%) were female. At baseline, pooled non-memory patients had worse MMSE scores (23.1±0.1) and slightly worse CDR sob (4.4±0.1) than memory patients (MMSE 24.0±0.1; p < 0.001; CDR sob 4.1±0.1; p < 0.001). During follow-up, pooled non-memory patients showed steeper annual decline in MMSE (-2.8±0.1) and steeper annual increase in CDR sob (1.8±0.1) than memory patients (MMSE - 1.9±0.1; pinteraction<0.001; CDR sob 1.3±0.1; pinteraction<0.001). Furthermore, the non-memory subtype was associated with an increased risk of mortality compared with the memory subtype at trend level (HR = 1.36, CI = 1.00-1.85, p = 0.05). CONCLUSIONS: AD patients with most prominently non-memory impairment show faster disease progression and higher risk of mortality than patients with most prominently memory impairment.

Protective Effects of Indian Spice Curcumin Against Amyloid-β in Alzheimer's Disease. - Reddy, P Hemachandra; Manczak, Maria; Yin, XiangLing; Grady, Mary Catherine; Mitchell, Andrew; Tonk, Sahil; Kuruva, Chandra Sekhar; Bhatti, Jasvinder Singh; Kandimalla, Ramesh; Vijayan, Murali; Kumar, Subodh; Wang, Rui; et al. (J Alzheimers Dis, 2018)
The purpose of our article is to assess the current understanding of Indian spice, curcumin, against amyloid-β (Aβ)-induced toxicity in Alzheimer's disease (AD) pathogenesis. Natural products, such as ginger, curcumin, and gingko biloba have been used as diets and dietary supplements to treat human diseases, including cancer, cardiovascular, respiratory, infectious, diabetes, obesity, metabolic syndromes, and neurological disorders. Products derived from plants are known to have protective effects, including anti-inflammatory, antioxidant, anti-arthritis, pro-healing, and boosting memory cognitive functions. In the last decade, several groups have designed and synthesized curcumin and its derivatives and extensively tested using cell and mouse models of AD. Recent research on Aβ and curcumin has revealed that curcumin prevents Aβ aggregation and crosses the blood-brain barrier, reach brain cells, and protect neurons from various toxic insults of aging and Aβ in humans. Recent research has also reported that curcumin ameliorates cognitive decline and improves synaptic functions in mouse models of AD. Further, recent groups have initiated studies on elderly individuals and patients with AD and the outcome of these studies is currently being assessed. This article highlights the beneficial effects of curcumin on AD. This article also critically assesses the current limitations of curcumin's bioavailability and urgent need for new formulations to increase its brain levels to treat patients with AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Blood-Brain Barrier; Curcumin; Disease Models, Animal; Humans; Mice; Neuroprotective Agents; Randomized Controlled Trials as Topic; Spices

Protofibrillar and Fibrillar Amyloid-β Binding Proteins in Cerebrospinal Fluid. - Rahman, M Mahafuzur; Westermark, Gunilla T; Zetterberg, Henrik; Härd, Torleif; Sandgren, Mats (J Alzheimers Dis, 2018)
Aggregation and deposition of misfolded amyloid-β (Aβ) peptide in the brain is central to Alzheimer's disease (AD). Oligomeric, protofibrillar, and fibrillar forms of Aβ are believed to be neurotoxic and cause neurodegeneration in AD, but the toxicity mechanisms are not well understood and may involve Aβ-interacting molecular partners. In a previous study, we identified potential Aβ42 protofibrillar-binding proteins in serum and cerebrospinal fluid (CSF) using an engineered version of Aβ42 (Aβ42CC) that forms protofibrils, but not fibrils. Here we studied binding of proteins to Aβ42 fibrils in AD and non-AD CSF and compared these with protofibrillar Aβ42CC-binding partners. Aβ42 fibrils sequestered 2.4-fold more proteins than Aβ42CC protofibrils. Proteins with selective binding to fibrillar aggregates with low nanomolar affinity were identified. We also found that protofibrillar and fibrillar Aβ-binding proteins represent distinct functional categories. Aβ42CC protofibrils triggered interactions with proteins involved in catalytic activities, like transferases and oxidoreductases, while Aβ42 fibrils were more likely involved in binding to proteoglycans, growth factors and neuron-associated proteins, e.g., neurexin-1, -2, and -3. Interestingly, 10 brain-enriched proteins were identified among the fibril-binding proteins, while protofibril-extracted proteins had more general expression patterns. Both types of Aβ aggregates bound several extracellular proteins. Additionally, we list a set of CSF proteins that might have potential to discriminate between AD and non-AD CSF samples. The results may be of relevance both for biomarker studies and for studies of Aβ-related toxicity mechanisms.

Psychological and Mnemonic Benefits of Nostalgia for People with Dementia. - Ismail, Sanda; Christopher, Gary; Dodd, Emily; Wildschut, Tim; Sedikides, Constantine; Ingram, Tom A; Jones, Roy W; Noonan, Krist A; Tingley, Danielle; Cheston, Richard (J Alzheimers Dis, 2018)
BACKGROUND: Studies with non-clinical populations show that nostalgia increases psychological resources, such as self-esteem and social connectedness. OBJECTIVES: Our objectives were to find out if the benefits of nostalgia in non-clinical populations generalize to people with dementia and if nostalgia facilitates recall of dementia-related information. METHODS: All three experiments recruited participants with mild or moderate levels of dementia. Experiment 1 tested whether nostalgia (compared to control) enhances psychological resources among 27 participants. Experiment 2 used music to induce nostalgia (compared to control) in 29 participants. Experiment 3 compared recall for self-referent dementia statements among 50 participants randomized to either a nostalgia or control condition. Findings across experiments were synthesized with integrative data analysis. RESULTS: Nostalgia (compared to control) significantly increased self-reported social connectedness, meaning in life, self-continuity, optimism, self-esteem, and positive (but not negative) affect (Experiments 1-3). Compared to controls, nostalgic participants also recalled significantly more self-referent dementia-related information (Experiment 3). CONCLUSION: This series of experiments extends social psychological research with non-clinical populations into dementia care, providing evidence that nostalgia significantly enhances psychological resources. The finding that nostalgia increased recall of self-referent statements about dementia suggests that this emotion lends participants the fortitude to face the threat posed by their illness. The finding has potentially important clinical implications both for the development of reminiscence therapy and for facilitating adjustment to a diagnosis of dementia.

Putative Dementia Cases Fluctuate as a Function of Mini-Mental State Examination Cut-Off Points. - Rosa, Ilka M; Henriques, Ana G; Wiltfang, Jens; da Cruz E Silva, Odete A B (J Alzheimers Dis, 2018)
As the population ages, there is a growing need to quickly and accurately identify putative dementia cases. Many cognitive tests are available; among those commonly used are the Cognitive Dementia Rating (CDR) and the Mini-Mental Status Examination (MMSE). The aim of this work was to compare the validity and reliability of these cognitive tests in a primary care based cohort (pcb-Cohort). The MMSE and the CDR were applied to 568 volunteers in the pcb-Cohort. Distinct cut-off points for the MMSE were considered, namely MMSE 27, MMSE 24, and MMSE PT (adapted for the Portuguese population). The MMSE 27 identified the greatest number of putative dementia cases, and, as determined by the ROC curve, it was the most sensitive and specific of the MMSE cut-offs considered. Putative predictive or risk factors identified included age, literacy, depression, and diabetes mellitus (DM). DM has previously been indicated as a risk factor for dementia and Alzheimer's disease. Comparatively, the MMSE 27 cut-off has the greatest sensibility (94.9%) and specificity (66.3%) when compared to MMSE PT and MMSE 24. Upon comparing MMSE and CDR scores, the latter identified a further 146 putative dementia cases, thus permitting one to propose that in an ideal situation, both tests should be employed. This increases the likelihood of identifying putative dementia cases for subsequent follow up work, thus these cognitive tests represent important tools in patient care. Further, this is a significant study for Portuguese populations, where few of these studies have been carried out.
Keywords: Age Factors; Aged; Aged, 80 and over; Cohort Studies; Community Health Planning; Cross-Sectional Studies; Dementia; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Neuropsychological Tests; ROC Curve

Quality of Life, Care Resource Use, and Costs of Dementia in 8 European Countries in a Cross-Sectional Cohort of the Actifcare Study. - Handels, Ron L H; Sköldunger, Anders; Bieber, Anja; Edwards, Rhiannon Tudor; Gonçalves-Pereira, Manuel; Hopper, Louise; Irving, Kate; Jelley, Hannah; Kerpershoek, Liselot; Marques, Maria J; Meyer, Gabriele; Michelet, Mona; et al. (J Alzheimers Dis, 2018)
BACKGROUND: With 10.5 million people with dementia in Europe and $301 billion associated costs, governments face challenges organizing access to care. OBJECTIVE: To examine the costs related to formal and informal care use and quality of life for people with dementia in eight European countries, and explore the association with unmet needs. METHODS: Cross-sectional data from 451 persons with dementia and their informal caregivers of the Actifcare cohort study were obtained. Formal and informal care use was multiplied by country specific unit prices of services. Needs were measured using the CANE and health-related quality of life (HRQOL) of the person with dementia (both self- and proxy-rated) and informal caregiver's quality of life using EQ-5D-5L, ICECAP-O, DEMQOL-U, and CarerQol utility scores. The association between costs and country, European region, and unmet needs was assessed using multi-level linear regression. RESULTS: Self-rated EQ-5D-5L utility score was higher than proxy-rated (0.84 and 0.71, respectively). Informal caregivers' utility score was 0.84. Across eight countries annual mean costs of formal and informal care were approximately € 17,000. Unmet needs were not associated with annual costs of care, nor with proxy-rated HRQOL, but were associated with self-rated HRQOL. CONCLUSION: We found varying relationships between unmet needs and quality of life, and no association between unmet needs and care costs, although the results were sensitive to various factors. Future research should further investigate the relation between unmet needs, quality of life and costs to generate a better understanding of the effects of (un)timely access to care.

Quantifying the Diagnostic Pathway for Patients with Cognitive Impairment: Real-World Data from Seven European and North American Countries. - Ritchie, Craig W; Black, Christopher M; Khandker, Rezaul K; Wood, Robert; Jones, Eddie; Hu, Xiaohan; Ambegaonkar, Baishali M (J Alzheimers Dis, 2018)
To ensure that patients with dementia and their caregivers receive appropriate treatment and support, early diagnosis is essential but remains challenging. Real-world data from a multi-national, cross-sectional survey of physicians and their patients were analyzed to quantify the diagnostic pathway for dementia, including a focus on severity of patients' cognitive impairment (CI) at the time of symptom onset, referral and subsequent diagnosis. Data were collected for 7,620 patients with CI. Most patients saw a healthcare professional within 1 year of first symptoms and received a diagnosis within 3-7 months of initial consultation. However, only 20% of patients received a diagnosis before their disease progressed beyond the prodromal stage and 23.5% already had moderate CI at diagnosis. These findings show that the goal of identifying and diagnosing CI at the earliest stages of disease is, for many patients, not achieved. Efforts toward public awareness and proactive, earlier detection and intervention, must be maintained-indeed where possible invigorated.

Quantitative Genetics Validates Previous Genetic Variants and Identifies Novel Genetic Players Influencing Alzheimer's Disease Cerebrospinal Fluid Biomarkers. - Ramos de Matos, Mafalda; Ferreira, Catarina; Herukka, Sanna-Kaisa; Soininen, Hilkka; Janeiro, André; Santana, Isabel; Baldeiras, Ines; Almeida, Maria Rosário; Lleo, Alberto; Dols-Icardo, Oriol; Alcolea, Daniel; Benussi, Luisa; et al. (J Alzheimers Dis, 2018)
Cerebrospinal fluid (CSF) biomarkers have been extensively investigated in the Alzheimer's disease (AD) field, and are now being applied in clinical practice. CSF amyloid-beta (Aβ1-42), total tau (t-tau), and phosphorylated tau (p-tau) reflect disease pathology, and may be used as quantitative traits for genetic analyses, fostering the identification of new genetic factors and the proposal of novel biological pathways of the disease. In patients, the concentration of CSF Aβ1-42 is decreased due to the accumulation of Aβ1-42 in amyloid plaques in the brain, while t-tau and p-tau levels are increased, indicating the extent of neuronal damage. To better understand the biological mechanisms underlying the regulation of AD biomarkers, and its relation to AD, we examined the association between 36 selected single nucleotide polymorphisms (SNPs) and AD biomarkers Aβ1-42, t-tau, and p-tau in CSF in a cohort of 672 samples (571 AD patients and 101 controls) collected within 10 European consortium centers.Our results highlighted five genes, APOE, LOC100129500, PVRL2, SNAR-I, and TOMM40, previously described as main players in the regulation of CSF biomarkers levels, further reinforcing a role for these in AD pathogenesis. Three new AD susceptibility loci, INPP5D, CD2AP, and CASS4, showed specific association with CSF tau biomarkers. The identification of genes that specifically influence tau biomarkers point out to mechanisms, independent of amyloid processing, but in turn related to tau biology that may open new venues to be explored for AD treatment.

Rab10 Phosphorylation is a Prominent Pathological Feature in Alzheimer's Disease. - Yan, Tingxiang; Wang, Luwen; Gao, Ju; Siedlak, Sandra L; Huntley, Mikayla L; Termsarasab, Pichet; Perry, George; Chen, Shu G; Wang, Xinglong (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is the leading cause of dementia in the elderly, characterized by neurofibrillary tangles (NFTs), senile plaques (SPs), and a progressive loss of neuronal cells in selective brain regions. Rab10, a small Rab GTPase involved in vesicular trafficking, has recently been identified as a novel protein associated with AD. Interestingly, Rab10 is a key substrate of leucine-rich repeat kinase 2 (LRRK2), a serine/threonine protein kinase genetically associated with the second most common neurodegenerative disease Parkinson's disease. However, the phosphorylation state of Rab10 has not yet been investigated in AD. Here, using a specific antibody recognizing LRRK2-mediated Rab10 phosphorylation at the amino acid residue threonine 73 (pRab10-T73), we performed immunocytochemical analysis of pRab10-T73 in hippocampal tissues of patients with AD. pRab10-T73 was prominent in NFTs in neurons within the hippocampus in all cases of AD examined, whereas immunoreactivity was very faint in control cases. Other characteristic AD pathological structures including granulovacuolar degeneration, dystrophic neurites and neuropil threads also contained pRab10-T73. The pRab10-T73 immunoreactivity was diminished greatly following dephosphorylation with alkaline phosphatase. pRab10-T73 was further found to be highly co-localized with hyperphosphorylated tau (pTau) in AD, and demonstrated similar pathological patterns as pTau in Down syndrome and progressive supranuclear palsy. Although pRab10-T73 immunoreactivity could be noted in dystrophic neurites surrounding SPs, SPs were largely negative for pRab10-T73. These findings indicate that Rab10 phosphorylation could be responsible for aberrations in the vesicle trafficking observed in AD leading to neurodegeneration.

Rationale and Design of the Mechanistic Potential of Antihypertensives in Preclinical Alzheimer's (HEART) Trial. - Wharton, Whitney; Goldstein, Felicia C; Tansey, Malú G; Brown, Alexandra L; Tharwani, Sonum D; Verble, Danielle D; Cintron, Amarallys; Kehoe, Patrick G (J Alzheimers Dis, 2018)
Research indicates that certain antihypertensive medications alter Alzheimer's disease (AD) biomarkers in Caucasians. The renin angiotensin system (RAS) regulates blood pressure (BP) in the body and the brain and may directly influence AD biomarkers, including amyloid-β (Aβ) neuropathology, cerebral blood flow (CBF), and inflammatory markers. This hypothesis is supported by studies, including ours, showing that antihypertensives targeting the RAS reduce the risk and slow the progression of AD in Caucasians. While mounting evidence supports a protective role of RAS medications in Caucasians, this mechanism has not been explored in African Americans. To assess the mechanism by which RAS medications modify the brain RAS, cerebrospinal fluid (CSF) Aβ, CBF, and inflammatory markers in African Americans, we are conducting an eight month, Phase Ib randomized, placebo controlled trial, enrolling 60 middle-aged (45-70 years), non-demented individuals, at risk for AD by virtue of a parental history. Participants include normotensive and treated hypertensives that have never been exposed to a RAS medication. Participants are randomized (1 : 1:1) by gender and BP medication use (yes/no) to one of three groups: placebo, or 20 mg, or 40 mg telmisartan (Micardis), to determine the dose required to penetrate the CNS. Our overarching hypothesis is that, compared to placebo, both doses of telmisartan will penetrate the CNS and produce salutary, dose dependent effects on the brain RAS as well as CSF Aβ, CBF, and CSF inflammatory markers in African Americans, over eight months. This manuscript describes the trial rationale and design.
Keywords: African Americans; Aged; Alzheimer Disease; Amyloid beta-Peptides; Antihypertensive Agents; Biomarkers; Blood Pressure; Brain; Clinical Trials, Phase I as Topic; Female; Georgia; Humans; Linear Models; Male; Middle Aged; Randomized Controlled Trials as Topic; Renin-Angiotensin System; Telmisartan

The Rationale and Design of the Reducing Pathology in Alzheimer's Disease through Angiotensin TaRgeting (RADAR) Trial. - Kehoe, Patrick G; Blair, Peter S; Howden, Beth; Thomas, David L; Malone, Ian B; Horwood, Jeremy; Clement, Clare; Selman, Lucy E; Baber, Hannah; Lane, Athene; Coulthard, Elizabeth; Passmore, Anthony Peter; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Anti-hypertensives that modify the renin angiotensin system may reduce Alzheimer's disease (AD) pathology and reduce the rate of disease progression. OBJECTIVE: To conduct a phase II, two arm, double-blind, placebo-controlled, randomized trial of losartan to test the efficacy of Reducing pathology in Alzheimer's Disease through Angiotensin TaRgeting (RADAR). METHODS: Men and women aged at least 55 years with mild-to-moderate AD will be randomly allocated 100 mg encapsulated generic losartan or placebo once daily for 12 months after successful completion of a 2-week open-label phase and 2-week placebo washout to establish drug tolerability. 228 participants will provide at least 182 subjects with final assessments to provide 84% power to detect a 25% difference in atrophy rate (therapeutic benefit) change over 12 months at an alpha level of 0.05. We will use intention-to-treat analysis, estimating between-group differences in outcomes derived from appropriate (linear or logistic) multivariable regression models adjusting for minimization variables. RESULTS: The primary outcome will be rate of whole brain atrophy as a surrogate measure of disease progression. Secondary outcomes will include changes to 1) white matter hyperintensity volume and cerebral blood flow; 2) performance on a standard series of assessments of memory, cognitive function, activities of daily living, and quality of life. Major assessments (for all outcomes) and relevant safety monitoring of blood pressure and bloods will be at baseline and 12 months. Additional cognitive assessment will also be conducted at 6 months along with safety blood pressure and blood monitoring. Monitoring of blood pressure, bloods, and self-reported side effects will occur during the open-label phase and during the majority of the post-randomization dispensing visits. CONCLUSION: This study will identify whether losartan is efficacious in the treatment of AD and whether definitive Phase III trials are warranted.
Keywords: Activities of Daily Living; Alzheimer Disease; Antihypertensive Agents; Atrophy; Blood Pressure Monitors; Brain; Clinical Trials, Phase II as Topic; Disease Progression; Double-Blind Method; Female; Humans; Losartan; Magnetic Resonance Imaging; Male; Multivariate Analysis; Quality of Life; Randomized Controlled Trials as Topic; Regression Analysis; Renin-Angiotensin System

Regional Distribution, Asymmetry, and Clinical Correlates of Tau Uptake on [18F]AV-1451 PET in Atypical Alzheimer's Disease. - Tetzloff, Katerina A; Graff-Radford, Jonathan; Martin, Peter R; Tosakulwong, Nirubol; Machulda, Mary M; Duffy, Joseph R; Clark, Heather M; Senjem, Matthew L; Schwarz, Christopher G; Spychalla, Anthony J; Drubach, Daniel A; Jack, Clifford R; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Despite common pathology, Alzheimer's disease (AD) can have multiple clinical presentations which pathological studies suggest result from differences in the regional distribution of tau pathology. Positron emission tomography (PET) ligands are now available that can detect tau proteins in vivo and hence can be used to investigate the biological mechanisms underlying atypical AD. OBJECTIVE: To assess regional patterns of tau uptake on PET imaging in two atypical AD variants, posterior cortical atrophy (PCA) and logopenic progressive aphasia (lvPPA). METHODS: Eighteen PCA and 19 lvPPA subjects that showed amyloid-β deposition on PET underwent tau-PET imaging with [18F]AV-1451. Group comparisons of tau uptake in PCA and lvPPA were performed using voxel-level and regional-level analyses. We also assessed the degree of lobar tau asymmetry and correlated regional tau uptake to age and performance on clinical evaluations. RESULTS: Both syndromes showed diffuse tau uptake throughout all cortical regions, although PCA showed greater uptake in occipital regions compared to lvPPA, and lvPPA showed greater uptake in left frontal and temporal regions compared to PCA. While lvPPA showed predominant left-asymmetric tau deposition, PCA was more bilateral. Younger subjects showed greater tau uptake bilaterally in frontal and parietal lobes than older subjects, and sentence repetition, Boston naming test, simultanagnosia, and visuoperceptual function showed specific regional tau correlates. CONCLUSION: Tau deposition is closely related to clinical presentation in atypical AD with age playing a role in determining the degree of cortical tau deposition.

Relationship Between Amyloid-β Positivity and Progression to Mild Cognitive Impairment or Dementia over 8 Years in Cognitively Normal Older Adults. - Dang, Christa; Harrington, Karra D; Lim, Yen Ying; Ames, David; Hassenstab, Jason; Laws, Simon M; Yassi, Nawaf; Hickey, Martha; Rainey-Smith, Stephanie; Robertson, Joanne; Sohrabi, Hamid R; Salvado, Olivier; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Preclinical Alzheimer's disease (AD) is defined by cerebral amyloid-β positivity (Aβ+) in cognitively normal (CN) older adults. OBJECTIVE: To estimate the risk of progression to the symptomatic stages of AD due to PET Aβ+ and the extent that progression was influenced by other demographic, genetic, and clinical characteristics in a large prospective study. METHODS: Fine-Gray subdistribution modeling was used to examine the risk of progression from CN to MCI/dementia due to Aβ+, APOEɛ4 carriage, and their interaction in the Australian Imaging, Biomarkers and Lifestyle (AIBL) flagship study of aging CN cohort (n = 599) over 8 years. RESULTS: 17.7% Aβ+ and 8.1% Aβ-progressed over 8 years (OR: 2.43). Risk of progression for Aβ+ was 65-104% greater than Aβ-. Aβ+ APOEɛ4 carriers were at 348% greater risk than all other participants. Significant risk factors of progression in Aβ+ were age (HR: 1.05), PET SUVR (HR: 2.49) and APOE ɛ4 carriage (HR: 2.63); only age was a significant risk factor in Aβ-(HR: 1.09). Aβ-progressors were not near the threshold for Aβ+. These relationships were not moderated by hypertension, diabetes, obesity, or stroke/TIA. CONCLUSION: Aβ+ is an important prognostic marker for progression from CN to MCI/dementia in older adults and APOEɛ4 carriage provides further predictive value in the presence of Aβ+. These data suggest that Aβ-associated clinical progression is consistent with clinical-pathological models of AD, whereas progression in the absence of elevated Aβ deposition may be the result of neuropathological processes other than AD that accumulate with age.

Relationship Between Body Mass Index, ApoE4 Status, and PET-Based Amyloid and Neurodegeneration Markers in Amyloid-Positive Subjects with Normal Cognition or Mild Cognitive Impairment. - Blautzik, Janusch; Kotz, Sebastian; Brendel, Matthias; Sauerbeck, Julia; Vettermann, Franziska; Winter, Yaroslav; Bartenstein, Peter; Ishii, Kazunari; Rominger, Axel (J Alzheimers Dis, 2018)
Body weight loss in late-life is known to occur at a very early stage of Alzheimer's disease (AD). Apolipoprotein E4 (ApoE4) represents a major genetic risk factor for AD and is linked to an increased cortical amyloid-β (Aβ) accumulation. Since the relationship between body weight, ApoE4, and AD pathology is poorly investigated, we aimed to evaluate whether ApoE4 allelic status modifies the association of body mass index (BMI) with markers of AD pathology. A total of 368 Aβ-positive cognitively healthy or mild cognitive impaired subjects had undergone [18F]-AV45-PET, [18F]-FDG-PET, and T1w-MRI examinations. Composite cortical [18F]-AV45 uptake and [18F]-FDG uptake in posterior cingulate cortex were calculated as surrogates of cortical Aβ load and glucose metabolism, respectively. Multiple linear regressions were performed to assess the relationships between these PET biomarkers with BMI, present cognitive performance, and cognitive changes over time. Multivariate analysis of covariance was conducted to test for statistical differences between ApoE4/BMI categories on the PET markers and cognitive scores. In carriers of the ApoE4 allele only, BMI was inversely associated with cortical amlyoid load (β= -0.193, p < 0.005) and recent cognitive decline (β= -0.209, p < 0.05), and positively associated with cortical glucose metabolism in an AD-vulnerable region (β= 0.145, p < 0.05). ApoE4/BMI category analyses demonstrated lower Aβ load, higher posterior cingulate glucose metabolism, improved cognitive performance, and lower progression of cognitive decline in obese ApoE4 carriers. The effect of ApoE4 in promoting the accumulation of cortical amyoid, which may itself be a driver for weight loss, may be moderated by altering leptin signaling in the hypothalamus.

The Relevance of Iron in the Pathogenesis of Multiple System Atrophy: A Viewpoint. - Kaindlstorfer, Christine; Jellinger, Kurt A; Eschlböck, Sabine; Stefanova, Nadia; Weiss, Günter; Wenning, Gregor K (J Alzheimers Dis, 2018)
Iron is essential for cellular development and maintenance of multiple physiological processes in the central nervous system. The disturbance of its homeostasis leads to abnormal iron deposition in the brain and causes neurotoxicity via generation of free radicals and oxidative stress. Iron toxicity has been established in the pathogenesis of Parkinson's disease; however, its contribution to multiple system atrophy (MSA) remains elusive. MSA is characterized by cytoplasmic inclusions of misfolded α-synuclein (α-SYN) in oligodendrocytes referred to as glial cytoplasmic inclusions (GCIs). Remarkably, the oligodendrocytes possess high amounts of iron, which together with GCI pathology make a contribution toward MSA pathogenesis likely. Consistent with this observation, the GCI density is associated with neurodegeneration in central autonomic networks as well as olivopontocerebellar and striatonigral pathways. Iron converts native α-SYN into a β-sheet conformation and promotes its aggregation either directly or via increasing levels of oxidative stress. Interestingly, α-SYN possesses ferrireductase activity and α-SYN expression underlies iron mediated translational control via RNA stem loop structures. Despite a correlation between progressive putaminal atrophy and iron accumulation as well as clinical decline, it remains unclear whether pathologic iron accumulation in MSA is a secondary event in the cascade of neuronal degeneration rather than a primary cause. This review summarizes the current knowledge of iron in MSA and gives evidence for perturbed iron homeostasis as a potential pathogenic factor in MSA-associated neurodegeneration.
Keywords: alpha-Synuclein; Brain; Humans; Inclusion Bodies; Iron; Magnetic Resonance Imaging; Multiple System Atrophy; Oligodendroglia; Parkinsonian Disorders

Religious Orders Study and Rush Memory and Aging Project. - Bennett, David A; Buchman, Aron S; Boyle, Patricia A; Barnes, Lisa L; Wilson, Robert S; Schneider, Julie A (J Alzheimers Dis, 2018)
BACKGROUND: The Religious Orders Study and Rush Memory and Aging Project are both ongoing longitudinal clinical-pathologic cohort studies of aging and Alzheimer's disease (AD). OBJECTIVES: To summarize progress over the past five years and its implications for understanding neurodegenerative diseases. METHODS: Participants in both studies are older adults who enroll without dementia and agree to detailed longitudinal clinical evaluations and organ donation. The last review summarized findings through the end of 2011. Here we summarize progress and study findings over the past five years and discuss new directions for how these studies can inform on aging and AD in the future. RESULTS: We summarize 1) findings on the relation of neurobiology to clinical AD; 2) neurobiologic pathways linking risk factors to clinical AD; 3) non-cognitive AD phenotypes including motor function and decision making; 4) the development of a novel drug discovery platform. CONCLUSION: Complexity at multiple levels needs to be understood and overcome to develop effective treatments and preventions for cognitive decline and AD dementia.

Reproducibility of Alzheimer's Disease Cerebrospinal Fluid-Biomarker Measurements under Clinical Routine Conditions. - Vogelgsang, Jonathan; Wedekind, Dirk; Bouter, Caroline; Klafki, Hans-W; Wiltfang, Jens (J Alzheimers Dis, 2018)
Analysis of cerebrospinal fluid (CSF) is one of the key tools for the state-of-the-art differential diagnosis of dementias. Dementia due to Alzheimer's disease (AD) is characterized by elevated CSF levels of total Tau (tTau) and phospho-181-Tau (pTau) and low CSF amyloid-β42 (Aβ42). Discrepancies in the laboratory analysis of human materials are well known and much effort has been put into harmonization procedures. In this study, we measured CSF biomarkers of more than 100 patients obtained under clinical routine conditions in two different clinical laboratories. The CSF biomarker levels obtained from the two different sites were significantly correlated: R2 = 0.7129 (tTau, p < 0.001), 0.7914 (pTau, p < 0.001), 0.5078 (Aβ42, p < 0.001), 0.5739 (Aβ40, p < 0.001), and 0.4308 (Aβ42/40, p < 0.001). However, the diagnostic classifications of the Aβ42, tTau, and pTau levels of identical subjects into normal versus pathological range made by the two different sites showed substantial discrepancies (31.5%, 29.6%, and 25.0% discordant cases, respectively). Applying Aβ42/40, instead of CSF Aβ42 alone, lead to a reduction of the discordant cases to 16.8%. Our findings suggest that CSF Aβ42/40 can outperform Aβ42 as a biomarker for AD neuropathology, not only under well-controlled study conditions but also in real life clinical routine. Thus, we recommend the inclusion of Aβ42/40 as a CSF biomarker in the diagnostic procedure.

Risk Factors of Rapid Cognitive Decline in Alzheimer's Disease and Mild Cognitive Impairment: A Systematic Review and Meta-Analysis. - Song, Ya-Nan; Wang, Ping; Xu, Wei; Li, Jie-Qiong; Cao, Xi-Peng; Yu, Jin-Tai; Tan, Lan (J Alzheimers Dis, 2018)
BACKGROUND: The conclusions about risk factors for rapid cognitive decline (RCD) in Alzheimer's disease (AD) and mild cognitive impairment (MCI) remain contradictory. OBJECTIVE: To explore the factors predicting RCD in AD and MCI. METHODS: We searched the PubMed, EMBASE, and the Cochrane Library from inception to May 27, 2017 for studies investigating factors associated with faster cognitive progression in AD and MCI. Effect sizes were meta-analyzed using fixed-effects and random-effects models. RESULTS: Fifty-three studies with 14,330 patients (12,396 AD and 1,934 MCI) were included in the systematic review. The following factors were identified to increase the risk of RCD in AD: Apolipoprotein E4 (ApoE4) (SMD [95% CI]: 0.52 [0.06,0.98]), early age at onset (SMD [95% CI]: -0.42 [-0.71, -0.13]), high level of education (RR = 2.05, 95% CI = 1.26 to 3.33), early appearance of extrapyramidal signs (RR = 2.18; 95% CI = 1.30 to 3.67), and neuropsychiatric conditions including hallucination (RR = 2.01, 95% CI = 1.40 to 2.87), strolling (RR = 1.99, 95% CI = 1.38 to 2.86), agitation (RR = 1.66, 95% CI = 1.23 to 2.24), and psychosis (RR = 1.42, 95% CI = 1.07 to 1.89). Instead, advanced age (≥75 years) (RR = 0.96, 95% CI = 0.93 to 0.99), diabetes (RR = 0.57; 95% CI = 0.35 to 0.93), and multidrug therapy (RR = 0.61, 95% CI = 0.60 to 0.62) would lower the risk of RCD. Furthermore, systematic research also reviewed seven risk factors associated with RCD in MCI. CONCLUSION: ApoE4, early onset, early appearance of extrapyramidal signs, high education level, and neuropsychiatric conditions might increase the risk of RCD while older age, diabetes, and multidrug therapy were the protective factors for AD.

Risk of Alzheimer's Disease in Obstructive Sleep Apnea Syndrome: Amyloid-β and Tau Imaging. - Elias, Alby; Cummins, Tia; Tyrrell, Regan; Lamb, Fiona; Doré, Vincent; Williams, Robert; Rosenfeld, J V; Hopwood, Malcolm; Villemagne, Victor L; Rowe, Christopher C (J Alzheimers Dis, 2018)
BACKGROUND: An association between obstructive sleep apnea (OSA) and Alzheimer's disease has been suggested but little is known about amyloid-β and tau deposition in this syndrome. OBJECTIVE: To determine amyloid and tau burden and cognitive function in OSA in comparison with those without a diagnosis of OSA. METHODS: The status of OSA was determined by asking participants about history of polysomnographic diagnosis of OSA and the use of Continuous Positive Airway Pressure (CPAP). A comprehensive neuropsychological battery measured cognitive function. Positron emission tomography (PET) was used to measure standardized uptake value ratio (SUVR) of 18F-florbetaben and 18F-AV1451, to quantify amyloid and tau burden. RESULTS: 119 male Vietnam veterans completed assessment. Impairment in visual attention and processing speed and increased body mass index (BMI) were seen in subjects with OSA compared with those without a diagnosis OSA. The cortical uptake of 18F-florbetaben was higher in the OSA group than in the control group (SUVR: 1.35±0.21 versus 1.27±0.16, p = 0.04). There were more apolipoprotein E ɛ4 allele (APOE ɛ4) carriers in the OSA group than in the control group. In multilinear regression analysis, the significance of OSA in predicting 18F-florbetaben uptake remained independent of age and vascular risk factors but not when BMI or APOE ɛ4 was adjusted. The reported use of CPAP (n = 14) had no effect on cognitive or amyloid PET findings. There was no significant difference in 18F-AV1451 uptake between the two groups. CONCLUSIONS: Obstructive sleep apnea is associated with Alzheimer's disease pathology, but this relationship is moderated by APOE ɛ4 and BMI.

Role of Blood-Brain Barrier in Alzheimer's Disease. - Cai, Zhiyou; Qiao, Pei-Feng; Wan, Cheng-Qun; Cai, Min; Zhou, Nan-Kai; Li, Qin (J Alzheimers Dis, 2018)
The blood-brain barrier (BBB) is involved in the pathogenesis of Alzheimer's disease (AD). BBB is a highly selective semipermeable structural and chemical barrier which ensures a stable internal environment of the brain and prevents foreign objects invading the brain tissue. BBB dysfunction induces the failure of Aβ transport from brain to the peripheral circulation across the BBB. Especially, decreased levels of LRP-1 (low density lipoprotein receptor-related protein 1) and increased levels of RAGE (receptor for advanced glycation endproducts) at the BBB can cause the failure of Aβ transport. The pathogenesis of AD is related to the BBB structural components, including pericytes, astrocytes, vascular endothelial cells, and tight junctions. BBB dysfunction will trigger neuroinflammation and oxidative stress, then enhance the activity of β-secretase and γ-secretase, and finally promote Aβ generation. A progressive accumulation of Aβ in brain and BBB dysfunction may become a feedback loop that gives rise to cognitive impairment and the onset of dementia. The correlation between BBB dysfunction and tau pathology has been well-reported. Therefore, regulating BBB function may be a new therapeutic target for treating AD.

The Role of Lifestyle Factors and Sleep Duration for Late-Onset Dementia: A Cohort Study. - Larsson, Susanna C; Wolk, Alicja (J Alzheimers Dis, 2018)
BACKGROUND: The role of lifestyle factors and sleep for dementia is uncertain. OBJECTIVE: To examine the associations of major lifestyle factors and sleep duration with risk of late-onset dementia. METHODS: We used data from a population-based cohort of 28,775 Swedish adults who were ≥65 years of age and completed a questionnaire about lifestyle and other modifiable factors in the autumn of 1997. Dementia cases were ascertained by linkage with the Swedish National Patient Register. RESULTS: During a mean follow-up of 12.6 years, dementia was diagnosed among 3,755 participants (mean age at diagnosis 83.2±5.1 years). There were no associations of an overall healthy diet (defined by a modified Dietary Approaches to Stop Hypertension Diet score or a Mediterranean diet score), alcohol and coffee consumption, or physical activity with dementia incidence. Compared with never smokers, dementia risk was increased in former and current smokers (hazard ratio [95% confidence interval] = 1.13 [1.04-1.23] and 1.10 [1.00-1.21], respectively). Extended time of sleep (>9 h per night) was associated with an increased risk of dementia. However, this association appeared to be related to a reverse causation effect since the association did not remain after exclusion of cases diagnosed within the first five or ten years of follow-up. CONCLUSIONS: This study found no evidence that major lifestyle factors, aside from smoking, or sleep duration influence the risk of dementia.

Role of Noradrenergic Brain Nuclei in the Regulation of Carotid Artery Blood Flow: Pharmacological Evidence from Anesthetized Pigs with Alpha-2 Adrenergic Receptor Modulator Drugs. - Wirth, Klaus J (J Alzheimers Dis, 2018)
BACKGROUND: Cerebral hypoperfusion and degeneration of the noradrenergic locus coeruleus (LC) occur early in Alzheimer's disease (AD). Cerebral blood vessels are densely innervated by noradrenergic projections from the LC suggesting a functional role for the regulation of cerebral blood flow (CBF). Experimental LC stimulation, however, has provided no clarity as decreases or increases in CBF were reported from different experimental settings and investigators. OBJECTIVE: To find out with pharmacological methods whether endogenously released norepinephrine (NE) increases or decreases carotid artery blood flow (CABF) in anesthetized pigs by investigating the effect of centrally acting alpha-2 adrenergic drugs, which increase (atipamezole) or decrease (xylazine) NE in the brain. METHODS: CABF was measured by a Doppler-flow probe placed around the left carotid artery in pentobarbital anesthetized young pigs. RESULTS: Neither current antihypertensive drugs nor pharmacological stimulation of dopamine, histamine, serotonin or acetylcholine receptors changed CABF. The alpha-2 adrenergic-receptor agonist xylazine decreased, while the antagonist atipamezole raised CABF. This rise was abolished by a combined treatment with endothelial NO-synthase inhibitor Nω-Nitro-L-arginine methyl ester (L-NAME) and the non-selective β-receptor antagonist propranolol. Propranolol alone did not decrease CABF in contrast to L-NAME but decreased CABF after L-NAME, surprisingly. CONCLUSION: Pharmacological evidence suggests that NE released in the brain of anesthetized pigs raises CABF involving β-adrenergic mechanisms and nitric oxide. If in awake humans NE released from the LC had vasodilator effects early LC degeneration could be involved in early cerebral hypoperfusion of AD. Moreover, a cerebral adrenergic vascular innervation deficit, possibly resulting from LC degeneration, and systemic endothelial dysfunction together may act synergistically to reduce CBF.

Role of the Glyoxalase System in Alzheimer's Disease. - Jiang, Lianying; Wang, Jiafeng; Wang, Zhigang; Huang, Wenhui; Yang, Yixia; Cai, Zhiyou; Li, Keshen (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is an insidious and progressive neurodegenerative disease. The main pathological features of AD are the formation of amyloid-β deposits in the anterior cerebral cortex and hippocampus as well as the formation of intracellular neurofibrillary tangles. Thus far, accumulating evidence shows that glycation is closely related to AD. As a final product resulting from the crosslinking of a reducing sugar or other reactive carbonyls and a protein, the advanced glycation end products have been found to be associated with the formation of amyloid-β and neurofibrillary tangles in AD. As a saccharification inhibitor, the glyoxalase system and its substrate methylglyoxal (MG) were certified to be associated with AD onset and development. As an active substance of AGEs, MG could cause direct or indirect damage to nerve cells and tissues. MG is converted to D-lactic acid after decomposition by the glyoxalase system. Under normal circumstances, MG metabolism is in a dynamic equilibrium, whereas MG accumulates in cells in the case of aging or pathological states. Studies have shown that increasing glyoxalase activity and reducing the MG level can inhibit the generation of oxidative stress and AGEs, thereby alleviating the symptoms and signs of AD to some extent. This paper focuses on the relevant mechanisms of action of the glyoxalase system and MG in the pathogenesis of AD, as well as the potential of inhibiting the production of advanced glycation end products in the treatment of AD.

The Role of the Gut Microbiota in the Metabolism of Polyphenols as Characterized by Gnotobiotic Mice. - Pasinetti, Giulio Maria; Singh, Risham; Westfall, Susan; Herman, Francis; Faith, Jeremiah; Ho, Lap (J Alzheimers Dis, 2018)
A growing body of experimental data suggests that microbes in the gut influence behavior and can alter brain physiology and neurochemistry. Although promising, researchers are only starting to understand the potential of the gut microbiota for use in neurological disease. Recent evidence demonstrated that gastrointestinal activities are linked to mood disorders such as anxiety, depression, and most recently, cognitive functions in age-related neurodegenerative disorders. Studies from our group and others are uncovering new evidence suggesting that the gut microbiota plays a crucial role in the metabolism and bioavailability of certain dietary compounds and synthetic drugs. Based on this evidence, this review article will discuss the implications of the gut microbiota in mechanisms of bioavailability and biotransformation with an emphasis on dietary polyphenol compounds. This will be followed by a survey of ongoing innovative research identifying the ability of individual gut bacteria to enhance the bioavailability of gut-derived, brain-penetrating, bioactive polyphenol metabolites that ultimately influence mechanisms associated with the promotion of resilience against psychological and cognitive impairment in response to stress. Lastly, current research initiatives aimed at promoting the generation of brain bioactive polyphenol metabolites by specialized gut microbes will be discussed, specifically the use of gnotobiotic mice to develop bioengineered second generation probiotics. We propose that leveraging the gut microbial ecosystem to generate brain targeted bioactive metabolites from dietary polyphenols can attenuate lifestyle risk factors and promote resilience against age-related cognitive decline.

Sally-Anne Test in Patients with Alzheimer's Disease Dementia. - Takenoshita, Shintaro; Terada, Seishi; Yokota, Osamu; Kutoku, Yumiko; Wakutani, Yosuke; Nakashima, Makoto; Maki, Yohko; Hattori, Hideyuki; Yamada, Norihito (J Alzheimers Dis, 2018)
Social cognition has recently been recognized as one of the essential cognitive domains. Some reports suggested that patients with Alzheimer's disease dementia (ADD) presented significant theory of mind deficits even in the mild condition. However, most previous studies included only small numbers of patients with ADD. The present study administered the first-order false belief (Sally-Anne) test to 116 consecutive patients with ADD from the outpatient units of the Memory Clinic and compared the characteristics of the two groups with correct and incorrect answers on the test. Then various clinical characteristics were evaluated. Only 37.1% of patients with ADD correctly answered the Sally-Anne test with the right explanation. Comparison between the two groups of correct and incorrect answers revealed a significant association between the frontal assessment battery score and the result of the Sally-Anne test in the multiple logistic regression analyses. Thus, patients with ADD presented a significant deficit in social cognition even in the mild condition. Frontal dysfunction was thought to be related to the deficits in mild ADD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition Disorders; Disease Progression; Female; Humans; Logistic Models; Male; Neuropsychological Tests; Social Behavior Disorders; Theory of Mind

Severity-Related Increase and Cognitive Correlates of Serum VEGF Levels in Alzheimer's Disease ApoE4 Carriers. - Alvarez, X Anton; Alvarez, Irene; Aleixandre, Manuel; Linares, Carlos; Muresanu, Dafin; Winter, Stefan; Moessler, Herbert (J Alzheimers Dis, 2018)
Vascular endothelial growth factor (VEGF) is an angioneurin involved in the regulation of vascular and neural functions relevant for the pathophysiology of Alzheimer's disease (AD), but the influence of AD severity and ApoE4 status on circulating VEGF and its relationship with cognition has not been investigated. We assessed serum VEGF levels and cognitive performance in AD, amnestic mild cognitive impairment (MCI), and control subjects. VEGF levels were higher in AD patients than in MCI cases and controls (p < 0.05) and showed a progressive increase with clinical severity in the whole study population (p < 0.01). Among AD patients, severity-related VEGF elevations were significant in ApoE4 carriers (p < 0.05), but not in non-carriers. Increased VEGF levels were associated with disease severity and showed mild correlations with cognitive impairment that were only consistent for the ADAS-cog+ items remembering test instructions (memory) and maze task (executive functions) in the group of AD patients (p < 0.05). On the other hand, higher VEGF values were related to better memory and language performance in ApoE4 carriers with moderately-severe AD. According to these results showing severity- and ApoE4-related differences in serum VEGF and its cognitive correlates, it is suggested that increases in VEGF levels might represent an endogenous response driven by pathological factors and could entail cognitive benefits in AD patients, particularly in ApoE4 carriers. Our findings support the notion that VEGF constitutes a relevant molecular target to be further explored in AD pathology and therapy.

Simultaneous Aerobic Exercise and Memory Training Program in Older Adults with Subjective Memory Impairments. - McEwen, Sarah C; Siddarth, Prabha; Abedelsater, Berna; Kim, Yena; Mui, Wenli; Wu, Pauline; Emerson, Natacha D; Lee, Jacob; Greenberg, Shayna; Shelton, Tiffany; Kaiser, Scott; Small, Gary W; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Several modifiable lifestyle factors have been shown to have potential beneficial effects in slowing cognitive decline. Two such factors that may affect cognitive performance and slow the progression of memory loss into dementia in older adults are cognitive training and physical activity. There are currently no effective treatments for dementia; therefore, preventative strategies to delay or prevent the onset of dementia are of critical importance. OBJECTIVE: The aim of this study was to determine the relative effectiveness of simultaneous performance of memory training and aerobic exercise to a sequential performance intervention on memory functioning in older adults. METHODS: 55 older adults (aged 60- 75) with subjective memory impairments (non-demented and non-MCI) completed the intervention that consisted of 90-minute small group classes held twice weekly. Participants were randomized to either 4-weeks of supervised strategy-based memory training done simultaneously while stationary cycling (SIM) or sequentially after the stationary cycling (SEQ). Standardized neurocognitive measures of memory, executive functioning, speed of processing, attention, and cognitive flexibility were assessed at baseline and post-intervention. RESULTS: The SIM group, but not the SEQ group, had a significant improvement on composite memory following the intervention (t(51) = 2.7, p = 0.01, effect size (ES) = 0.42) and transfer to non-trained reasoning abilities (t(51) = 6.0, ES = 0.49) and complex attention (t(51) = 3.1, p = 0.003, ES = 0.70). Conversely, the SEQ group, but not the SIM, showed significant improvement in executive functioning (t(51) = 5.0, p = 0.0001, ES = 0.96). CONCLUSION: These findings indicate that a 4-week simultaneous memory training and aerobic exercise program is sufficient to improve memory, attention, and reasoning abilities in older adults.
Keywords: Aged; Attention; California; Cognition; Executive Function; Exercise; Female; Humans; Learning; Male; Memory; Memory Disorders; Middle Aged; Treatment Outcome

Single Subject Classification of Alzheimer's Disease and Behavioral Variant Frontotemporal Dementia Using Anatomical, Diffusion Tensor, and Resting-State Functional Magnetic Resonance Imaging. - Bouts, Mark J R J; Möller, Christiane; Hafkemeijer, Anne; van Swieten, John C; Dopper, Elise; van der Flier, Wiesje M; Vrenken, Hugo; Wink, Alle Meije; Pijnenburg, Yolande A L; Scheltens, Philip; Barkhof, Frederik; Schouten, Tijn M; et al. (J Alzheimers Dis, 2018)
BACKGROUND/OBJECTIVE: Overlapping clinical symptoms often complicate differential diagnosis between patients with Alzheimer's disease (AD) and behavioral variant frontotemporal dementia (bvFTD). Magnetic resonance imaging (MRI) reveals disease specific structural and functional differences that aid in differentiating AD from bvFTD patients. However, the benefit of combining structural and functional connectivity measures to-on a subject-basis-differentiate these dementia-types is not yet known. METHODS: Anatomical, diffusion tensor (DTI), and resting-state functional MRI (rs-fMRI) of 30 patients with early stage AD, 23 with bvFTD, and 35 control subjects were collected and used to calculate measures of structural and functional tissue status. All measures were used separately or selectively combined as predictors for training an elastic net regression classifier. Each classifier's ability to accurately distinguish dementia-types was quantified by calculating the area under the receiver operating characteristic curves (AUC). RESULTS: Highest AUC values for AD and bvFTD discrimination were obtained when mean diffusivity, full correlations between rs-fMRI-derived independent components, and fractional anisotropy (FA) were combined (0.811). Similarly, combining gray matter density (GMD), FA, and rs-fMRI correlations resulted in highest AUC of 0.922 for control and bvFTD classifications. This, however, was not observed for control and AD differentiations. Classifications with GMD (0.940) and a GMD and DTI combination (0.941) resulted in similar AUC values (p = 0.41). CONCLUSION: Combining functional and structural connectivity measures improve dementia-type differentiations and may contribute to more accurate and substantiated differential diagnosis of AD and bvFTD patients. Imaging protocols for differential diagnosis may benefit from also including DTI and rs-fMRI.

SIRT1 Deacetylates SC35 and Suppresses Its Function in Tau Exon 10 Inclusion. - Yin, Xiaomin; Jiang, Xiaosu; Wang, Jia; Qian, Shuo; Liu, Fei; Qian, Wei (J Alzheimers Dis, 2018)
Approximately equal amounts of 3R-tau and 4R-tau resulting from alternative splicing of tau exon 10 is necessary to maintain normal brain function. Dysregulation of alternative splicing of tau exon 10 and the imbalance of 3R-tau/4R-tau have been seen in inherited and sporadic tauopathies. Splicing factor SC35 (also name as SRSF2) plays an important role in promoting tau exon 10 inclusion. SC35 is post-translationally modified by phosphorylation and acetylation, but the role of acetylation in SC35-medicated tau exon 10 inclusion is unknown. Sirtuin type 1 (SIRT1) is an enzyme that deacetylates proteins and associates with age-related disease such as Alzheimer's disease. In the present study, we determined the role of SIRT1 in SC35 acetylation and in the alternative splicing of tau exon 10. We found that SIRT1 interacts with and deacetylates SC35, and inhibits SC35-promoted tau exon 10 inclusion. Substituting K52 residue of SC35 by arginine impairs the role of SC35 in tau exon 10 inclusion. These results suggest that SIRT1 may serve as a therapeutic target for tauopathy by regulating SC35-mediated tau exon 10 splicing.
Keywords: Alternative Splicing; Alzheimer Disease; Exons; HEK293 Cells; HeLa Cells; Humans; Phosphorylation; Ribonucleoproteins; Serine-Arginine Splicing Factors; Sirtuin 1; tau Proteins; Tauopathies

Some Methodological Characteristics of Alzheimer-Associated Urine Neuronal Thread Protein Detected by Enzyme-Linked Immunosorbent Assay. - Jin, He; Wang, Rong; Liu, Zhaohui; Jia, Qiang; Wu, Yanchuan; Zhao, Zhiwei; Wang, Yulan; Zhang, Xu (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer-associated neuronal thread protein (AD7c-NTP) has been found to be a candidate biomarker of Alzheimer's disease (AD). OBJECTIVE: To investigate the effects of urine collected time, different preservatives addition, and storage condition on the measurement of urine AD7c-NTP by enzyme-linked immunosorbent assay (ELISA). METHODS: Three hundred urine samples were collected from 20 participants at three time points on five consecutive days. These samples were immediately placed at 4°C and detected within 2 h. The single spot samples of the first day morning were split into eleven duplicate aliquots (a-k) of 1 ml each, (a) without any preservative (untreated), (b) containing boric acid (2 g/L), (c) containing NaHCO3 (5 g/L), (a-c) were detected at six different time points. For the other eight preservative-free samples, (d-g) were stored at -20°C and (h-k) were stored at -70°C, respectively, detected at different time points. All of the results were compared with the baseline urine. RESULTS: The urine AD7c-NTP levels at different time points behaved stably (p > 0.05). Urine samples without any preservative increased over time, and compared with the NaHCO3 addition group, boric acid addition group behaved stably. Samples stored at -20°C and -70°C led to an obviously false positive. CONCLUSIONS: AD7c-NTP can be tested using random urine instead of the first morning urine. If the specimen cannot be tested in time, boric acid appears to be an acceptable preservative with storage at 4°C, freezing is not recommended.

Stabilized Low-n Amyloid-β Oligomers Induce Robust Novel Object Recognition Deficits Associated with Inflammatory, Synaptic, and GABAergic Dysfunction in the Rat. - Watremez, William; Jackson, Joshua; Almari, Bushra; McLean, Samantha L; Grayson, Ben; Neill, Joanna C; Fischer, Nicolas; Allouche, Ahmad; Koziel, Violette; Pillot, Thierry; Harte, Michael K (J Alzheimers Dis, 2018)
BACKGROUND: With current treatments for Alzheimer's disease (AD) only providing temporary symptomatic benefits, disease modifying drugs are urgently required. This approach relies on improved understanding of the early pathophysiology of AD. A new hypothesis has emerged, in which early memory loss is considered a synapse failure caused by soluble amyloid-β oligomers (Aβo). These small soluble Aβo, which precede the formation of larger fibrillar assemblies, may be the main cause of early AD pathologies. OBJECTIVE: The aim of the current study was to investigate the effect of acute administration of stabilized low-n amyloid-β1-42 oligomers (Aβo1-42) on cognitive, inflammatory, synaptic, and neuronal markers in the rat. METHODS: Female and male Lister Hooded rats received acute intracerebroventricular (ICV) administration of either vehicle or 5 nmol of Aβo1-42 (10μL). Cognition was assessed in the novel object recognition (NOR) paradigm at different time points. Levels of inflammatory (IL-1β, IL-6, TNF-α), synaptic (PSD-95, SNAP-25), and neuronal (n-acetylaspartate, parvalbumin-positive cells) markers were investigated in different brain regions (prefrontal and frontal cortex, striatum, dorsal and ventral hippocampus). RESULTS: Acute ICV administration of Aβo1-42 induced robust and enduring NOR deficits. These deficits were reversed by acute administration of donepezil and rolipram but not risperidone. Postmortem analysis revealed an increase in inflammatory markers, a decrease in synaptic markers and parvalbumin containing interneurons in the frontal cortex, with no evidence of widespread neuronal loss. CONCLUSION: Taken together the results suggest that acute administration of soluble low-n Aβo may be a useful model to study the early mechanisms involved in AD and provide us with a platform for testing novel therapeutic approaches that target the early underlying synaptic pathology.

Stimulation of SIRT1 Attenuates the Level of Oxidative Stress in the Brains of APP/PS1 Double Transgenic Mice and in Primary Neurons Exposed to Oligomers of the Amyloid-β Peptide. - Dong, Yang-Ting; Cao, Kun; Tan, Long-Chun; Wang, Xiao-Ling; Qi, Xiao-Lan; Xiao, Yan; Guan, Zhi-Zhong (J Alzheimers Dis, 2018)
In the study, we examined whether the silent information regulator 1 (SIRT1) can attenuate oxidative stress in the brains of mice carrying the APP/PS1 double mutation and/or in primary neonatal rat neurons exposed to oligomers of amyloid-β peptide (AβOs). Starting at 4 or 8 months of age, the transgenic mice were treated with resveratrol (RSV, a stimulator of SIRT1) or suramin (an inhibitor) (each 20 mg/kg BW/day) for two months. The primary neurons were exposed to AβOs (0.5 μM) for 48 h and thereafter RSV (20 μM) or suramin (300 mg/ml) for 24 h. Cell viability was assessed by the CCK-8 assay; SIRT1 protein and mRNA determined by western blotting and real-time PCR, respectively; senile plaques examined immunohistochemically; ROS monitored by flow cytometry; and the contents of OH-, H2O2, O2·-, and MDA, and the activities of SOD and GSH-Px measured by standard biochemical procedures. In comparison to wild-type mice or untreated primary neurons, the expression of SIRT1 was significantly lower in the brains of APP/PS1 mice or neurons exposed to AβOs. In these same systems, increased numbers of senile plaques and a high level of oxidative stress were apparent. Interestingly, these two latter changes were attenuated by treatment with RSV, but enhanced by suramin. These findings indicate that SIRT1 may be neuroprotective.

Subjective Cognitive Decline Prediction of Mortality: Results from the Einstein Aging Study. - Katz, Mindy J; Wang, Cuiling; Derby, Carol A; Lipton, Richard B; Zimmerman, Molly E; Sliwinski, Martin J; Rabin, Laura A (J Alzheimers Dis, 2018)
BACKGROUND: The relation of pre-dementia stages to mortality has not been fully explored. Previous work examining subjective cognitive decline (SCD) and mortality is limited and mixed regarding methods used and consistency of findings. OBJECTIVE: To examine SCD and mortality in a longitudinal, community-based cohort, using item response theory (IRT) methodology to form a composite SCD measure. Also, to assess whether this relationship was independent of clinical cognitive status. METHODS: The Einstein Aging Study is a diverse longitudinal cohort of adults aged ≥70. SCD items were extracted from baseline CERAD questionnaires and a composite score was formed using IRT methodology. A total of 1,741 participants with complete data were clinically diagnosed as cognitively normal, or as having amnestic mild cognitive impairment (aMCI), nonamnestic mild cognitive impairment (naMCI), or dementia. 645 deaths occurred over a period of 8,912 person-years of follow-up. Cox proportional hazard models predicted time to death adjusting for covariates. RESULTS: A one standard deviation unit increase in level of SCD was associated with >20% higher risk of mortality. However, when models were adjusted for clinical cognitive status, the association was no longer significant. Both dementia and aMCI predicted mortality. Furthermore, when analyses focused only on those without cognitive impairment, SCD level did not predict mortality. CONCLUSIONS: The association of SCD with mortality may be due to the association of SCD with clinical cognitive status. Thus, SCD may be used as a community-based screen to initially identify those with cognitive impairment who may be at greatest risk for death.

Subjective Sleep Quality is not Associated with Incident Dementia: The Rotterdam Study. - Lysen, Thom S; Wolters, Frank J; Luik, Annemarie I; Ikram, M Kamran; Tiemeier, Henning; Ikram, M Arfan (J Alzheimers Dis, 2018)
BACKGROUND: Poor sleep is related to higher dementia risk, but this association is more equivocal for subjective sleep quality specifically. This study investigates the link between subjective sleep quality and dementia risk in the general population. OBJECTIVE: To study the role of subjective sleep quality in the risk of dementia in the general population. METHODS: In the prospective population-based Rotterdam Study, 4,835 persons (mean age 72 years, 58% women) underwent a home interview (2002- 2006) that included the validated Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality. Participants were followed until 2015 for incident dementia, through in-person screening and continuous monitoring of medical records. We used Cox regression models to associate sleep quality with dementia risk, adjusting for age, sex, education, smoking, employment, coffee consumption, alcohol consumption, activities of daily living, cardiovascular risk factors, anxiety, depressive symptoms, cognition, and snoring. RESULTS: During 41,385 person-years (8.5 years mean), 420 participants developed dementia, of whom 320 Alzheimer's disease (AD). Poorer subjective sleep quality was not associated with the risk of all-cause dementia (hazard ratio [HR] per SD increase in PSQI score: 0.91, 95% CI 0.82- 1.02) or AD (HR 0.92, 95% CI 0.81- 1.05). Similarly, individual components of the PSQI were also not associated with dementia. Several sensitivity analyses, i.e., excluding last years of the follow-up time duration or restricting to those with best MMSE scores at baseline, did not reveal subgroups with increased risks. CONCLUSION: In this study, we found no association of poor subjective sleep quality with higher risk of dementia.

Sulforaphane Inhibits the Generation of Amyloid-β Oligomer and Promotes Spatial Learning and Memory in Alzheimer's Disease (PS1V97L) Transgenic Mice. - Hou, Ting-Ting; Yang, He-Yun; Wang, Wei; Wu, Qiao-Qi; Tian, Yuan-Ruhua; Jia, Jian-Ping (J Alzheimers Dis, 2018)
Abnormal amyloid-β (Aβ) aggregates are a striking feature of Alzheimer's disease (AD), and Aβ oligomers have been proven to be crucial in the pathology of AD. Any intervention targeting the generation or aggregation of Aβ can be expected to be useful in AD treatment. Oxidative stress and inflammation are common pathological changes in AD that are involved in the generation and aggregation of Aβ. In the present study, 6-month-old PS1V97L transgenic (Tg) mice were treated with sulforaphane, an antioxidant, for 4 months, and this treatment significantly inhibited the generation and aggregation of Aβ. Sulforaphane also alleviated several downstream pathological changes that including tau hyperphosphorylation, oxidative stress, and neuroinflammation. Most importantly, the cognition of the sulforaphane-treated PS1V97L Tg mice remained normal compared to that of wild-type mice at 10 months of age, when dementia typically emerges in PS1V97L Tg mice. Pretreating cultured cortical neurons with sulforaphane also protected against neuronal injury caused by Aβ oligomers in vitro. These findings suggest that sulforaphane may be a potential compound that can inhibit Aβ oligomer production in AD.

Targeted Assessment of Enlargement of the Perivascular Space in Alzheimer's Disease and Vascular Dementia Subtypes Implicates Astroglial Involvement Specific to Alzheimer's Disease. - Boespflug, Erin L; Simon, Matthew J; Leonard, Emmalyn; Grafe, Marjorie; Woltjer, Randall; Silbert, Lisa C; Kaye, Jeffrey A; Iliff, Jeffrey J (J Alzheimers Dis, 2018)
Waste clearance from the brain parenchyma occurs along perivascular pathways. Enlargement of the perivascular space (ePVS) is associated with pathologic features of Alzheimer's disease (AD), although the mechanisms and implications of this dilation are unclear. Fluid exchange along the cerebral vasculature is dependent on the perivascular astrocytic water channel aquaporin-4 (AQP4) and loss of perivascular AQP4 localization is found in AD. We directly measured ePVS in postmortem samples of pathologically characterized tissue from participants who were cognitively intact or had AD or mixed dementia (vascular lesions with AD). We found that both AD and mixed dementia groups had significantly increased ePVS compared to cognitively intact subjects. In addition, we found increased global AQP4 expression of the AD group over both control and mixed dementia groups and a qualitative reduction in perivascular localization of AQP4 in the AD group. Among these cases, increasing ePVS burden was associated with the presence of tau and amyloid-β pathology. These findings are consistent with the existing evidence of ePVS in AD and provide novel information regarding differences in AD and vascular dementia and the potential role of astroglial pathology in ePVS.

TDP-43 and Alzheimer's Disease Pathologic Subtype in Non-Amnestic Alzheimer's Disease Dementia. - Sahoo, Aradhana; Bejanin, Alexandre; Murray, Melissa E; Tosakulwong, Nirubol; Weigand, Stephen D; Serie, Amanda M; Senjem, Matthew L; Machulda, Mary M; Parisi, Joseph E; Boeve, Bradley F; Knopman, David S; Petersen, Ronald C; et al. (J Alzheimers Dis, 2018)
BACKGROUND: TDP-43 has been shown to be strongly associated with memory loss, smaller hippocampal volumes, and faster rates of hippocampal atrophy in Alzheimer's disease (AD) patients with an amnestic presentation. Whether TDP-43 has any clinical or anatomical associations in AD patients with non-amnestic phenotype is unknown. OBJECTIVE: To determine whether TDP-43 plays a significant role in the clinic-anatomic features of non-amnestic AD. METHODS: All cases with pathologically confirmed intermediate-high probability AD from 1996-2012 were identified and retrospectively sub-classified into amnestic versus non-amnestic dementia at the time of presentation. Neurofibrillary tangle counts were performed in those with a non-amnestic presentation using thioflavin-S microscopy in the hippocampus and three neocortical regions, and all cases were subtyped into hippocampal-sparing, limbic-predominant, and typical AD pathology. TDP-43 immunoreactivity was used to assess for the presence of TDP-43. Statistical analyses helped determine whether pathologic subtype or TDP-43 was more strongly associated with clinico-imaging features. RESULTS: Out of 172 pathologically confirmed AD cases, 36 (19%) were classified as non-amnestic. Twenty-five of these 36 (69%) had typical pathology, 0 limbic-predominant pathology, and 11 (31%) hippocampal-sparing pathology. Eleven (44%) of the 25 cases with typical pathology were TDP-43+. Of the 11 cases with hippocampal-sparing pathology, 4 (36%) were TDP-43+. There were no differences in demographic, clinical, or neuroimaging features in those with TDP-43 versus those without except for older age at onset (p = 0.02) and age at death (p = 0.02) in those with TDP-43. AD pathological subtype accounted for slightly more of the variances in the neocortex than TDP-43. CONCLUSION: In non-amnestic AD, we find little evidence that clinical or anatomical features of the disease are related to TDP-43.

TDP-43 Neuropathologic Associations in the Nun Study and the Honolulu-Asia Aging Study. - Flanagan, Margaret E; Cholerton, Brenna; Latimer, Caitlin S; Hemmy, Laura S; Edland, Steven D; Montine, Kathleen S; White, Lon R; Montine, Thomas J (J Alzheimers Dis, 2018)
Transactive response binding protein-43 (TDP-43) cytoplasmic neuronal and glial aggregates (pathologic TDP-43) have been described in multiple brain diseases. We describe the associations between neuropathologically confirmed TDP-43 and cognition in two population-based cohorts: the Nun Study (NS) and the Honolulu-Asia Aging Study (HAAS). In the HAAS, there was a significant association between hippocampal sclerosis (HS) and TDP-43 (OR = 11.04, p < 0.0001, 95% CI 3.57-34.13). In the NS, there were significant associations between TDP-43 and HS (OR = 16.44, p > 0.001 95%, CI 7.10-38.00) and Alzheimer's disease (AD) severity (OR = 1.74, p = 0.009, 95% CI 1.15-2.64). When cognitive scores were added to the model, HS remained significant but the other variables were not. When HS was removed from the model, the overall model remained significant and the associations between cognitive performance and TDP-43 (OR = 2.11, p = 0.022, 95% CI 1.11-4.02) were significant. In the NS, there was a significant association between cognitive performance and TDP-43 (OR 1.94 p = 0.005, 95% CI 1.22-3.09) (HS remained significant, but AD did not). When HS was removed from the model, only CERAD was significant (OR = 2.43 p < 0.001, 95% CI 1.58-3.74). These results support a consistent association between pathologic TDP-43, HS, and the development of cognitive impairment in two large studies of brain aging, while the relationship between AD pathology and TDP-43 may vary according to cohort-specific features.

Three Decades of Dementia Research: Insights from One Small Community of Indomitable Rotterdammers. - Wolters, Frank J; Adams, Hieab H H; Bos, Daniel; Licher, Silvan; Ikram, M Arfan (J Alzheimers Dis, 2018)
The most commonly encountered opening sentence in scientific publications about dementia undoubtedly relates to the overwhelming burden of disease. Finding an effective preventive or therapeutic intervention against dementia has been considered the most important unmet need in contemporary medicine. While efforts on tackling this devastating disease have increased exponentially, it is difficult to imagine that in the 1980s and early-1990s, the disease did not feature prominently on any public health report. Yet, it was already then that epidemiologists recognized the growing societal burden of dementia and rationalized that dementia is not necessarily part of aging. Indeed, the conviction that dementia is pathologically distinct from aging led to various efforts in search of unravelling its risk factors and understanding its pre-clinical phase. Among the early pioneers, the population-based Rotterdam Study was initiated in 1990 clearly aiming on chronic diseases including dementia, and among this Alzheimer's disease, as one of its focus points. Ever since, the Rotterdam Study has been an important cornerstone in increasing our knowledge about dementia from an epidemiological perspective. Here, we summarize the main findings originating from this study, and put these into perspective with previous and current work in the field. With an expanding scope of the Rotterdam Study over the years, we discuss findings on occurrence, modifiable risk factors, imaging, and its genetic underpinnings. Importantly, we conclude with recommendations- or, perhaps better stated, a wish list- for future research which may help us reach our finish line: finding an effective preventive or therapeutic intervention against dementia.

Three VCP Mutations in Patients with Frontotemporal Dementia. - Wong, Tsz Hang; Pottier, Cyril; Hondius, David C; Meeter, Lieke H H; van Rooij, Jeroen G J; Melhem, Shami; van Minkelen, Rick; van Duijn, Cornelia M; Rozemuller, Annemieke J M; Seelaar, Harro; Rademakers, Rosa; van Swieten, John C (J Alzheimers Dis, 2018)
Valosin-containing protein (VCP) is involved in multiple cellular activities. Mutations in VCP lead to heterogeneous clinical presentations including inclusion body myopathy with Paget's disease of the bone, frontotemporal dementia and amyotrophic lateral sclerosis, even in patients carrying the same mutation. We screened a cohort of 48 patients with familial frontotemporal dementia (FTD) negative for MAPT, GRN, and C9orf72 mutations for other known FTD genes by using whole exome sequencing. In addition, we carried out targeted sequencing of a cohort of 37 patients with frontotemporal lobar degeneration with Transactive response DNA-binding protein 43 (TDP-43) subtype from the Netherlands Brain bank. Two novel (p.Thr262Ser and p.Arg159Ser) and one reported (p.Met158Val) VCP mutations in three patients with a clinical diagnosis of FTD were identified, and were absence in population-match controls. All three patients presented with behavioral changes, with additional semantic deficits in one. No signs of Paget or muscle disease were observed. Pathological examination of the patient with VCP p.Arg159Ser mutation showed numerous TDP-43 immunoreactive (IR) neuronal intranuclear inclusions (NII) and dystrophic neurites (DN), while a lower number of NII and DN were observed in the patient with the VCP p.Thr262Ser mutation. Pathological findings of both patients were consistent with FTLD-TDP subtype D. Furthermore, only rare VCP-IR NII was observed in both cases. Our study expands the clinical heterogeneity of VCP mutations carriers, and indicates that other additional factors, such as genetic modifiers, may determine the clinical phenotype.

Total MRI Small Vessel Disease Burden Correlates with Cognitive Performance, Cortical Atrophy, and Network Measures in a Memory Clinic Population. - Banerjee, Gargi; Jang, Hyemin; Kim, Hee Jin; Kim, Sung Tae; Kim, Jae Seung; Lee, Jae Hong; Im, Kiho; Kwon, Hunki; Lee, Jong Min; Na, Duk L; Seo, Sang Won; Werring, David John (J Alzheimers Dis, 2018)
BACKGROUND: Recent evidence suggests that combining individual imaging markers of cerebral small vessel disease (SVD) may more accurately reflect its overall burden and better correlate with clinical measures. OBJECTIVE: We wished to establish the clinical relevance of the total SVD score in a memory clinic population by investigating the association with SVD score and cognitive performance, cortical atrophy, and structural network measures, after adjusting for amyloid-β burden. METHODS: We included 243 patients with amnestic mild cognitive impairment (MCI), Alzheimer's disease dementia, subcortical vascular MCI, or subcortical vascular dementia. All underwent MR and [11C] PiB-PET scanning and had standardized cognitive testing. Multiple linear regression was used to evaluate the relationships between SVD score and cognition, cortical thickness, and structural network measures. Path analyses were performed to evaluate whether network disruption mediates the effects of SVD score on cortical thickness and cognition. RESULTS: Total SVD score was associated with the performance of frontal (β - 4.31, SE 2.09, p = 0.040) and visuospatial (β - 0.95, SE 0.44, p = 0.032) tasks, and with reduced cortical thickness in widespread brain regions. Total SVD score was negatively correlated with nodal efficiency, as well as changes in brain network organization, with evidence of reduced integration and increasing segregation. Path analyses showed that the associations between SVD score and frontal and visuospatial scores were partially mediated by decreases in their corresponding nodal efficiency and cortical thickness. CONCLUSION: Total SVD burden has clinical relevance in a memory clinic population and correlates with cognition, and cortical atrophy, as well as structural network disruption.

Transcranial Sonography in Neurodegenerative Diseases with Cognitive Decline. - Favaretto, Silvia; Walter, Uwe; Baracchini, Claudio; Cagnin, Annachiara (J Alzheimers Dis, 2018)
Transcranial sonography (TCS) of the brain parenchyma detects alterations in the substantia nigra (SN), raphe nuclei and basal ganglia; this technique has been established as a tool for the early diagnosis of Parkinson's disease and differential diagnosis from atypical parkinsonian syndromes. Here, we aimed to review the main applications of TCS in neurodegenerative diseases presenting with dementia syndrome, focusing on Alzheimer's disease (AD), dementia with Lewy bodies (DLB), frontotemporal lobar degeneration, idiopathic normal pressure hydrocephalus, and atypical and secondary parkinsonisms. The finding of bilaterally marked hyperechogenicity of the SN appears as a characteristic feature of DLB, while it is found only in a minority of AD patients. SN hyperechogenicity is also detected in most patients with corticobasal degeneration and in about one third of patients with progressive supranuclear palsy, in which is constantly associated with hyperechogenic alterations of the basal ganglia. In conclusion, TCS is a valid supportive tool in the diagnostic workup of patients with dementia due to different neurodegenerative conditions. A promising new application is the differentiation of DLB from AD even at the early stages of these diseases.
Keywords: Cognition Disorders; Humans; Neurodegenerative Diseases; Ultrasonography, Doppler, Transcranial

Traumatic Brain Injury and Age of Onset of Dementia with Lewy Bodies. - Nguyen, Trung P; Schaffert, Jeff; LoBue, Christian; Womack, Kyle B; Hart, John; Cullum, C Munro (J Alzheimers Dis, 2018)
BACKGROUND: Traumatic brain injury (TBI) with loss of consciousness (LOC) has been associated with earlier onset of mild cognitive impairment, frontotemporal dementia, Parkinson's disease, and Alzheimer's disease (AD), but has not been examined as a risk factor for earlier onset of dementia with Lewy bodies (DLB). OBJECTIVE: The purpose of this study was to assess the association between a history of TBI and the age of onset of DLB. METHOD: Data from 576 subjects with a clinical diagnosis of DLB were obtained from the National Alzheimer's Coordinating Center (NACC). Analyses of Covariance examined whether self-reported history of remote TBI with LOC (i.e., >1 year prior to the first Alzheimer's Disease Center visit) was associated with earlier DLB symptom onset. RESULTS: Controlling for sex, those with a history of remote TBI had an approximately 1.5-year earlier clinician-estimated age of onset (F = 0.87, p = 0.35) and 0.75-years earlier age of diagnosis (F = 0.14, p = 0.71) of DLB compared to those without a history of TBI, though the differences did not reach statistical significance. Analysis of subjects with autopsy-confirmed diagnoses was underpowered due to the low number of TBI+ subjects. CONCLUSIONS: Remote TBI with LOC was not significantly associated with DLB onset, despite being a significant risk factor for cognitive decline and earlier age of onset in other neurodegenerative conditions. Replication of these results using a larger cohort of DLB subjects with and without a TBI history who have undergone autopsy is indicated, as our TBI+ subjects did show a slightly earlier onset of about 1.5 years. Further investigations into other potential DLB risk factors are also warranted.

Treatment of Atrial Fibrillation in Patients with Dementia: A Cohort Study from the Swedish Dementia Registry. - Subic, Ana; Cermakova, Pavla; Religa, Dorota; Han, Shuang; von Euler, Mia; Kåreholt, Ingemar; Johnell, Kristina; Fastbom, Johan; Bognandi, Liselia; Winblad, Bengt; Kramberger, Milica G; Eriksdotter, Maria; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Patients with dementia might have higher risk for hemorrhagic complications with anticoagulant therapy prescribed for atrial fibrillation (AF). OBJECTIVE: This study assesses the risks and benefits of warfarin, antiplatelets, and no treatment in patients with dementia and AF. METHODS: Of 49,792 patients registered in the Swedish Dementia Registry 2007-2014, 8,096 (16%) had a previous diagnosis of AF. Cox proportional hazards models were used to calculate the risk for ischemic stroke (IS), nontraumatic intracranial hemorrhage, any-cause hemorrhage, and death. RESULTS: Out of the 8,096 dementia patients with AF, 2,143 (26%) received warfarin treatment, 2,975 (37%) antiplatelet treatment, and 2,978 (37%) had no antithrombotic treatment at the time of dementia diagnosis. Patients on warfarin had fewer IS than those without treatment (5.2% versus 8.7%; p < 0.001) with no differences compared to antiplatelets. In adjusted analyses, warfarin was associated with a lower risk for IS (HR 0.76, CI 0.59-0.98), while antiplatelets were associated with increased risk (HR 1.25, CI 1.01-1.54) compared to no treatment. For any-cause hemorrhage, there was a higher risk with warfarin (HR 1.28, CI 1.03-1.59) compared to antiplatelets. Warfarin and antiplatelets were associated with a lower risk for death compared to no treatment. CONCLUSIONS: Warfarin treatment in Swedish patients with dementia is associated with lower risk of IS and mortality, and a small increase in any-cause hemorrhage. This study supports the use of warfarin in appropriate cases in patients with dementia. The low percentage of patients on warfarin treatment indicates that further gains in stroke prevention are possible.
Keywords: Aged; Aged, 80 and over; Anticoagulants; Atrial Fibrillation; Dementia; Female; Hemorrhage; Humans; Longitudinal Studies; Male; Registries; Risk Factors; Stroke; Survival Analysis; Sweden; Warfarin

TRPC1 Null Exacerbates Memory Deficit and Apoptosis Induced by Amyloid-β. - Li, Mengzhu; Liu, Enjie; Zhou, Qiuzhi; Li, Shihong; Wang, Xin; Liu, Yanchao; Wang, Lin; Sun, Dongsheng; Ye, Jinwang; Gao, Yuan; Yang, Xifei; Liu, Jianjun; et al. (J Alzheimers Dis, 2018)
The transient receptor potential cation (TRPC) channels are widely expressed in nervous system but their functions remain largely unclear. Here, we found that TRPC1 deletion did not affect learning and memory in physiological conditions, while it aggravated learning and memory deficits induced by amyloid-β (Aβ), the major component of the senile plaques observed in the brains of Alzheimer's disease (AD). Further studies demonstrated that TRPC1 deletion did not affect cell apoptosis in physiological condition, but it exacerbated the Aβ-induced cell death in mouse hippocampus. Moreover, the level of TRPC1 was decreased in AD cell and mouse models, and upregulation of TRPC1 decreased Aβ levels with attenuation of apoptosis in the cells stably overexpressing amyloid-β protein precursor (AβPP). Finally, the transmembrane domain of TRPC1 could bind to AβPP and thus decreased Aβ production. These findings indicate that loss of TRPC1 exacerbates Aβ-induced memory deficit and cell apoptosis, though it does not impair cognitive function or induce cell death in physiological conditions.

TTC7 and Hyccin Regulate Neuronal Aβ42 Accumulation and its Associated Neural Deficits in Aβ42-Expressing Drosophila. - Sun, Minghao; Zhao, Yinghui; Han, Men; Zhang, Baozhu; Zhang, Xiao; Zhang, Qichao; Lim, Nastasia K-H; Wang, Wen-An; Huang, Fu-De (J Alzheimers Dis, 2018)
Neuronal amyloid-β (Aβ) accumulation plays an important role in the pathogenesis of Alzheimer's disease (AD). The conformation and toxicity of Aβ are regulated by lipids on the plasma membrane. Previously, we found downregulation of Rolling Blackout (RBO) or phosphatidylinositol-4-kinase type IIIα (PI4KIIIα) reduces neuronal Aβ accumulation and associated neural deficits in a Drosophila model expressing Aβ42. In mammals, the homologs of RBO and PI4KIIIα were reported to form a plasma membrane-localized complex with a scaffold protein TTC7 and cytosolic protein Hyccin/FAM126A to tightly control the plasmalemmal level of phosphatidylinositol-4-phosphate. Here, we show genetic downregulation of Drosophila TTC7 and Hyccin also reduces neuronal Aβ accumulation and associated synaptic and motor defects as well as premature death in Aβ42-expressing flies, while overexpression of TTC7 and Hyccin produced the opposite effect. These results, together with our previous study, demonstrate that RBO/TTC7/PI4KIIIα/Hyccin regulate neuronal Aβ accumulation and associated neural deficits in the Drosophila model, further supporting the RBO/Efr3-PI4KIIIα complex as a potential therapeutic target for AD.

Update on Vascular Cognitive Impairment Associated with Subcortical Small-Vessel Disease. - Wallin, Anders; Román, Gustavo C; Esiri, Margaret; Kettunen, Petronella; Svensson, Johan; Paraskevas, George P; Kapaki, Elisabeth (J Alzheimers Dis, 2018)
Subcortical small-vessel disease (SSVD) is a disorder well characterized from the clinical, imaging, and neuropathological viewpoints. SSVD is considered the most prevalent ischemic brain disorder, increasing in frequency with age. Vascular risk factors include hypertension, diabetes, hyperlipidemia, elevated homocysteine, and obstructive sleep apnea. Ischemic white matter lesions are the hallmark of SSVD; other pathological lesions include arteriolosclerosis, dilatation of perivascular spaces, venous collagenosis, cerebral amyloid angiopathy, microbleeds, microinfarcts, lacunes, and large infarcts. The pathogenesis of SSVD is incompletely understood but includes endothelial changes and blood-brain barrier alterations involving metalloproteinases, vascular endothelial growth factors, angiotensin II, mindin/spondin, and the mammalian target of rapamycin pathway. Metabolic and genetic conditions may also play a role but hitherto there are few conclusive studies. Clinical diagnosis of SSVD includes early executive dysfunction manifested by impaired capacity to use complex information, to formulate strategies, and to exercise self-control. In comparison with Alzheimer's disease (AD), patients with SSVD show less pronounced episodic memory deficits. Brain imaging has advanced substantially the diagnostic tools for SSVD. With the exception of cortical microinfarcts, all other lesions are well visualized with MRI. Diagnostic biomarkers that separate AD from SSVD include reduction of cerebrospinal fluid amyloid-β (Aβ)42 and of the ratio Aβ42/Aβ40 often with increased total tau levels. However, better markers of small-vessel function of intracerebral blood vessels are needed. The treatment of SSVD remains unsatisfactory other than control of vascular risk factors. There is an urgent need of finding targets to slow down and potentially halt the progression of this prevalent, but often unrecognized, disorder.
Keywords: Animals; Cerebrovascular Disorders; Dementia; Humans

Urine-Based Biomarkers for Alzheimer's Disease Identified Through Coupling Computational and Experimental Methods. - Yao, Fang; Hong, Xiaoyu; Li, Shuiming; Zhang, Yan; Zhao, Qing; Du, Wei; Wang, Yong; Ni, Jiazuan (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a chronic neurodegenerative disorder contributing to nearly 70% of dementia cases. However, no diagnostic protein biomarkers are available in urine. In this study, we combined computational and experimental methods to identify urinary biomarkers for AD. First, by analyzing brain tissue-based gene expression data of AD, 2,754 differentially expressed genes were identified, 559 of which were predicted to encode urine-excretory proteins that might act as candidate protein biomarkers of AD. GO enrichment analyses implied that they were mainly involved in microtubule-based process, myelin sheath, and calcium ion binding, suggesting that they might be associated with AD pathogenesis. In order to verify these proteins in urine, an iTRAQ experiment was carried out to analyze urine samples from AD patients and healthy controls, and 15 proteins were detected. Based on the expression changes of these proteins, 4 proteins were chosen for further validation by ELISA experiment, and SPP1, GSN, and IGFBP7 were found to be differentially expressed in the urine of AD patients. After a literature survey, we found that they were involved in AD pathophysiology and might serve as new urine biomarkers for AD. To our knowledge, this is the first time that urine biomarkers for AD were identified by combining computational and experimental methods. Furthermore, this is the first time SPP1, GSN, and IGFBP7 have been reported as potential urine protein biomarkers for AD. Therefore, our findings might provide significant guidance for finding early biomarkers of AD in urine.

Validation of the Delayed Matching-to-Sample Task 48 (DMS48) in Elderly Chinese. - Feng, Xueyan; Zhou, Aihong; Liu, Zhixin; Li, Fangyu; Wei, Cuibai; Zhang, Guili; Jia, Jianping (J Alzheimers Dis, 2018)
BACKGROUND: Delayed Matching-to-Sample Task 48 (DMS48), a brief tool measuring visual recognition memory, is valid to identify the early stage of Alzheimer's disease (AD) in Caucasians. However, little data is available in Chinese. OBJECTIVE: To develop norms and optimal cutoff points for the DMS48 in Chinese elders. METHODS: A cross-sectional study was conducted in seven memory clinics from five cities across China. DMS48 was applied to 369 Chinese aged 50 or older (138 cognitively normal [CN], 112 mild cognitive impairment due to AD (MCI-A), and 119 mild AD dementia). The demographic factors which influence DMS48 scores were investigated and the norms were established considering those factors. Receiver operating characteristic (ROC) analysis was used to determine the optimal cutoff points. RESULTS: Age was shown to influence DMS48 scores (r = -0.36, p < 0.05), and we presented the age-stratified normative data for the DMS48. The optimal cutoff point is 42/43 for identifying cognitive impairment (MCI-A and AD dementia) against CN (sensitivity 97.80% and specificity 89.13%) and MCI-A against CN (sensitivity 86.60% and specificity 94.20%). A cutoff of 39/40 obtained good sensitivity (100.00%) and specificity (94.90%) in discriminating AD dementia from CN. The age-stratified optimal cutoff points for identifying MCI-A were 43/44 for individuals aged 50 to 59 years old, 42/43 for 60 to 69 years old, 41/42 for 70 to 79 years old, and 40/41 for 80 or older, respectively (sensitivity 84.80% and specificity 95.70%). CONCLUSION: This study proved that DMS48 is of good validation in screening MCI-A in elderly Chinese.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; China; Cognitive Dysfunction; Cross-Sectional Studies; Female; Humans; Linear Models; Male; Memory Disorders; Middle Aged; Neuropsychological Tests; ROC Curve; Sensitivity and Specificity; Severity of Illness Index

Vascular Cognitive Impairment and the Gut Microbiota. - Li, Sinian; Shao, Yiming; Li, Kanglan; HuangFu, Changmei; Wang, Wenjie; Liu, Zhou; Cai, Zhiyou; Zhao, Bin (J Alzheimers Dis, 2018)
Vascular cognitive impairment (VCI), the second most common cause of dementia in elderly people, is a term that refers to all forms of cognitive disorders that can be attributed to cerebrovascular disease such as manifestations of discrete infarctions, brain hemorrhages, and white matter lesions. The gut microbiota (GM) has emerged recently as an essential player in the development of VCI. The GM may affect the brain's physiological, behavioral, and cognitive functions through the brain-gut axis via neural, immune, endocrine, and metabolic pathways. Therefore, microbiota dysbiosis may mediate or affect atherosclerosis, cerebrovascular disease, and endothelial dysfunction, which are the predominant risk factors for VCI. Moreover, the composition of the GM includes the bacterial component lipopolysaccharides and their metabolic products including trimethylamine-N-oxide and short-chain fatty acids. These products may increase the permeability of the intestinal epithelium, leading to systemic immune responses, low-grade inflammation, and altered signaling pathways that are associated with the pathogenesis of VCI. In this review, we discuss the proposed mechanisms of the GM in the maintenance of VCI and how it is implicated in acquired metabolic diseases, particularly in VCI regulation.

Vestibular Loss Predicts Poorer Spatial Cognition in Patients with Alzheimer's Disease. - Wei, Eric X; Oh, Esther S; Harun, Aisha; Ehrenburg, Matthew; Agrawal, Yuri (J Alzheimers Dis, 2018)
The vestibular system is an important contributor to balance control, spatial orientation, and falls risk. Recent evidence has shown that Alzheimer's disease (AD) patients have a higher prevalence of vestibular impairment relative to healthy controls. We sought to evaluate whether vestibular loss is specifically associated with poor spatial cognitive skills among patients with mild cognitive impairment (MCI) and AD. We enrolled 50 patients (22 MCI and 28 AD) from an interdisciplinary Memory Clinic and measured vestibular physiologic function in all patients. Spatial cognitive function was assessed using the Money Road Map Test (MRMT) and the Trail Making Test Part B (TMT-B). General cognitive function was assessed with the Mini-Mental Status Examination (MMSE). In multivariable linear regression analyses adjusted for age, gender, education level, and MMSE, MCI and AD patients with vestibular loss made significantly more errors on the MRMT relative to patients with normal vestibular function (β= 7.3, 95% CI 2.4, 12.1 for unilateral vestibular loss and β= 6.4, 95% CI 1.9, 10.9 for bilateral vestibular loss). We further stratified AD patients into "spatially normal" and "spatially impaired" groups based on MRMT performance, and found that the prevalence of vestibular loss was significantly higher in the spatially impaired AD group relative to the spatially normal AD group. These findings support the hypothesis that vestibular loss contributes specifically to a decline in spatial cognitive ability in MCI and AD patients, independently of general cognitive decline, and may predict a "spatially impaired" subtype of AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Bilateral Vestibulopathy; Cognitive Dysfunction; Cross-Sectional Studies; Female; Humans; Linear Models; Male; Multivariate Analysis; Neuropsychological Tests; Prospective Studies; Spatial Navigation; Vestibular Function Tests

Visualization of Focal Thinning of the Ganglion Cell-Inner Plexiform Layer in Patients with Mild Cognitive Impairment and Alzheimer's Disease. - Shao, Yi; Jiang, Hong; Wei, Yantao; Shi, Yingying; Shi, Ce; Wright, Clinton B; Sun, Xiaoyan; Vanner, Elizabeth A; Rodriguez, Anny D; Lam, Byron L; Rundek, Tatjana; Baumel, Barry S; et al. (J Alzheimers Dis, 2018)
BACKGROUND: A detailed analysis of the tomographic thickness of intraretinal layers may provide more information on neurodegeneration in patients with mild cognitive impairment (MCI) and Alzheimer's disease (AD). OBJECTIVE: The goal was to analyze tomographic thickness patterns of intraretinal layers in patients with AD andMCI. METHOD: Forty-nine patients (25 AD and 24 MCI) and 21 cognitively normal (CN) controls were imaged using ultra-high-resolution optical coherence tomography to obtain volumetric data centered on the fovea. The segmented intraretinal layers were retinal nerve fiber layer (RNFL), ganglion cell- inner plexiform layer (GCIPL), inner nuclear layer (INL), outer nuclear layer (ONL), outer plexiform layer (OPL), and retinal photoreceptor (PR), in addition to the total retinal thickness(TRT). RESULTS: The thickness differences were negative (thinning) mainly in TRT, RNFL, and GCIPL in both AD and MCI groups in comparison to CN, while the thickness differences were positive (thickening) mainly in ONL and PR in AD. GCIPL of AD and MCI was thinner in superior, nasal superior, and temporal superior quadrants, compared to CN (p < 0.05). GCIPL of the inner superior, inner nasal superior, inner temporal superior, and outer nasal superior sectors was significantly thinner in AD than CN (p < 0.05). GCIPL of the outer superior, inner temporal superior, outer nasal, and temporal superior sectors was significantly thinner in MCI than CN (p < 0.05). CONCLUSION: Focal thinning of the GCIPL was visualized and quantified by detailed partitions in AD and MCI, which provides specific information about neurodegeneration in MCI and AD.

White Matter Hyperintensity Predicts the Risk of Incident Cognitive Decline in Community Dwelling Elderly. - Ding, Ding; Xiong, Yunyun; Zhao, Qianhua; Guo, Qihao; Chu, Shuguang; Chu, Winnie W C; Luo, Jianfeng; Liang, Xiaoniu; Zheng, Li; Hong, Zhen; Wong, Lawrence K S; Mok, Vincent C T (J Alzheimers Dis, 2018)
BACKGROUND: Unlike western countries, data on white matter hyperintensity (WMH) in community dwelling elderly in Asian population is very limited. OBJECTIVE: To examine the relation between baseline WMH burden and the risk of incident cognitive decline in a community-based cohort with Chinese-dwelling elderly. METHODS: We prospectively evaluated the incident cognitive decline for 226 participants in the Shanghai Aging Study. Baseline WMH severity was visually rated by the age-related white matter changes (ARWMC) scale based on MRI. Cox proportional hazards regression model was used to estimate the relative risk (RR) of total ARWMC scale, global ARWMC score, presence of lacune and microbleed, for incident cognitive decline by adjusting potential confounders. RESULTS: Forty subjects were identified with incident cognitive decline (new onset 34 mild cognitive impairment and 6 dementia) during a median duration of 6 years follow-up. The incidence of cognitive decline was 3.0 (95% confidence interval [CI] 2.2-4.1) per 100 person-years. Increasing total ARWMC scale [RR1.21 (95% CI 1.06-1.39), p = 0.004)], confluent WMH [RR3.16 (95% CI 1.50-6.64), p = 0.002), and presence of lacunes [RR 2.73 (95% CI 1.21-6.15)] at baseline were independent predictors of incident cognitive decline. CONCLUSION: Our study demonstrated that confluent WMH may increase the risk of incident cognitive decline by 3 folds in community dwelling subjects. Small vessel disease may cause heavy burden of cognitive impairment in the elderly in China.
Keywords: Aged; China; Cognitive Dysfunction; Female; Humans; Independent Living; Kaplan-Meier Estimate; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Proportional Hazards Models; Prospective Studies; Risk Factors; White Matter

18F-AV-1451 PET Imaging in Three Patients with Probable Cerebral Amyloid Angiopathy. - Kim, Hee Jin; Cho, Hanna; Werring, David J; Jang, Young Kyoung; Kim, Yeo Jin; Lee, Jin San; Lee, Juyoun; Jun, Soomin; Park, Seongbeom; Ryu, Young Hoon; Choi, Jae Yong; Cho, Young Seok; et al. (J Alzheimers Dis, 2017)
Cerebrovascular deposition of amyloid-β, known as cerebral amyloid angiopathy (CAA), is associated with MRI findings of lobar hemorrhage, cerebral microbleeds, and cortical superficial siderosis. Although pathological studies suggest that tau may co-localize with vascular amyloid, this has not yet been investigated in CAA in vivo. Three patients with probable CAA underwent 11C-Pittsburgh Compound B (PiB) PET or 18F-florbetaben PET to evaluate amyloid burden, and 18F-AV-1451 PET to evaluate paired helical filament tau burden. Regions that had cerebral microbleeds or cortical superficial siderosis largely overlapped with those showing increased 18F-AV-1451. Our preliminary study raised the possibility that lobar cerebral microbleeds, and cortical superficial siderosis, which are characteristic markers of vascular amyloid, may be associated with local production of paired helical filament tau.
Keywords: Aged; Aged, 80 and over; Aniline Compounds; Brain; Carbolines; Cerebral Amyloid Angiopathy; Female; Humans; Image Processing, Computer-Assisted; Male; Positron-Emission Tomography; Thiazoles

A 9-microRNA Signature in Serum Serves as a Noninvasive Biomarker in Early Diagnosis of Alzheimer's Disease. - Guo, Rui; Fan, Gang; Zhang, Jian; Wu, Chunxiao; Du, Yifeng; Ye, Hui; Li, Zhang; Wang, Lili; Zhang, Zhihui; Zhang, Lu; Zhao, Yueran; Lu, Zhiming (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is the most common type of age-related neurodegenerative disorder; nevertheless, nowadays there are no reliable biomarkers or non-invasive techniques available for its early detection. Recent studies have indicated that the circulating level profiles of microRNAs (miRNAs) have the potential to be used as valuable biomarkers for diagnosis, staging, and progress monitoring of various diseases. Here we report a novel 9-miRNA signature (hsa-miR-26a-5p, hsa-miR-181c-3p, hsa-miR-126-5p, hsa-miR-22-3p, hsa-miR-148b-5p, hsa-miR-106b-3p, hsa-miR-6119-5p, hsa-miR-1246, and hsa-miR-660-5p) that can be utilized as biomarker for detecting AD. We respectively profiled the serum miRNAs from 19 AD patients and 9 healthy control (HC) participants using the Next-Generation Sequencing (NGS). The NGS results were validated by quantitative real-time polymerase chain reaction (qRT-PCR) on a larger cohort of 121 AD and 86 HC cases. All the patients were divided into three groups (mild, moderate, and severe AD) based on the Mini-Mental State Examination (MMSE) and Clinical Dementia Rating (CDR). Our research indicates that abnormal expression of distinct serum miRNAs occurs at different stages of AD. The difference of the area under the receiver operator characteristics curve (AUC) between the AD and the HC is between 70% and 85%. Among the 9 miRNAs, hsa-miR-22-3p has the best sensitivity (81.8%) and specificity (70.9%). The miRNA-panel is more valuable for AD diagnosis. The data suggest that the differentially expressed serum miRNAs could be used as biomarkers to improve the diagnosis of AD, particularly at the early stage, and to classify its clinical stages.

Age and Graphomotor Decision Making Assessed with the Digital Clock Drawing Test: The Framingham Heart Study. - Piers, Ryan J; Devlin, Kathryn N; Ning, Boting; Liu, Yulin; Wasserman, Ben; Massaro, Joseph M; Lamar, Melissa; Price, Catherine C; Swenson, Rod; Davis, Randall; Penney, Dana L; Au, Rhoda; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Digital Clock Drawing Test (dCDT) technology enables the examination of detailed neurocognitive behavior as behavior unfolds in real time; a capability that cannot be obtained using a traditional pen and paper testing format. OBJECTIVE: Parameters obtained from the dCDT were used to investigate neurocognitive constructs related to higher-order neurocognitive decision making and information processing speed. The current research sought to determine the effect of age as related to combined motor and non-motor components of drawing, and higher-order decision making latencies. METHODS: A large group of stroke- and dementia- free Framingham Heart Study participants were administered the dCDT to command and copy with hands set for "10 after 11". Six age groups (age range 28-98) were constructed. RESULTS: Differences between age groups were found for total time to completion, total pen stroke count, and higher-order decision making latencies in both command and copy test conditions. CONCLUSION: Longer age-related decision making latencies may reflect a greater need for working memory and increased self-monitoring in older subjects. These latency measures have potential to serve as neurocognitive biomarkers of Alzheimer's disease and other insidious neurodegenerative disorders.

Altered Gut Microbiota in a Mouse Model of Alzheimer's Disease. - Zhang, Ling; Wang, Ying; Xiayu, Xia; Shi, Changhua; Chen, Wei; Song, Nan; Fu, Xinjing; Zhou, Rui; Xu, Yan-Feng; Huang, Lan; Zhu, Hua; Han, Yunlin; et al. (J Alzheimers Dis, 2017)
The topic of gut microbiota is currently attracting considerable interest as a potential factor in Alzheimer's disease (AD). However, the extent and time course of alterations in the gut microbiota, and their effects on AD pathology remain uncertain. Herein, we compared the fecal microbiomes and fecal short chain fatty acid composition (SCFAs) between wild-type and AD model mice at different ages under strictly controlled specific pathogen free conditions, and also conducted microscopic investigations of intestinal structures. Our results showed that the microbiota composition and diversity were perturbed and the level of SCFAs was reduced in AD mice, predicting alterations in more than 30 metabolic pathways, which may be associated with amyloid deposition and ultrastructural abnormalities in AD mouse intestine. These findings indicate that AD pathology might not only affect brain function directly, but also exacerbate cognitive deficits through reducing the level of SCFAs via alterations of gut microbiota induced by intestinal amyloid deposition. Our data may support a role of gut microbiota, and suggest a novel route for therapeutic intervention in AD.

Altered Sphingolipid Balance in Capillary Cerebral Amyloid Angiopathy. - de Wit, Nienke M; Snkhchyan, Hripsime; den Hoedt, Sandra; Wattimena, Darcos; de Vos, Rob; Mulder, Monique T; Walter, Jochen; Martinez-Martinez, Pilar; Hoozemans, Jeroen J; Rozemuller, Annemieke J; De Vries, Helga E (J Alzheimers Dis, 2017)
BACKGROUND: The majority of patients with Alzheimer's disease (AD) exhibit amyloid-β (Aβ) deposits at the brain vasculature, a process referred to as cerebral amyloid angiopathy (CAA). In over 51% of AD cases, Aβ also accumulates in cortical capillaries, which is termed capillary CAA (capCAA). It has been postulated that the presence of capCAA in AD is a specific subtype of AD, although underlying mechanisms are not yet fully understood. Sphingolipids (SLs) are implicated in neurodegenerative disorders, including AD. However, to date it remains unknown whether alterations in the SL pathway are involved in capCAA pathogenesis and if these differ from AD. OBJECTIVE: To determine whether AD cases with capCAA have an altered SL profile compared to AD cases without capCAA. METHODS: Immunohistochemistry was performed to assess the expression and localization of ceramide, acid sphingomyelinase (ASM), and sphingosine-1-phosphate receptors (S1P1, S1P3). In addition, we determined the concentrations of S1P as well as different chain-lengths of ceramides using HPLC-MS/MS. RESULTS: Immunohistochemical analysis revealed an altered expression of ceramide, ASM, and S1P receptors by reactive astrocytes and microglial cells specifically associated with capCAA. Moreover, a shift in the balance of ceramides with different chain-lengths and S1P content is observed in capCAA. CONCLUSION: Here we provide evidence of a deregulated SL balance in capCAA. The increased levels of ASM and ceramide in activated glia cells suggest that the SL pathway is involved in the neuroinflammatory response in capCAA pathogenesis. Future research is needed to elucidate the role of S1P in capCAA.

Alzheimer's Disease in the Latino Community: Intersection of Genetics and Social Determinants of Health. - Vega, Irving E; Cabrera, Laura Y; Wygant, Cassandra M; Velez-Ortiz, Daniel; Counts, Scott E (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is the most common type of dementia among individuals 65 or older. There are more than 5 million diagnosed cases in the US alone and this number is expected to triple by 2050. Therefore, AD has reached epidemic proportions with significant socioeconomic implications. While aging in general is the greatest risk factor for AD, several additional demographic factors that have contributed to the rise in AD in the US are under study. One such factor is associated with the relatively fast growth of the Latino population. Several reports indicate that AD is more prevalent among blacks and Latinos. However, the reason for AD disparity among different ethnic groups is still poorly understood and highly controversial. The Latino population is composed of different groups based on nationality, namely South and Central America, Mexico, and Caribbean Hispanics. This diversity among the Latino population represents an additional challenge since there are distinct characteristics associated with AD and comorbidities. In this review, we aim to bring attention to the intersection between social determinants of health and genetic factors associated with AD within the Latino community. We argue that understanding the interplay between identified social determinants of health, co-morbidities, and genetic factors could lead to community empowerment and inclusiveness in research and healthcare services, contributing to improved diagnosis and treatment of AD patients. Lastly, we propose that inserting a neuroethics perspective could help understand key challenges that influence healthcare disparities and contribute to increased risk of AD among Latinos.

Alzheimer's Disease-Associated Cerebrospinal Fluid (CSF) Biomarkers do not Correlate with CSF Volumes or CSF Production Rate. - Edsbagge, Mikael; Andreasson, Ulf; Ambarki, Khalid; Wikkelsø, Carsten; Eklund, Anders; Blennow, Kaj; Zetterberg, Henrik; Tullberg, Mats (J Alzheimers Dis, 2017)
BACKGROUND: Neuropathologically, Alzheimer's disease (AD) is characterized by accumulation of a 42 amino acid peptide called amyloid-β (Aβ42) in extracellular senile plaques together with intraneuronal inclusions of hyperphosphorylated tau protein in neurofibrillary tangles and neuronal degeneration. These changes are reflected in the cerebrospinal fluid (CSF), the volumes and production rates of which vary considerably between individuals, by reduced concentration of Aβ42, increased concentration of phosphorylated tau (P-tau) protein, and increased concentration of total tau (T-tau) protein, respectively. OBJECTIVE: To examine the outstanding question if CSF concentrations of AD associated biomarkers are influenced by variations in CSF volumes, CSF production rate, and intracranial pressure in healthy individuals. METHODS: CSF concentrations of Aβ42, P-tau, and T-tau, as well as a number of other AD-related CSF biomarkers were analyzed together with intracranial subarachnoid, ventricular, and spinal CSF volumes, as assessed by magnetic resonance imaging volumetric measurements, and CSF production rate in 19 cognitively normal healthy subjects (mean age 70.6, SD 3.6 years). RESULTS: Negative correlations were seen between the concentrations of three CSF biomarkers (albumin ratio, Aβ38, and Aβ40), and ventricular CSF volume, but apart from this finding, no significant correlations were observed. CONCLUSION: These results speak against inter-individual variations in CSF volume and production rate as important confounds in the AD biomarker research field.

Amylin Enhances Amyloid-β Peptide Brain to Blood Efflux Across the Blood-Brain Barrier. - Mohamed, Loqman A; Zhu, Haihao; Mousa, Youssef M; Wang, Erming; Qiu, Wei Qiao; Kaddoumi, Amal (J Alzheimers Dis, 2017)
Findings from Alzheimer's disease (AD) mouse models showed that amylin treatment improved AD pathology and enhanced amyloid-β (Aβ) brain to blood clearance; however, the mechanism was not investigated. Using the Tg2576 AD mouse model, a single intraperitoneal injection of amylin significantly increased Aβ serum levels, and the effect was abolished by AC253, an amylin receptor antagonist, suggesting that amylin effect could be mediated by its receptor. Subsequent mechanistic studies showed amylin enhanced Aβ transport across a cell-based model of the blood-brain barrier (BBB), an effect that was abolished when the amylin receptor was inhibited by two amylin antagonists and by siRNA knockdown of amylin receptor Ramp3. To explain this finding, amylin effect on Aβ transport proteins expressed at the BBB was evaluated. Findings indicated that cells treated with amylin induced LRP1 expression, a major receptor involved in brain Aβ efflux, in plasma membrane fraction, suggesting intracellular translocation of LRP1 from the cytoplasmic pool. Increased LRP1 in membrane fraction could explain, at least in part, the enhanced uptake and transport of Aβ across the BBB. Collectively, our findings indicated that amylin induced Aβ brain to blood clearance through amylin receptor by inducing LRP1 subcellular translocation to the plasma membrane of the BBB endothelium.

Amylin Treatment Reduces Neuroinflammation and Ameliorates Abnormal Patterns of Gene Expression in the Cerebral Cortex of an Alzheimer's Disease Mouse Model. - Wang, Erming; Zhu, Haihao; Wang, Xiaofan; Gower, Adam; Wallack, Max; Blusztajn, Jan Krzysztof; Kowall, Neil; Qiu, Wei Qiao (J Alzheimers Dis, 2017)
Our recent study has demonstrated that peripheral amylin treatment reduces the amyloid pathology in the brain of Alzheimer's disease (AD) mouse models, and improves their learning and memory. We hypothesized that the beneficial effects of amylin for AD was beyond reducing the amyloids in the brain, and have now directly tested the actions of amylin on other aspects of AD pathogenesis, especially neuroinflammation. A 10-week course of peripheral amylin treatment significantly reduced levels of cerebral inflammation markers, Cd68 and Iba1, in amyloid precursor protein (APP) transgenic mice. Mechanistic studies indicated the protective effect of amylin required interaction with its cognate receptor because silencing the amylin receptor expression blocked the amylin effect on Cd68 in microglia. Using weighted gene co-expression network analysis, we discovered that amylin treatment influenced two gene modules linked with amyloid pathology: 1) a module related to proinflammation and transport/vesicle process that included a hub gene of Cd68, and 2) a module related to mitochondria function that included a hub gene of Atp5b. Amylin treatment restored the expression of most genes in the APP cortex toward levels observed in the wild-type (WT) cortex in these two modules including Cd68 and Atp5b. Using a human dataset, we found that the expression levels of Cd68 and Atp5b were significantly correlated with the neurofibrillary tangle burden in the AD brain and with their cognition. These data suggest that amylin acts on the pathological cascade in animal models of AD, and further supports the therapeutic potential of amylin-type peptides for AD.

Amyloid-Related Imaging Abnormalities in an Aged Squirrel Monkey with Cerebral Amyloid Angiopathy. - Heuer, Eric; Jacobs, Jessica; Du, Rebecca; Wang, Silun; Keifer, Orion P; Cintron, Amarallys F; Dooyema, Jeromy; Meng, Yuguang; Zhang, Xiaodong; Walker, Lary C (J Alzheimers Dis, 2017)
Amyloid-related imaging abnormalities (ARIA) in magnetic resonance imaging scans have emerged as indicators of potentially serious side effects in clinical trials of therapeutics for Alzheimer's disease. These anomalies include an edematous type (ARIA-E) that appears as hyperintense (bright) regions by T2-weighted MRI, and a type characterized by the deposition of hemosiderin (ARIA-H) that elicits a hypointense signal, especially in T2* susceptibility weighted images. ARIA in general has been linked to the presence of amyloid-β (Aβ)-type cerebral amyloid angiopathy, an accumulation of misfolded Aβ protein in the vascular wall that impairs the integrity of brain blood vessels. However, the pathobiology of ARIA remains poorly understood, in part due to the absence of an animal model of the disorder that would enable a contemporaneous analysis of tissue integrity in the affected region. Here we describe both ARIA-E and ARIA-H in an aged squirrel monkey (Saimiri sciureus), a nonhuman primate model of naturally occurring cerebral amyloid angiopathy. Histopathologic examination of the anomalous region revealed reactive astrocytosis and microgliosis, infiltration of systemic inflammatory/immune cells, damage to axons and myelin, and hemosiderin deposition. The disruption of axons in particular suggests that ARIA-E could have functional consequences for affected regions. The squirrel monkey model can be useful for studying the pathogenesis and long-term effects of ARIA, and for testing the safety and efficacy of emerging therapies for Alzheimer's disease.

Amyloid-β Deposition and Long-Term Progression in Mild Cognitive Impairment due to Alzheimer's Disease Defined with Amyloid PET Imaging. - Hatashita, Shizuo; Wakebe, Daichi (J Alzheimers Dis, 2017)
The aim was to evaluate brain amyloid-β (Aβ) deposition in patients with mild cognitive impairment (MCI) due to Alzheimer's disease (AD) using amyloid PET imaging and clarify the relationship between the annual change in Aβ deposition and disease progression. Forty-eight MCI patients underwent neuropsychological assessment and amyloid PET imaging using [11C]-PIB over a follow-up of 5.7±1.5 years. Thirty-nine MCI patients who had an amyloid-positive scan were defined as MCI due to AD, and 9 MCI patients who had an amyloid-negative scan were included. Regions of interest were defined on co-registered MRI, and the PIB standardized uptake value ratio (SUVR) on the same regions was used over follow-up. Annual change in PIB SUVR was calculated. Patients with MCI due to AD had higher baseline PIB SUVR (1.81±0.32, n = 39, p < 0.01) and a greater annual rate of change in PIB SUVR (0.044±0.027, n = 39, p < 0.01) compared to amyloid-negative MCI patients. Twenty-eight (71.8%) progressed to AD. In patients who progressed during a short duration of 1.7±0.8 years, the annual rate of increase in PIB SUVR was 0.101±0.094 (n = 16, p < 0.05), which was greater compared to patients with long conversion or stable patients. There was a negative correlation between the annual rate of increase in PIB SUVR and duration of progression to AD among individual MCI converters (r = -0.47, n = 28, p < 0.05). The patients defined as MCI due to AD could progress to AD with a shorter period if they have a greater increased annual rate in brain Aβ deposition.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid; Aniline Compounds; Cognitive Dysfunction; Disease Progression; Female; Follow-Up Studies; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Positron-Emission Tomography; Thiazoles

The Anti-Amyloid-β and Neuroprotective Properties of a Novel Tricyclic Pyrone Molecule. - Maezawa, Izumi; Zou, Bende; Di Lucente, Jacopo; Cao, William S; Pascual, Conrado; Weerasekara, Sahani; Zhang, Man; Xie, Xinmin Simon; Hua, Duy H; Jin, Lee-Way (J Alzheimers Dis, 2017)
There is an urgent unmet need for new therapeutics for Alzheimer's disease (AD), the most common cause of dementia in the elderly. Therapeutic approaches targeting amyloid-β (Aβ) and its downstream toxicities have become major strategies in AD drug development. We have taken a rational design approach and synthesized a class of tricyclic pyrone (TP) compounds that show anti-Aβ and other neuroprotective actions. The in vivo efficacy of a lead TP named CP2 to ameliorate AD-like pathologies has been shown in mouse models. Here we report the selection and initial characterization of a new lead TP70, which exhibited an anti-Aβ therapeutic index even higher than CP2. Moreover, TP70 was able to reduce oxidative stress, inhibit acyl-coenzyme A:cholesterol acyltransferase (ACAT), and upregulate the expression of ATP-binding cassette subfamily A, member 1 (ABCA1), actions considered neuroprotective in AD. TP70 further showed excellent pharmacokinetic properties, including brain penetration and oral availability. When administered to 5xFAD mice via intraperitoneal or oral route, TP70 enhanced the overall solubility and decreased the level of cerebral Aβ, including both fibrillary and soluble Aβ species. Interestingly, TP70 enhanced N-methyl-D-aspartate (NMDA) receptor-mediated excitatory post-synaptic potential (EPSP) in the hippocampal CA1 area, increased the magnitude of NMDA-dependent hippocampal long-term potentiation (LTP), a cellular model of learning and memory, and prevented the Aβ oligomer-impaired LTP. Significantly, a single dose of TP70 administered to aged 5xFAD mice was effective in mitigating the impaired LTP induction, recorded at 24 h after administration. Our results support a potential of TP70 in clinical development for AD in view of its synergistic neuroprotective actions, ability to positively modulate NMDA receptor-mediated hippocampal plasticity, and favorable pharmacokinetic properties in rodents.

Aortic Valve Calcification and the Risk of dementia: A Population-Based Study. - Wolters, Frank J; Bos, Daniel; Vernooij, Meike W; Franco, Oscar H; Hofman, Albert; Koudstaal, Peter J; van der Lugt, Aad; Ikram, M Arfan (J Alzheimers Dis, 2017)
The association of aortic valve calcification (AVC) with dementia remains unknown. In 2,428 non-demented participants from the population-based Rotterdam Study, we investigated the association of CT-assessed AVC with risk of dementia and cognitive decline. AVC was present in 33.1% of the population. During a median follow-up of 9.3 years, 160 participants developed dementia. We found no association between presence of AVC and risk of all-cause dementia [hazard ratio (HR): 0.89 (95% confidence interval (CI):0.63;1.26)]. Presence of AVC was not associated with cognitive decline on any of the cognitive tests, nor with a measure of global cognition.

Apolipoprotein E Isoforms Differentially Regulate Alzheimer's Disease and Amyloid-β-Induced Inflammatory Response in vivo and in vitro. - Dorey, Evan; Bamji-Mirza, Michelle; Najem, Dema; Li, Yan; Liu, Hong; Callaghan, Debbie; Walker, Douglas; Lue, Lih-Fen; Stanimirovic, Danica; Zhang, Wandong (J Alzheimers Dis, 2017)
Neuroinflammation plays a critical role in neuronal dysfunction and death of Alzheimer's disease (AD). ApoE4 is a major risk factor of AD, while ApoE2 is neuroprotective. Little is known about the roles of ApoE isoforms in the neuroinflammation seen in AD. Their roles and mechanisms in Aβ-induced/neuroinflammation were investigated in this study using in vivo and in vitro models. Rat astrocytes were treated with lipid-poor recombinant hApoE and/or Aβ42. Mouse astrocyte lines-expressing lipidated hApoE were treated with Aβ42 and/or vitamin D receptor (VDR) agonist, 1α,25-dihydroxyvitamin D3. Cells and media were harvested for cytokine ELISA, RNA isolated for qRT-PCR, and nuclear protein for transcription factor (TF) arrays and EMSA. hApoE-transgenic and AD mice were mated to generate hApoE2/AD and hApoE4/AD mice. Mice were euthanized at 6 months of age. Brain tissues were collected for cytokine ELISA array, Aβ ELISA, immunoblotting, and immunohistochemistry. hApoE4/AD mice had significantly higher levels of inflammatory cytokines than hApoE2/AD mice. Lipidated hApoE4 significantly promoted inflammatory gene expression induced by Aβ42 but not recombinant hApoE4 in astrocytes as compared to controls. Lipidated hApoE3 provided a certain degree of protection against Aβ42-induced inflammatory response but not recombinant hApoE3 as compared to controls. Both lipidated and recombinant hApoE2 provided protection against Aβ42-induced inflammatory response compared to controls. TF array revealed that ApoE2 strongly activated VDR in Aβ42-treated astrocytes. Application of 1α,25-dihydroxyvitamin D3 completely inhibited Aβ-induced inflammatory gene expression in hApoE4-expressing astrocytes. The results suggest that ApoE4 promotes, but ApoE2 inhibits, AD/Aβ-induced neuroinflammation via VDR signaling. Targeting VDR signaling or active form of VD3 may relieve AD neuroinflammation or/and neurodegeneration.

APP Mutations in Cerebral Amyloid Angiopathy with or without Cortical Calcifications: Report of Three Families and a Literature Review. - Sellal, François; Wallon, David; Martinez-Almoyna, Laurent; Marelli, Cecilia; Dhar, Abhinav; Oesterlé, Héléne; Rovelet-Lecrux, Anne; Rousseau, Stéphane; Kourkoulis, Christina E; Rosand, Jon; DiPucchio, Zora Y; Frosch, Matthew; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Specific APP mutations cause cerebral amyloid angiopathy (CAA) with or without Alzheimer's disease (AD). OBJECTIVE: We aimed at reporting APP mutations associated with CAA, describe the clinical, cerebrospinal fluid AD biomarkers, and neuroimaging features, and compare them with the data from the literature. METHODS: We performed a retrospective study in two French genetics laboratories by gathering all clinical and neuroimaging data from patients referred for a genetic diagnosis of CAA with an age of onset before 66 years and fulfilling the other Boston revised criteria. We studied the segregation of mutations in families and performed a comprehensive literature review of all cases reported with the same APP mutation. RESULTS: We screened APP in 61 unrelated French patients. Three mutations, located in the Aβ coding region, were detected in five patients from three families: p.Ala692Gly (Flemish), p.Glu693Lys (Italian), and p.Asp694Asn (Iowa). Patients exhibited CAA and progressive cognitive impairment associated with cortical calcifications in the Iowa and Italian mutation carriers, but not the patient carrying the Flemish mutation. CONCLUSIONS: This is the first evidence of cortical calcification in patients with an APP mutation other than the Iowa mutation. We discuss the radiological, cerebrospinal fluid, and clinical phenotype of patients carrying these mutations in the literature.

Assessment of Driving Safety in Older Adults with Mild Cognitive Impairment. - Anstey, Kaarin J; Eramudugolla, Ranmalee; Chopra, Sidhant; Price, Jasmine; Wood, Joanne M (J Alzheimers Dis, 2017)
BACKGROUND: With population aging, drivers with mild cognitive impairment (MCI) are increasing; however, there is little evidence available regarding their safety. OBJECTIVE: We aimed to evaluate risk of unsafe on-road driving performance among older adults with MCI. METHOD: The study was a cross-sectional observational study, set in Canberra, Australia. Participants were non-demented, current drivers (n = 302) aged 65 to 96 years (M = 75.7, SD = 6.18, 40% female) recruited through the community and primary and tertiary care clinics. Measures included a standardized on-road driving test (ORT), a battery of screening measures designed to evaluate older driver safety (UFOV®, DriveSafe, Multi-D), a neurocognitive test battery, and questionnaires on driving history and behavior. RESULTS: Using Winblad criteria, 57 participants were classified as having MCI and 245 as cognitively normal (CN). While the MCI group had a significantly lower overall safety rating on the ORT (5.61 versus 6.05, p = 0.03), there was a wide range of driving safety scores in the CN and MCI groups. The MCI group performed worse than the CN group on the off-road screening tests. The best fitting model of predictors of ORT performance across the combined sample included age, the Multi-D, and DriveSafe, classifying 90.4% of the sample correctly. CONCLUSION: Adults with MCI exhibit a similar range of driving ability to CN adults, although on average they scored lower on off-road and on-road assessments. Driving specific tests were more strongly associated with safety ratings than traditional neuropsychological tests.

Association Between Later Life Lifestyle Factors and Alzheimer's Disease Biomarkers in Non-Demented Individuals: A Longitudinal Descriptive Cohort Study. - Reijs, Babette L R; Vos, Stephanie J B; Soininen, Hilkka; Lötjönen, Jyrki; Koikkalainen, Juha; Pikkarainen, Maria; Hall, Anette; Vanninen, Ritva; Liu, Yawu; Herukka, Sanna-Kaisa; Freund-Levi, Yvonne; Frisoni, Giovanni B; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Lifestyle factors have been associated with the risk of dementia, but the association with Alzheimer's disease (AD) remains unclear. OBJECTIVE: To examine the association between later life lifestyle factors and AD biomarkers (i.e., amyloid-β 1-42 (Aβ42) and tau in cerebrospinal fluid (CSF), and hippocampal volume) in individuals with subjective cognitive decline (SCD) and mild cognitive impairment (MCI). In addition, to examine the effect of later life lifestyle factors on developing AD-type dementia in individuals with MCI. METHODS: We selected individuals with SCD (n = 111) and MCI (n = 353) from the DESCRIPA and Kuopio Longitudinal MCI studies. CSF Aβ42 and tau concentrations were assessed with ELISA assay and hippocampal volume with multi-atlas segmentation. Lifestyle was assessed by clinical interview at baseline for: social activity, physical activity, cognitive activity, smoking, alcohol consumption, and sleep. We performed logistic and Cox regression analyses adjusted for study site, age, gender, education, and diagnosis. Prediction for AD-type dementia was performed in individuals with MCI only. RESULTS: Later life lifestyle factors were not associated with AD biomarkers or with conversion to AD-type dementia. AD biomarkers were strongly associated with conversion to AD-type dementia, but these relations were not modulated by lifestyle factors. Apolipoprotein E (APOE) genotype did not influence the results. CONCLUSIONS: Later life lifestyle factors had no impact on key AD biomarkers in individuals with SCD and MCI or on conversion to AD-type dementia in MCI.

Association between Mid-Regional Proadrenomedullin Levels and Progression of Deep White Matter Lesions in the Brain Accompanying Cognitive Decline. - Kuriyama, Nagato; Ihara, Masafumi; Mizuno, Toshiki; Ozaki, Etsuko; Matsui, Daisuke; Watanabe, Isao; Koyama, Teruhide; Kondo, Masaki; Tokuda, Takahiko; Tamura, Aiko; Yamada, Kei; Akazawa, Kentaro; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Adrenomedullin (ADM) is a vasoreactive physiological peptide with anti-inflammatory effects and vasodilative and immunomodulatory actions that is widely distributed throughout the vascular system of the brain. OBJECTIVE: To investigate mid-regional proADM (MR-proADM), a stable fragment of the ADM precursor, and cerebral deep white matter lesions (DWMLs) in association with cognitive decline. METHODS: The study participants were 288 patients (194 men, 94 women) who gave consent to participate in a 5-year longitudinal survey on arteriosclerosis from 2008 to 2013. The Fazekas classification system (Grade [G] 0 [normal] to G3 [severe]) was used for the evaluation of DWMLs on brain magnetic resonance imaging (MRI). In addition, all participants were asked to undergo cognitive function tests regarding word/letter fluency, the results of which were assessed for correlations with MR-proADM levels. RESULTS: MR-proADM levels significantly increased with DWML grade progression. The odds ratio for high MR-proADM levels was 3.08 (95% confidence interval: 1.49-5.17) in the groups graded G3 on brain MRI, suggesting that a high level of MR-proADM is an independent risk factor for DWMLs. A significant inverse correlation was observed between MR-proADM levels and cognitive test scores. MR-proADM levels were significantly increased in the G3 group in 2013 compared with 2008. CONCLUSION: MR-proADM levels were significantly different between the DWML groups and inversely correlated with cognitive function test scores, suggesting that high MR-proADM levels and DWMLs are associated with cognitive decline. Therefore, the MR-proADM level may be an effective candidate as a potential diagnostic surrogate marker of cognitive decline.

Association between Plasma Ceramides and Phosphatidylcholines and Hippocampal Brain Volume in Late Onset Alzheimer's Disease. - Kim, Min; Nevado-Holgado, Alejo; Whiley, Luke; Snowden, Stuart G; Soininen, Hilkka; Kloszewska, Iwona; Mecocci, Patrizia; Tsolaki, Magda; Vellas, Bruno; Thambisetty, Madhav; Dobson, Richard J B; Powell, John F; et al. (J Alzheimers Dis, 2017)
Lipids such as ceramides and phosphatidylcholines (PC) have been found altered in the plasma of Alzheimer's disease (AD) patients in a number of discovery studies. For this reason, the levels of 6 ceramides and 3 PCs, with different fatty acid length and saturation levels, were measured in the plasma from 412 participants (AD n = 205, Control n = 207) using mass spectrometry coupled with ultra-performance liquid chromatography. After this, associations with AD status, brain atrophy, and age-related effects were studied. In the plasma of AD participants, cross-sectional analysis revealed elevated levels of three ceramides (Cer16:0 p < 0.01, Cer18:0 p < 0.01, Cer24:1 p < 0.05). In addition, two PCs in AD plasma (PC36:5 p < 0.05, PC38:6 p < 0.05) were found to be depleted compared to the control group, with PC36:5 also associating with hippocampal atrophy (p < 0.01). Age-specific analysis further revealed that levels of Cer16:0, Cer18:0, and Cer20:0 were associated with hippocampal atrophy only in younger participants (age < 75, p < 0.05), while all 3 PCs did so in the older participants (age > 75, p < 0.05). PC36:5 was associated with AD status in the younger group (p < 0.01), while PC38:6 and 40:6 did so in the older group (p < 0.05). In this study, elevated ceramides and depleted PCs were found in the plasma from 205 AD volunteers. Our findings also suggest that dysregulation in PC and ceramide metabolism could be occurring in different stages of AD progression.

Association of Cancer History with Alzheimer's Disease Dementia and Neuropathology. - Yarchoan, Mark; James, Bryan D; Shah, Raj C; Arvanitakis, Zoe; Wilson, Robert S; Schneider, Julie; Bennett, David A; Arnold, Steven E (J Alzheimers Dis, 2017)
BACKGROUND: Cancer and Alzheimer's disease (AD) are common diseases of aging and share many risk factors. Surprisingly, however, epidemiologic data from several recent independent cohort studies suggest that there may be an inverse association between these diseases. OBJECTIVE: To determine the relationship between history of cancer and odds of dementia proximate to death and neuropathological indices of AD. METHODS: Using data from two separate clinical-pathologic cohort studies of aging and AD, the Religious Orders Study (ROS) and the Rush Memory and Aging Project (MAP), we compared odds of AD dementia proximate to death among participants with and without a history of cancer. We then examined the relation of history of cancer with measures of AD pathology at autopsy, i.e., paired helical filament tau (PHFtau) neurofibrillary tangles and amyloid-β load. RESULTS: Participants reporting a history of cancer had significantly lower odds of AD (OR 0.70 [0.55-0.89], p = 0.0040) proximate to death as compared to participants reporting no prior history of cancer. The results remained significant after adjusting for multiple risk factors including age, sex, race, education, and presence of an APOEɛ4 allele. At autopsy, participants with a history of cancer had significantly fewer PHFtau tangles (p < 0.001) than participants without a history of cancer, but similar levels of amyloid-β. CONCLUSIONS: Cancer survivors have reduced odds of developing AD and a lower burden of neurofibrillary tangle deposition.

Association of Central Arterial Stiffness and Pressure Pulsatility with Mild Cognitive Impairment and Dementia: The Atherosclerosis Risk in Communities Study-Neurocognitive Study (ARIC-NCS). - Meyer, Michelle L; Palta, Priya; Tanaka, Hirofumi; Deal, Jennifer A; Wright, Jacqueline; Knopman, David S; Griswold, Michael E; Mosley, Thomas H; Heiss, Gerardo (J Alzheimers Dis, 2017)
BACKGROUND: The association of central arterial stiffness and pressure pulsatility with mild cognitive impairment (MCI) and dementia is not well characterized in the population-based setting. OBJECTIVE: The aim of this study was to quantify the cross-sectional association of arterial stiffness and pressure pulsatility with MCI and dementia among 4,461 older white and black adults from the population-based Atherosclerosis Risk in Communities Study-Neurocognitive Study. METHODS: We used race-stratified multinomial logistic regression to evaluate associations of percentile cut points of carotid-femoral pulse wave velocity, central systolic blood pressure, central pulse pressure, and pulse pressure amplification with MCI and dementia versus no cognitive impairment. RESULTS: Among whites, those with carotid-femoral pulse wave velocity or central systolic blood pressure ≥75th percentile had a higher prevalence of MCI compared to participants <75th percentile (conditional odds ratio (OR); 95% confidence interval (CI): 1.27 (1.02, 1.56) and 1.28 (1.04, 1.57), respectively) and those with central pulse pressure ≥75th percentile had a higher prevalence of MCI (OR 1.27 (95% CI: 1.03, 1.58)) and dementia (OR 1.76 (95% CI: 1.06, 2.92) compared to participants <75th percentile. Also among whites, those with pulse pressure amplification ≤25th percentile had a higher prevalence of dementia compared to participants >25th percentile (OR 1.65; (95% CI: 1.01, 2.70). Weaker associations were seen among black participants. CONCLUSION: Higher arterial stiffness and pulsatility were associated with MCI and dementia in white participants. Longitudinal characterization of the observed associations is warranted to assess whether arterial stiffness and pressure pulsatility predict MCI and dementia among older adults.

Association of Kidney Function Biomarkers with Brain MRI Findings: The BRINK Study. - Vemuri, Prashanthi; Knopman, David S; Jack, Clifford R; Lundt, Emily S; Weigand, Stephen D; Zuk, Samantha M; Thostenson, Kaely B; Reid, Robert I; Kantarci, Kejal; Slinin, Yelena; Lakshminarayan, Kamakshi; Davey, Cynthia S; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Chronic kidney disease (CKD) studies have reported variable prevalence of brain pathologies, in part due to low inclusion of participants with moderate to severe CKD. OBJECTIVE: To measure the association between kidney function biomarkers and brain MRI findings in CKD. METHODS: In the BRINK (BRain IN Kidney Disease) study, MRI was used to measure gray matter volumes, cerebrovascular pathologies (white matter hyperintensity (WMH), infarctions, microhemorrhages), and microstructural changes using diffusion tensor imaging (DTI). We performed regression analyses with estimated glomerular filtration rate (eGFR) and urine albumin to creatinine ratio (UACR) as primary predictors, and joint models that included both predictors, adjusted for vascular risk factors. RESULTS: We obtained 240 baseline MRI scans (150 CKD with eGFR <45 in ml/min/1.73 m2; 16 mild CKD: eGFR 45-59; 74 controls: eGFR≥60). Lower eGFR was associated with greater WMH burden, increased odds of cortical infarctions, and worsening diffusion changes throughout the brain. In eGFR models adjusted for UACR, only cortical infarction associations persisted. However, after adjusting for eGFR, higher UACR provided additional information related to temporal lobe atrophy, increased WMH, and whole brain microstructural changes as measured by increased DTI mean diffusivity. CONCLUSIONS: Biomarkers of kidney disease (eGFR and UACR) were associated with MRI brain changes, even after accounting for vascular risk factors. UACR adds unique additional information to eGFR regarding brain structural and diffusion biomarkers. There was a greater impact of kidney function biomarkers on cerebrovascular pathologies and microstructural brain changes, suggesting that cerebrovascular etiology may be the primary driver of cognitive impairment in CKD.

Autonomic Cardiac Function in Preclinical Alzheimer's Disease. - Santos, Cláudia Y; Machan, Jason T; Wu, Wen-Chih; Snyder, Peter J (J Alzheimers Dis, 2017)
To explore early autonomic cardiac changes in pre-clinical Alzheimer's disease (AD), we have evaluated electrocardiologic measures of vagal tone for 63 adults (ages 55-75) at rest, during cognitive testing, and then again at rest. All subjects had multiple risk factors for AD, and all completed amyloid PET scans (18F-Florbetapir) to determine amyloid positivity (Aβ+). No change in electrocardiographic measures were observed for Aβ+ participants under each testing condition, whereas Aβ-subjects showed an expected increase in vagal tone during the cognitive stress condition. These findings suggest an early relationship between cortical Aβ accumulation, a precursor to AD development, and autonomic cardiac function.

Autophagy-ERK1/2-Involved Disinhibition of Hippocampal Neurons Contributes to the Pre-Synaptic Toxicity Induced by Aβ42 Exposure. - Yin, Yanling; Zhao, Yuanyuan; Han, Song; Zhang, Nan; Chen, Hanyu; Wang, Xiaomin (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a progressive neurodegenerative disease and the most frequent cause of progressive cognitive decline in the elderly population. To date, there is still no effective treatment for AD, requiring more underlying mechanisms. In the present study, we investigated the effects of Aβ42 on the inhibitory synaptic transmission in the cultured hippocampal neurons, and explored the possible mechanism. The frequency, but not amplitude, of miniature inhibitory post-synaptic currents was significantly suppressed by Aβ42, indicating that Aβ42 played its role in inhibitory transmitter release at the pre-synaptic sites. Aβ42 had no effect on miniature excitatory post-synaptic currents, suggesting GABAergic synapses are more susceptible to Aβ42 exposure. However, the number of GABAergic neurons or synapses was not influenced, suggesting the corresponding stage may be a preclinical one. The effect of Aβ42 can be mimicked by PD98059 (an inhibitor of ERK1/2) and blocked by curcumin (an activator of MEK), which reveals Aβ-involved influence is via the decreased phosphorylation of MAPK-ERK1/2. In addition, synaptophysin is confirmed to be a downstream protein of MAPK-ERK1/2 at the pre-synaptic site. At the same time, suppressed autophagy was observed after Aβ42 exposure, and the activation of autophagy increased pERK1/2 level and salvaged the disinhibition of hippocampal neurons. These data suggest that diminished GABAergic tone likely starts from the preclinical stage of AD, so some GABAergic stress test may be effective for identifying cognitively normal elder adults. Strategies against the dysfunction of autophagy should be adopted in the early stage of AD because of its initial effects.

Autotaxin is Related to Metabolic Dysfunction and Predicts Alzheimer's Disease Outcomes. - McLimans, Kelsey E; Willette, Auriel A (J Alzheimers Dis, 2017)
BACKGROUND: Obesity and insulin resistance are associated with neuropathology and cognitive decline in Alzheimer's disease (AD). OBJECTIVE: Ecto-nucleotide pyrophosphatase/phosphodiesterase 2, also called autotaxin, is produced by beige adipose tissue, regulates metabolism, and is higher in AD prefrontal cortex (PFC). Autotaxin may be a novel biomarker of dysmetabolism and AD. METHODS: We studied Alzheimer's Disease Neuroimaging Initiative participants who were cognitively normal (CN; n = 86) or had mild cognitive impairment (MCI; n = 135) or AD (n = 66). Statistical analyses were conducted using SPSS software. Multinomial regression analyses tested if higher autotaxin was associated with higher relative risk for MCI or AD diagnosis, compared to the CN group. Linear mixed model analyses were used to regress autotaxin against MRI, FDG-PET, and cognitive outcomes. Spearman correlations were used to associate autotaxin and CSF biomarkers due to non-normality. FreeSurfer 4.3 derived mean cortical thickness in medial temporal lobe and prefrontal regions of interest. RESULTS: Autotaxin levels were significantly higher in MCI and AD. Each point increase in log-based autotaxin corresponded to a 3.5 to 5 times higher likelihood of having MCI and AD, respectively. Higher autotaxin in AD predicted hypometabolism in the medial temporal lobe [R2 = 0.343, p < 0.001] and PFC [R2 = 0.294, p < 0.001], and worse performance on executive function and memory factors. Autotaxin was associated with less cortical thickness in PFC areas like orbitofrontal cortex [R2 = 0.272, p < 0.001], as well as levels of total tau, p-tau181, and total tau/Aβ1-42. CONCLUSIONS: These results are comparable to previous reports using insulin resistance. CSF autotaxin may be a useful dysmetabolism biomarker for examining AD outcomes and risk.

Baseline Telomere Length and Effects of a Multidomain Lifestyle Intervention on Cognition: The FINGER Randomized Controlled Trial. - Sindi, Shireen; Ngandu, Tiia; Hovatta, Iiris; Kåreholt, Ingemar; Antikainen, Riitta; Hänninen, Tuomo; Levälahti, Esko; Laatikainen, Tiina; Lindström, Jaana; Paajanen, Teemu; Peltonen, Markku; Khalsa, Dharma Singh; et al. (J Alzheimers Dis, 2017)
Leukocyte telomere length (LTL) is a biomarker of aging, and it is associated with lifestyle. It is currently unknown whether LTL is associated with the response to lifestyle interventions. The goal is to assess whether baseline LTL modified the cognitive benefits of a 2-year multidomain lifestyle intervention (exploratory analyses). The Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability (FINGER) was a 2-year randomized controlled trial including 1,260 people at risk of cognitive decline, aged 60-77 years identified from the general population. Participants were randomly assigned to the lifestyle intervention (diet, exercise, cognitive training, and vascular risk management) and control (general health advice) groups. Primary outcome was change in cognition (comprehensive neuropsychological test battery). Secondary outcomes were changes in cognitive domains: memory, executive functioning, and processing speed. 775 participants (392 control, 383 intervention) had baseline LTL (peripheral blood DNA). Mixed effects regression models with maximum likelihood estimation were used to analyze change in cognition as a function of randomization group, time, baseline LTL, and their interaction. Intervention and control groups did not significantly differ at baseline. Shorter LTL was related to less healthy baseline lifestyle. Intervention benefits on executive functioning were more pronounced among those with shorter baseline LTL (p-value for interaction was 0.010 adjusted for age and sex, and 0.007 additionally adjusted for baseline lifestyle factors). The FINGER intervention cognitive benefits were more pronounced with shorter baseline LTL, particularly for executive functioning, indicating that the multidomain lifestyle intervention was especially beneficial among higher-risk individuals.

BDNF Responses in Healthy Older Persons to 35 Minutes of Physical Exercise, Cognitive Training, and Mindfulness: Associations with Working Memory Function. - Håkansson, Krister; Ledreux, Aurélie; Daffner, Kirk; Terjestam, Yvonne; Bergman, Patrick; Carlsson, Roger; Kivipelto, Miia; Winblad, Bengt; Granholm, Ann-Charlotte; Mohammed, Abdul Kadir H (J Alzheimers Dis, 2017)
Brain-derived neurotrophic factor (BDNF) has a central role in brain plasticity by mediating changes in cortical thickness and synaptic density in response to physical activity and environmental enrichment. Previous studies suggest that physical exercise can augment BDNF levels, both in serum and the brain, but no other study has examined how different types of activities compare with physical exercise in their ability to affect BDNF levels. By using a balanced cross over experimental design, we exposed nineteen healthy older adults to 35-minute sessions of physical exercise, cognitive training, and mindfulness practice, and compared the resulting changes in mature BDNF levels between the three activities. We show that a single bout of physical exercise has significantly larger impact on serum BDNF levels than either cognitive training or mindfulness practice in the same persons. This is the first study on immediate BDNF effects of physical activity in older healthy humans and also the first study to demonstrate an association between serum BDNF responsivity to acute physical exercise and working memory function. We conclude that the BDNF increase we found after physical exercise more probably has a peripheral than a central origin, but that the association between post-intervention BDNF levels and cognitive function could have implications for BDNF responsivity in serum as a potential marker of cognitive health.

Benefits of Occupational Therapy in Dementia Patients: Findings from a Real-World Observational Study. - Pimouguet, Clément; Le Goff, Mélanie; Wittwer, Jérôme; Dartigues, Jean-François; Helmer, Catherine (J Alzheimers Dis, 2017)
BACKGROUND: There is a growing interest in developing non-pharmacological approaches in dementia. Clinical efficacy of occupational therapy (OT) under routine care conditions has not been investigated yet. OBJECTIVE: To analyze the short-term effects of OT in patients with dementia; and to identify factors related to greater benefit. METHODS: Patients referred to OT were evaluated before starting a 3-month intervention and at 3 and 6 months later. Measures included: Mini-Mental State Examination (MMSE), Disability Assessment in Dementia (DAD), Neuropsychiatric Inventory (NPI) Questionnaire, patients' quality of life (EQ 5D-VAS), caregivers' burden (Zarit scale), and amount of informal care. Linear mixed models were used to analyze trajectories of outcomes. Logistic regressions with stepwise descending selection were used to study factors associated with benefits. RESULTS: 421 dementia patients benefited from OT (mean MMSE = 17.3). Patients remained cognitively stable over time. Functional performances also remained stable at 3 months and significantly decreased at 6 months (crude reduction of 2.8 points, p < 0.01). Behavioral troubles were significantly reduced over the intervention period and remained stable after (p < 0.01). Patients' quality of life increased over the 3-month intervention (p = 0.16) and significantly decreased thereafter. Caregivers' burden and informal care significantly decreased over the 3-month intervention and remained stable thereafter. Patients who benefited from OT with regard to function were less educated and had higher cognitive level. CONCLUSION: OT may be an effective intervention to maintain cognition and functionality and to reduce psychiatric symptoms in dementia patients. Mild stages of dementia could gain more benefits from OT with regard to functional decline.

Bilingualism and Cognitive Decline: A Story of Pride and Prejudice. - Woumans, Evy; Versijpt, Jan; Sieben, Anne; Santens, Patrick; Duyck, Wouter (J Alzheimers Dis, 2017)
In a recent review, Mukadam, Sommerlad, and Livingston (2017) argue that bilingualism offers no protection against cognitive decline. The authors examined the results of 13 studies (five prospective, eight retrospective) in which monolinguals and bilinguals were compared for cognitive decline and onset of dementia symptoms. Analysis of four of the five prospective studies resulted in the conclusion that there was no difference between monolinguals and bilinguals, whereas seven of the eight retrospective studies actually showed bilingualism to result in a four-to-five year delay of symptom onset. The authors decided to ignore the results from the retrospective studies in favor of those from the prospective studies, reasoning that the former may be confounded by participants' cultural background and education levels. In this commentary, we argue that most of these studies actually controlled for these two variables and still found a positive effect of bilingualism. Furthermore, we argue that the meta-analysis of the prospective studies is not complete, lacking the results of two crucial reports. We conclude that the literature offers substantial evidence for a bilingual effect on the development of cognitive decline and dementia.

Biomarkers and Functional Decline in Prodromal Alzheimer's Disease. - Robb, Catherine; Udeh-Momoh, Chinedu; Wagenpfeil, Stefan; Schöpe, Jakob; Alexopoulos, Panagiotis; Perneczky, Robert (J Alzheimers Dis, 2017)
BACKGROUND: Little is known of possible associations between Alzheimer's disease (AD) biomarkers and instrumental activities of daily living (IADL) change over time. OBJECTIVE: The present study seeks to identify relationships between baseline imaging and fluid biomarker profiles, and decline in IADL utilizing data collated from the Alzheimer's Disease Neuroimaging Initiative (ADNI) cohort. METHODS: Generalized estimating equations analysis, adjusted for cognitive deterioration, was applied to a cohort of 509 individuals from all stages of ADNI, including 156 healthy controls, 189 early mild cognitive impairment (MCI) patients and 164 MCI patients. RESULTS: A significant correlation was found between baseline biomarkers, specifically CSF Aβ and FDG PET, and IADL change over a 3-year period in individuals with MCI. Importantly, comparable correlations between presence of pathological biomarker levels and temporal decline in both functional and cognitive performance were also noted. DISCUSSION: We show that distinct baseline biomarkers may predict latent changes in IADL. Our results necessitate a revision of the commonly held view upholding cognitive changes as the predominant endpoint measure associated with presence of abnormal baseline biomarkers.

Blood-Based Oligomeric and Other Protein Variant Biomarkers to Facilitate Pre-Symptomatic Diagnosis and Staging of Alzheimer's Disease. - Williams, Stephanie M; Schulz, Philip; Rosenberry, Terrone L; Caselli, Richard J; Sierks, Michael R (J Alzheimers Dis, 2017)
Oligomeric forms of amyloid-β (Aβ), tau, and TDP-43 play important roles in Alzheimer's disease (AD), and therefore are promising biomarkers. We previously generated single chain antibody fragments (scFvs) that selectively bind disease-related variants of these proteins including A4, C6T, and E1, which bind different oligomeric Aβ variants; D11C, which binds oligomeric tau; and AD-TDP1 and AD-TDP2, which bind disease related TDP-43 variants. To determine the utility of these disease-related variants as early biomarkers, we first analyzed 11 human sera samples obtained ∼2 years prior to an initial mild cognitive impairment (MCI) diagnosis. While the subsequent diagnoses for the cases covered several different conditions, all samples had elevated protein variant levels relative to the plasma controls although with different individual biomarker profiles. We then analyzed a set of longitudinal human plasma samples from four AD (encompassing time points prior to MCI diagnosis and continuing until after conversion to AD) and two control cases. Pre-MCI samples were characterized by high TDP-43 variant levels, MCI samples by high Aβ variant levels, and AD samples by high Aβ and tau variant levels. Sample time points ranged from ∼7 years pre-MCI to ∼9 years after AD conversion. Bivariate correlations showed a negative correlation with TDP-43 levels and positive correlations with cumulative Aβ and oligomeric tau levels indicating an increase in neurodegenerative processes with time in AD. Detection of disease related protein variants not only readily selects AD cases from controls, but also stages progression of AD and holds promise for a pre-symptomatic blood-based biomarker profile for AD.

Brain Biomarkers in Familial Alzheimer's Disease Mouse Models. - Kuttner-Hirshler, Yafit; Venkatasubramanian, Palamadai N; Apolinario, Joan; Bonds, Jacqueline; Wyrwicz, Alice M; Lazarov, Orly (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is characterized by progressive loss of memory and cognitive deterioration. It is thought that the onset of the disease takes place several decades before memory deficits are apparent. Reliable biomarkers for the diagnosis or prognostication of the disease are highly desirable. Neural stem cells (NSC) exist in the adult brain throughout life and give rise to neural progenitor cells (NPC), which differentiate into neurons or glia. The level of NPC proliferation and new neuron formation is significantly compromised in mouse models of familial Alzheimer's disease (FAD). These deficits are readily detected in young adults, at 2-3 months of age, preceding amyloid deposition and cognitive impairments, which may indicate that impaired neurogenesis can be an early biomarker for cognitive deficits in AD. Recent studies suggest that NSC can be detected in live rodents, noninvasively, using proton magnetic resonance spectroscopy (1H-MRS) signal at 1.28 ppm. Here we examined the use of 1H-MRS for determining the extent of neurogenesis in the brains of FAD mice. We observed that the reduction in neurogenesis in the FAD mice as observed by immunohistochemistry, was not manifested by a reduction in the 1.28 ppm signal, suggesting that this marker is either not specific for neurogenesis or not sensitive enough for the detection of alterations in hippocampal neurogenesis in the brains of FAD mice.

Capsaicin Attenuates Amyloid-β-Induced Synapse Loss and Cognitive Impairments in Mice. - Chen, Long; Huang, Zhilin; Du, Yehong; Fu, Min; Han, Huili; Wang, Yutian; Dong, Zhifang (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is the most common cause of progressive cognitive impairment in the aged. The aggregation of the amyloid β-protein (Aβ) is a hallmark of AD and is linked to synapse loss and cognitive impairment. Capsaicin, a specific agonist of the transient receptor potential vanilloid 1 (TRPV1), has been proven to ameliorate stress-induced AD-like pathological and cognitive impairments, but it is unclear whether TRPV1 activation can affect cognitive and synaptic functions in Aβ-induced mouse model of AD. In this study, we investigated the effects of TRPV1 activation on spatial memory and synaptic plasticity in mice treated with Aβ. To induce AD-like pathological and cognitive impairments, adult C57Bl/6 mice were microinjected with Aβ42 (100 μM, 2.5 μl/mouse, i.c.v.). Two weeks after Aβ42 microinjection, spatial learning and memory as well as hippocampal long-term potentiation (LTP) were examined. The results showed that Aβ42 microinjection significantly impaired spatial learning and memory in the Morris water maze and novel object recognition tests compared with controls. These behavioral changes were accompanied by synapse loss and impaired LTP in the CA1 area of hippocampus. More importantly, daily capsaicin (1 mg/kg, i.p.) treatment throughout the experiment dramatically improved spatial learning and memory and synaptic function, as reflected by enhanced hippocampal LTP and reduced synapse loss, whereas the TRPV1 antagonist capsazepine (1 mg/kg, i.p.) treatment had no effects on cognitive and synaptic function in Aβ42-treated mice. These results indicate that TRPV1 activation by capsaicin rescues cognitive deficit in the Aβ42-induced mouse model of AD both structurely and functionally.

Central Olfactory Dysfunction in Alzheimer's Disease and Mild Cognitive Impairment: A Functional MRI Study. - Vasavada, Megha M; Martinez, Brittany; Wang, Jianli; Eslinger, Paul J; Gill, David J; Sun, Xiaoyu; Karunanayaka, Prasanna; Yang, Qing X (J Alzheimers Dis, 2017)
BACKGROUND: Olfactory deficits are present in early Alzheimer's disease (AD) and mild cognitively impaired (MCI) patients. However, whether these deficits are due to dysfunction of the central or peripheral olfactory nervous system remains uncertain. This question is fundamentally important for developing imaging biomarkers for AD using olfactory testing. OBJECTIVE: This study sought to use olfactory functional magnetic resonance imaging (fMRI) to further demonstrate the involvement of the central olfactory system in olfactory deficits in MCI and AD. METHODS: We investigated the central olfactory system in 27 cognitively normal controls (CN), 21 MCI, and 15 AD subjects using olfactory fMRI with an odor-visual association paradigm during which a visual cue was paired with lavender odorant (odor condition) or odorless air (no-odor condition). RESULTS: The CN subjects had significantly greater activated volume in the primary olfactory cortex during both the odor and no-odor conditions compared to either the MCI or AD groups (p < 0.05). No significant differences were observed between the odor and no-odor conditions within each group. No-odor condition activation in AD and MCI correlated with the cognitive and olfactory assessments. CONCLUSION: The no-odor condition, allowing investigation of activation patterns when the peripheral olfactory system was not directly involved, elicited the same functional response as the odor condition for each of the three groups. Thus, the olfactory activation deficits present in AD and MCI patients are most likely caused by degeneration of the central olfactory nervous system.

Cerebral Artery Pulsatility is Associated with Cognitive Impairment and Predicts Dementia in Individuals with Subjective Memory Decline or Mild Cognitive Impairment. - Chung, Chih-Ping; Lee, Hsiang-Ying; Lin, Po-Chen; Wang, Pei-Ning (J Alzheimers Dis, 2017)
The concept that excess pulsation in cerebral arteries might be involved at the early stage of dementia is based on the results of studies on aorta stiffness. In these studies, aorta stiffness is cross-sectionally associated with cognitive impairment and longitudinally related to cognitive decline in non-demented subjects. However, a direct measure of cerebral artery pulsatility is absent in the literature. We aimed to investigate the associations between cerebral artery pulsatility and (1) different cognitive-domains and (2) conversion to dementia in non-demented individuals at the prodromal-stage of Alzheimer's disease (AD). Non-demented individuals with subjective memory decline or mild cognitive impairment were included. Neuropsychological tests at baseline and cognitive status at 6 years were evaluated. Cerebral pulsatility was assessed in the middle cerebral artery (MCA) and posterior cerebral artery by transcranial color-coded sonography. Multivariate-analyses of 79 subjects with robust acoustic windows showed that increased pulsatility in cerebral arteries was significantly associated with impairment in corresponding cognitive domains. Analyses in 54 subjects who completed 6-year follow up revealed that high left MCA pulsation (pulsatility index≥1.1) independently predicted conversion to AD with an odds-ratio of 11.2. Our results demonstrate the spatio-temporal relationship between increased cerebral artery pulsation and cognitive impairment and suggest that increased cerebrovascular pulsation might be involved in the early pathogenesis of AD. Cerebrovascular pulsation may be a therapeutic target to prevent/delay AD onset. Future studies with other AD biomarkers and animal/cell models of increased vascular-pulsation are needed to elucidate the mechanisms by which cerebrovascular pulsatile injury initiates or precipitates neurodegeneration in AD.

The Cerebrospinal Fluid Aβ1-42/Aβ1-40 Ratio Improves Concordance with Amyloid-PET for Diagnosing Alzheimer's Disease in a Clinical Setting. - Niemantsverdriet, Ellis; Ottoy, Julie; Somers, Charisse; De Roeck, Ellen; Struyfs, Hanne; Soetewey, Femke; Verhaeghe, Jeroen; Van den Bossche, Tobi; Van Mossevelde, Sara; Goeman, Johan; De Deyn, Peter Paul; Mariën, Peter; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Evidence suggests that the concordance between amyloid-PET and cerebrospinal fluid (CSF) amyloid-β (Aβ) increases when the CSF Aβ1-42/Aβ1-40 ratio is used as compared to CSF Aβ1-42 levels alone. OBJECTIVE: In order to test this hypothesis, we set up a prospective longitudinal study comparing the concordance between different amyloid biomarkers for Alzheimer's disease (AD) in a clinical setting. METHODS: Seventy-eight subjects (AD dementia (n = 17), mild cognitive impairment (MCI, n = 48), and cognitively healthy controls (n = 13)) underwent a [18F]Florbetapir ([18F]AV45) PET scan, [18F]FDG PET scan, MRI scan, and an extensive neuropsychological examination. In a large subset (n = 67), a lumbar puncture was performed and AD biomarkers were analyzed (Aβ1-42, Aβ1-40, T-tau, P-tau181). RESULTS: We detected an increased concordance in the visual and quantitative (standardized uptake value ratio (SUVR) and total volume of distribution (VT)) [18F]AV45 PET measures when the CSF Aβ1-42/Aβ1-40 was applied compared to Aβ1-42 alone. CSF biomarkers were stronger associated to [18F]AV45 PET for SUVR values when considering the total brain white matter as reference region instead of cerebellar grey matterConclusions:The concordance between CSF Aβ and [18F]AV45 PET increases when the CSF Aβ1-42/Aβ1-40 ratio is applied. This finding is of most importance for the biomarker-based diagnosis of AD as well as for selection of subjects for clinical trials with potential disease-modifying therapies for AD.

Cerebrospinal Fluid Aβ42/Aβ40 as a Means to Limiting Tube- and Storage-Dependent Pre-Analytical Variability in Clinical Setting. - Gervaise-Henry, Christelle; Watfa, Gasshan; Albuisson, Eliane; Kolodziej, Allan; Dousset, Brigitte; Olivier, Jean-Luc; Jonveaux, Thérèse Rivasseau; Malaplate-Armand, Catherine (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) cerebrospinal fluid (CSF) biomarkers have recently been included in the criteria for AD diagnosis. Unfortunately, their wider use in routine and interpretation require more standardization, particularly for the pre-analytical steps. In particular, amyloid-β (Aβ)42 peptide measurement is strongly influenced by the type of collection tube and by repeated freeze/thaw cycles. OBJECTIVE: The objectives of this study were to compare, in clinical setting, the impact of collection tubes and the repetition of freeze/thaw cycles on Aβ42 and Aβ40 concentrations and consequently determine if the Aβ42/Aβ40 ratio could resolve the diagnosis difficulties related to these pre-analytical parameters. METHODS: CSF from 35 patients was collected in different polypropylene (PP) and stored at - 80°C after sampling. For CSF collected in the reference tube, three successive freeze-thaw cycles were done. Aβ42 and Aβ40 concentrations were determined in each condition in order to calculate the Aβ42/Aβ40 ratio. RESULTS: Our results showed that CSF Aβ42 and Aβ40 values were significantly different according to the type of collection tube and the number of freeze/thaw cycles. Although the calculation of the Aβ42/Aβ40 ratio eliminated the effect of PP tube-dependent variation, this was not the case for freeze-thaw cycle-associated variation. CONCLUSION: The use of Aβ42/Aβ40 ratio rather than Aβ42 alone could contribute toward pre-analytical standardization, thus allowing the general use of CSF AD biomarkers in routine practice.

Cerebrospinal Fluid Biomarkers and Clinical Progression in Patients with Subjective Cognitive Decline and Mild Cognitive Impairment. - Wolfsgruber, Steffen; Polcher, Alexandra; Koppara, Alexander; Kleineidam, Luca; Frölich, Lutz; Peters, Oliver; Hüll, Michael; Rüther, Eckart; Wiltfang, Jens; Maier, Wolfgang; Kornhuber, Johannes; Lewczuk, Piotr; et al. (J Alzheimers Dis, 2017)
BACKGROUND: There is very limited data on the prevalence of abnormal cerebrospinal fluid (CSF) biomarkers of Alzheimer's disease (AD) and their predictive value for clinical progression in memory clinic patients with subjective cognitive decline (SCD). OBJECTIVE: To assess the frequency of abnormal CSF biomarkers of AD and their predictive value for clinical progression in memory clinic patients with SCD in comparison to patients with mild cognitive impairment (MCI) from the same cohort. METHODS: We analyzed prospective data from memory clinic patients of the German Competence Network Dementia cohort with a baseline diagnosis of SCD (n = 82) or MCI (n = 134), distinguished by actuarial neuropsychological MCI criteria ("Jak-Bondi criteria"). Risk of clinical progression during 3-year follow-up was evaluated with Cox-Proportional-Hazard models. RESULTS: Prevalence of abnormal values in CSF markers of tau-mediated neurodegeneration (67.8% versus 46.3%) but not of amyloid deposition (40.3% versus 35.4%) was significantly higher in MCI compared to SCD. The rate of incident AD dementia (26.1% versus 12.2%) was also significantly higher in MCI. In SCD, additional 22% progressed to MCI during follow-up. Combined amyloid/tau abnormality was the strongest predictor of clinical progression in both groups. CONCLUSION: High prevalence of biomarker abnormality and clinical progression, together with the predictive value of CSF biomarkers, in memory clinic patients with SCD support the validity and usefulness of this condition as a "pre-MCI" at risk stage of AD.

Cerebrospinal Fluid Biomarkers for Alzheimer's Disease: A View of the Regulatory Science Qualification Landscape from the Coalition Against Major Diseases CSF Biomarker Team. - Arnerić, Stephen P; Batrla-Utermann, Richard; Beckett, Laurel; Bittner, Tobias; Blennow, Kaj; Carter, Leslie; Dean, Robert; Engelborghs, Sebastiaan; Genius, Just; Gordon, Mark Forrest; Hitchcock, Janice; Kaplow, June; et al. (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) drug development is burdened with the current requirement to conduct large, lengthy, and costly trials to overcome uncertainty in patient progression and effect size on treatment outcome measures. There is an urgent need for the discovery, development, and implementation of novel, objectively measured biomarkers for AD that would aid selection of the appropriate subpopulation of patients in clinical trials, and presumably, improve the likelihood of successfully evaluating innovative treatment options. Amyloid deposition and tau in the brain, which are most commonly assessed either in cerebrospinal fluid (CSF) or by molecular imaging, are consistently and widely accepted. Nonetheless, a clear gap still exists in the accurate identification of subjects that truly have the hallmarks of AD. The Coalition Against Major Diseases (CAMD), one of 12 consortia of the Critical Path Institute (C-Path), aims to streamline drug development for AD and related dementias by advancing regulatory approved drug development tools for clinical trials through precompetitive data sharing and adoption of consensus clinical data standards. This report focuses on the regulatory process for biomarker qualification, briefly comments on how it contrasts with approval or clearance of companion diagnostics, details the qualifications currently available to the field of AD, and highlights the current challenges facing the landscape of CSF biomarkers qualified as hallmarks of AD. Finally, it recommends actions to accelerate regulatory qualification of CSF biomarkers that would, in turn, improve the efficiency of AD therapeutic development.

Cerebrospinal Fluid Biomarkers for the Differential Diagnosis between Alzheimer's Disease and Frontotemporal Lobar Degeneration: Systematic Review, HSROC Analysis, and Confounding Factors. - Rivero-Santana, Amado; Ferreira, Daniel; Perestelo-Pérez, Lilisbeth; Westman, Eric; Wahlund, Lars-Olof; Sarría, Antonio; Serrano-Aguilar, Pedro (J Alzheimers Dis, 2017)
BACKGROUND: Differential diagnosis in dementia is at present one of the main challenges both in clinical practice and research. Cerebrospinal fluid (CSF) biomarkers are included in the current diagnostic criteria of Alzheimer's disease (AD) but their clinical utility is still unclear. OBJECTIVE: We performed a systematic review of studies analyzing the diagnostic performance of CSF Aβ42, total tau (t-tau), and phosphorylated tau (p-tau) in the discrimination between AD and frontotemporal lobar degeneration (FTLD) dementias. METHODS: The following electronic databases were consulted until May 2016: Medline and PreMedline, EMBASE, PsycInfo, CINAHL, Cochrane Library, and CRD. For the first-time in the field, a Hierarchical Summary Receiver Operating Characteristic (HRSOC) model was applied, which avoids methodological problems of meta-analyses based on summary points of sensitivity and specificity values. We also investigated relevant confounders of CSF biomarkers' diagnostic performance such as age, disease duration, and global cognitive impairment. RESULTS: The p-tau/Aβ42 ratio showed the best diagnostic performance. No statistically significant effects of the confounders were observed. Nonetheless, the p-tau/Aβ42 ratio may be especially indicated for younger patients. P-tau may be preferable for less cognitively impaired patients (high MMSE scores) and the t-tau/Aβ42 ratio for more cognitively impaired patients (low MMSE scores). CONCLUSION: The p-tau/Aβ42 ratio has potential for being implemented in the clinical routine for the differential diagnosis between AD and FTLD. It is of utmost importance that future studies report information on confounders such as age, disease duration, and cognitive impairment, which should also stimulate understanding of the role of these factors in disease mechanisms and pathophysiology.

Changes in Synaptic Plasticity and Glutamate Receptors in Type 2 Diabetic KK-Ay Mice. - Yin, Huajing; Wang, Weiping; Yu, Wenwen; Li, Jiang; Feng, Nan; Wang, Ling; Wang, Xiaoliang (J Alzheimers Dis, 2017)
In the present study, the progressive alteration of cognition and the mechanisms of reduction in long-term potentiation (LTP) in spontaneous obese KK-Ay type 2 diabetic mice were investigated. In the study, 3-, 5-, and 7-month-old KK-Ay mice were used. The results indicated that KK-Ay mice showed cognitive deficits in the Morris water maze test beginning at the age of 3 months. LTP was significantly impaired in KK-Ay mice during whole study period (3 to 7 months). The above deficits were reversible at an early stage (3 to 5 months old) by diet intervention. Moreover, we found the underlying mechanisms of LTP impairment in KK-Ay mice might be attributed to abnormal phosphorylation or expression of postsynaptic glutamate receptor subunits instead of alteration of basal synaptic transmission. The expression levels of NR1, NR2A, and NR2B subunits of N-methyl-d-aspartate receptors (NMDARs) were unchanged while the Tyr-dependent phosphorylation of both NR2A and NR2B subunits were significantly reduced in KK-Ay mice. The level of p-Src expression mediating this process was decreased, and the level of αCaMKII autophosphorylation was also reduced. Meanwhile, the GluR1 of α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptors (AMPARs) was decreased, and GluR2 was significantly increased. These data suggest that deficits in synaptic plasticity in KK-Ay mice may arise from the abnormal phosphorylation of the NR2 subunits and the alteration of subunit composition of AMPARs. Diet intervention at an early stage of diabetes might alleviate the cognitive deficits and LTP reduction in KK-Ay mice.

Cognitive Rehabilitation in Alzheimer's Disease: A Controlled Intervention Trial. - Brueggen, Katharina; Kasper, Elisabeth; Ochmann, Sina; Pfaff, Henrike; Webel, Steffi; Schneider, Wolfgang; Teipel, Stefan (J Alzheimers Dis, 2017)
BACKGROUND: Cognitive Rehabilitation for Alzheimer's disease (AD) is an integrative multimodal intervention. It aims to maintain autonomy and quality of life by enhancing the patients' abilities to compensate for decreased cognitive functioning. OBJECTIVE: We evaluated the feasibility of a group-based Cognitive Rehabilitation approach in mild AD dementia and assessed its effect on activities of daily living (ADL). METHODS: We included 16 patients with AD dementia in a controlled partial-randomized design. We adapted the manual-guided Cognitive Rehabilitation program (CORDIAL) to a group setting. Over the course of three months, one group received the Cognitive Rehabilitation intervention (n = 8), while the other group received a standardized Cognitive Training as an active control condition (n = 8). ADL-competence was measured as primary outcome. The secondary outcome parameters included cognitive abilities related to daily living, functional cognitive state, and non-cognitive domains, e.g., quality of life. For each scale, we assessed the interaction effect 'intervention by time', i.e., from pre-to post-intervention. RESULTS: We found no significant interaction effect of intervention by time on the primary outcome ADL-competence. The interaction effect was significant for quality of life (Cohen's d: -1.43), showing an increase in the intervention group compared with the control group. CONCLUSIONS: Our study demonstrates the feasibility of a group-based Cognitive Rehabilitation program for patients with mild AD dementia. The Cognitive Rehabilitation showed no significant effect on ADL, possibly reflecting a lack of transfer between the therapy setting and real life. However, the group setting enhanced communication skills and coping mechanisms. Effects on ADL may not have reached statistical significance due to a limited sample size. Furthermore, future studies might use an extended duration of the intervention and integrate caregivers to a greater extent to increase transfer to activities of daily living.

Colivelin Ameliorates Impairments in Cognitive Behaviors and Synaptic Plasticity in APP/PS1 Transgenic Mice. - Wu, Meina; Shi, Hui; He, Yexin; Yuan, Li; Qu, Xuesong; Zhang, Jun; Wang, Zhaojun; Cai, Hongyan; Qi, Jinshun (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is the most common cause of dementia, and effective therapeutics are lacking. Colivelin (CLN), a novel, strong humanin derivative, is effective in vitro in preventing cell death induced by AD-causative genes and amyloid-β protein (Aβ) even at a low concentration. We recently demonstrated that intrahippocampal injection of CLN prevents Aβ25-35-induced deficits in spatial memory and synaptic plasticity in normal rats. Here, we further observed the effects of chronically intranasally (i.n.) administered CLN on cognitive behaviors and pathological hallmarks in 9-month-old APPswe/PS1dE9 (APP/PS1) AD mice using multiple behavioral tests and immunochemistry. The electrophysiological mechanism of CLN neuroprotection was also investigated by recording in vivo hippocampal long-term potentiation (LTP). CLN pretreatment effectively prevented impairments in new object recognition, working memory, and long-term spatial memory and reversed the depression of in vivo hippocampal LTP in APP/PS1 mice. Additionally, chronic application of CLN obviously reduced Aβ deposition in the hippocampus in APP/PS1 mice. These results indicate that CLN has strong neuroprotective effects on learning and memory behaviors in APP/PS1 mice and that this behavioral improvement is closely associated with the reduction of Aβ deposition and alleviation of LTP suppression in the hippocampus, supporting the potential of CLN for the prevention and treatment of AD.

A Common Variant of IL-6R is Associated with Elevated IL-6 Pathway Activity in Alzheimer's Disease Brains. - Haddick, Patrick C G; Larson, Jessica L; Rathore, Nisha; Bhangale, Tushar R; Phung, Qui T; Srinivasan, Karpagam; Hansen, David V; Lill, Jennie R; Pericak-Vance, Margaret A; Haines, Jonathan; Farrer, Lindsay A; Kauwe, John S; et al. (J Alzheimers Dis, 2017)
The common p.D358A variant (rs2228145) in IL-6R is associated with risk for multiple diseases and with increased levels of soluble IL-6R in the periphery and central nervous system (CNS). Here, we show that the p.D358A allele leads to increased proteolysis of membrane bound IL-6R and demonstrate that IL-6R peptides with A358 are more susceptible to cleavage by ADAM10 and ADAM17. IL-6 responsive genes were identified in primary astrocytes and microglia and an IL-6 gene signature was increased in the CNS of late onset Alzheimer's disease subjects in an IL6R allele dependent manner. We conducted a screen to identify variants associated with the age of onset of Alzheimer's disease in APOE ɛ4 carriers. Across five datasets, p.D358A had a meta P = 3 ×10-4 and an odds ratio = 1.3, 95% confidence interval 1.12 -1.48. Our study suggests that a common coding region variant of the IL-6 receptor results in neuroinflammatory changes that may influence the age of onset of Alzheimer's disease in APOE ɛ4 carriers.

Comparison of Gait Parameters for Predicting Cognitive Decline: The Mayo Clinic Study of Aging. - Savica, Rodolfo; Wennberg, Alexandra M V; Hagen, Clinton; Edwards, Kelly; Roberts, Rosebud O; Hollman, John H; Knopman, David S; Boeve, Bradley F; Machulda, Mary M; Petersen, Ronald C; Mielke, Michelle M (J Alzheimers Dis, 2017)
BACKGROUND: Previous studies reported that slower gait speed might predict cognitive impairment and dementing illnesses, supporting the role of gait speed as a possible subclinical marker of cognitive impairment. However, the predictive value of other gait parameters for cognitive decline is unclear. OBJECTIVE: To investigate and compare the association with, and prediction of, specific gait parameters for cognition in a population-based sample. METHODS: The analysis included 3,426 cognitively normal participants enrolled in the Mayo Clinic Study of Aging. At baseline and every 15 months (mean follow-up = 1.93 years), participants had a study coordinator evaluation, neurological examination, and a neuropsychological assessment using nine tests that covered four domains. Gait parameters were assessed with the GAITRite® instrument. General linear mixed effects models were used to compute the annualized rate of change in cognitive domain z-scores, controlling for age, sex, education, depression, comorbidities, body mass index, APOE ɛ4 allele, and visit number, and excluding individuals with a history of stroke, alcoholism, Parkinson's disease, subdural hematoma, and normal pressure hydrocephalus. RESULTS: Spatial (stride length), temporal (ambulatory time, gait speed, step count, cadence, double support time), and spatiotemporal (cadence) gait parameters, and greater intraindividual variability in stride length, swing time, and stance time were associated with a significant decline in global cognition and in specific domains including memory, executive function, visuospatial, and language. CONCLUSIONS: Spatial, temporal, and spatiotemporal measures of gait and greater variability of gait parameters were associated with and predictive of both global- and domain-specific cognitive decline.

Comprehensive Quantitative Profiling of Tau and Phosphorylated Tau Peptides in Cerebrospinal Fluid by Mass Spectrometry Provides New Biomarker Candidates. - Russell, Claire L; Mitra, Vikram; Hansson, Karl; Blennow, Kaj; Gobom, Johan; Zetterberg, Henrik; Hiltunen, Mikko; Ward, Malcolm; Pike, Ian (J Alzheimers Dis, 2017)
Aberrant tau phosphorylation is a hallmark in Alzheimer's disease (AD), believed to promote formation of paired helical filaments, the main constituent of neurofibrillary tangles in the brain. While cerebrospinal fluid (CSF) levels of total tau and tau phosphorylated at threonine residue 181 (pThr181) are established core biomarkers for AD, the value of alternative phosphorylation sites, which may have more direct relevance to pathology, for early diagnosis is not yet known, largely due to their low levels in CSF and lack of standardized detection methods. To overcome sensitivity limitations for analysis of phosphorylated tau in CSF, we have applied an innovative mass spectrometry (MS) workflow, TMTcalibratortrademark, to enrich and enhance the detection of phosphoproteome components of AD brain tissue in CSF, and enable the quantitation of these analytes. We aimed to identify which tau species present in the AD brain are also detectable in CSF and which, if any, are differentially regulated with disease. Over 75% coverage of full-length (2N4R) tau was detected in the CSF with 47 phosphopeptides covering 31 different phosphorylation sites. Of these, 11 phosphopeptides were upregulated by at least 40%, along with an overall increase in tau levels in the CSF of AD patients relative to controls. Use of the TMTcalibratortrademark workflow dramatically improved our ability to detect tau-derived peptides that are directly related to human AD pathology. Further validation of regulated tau peptides as early biomarkers of AD is warranted and is currently being undertaken.

Comprehensive Screening for Disease Risk Variants in Early-Onset Alzheimer's Disease Genes in African Americans Identifies Novel PSEN Variants. - N'Songo, Aurelie; Carrasquillo, Minerva M; Wang, Xue; Nguyen, Thuy; Asmann, Yan; Younkin, Steven G; Allen, Mariet; Duara, Ranjan; Custo, Maria T Greig; Graff-Radford, Neill; Ertekin-Taner, Nilufer (J Alzheimers Dis, 2017)
We conducted a comprehensive screening of rare coding variants in an African American cohort to identify novel pathogenic mutations within the early-onset Alzheimer's disease (EOAD) genes (APP, PSEN1, and PSEN2) in this understudied population. Whole-exome sequencing of 238 African American subjects identified 6 rare missense variants within the EOAD genes, which were observed in AD cases but never among controls. These variants were analyzed in an independent cohort of 300 African American subjects in which PSEN2:NM_000447:exon5:c.T331C:p.Phe111Leu and PSEN1-minilin rs777923890 variants were again not observed, indicating that these novel rare variants, may contribute to AD risk in this population.

Computerized Cognitive Screen (CoCoSc): A Self-Administered Computerized Test for Screening for Cognitive Impairment in Community Social Centers. - Wong, Adrian; Fong, Ching-Hang; Mok, Vincent Chung-Tong; Leung, Kam-Tat; Tong, Raymond Kai-Yu (J Alzheimers Dis, 2017)
BACKGROUND: Computerized cognitive tests may serve as a preliminary, low-cost method to identify individuals with suspected cognitive impairment in the community. OBJECTIVE: To develop a self-administered computerized test, namely the "Computerized Cognitive Screen (CoCoSc), Hong Kong version", for screening of individuals with cognitive impairment (CI) in community settings. METHODS: The CoCoSc is a 15-min computerized cognitive screen covering memory, executive functions, orientation, attention and working memory, and prospective memory administered on a touchscreen computer. Individuals with CI and cognitively normal controls were administered the CoCoSc and the Montreal Cognitive Assessment (MoCA). Validity of the CoCoSc was assessed based on the relationship with the MoCA using Pearson correlation. Receiver operating characteristic curve (ROC) was used to examine the ability of the CoCoSc to differentiate CI from controls. RESULTS: Fifty-nine individuals with CI and 101 controls were recruited. Seventy-five (46.9%) participants had ≤6 years of education. Performance on the CoCoSc differed between normal and CI groups in both low and high education subgroups. Total scores of the CoCoSc and MoCA were significantly correlated (r = 0.71, p < 0.001). The area under ROC was 0.78, p < 0.001 for the CoCoSc total score in differentiating the CI group from the cognitively normal group. A cut-off of ≤30 on the CoCoSc was associated with a sensitivity of 0.78 and specificity of 0.69. The CoCoSc was well accepted by attendees of community social centers. CONCLUSION: The CoCoSc is a promising computerized cognitive screen for self-administration in community social centers. It is feasible for testing individuals with high or low education levels.

The Correlation between Inflammatory Biomarkers and Polygenic Risk Score in Alzheimer's Disease. - Morgan, Angharad R; Touchard, Samuel; O'Hagan, Caroline; Sims, Rebecca; Majounie, Elisa; Escott-Price, Valentina; Jones, Lesley; Williams, Julie; Morgan, B Paul (J Alzheimers Dis, 2017)
Plasma biomarkers to aid the early diagnosis of Alzheimer's disease (AD) or to monitor disease progression have long been sought and continue to be widely studied. Biomarkers that correlate with AD polygenic risk score, a measure of the polygenic architecture of the disease and highly predictive of AD status, would be excellent candidates. Therefore, we undertook a preliminary study to assess the association of plasma inflammatory biomarkers with an overall AD polygenic risk score as well as with an inflammation-specific AD polygenic risk score in a sample set of 93 AD cases. We measured five complement biomarkers [complement receptor 1 (CR1), clusterin, complement component 9 (C9), C1 inhibitor (C1inh), terminal complement complex (TCC)] and the benchmark inflammatory marker C-reactive protein (CRP). Plasma clusterin level showed an association with overall AD polygenic risk score, while clusterin, C1inh, and CRP levels each displayed some association with the inflammatory-specific AD polygenic risk score. The results suggest that elevated plasma levels of inflammatory biomarkers, including complement proteins, associate with polygenic risk scores in AD, further strengthening the link between genetic and biomarker disease predictors and indicating a potential role for these markers in disease prediction and patient stratification in AD.

Cortical Metabolic and Cognitive Correlates of Disorientation in Alzheimer's Disease. - Weissberger, Gali H; Melrose, Rebecca J; Fanale, Candace M; Veliz, Joseph V; Sultzer, David L (J Alzheimers Dis, 2017)
Orientation to time, date, and place is commonly utilized in clinical settings to aid in diagnosis, staging, and monitoring of Alzheimer's disease (AD). This study aimed to identify the cerebral metabolic correlates of orientation in patients with AD, and the degree to which regions associated with orientation overlap with memory-related structures. Eighty-five patients with a diagnosis of probable AD underwent fluorodeoxyglucose positron emission tomography (FDG-PET) and neuropsychological testing. Orientation items from the Dementia Rating Scale and recognition performance from the Consortium to Establish a Registry for AD (CERAD) Word List Learning test were correlated with cerebral glucose metabolism. Post-hoc analyses examined neuropsychological predictors of orientation. Better orientation performance related to greater cerebral metabolism in the bilateral middle-inferior temporal lobes, bilateral middle-posterior cingulate, left angular gyrus, and left middle occipital gyrus. In comparison, higher CERAD recognition discriminability score was associated with greater metabolic activity in left medial temporal lobe regions including the hippocampal and parahippocampal gyri, and the left fusiform gyrus. Post-hoc behavioral analyses revealed multiple cognitive functions to be related to orientation, including list learning, recognition memory, visuospatial functioning, attention, and language. Findings from the present study suggest that disorientation in AD results from dysfunction of a network of structures and cognitive abilities commonly found to be implicated in AD. The study supports the notion that memory is necessary but not sufficient for successful orientation.

Cortical Thickness and Microstructural White Matter Changes Detect Amnestic Mild Cognitive Impairment. - Wang, Zan; Dai, Zhengjia; Shu, Hao; Liu, Duan; Guo, Qihao; He, Yong; Zhang, Zhijun (J Alzheimers Dis, 2017)
Both the apolipoprotein E (APOE) ɛ4 allele and amnestic mild cognitive impairment (aMCI) are considered to be risk factors for Alzheimer's disease (AD). The primary aim of this study was to determine whether the aMCI-related abnormality in gray matter (GM) cortical thickness and white matter (WM) tracts integrity would be modified by the APOE genotype. A total of 146 older adults, including 64 aMCI patients (28 ɛ4 carriers and 36 non-carriers) and 82 healthy controls (39 ɛ4 carriers and 43 non-carriers), underwent a standardized clinical interview, neuropsychological battery assessment, and multi-modal brain magnetic resonance imaging scans. Compared with control subjects, the patients with aMCI showed significantly reduced cortical thickness bilaterally in the parahippocampal gyrus and disrupted WM integrity in the limbic tracts (e.g., increased mean diffusivity in the right parahippocampal cingulum and bilateral uncinate fasciculus). However, no significant main effects of the APOE genotype and diagnosis-by-genotype interaction on GM thickness and WM integrity were observed. Further, diffusivity measures of the limbic WM tracts were significantly correlated with the parahippocampal atrophy in aMCI. Importantly, the parahippocampal thickness and diffusivity measures of the limbic WM tracts were significantly correlated with the cognitive performance (i.e., episodic memory Z score) in patients with aMCI. These results demonstrate that WM microstructural disruptions in the limbic tracts are present at the early stage of AD in an APOE-independent manner; and this degeneration may occur progressively, in parallel with parahippocampal atrophy, and may specifically contribute to early initial impairment in episodic memory.

Cost-Utility of Using Alzheimer's Disease Biomarkers in Cerebrospinal Fluid to Predict Progression from Mild Cognitive Impairment to Dementia. - Handels, Ron L H; Wimo, Anders; Dodel, Richard; Kramberger, Milica G; Visser, Pieter Jelle; Molinuevo, José Luis; Verhey, Frans R J; Winblad, Bengt (J Alzheimers Dis, 2017)
BACKGROUND: Diagnostic research criteria for Alzheimer's disease support the use of biomarkers in the cerebrospinal fluid (CSF) to improve the accuracy of the prognosis regarding progression to dementia for people with mild cognitive impairment (MCI). OBJECTIVE: The aim of this study was to estimate the potential incremental cost-effectiveness ratio of adding CSF biomarker testing to the standard diagnostic workup to determine the prognosis for patients with MCI. METHODS: In an early technology assessment, a mathematical simulation model was built, using available evidence on added prognostic value as well as expert opinion to estimate the incremental costs and quality-adjusted life years (QALYs) of 20,000 virtual MCI patients with (intervention strategy) and without (control strategy) relying on CSF, from a health-care sector perspective and with a 5-year time horizon. RESULTS: Adding the CSF test improved the accuracy of prognosis by 11%. This resulted in an average QALY gain of 0.046 and € 432 additional costs per patient, representing an incremental cost-effectiveness ratio of € 9,416. CONCLUSION: The results show the potential of CSF biomarkers in current practice from a health-economics perspective. This result was, however, marked by a high degree of uncertainty, and empirical research is required into the impact of a prognosis on worrying, false-positive/negative prognosis, and stigmatization.

A Cross-Validation of FDG- and Amyloid-PET Biomarkers in Mild Cognitive Impairment for the Risk Prediction to Dementia due to Alzheimer's Disease in a Clinical Setting. - Iaccarino, Leonardo; Chiotis, Konstantinos; Alongi, Pierpaolo; Almkvist, Ove; Wall, Anders; Cerami, Chiara; Bettinardi, Valentino; Gianolli, Luigi; Nordberg, Agneta; Perani, Daniela (J Alzheimers Dis, 2017)
Assessments of brain glucose metabolism (18F-FDG-PET) and cerebral amyloid burden (11C-PiB-PET) in mild cognitive impairment (MCI) have shown highly variable performances when adopted to predict progression to dementia due to Alzheimer's disease (ADD). This study investigates, in a clinical setting, the separate and combined values of 18F-FDG-PET and 11C-PiB-PET in ADD conversion prediction with optimized data analysis procedures. Respectively, we investigate the accuracy of an optimized SPM analysis for 18F-FDG-PET and of standardized uptake value ratio semiquantification for 11C-PiB-PET in predicting ADD conversion in 30 MCI subjects (age 63.57±7.78 years). Fourteen subjects converted to ADD during the follow-up (median 26.5 months, inter-quartile range 30 months). Receiver operating characteristic analyses showed an area under the curve (AUC) of 0.89 and of 0.81 for, respectively, 18F-FDG-PET and 11C-PiB-PET. 18F-FDG-PET, compared to 11C-PiB-PET, showed higher specificity (1.00 versus 0.62, respectively), but lower sensitivity (0.79 versus 1.00). Combining the biomarkers improved classification accuracy (AUC = 0.96). During the follow-up time, all the MCI subjects positive for both PET biomarkers converted to ADD, whereas all the subjects negative for both remained stable. The difference in survival distributions was confirmed by a log-rank test (p = 0.002). These results indicate a very high accuracy in predicting MCI to ADD conversion of both 18F-FDG-PET and 11C-PiB-PET imaging, the former showing optimal performance based on the SPM optimized parametric assessment. Measures of brain glucose metabolism and amyloid load represent extremely powerful diagnostic and prognostic biomarkers with complementary roles in prodromal dementia phase, particularly when tailored to individual cases in clinical settings.

Curcumin Ameliorates Neuroinflammation, Neurodegeneration, and Memory Deficits in p25 Transgenic Mouse Model that Bears Hallmarks of Alzheimer's Disease. - Sundaram, Jeyapriya Raja; Poore, Charlene Priscilla; Sulaimee, Noor Hazim Bin; Pareek, Tej; Cheong, Wei Fun; Wenk, Markus R; Pant, Harish C; Frautschy, Sally A; Low, Chian-Ming; Kesavapany, Sashi (J Alzheimers Dis, 2017)
Several studies have indicated that neuroinflammation is indeed associated with neurodegenerative disease pathology. However, failures of recent clinical trials of anti-inflammatory agents in neurodegenerative disorders have emphasized the need to better understand the complexity of the neuroinflammatory process in order to unravel its link with neurodegeneration. Deregulation of Cyclin-dependent kinase 5 (Cdk5) activity by production of its hyperactivator p25 is involved in the formation of tau and amyloid pathology reminiscent of Alzheimer's disease (AD). Recent studies show an association between p25/Cdk5 hyperactivation and robust neuroinflammation. In addition, we recently reported the novel link between the p25/Cdk5 hyperactivation-induced inflammatory responses and neurodegenerative changes using a transgenic mouse that overexpresses p25 (p25Tg). In this study, we aimed to understand the effects of early intervention with a potent natural anti-inflammatory agent, curcumin, on p25-mediated neuroinflammation and the progression of neurodegeneration in p25Tg mice. The results from this study showed that curcumin effectively counteracted the p25-mediated glial activation and pro-inflammatory chemokines/cytokines production in p25Tg mice. Moreover, this curcumin-mediated suppression of neuroinflammation reduced the progression of p25-induced tau/amyloid pathology and in turn ameliorated the p25-induced cognitive impairments. It is widely acknowledged that to treat AD, one must target the early-stage of pathological changes to protect neurons from irreversible damage. In line with this, our results demonstrated that early intervention of inflammation could reduce the progression of AD-like pathological outcomes. Moreover, our data provide a rationale for the potential use of curcuminoids in the treatment of inflammation associated neurodegenerative diseases.

Current Approaches and Clinician Attitudes to the Use of Cerebrospinal Fluid Biomarkers in Diagnostic Evaluation of Dementia in Europe. - Miller, Anne-Marie; Balasa, Mircea; Blennow, Kaj; Gardiner, Mary; Rutkowska, Aleksandra; Scheltens, Philip; Teunissen, Charlotte E; Visser, Pieter Jelle; Winblad, Bengt; Waldemar, Gunhild; Lawlor, Brian (J Alzheimers Dis, 2017)
BACKGROUND: BIOMARKAPD seeks to diminish the barriers associated with the clinical use of cerebrospinal fluid (CSF) biomarker analysis by reducing variation in CSF laboratory methodologies and generating consensus recommendations on their clinical interpretation and application for dementia diagnosis. OBJECTIVE: To examine the disparity in practitioner attitudes and clinical practice relating to the use of CSF biomarkers for dementia diagnosis across Europe. METHODS: Clinical dementia experts were surveyed on the prevalence of national consensus guidelines and analytical reimbursement across Europe, their biomarker platform preferences, lumbar puncture methodologies and application of reference values and cut-offs for CSF analysis. RESULTS: 74% of respondents (total n = 51) use CSF biomarkers in clinical practice and 69% perform lumbar punctures on an outpatient basis. Most use CSF biomarkers to diagnose atypical (84%) and early-onset cases of cognitive impairment (71%) and for the differential diagnosis of other dementias (69%). 82% state they are sufficiently informed about CSF biomarkers yet 61% report a lack of national consensus guidelines on their use for dementia diagnosis. 48% of countries represented do not reimburse clinical CSF analysis costs. 43% report using normal reference ranges derived from publications. CONCLUSION: Variations in attitude and practice relating to CSF biomarkers, widely recognised as barriers to their clinical acceptance, remain evident within and between countries across Europe, even in expert centres. These shortcomings must be addressed by developing consensus guidelines on CSF-related methodologies and their clinical application, to further their use for the diagnostic evaluation of dementia.

Daily Physical Activity Patterns During the Early Stage of Alzheimer's Disease. - Varma, Vijay R; Watts, Amber (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) is a neurodegenerative disease that results in severe disability. Very few studies have explored changes in daily physical activity patterns during early stages of AD when components of physical function and mobility may be preserved. OBJECTIVE: Our study explored differences in daily physical activity profiles, independent of the effects of non-cognitive factors including physical function and age, among individuals with mild AD compared to controls. METHODS: Patients with mild AD and controls (n = 92) recruited from the University of Kansas Alzheimer's Disease Center Registry, wore the Actigraph GT3X+ for seven days, and provided objective physical function (VO2 max) and mobility data. Using multivariate linear regression, we explored whether individuals with mild AD had different daily average and diurnal physical activity patterns compared to controls independent of non-cognitive factors that may affect physical activity, including physical function and mobility. RESULTS: We found that mild AD was associated with less moderate-intensity physical activity (p < 0.05), lower peak activity (p < 0.01), and lower physical activity complexity (p < 0.05) particularly during the morning. Mild AD was not associated with greater sedentary activity or less lower-intensity physical activity across the day after adjusting for non-cognitive covariates. CONCLUSIONS: These findings suggest that factors independent of physical capacity and mobility may drive declines in moderate-intensity physical activity, and not lower-intensity or sedentary activity, during the early stage of AD. This underscores the importance of a better mechanistic understanding of how cognitive decline and AD pathology impact physical activity. Findings emphasize the potential value of designing and testing time-of-day specific physical activity interventions targeting individuals in the early stages of AD, prior to significant declines in mobility and physical function.

Decreased N-Acetyl Aspartate/Myo-Inositol Ratio in the Posterior Cingulate Cortex Shown by Magnetic Resonance Spectroscopy May Be One of the Risk Markers of Preclinical Alzheimer's Disease: A 7-Year Follow-Up Study. - Waragai, Masaaki; Moriya, Masaru; Nojo, Takeshi (J Alzheimers Dis, 2017)
Although molecular positron emission tomography imaging of amyloid and tau proteins can facilitate the detection of preclinical Alzheimer's disease (AD) pathology, it is not useful in clinical practice. More practical surrogate markers for preclinical AD would provide valuable tools. Thus, we sought to validate the utility of conventional magnetic resonance spectroscopy (MRS) as a screening method for preclinical AD. A total of 289 older participants who were cognitively normal at baseline were clinically followed up for analysis of MRS metabolites, including N-acetyl aspartate (NAA) and myo-inositol (MI) in the posterior cingulate cortex (PCC) for 7 years. The 289 participants were retrospectively divided into five groups 7 years after baseline: 200 (69%) remained cognitively normal; 53 (18%) developed mild cognitive impairment (MCI); 21 (7%) developed AD; eight (2%) developed Parkinson's disease with normal cognition, and seven (2%) developed dementia with Lewy bodies (DLB). The NAA/MI ratios of the PCC in the AD, MCI, and DLB groups were significantly decreased compared with participants who maintained normal cognition from baseline to 7 years after baseline. MMSE scores 7 years after baseline were significantly correlated with MI/Cr and NAA/MI ratios in the PCC. These results suggest that cognitively normal elderly subjects with low NAA/MI ratios in the PCC might be at risk of progression to clinical AD. Thus, the NAA/MI ratio in the PCC measured with conventional 1H MRS should be reconsidered as a possible adjunctive screening marker of preclinical AD in clinical practice.

Detecting At-Risk Alzheimer's Disease Cases. - Fladby, Tormod; Pålhaugen, Lene; Selnes, Per; Waterloo, Knut; Bråthen, Geir; Hessen, Erik; Almdahl, Ina Selseth; Arntzen, Kjell-Arne; Auning, Eirik; Eliassen, Carl Fredrik; Espenes, Ragna; Grambaite, Ramune; et al. (J Alzheimers Dis, 2017)
While APOEɛ4 is the major genetic risk factor for Alzheimer's disease (AD), amyloid dysmetabolism is an initial or early event predicting clinical disease and is an important focus for secondary intervention trials. To improve identification of cases with increased AD risk, we evaluated recruitment procedures using pathological CSF concentrations of Aβ42 (pAβ) and APOEɛ4 as risk markers in a multi-center study in Norway. In total, 490 subjects aged 40-80 y were included after response to advertisements and media coverage or memory clinics referrals. Controls (n = 164) were classified as normal controls without first-degree relatives with dementia (NC), normal controls with first-degree relatives with dementia (NCFD), or controls scoring below norms on cognitive screening. Patients (n = 301) were classified as subjective cognitive decline or mild cognitive impairment. Subjects underwent a clinical and cognitive examination and MRI according to standardized protocols. Core biomarkers in CSF from 411 and APOE genotype from 445 subjects were obtained. Cases (both self-referrals (n = 180) and memory clinics referrals (n = 87)) had increased fractions of pAβ and APOEɛ4 frequency compared to NC. Also, NCFD had higher APOEɛ4 frequencies without increased fraction of pAβ compared to NC, and cases recruited from memory clinics had higher fractions of pAβ and APOEɛ4 frequency than self-referred. This study shows that memory clinic referrals are pAβ enriched, whereas self-referred and NCFD cases more frequently are pAβ negative but at risk (APOEɛ4 positive), suitable for primary intervention.

Diabetes and Alzheimer's Disease: Can Tea Phytochemicals Play a Role in Prevention? - Fernando, Warnakulasuriya M A D B; Somaratne, Geeshani; Goozee, Kathryn G; Williams, Shehan; Singh, Harjinder; Martins, Ralph N (J Alzheimers Dis, 2017)
Dementia and diabetes mellitus are prevalent disorders in the elderly population. While recognized as two distinct diseases, diabetes has more recently recognized as a significant contributor to risk for developing dementia, and some studies make reference to type 3 diabetes, a condition resulting from insulin resistance in the brain. Alzheimer's disease, the most common form of dementia, and diabetes, interestingly, share underlying pathological processes, commonality in risk factors, and, importantly, pathways for intervention. Tea has been suggested to possess potent antioxidant properties. It is rich in phytochemicals including, flavonoids, tannins, caffeine, polyphenols, boheic acid, theophylline, theobromine, anthocyanins, gallic acid, and finally epigallocatechin-3-gallate, which is considered to be the most potent active ingredient. Flavonoid phytochemicals, known as catechins, within tea offer potential benefits for reducing the risk of diabetes and Alzheimer's disease by targeting common risk factors, including obesity, hyperlipidemia, hypertension, cardiovascular disease, and stroke. Studies also show that catechins may prevent the formation of amyloid-β plaques and enhance cognitive functions, and thus may be useful in treating patients who have Alzheimer's disease or dementia. Furthermore, other phytochemicals found within tea offer important antioxidant properties along with innate properties capable of modulating intracellular neuronal signal transduction pathways and mitochondrial function.

The Diagnostic and Prognostic Value of Neuropsychological Assessment in Memory Clinic Patients. - Jansen, Willemijn J; Handels, Ron L H; Visser, Pieter Jelle; Aalten, Pauline; Bouwman, Femke; Claassen, Jurgen; van Domburg, Peter; Hoff, Erik; Hoogmoed, Jan; Leentjens, Albert F G; Rikkert, Marcel Olde; Oleksik, Ania M; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Neuropsychological testing has long been embedded in daily clinical practice at memory clinics but the added value of a complete neuropsychological assessment (NPA) to standard clinical evaluation is unknown. OBJECTIVE: To evaluate the added diagnostic and prognostic value of NPA to clinical evaluation only in memory clinic patients. METHODS: In 221 memory clinic patients of a prospective cohort study, clinical experts diagnosed clinical syndrome (subjective cognitive impairment (SCI), mild cognitive impairment (MCI), or dementia) and etiology (Alzheimer's disease (AD) or no AD), and provided a prognosis of disease course (decline or no decline) before and after results of NPA were made available. The reference standard was a panel consensus based on all clinical information at baseline and up to 2 follow-up assessments. RESULTS: With NPA data available, clinicians changed their initial syndromal diagnosis in 22% of patients, and the etiological diagnosis as well as the prognosis in 15%. This led to an increase in correctly classified cases of 18% for syndromal diagnosis, 5% for etiological diagnosis, and 1% for prognosis. NPA data resulted in the largest improvement in patients initially classified as SCI (syndrome: 93.3% (n = 14) correctly reclassified, etiology: net reclassification improvement [NRI] = 0.61, prognosis: NRI = 0.13) or MCI (syndrome: 89.3% (n = 23) correctly reclassified, etiology: NRI = 0.17, prognosis: NRI = 0.14), while there was no improvement in patients with dementia (syndrome: 100% (n = 1) correctly reclassified, etiology: NRI = -0.05, prognosis: NRI = -0.06). Overall, inclusion of NPA in the diagnostic process increased confidence in all diagnoses with 6-7%. CONCLUSION: Administration of a complete NPA after standard clinical evaluation has added value for diagnosing cognitive syndrome and its underlying etiology in patients regarded as non-demented based on the first clinical impression.

Diagnostic Biomarkers of Alzheimer's Disease as Identified in Saliva using 1H NMR-Based Metabolomics. - Yilmaz, Ali; Geddes, Tim; Han, BeomSoo; Bahado-Singh, Ray O; Wilson, George; Imam, Khaled; Maddens, Michael; Graham, Stewart F (J Alzheimers Dis, 2017)
Using 1H NMR metabolomics, we biochemically profiled saliva samples collected from healthy-controls (n = 12), mild cognitive impairment (MCI) sufferers (n = 8), and Alzheimer's disease (AD) patients (n = 9). We accurately identified significant concentration changes in 22 metabolites in the saliva of MCI and AD patients compared to controls. This pilot study demonstrates the potential for using metabolomics and saliva for the early diagnosis of AD. Given the ease and convenience of collecting saliva, the development of accurate and sensitive salivary biomarkers would be ideal for screening those at greatest risk of developing AD.

Diaschisis-Like Association of Hippocampal Atrophy and Posterior Cingulate Cortex Hypometabolism in Cognitively Normal Elderly Depends on Impaired Integrity of Parahippocampal Cingulum Fibers. - Fischer, Florian U; Wolf, Dominik; Fellgiebel, Andreas (J Alzheimers Dis, 2017)
Hippocampal atrophy and hypometabolism of the posterior cingulate cortex (PCC), early markers of Alzheimer's disease (AD), have been shown to be associated in late mild cognitive impairment and early AD via atrophy of connecting cingulum fibers. Recently, a direct association of hippocampal atrophy and PCC hypometabolism has been shown in cognitively normal elderly. We aimed to investigate if this association might be modulated by partly non-hippocampogenic alterations of parahippocampal cingulum (PHC) integrity. 45 cognitively healthy elderly aged 59 to 89 years were included from the Alzheimer's Disease Neuroimaging Initiative. Hippocampal volumes and PCC glucose metabolism were measured using MRI and FDG-PET. PHC fibers connecting the hippocampus and the PCC were reconstructed using diffusion weighted MRI and measures of diffusivity were calculated. Using robust linear regression, interaction effects of PHC diffusivity and hippocampal volume on PCC metabolism were calculated. For both hemispheres, significant interaction effects were found for PHC mean diffusivity. Interaction effects were such that the association of hippocampal volume and PCC metabolism was higher in subjects with increased mean diffusivity in PHC fibers. In cognitively normal elderly, compromised integrity of the PHC may increase the risk of PCC hypometabolism due to hippocampal atrophy. Spared PHC fiber integrity may protect against PCC hypometabolism due to hippocampal atrophy.

Dietary Lycopene Supplementation Improves Cognitive Performances in Tau Transgenic Mice Expressing P301L Mutation via Inhibiting Oxidative Stress and Tau Hyperphosphorylation. - Yu, Lixia; Wang, Weiguang; Pang, Wei; Xiao, Zhonghai; Jiang, Yugang; Hong, Yan (J Alzheimers Dis, 2017)
BACKGROUND: Oxidative stress is implicated in the pathogenesis of Alzheimer's disease (AD) and other tauopathies and participates in their development by promoting hyperphosphorylation of microtubule-associated protein tau. Lycopene, as an effective antioxidant, combined with vitamin E seemed to be additive against oxidative stress. OBJECTIVE: The present study was undertaken to examine whether lycopene or lycopene/vitamin E could exert protective effects on memory deficit and oxidative stress in tau transgenic mice expressing P301L mutation. MATERIALS AND METHODS: P301L transgenic mice were assigned to three groups: P301L group (P301L), P301L+lycopene (Lyc), and P301L+lycopene/vitamin E (Lyc+VE). Age-matched C57BL/6J mice as wild type controls (Con) were used in the present study. Spatial memory was assessed by radial arm while passive memories were evaluated by step-down and step-through tests. Levels of tau phosphorylation were detected by western blot. Oxidative stress biomarkers were measured in the serum using biochemical assay kits. RESULTS: Compared with the control group, P301L mice displayed significant spatial and passive memory impairments, elevated malondialdehyde (MDA) levels and decreased glutathione peroxidase (GSH-Px) activities in serum, and increased tau phosphorylation at Thr231/Ser235, Ser262, and Ser396 in brain. Supplementations of lycopene or lycopene/vitamin E could significantly ameliorate the memory deficits, observably decreased MDA concentrations and increased GSH-Px activities, and markedly attenuated tau hyperphosphorylation at multiple AD-related sites. CONCLUSIONS: Our findings indicated that the combination of lycopene and vitamin E antioxidants acted in a synergistic fashion to bring significant effects against oxidative stress in tauopathies.

Diverging Progression of Network Disruption and Atrophy in Alzheimer's Disease and Semantic Dementia. - Andreotti, Jennifer; Dierks, Thomas; Wahlund, Lars-Olof; Grieder, Matthias (J Alzheimers Dis, 2017)
The progression of cognitive deficits in Alzheimer's disease and semantic dementia is accompanied by grey matter atrophy and white matter deterioration. The impact of neuronal loss on the structural network connectivity in these dementia subtypes is, however, not well understood. In order to gain a more refined knowledge of the topological organization of white matter alterations in dementia, we used a network-based approach to analyze the brain's structural connectivity network. Diffusion-weighted and anatomical MRI images of groups with eighteen Alzheimer's disease and six semantic dementia patients, as well as twenty-one healthy controls were recorded to reconstruct individual connectivity networks. Additionally, voxel-based morphometry, using grey and white matter volume, served to relate atrophy to altered structural connectivity. The analyses showed that Alzheimer's disease is characterized by decreased connectivity strength in various cortical regions. An overlap with grey matter loss was found only in the inferior frontal and superior temporal areas. In semantic dementia, significantly reduced network strength was found in the temporal lobes, which converged with grey and white matter atrophy. Therefore, this study demonstrated that the structural disconnection in early Alzheimer's disease goes beyond grey matter atrophy and is independent of white matter volume loss, an observation that was not found in semantic dementia.

Does Functional Connectivity Provide a Marker for Cognitive Rehabilitation Effects in Alzheimer's Disease? An Interventional Study. - Ochmann, Sina; Dyrba, Martin; Grothe, Michel J; Kasper, Elisabeth; Webel, Steffi; Hauenstein, Karlheinz; Teipel, Stefan J (J Alzheimers Dis, 2017)
BACKGROUND: Cognitive rehabilitation (CR) is a cognitive intervention for patients with Alzheimer's disease (AD) that aims to maintain everyday competences. The analysis of functional connectivity (FC) in resting-state functional MRI has been used to investigate the effects of cognitive interventions. OBJECTIVES: We evaluated the effect of CR on the default mode network FC in a group of patients with mild AD, compared to an active control group. METHODS: We performed a three-month interventional study including 16 patients with a diagnosis of AD. The intervention group (IG) consisted of eight patients, performing twelve sessions of CR. The active control group (CG) performed a standardized cognitive training. We used a seed region placed in the posterior cingulate cortex (PCC) for FC analysis, comparing scans acquired before and after the intervention. Effects were thresholded at a significance of p < 0.001 (uncorrected) and a minimal cluster size of 50 voxels. RESULTS: The interaction of group by time showed a higher increase of PCC connectivity in IG compared to CG in the bilateral cerebellar cortex. CG revealed widespread, smaller clusters of higher FC increase compared with IG. Across all participants, an increase in quality of life was associated with connectivity increase over time in the bilateral precuneus. CONCLUSIONS: CR showed an effect on the FC of the DMN in the IG. These effects need further study in larger samples to confirm if FC analysis may suit as a surrogate marker for the effect of cognitive interventions in AD.

Early Evidence of Low Bone Density and Decreased Serotonergic Synthesis in the Dorsal Raphe of a Tauopathy Model of Alzheimer's Disease. - Dengler-Crish, Christine M; Smith, Matthew A; Wilson, Gina N (J Alzheimers Dis, 2017)
Reduced bone mineral density (BMD) and its clinical sequelae, osteoporosis, occur at a much greater rate in patients with Alzheimer's disease (AD), often emerging early in the disease before significant cognitive decline is seen. Reduced BMD translates to increased bone fracture risk, decreased quality of life, and increased mortality for AD patients. However, the mechanism responsible for this observation is unclear. We hypothesize that bone loss is an additional component of an AD prodrome-changes that emerge prior to dementia and are mediated by dysfunction of the central serotonergic pathways. We characterized the skeletal phenotype of htau mice that express human forms of the microtubule-associated protein tau that become pathologically hyperphosphorylated in AD. Using radiographic densitometry, we measured BMD in female and male htau mice from 2-6 months of age-time-points prior to the presence of significant tauopathy in the hippocampal/entorhinal regions characteristic of this model. We found a significantly reduced BMD phenotype in htau mice that was most pronounced in males. Using western blotting and immunofluorescence, we showed overall reduced tryptophan hydroxylase (TPH) protein in htau brainstem and a 70% reduction in TPH-positive cells in the dorsal raphe nucleus (DRN)-a pivotal structure in the regulation of the adult skeleton. Elevations of hyperphosphorylated tau (ptau) proteins were also measured in brainstem, and co-labeled immunofluorescence studies showed presence of ptau in TPH-positive cells of the DRN as early as 4 months of age in htau mice. Together, these findings demonstrate that reduced BMD occurs earlier than overt degeneration in a tau-based AD model and that pathological changes in tau phosphorylation occur in the serotonin-producing neurons of the brainstem raphe in these mice. This illuminates a need to define a mechanistic relationship between bone loss and serotonergic deficits in early AD.

Effect of APOE Genotype on Amyloid Deposition, Brain Volume, and Memory in Cognitively Normal Older Individuals. - Lim, Yen Ying; Williamson, Robert; Laws, Simon M; Villemagne, Victor L; Bourgeat, Pierrick; Fowler, Christopher; Rainey-Smith, Stephanie; Salvado, Olivier; Martins, Ralph N; Rowe, Christopher C; Masters, Colin L; Maruff, Paul (J Alzheimers Dis, 2017)
BACKGROUND: The association between the apolipoprotein E (APOE) ɛ4 allele and high risk of developing Alzheimer's disease (AD) dementia before the age of 80 has been recognized for over 30 years. However, the timing and mode of action of APOE is not understood, nor has there been a detailed analysis of the effect of APOE genotype on memory, hippocampal volume, and amyloid-β (Aβ) levels in cognitively normal adults. OBJECTIVE: Examine the effect of APOE allelic genotype on the relationship between Aβ levels, hippocampal volume, and memory in cognitively normal adults. METHODS: This is a cross-sectional study of 989 cognitively normal older adults enrolled in the Australian Imaging, Biomarkers and Lifestyle (AIBL) study, all of whom underwent APOE genotyping and memory assessment. A subset of this group underwent PET neuroimaging for Aβ (n = 585) and MRI for hippocampal volume (n = 303). RESULTS: APOEɛ4 homozygotes (ɛ4/ɛ4) showed significantly worse episodic memory and higher Aβ levels than ɛ4 heterozygotes. The relationship between increasing Aβ levels and worse episodic memory was significant for ɛ3 homozygotes (ɛ3/ɛ3), ɛ4 heterozygotes, and strongest for ɛ4 homozygotes. There were no differences in hippocampal volume between APOE groups; the relationship between smaller hippocampal volume and worse episodic memory was significant only for ɛ4 homozygotes. CONCLUSION: APOE acts in a co-dominant fashion on Aβ levels, episodic memory, and hippocampal volume in cognitively normal older adults. APOEɛ4 is central to the events that lead to AD in cognitively normal older adults, likely through a quantitative role in the disruption of Aβ clearance.

Effect of APOE ε4 Genotype on Metabolic Biomarkers in Aging and Alzheimer's Disease. - Morris K, Jill; Uy, Roxanne Adeline Z; Vidoni, Eric D; Wilkins, Heather M; Archer, Ashley E; Thyfault, John P; Miles, John M; Burns, Jeffrey M (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) may have heterogeneous pathophysiological underpinnings, with risk factors including apolipoprotein rmvarep4 (APOE4) genotype and insulin resistance. We hypothesized that distinct phenotypes exist within AD. We examined APOE4 and metabolic biomarkers in 338 subjects (n = 213 nondemented (ND), n = 125 AD). We further characterized steady state free fatty acid (FFA) levels in a subset of 45 participants who had also participated in a hyperinsulinemic-euglycemic clamp. Insulin resistance (HOMA-IR) was elevated in AD versus ND (p = 0.04) and in APOE4 noncarriers versus carriers (p < 0.01). This was driven by increased fasting insulin in AD versus ND (p < 0.01) and in APOE4 non-carriers versus carriers (p = 0.01). Fasting glucose was not different. In subjects who underwent a clamp, there was a group x genotype interaction on FFA levels during hyperinsulinemia (p = 0.03). APOE4 non-carriers with AD had higher FFA levels, while APOE4 carriers with AD exhibited lower FFA levels. Metabolic dysfunction is overrepresented in individuals with AD dementia who do not carry the APOE4 allele. This suggests that important subsets of AD phenotypes may exist that diverge metabolically.

Effect of Spinal Manometers on Cerebrospinal Fluid Amyloid-β Concentration. - Toombs, Jamie; Foiani, Martha S; Paterson, Ross W; Heslegrave, Amanda; Wray, Selina; Schott, Jonathan M; Fox, Nick C; Lunn, Michael P; Blennow, Kaj; Zetterberg, Henrik (J Alzheimers Dis, 2017)
The effect of spinal manometers on cerebrospinal fluid (CSF) amyloid-β (Aβ) concentration was investigated. Pooled human CSF samples were divided in two, one half passed through a manometer into a collection tube, the other transferred directly to a collection tube. CSF was analyzed for Aβ38/40/42 using an electrochemiluminescence immunoassay. Relative to control, use of a manometer decreased Aβ38/40/42 concentration by 5.6% (±1.5SE), 4.4% (±1.7SE), and 4.3% (±2.4SE), respectively. The ratios of Aβ42 :40, Aβ42 :38, and Aβ40 :38 were not affected by manometer treatment. Factors which artificially lower CSF Aβ concentrations are relevant to clinical diagnosis for AD and study design.

Effect Size Analyses of Souvenaid in Patients with Alzheimer's Disease. - Cummings, Jeffrey; Scheltens, Philip; McKeith, Ian; Blesa, Rafael; Harrison, John E; Bertolucci, Paulo H F; Rockwood, Kenneth; Wilkinson, David; Wijker, Wouter; Bennett, David A; Shah, Raj C (J Alzheimers Dis, 2017)
BACKGROUND: Souvenaid® (uridine monophosphate, docosahexaenoic acid, eicosapentaenoic acid, choline, phospholipids, folic acid, vitamins B12, B6, C, and E, and selenium), was developed to support the formation and function of neuronal membranes. OBJECTIVE: To determine effect sizes observed in clinical trials of Souvenaid and to calculate the number needed to treat to show benefit or harm. METHODS: Data from all three reported randomized controlled trials of Souvenaid in Alzheimer's disease (AD) dementia (Souvenir I, Souvenir II, and S-Connect) and an open-label extension study were included in analyses of effect size for cognitive, functional, and behavioral outcomes. Effect size was determined by calculating Cohen's d statistic (or Cramér's V method for nominal data), number needed to treat and number needed to harm. Statistical calculations were performed for the intent-to-treat populations. RESULTS: In patients with mild AD, effect sizes were 0.21 (95% confidence intervals: -0.06, 0.49) for the primary outcome in Souvenir II (neuropsychological test battery memory z-score) and 0.20 (0.10, 0.34) for the co-primary outcome of Souvenir I (Wechsler memory scale delayed recall). No effect was shown on cognition in patients with mild-to-moderate AD (S-Connect). The number needed to treat (6 and 21 for Souvenir I and II, respectively) and high number needed to harm values indicate a favorable harm:benefit ratio for Souvenaid versus control in patients with mild AD. CONCLUSIONS: The favorable safety profile and impact on outcome measures converge to corroborate the putative mode of action and demonstrate that Souvenaid can achieve clinically detectable effects in patients with early AD.

The Effects of Cardiotrophin-1 on Early Synaptic Mitochondrial Dysfunction and Synaptic Pathology in APPswe/PS1dE9 Mice. - Wang, Dongmei; Liu, Xiaozhuan; Liu, Yumei; Li, Sanqiang; Wang, Chenying (J Alzheimers Dis, 2017)
The coexistence of neuronal mitochondrial pathology and synaptic dysfunction is an early pathological feature of Alzheimer's disease (AD). Cardiotrophin-1 (CT-1) has been shown to exhibit impressive neuroprotective effects. Previous studies have shown positive effects of CT-1 on brain glucose metabolism and cognition in APPswe/PS1dE9 transgenic mice; however, little is known about the effects of CT-1 on early synaptic mitochondrial dysfunction and resultant synaptic pathology in the brain. In this study, 4-month-old transgenic mice with brain tissue-specific CT-1 expression were used alone or in combination with APPswe/PS1dE9 transgenic mice to evaluate the effect of CT-1 on synaptic mitochondrial dysfunction and resultant synaptic pathology, and cryptic memory deficits in the APPswe/PS1dE9 transgenic mice. The potential mechanism of action of CT-1 was also examined. Young CT-1×APPswe/PS1dE9 transgenic mice exhibited improvements in long-term learning and memory ability and ameliorations of synaptic mitochondrial/synaptic impairments compared to young APPswe/PS1dE9 transgenic mice. Moreover, CT-1 upregulated the expression of AMPAR and increased AMP-activated protein kinase (AMPK) activity in the hippocampus of APPswe/PS1dE9 transgenic mice. However, AMPK inhibition through shRNA knockdown of AMPKα blocked the neuroprotective effects of CT-1 on the expression of AMPAR and mitochondrial/synaptic dysfunction in Aβ-treated mouse neurons. These results suggest that CT-1 may be a potent candidate for the early prevention and treatment of AD.

Effects of DHA Supplementation on Hippocampal Volume and Cognitive Function in Older Adults with Mild Cognitive Impairment: A 12-Month Randomized, Double-Blind, Placebo-Controlled Trial. - Zhang, Yan-Ping; Miao, Rujuan; Li, Qing; Wu, Tianfeng; Ma, Fei (J Alzheimers Dis, 2017)
Docosahexaenoic acid (DHA) is important for brain function, and higher DHA intake is inversely correlated with relative risk of Alzheimer's disease. The potential benefits of DHA supplementation in people with mild cognitive impairment (MCI) have not been fully examined. Our study aimed to determine the effect of DHA supplementation on cognitive function and hippocampal atrophy in elderly subjects with MCI. This was a randomized, double-blind, placebo-controlled trial in Tianjin, China. 240 individuals with MCI aged 65 years and over were recruited and equalized randomly allocated to the DHA or the placebo group. Participants received 12-month DHA supplementation (2 g/day) or corn oil as placebo. Both global and specific subdomains of cognitive function and hippocampal volume were measured at baseline, 6 months, and 12 months. Both changes were analyzed by repeated-measure analysis of variance (ANOVA). This trial has been registered: ChiCTR-IOR-15006058. A total of 219 participants (DHA: 110, Placebo: 109) completed the trial. The change in mean serum DHA levels was greater in the intervention group (+3.85%) compared to the control group (+1.06%). Repeated-measures analyses of covariance showed that, over 12 months, there was a significant difference in the Full-Scale Intelligence Quotient (ηp2 = 0.084; p = 0.039), Information (ηp2 = 0.439; p = 0.000), and Digit Span (ηp2 = 0.375; p = 0.000) between DHA-treated versus the placebo group. In addition, there were significant differences in volumes of left hippocampus (ηp2 = 0.121, p = 0.016), right hippocampus (ηp2 = 0.757, p = 0.008), total hippocampus (ηp2 = 0.124, p = 0.023), and global cerebrum (ηp2 = 0.145, p = 0.032) between the two groups. These findings suggest that DHA supplementation (2 g/day) for 12 months in MCI subjects can significantly improve cognitive function and slow the progression of hippocampal atrophy. Larger, longer-term confirmatory studies are warranted.

The Effects of Gene Mutations on Default Mode Network in Familial Alzheimer's Disease. - Li, Xiaozhen; Westman, Eric; Thordardottir, Steinunn; Ståhlbom, Anne Kinhult; Almkvist, Ove; Blennow, Kaj; Wahlund, Lars-Olof; Graff, Caroline (J Alzheimers Dis, 2017)
Familial Alzheimer's disease (FAD) mutations have very high penetrance but age at onset and rate of disease progression differ. Neuroimaging and cerebrospinal fluid (CSF) examinations in mutation carriers (MCs) may provide an opportunity to identify early biomarkers that can be used to track disease progression from presymptomatic to the dementia stages of disease. The default mode network (DMN) is a resting state neuronal network composed of regions known to associate with amyloid deposition in AD. We hypothesized that functional connectivity in the DMN might change at pre-clinical stages in FAD MCs and correlate with changes in CSF biomarkers as a consequence of AD brain pathology. To test the hypothesis, we compared the functional connectivity in DMN between pre-MCs/MCs and non-carriers (NCs). No significant differences between pre-MCs and NCs were observed. When comparing all MCs with NCs, significant decreased functional connectivity in the right inferior parietal lobule, right precuneus, and left posterior cingulate cortex were found. We also found statistically significant correlations between CSF amyloid-β 42 and tau protein levels and average Z-score, a resting-state functional MRI measurement reflecting the degree of the correlation between a given voxel's time courses and the time courses corresponding to DMN, from the region with statistical difference. The observed disruption of DMN and pathological levels of AD CSF-biomarkers in FAD MCs are similar to the changes described in sporadic AD, which give further support that amyloid and tau pathology impairs neuronal and synaptic function.

The Effects of LW-AFC on the Hippocampal Transcriptome in Senescence-Accelerated Mouse Prone 8 Strain, a Mouse Model of Alzheimer's Disease. - Wang, Jianhui; Liu, Yang; Cheng, Xiaorui; Zhang, Xiaorui; Liu, Feng; Liu, Gang; Qiao, Shanyi; Ni, Ming; Zhou, Wenxia; Zhang, Yongxiang; Li, Fei (J Alzheimers Dis, 2017)
The senescence-accelerated mouse prone 8 (SAMP8) strain is considered a robust experimental model for developing preventative and therapeutic treatments for Alzheimer's disease (AD), a neurodegenerative disease which cannot be effectively prevented, halted, or cured. Our previous studies showed that LW-AFC, a new formula derived from the classical traditional Chinese medicinal prescription Liuwei Dihuang decoction, ameliorates cognitive deterioration in PrP-hAβPPswe/PS1ΔE9 transgenic mice and SAMP8 mice. This study aims to investigate the mechanism that mediates how LW-AFC improves cognitive deficit on the basis of the transcriptome. We conducted a genome-wide survey of gene expression in the hippocampus in mice from the senescence accelerated mouse resistant 1 (SAMR1) strain, from SAMP8 and from LW-AFC treated SAMP8. The results showed that LW-AFC reversed the transcriptome in the hippocampus of SAMP8 mice. The specific investigation of altered gene expression in subtypes defined by cognitive profiles indicated that the systemic lupus erythematosus pathway, spliceosomes, amyotrophic lateral sclerosis, and the insulin signaling were involved in the improvement of cognitive ability by LW-AFC. The expression of genes Enpp2, Etnk1, Epdr1, and Gm5900 in the hippocampus were correlated with that of LW-AFC's ameliorating cognitive impairment in SAMP8 mice. Because LW-AFC is composed of polysaccharides, glycosides, and oligosaccharides, we infer that LW-AFC has direct or indirect effects on altering gene expressions and regulating pathways in the hippocampus of SAMP8 mice. These data are helpful for the enhanced identification of LW-AFC as new therapeutic modalities to AD.

Effects of Regular and Long-Acting Insulin on Cognition and Alzheimer's Disease Biomarkers: A Pilot Clinical Trial. - Craft, Suzanne; Claxton, Amy; Baker, Laura D; Hanson, Angela J; Cholerton, Brenna; Trittschuh, Emily H; Dahl, Deborah; Caulder, Erin; Neth, Bryan; Montine, Thomas J; Jung, Youngkyoo; Maldjian, Joseph; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Long acting insulin detemir administered intranasally for three weeks enhanced memory for adults with Alzheimer's disease dementia (AD) or amnestic mild cognitive impairment (MCI). The investigation of longer-term administration is necessary to determine whether benefits persist, whether they are similar to benefits provided by regular insulin, and whether either form of insulin therapy affects AD biomarkers. OBJECTIVE: The present study aimed to determine whether four months of treatment with intranasal insulin detemir or regular insulin improves cognition, daily functioning, and AD biomarkers for adults with MCI or AD. METHODS: This randomized, double-blind, placebo-controlled trial included an intent-to-treat sample consisting of 36 adults diagnosed with MCI or mild to moderate AD. Participants received placebo (n = 12), 40 IU of insulin detemir (n = 12), or 40 IU of regular insulin (n = 12) daily for four months, administered with a nasal delivery device. A cognitive battery was administered at baseline and after two and four months of treatment. MRI was administered for all participants and lumbar puncture for a subset (n = 20) at baseline and four months. The primary outcome was change from baseline to four months on a memory composite (sum of Z scores for delayed list and story recall). Secondary outcomes included: global cognition (Alzheimer's Disease Assessment Scale-Cognition), daily functioning (Dementia Severity Rating Scale), MRI volume changes in AD-related regions of interest, and cerebrospinal fluid AD markers. RESULTS: The regular insulin treated group had better memory after two and four months compared with placebo (p < 0.03). No significant effects were observed for the detemir-assigned group compared with the placebo group, or for daily functioning for either group. Regular insulin treatment was associated with preserved volume on MRI. Regular insulin treatment was also associated with reduction in the tau-P181/Aβ42 ratio. CONCLUSION: Future research is warranted to examine the mechanistic basis of treatment differences, and to further assess the efficacy and safety of intranasal insulin.

Effects of Risperidone and Galantamine Treatment on Alzheimer's Disease Biomarker Levels in Cerebrospinal Fluid. - Bloniecki, Victor; Aarsland, Dag; Blennow, Kaj; Cummings, Jeffrey; Falahati, Farshad; Winblad, Bengt; Freund-Levi, Yvonne (J Alzheimers Dis, 2017)
BACKGROUND: Treatment for neuropsychiatric symptoms (NPS) in dementia is insufficient. Antipsychotics and acetylcholinesterase inhibitors are used generating symptomatic improvements in behavior and cognition, but few studies have investigated their effect on Alzheimer's disease (AD) biomarkers in cerebrospinal fluid (CSF). OBJECTIVE: This is a secondary analysis based on an earlier clinical trial comparing the treatment effects on NPS. The aim of this study was to examine whether treatment with risperidone and galantamine affect levels of the biomarkers T-Tau, P-Tau, Aβ1-42, and Aβ42/40-ratio in CSF. The secondary aim was to test if baseline levels of these biomarkers are associated with the clinical course of NPS. METHODS: 83 patients (mean + SD 77.9.6±7.7 years) with dementia and NPS were randomized to galantamine (n = 44) or risperidone (n = 39) treatment. CSF samples were collected at baseline and after 12 weeks. RESULTS: Changes in levels of biomarkers between the two treatment groups did not differ significantly. Low baseline levels of Aβ1 - 42 was significantly associated with reduction of irritability at follow up. Low baseline levels of Aβ1-42, Aβ42/40, and P-Tau were significant correlates of reduction in appetite and eating disorders. CSF Aβ1-42 levels in patients treated with risperidone were significantly decreased at follow up, showing an 8% (40 pg/mL) reduction as compared with baseline (p = 0.03). CONCLUSIONS: Our results suggest that risperidone may affect the CSF profile of AD biomarkers indicating more amyloid pathology. Treatment with galantamine did not affect the CSF biomarkers in any direction. The AD CSF biomarkers displayed correlations with specific NPS suggesting potential research questions to be pursued.

Efficacy and Safety of Donepezil in Chinese Patients with Severe Alzheimer's Disease: A Randomized Controlled Trial. - Jia, Jianping; Wei, Cuibai; Jia, Longfei; Tang, Yi; Liang, Junhua; Zhou, Aihong; Li, Fangyu; Shi, Lu; Doody, Rachelle S (J Alzheimers Dis, 2017)
BACKGROUND: Donepezil has been used worldwide for the treatment of severe Alzheimer's disease (AD). Whether it is also appropriate for severe AD in Chinese patients remains unknown. OBJECTIVE: To determine whether donepezil is effective and tolerable for Chinese patients with severe AD. METHODS: The present study was a 24-week, multicenter, double-blind, randomized, placebo-controlled, parallel-group study conducted at 38 investigational hospitals in China. Patients with severe AD were enrolled in this trial. Patients were randomly assigned in a 1:1 ratio to receive either donepezil or placebo (5 mg for 6 weeks and10 mg for the remaining 18 weeks). The efficacy for donepezil were evaluated by the SIB, the Clinician's Interview-Based Impression of Change-Plus caregiver input (CIBIC-plus) and the MMSE. Safety parameters were monitored throughout. RESULTS: A total of 313 patients included the donepezil (n = 157) and the placebo groups (n = 156). Donepezil group improved more in SIB scores (least squares [LS] mean difference: 4.8, 95% CI 1.56 to 8.08, p = 0.004) and CIBIC-plus scores (drug-placebo difference: -0.4, 95% CI -0.66 to 0.03, p = 0.04) than placebo groups at Week 24. The MMSE scores between drug and placebo groups did not differ significantly. Twenty-nine patients with serious adverse events (SAEs) were reported in donepezil (n = 11) and placebo groups (n = 18) (p = 0.08). Most SAEs were not considered drug-related. CONCLUSION: Donepezil for 24 weeks was more effective than placebo and showed good safety and tolerability in Chinese patients with severe AD. This study supports utility of the drug in severe stages of AD in the Chinese population.

Estimated Glomerular Filtration Rate is not Associated with Alzheimer's Disease in a Northern Ireland Cohort. - Paterson, Euan N; Williams, Michael A; Passmore, Peter; Silvestri, Giuliana; MacGillivray, Tom J; Maxwell, Alexander P; McKay, Gareth J (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) prevalence is increasing globally and typically progresses for several years prior to clinical presentation of dementia. Renal dysfunction and vascular disease have been reported in association with dementia in several cross-sectional and longitudinal studies, and may contribute to AD risk. Experimental and observational studies suggest amyloid-β (Aβ) clearance may be impaired in chronic kidney disease (CKD) indicating a mechanism for increased AD risk. OBJECTIVE: The objective of this study was to compare estimated glomerular filtration rate (eGFR) between individuals with AD and cognitively intact controls, controlling for potential confounding factors. METHODS: A cross-sectional, case-control study was carried out in 317 cognitively normal participants and 253 cases with a clinical diagnosis of AD in a UK tertiary care dementia clinic. Associations were considered using logistic regression adjusting for confounding variables (age, APOEɛ4 genotype, systolic blood pressure, education (left school at 14), and smoking status). RESULTS: AD cases were older than cognitively intact controls, had lower MMSE scores, were more likely to have at least one APOEɛ4 allele, had higher rates of smoking, were more likely to be taking aspirin and/or clopidogrel, and had lower blood pressure. We found no significant association between eGFR and AD both before and following adjustment for appropriate confounders. CONCLUSION: This study failed to find an association between eGFR and AD in a cross-sectional sample study of elderly white individuals.

Evaluation of a DNA Aβ42 Vaccine in Aged NZW Rabbits: Antibody Kinetics and Immune Profile after Intradermal Immunization with Full-Length DNA Aβ42 Trimer. - Lambracht-Washington, Doris; Fu, Min; Wight-Carter, Mary; Riegel, Matthew; Rosenberg, Roger N (J Alzheimers Dis, 2017)
A pathological hallmark of Alzheimer's disease (AD) are amyloid plaques in the brain consisting of aggregated amyloid-β 42 peptide (Aβ42) derived from cellular amyloid-β protein precursor (AβPP). Based on successful experiments in mouse AD models, active immunization with Aβ42 peptide and passive immunizations with anti-Aβ42 antibodies were started in clinical trials. Active Aβ42 peptide immunization in humans had led to an inflammatory autoimmune response, and the trial was stopped. Passive immunizations had shown some effects in slowing AD pathology. Active DNA Aβ42 immunizations administered with the gene gun into the skin elicits a different immune response and is non-inflammatory. While in rodents, good responses had been found for this type of immunization, positive results in larger mammals are missing. We present here results from sixteen New Zealand White Rabbits, which underwent intradermal DNA Aβ42 immunization via gene gun. The humoral immune response was analyzed from blood throughout the study, and cellular immune responses were determined from spleens at the end of the study. A good anti-Aβ antibody response was found in the rabbit model. The T cell response after re-stimulation in cell culture showed no IFNγ producing cells when ELISPOT assays were analyzed from PBMC, but low numbers of IFNγ and IL-17 producing cells were found in ELISPOTS from spleens (both 5 immunizations). Brains from immunized rabbits showed no signs of encephalitis. Based on these results, DNA Aβ42 immunization is highly likely to be safe and effective to test in a possible clinical AD prevention trial in patients.

Evidence of a Cardiovascular Function for Microtubule-Associated Protein Tau. - Betrie, Ashenafi H; Ayton, Scott; Bush, Ashley I; Angus, James A; Lei, Peng; Wright, Christine E (J Alzheimers Dis, 2017)
Aggregation of tau protein into intracellular deposits is a pathognomonic feature of tauopathies such as Alzheimer's disease (AD) and lowering tau is a prominent therapeutic strategy under development. However, the physiological function of tau protein is not well known, particularly in the periphery. Lowering tau protein risks disrupting its physiological role leading to unwanted effects. In this study, the presence of tau protein in cardiac tissue is confirmed and the functional role in the cardiovascular system and the consequences of its loss were explored. Isolated right and left atria and small mesenteric arteries from wild type and tau deficient (KO) mice of two age groups (13 and 23 months old) were used to assess cardiovascular phenotypes. Tau KO mice showed an increased systolic blood pressure and cardiac hypertrophy at 13 months, which was accompanied by a significantly lower right atrial rate and a subtle decrease in the maximum contractility to calcium, isoprenaline, and electrical sympathetic nerve stimulation. Aging tau KO mice to 23 months resulted in cardiac hypertrophy with significantly attenuated left atrial contractility, increased blood pressure, and sensitivity of isolated mesenteric arteries to angiotensin II contraction and isoprenaline relaxation compared to their younger counterparts. This study supports a functional role of tau in the heart and loss of this protein leads to a deterioration in cardiovascular performance which worsens with age. Taken together, these results provide insight into the peripheral function of tau protein, and give caution to the therapeutic strategy of lowering tau protein.

Exercise Training and Functional Connectivity Changes in Mild Cognitive Impairment and Healthy Elders. - Chirles, Theresa J; Reiter, Katherine; Weiss, Lauren R; Alfini, Alfonso J; Nielson, Kristy A; Smith, J Carson (J Alzheimers Dis, 2017)
BACKGROUND: Effective interventions are needed to improve brain function in mild cognitive impairment (MCI), an early stage of Alzheimer's disease (AD). The posterior cingulate cortex (PCC)/precuneus is a hub of the default mode network (DMN) and is preferentially vulnerable to disruption of functional connectivity in MCI and AD. OBJECTIVE: We investigated whether 12 weeks of aerobic exercise could enhance functional connectivity of the PCC/precuneus in MCI and healthy elders. METHODS: Sixteen MCI and 16 healthy elders (age range = 60-88) engaged in a supervised 12-week walking exercise intervention. Functional MRI was acquired at rest; the PCC/precuneus was used as a seed for correlated brain activity maps. RESULTS: A linear mixed effects model revealed a significant interaction in the right parietal lobe: the MCI group showed increased connectivity while the healthy elders showed decreased connectivity. In addition, both groups showed increased connectivity with the left postcentral gyrus. Comparing pre to post intervention changes within each group, the MCI group showed increased connectivity in 10 regions spanning frontal, parietal, temporal and insular lobes, and the cerebellum. Healthy elders did not demonstrate any significant connectivity changes. CONCLUSION: The observed results show increased functional connectivity of the PCC/precuneus in individuals with MCI after 12 weeks of moderate intensity walking exercise training. The protective effects of exercise training on cognition may be realized through the enhancement of neural recruitment mechanisms, which may possibly increase cognitive reserve. Whether these effects of exercise training may delay further cognitive decline in patients diagnosed with MCI remains to be demonstrated.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Exercise; Exercise Test; Female; Gyrus Cinguli; Humans; Image Processing, Computer-Assisted; Linear Models; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Oxygen; Psychiatric Status Rating Scales

The Experiences of People with Dementia and Their Caregivers in Dementia Diagnosis. - Lian, Yan; Xiao, Lily Dongxia; Zeng, Fan; Wu, Xianmu; Wang, Zhen; Ren, Hui (J Alzheimers Dis, 2017)
BACKGROUND: People can live well with dementia if they are diagnosed early and receive early interventions and appropriate dementia management and care. However, dementia is currently under-detected and under-diagnosed. The diagnosis rate is around 50% only in higher-income countries and 5-10% only in low- and middle-income countries. Studies on consumers' experiences in engaging in dementia diagnosis in a socio-cultural context are much needed in order to generate research evidence to inform person-centered dementia care and services. OBJECTIVE: The aim of the study was to understand the experiences of people with dementia and their caregivers in engaging in dementia diagnosis. METHODS: An interpretative study design informed by Gadamer's hermeneutic principles was applied to the present study to achieve the aim of the study. The study was strengthened by applying a social ecological framework to the study design. In total, 23 participants contributed to the interviews or focus group. Thematic analysis was applied to data analysis. RESULTS: Four themes were determined from data and described as: capabilities to detect the memory loss in an early stage, perceptions and beliefs of dementia in the community, different journeys toward the diagnosis and expectations of a smooth journey for others. These findings illuminate a social ecological perspective of improving early detection and timely diagnosis of dementia in the community settings. CONCLUSION: The findings of this study have implications for policy, resource, and practice development. Consumers expect that government subsidized dementia care services in primary care and specialist care settings are needed in order to enable consumer-driven timely diagnosis and dementia management in home care settings.

Face-Name Associative Recognition Deficits in Subjective Cognitive Decline and Mild Cognitive Impairment. - Polcher, Alexandra; Frommann, Ingo; Koppara, Alexander; Wolfsgruber, Steffen; Jessen, Frank; Wagner, Michael (J Alzheimers Dis, 2017)
BACKGROUND: There is a need for more sensitive neuropsychological tests to detect subtle cognitive deficits emerging in the preclinical stage of Alzheimer's disease (AD). Associative memory is a cognitive function supported by the hippocampus and affected early in the process of AD. OBJECTIVE: We developed a short computerized face-name associative recognition test (FNART) and tested whether it would detect memory impairment in memory clinic patients with mild cognitive impairment (MCI) and subjective cognitive decline (SCD). METHODS: We recruited 61 elderly patients with either SCD (n = 32) or MCI (n = 29) and 28 healthy controls (HC) and compared performance on FNART, self-reported cognitive deterioration in different domains (ECog-39), and, in a reduced sample (n = 46), performance on the visual Paired Associates Learning of the CANTAB battery. RESULTS: A significant effect of group on FNART test performance in the total sample was found (p < 0.001). Planned contrasts indicated a significantly lower associative memory performance in the SCD (p = 0.001, d = 0.82) and MCI group (p < 0.001, d = 1.54), as compared to HCs, respectively. The CANTAB-PAL discriminated only between HC and MCI, possibly because of reduced statistical power. Adjusted for depression, performance on FNART was significantly related to ECog-39 Memory in SCD patients (p = 0.024) but not in MCI patients. CONCLUSIONS: Associative memory is substantially impaired in memory clinic patients with SCD and correlates specifically with memory complaints at this putative preclinical stage of AD. Further studies will need to examine the predictive validity of the FNART in SCD patients with regard to longitudinal (i.e., conversion to MCI/AD) and biomarker outcomes.

Financial and Health Literacy Predict Incident Alzheimer's Disease Dementia and Pathology. - Yu, Lei; Wilson, Robert S; Schneider, Julie A; Bennett, David A; Boyle, Patricia A (J Alzheimers Dis, 2017)
BACKGROUND: Domain specific literacy is a multidimensional construct that requires multiple resources including cognitive and non-cognitive factors. OBJECTIVE: We test the hypothesis that domain specific literacy is associated with Alzheimer's disease (AD) dementia and AD pathology after controlling for cognition. METHODS: Participants were community-based older persons who completed a baseline literacy assessment, underwent annual clinical evaluations for up to 8 years, and agreed to organ donation after death. Financial and health literacy was measured using 32 questions and cognition was measured using 19 tests. Annual diagnosis of AD dementia followed standard criteria. AD pathology was examined postmortem by quantifying plaques and tangles. Cox models examined the association of literacy with incident AD dementia. Performance of model prediction for incident AD dementia was assessed using indices for integrated discrimination improvement and continuous net reclassification improvement. Linear regression models examined the independent association of literacy with AD pathology in autopsied participants. RESULTS: All 805 participants were free of dementia at baseline and 102 (12.7%) developed AD dementia during the follow-up. Lower literacy was associated with higher risk for incident AD dementia (p < 0.001), and the association persisted after controlling for cognition (hazard ratio = 1.50, p = 0.004). The model including the literacy measure had better predictive performance than the one with demographics and cognition only. Lower literacy also was associated with higher burden of AD pathology after controlling for cognition (β= 0.07, p = 0.035). CONCLUSION: Literacy predicts incident AD dementia and AD pathology in community-dwelling older persons, and the association is independent of traditional measures of cognition.

Five-Year Longitudinal Brain Volume Change in Healthy Elders at Genetic Risk for Alzheimer's Disease. - Reiter, Katherine; Nielson, Kristy A; Durgerian, Sally; Woodard, John L; Smith, J Carson; Seidenberg, Michael; Kelly, Dana A; Rao, Stephen M (J Alzheimers Dis, 2017)
Neuropathological changes associated with Alzheimer's disease (AD) precede symptom onset by more than a decade. Possession of an apolipoprotein E (APOE) ɛ4 allele is the strongest genetic risk factor for late onset AD. Cross-sectional studies of cognitively intact elders have noted smaller hippocampal/medial temporal volumes in ɛ4 carriers (ɛ4+) compared to ɛ4 non-carriers (ɛ4-). Few studies, however, have examined long-term, longitudinal, anatomical brain changes comparing healthy ɛ4+ and ɛ4- individuals. The current five-year study examined global and regional volumes of cortical and subcortical grey and white matter and ventricular size in 42 ɛ4+ and 30 ɛ4- individuals. Cognitively intact participants, ages 65-85 at study entry, underwent repeat anatomical MRI scans on three occasions: baseline, 1.5, and 4.75 years. Results indicated no between-group volumetric differences at baseline. Over the follow-up interval, the ɛ4+ group experienced a greater rate of volume loss in total grey matter, bilateral hippocampi, right hippocampal subfields, bilateral lingual gyri, bilateral parahippocampal gyri, and right lateral orbitofrontal cortex compared to the ɛ4- group. Greater loss in grey matter volumes in ɛ4+ participants were accompanied by greater increases in lateral, third, and fourth ventricular volumes. Rate of change in white matter volumes did not differentiate the groups. The current results indicate that longitudinal measurements of brain atrophy can serve as a sensitive biomarker for identifying neuropathological changes in persons at genetic risk for AD and potentially, for assessing the efficacy of treatments designed to slow or prevent disease progression during the preclinical stage of AD.

Frequency-Dependent Changes in the Amplitude of Low-Frequency Fluctuations in Mild Cognitive Impairment with Mild Depression. - Li, Yuxia; Jing, Bin; Liu, Han; Li, Yifan; Gao, Xuan; Li, Yongqiu; Mu, Bin; Yu, Haikuo; Cheng, Jinbo; Barker, Peter B; Wang, Hongxing; Han, Ying (J Alzheimers Dis, 2017)
BACKGROUND: Depression is a potential marker of preclinical Alzheimer's disease (AD). However, little is known about the abnormal characteristics revealed by resting-state functional magnetic resonance imaging (rs-fMRI) in mild cognitive impairment (MCI) subjects with depressive symptoms (MCI-d). OBJECTIVE: The study was to examine whether abnormalities in amplitudes of low-frequency oscillation occurred in MCI-d and tried to find the possible spectrum showed higher recognition ability to the diagnosis by utilizing functional MRI (fMRI). METHODS: The amplitude of low-frequency fluctuation (ALFF) and fractional ALFF (fALFF) within full frequency (0.01-0.1 Hz), slow-5 (0.01-0.027 Hz), and slow-4 (0.027-0.073 Hz) were computed using resting-state fMRI data of 27 MCI without depressive symptoms, 19 MCI-d, and 32 well-matched healthy controls (HC). Analysis of covariance was performed on ALFF and fALFF among MCI, MCI-d, and HC groups. RESULTS: Several brain regions showed significant differences in ALFF and fALFF within full frequency, slow-5, and slow-4 bands among three groups. Importantly, receiver operating characteristic analysis revealed that the ALFF values in the full frequency band in the left parahippocampal gyrus and the left precuneus, Slow 5 value in ALFF in the left inferior frontal gyrus, and Slow 4 value in ALFF in the left precuneus could effectively differentiate MCI-d from MCI patients. CONCLUSION: In this study, we found that several changes in special brain regions are associated with MCI and MCI-d patients. And the differences depend on the studied frequency bands of rs-fMRI data. The affective network and the default-mode network might be damaged simultaneously in MCI-d patients.

Gender-Based Cerebral Perfusion Differences in 46,034 Functional Neuroimaging Scans. - Amen, Daniel G; Trujillo, Manuel; Keator, David; Taylor, Derek V; Willeumier, Kristen; Meysami, Somayeh; Raji, Cyrus A (J Alzheimers Dis, 2017)
BACKGROUND: Studies have reported that females have widespread increases in regional cerebral blood flow, but the studies were relatively small and inconsistent. OBJECTIVE: Here we analyzed a healthy and a very large clinical psychiatric population to determine the effect of gender, using single photon emission computed tomography (SPECT). METHODS: Whole brain and region of interest (ROI) gender differences were analyzed in a total of 46,034 SPECT scans at baseline and concentration. The sample included 119 healthy subjects and 26,683 patients (60.4% male, 39.6% female); a subset of 11,587 patients had complete diagnostic information. A total of 128 regions were analyzed according to the AAL Atlas, using ROI Extract and SPSS statistical software programs, controlling for age, diagnoses, and correcting for multiple comparisons. RESULTS: Compared to males, healthy females showed significant whole brain (p < 0.01) and ROI increases in 65 baseline and 48 concentration regions (p < 0.01 corrected). Healthy males showed non-significant increases in 9 and 22 regions, respectively. In the clinical group, there were widespread significant increases in females, especially in the prefrontal and limbic regions, and specific increases in males in the inferior occipital lobes, inferior temporal lobes, and lobule 7 and Crus 2 of the cerebellum. These findings were replicated in the subset of 11,587 patients with the effect of diagnoses removed. CONCLUSIONS: Our results demonstrated significant gender differences in a healthy and clinical population. Understanding these differences is crucial in evaluating functional neuroimaging and may be useful in understanding the epidemiological gender differences among psychiatric disorders.

Generation and Partial Characterization of Rabbit Monoclonal Antibody to Amyloid-β Peptide 1-37 (Aβ37). - Mehta, Pankaj D; Blain, Jean-Francois; Freeman, Emily A; Patrick, Bruce A; Barshatzky, Marc; Hrdlicka, Lori A; Mehta, Sangita P; Frackowiak, Janusz; Mazur-Kolecka, Bozena; Wegiel, Jerzy; Patzke, Holger; Miller, David L (J Alzheimers Dis, 2017)
Secreted soluble amyloid-β 1-37 (Aβ37) peptide is one of the prominent Aβ forms next to Aβ40, and is found in cerebrospinal fluid (CSF) and blood. Recent studies have shown the importance of quantitation of CSF Aβ37 levels in combination with Aβ38, Aβ40, and Aβ42 to support the diagnosis of patients with probable Alzheimer's disease (AD), and the value of antibody to Aβ37 to facilitate drug discovery studies. However, the availability of reliable and specific monoclonal antibody to Aβ37 is very limited. Our aims were: 1) to generate and partially characterize rabbit monoclonal antibody (RabmAb) to Aβ37, and 2) to determine whether the antibody detects changes in Aβ37 levels produced by a γ-secretase modulator (GSM). Our generated RabmAb to Aβ37 was found to be specific to Aβ37, since it did not react with Aβ36, Aβ38, Aβ39, Aβ40, and Aβ42 in an ELISA or immunoblotting. The epitope of the antibody was contained in the seven C-terminal residues of Aβ37. The antibody was sensitive enough to measure CSF and plasma Aβ37 levels in ELISA. Immunohistological studies showed the presence of Aβ37-positive deposits in the brain of AD, and Down syndrome persons diagnosed with AD. Our studies also showed that the antibody detected Aβ37 increases in CSF and brains of rodents following treatment with a GSM. Thus, our antibody can be widely applied to AD research, and in a panel based approach it may have potential to support the diagnosis of probable AD, and in testing the effect of GSMs to target AD.

Heterogeneous Association of Alzheimer's Disease-Linked Amyloid-β and Amyloid-β Protein Precursor with Synapses. - Willén, Katarina; Sroka, Agnieszka; Takahashi, Reisuke H; Gouras, Gunnar K (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is increasingly viewed as a disease of synapses. Loss of synapses correlates better with cognitive decline than amyloid plaques and neurofibrillary tangles, the hallmark neuropathological lesions of AD. Soluble forms of amyloid-β (Aβ) have emerged as mediators of synapse dysfunction. Aβ binds to, accumulates, and aggregates in synapses. However, the anatomical and neurotransmitter specificity of Aβ and the amyloid-β protein precursor (AβPP) in AD remain poorly understood. In addition, the relative roles of Aβ and AβPP in the development of AD, at pre- versus post-synaptic compartments and axons versus dendrites, respectively, remain unclear. Here we use immunogold electron microscopy and confocal microscopy to provide evidence for heterogeneity in the localization of Aβ/AβPP. We demonstrate that Aβ binds to a subset of synapses in cultured neurons, with preferential binding to glutamatergic compared to GABAergic neurons. We also highlight the challenge of defining pre- versus post-synaptic localization of this binding by confocal microscopy. Further, endogenous Aβ42 accumulates in both glutamatergic and GABAergic AβPP/PS1 transgenic primary neurons, but at varying levels. Moreover, upon knock-out of presenilin 1 or inhibition of γ-secretase AβPP C-terminal fragments accumulate both pre- and post-synaptically; however earlier pre-synaptically, consistent with a higher rate of AβPP processing in axons. A better understanding of the synaptic and anatomical selectivity of Aβ/AβPP in AD can be important for the development of more effective new therapies for this major disease of aging.

Humans with Type-2 Diabetes Show Abnormal Long-Term Potentiation-Like Cortical Plasticity Associated with Verbal Learning Deficits. - Fried, Peter J; Schilberg, Lukas; Brem, Anna-Katharine; Saxena, Sadhvi; Wong, Bonnie; Cypess, Aaron M; Horton, Edward S; Pascual-Leone, Alvaro (J Alzheimers Dis, 2017)
BACKGROUND: Type-2 diabetes mellitus (T2DM) accelerates cognitive aging and increases risk of Alzheimer's disease. Rodent models of T2DM show altered synaptic plasticity associated with reduced learning and memory. Humans with T2DM also show cognitive deficits, including reduced learning and memory, but the relationship of these impairments to the efficacy of neuroplastic mechanisms has never been assessed. OBJECTIVE: Our primary objective was to compare mechanisms of cortical plasticity in humans with and without T2DM. Our secondary objective was to relate plasticity measures to standard measures of cognition. METHODS: A prospective cross-sectional cohort study was conducted on 21 adults with T2DM and 15 demographically-similar non-diabetic controls. Long-term potentiation-like plasticity was assessed in primary motor cortex by comparing the amplitude of motor evoked potentials (MEPs) from single-pulse transcranial magnetic stimulation before and after intermittent theta-burst stimulation (iTBS). Plasticity measures were compared between groups and related to neuropsychological scores. RESULTS: In T2DM, iTBS-induced modulation of MEPs was significantly less than controls, even after controlling for potential confounds. Furthermore, in T2DM, modulation of MEPs 10-min post-iTBS was significantly correlated with Rey Auditory Verbal Learning Task (RAVLT) performance. CONCLUSION: Humans with T2DM show abnormal cortico-motor plasticity that is correlated with reduced verbal learning. Since iTBS after-effects and the RAVLT are both NMDA receptor-dependent measures, their relationship in T2DM may reflect brain-wide alterations in the efficacy of NMDA receptors. These findings offer novel mechanistic insights into the brain consequences of T2DM and provide a reliable means to monitor brain health and evaluate the efficacy of clinical interventions.

Identification of Successful Cognitive Aging in the Alzheimer's Disease Neuroimaging Initiative Study. - Lin, Feng V; Wang, Xixi; Wu, Rachel; Rebok, George W; Chapman, Benjamin P (J Alzheimers Dis, 2017)
The present prospective observational study aimed to identify the existence of successful cognitive agers among a group of well-defined cognitively healthy older adults (n = 354, mean age = 75 years), and to examine baseline individual-level predictors and associated health outcomes over time. Episodic memory (EM) and executive function (EF) composite scores and multiple health outcomes were obtained annually over 5 years. Potential individual-level predictors that were related to Alzheimer's disease pathology or genetic risk, neurodegeneration, and vascular risks were collected at baseline. Three latent classes with matched age and education were identified using growth mixture modeling: a group of participants who exhibited high, stable EM and EF (40.7% of the sample, "successful agers"); a group who had initial high cognitive performance that declined over time (21.2%, "declining agers"); and a group who had normal (EM) or poor (EF) but stable cognitive performance over time (38.1%, "low stable agers"). The group classification predicted significant differences in the incidence of global cognitive impairment, the development of at least one depressive symptom, and everyday functional impairment. Sex, apolipoprotein E allele 4, amyloid-β1-42, and t-tau significantly contributed to the difference in cognitive trajectories between the successful agers and the other two groups. Characterizing successful cognitive agers who are relatively resistant to both tau and amyloid pathology provides potential pathways for promoting successful cognitive aging and preventing cognitive decline.

Improved Cerebrospinal Fluid-Based Discrimination between Alzheimer's Disease Patients and Controls after Correction for Ventricular Volumes. - van Waalwijk van Doorn, Linda J C; Gispert, Juan D; Kuiperij, H Bea; Claassen, Jurgen A H R; Arighi, Andrea; Baldeiras, Ines; Blennow, Kaj; Bozzali, Marco; Castelo-Branco, Miguel; Cavedo, Enrica; Emek-Savaş, Derya D; Eren, Erden; et al. (J Alzheimers Dis, 2017)
Cerebrospinal fluid (CSF) biomarkers may support the diagnosis of Alzheimer's disease (AD). We studied if the diagnostic power of AD CSF biomarker concentrations, i.e., Aβ42, total tau (t-tau), and phosphorylated tau (p-tau), is affected by differences in lateral ventricular volume (VV), using CSF biomarker data and magnetic resonance imaging (MRI) scans of 730 subjects, from 13 European Memory Clinics. We developed a Matlab-algorithm for standardized automated segmentation analysis of T1 weighted MRI scans in SPM8 for determining VV, and computed its ratio with total intracranial volume (TIV) as proxy for total CSF volume. The diagnostic power of CSF biomarkers (and their combination), either corrected for VV/TIV ratio or not, was determined by ROC analysis. CSF Aβ42 levels inversely correlated to VV/TIV in the whole study population (Aβ42: r = -0.28; p < 0.0001). For CSF t-tau and p-tau, this association only reached statistical significance in the combined MCI and AD group (t-tau: r = -0.15; p-tau: r = -0.13; both p < 0.01). Correction for differences in VV/TIV improved the differentiation of AD versus controls based on CSF Aβ42 alone (AUC: 0.75 versus 0.81) or in combination with t-tau (AUC: 0.81 versus 0.91). In conclusion, differences in VV may be an important confounder in interpreting CSF Aβ42 levels.

Increased Carbohydrate Intake is Associated with Poorer Performance in Verbal Memory and Attention in an APOE Genotype-Dependent Manner. - Gardener, Samantha L; Rainey-Smith, Stephanie R; Sohrabi, Hamid R; Weinborn, Michael; Verdile, Giuseppe; Fernando, W M A D Binosha; Lim, Yen Ying; Harrington, Karra; Burnham, Samantha; Taddei, Kevin; Masters, Colin L; Macaulay, Stuart L; et al. (J Alzheimers Dis, 2017)
Evidence suggests that a diet low in carbohydrates can impact on cognitive performance among those with Alzheimer's disease (AD). However, there is a lack of data assessing this relationship among cognitively normal (CN) older adults at increased future risk of developing AD due to carriage of the apolipoprotein E (APOE) ɛ4 allele. We assessed the cross-sectional association between carbohydrate intake, cognitive performance, and cerebral amyloid-β (Aβ) load in CN older adults, genotyped for APOEɛ4 allele carrier status. Greater carbohydrate intake was associated with poorer performance in verbal memory in APOEɛ4 allele non-carriers, and poorer performance in attention in APOEɛ4 allele carriers. There were no associations between carbohydrate intake and cerebral Aβ load. These results provide support to the idea that decreasing carbohydrate intake may offer neurocognitive benefits, with specific cognitive domains affected in an APOE genotype-dependent manner. These findings warrant further investigation utilizing a longitudinal study design.

Increased Plasma Homocysteine Level is Associated with Executive Dysfunction in Type 2 Diabetic Patients with Mild Cognitive Impairment. - Tian, Sai; Han, Jing; Huang, Rong; Sun, Jie; Cai, Rongrong; Shen, Yanjue; Wang, Shaohua (J Alzheimers Dis, 2017)
BACKGROUND: Homocysteine (Hcy) is involved in the pathogenesis of type 2 diabetes mellitus (T2DM) and Alzheimer's disease. OBJECTIVE: We aimed to investigate the role of Hcy in T2DM patients with mild cognitive impairment (MCI), and to determine whether methylene tetrahydrofolate reductase (MTHFR) C677T or cystathionine beta-synthase (CBS) 844ins68 polymorphism is related to T2DM-associated MCI. METHODS: We recruited 285 T2DM patients and divided them into two groups, 140 patients with MCI, and 145 healthy-cognition controls, on the basis of Montreal Cognitive Assessment (MoCA) scores. Demographic characteristics, clinical parameters, and neuropsychological tests were assessed. MTHFR C677T and CBS 844ins68 polymorphisms were analyzed. RESULTS: The MCI group exhibited significantly higher plasma total Hcy (tHcy) levels than control group (p < 0.001). Plasma tHcy level was negatively correlated with MoCA scores (p = 0.002), but positively associated with Trail Making Test A and B scores (p = 0.044; p = 0.005, respectively). Multivariable logistic regression model showed that high tHcy level was an independent factor for MCI in T2DM patients. No significant difference was observed in the genotype or allele distributions of MTHFR and CBS between MCI and control groups. We did not find significant MCI risks in MTHFR T allele compared with C allele, and in CBS I allele compared with D allele (OR = 1.361, p = 0.067; OR = 1.048, p = 0.909, respectively). CONCLUSION: Increased plasma tHcy level was significantly related to T2DM-associated MCI, especially executive dysfunction. Further investigation with a large population size should be conducted to confirm these findings.

Increased Serum miR-206 Level Predicts Conversion from Amnestic Mild Cognitive Impairment to Alzheimer's Disease: A 5-Year Follow-up Study. - Xie, Bing; Liu, Zanchao; Jiang, Lei; Liu, Wei; Song, Mei; Zhang, Qingfu; Zhang, Rui; Cui, Dongsheng; Wang, Xueyi; Xu, Shunjiang (J Alzheimers Dis, 2017)
Evidence suggests that individuals with amnestic mild cognitive impairment (aMCI) tend to progress to probable Alzheimer's disease (AD) with aging. This study was performed to examine whether circulating miRNAs could be potential predictors for the progression of aMCI to AD. A total of 458 patients with aMCI were included in this study, and the clinical data were collected at two time points: the baseline and the follow-up assessment. These aMCI patients were classified into two groups after 5 years: aMCI-stable group (n = 330) and AD-conversion group (n = 128). The expression of miR-206 and miR-132 and the levels of BDNF and SIRT1 in serum were detected using a quantitative real-time RT-PCR (qPCR) and the ELISA method, respectively. Kaplan-Meier method (Log-rank test) was used for univariate survival analysis. Cox proportional hazard model was used to estimate the prognostic value of miRNAs in conversion from aMCI to AD. At the baseline, serum levels of miR-206 in aMCI-AD group were significantly elevated compared to aMCI-aMCI group and the same trend was found at 5-year follow-up time point as well. There were no significant differences in serum levels of miR-132 between the conversion and non-conversion group at both time points. Kaplan-Meier analysis showed significant correlation between AD conversion and higher serum levels of miR-206 for aMCI patients (HR = 3.60, 95% CI: 2.51- 5.36, p < 0.001). Multivariate Cox regression analysis revealed that serum miR-206 and its target BDNF were significant independent predictors for AD conversion (HR = 4.22, p < 0.001). These results suggested that increased serum miR-206 level might be a potential predictor of conversion from aMCI to AD.

Inflammation, Amyloid, and Atrophy in The Aging Brain: Relationships with Longitudinal Changes in Cognition. - Sala-Llonch, Roser; Idland, Ane-Victoria; Borza, Tom; Watne, Leiv Otto; Wyller, Torgeir Bruun; Brækhus, Anne; Zetterberg, Henrik; Blennow, Kaj; Walhovd, Kristine Beate; Fjell, Anders Martin (J Alzheimers Dis, 2017)
Amyloid deposition occurs in aging, even in individuals free from cognitive symptoms, and is often interpreted as preclinical Alzheimer's disease (AD) pathophysiology. YKL-40 is a marker of neuroinflammation, being increased in AD, and hypothesized to interact with amyloid-β (Aβ) in causing cognitive decline early in the cascade of AD pathophysiology. Whether and how Aβ and YKL-40 affect brain and cognitive changes in cognitively healthy older adults is still unknown. We studied 89 participants (mean age: 73.1 years) with cerebrospinal fluid samples at baseline, and both MRI and cognitive assessments from two time-points separated by two years. We tested how baseline levels of Aβ42 and YKL-40 correlated with changes in cortical thickness and cognition. Thickness change correlated with Aβ42 only in Aβ42+ participants (<600 pg/mL, n = 27) in the left motor and premotor cortices. Aβ42 was unrelated to cognitive change. Increased YKL-40 was associated with less preservation of scores on the animal naming test in the total sample (r = -0.28, p = 0.012) and less preservation of a score reflecting global cognitive function for Aβ42+ participants (r = -0.58, p = 0.004). Our results suggest a role for inflammation in brain atrophy and cognitive changes in cognitively normal older adults, which partly depended on Aβ accumulation.

Inflection Point in Course of Mild Cognitive Impairment: Increased Functional Connectivity of Default Mode Network. - Tao, Wuhai; Li, Xin; Zhang, Junying; Chen, Yaojing; Ma, Chao; Liu, Zhen; Yang, Caishui; Wang, Wenxiao; Chen, Kewei; Wang, Jun; Zhang, Zhanjun (J Alzheimers Dis, 2017)
The alteration of the default mode network (DMN) functional connectivity (FC) has been reported in patients with amnestic mild cognitive impairment (aMCI) as a predictor of Alzheimer's disease (AD). However, no studies exist that examined stage-dependent DMN FC changes throughout the course of aMCI. The present study aims to characterize patterns of DMN FC over three aMCI stages as first defined. Utilizing the extreme groups approach on the performance of memory tasks, aMCI subjects were divided into mild, moderate, and severe stages. Independent component analysis was used to assess DMN for individual patients in each of the three cross-sectionally defined stages. Instead of finding that continued monotonic decline was the case for the hippocampus volume, which we also investigated in this study, we observed an increase in DMN functional connectivity from mild aMCI to moderate aMCI and a decrease to severe aMCI, mainly in the left precuneus and superior parietal lobe. Moreover, the FC was significantly associated with cognitive performance. Though a longitudinal study is needed to confirm these results, our cross-sectional finding is that non-linear FC changes in DMN could be a characteristic of prodromal early disease development.

Insulin Resistance and Future Cognitive Performance and Cognitive Decline in Elderly Patients with Cardiovascular Disease. - Lutski, Miri; Weinstein, Galit; Goldbourt, Uri; Tanne, David (J Alzheimers Dis, 2017)
BACKGROUND: The role of insulin resistance (IR) in the pathogenesis of cognitive performance is not yet clear. OBJECTIVE: To examine the associations between IR and cognitive performance and change in cognitive functions two decades later in individuals with cardiovascular disease with and without diabetes. METHODS: A subset of 489 surviving patients (mean age at baseline 57.7±6.5 y) with coronary heart disease who previously participated in the secondary prevention Bezafibrate Infarction Prevention (BIP trial; 1990-1997), were included in the current neurocognitive study. Biochemical parameters including IR (using the homeostasis model of assessment; HOMA-IR) were measured at baseline. During 2004-2008, computerized cognitive assessment and atherosclerosis parameters were measured (T1; n = 558; mean age 72.6±6.4 years). A second cognitive assessment was performed during 2011-2013 (T2; n = 351; mean age 77.2±6.4 years). Cognitive function, overall and in specific domains, was assessed. We used linear regression models and linear mixed models to evaluate the differences in cognitive performance and decline, respectively. RESULTS: Controlling for potential confounders, IR (top HOMA-IR quartile versus others) was associated with subsequent poorer cognitive performance overall (β= -4.45±Standard Error (SE) 1.54; p = 0.004) and on tests of memory and executive function among non-diabetic patients (β= -7.16±2.38; p = 0.003 and β= -3.33±1.84; p = 0.073, respectively). Moreover, among non-diabetic patients, IR was related to a greater decline overall (β= -0.17±0.06; p = 0.008), and in memory (β= -0.22±0.10; p = 0.024) and executive function (β= -0.19±0.08; p = 0.012). The observed associations did not differ after excluding subjects with prevalent stroke or dementia. CONCLUSION: IR is related to subsequent poorer cognitive performance and greater cognitive decline among patients with cardiovascular disease with and without diabetes.

Intelligent Assistive Technology for Alzheimer's Disease and Other Dementias: A Systematic Review. - Ienca, Marcello; Fabrice, Jotterand; Elger, Bernice; Caon, Maurizio; Pappagallo, Alessandro Scoccia; Kressig, Reto W; Wangmo, Tenzin (J Alzheimers Dis, 2017)
Intelligent assistive technologies (IATs) have the potential of offering innovative solutions to mitigate the global burden of dementia and provide new tools for dementia care. While technological opportunities multiply rapidly, clinical applications are rare as the technological potential of IATs remains inadequately translated into dementia care. In this article, the authors present the results of a systematic review and the resulting comprehensive technology index of IATs with application in dementia care. Computer science, engineering, and medical databases were extensively searched and the retrieved items were systematically reviewed. For each IAT, the authors examined their technological type, application, target population, model of development, and evidence of clinical validation. The findings reveal that the IAT spectrum is expanding rapidly in volume and variety over time, and encompasses intelligent systems supporting various assistive tasks and clinical uses. At the same time, the results confirm the persistence of structural limitations to successful adoption including partial lack of clinical validation and insufficient focus on patients' needs. This index is designed to orient clinicians and relevant stakeholders involved in the implementation and management of dementia care across the current capabilities, applications, and limitations of IATs and to facilitate the translation of medical engineering research into clinical practice. In addition, a discussion of the major methodological challenges and policy implications for the successful and ethically responsible implementation of IAT into dementia care is provided.

Intracerebroventricular Streptozotocin Induces Obesity and Dementia in Lewis Rats. - Bloch, Konstantin; Gil-Ad, Irit; Vanichkin, Alexey; Hornfeld, Shay Henry; Koroukhov, Nickolay; Taler, Michal; Vardi, Pnina; Weizman, Abraham (J Alzheimers Dis, 2017)
BACKGROUND: Animal models of dementia associated with metabolic abnormalities play an important role in understanding the bidirectional relationships between these pathologies. Rodent strains develop cognitive dysfunctions without alteration of peripheral metabolism following intracerebroventricular administration of streptozotocin (icv-STZ). OBJECTIVE: We aimed to estimate the effect of icv-STZ on cognitive functions and peripheral metabolism in Lewis rats, which are rarely used for the induction of cognitive abnormalities. METHODS: Inbred adult Lewis rats were treated with single icv-STZ (3 mg/kg). Cognitive functions were assessed using Morris water maze (MWM) test and locomotion by the Open Field test. Metabolic alterations were studied using histological and biochemical analysis of brain and peripheral tissues. RESULTS: The icv-STZ induced rapid weight decline during the first two weeks. Thereafter, the rats showed an accelerated weight gain. Three months after the icv-STZ treatment, the rats were severely obese and revealed fatty liver, pancreatic islet hypertrophy, significantly elevated levels of blood insulin, leptin, and adiponectin, but intact peripheral glucose homeostasis. The icv-STZ rats expressed amyloid-β deposits in blood vessels of leptomeningeal area, microgliosis, astrogliosis, and spongiosis in fimbria-fornix area of hippocampus. Locomotor activities of icv-STZ treated and sham-operated rats were similar. In the MWM test, the icv-STZ treated rats demonstrated severely impaired spatial learning during both acquisition and reversal phases. CONCLUSIONS: Icv-STZ treated Lewis rats develop severe dementia associated with obesity and peripheral metabolic abnormalities. This animal model may be useful for exploring the pathophysiological relationship between obesity and dementia and provides a new tool for development of effective therapy.

Intracranial Arterial 4D Flow in Individuals with Mild Cognitive Impairment is Associated with Cognitive Performance and Amyloid Positivity. - Berman, Sara E; Clark, Lindsay R; Rivera-Rivera, Leonardo A; Norton, Derek; Racine, Annie M; Rowley, Howard A; Bendlin, Barbara B; Blennow, Kaj; Zetterberg, Henrik; Carlsson, Cynthia M; Asthana, Sanjay; Turski, Patrick; et al. (J Alzheimers Dis, 2017)
It is becoming increasingly recognized that cerebrovascular disease is a contributing factor in the pathogenesis of Alzheimer's disease (AD). A unique 4D-Flow magnetic resonance imaging (MRI) technique, phase contrast vastly undersampled isotropic projection imaging (PC VIPR), enables examination of angiographic and quantitative metrics of blood flow in the arteries of the Circle of Willis within a single MRI acquisition. Thirty-eight participants with mild cognitive impairment (MCI) underwent a comprehensive neuroimaging protocol (including 4D-Flow imaging) and a standard neuropsychological battery. A subset of participants (n = 22) also underwent lumbar puncture and had cerebrospinal fluid (CSF) assayed for AD biomarkers. Cut-offs for biomarker positivity in CSF resulting from a receiver operating characteristic curve analysis of AD cases and controls from the larger Wisconsin Alzheimer's Disease Research Center cohort were used to classify MCI participants as biomarker positive or negative on amyloid-β (Aβ42), total-tau and total-tau/Aβ42 ratio. Internal carotid artery (ICA) and middle cerebral artery (MCA) mean flow were associated with executive functioning performance, with lower mean flow corresponding to worse performance. MCI participants who were biomarker positive for Aβ42 had lower ICA mean flow than did those who were Aβ42 negative. In sum, mean ICA and MCA arterial flow was associated with cognitive performance in participants with MCI and lower flow in the ICA was associated with amyloid positivity. This provides further evidence for vascular health as a contributing factor in the etiopathogenesis of AD, and could represent a point to intervene in the disease process.

Investigations into Retinal Pathology in the Early Stages of a Mouse Model of Alzheimer's Disease. - Chidlow, Glyn; Wood, John P M; Manavis, Jim; Finnie, John; Casson, Robert J (J Alzheimers Dis, 2017)
There is increasing recognition that visual performance is impaired in early stages of Alzheimer's disease (AD); however, no consensus exists as to the mechanisms underlying this visual dysfunction, in particular regarding the timing, nature, and extent of retinal versus cortical pathology. If retinal pathology presents sufficiently early, it offers great potential as a source of novel biomarkers for disease diagnosis. The current project utilized an array of immunochemical and molecular tools to perform a characterization of retinal pathology in the early stages of disease progression using a well-validated mouse model of AD (APPSWE/PS1ΔE9). Analytical endpoints included examination of aberrant amyloid and tau in the retina, quantification of any neuronal degeneration, delineation of cellular stress responses of neurons and particularly glial cells, and investigation of oxidative stress. Brain, eyes, and optic nerves were taken from transgenic and wild-type mice of 3 to 12 months of age and processed for immunohistochemistry, qPCR, or western immunoblotting. The results revealed robust expression of the human APP transgene in the retinas of transgenic mice, but a lack of identifiable retinal pathology during the period when amyloid deposits were dramatically escalating in the brain. We were unable to demonstrate the presence of amyloid plaques, dystrophic neurites, neuronal loss, macro- or micro-gliosis, aberrant cell cycle re-entry, oxidative stress, tau hyperphosphorylation, or upregulations of proinflammatory cytokines or stress signaling molecules in the retina. The overall results do not support the hypothesis that detectable retinal pathology occurs concurrently with escalating amyloid deposition in the brains of APPSWE/PS1ΔE9 mice.

Iron Concentration in Deep Gray Matter Structures is Associated with Worse Visual Memory Performance in Healthy Young Adults. - Darnai, Gergely; Nagy, Szilvia Anett; Horváth, Réka; Ács, Péter; Perlaki, Gábor; Orsi, Gergely; Kovács, Norbert; Altbäcker, Anna; Plózer, Enikő; Tényi, Dalma; Weintraut, Rita; Schwarcz, Attila; et al. (J Alzheimers Dis, 2017)
Abnormally high deposition of iron can contribute to neurodegenerative disorders with cognitive impairment. Since previous studies investigating cognition-brain iron accumulation relationships focused on elderly people, our aim was to explore the association between iron concentration in subcortical nuclei and two types of memory performances in a healthy young population. Gender difference was found only in the globus pallidus. Our results showed that iron load characterized by R2* value on the MRI in the caudate and putamen was related to visual memory, while verbal memory was unrelated to iron concentration.

The Link between Type 2 Diabetes and Neurodegeneration: Roles for Amyloid-β, Amylin, and Tau Proteins. - Bharadwaj, Prashant; Wijesekara, Nadeeja; Liyanapathirana, Milindu; Newsholme, Philip; Ittner, Lars; Fraser, Paul; Verdile, Giuseppe (J Alzheimers Dis, 2017)
A wealth of evidence indicates a strong link between type 2 diabetes (T2D) and neurodegenerative diseases such as Alzheimer's disease (AD). Although the precise mechanism remains unclear, T2D can exacerbate neurodegenerative processes. Brain atrophy, reduced cerebral glucose metabolism, and central nervous system insulin resistance are features of both AD and T2D. The T2D phenotype (glucose dyshomeostasis, insulin resistance, impaired insulin signaling) also promotes AD pathology, namely accumulation of amyloid-β (Aβ) and hyperphosphorylated tau and can induce other aspects of neuronal degeneration including inflammatory and oxidative processes. Aβ and hyperphosphorylated tau may also have roles in pancreatic β-cell dysfunction and in reducing insulin sensitivity and glucose uptake by peripheral tissues such as liver, skeletal muscle, and adipose tissue. This suggests a role for these AD-related proteins in promoting T2D. The accumulation of the islet amyloid polypeptide (IAPP, or amylin) within islet β-cells is a major pathological feature of the pancreas in patients with chronic T2D. Co-secreted with insulin, amylin accumulates over time and contributes to β-cell toxicity, ultimately leading to reduced insulin secretion and onset of overt (insulin dependent) diabetes. Recent evidence also suggests that this protein accumulates in the brain of AD patients and may interact with Aβ to exacerbate the neurodegenerative process. In this review, we highlight evidence indicating T2D in promoting Aβ and tau mediated neurodegeneration and the potential contributions of Aβ and tau in promoting a diabetic phenotype that could further exacerbate neurodegeneration. We also discuss underlying mechanisms by which amylin can contribute to the neurodegenerative processes.

Living Alone with Alzheimer's Disease: Data from SveDem, the Swedish Dementia Registry. - Cermakova, Pavla; Nelson, Maja; Secnik, Juraj; Garcia-Ptacek, Sara; Johnell, Kristina; Fastbom, Johan; Kilander, Lena; Winblad, Bengt; Eriksdotter, Maria; Religa, Dorota (J Alzheimers Dis, 2017)
BACKGROUND: Many people with Alzheimer's disease (AD) live alone in their own homes. There is a lack of knowledge about whether these individuals receive the same quality of diagnostics and treatment for AD as patients who are cohabiting. OBJECTIVES: To investigate the diagnostic work-up and treatment of community-dwelling AD patients who live alone. METHODS: We performed a cross-sectional cohort study based on data from the Swedish Dementia Registry (SveDem). We studied patients diagnosed with AD between 2007 and 2015 (n = 26,163). Information about drugs and comorbidities was acquired from the Swedish Prescribed Drug Register and the Swedish Patient Register. RESULTS: 11,878 (46%) patients lived alone, primarily older women. After adjusting for confounders, living alone was inversely associated with receiving computed tomography (OR 0.90; 95% CI 0.82-0.99), magnetic resonance imaging (OR 0.91; 95% CI 0.83-0.99), and lumbar puncture (OR 0.86; 95% CI 0.80-0.92). Living alone was also negatively associated with the use of cholinesterase inhibitors (OR 0.81; 95% CI 0.76; 0.87), memantine (OR 0.77; 95% CI 0.72; 0.83), and cardiovascular medication (OR 0.92; 0.86; 0.99). On the other hand, living alone was positively associated with the use of antidepressants (OR 1.15; 95% CI 1.08; 1.22), antipsychotics (OR 1.41; 95% CI 1.25; 1.58), and hypnotics and sedatives (OR 1.09; 95% CI 1.02; 1.17). CONCLUSIONS: Solitary living AD patients do not receive the same extent of care as those who are cohabiting.

Localization and Processing of the Amyloid-β Protein Precursor in Mitochondria-Associated Membranes. - Del Prete, Dolores; Suski, Jan M; Oulès, Bénédicte; Debayle, Delphine; Gay, Anne Sophie; Lacas-Gervais, Sandra; Bussiere, Renaud; Bauer, Charlotte; Pinton, Paolo; Paterlini-Bréchot, Patrizia; Wieckowski, Mariusz R; Checler, Frédéric; et al. (J Alzheimers Dis, 2017)
Alteration of mitochondria-associated membranes (MAMs) has been proposed to contribute to the pathogenesis of Alzheimer's disease (AD). We studied herein the subcellular distribution, the processing, and the protein interactome of the amyloid-β protein precursor (AβPP) and its proteolytic products in MAMs. We reveal that AβPP and its catabolites are present in MAMs in cellular models overexpressing wild type AβPP or AβPP harboring the double Swedish or London familial AD mutations, and in brains of transgenic mice model of AD. Furthermore, we evidenced that both β- and γ-secretases are present and harbor AβPP processing activities in MAMs. Interestingly, cells overexpressing APPswe show increased ER-mitochondria contact sites. We also document increased neutral lipid accumulation linked to Aβ production and reversed by inhibiting β- or γ-secretases. Using a proteomic approach, we show that AβPP and its catabolites interact with key proteins of MAMs controlling mitochondria and ER functions. These data highlight the role of AβPP processing and proteomic interactome in MAMs deregulation taking place in AD.

Longitudinal Characterization of [18F]-FDG and [18F]-AV45 Uptake in the Double Transgenic TASTPM Mouse Model. - Waldron, Ann-Marie; Wyffels, Leonie; Verhaeghe, Jeroen; Richardson, Jill C; Schmidt, Mark; Stroobants, Sigrid; Langlois, Xavier; Staelens, Steven (J Alzheimers Dis, 2017)
We aimed to monitor the timing of amyloid-β deposition in relation to changes in brain function using in vivo imaging with [18F]-AV45 and [18F]-FDG in a mouse model of Alzheimer's disease. TASTPM transgenic mice and wild-type controls were scanned longitudinally with [18F]-AV45 and [18F]-FDG before (3 months of age) and at multiple time points after the onset of amyloid deposition (6, 9, 12, and 15 months of age). As expected with increasing amyloidosis, TASTPM mice demonstrated progressive age-dependent increases in [18F]-AV45 uptake that were significantly higher than for WT from 9 months onwards and correlated to ex vivo measures of amyloid burden. The metabolism of [18F]-AV45 produces several brain penetrant radiometabolites and normalization to a reference region helps to negate this non-specific binding and improve the sensitivity of [18F]-AV45. The observed trajectory of [18F]-FDG alterations deviated from our proposed hypothesis of gradual decreases with worsening amyloidosis. While [18F]-FDG uptake in TASTPM mice was significantly lower than that of WT at 9 months, reduced [18F]-FDG was not associated with aging in TASTPM mice. Moreover, [18F]-FDG uptake did not correlate to measures of ex vivo amyloid burden. Our findings suggest that while amyloid-β is sufficient to induce hypometabolism, these pathologies are not linked in a dose-dependent manner in TASTPM mice.

Long-Term Cognitive Decline in Dementia with Lewy Bodies in a Large Multicenter, International Cohort. - Kramberger, Milica G; Auestad, Bjørn; Garcia-Ptacek, Sara; Abdelnour, Carla; Olmo, Josep Garre; Walker, Zuzana; Lemstra, Afina W; Londos, Elisabet; Blanc, Frédéric; Bonanni, Laura; McKeith, Ian; Winblad, Bengt; et al. (J Alzheimers Dis, 2017)
BACKGROUND/OBJECTIVE: The aim of this study was to describe the rate and clinical predictors of cognitive decline in dementia with Lewy bodies (DLB), and compare the findings with Alzheimer's disease (AD) and Parkinson's disease dementia (PDD) patients. METHODS: Longitudinal scores for the Mini-Mental State Examination (MMSE) in 1,290 patients (835 DLB, 198 PDD, and 257 AD) were available from 18 centers with up to three years longitudinal data. Linear mixed effects analyses with appropriate covariates were used to model MMSE decline over time. Several subgroup analyses were performed, defined by anti-dementia medication use, baseline MMSE score, and DLB core features. RESULTS: The mean annual decline in MMSE score was 2.1 points in DLB, compared to 1.6 in AD (p = 0.07 compared to DLB) and 1.8 in PDD (p = 0.19). Rates of decline were significantly higher in DLB compared to AD and PDD when baseline MMSE score was included as a covariate, and when only those DLB patients with an abnormal dopamine transporter SPECT scan were included. Decline was not predicted by sex, baseline MMSE score, or presence of specific DLB core features. CONCLUSIONS: The average annual decline in MMSE score in DLB is approximately two points. Although in the overall analyses there were no differences in the rate of decline between the three neurodegenerative disorders, there were indications of a more rapid decline in DLB than in AD and PDD. Further studies are needed to understand the predictors and mechanisms of cognitive decline in DLB.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Cognition Disorders; Cohort Studies; Female; Humans; International Cooperation; Lewy Body Disease; Male; Mental Status Schedule; Middle Aged

Low Prevalence and Clinical Effect of Vascular Risk Factors in Early-Onset Alzheimer's Disease. - Chen, Yaohua; Sillaire, Adeline Rollin; Dallongeville, Jean; Skrobala, Emilie; Wallon, David; Dubois, Bruno; Hannequin, Didier; Pasquier, Florence (J Alzheimers Dis, 2017)
BACKGROUND: Determinants of early-onset Alzheimer's disease (EOAD) are not well known. In late-onset AD, vascular risk factors (VRFs) are associated with earlier clinical manifestation. OBJECTIVE: The objective of this study was to assess the putative association between VRFs and EOAD. METHODS: We studied participants with dementia meeting criteria for EOAD (recruited into the French CoMAJ prospective cohort study from 1 June 2009 to 28 February 2014) and age-, gender-matched controls (ratio 1:3, drawn randomly from the French MONA-LISA population-based survey between 2005 and 2007). Demographic data, VRFs, comorbidities, treatments, and APOE genotypes were compared in multivariable logistic regression analyses. RESULTS: We studied 102 participants with dementia (mean±standard deviation age: 59.5±3.8; women: 59.8%) and 306 controls. Compared with controls, EOAD participants had spent less time in formal education (9.9±2.9 versus 11.7±3.8 y; p < 0.0001), were less likely to be regular alcohol consumers (p < 0.0001), had a lower body mass index (-2 kg/m2; p < 0.0004), and a lower mean systolic blood pressure (-6.2 mmHg; p = 0.0036). The prevalence of APOE ɛ4 allele was higher in participants with dementia than in controls (50% versus 29.4%; p = 0.0002), as was the prevalence of depression (48% versus 32%; p < 0.001). Similar results were observed in multivariable analysis. Compared with EOAD participants lacking VRFs, EOAD participants with at least one VRF had a higher prevalence of depression (29.6% versus 53.3%, respectively; p = 0.03). CONCLUSION: The prevalence of VRFs is not elevated in EOAD patients (in contrast to older AD patients). Extensive genetic testing should be considered more frequently in the context of EOAD.

Memory Correlates of Alzheimer's Disease Cerebrospinal Fluid Markers: A Longitudinal Cohort Study. - Reijs, Babette L R; Ramakers, Inez H G B; Köhler, Sebastian; Teunissen, Charlotte E; Koel-Simmelink, Marleen; Nathan, Pradeep J; Tsolaki, Magda; Wahlund, Lars-Olof; Waldemar, Gunhild; Hausner, Lucrezia; Vandenberghe, Rik; Johannsen, Peter; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Performance on episodic, semantic, and working memory tests is impaired in Alzheimer's disease (AD)-type dementia, but it is unclear which type of memory test is most strongly associated with early AD biomarkers in cerebrospinal fluid (CSF), and most useful for monitoring disease progression. OBJECTIVE: To examine the association between amyloid-β 1-42 (Aβ42) and tau in CSF with performance on different memory domains at baseline, and how these CSF markers are related with memory decline. METHODS: We included 263 individuals with normal cognition, mild cognitive impairment, AD-type dementia, and non-AD dementia from the European EDAR study. Assessment included CSF Aβ42 and t-tau analyses with INNO-BIA AlzBio3 Luminex assay, the CERAD wordlist learning and delayed recall, animal fluency test, and the CANTAB Paired Associates Learning (PAL) and Spatial Working Memory tasks. Follow-up assessments were performed within 3 years after baseline. RESULTS: At baseline, decreased CSF Aβ42 correlated most strongly with the PAL total errors adjusted and the wordlist delayed recall and increased CSF t-tau with the wordlist delayed recall. Over time, decreased CSF Aβ42 was associated with decline on the wordlist learning, whereas increased CSF t-tau were associated with decline in scores on the wordlist learning, wordlist delayed recall, and animal fluency. Associations were independent of baseline diagnosis. CONCLUSION: Tests assessing episodic verbal and visuospatial memory are most useful for detection of AD pathology. Tests for episodic verbal memory and semantic memory are most useful for tracking memory decline.

Meta-Analysis of Parkinson's Disease and Alzheimer's Disease Revealed Commonly Impaired Pathways and Dysregulation of NRF2-Dependent Genes. - Wang, Qian; Li, Wen-Xing; Dai, Shao-Xing; Guo, Yi-Cheng; Han, Fei-Fei; Zheng, Jun-Juan; Li, Gong-Hua; Huang, Jing-Fei (J Alzheimers Dis, 2017)
Many lines of evidence suggest that Parkinson's disease (PD) and Alzheimer's disease (AD) have common characteristics, such as mitochondrial dysfunction and oxidative stress. As the underlying molecular mechanisms are unclear, we perform a meta-analysis with 9 microarray datasets of PD studies and 7 of AD studies to explore it. Functional enrichment analysis revealed that PD and AD both showed dysfunction in the synaptic vesicle cycle, GABAergic synapses, phagosomes, oxidative phosphorylation, and TCA cycle pathways, and AD had more enriched genes. Comparing the differentially expressed genes between AD and PD, we identified 54 common genes shared by more than six tissues. Among them, 31 downregulated genes contained the antioxidant response element (ARE) consensus sequence bound by NRF2. NRF2 is a transcription factor, which protects cells against oxidative stress through coordinated upregulation of ARE-driven genes. To our surprise, although NRF2 was upregulated, its target genes were all downregulated. Further exploration found that MAFF was upregulated in all tissues and significantly negatively correlated with the 31 NRF2-dependent genes in diseased conditions. Previous studies have demonstrated over-expressed small MAFs can form homodimers and act as transcriptional repressors. Therefore, MAFF might play an important role in dysfunction of NRF2 regulatory network in PD and AD.

Metabolic and Growth Rate Alterations in Lymphoblastic Cell Lines Discriminate Between Down Syndrome and Alzheimer's Disease. - Coskun, Pinar; Helguera, Pablo; Nemati, Zahra; Bohannan, Ryan C; Thomas, Jean; Samuel, Schriner E; Argueta, Jocelyn; Doran, Eric; Wallace, Douglas C; Lott, Ira T; Busciglio, Jorge (J Alzheimers Dis, 2017)
BACKGROUND: Deficits in mitochondrial function and oxidative stress play pivotal roles in Down syndrome (DS) and Alzheimer's disease (AD) and these alterations in mitochondria occur systemically in both conditions. OBJECTIVE: We hypothesized that peripheral cells of elder subjects with DS exhibit disease-specific and dementia-specific metabolic features. To test this, we performed a comprehensive analysis of energy metabolism in lymphoblastic-cell-lines (LCLs) derived from subjects belonging to four groups: DS-with-dementia (DSAD), DS-without-dementia (DS), sporadic AD, and age-matched controls. METHODS: LCLs were studied under regular or minimal feeding regimes with galactose or glucose as primary carbohydrate sources. We assessed metabolism under glycolysis or oxidative phosphorylation by quantifying cell viability, oxidative stress, ATP levels, mitochondrial membrane potential (MMP), mitochondrial calcium uptake, and autophagy. RESULTS: DS and DSAD LCLs showed slower growth rates under minimal feeding. DS LCLs mainly dependent on mitochondrial respiration exhibited significantly slower growth and higher levels of oxidative stress compared to other groups. While ATP levels (under mitochondrial inhibitors) and mitochondrial calcium uptake were significantly reduced in DSAD and AD cells, MMP was decreased in DS, DSAD, and AD LCLs. Finally, DS LCLs showed markedly reduced levels of the autophagy marker LC3-II, underscoring the close association between metabolic dysfunction and impaired autophagy in DS. CONCLUSION: There are significant mitochondrial functional changes in LCLs derived from DS, DSAD, and AD patients. Several parameters analyzed were consistently different between DS, DSAD, and AD lines suggesting that metabolic indicators between LCL groups may be utilized as biomarkers of disease progression and/or treatment outcomes.

A Metal-Free Method for Producing MRI Contrast at Amyloid-β. - Hilt, Silvia; Tang, Tang; Walton, Jeffrey H; Budamagunta, Madhu; Maezawa, Izumi; Kálai, Tamás; Hideg, Kálmán; Singh, Vikrant; Wulff, Heike; Gong, Qizhi; Jin, Lee-Way; Louie, Angelique; et al. (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is characterized by depositions of the amyloid-β (Aβ) peptide in the brain. The disease process develops over decades, with substantial neurological loss occurring before a clinical diagnosis of dementia can be rendered. It is therefore imperative to develop methods that permit early detection and monitoring of disease progression. In addition, the multifactorial pathogenesis of AD has identified several potential avenues for AD intervention. Thus, evaluation of therapeutic candidates over lengthy trial periods also demands a practical, noninvasive method for measuring Aβ in the brain. Magnetic resonance imaging (MRI) is the obvious choice for such measurements, but contrast enhancement for Aβ has only been achieved using Gd(III)-based agents. There is great interest in gadolinium-free methods to image the brain. In this study, we provide the first demonstration that a nitroxide-based small-molecule produces MRI contrast in brain specimens with elevated levels of Aβ. The molecule is comprised of a  fluorene (a molecule with high affinity for Aβ) and a nitroxide spin label (a paramagnetic MRI contrast species). Labeling of brain specimens with the spin-labeled fluorene produces negative contrast in samples from AD model mice whereas no negative contrast is seen in specimens harvested from wild-type mice. Injection of spin-labeled fluorene into live mice resulted in good brain penetration, with the compound able to generate contrast 24-h post injection. These results provide a proof of concept method that can be used for early, noninvasive, gadolinium-free detection of amyloid plaques by MRI.

Methylene Blue (Tetramethylthionine Chloride) Influences the Mobility of Adult Neural Stem Cells: A Potentially Novel Therapeutic Mechanism of a Therapeutic Approach in the Treatment of Alzheimer's Disease. - van der Ven, Amelie T; Pape, Julius C; Hermann, Dirk; Schloesser, Robert; Genius, Just; Fischer, Nadine; Mößner, Rainald; Scherbaum, Norbert; Wiltfang, Jens; Rujescu, Dan; Benninghoff, Jens (J Alzheimers Dis, 2017)
An interest in neurogenesis in the adult human brain as a relevant and targetable process has emerged as a potential treatment option for Alzheimer's disease and other neurodegenerative conditions. The aim of this study was to investigate the effects of tetramethylthionine chloride (methylene blue, MB) on properties of adult murine neural stem cells. Based on recent clinical studies, MB has increasingly been discussed as a potential treatment for Alzheimer's disease. While no differences in the proliferative capacity were identified, a general potential of MB in modulating the migratory capacity of adult neural stem cells was indicated in a cell mobility assay. To our knowledge, this is the first time that MB could be associated with neural mobility. The results of this study add insight to the spectrum of features of MB within the central nervous system and may be helpful for understanding the molecular mechanisms underlying a potential therapeutic effect of MB.

MicroRNAs in Human Cerebrospinal Fluid as Biomarkers for Alzheimer's Disease. - Lusardi, Theresa A; Phillips, Jay I; Wiedrick, Jack T; Harrington, Christina A; Lind, Babett; Lapidus, Jodi A; Quinn, Joseph F; Saugstad, Julie A (J Alzheimers Dis, 2017)
BACKGROUND: Currently available biomarkers of Alzheimer's disease (AD) include cerebrospinal fluid (CSF) protein analysis and amyloid PET imaging, each of which has limitations. The discovery of extracellular microRNAs (miRNAs) in CSF raises the possibility that miRNA may serve as novel biomarkers of AD. OBJECTIVE: Investigate miRNAs in CSF obtained from living donors as biomarkers for AD. METHODS: We profiled miRNAs in CSF from 50 AD patients and 49 controls using TaqMan® arrays. Replicate studies performed on a subset of 32 of the original CSF samples verified 20 high confidence miRNAs. Stringent data analysis using a four-step statistical selection process including log-rank and receiver operating characteristic (ROC) tests, followed by random forest tests, identified 16 additional miRNAs that discriminate AD from controls. Multimarker modeling evaluated linear combinations of these miRNAs via best-subsets logistic regression, and computed area under the ROC (AUC) curve ascertained classification performance. The influence of ApoE genotype on miRNA biomarker performance was also evaluated. RESULTS: We discovered 36 miRNAs that discriminate AD from control CSF. 20 of these retested in replicate studies verified differential expression between AD and controls. Stringent statistical analysis also identified these 20 miRNAs, and 16 additional miRNA candidates. Top-performing linear combinations of 3 and 4 miRNAs have AUC of 0.80-0.82. Addition of ApoE genotype to the model improved performance, i.e., AUC of 3 miRNA plus ApoE4 improves to 0.84. CONCLUSIONS: CSF miRNAs can discriminate AD from controls. Combining miRNAs improves sensitivity and specificity of biomarker performance, and adding ApoE genotype improves classification.

A Mitochondrial Biomarker-Based Study of S-Equol in Alzheimer's Disease Subjects: Results of a Single-Arm, Pilot Trial. - Wilkins, Heather M; Mahnken, Jonathan D; Welch, Paul; Bothwell, Rebecca; Koppel, Scott; Jackson, Richard L; Burns, Jeffrey M; Swerdlow, Russell H (J Alzheimers Dis, 2017)
Reductions in bioenergetic fluxes, mitochondrial enzyme activities, and mitochondrial number are observed in Alzheimer's disease (AD). Preclinical work indicates estrogen pathway signaling by either estrogen or selective β estrogen receptor (ERβ) agonists benefits these parameters. To assess whether an ERβ agonist could improve mitochondrial function in actual AD subjects, we administered S-equol (10 mg twice daily) to 15 women with AD and determined the platelet mitochondria cytochrome oxidase (COX) activity before initiating S-equol (lead-in), after two weeks of S-equol (active treatment), and two weeks after stopping S-equol (wash-out). Because the intra-individual variation of this enzyme across samples taken at different times was unknown we used a nonparametric, single-arm, dichotomous endpoint that classified subjects whose active treatment COX activity exceeded the average of their lead-in and wash-out measures as positive responders. Eleven positive responses were observed (p < 0.06). The implications of this finding on our null hypothesis (that S-equol does not influence platelet mitochondria COX activity) are discussed. To our knowledge, this is the first time a direct mitochondrial target engagement biomarker has been utilized in an AD clinical study.

Mitochondrial Repair Effects of Oxygen Treatment on Alzheimer's Disease Model Mice Revealed by Quantitative Proteomics. - Wang, Hao; Hong, Xiaoyu; Wang, Yong (J Alzheimers Dis, 2017)
Mitochondrial dysfunction plays a pivotal role in Alzheimer's disease (AD), even before signs of AD pathology are evident. Our previous research has shown that oxygen treatment can improve cognitive function in AD model mice. To address whether oxygen treatment is beneficial to mitochondrial biology, we analyzed differential expressions of hippocampal mitochondrial proteins in AD model mice given supplementary oxygen. Numerous respiratory chain, Kreb's cycle, and glycolysis proteins were upregulated significantly after oxygen treatment, suggesting that oxygen therapy can alleviate mitochondrial damage. Furthermore, the treatment was associated with decreased expressions of some AD biomarkers, suggesting oxygen treatment to be a potential therapy for AD.

Modeling the Distress of Spousal Caregivers of People with Dementia. - Wawrziczny, Emilie; Berna, Guillaume; Ducharme, Francine; Kergoat, Marie-Jeanne; Pasquier, Florence; Antoine, Pascal (J Alzheimers Dis, 2017)
BACKGROUND: The progressive mobilization of spouse caregivers who take care of a person with dementia (PWD) can lead to situations of distress. OBJECTIVE: The current study sought to investigate the influence of the characteristics of the caregiving context on spousal caregiver distress. METHODS: 125 spousal caregivers participated in this study. The characteristics of the caregiving context were assessed using questionnaires. We examined a moderated-mediator model (Step 1) in which we hypothesized that PWD and caregiver characteristics and dyadic determinants contribute to spousal caregiver distress. This model was compared based on the age at onset of the disease and the gender of the caregiver (Step 2). RESULTS: The model revealed that poor self-rated health and a lack of family support accentuated spousal caregiver distress, whereas the feeling of being prepared and level of confidence decreased spousal caregiver distress. Moreover, the quality of couple adjustment affected spousal caregiver distress, and this effect was mediated by the severity of the PWD's symptoms. Regarding the age at onset of the disease, the path between Couple Adjustment and the Care recipient's impairments was more important for caregivers of person with early-onset dementia (PEOD). Female caregivers who reported poor self-rated health experienced greater distress. CONCLUSIONS: It would be interesting to create a support program that would incorporate these three areas of intervention regarding the progression of the disease: first, "preparedness modules"; second, "dyadic modules" (especially for caregivers of PEOD); and third, "family modules". Specific attention should be given to female caregivers who report poor self-rated health.

Modulation of AβPP and GSK3β by Endoplasmic Reticulum Stress and Involvement in Alzheimer's Disease. - Liu, Xin-Jun; Wei, Jun; Shang, Ying-Hui; Huang, Han-Chang; Lao, Feng-Xue (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a dementia disease with neuronal loss and synaptic impairment. This impairment is caused, at least partly, by the generation of two main AD hallmarks, namely the hyperphosphorylated tau protein comprising neurofibrillary tangles and senile plaques containing amyloid-β (Aβ) peptides. The amyloid-β protein precursor (AβPP) and glycogen synthase kinase-3β (GSK3β) are two main proteins associated with AD and are closely correlated with these hallmarks. Recently, both of the proteins were reported to be modulated by endoplasmic reticulum stress (ERS) and are involved in the pathogenesis of AD. The mechanism of ERS plus the modulation of AβPP processing and GSK3β activity by ERS in AD are summarized and explored in this review.

A Multi-Cohort Study of ApoE ɛ4 and Amyloid-β Effects on the Hippocampus in Alzheimer's Disease. - Khan, Wasim; Giampietro, Vincent; Banaschewski, Tobias; Barker, Gareth J; Bokde, Arun L W; Büchel, Christian; Conrod, Patricia; Flor, Herta; Frouin, Vincent; Garavan, Hugh; Gowland, Penny; Heinz, Anreas; et al. (J Alzheimers Dis, 2017)
The apolipoprotein E (APOE) gene has been consistently shown to modulate the risk of Alzheimer's disease (AD). Here, using an AD and normal aging dataset primarily consisting of three AD multi-center studies (n = 1,781), we compared the effect of APOE and amyloid-β (Aβ) on baseline hippocampal volumes in AD patients, mild cognitive impairment (MCI) subjects, and healthy controls. A large sample of healthy adolescents (n = 1,387) was also used to compared hippocampal volumes between APOE groups. Subjects had undergone a magnetic resonance imaging (MRI) scan and APOE genotyping. Hippocampal volumes were processed using FreeSurfer. In the AD and normal aging dataset, hippocampal comparisons were performed in each APOE group and in ɛ4 carriers with positron emission tomography Aβ who were dichotomized (Aβ+/Aβ-) using previous cut-offs. We found a linear reduction in hippocampal volumes with ɛ4 carriers possessing the smallest volumes, ɛ3 carriers possessing intermediate volumes, and ɛ2 carriers possessing the largest volumes. Moreover, AD and MCI ɛ4 carriers possessed the smallest hippocampal volumes and control ɛ2 carriers possessed the largest hippocampal volumes. Subjects with both APOE ɛ4 and Aβ+ had the lowest hippocampal volumes when compared to Aβ- ɛ4 carriers, suggesting a synergistic relationship between APOE ɛ4 and Aβ. However, we found no hippocampal volume differences between APOE groups in healthy 14-year-old adolescents. Our findings suggest that the strongest neuroanatomic effect of APOE ɛ4 on the hippocampus is observed in AD and groups most at risk of developing the disease, whereas hippocampi of old and young healthy individuals remain unaffected.

Multifunctional Compound AD-35 Improves Cognitive Impairment and Attenuates the Production of TNF-α and IL-1β in an Aβ25-35-induced Rat Model of Alzheimer's Disease. - Li, Lin; Xu, Shaofeng; Liu, Lifei; Feng, Rentian; Gong, Yongxiang; Zhao, Xuyang; Li, Jiang; Cai, Jie; Feng, Nan; Wang, Ling; Wang, Xiaoliang; Peng, Ying (J Alzheimers Dis, 2017)
The dyshomeostasis of transition metal ions, accumulation of amyloid-β (Aβ) senile plaques and neuroinflammatory response found in the brain of patients with Alzheimer's disease (AD) have been suggested to be involved in AD pathogenesis. Novel compounds capable of targeting metal-Aβ species and neuroinflammation would be valuable. AD-35 is such a patented small-molecule compound derived from innovative modification of the chemical structure of donepezil. This compound could moderately inhibit acetylcholinesterase and metal-induced Aβ aggregation in vitro and showed disassembly of Aβ aggregates. The effects of AD-35 on cognitive impairments and neuroinflammatory changes caused by intracerebroventricular injection of Aβ25-35 were studied in rats. Compared to sham group, Aβ25-35 injection significantly led to learning and memory deficits, astrocyte activation, and pro-inflammatory cytokines releases (TNF-α and IL-1β). Further studies indicated that the phosphorylation of extracellular signal-regulated kinase was involved in astrocyte activation and pro-inflammatory cytokines production. Oral administration of AD-35 could markedly attenuate Aβ25-35 injection-induced astrocyte activation, pro-inflammatory cytokines TNF-α and IL-1β release, and memory deficits. On the contrary, donepezil only showed inhibition of IL-1β production, but failed to block astrocyte activation and TNF-α production. These results showed that AD-35 would be a novel multi-mechanism drug for the prevention and/or treatment of AD.

Music Perception in Dementia. - Golden, Hannah L; Clark, Camilla N; Nicholas, Jennifer M; Cohen, Miriam H; Slattery, Catherine F; Paterson, Ross W; Foulkes, Alexander J M; Schott, Jonathan M; Mummery, Catherine J; Crutch, Sebastian J; Warren, Jason D (J Alzheimers Dis, 2017)
Despite much recent interest in music and dementia, music perception has not been widely studied across dementia syndromes using an information processing approach. Here we addressed this issue in a cohort of 30 patients representing major dementia syndromes of typical Alzheimer's disease (AD, n = 16), logopenic aphasia (LPA, an Alzheimer variant syndrome; n = 5), and progressive nonfluent aphasia (PNFA; n = 9) in relation to 19 healthy age-matched individuals. We designed a novel neuropsychological battery to assess perception of musical patterns in the dimensions of pitch and temporal information (requiring detection of notes that deviated from the established pattern based on local or global sequence features) and musical scene analysis (requiring detection of a familiar tune within polyphonic harmony). Performance on these tests was referenced to generic auditory (timbral) deviance detection and recognition of familiar tunes and adjusted for general auditory working memory performance. Relative to healthy controls, patients with AD and LPA had group-level deficits of global pitch (melody contour) processing while patients with PNFA as a group had deficits of local (interval) as well as global pitch processing. There was substantial individual variation within syndromic groups. Taking working memory performance into account, no specific deficits of musical temporal processing, timbre processing, musical scene analysis, or tune recognition were identified. The findings suggest that particular aspects of music perception such as pitch pattern analysis may open a window on the processing of information streams in major dementia syndromes. The potential selectivity of musical deficits for particular dementia syndromes and particular dimensions of processing warrants further systematic investigation.

Nitrosylation of Vesicular Transporters in Brain of Amyloid Precursor Protein/Presenilin 1 Double Transgenic Mice. - Wang, Ying; Zhou, Zhu; Tan, Hua; Zhu, Shenghua; Wang, Yiran; Sun, Yingxia; Li, Xin-Min; Wang, Jun-Feng (J Alzheimers Dis, 2017)
Nitric oxide can attack thiol groups of cysteine residues in proteins and induce protein cysteine S-nitrosylation. Cholinergic and glutamatergic systems are dysregulated in Alzheimer's disease. Vesicular acetylcholine transporter (VAChT) and vesicular glutamate transporter 1 (VGLUT1) are important in packaging acetylcholine and glutamate into vesicles, which is an important step for neurotransmission. Previously we found that VAChT and VGLUT1 can be nitrosylated and that S-nitrosylation of these transporters inhibits vesicular uptake of acetylcholine and glutamate. To understand the role of VAChT and VGLUT1 nitrosylation in the pathophysiological development of Alzheimer's disease, we analyzed nitrosylation of VAChT and VGLUT1 in brain of amyloid precursor protein (APP) and presenilin 1 (PS1) double transgenic mice, an animal model for Alzheimer's disease. Using a Morris water maze test, we found that 9- and 12-month-old APP/PS1 mice showed memory deficit, compared to wild type mice. We further found that total protein nitrosylation was increased in frontal cortex and hippocampus of 9- and 12-month-old APP/PS1 mice. Although nitrosylation of VAChT and VGLUT1 was not changed in hippocampus of 9- and 12-month-old APP/PS1 mice, nitrosylation of VAChT and VGLUT1 was significantly increased in frontal cortex of APP/PS1 mice at these ages. We also found that nitrosylation of VAChT and VGLUT1 was increased in hippocampus (but not frontal cortex) of 3-month-old APP/PS1 mice. These findings suggest that nitrosylation of VAChT and VGLUT1 may be associated with dysfunctional acetylcholinergic and glutamatergic neurotransmission in Alzheimer's disease.

No Genetic Overlap Between Circulating Iron Levels and Alzheimer's Disease. - Lupton, Michelle K; Benyamin, Beben; Proitsi, Petroula; Nyholt, Dale R; Ferreira, Manuel A; Montgomery, Grant W; Heath, Andrew C; Madden, Pamela A; Medland, Sarah E; Gordon, Scott D; Lovestone, Simon; Tsolaki, Magda; et al. (J Alzheimers Dis, 2017)
Iron deposition in the brain is a prominent feature of Alzheimer's disease (AD). Recently, peripheral iron measures have also been shown to be associated with AD status. However, it is not known whether these associations are causal: do elevated or depleted iron levels throughout life have an effect on AD risk? We evaluate the effects of peripheral iron on AD risk using a genetic profile score approach by testing whether variants affecting iron, transferrin, or ferritin levels selected from GWAS meta-analysis of approximately 24,000 individuals are also associated with AD risk in an independent case-control cohort (n∼10,000). Conversely, we test whether AD risk variants from a GWAS meta-analysis of approximately 54,000 account for any variance in iron measures (n∼9,000). We do not identify a genetic relationship, suggesting that peripheral iron is not causal in the initiation of AD pathology.

Novel Blood-Based Biomarkers of Cognition, Stress, and Physical or Cognitive Training in Older Adults at Risk of Dementia: Preliminary Evidence for a Role of BDNF, Irisin, and the Kynurenine Pathway. - Küster, Olivia C; Laptinskaya, Daria; Fissler, Patrick; Schnack, Cathrin; Zügel, Martina; Nold, Verena; Thurm, Franka; Pleiner, Sina; Karabatsiakis, Alexander; von Einem, Björn; Weydt, Patrick; Liesener, André; et al. (J Alzheimers Dis, 2017)
Psychosocial stress and physical, cognitive, and social activity predict the risk of cognitive decline and dementia. The aim of this study was to elucidate brain-derived neurotrophic factor (BDNF), irisin, and the kynurenine pathway (KP) as potential underlying biological correlates. We evaluated associations of irisin and the KP with BDNF in serum and with cognition, stress, and activities. Furthermore, changes in serum concentrations of BDNF, irisin, and KP metabolites were investigated after physical or cognitive training. Forty-seven older adults at risk of dementia were assigned to 10 weeks of physical training, cognitive training, or a wait-list control condition. Previous physical, cognitive, and social activities and stressful life events were recorded; global cognition, episodic memory, and executive functions were assessed. Serum levels of L-kynurenine, kynurenic acid, 3-hydroxykynurenine (3-HK), and quinolinic acid (QUIN) were determined by validated assays based on liquid chromatography coupled to tandem mass spectrometry. BDNF and irisin serum levels were determined with enzyme-linked immunosorbent assays. BDNF and irisin correlated positively with global cognition and episodic memory, while the neurotoxic metabolite QUIN correlated negatively with executive functions. Stressful life events were associated with reduced BDNF and increased 3-HK. 3-HK decreased after cognitive training, while BDNF tended to increase after physical training. This suggests that psychosocial stress as well as cognitive and physical training may impact BDNF serum levels and the KP. Irisin and QUIN may constitute novel serum biomarkers of cognitive impairment, in addition to BDNF. Larger scale trials are needed to replicate and extend these novel findings.

A Novel PSEN1 K311R Mutation Discovered in Chinese Families with Late-Onset Alzheimer's Disease Affects Amyloid-β Production and Tau Phosphorylation. - Dong, Jing; Qin, Wei; Wei, Cuibai; Tang, Yi; Wang, Qi; Jia, Jianping (J Alzheimers Dis, 2017)
BACKGROUND: Presenilin-1 (PSEN1) is the most frequently mutated gene in familial Alzheimer's disease (AD), whereas only several novel mutations have been reported in China and functional studies were seldom conducted. OBJECTIVE: We describe a novel PSEN1 K311R mutation in two Chinese families with late-onset AD and its functional impact on amyloid-β protein precursor (AβPP) processing and tau phosphorylation. METHODS: The mutation was detected by direct sequencing of PSEN1 exon 9. HEK293 cells stably expressing wild-type APP695 (HEK293-APP695wt) were transfected with plasmids containing human wild-type PSEN1, PSEN1 K311R mutation, and PSEN1 E280A mutation to compare the K311R mutation's effects on AβPP processing with other groups. In addition, each group of cells were co-transfected with plasmids harboring PSEN1 and human wild-type MAPT complementary DNA to study the mutation's impacts on tau phosphorylation. RESULTS: The K311R mutation was detected in probands of two late-onset AD families. Expression of the K311R or E280A mutation increased amyloid-β (Aβ)42 levels but decreased Aβ40 levels, resulting in an overall increase in the Aβ42/Aβ40 ratio compared to those in wild-type PSEN1 transfected cells (p < 0.05). The K311R or E280A mutation also increased the levels of phosphorylated tau compared to wild-type PSEN1 (p < 0.05). CONCLUSION: The K311R mutation might contribute to AD pathogenesis by overproducing toxic Aβ species and enhancing tau phosphorylation. Further in-depth studies are needed to decipher the pathogenic mechanisms of the K311R mutation in terms of AβPP cleavage, tau phosphorylation, and other presenilin-1 mediated functional pathways.

N-Terminal Pro-B Type Natriuretic Peptide is Associated with Mild Cognitive Impairment in the General Population. - Kara, Kaffer; Mahabadi, Amir Abbas; Weimar, Christian; Winkler, Angela; Neumann, Till; Kälsch, Hagen; Dragano, Nico; Moebus, Susanne; Erbel, Raimund; Jöckel, Karl-Heinz; Jokisch, Martha (J Alzheimers Dis, 2017)
BACKGROUND: N-terminal pro-B type natriuretic peptide (NT-proBNP) is a marker of cardiac stress and is linked with silent cardiac diseases. While associations of cognitive impairment with manifest cardiovascular diseases are established, data on whether subclinical elevation of NT-proBNP levels below clinically established threshold of heart failure is related with cognitive functioning, especially mild cognitive impairment (MCI), is rare. OBJECTIVE: Aim of the present study was to investigate the cross-sectional association of NT-proBNP levels and MCI in a population-based study sample without heart failure. METHODS: We used data from the second examination of the population based Heinz-Nixdorf-Recall-Study. Subjects with overt coronary heart disease and subjects with NT-proBNP levels indicating potential heart failure (NT-proBNP≥300 pg/ml) were excluded from this analysis. Participants performed a validated brief cognitive assessment and were classified either as MCI [subtypes: amnestic-MCI (aMCI), non-amnestic-MCI (naMCI)], or cognitively-normal. RESULTS: We included 419 participants with MCI (63.1±7.4 y; 47% men; aMCI n = 209; naMCI n = 210) and 1,206 cognitively normal participants (62.42±7.1 y; 48% men). NT-proBNP-levels≥125 pg/ml compared to <125 pg/ml were associated with MCI in fully adjusted models (OR 1.65 (1.23;2.23) in the total sample, 1.73 (1.09;2.74) in men and 1.63(1.10;2.41) in women). For aMCI, the fully adjusted OR was 1.53 (1.04;2.25) and for naMCI, the fully adjusted OR was 1.34 (1.09; 166) in the total sample. CONCLUSION: Within normal ranges and without manifest heart failure, higher NT-proBNPlevels are associated with MCI and both MCI subtypes independent of traditional cardiovascular risk factors and sociodemographic parameters.

Occupational Attainment as Risk Factor for Progression from Mild Cognitive Impairment to Alzheimer's Disease: A CREDOS Study. - Myung, Woojae; Lee, Chunsoo; Park, Jin Hong; Woo, Sook-Young; Kim, Seonwoo; Kim, Sangha; Chung, Jae Won; Kang, Hyo Shin; Lim, Shinn-Won; Choi, Junbae; Na, Duk L; Kim, Seong Yoon; et al. (J Alzheimers Dis, 2017)
High occupational attainment has been known as a marker of cognitive reserve. Previous studies in the general population have shown that high occupational attainment is associated with reduced risk of Alzheimer's disease (AD). However, few studies have assessed the effect of occupational attainment on the clinical course of mild cognitive impairment (MCI). In this study, we evaluated whether individuals with high occupational attainment show more frequent progression from MCI to AD. Participants (n = 961) with MCI were recruited from a nationwide, hospital-based multi-center cohort, and were followed for up to 60 months (median: 17.64, interquartile range [12.36, 29.28]). We used Cox regression for competing risks to analyze the effect of occupational attainment on development of AD, treating dementia other than AD as a competing risk. Among the 961 individuals with MCI, a total of 280 (29.1%) converted to dementia during the follow-up period. The risk of progression to AD was higher in the individuals with high occupational attainment after controlling for potential confounders (hazard ratio = 1.83, 95% confidence interval = 1.25-2.69, p = 0.002). High occupational attainment in individuals with MCI is an independent risk factor for higher progression rate of MCI to AD. This result suggests that the protective effect of high occupational attainment against cognitive decline disappears in the MCI stage, and that careful assessment of occupational history can yield important clinical information for prognosis in individuals with MCI.

Odor Identification Screening Improves Diagnostic Classification in Incipient Alzheimer's Disease. - Quarmley, Megan; Moberg, Paul J; Mechanic-Hamilton, Dawn; Kabadi, Sushila; Arnold, Steven E; Wolk, David A; Roalf, David R (J Alzheimers Dis, 2017)
BACKGROUND: Measurements of olfaction may serve as useful biomarkers of incipient dementia. Here we examine the improvement in diagnostic accuracy of Alzheimer's disease (AD) and mild cognitive impairment (MCI) when assessing both cognitive functioning and odor identification. OBJECTIVE: To determine the utility of odor identification as a supplementary screening test in incipient AD. METHODS: Sniffin' Sticks Odor Identification Test (SS-OIT) and the Montreal Cognitive Assessment (MoCA) were administered in 262 AD, 174 MCI [150 amnestic (aMCI), and 24 non-amnestic (naMCI)], and 292 healthy older adults (HOA). RESULTS: Odor identification scores were higher in HOA relative to MCI or AD groups, and MCI outperformed AD. Odor identification scores were higher in aMCI single domain than aMCI multiple domain. Complementing MoCA scores with the SS-OIT significantly improved diagnostic accuracy of individuals with AD and MCI, including within MCI subgroups. DISCUSSION: Odor identification is a useful supplementary screening tool that provides additional information relevant for clinical categorization of AD and MCI, including those who are at highest risk to convert to AD.

Overexpression of Kinesin Superfamily Motor Proteins in Alzheimer's Disease. - Hares, Kelly; Miners, James Scott; Cook, Amelia Jane; Rice, Claire; Scolding, Neil; Love, Seth; Wilkins, Alastair (J Alzheimers Dis, 2017)
Defects in motor protein-mediated neuronal transport mechanisms have been implicated in a number of neurodegenerative disorders but remain relatively little studied in Alzheimer's disease (AD). Our aim in the present study was to assess the expression of the anterograde kinesin superfamily motor proteins KIF5A, KIF1B, and KIF21B, and to examine their relationship to levels of hyperphosphorylated tau, amyloid-β protein precursor (AβPP), and amyloid-β (Aβ) in human brain tissue. We used a combination of qPCR, immunoblotting, and ELISA to perform these analyses in midfrontal cortex from 49 AD and 46 control brains. Expression of KIF5A, KIF1B, and KIF21B at gene and protein level was significantly increased in AD. KIF5A protein expression correlated inversely with the levels of AβPP and soluble Aβ in AD brains. Upregulation of KIFs may be an adaptive response to impaired axonal transport in AD.

Overexpression of Ubiquilin-1 Alleviates Alzheimer's Disease-Caused Cognitive and Motor Deficits and Reduces Amyloid-β Accumulation in Mice. - Adegoke, Oludotun O; Qiao, Fangfang; Liu, Yanying; Longley, Kirsty; Feng, Shelley; Wang, Hongmin (J Alzheimers Dis, 2017)
Ubiquilin-1 (Ubqln1) is a ubiquitin-like protein that has been implicated in Alzheimer's disease (AD). However, whether Ubqln1 modulates learning and memory and alters AD-like behavior and/or pathology has not been determined in animal models. To understand the function of Ubqln1 in vivo, we previously generated Ubqln1 transgenic (TG) mice that overexpress mouse Ubqln1. With the model, we here characterized the TG mouse cognitive behaviors and found that Ubqln1 TG mice showed better spatial learning and memory capabilities than their wild-type littermates in both radial arm water maze and Y-maze tests. Additionally, we crossed the Ubqln1 TG mice with the AβPPswe/PSEN1dE9 double transgenic AD mouse to generate the AD/Ubqln1 triple TG (AD/TG) mice. Our results suggest that at 12 months of age following the onset of AD, AD/TG mice showed better spatial learning and memory than AD mice. AD/TG mice also exhibited better motor function than AD mice at the same age. Furthermore, compared to AD mice, AD/TG mice showed significant reduction in amyloid-β 40 (Aβ40) and Aβ42 levels in the cerebral cortex and in the hippocampus at the post-onset stage. The number of Aβ plaques was significantly decreased in the cerebral cortex of AD/TG mice at this post-onset stage. Moreover, mature AβPP level in AD/TG hippocampus was lower than that in AD hippocampus. These data not only provide a direct link between overexpression of Ubqln1 and altered learning and memory, but also raise the possibility that Ubqln1 is a potential therapeutic target for treating AD and possibly other neurodegenerative disorders.

Passive Assessment of Routine Driving with Unobtrusive Sensors: A New Approach for Identifying and Monitoring Functional Level in Normal Aging and Mild Cognitive Impairment. - Seelye, Adriana; Mattek, Nora; Sharma, Nicole; Witter, Phelps; Brenner, Ariella; Wild, Katherine; Dodge, Hiroko; Kaye, Jeffrey (J Alzheimers Dis, 2017)
BACKGROUND: Driving is a key functional activity for many older adults, and changes in routine driving may be associated with emerging cognitive decline due to early neurodegenerative disease. Current methods for assessing driving such as self-report are inadequate for identifying and monitoring subtle changes in driving patterns that may be the earliest signals of functional change in developing mild cognitive impairment (MCI). OBJECTIVE: This proof of concept study aimed to establish the feasibility of continuous driving monitoring in a sample of cognitively normal and MCI older adults for an average of 206 days using an unobtrusive driving sensor and demonstrate that derived sensor-based driving metrics could effectively discriminate between MCI and cognitively intact groups. METHODS: Novel objective driving measures derived from 6 months of routine driving monitoring were examined in older adults with intact cognition (n = 21) and MCI (n = 7) who were enrolled in the Oregon Center for Aging and Technology (ORCATECH) longitudinal assessment program. RESULTS: Unobtrusive continuous monitoring of older adults' routine driving using a driving sensor was feasible and well accepted. MCI participants drove fewer miles and spent less time on the highway per day than cognitively intact participants. MCI drivers showed less day-to-day fluctuations in their driving habits than cognitively intact drivers. CONCLUSION: Sensor-based driving measures are objective, unobtrusive, and can be assessed every time a person drives his or her vehicle to identify clinically meaningful changes in daily driving. This novel methodology has the potential to be useful for the early detection and monitoring of changes in daily functioning within individuals.

PCSK9 Promotes oxLDL-Induced PC12 Cell Apoptosis Through the Bcl-2/Bax-Caspase 9/3 Signaling Pathway. - Liu, Lu-Shan; Bai, Xue-Qin; Gao, Ya; Wu, Qi; Ren, Zhong; Li, Qing; Pan, Li-Hong; He, Ni-Ya; Peng, Juan; Tang, Zhi-Han (J Alzheimers Dis, 2017)
BACKGROUND: Hyperlipidemia is a risk factor for neurodegenerative diseases. Proprotein convertase subtilisin / Kexin type 9 (PCSK9) degrades hepatic low-density lipoprotein receptor (LDLR) to regulate lipid metabolism. It is unclear if PCSK9 plays a role in neurodegenerative diseases. OBJECTIVE: This study was designed to determine whether PCSK9 is crucial between hyperlipidemia and Alzheimer's disease. The interrelationship between PCSK9 and neuronal apoptosis was explored in PC12 cells in response to treatment with oxidized low-density lipoprotein (oxLDL). METHODS: Cultured PC12 cells were serum-starved and incubated with different concentrations of oxLDL for 24 h. Intracytoplasmic lipid droplets were observed by oil red O staining. Morphological assessment of apoptotic cells was performed using Hoechst 33258 staining and flow cytometry analysis. The expression of mRNA and protein was detected by reverse-transcription polymerase chain reaction (RT-PCR) and western blot analyses, respectively. Transfection of small interfering RNA (siRNA) into PC12 cells was conducted using HiperFect Transfection Reagent. Concentrations of Aβ40 and Aβ42 were detected by enzyme-linked immunosorbent assay (ELISA) kit. RESULTS: Intracellular lipid content, the number of apoptotic cells, and PCSK9 expression were increased in PC12 cells after oxLDL treatment. Transfection with PCSK9 siRNA reduced the oxLDL-induced apoptosis of PC12 cells. We further confirmed the involvement of Bcl-2/Bax-Caspase (9, 3) signaling pathway in the regulation of PC12 cells apoptosis.β-Secretase 1, another target gene of PCSK9, was downregulated in PC12 cells in response to oxLDL treatment. Aβ40 and Aβ42 contents were also decreased. CONCLUSION: PCSK9 promotes oxLDL-induced PC12 cell apoptosis through the Bcl-2/Bax-Caspase 9/3 signaling pathway.
Keywords: Amyloid beta-Peptides; Analysis of Variance; Animals; Apoptosis; bcl-2-Associated X Protein; Caspases; Culture Media, Serum-Free; Dose-Response Relationship, Drug; Flow Cytometry; Lipid Metabolism; Lipoproteins, LDL; PC12 Cells; Peptide Fragments; Proprotein Convertase 9; Proto-Oncogene Proteins c-bcl-2; Rats; RNA, Messenger; RNA, Small Interfering; Signal Transduction; Transfection

PE859, A Novel Curcumin Derivative, Inhibits Amyloid-β and Tau Aggregation, and Ameliorates Cognitive Dysfunction in Senescence-Accelerated Mouse Prone 8. - Okuda, Michiaki; Fujita, Yuki; Hijikuro, Ichiro; Wada, Mei; Uemura, Takuya; Kobayashi, Yukako; Waku, Tomonori; Tanaka, Naoki; Nishimoto, Takaaki; Izumi, Yasuhiko; Kume, Toshiaki; Akaike, Akinori; et al. (J Alzheimers Dis, 2017)
Aggregation of amyloid-β (Aβ) and tau plays a crucial role in the onset and progression of Alzheimer's disease (AD). Therefore, the inhibition of Aβ and tau aggregation may represent a potential therapeutic target for AD. Herein, we designed and synthesized both Aβ and tau dual aggregation inhibitors based on the structure of curcumin and developed the novel curcumin derivative PE859. In this study, we investigated the inhibitory activity of PE859 on Aβ aggregationin vitro and the therapeutic effects of PE859 on cognitive dysfunction via dual inhibition of Aβ and tau aggregation in vivo. PE859 inhibited Aβ aggregation in vitro and protected cultured cells from Aβ-induced cytotoxicity. Furthermore, PE859 ameliorated cognitive dysfunction and reduced the amount of aggregated Aβ and tau in brains of senescence-accelerated mouse prone 8 (SAMP8). These results warrant consideration of PE859 as a candidate drug for AD.

People with Dementia Can Learn Compensatory Movement Maneuvers for the Sit-to-Stand Task: A Randomized Controlled Trial. - Werner, Christian; Wiloth, Stefanie; Lemke, Nele Christin; Kronbach, Florian; Jansen, Carl-Philipp; Oster, Peter; Bauer, Jürgen M; Hauer, Klaus (J Alzheimers Dis, 2017)
BACKGROUND: A complex motor skill highly relevant to mobility in everyday life (e.g., sit-to-stand [STS] transfer) has not yet been addressed in studies on motor learning in people with dementia (PwD). OBJECTIVE: To determine whether a dementia-specific motor learning exercise program enables PwD to learn compensatory STS maneuvers commonly taught in geriatric rehabilitation therapy to enhance patients' STS ability. METHODS: Ninety-seven patients with mild-to-moderate dementia (Mini-Mental State Examination: 21.9±2.9 points) participated in a double-blinded, randomized, placebo-controlled trial with 10-week intervention and 3-month follow-up period. The intervention group (IG, n = 51) underwent a motor learning exercise program on compensatory STS maneuvers specifically designed for PwD. The control group (CG, n = 46) performed a low-intensity motor placebo activity. Primary outcomes were scores of the Assessment of Compensatory Sit-to-stand Maneuvers in People with Dementia (ACSID), which covers the number of recalled and initiated, and of effectively performed compensatory STS maneuvers. Secondary outcomes included temporal and kinematic STS characteristics measured by a body-fixed motion sensor (BFS, DynaPort® Hybrid). RESULTS: The IG significantly improved in all ACSID scores compared to the CG (p < 0.001). Secondary analysis confirmed learning effects for all BFS-based outcomes (p < 0.001-0.006). Learning gains were sustained during follow-up for most outcomes. CONCLUSION: People with mild-to-moderate dementia can learn and retain compensatory STS maneuvers in response to a dementia-specific motor learning exercise program. This is the first study that demonstrated preserved motor learning abilities in PwD by using a motor skill highly relevant to everyday life.

Peripheral versus Central Index of Metabolic Dysfunction and Associations with Clinical and Pathological Outcomes in Alzheimer's Disease. - McLimans, Kelsey E; Webb, Joseph L; Anantharam, Vellareddy; Kanthasamy, Anumantha; Willette, Auriel A (J Alzheimers Dis, 2017)
BACKGROUND/OBJECTIVE: Insulin-like growth factor binding protein 2 (IGFBP-2) regulates blood glucose levels, facilitates hippocampal synaptic plasticity and may have a predictive value for Alzheimer's disease (AD) diagnosis. METHODS: IGFBP-2 levels were studied in plasma in 566 subjects and in cerebrospinal fluid (CSF) in 245 subjects across the AD spectrum from the Alzheimer's Disease Neuroimaging Initiative (ADNI). Variants in the IGFBP-2 gene were examined. Linear mixed modeling in SPSS tested main effects of IGFBP-2 and interactions with APOE4 on neurocognitive indices and biomarkers. Voxel-wise regression was used to gauge IGFBP-2 and regional grey matter and glucose metabolism associations. RESULTS: Each point increase in IGFBP-2 corresponded to a three times greater likelihood of having mild cognitive impairment (MCI) or AD. IGFBP-2 showed beneficial associations with respect to cognitive scores in individuals with two APOE4 alleles. Higher IGFBP-2 predicted higher insulin resistance, but not CSF amyloid or tau. Voxel-wise analyses showed that plasma IGFBP-2 predicted lower grey matter volume and FDG metabolism in a large area spanning the frontal, temporal, and occipital lobes. CSF IGFBP-2 levels showed similar voxel-wise analysis results, but were uniquely associated with CSF amyloid and tau. Analysis of single nucleotide polymorphisms (SNPs) in IGFBP-2 showed that subjects carrying risk alleles versus common alleles had increased risk of AD and lower memory scores. Voxel-wise analyses of these SNPs also implicated the hippocampus and prefrontal cortex. CONCLUSIONS: IGFBP-2 is associated with AD risk and outcomes; plasma IGFBP-2 provides stronger predictive power for brain outcomes, while CSF IGFBP-2 provides improved predictive accuracy for AD CSF biomarkers.

PET Imaging of Tau Pathology and Relationship to Amyloid, Longitudinal MRI, and Cognitive Change in Down Syndrome: Results from the Down Syndrome Biomarker Initiative (DSBI). - Rafii, Michael S; Lukic, Ana S; Andrews, Randolph D; Brewer, James; Rissman, Robert A; Strother, Stephen C; Wernick, Miles N; Pennington, Craig; Mobley, William C; Ness, Seth; Matthews, Dawn C (J Alzheimers Dis, 2017)
BACKGROUND: Adults with Down syndrome (DS) represent an enriched population for the development of Alzheimer's disease (AD), which could aid the study of therapeutic interventions, and in turn, could benefit from discoveries made in other AD populations. OBJECTIVES: 1) Understand the relationship between tau pathology and age, amyloid deposition, neurodegeneration (MRI and FDG PET), and cognitive and functional performance; 2) detect and differentiate AD-specific changes from DS-specific brain changes in longitudinal MRI. METHODS: Twelve non-demented adults, ages 30 to 60, with DS were enrolled in the Down Syndrome Biomarker Initiative (DSBI), a 3-year, observational, cohort study to demonstrate the feasibility of conducting AD intervention/prevention trials in adults with DS. We collected imaging data with 18F-AV-1451 tau PET, AV-45 amyloid PET, FDG PET, and volumetric MRI, as well as cognitive and functional measures and additional laboratory measures. RESULTS: All amyloid negative subjects imaged were tau-negative. Among the amyloid positive subjects, three had tau in regions associated with Braak stage VI, two at stage V, and one at stage II. Amyloid and tau burden correlated with age. The MRI analysis produced two distinct volumetric patterns. The first differentiated DS from normal (NL) and AD, did not correlate with age or amyloid, and was longitudinally stable. The second pattern reflected AD-like atrophy and differentiated NL from AD. Tau PET and MRI atrophy correlated with several cognitive and functional measures. CONCLUSIONS: Tau accumulation is associated with amyloid positivity and age, as well as with progressive neurodegeneration measurable using FDG and MRI. Tau correlates with cognitive decline, as do AD-specific hypometabolism and atrophy.

Plasma Proteomic Profiles of Cerebrospinal Fluid-Defined Alzheimer's Disease Pathology in Older Adults. - Dayon, Loïc; Wojcik, Jérôme; Núñez Galindo, Antonio; Corthésy, John; Cominetti, Ornella; Oikonomidi, Aikaterini; Henry, Hugues; Migliavacca, Eugenia; Bowman, Gene L; Popp, Julius (J Alzheimers Dis, 2017)
BACKGROUND: Cerebrospinal fluid (CSF) biomarkers of the beta-amyloid and microtubule associated protein tau metabolism have proven the capacity to improve classification of subjects developing Alzheimer's disease (AD). The blood plasma proteome was characterized to further elaborate upon the mechanisms involved and identify proteins that may improve classification of older adults developing an AD dementia. OBJECTIVE: Identify and describe plasma protein expressions that best classify subjects with CSF-defined presence of AD pathology and cerebral amyloidosis. METHODS: We performed a cross-sectional analysis of samples collected from community-dwelling elderly with (n = 72) or without (n = 48) cognitive impairment. CSF Aβ1-42, tau, and phosphorylated tau (P-tau181) were measured using ELISA, and mass spectrometry quantified the plasma proteomes. Presence of AD pathology was defined as CSF P-tau181/Aβ1-42 > 0.0779, and presence of amyloidosis was defined as CSF Aβ1-42 < 724 pg/mL. RESULTS: Two hundred and forty-eight plasma proteins were quantified. Plasma proteins did not improve classification of the AD CSF biomarker profile in the whole sample. When the analysis was separately performed in the cognitively impaired individuals, the diagnosis accuracy of AD CSF profile was 88.9% with 19 plasma proteins included. Within the full cohort, there were 16 plasma proteins that improved diagnostic accuracy of cerebral amyloidosis to 92.4%. CONCLUSION: Plasma proteins improved classification accuracy of AD pathology in cognitively-impaired older adults and appeared representative of amyloid pathology. If confirmed, those candidates could serve as valuable blood biomarkers of the preclinical stages of AD or risk of developing AD.

Plasma Tau Association with Brain Atrophy in Mild Cognitive Impairment and Alzheimer's Disease. - Deters, Kacie D; Risacher, Shannon L; Kim, Sungeun; Nho, Kwangsik; West, John D; Blennow, Kaj; Zetterberg, Henrik; Shaw, Leslie M; Trojanowski, John Q; Weiner, Michael W; Saykin, Andrew J (J Alzheimers Dis, 2017)
BACKGROUND: Peripheral (plasma) and central (cerebrospinal fluid, CSF) measures of tau are higher in Alzheimer's disease (AD) relative to prodromal stages and controls. While elevated CSF tau concentrations have been shown to be associated with lower grey matter density (GMD) in AD-specific regions, this correlation has yet to be examined for plasma in a large study. OBJECTIVE: Determine the neuroanatomical correlates of plasma tau using voxel-based analysis. METHODS: Cross-sectional data for 508 ADNI participants were collected for clinical, plasma total-tau (t-tau), CSF amyloid (Aβ42) and tau, and MRI variables. The relationship between plasma tau and GMD and between CSF t-tau and GMD were assessed on a voxel-by-voxel basis using regression models. Age, sex, APOEɛ4 status, diagnosis, and total intracranial volume were used as covariates where appropriate. Participants were defined as amyloid positive (Aβ+) if CSF Aβ42 was <192 pg/mL. RESULTS: Plasma tau was negatively correlated with GMD in the medial temporal lobe (MTL), precuneus, thalamus, and striatum. The associations with thalamus and striatum were independent of diagnosis. A negative correlation also existed between plasma tau and GMD in Aβ+ participants in the MTL, precuneus, and frontal lobe. When compared to CSF t-tau, plasma tau showed a notably different associated brain atrophy pattern, with only small overlapping regions in the fusiform gyrus. CONCLUSION: Plasma tau may serve as a non-specific marker for neurodegeneration but is still relevant to AD considering low GMD was associated with plasma tau in Aβ+ participants and not Aβ-participants.

Pleiotropic Effect of Human ApoE4 on Cerebral Ceramide and Saturated Fatty Acid Levels. - den Hoedt, Sandra; Janssen, Carola I F; Astarita, Giuseppe; Piomelli, Daniele; Leijten, Frank P J; Crivelli, Simone M; Verhoeven, Adrie J M; De Vries, Helga E; Walter, Jochen; Martinez-Martinez, Pilar; Sijbrands, Eric J G; Kiliaan, Amanda J; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Apolipoprotein E (ApoE) is known for its role in lipid trafficking and the ɛ4 allele is a risk factor for late onset Alzheimer's disease (AD). Recently, aberrant ceramide and fatty acid (FA) levels have been implicated in AD. OBJECTIVE: To determine the specific effects of human ApoE4 (hE4) on cerebral ceramide and FA content during chow or a high fat/high cholesterol (HFHC) diet. METHODS: Cerebral ceramide and FA profiles were determined by LC-MSMS in 15-month-old female wild-type (WT), ApoE-knockout (E0), and hE4-knockin mice fed chow or a HFHC diet for 3 months. mRNA levels of genes involved in ceramide and FA metabolism were determined by qPCR. RESULTS: Similar to E0, hE4 mice displayed lower cerebral total ceramide, Cer16 : 0, and Cer24 : 1 levels than WT mice on both diets. Akin to WT mice, hE4 mice had lower total and saturated FA levels on chow than E0 mice. The HFHC diet significantly increased total and saturated FA levels in hE4 mice. Chow-fed hE4 mice showed lower mRNA levels of ceramide synthase (CerS) 6, acid sphingomyelinase, and of most ceramide and FA transporters than WT and E0 mice. The HFHC diet downregulated the expression of CerSs in hE4 and WT mice, and of ceramide and FA transporters in WT mice, but not in E0 mice. CONCLUSION: hE4 reduced cerebral ceramide levels to levels observed in E0 mice independent of diet. The HFHC diet increased cerebral FA levels in hE4 mice. This was associated with alterations in the expression of ceramide and FA transporters specifically in hE4 mice.

Polymorphonuclear Neutrophil Functions are Differentially Altered in Amnestic Mild Cognitive Impairment and Mild Alzheimer's Disease Patients. - Le Page, Aurélie; Lamoureux, Julie; Bourgade, Karine; Frost, Eric H; Pawelec, Graham; Witkowski, Jacek M; Larbi, Anis; Dupuis, Gilles; Fülöp, Tamás (J Alzheimers Dis, 2017)
The mechanisms of neurodegeneration in Alzheimer's disease (AD) remain under investigation. Alterations in the blood-brain barrier facilitate exchange of inflammatory mediators and immune cells between the brain and the periphery in AD. Here, we report analysis of phenotype and functions of polymorphonuclear neutrophils (PMN) in peripheral blood from patients with amnestic mild cognitive impairment (aMCI, n = 13), patients with mild AD (mAD, n = 15), and healthy elderly controls (n = 13). Results showed an increased expression of CD177 in mAD but not in healthy or aMCI patients. IL-8 stimulated increased expression of the CD11b integrin in PMN of healthy subjects in vitro but PMN of aMCI and mAD patients failed to respond. CD14 and CD16 expression was lower in PMN of mAD but not in aMCI individuals relative to controls. Only PMN of aMCI subjects expressed lower levels of CD88. Phagocytosis toward opsonized E. coli was differentially impaired in PMN of aMCI and mAD subjects whereas the capacity to ingest Dextran particles was absent only in mAD subjects. Killing activity was severely impaired in aMCI and mAD subjects whereas free radical production was only impaired in mAD patients. Inflammatory cytokine (TNFα, IL-6, IL-1β, IL-12p70) and chemokine (MIP-1α, MIP-1β, IL-8) production in response to LPS stimulation was very low in aMCI and nearly absent in mAD subjects. TLR2 expression was low only in aMCI. Our data showed a differentially altered capacity of PMN of aMCI and mAD subjects to respond to pathological aggression that may impact impaired responses associated with AD development.

Potentially Inappropriate Medication, Anticholinergic Burden, and Mortality in People Attending Memory Clinics. - Cross, Amanda J; George, Johnson; Woodward, Michael C; Ames, David; Brodaty, Henry; Wolfe, Rory; Connors, Michael H; Elliott, Rohan A (J Alzheimers Dis, 2017)
BACKGROUND: There is limited evidence regarding the association between potentially inappropriate medications (PIM) and mortality in older people with cognitive impairment. OBJECTIVE: To examine whether use of medications considered to be potentially inappropriate in older people with cognitive impairment (PIMcog) and anticholinergic cognitive burden (ACB) were associated with mortality in people who attended memory clinics. METHODS: Cross-sectional and longitudinal analyses of data from the Prospective Research In MEmory clinics (PRIME) study. Participants were community-dwelling people who attended nine memory clinics and had a diagnosis of mild cognitive impairment or dementia. PIMcog was defined as any medication considered potentially inappropriate for a person with cognitive impairment according to Beers or STOPP criteria. Anticholinergic burden was calculated using the ACB scale. Time-dependent Cox-proportional hazards regression was used to analyze associations between PIMcog use/ACB score and all-cause mortality over a three-year follow-up period. The regression model included the baseline variables: age, gender, education, cognitive diagnoses, total number of medications, disease-burden, cognition, physical function, and neuropsychiatric symptoms. RESULTS: Of 964 participants, 360 (37.3%) used one or more PIMcog at some time during the study; most commonly anticholinergics and sedatives. 624 (64.7%) participants used a medication with potential or definite anticholinergic properties (ACB>0) at some point during the study. Both PIMcog use (adjusted hazard ratio: 1.42 95% CI: 1.12-1.80) and ACB score (adjusted hazard ratio: 1.18 95% CI: 1.06-1.32) were associated with mortality. CONCLUSION: Use of PIMcogs and medications with anticholinergic properties was common among memory clinic patients and both were associated with mortality.

Potentially Inappropriate Medication in Community-Dwelling Primary Care Patients who were Screened Positive for Dementia. - Wucherer, Diana; Eichler, Tilly; Hertel, Johannes; Kilimann, Ingo; Richter, Steffen; Michalowsky, Bernhard; Thyrian, Jochen René; Teipel, Stefan; Hoffmann, Wolfgang (J Alzheimers Dis, 2017)
BACKGROUND: Potentially inappropriate medication (PIM) in older people is a risk factor for adverse drug effects. This risk is even higher in older people with dementia (PWD). OBJECTIVE: Our study aimed to determine (1) the prevalence of PIM among primary care patients who were screened positive for dementia and (2) the sociodemographic and clinical variables associated with the use of PIM. METHODS: DelpHi-MV (Dementia: life- and person-centered help in Mecklenburg-Western Pomerania) is a general practitioner-based, cluster-randomized, controlled intervention study to implement and evaluate an innovative concept of collaborative dementia care management in Germany. The comprehensive baseline assessment includes a home medication review. The present analyses are based on the data from 448 study participants (age 70+, DemTect <9). PIMs were identified using the list of Potentially Inappropriate Medications in the Elderly (Priscus). RESULTS: (1) A total of 99 study participants (22%) received at least one PIM. The highest prevalence was found for antidepressants, benzodiazepines, and analgetics. The most frequently prescribed PIMs were amitriptyline, etoricoxib, and doxazosin. (2) Use of a PIM was significantly associated with a diagnosis of a mental or behavioral disorder. CONCLUSIONS: The prescription rate of PIMs for community-dwelling PWD was comparable with the rates found for the general population of older people in Germany (20-29%). Antidepressants with anticholinergic properties and long-acting benzodiazepines were the most prescribed PIMs, despite having an unfavorable benefit-risk ratio. This high prevalence of PIM prescriptions in a vulnerable population of PWD indicates that standard care for dementia should include careful medication review and management.

Preclinical Amyloid-β and Axonal Degeneration Pathology in Delirium. - Idland, Ane-Victoria; Wyller, Torgeir Bruun; Støen, Randi; Eri, Lars Magne; Frihagen, Frede; Ræder, Johan; Chaudhry, Farrukh Abbas; Hansson, Oskar; Zetterberg, Henrik; Blennow, Kaj; Bogdanovic, Nenad; Brækhus, Anne; et al. (J Alzheimers Dis, 2017)
BACKGROUND: The clinical relevance of brain β-amyloidosis in older adults without dementia is not established. As delirium and dementia are strongly related, studies on patients with delirium may give pathophysiological clues. OBJECTIVE: To determine whether the Alzheimer's disease (AD) cerebrospinal fluid (CSF) biomarkers amyloid-β 1-42 (Aβ42), total tau (T-tau), and phosphorylated tau (P-tau) are associated with delirium in hip fracture patients with and without dementia. METHODS: CSF was collected in conjunction to spinal anesthesia in 129 patients. Delirium was assessed using the Confusion Assessment Method once daily in all patients, both pre- and postoperatively. The diagnosis of dementia at admission was based upon clinical consensus. CSF levels of Aβ42, T-tau, and P-tau were analyzed. RESULTS: In patients without dementia, we found lower CSF Aβ42 levels (median, 310 ng/L versus 489 ng/L, p = 0.006), higher T-tau levels (median, 505 ng/L versus 351 ng/L, p = 0.02), but no change in P-tau in patients who developed delirium (n = 16) compared to those who remained lucid (n = 49). Delirious patients also had lower ratios of Aβ42 to T-tau (p < 0.001) and P-tau (p = 0.001) relative to those without delirium. CSF Aβ42 and T-tau remained significantly associated with delirium status in adjusted analyses. In patients with dementia, CSF biomarker levels did not differ between those with (n = 54) and without delirium (n = 10). CONCLUSION: The reduction in CSF Aβ42, indicating β-amyloidosis, and increase in T-tau, indicating neurodegeneration, in hip fracture patients without dementia developing delirium indicates that preclinical AD brain pathology is clinically relevant and possibly plays a role in delirium pathophysiology.

Prediction Model of Conversion to Dementia Risk in Subjects with Amnestic Mild Cognitive Impairment: A Longitudinal, Multi-Center Clinic-Based Study. - Jang, Hyemin; Ye, Byoung Seok; Woo, Sookyoung; Kim, Sun Woo; Chin, Juhee; Choi, Seong Hye; Jeong, Jee Hyang; Yoon, Soo Jin; Yoon, Bora; Park, Kyung Won; Hong, Yun Jeong; Kim, Hee Jin; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Patients with amnestic mild cognitive impairment (aMCI) have an increased risk of dementia. However, conversion rate varies. Therefore, predicting the dementia conversion in these patients is important. OBJECTIVE: We aimed to develop a nomogram to predict dementia conversion in aMCI subjects using neuropsychological profiles. METHODS: A total of 338 aMCI patients from two hospital-based cohorts were used in analysis. All patients were classified into 1) verbal, visual, or both, 2) early or late, and 3) single or multiple-domain aMCI according to the modality, severity of memory dysfunction, and multiplicity of involved cognitive domains, respectively. Patients were followed up, and conversion to dementia within 3 years was defined as the primary outcome. Our patients were divided into a training data set and a validation data set. The associations of potential covariates with outcome were tested, and nomogram was constructed by logistic regression model. We also developed another model with APOE data, which included 242 patients. RESULTS: In logistic regression models, both modalities compared with visual only (OR 4.44, 95% CI 1.83-10.75, p = 0.001), late compared to early (OR 2.59, 95% CI 1.17-5.72, p = 0.019), and multiple compared to single domain (OR 3.51, 95% CI 1.62-7.60, p = 0.002) aMCI were significantly associated with dementia conversion within 3 years. A nomogram incorporating these clinical variables was constructed on the training data set and validated on the validation data set. Both nomograms with and without APOE data showed good prediction performance (c-statistics ≥ 0.75). CONCLUSIONS: This study showed that several neuropsychological profiles of aMCI are significantly associated with imminent dementia conversion, and a nomogram incorporating these clinical subtypes is simple and useful to help to predict disease progression.

Prevalence, Risk Factors, and Complaints Screening Tool Exploration of Subjective Cognitive Decline in a Large Cohort of the Chinese Population. - Hao, Lixiao; Wang, Xiaoni; Zhang, Ling; Xing, Yue; Guo, Qihao; Hu, Xiaochen; Mu, Bin; Chen, Yili; Chen, Guanqun; Cao, Jing; Zhi, Xiaodong; Liu, Jiaojiao; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Substantial studies have reported the prevalence and the affecting factors of subjective cognitive decline (SCD). The complaints screening scale has also been used for probing. However, little is known in China. OBJECTIVE: To investigate the prevalence and risk factors of SCD, and explore an SCD complaints screening scale in China. METHODS: Stratified cluster random sampling was conducted. 2,689 residents aged 60-80 years completed questionnaire 1. 814 residents were included for clinical and neuropsychological evaluations. Two standards were used to make the diagnosis of mild cognitive impairment (MCI) and SCD, and a preliminary screening rate comparison was carried out. Finally, we assessed the risk factors of SCD and the correlation between the SCD-questionnaire 9 (SCD-Q9) and the Auditory Verbal Learning Test-Long Delay Free Recall (AVLT-LR). RESULTS: 1) Standard 1 (ADNI2): the prevalence of SCD was 18.8% (95% CI = 14.7-22.9%) and zero conformed to six criteria (SCD plus). 2) Standard 2 (Jak/Bondi): the prevalence of SCD was 14.4% (95% CI = 10.7-18.1%). 3) Standard 1 had a relatively higher "false" positive rate, whereas Standard 2 had higher "false" negative rate. 4) Age, low education, fewer close friends, and daily drinking were independent risk factors for SCD progressing to MCI. 5) Total points of SCD-Q9 were negatively correlated to the value of AVLT-LR. CONCLUSIONS: The prevalence of SCD is high in the ShunYi District in Beijing, China. Age, low education, less social support, and daily drinking are independent risk factors. The brief SCD-Q9 can be used as a reference.

proBDNF Accelerates Brain Amyloid-β Deposition and Learning and Memory Impairment in APPswePS1dE9 Transgenic Mice. - Chen, Jia; Zhang, Tao; Jiao, Shusheng; Zhou, Xinfu; Zhong, Jinhua; Wang, Yanjiang; Liu, Juan; Deng, Juan; Wang, Shuiping; Xu, Zhiqiang (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) is pathologically known for the amyloid-β (Aβ) deposition, neurofibrillary tangles, and neuronal loss in the brain. The precursor of brain-derived neurotrophic factor (proBDNF) before proteolysis has opposing functions to its mature form in neuronal survival and neurite growth. However, the role of proBDNF in the pathogenesis of AD remains unclear. OBJECTIVE: To investigate the effects of proBDNF on neurons in vitro, and on learning and memory impairment and brain Aβ production in a transgenic AD mouse model (APPswePS1dE9). METHODS: We here examined the effects of proBDNF on the viability (MTT assay) and neurite growth (morphologic measurement) of the primary neurons in vitro. After the intracerebroventricular injection of adeno-associated virus-proBDNF (AAV-proBDNF), we then investigated the learning and memory impairment (Morris water maze) and Aβ deposition in the brains of the AD mice. RESULTS: The results showed that proBDNF could inhibit neuronal viability and neurite growth in vitro, enhance Aβ levels, and accelerate its deposition in the brain, which was consistent with the learning and memory impairment of AD mice, likely dependent on the membrane receptor of p75NTR. CONCLUSIONS: Our findings suggest that proBDNF may exert a crucially negative effect during AD pathogenesis andprogression.

Prodromal Dementia with Lewy Bodies and Prodromal Alzheimer's Disease: A Comparison of the Cognitive and Clinical Profiles. - Sadiq, Dilman; Whitfield, Tim; Lee, Lean; Stevens, Tim; Costafreda, Sergi; Walker, Zuzana (J Alzheimers Dis, 2017)
BACKGROUND: Dementia must be diagnosed accurately and early in the disease course to allow pathology-specific treatments to be effective. Dementia with Lewy bodies (DLB) is often misdiagnosed as Alzheimer's disease (AD), especially at the prodromal stage. OBJECTIVE: To compare the clinical and neuropsychological profiles of Mild Cognitive Impairment (MCI) patients who, at follow-up, progressed to AD (retrospectively AD-MCI) or DLB (retrospectively DLB-MCI) or remained MCI. METHODS: This longitudinal study used an unselected sample from a memory clinic database. A total of 1,848 new patients were seen at the memory clinic between 1994-2015. Of these, 560 patients (30%) had an initial diagnosis of MCI and were considered for the study. Inclusion criteria were patients who had a diagnosis of MCI at initial assessment and a minimum of 12 months' follow-up. RESULTS: Of the 429 MCI patients with follow-up data, 164 (38%) remained MCI, 107 (25%) progressed to AD, and 21 (5%) progressed to DLB. The remainder progressed to alternative diagnoses. At baseline, DLB-MCI patients performed significantly worse on visuospatial function and letter fluency tests than both AD-MCI and stable-MCI groups, and better on episodic memory tests than the AD-MCI group. At baseline, DLB-MCI patients had a significantly higher mean UPDRS score and were more likely to have REM sleep behavior disorder and fluctuating cognition. CONCLUSION: DLB-MCI patients have a specific cognitive and neuropsychiatric profile which should alert clinicians to the possibility of prodromal DLB. This is relevant when considered in the context of early disease-specific therapy.

A Prospective Study on the Association between Uric Acid and Cognitive Function among Middle-Aged and Older Chinese. - Wang, Tong; Wu, Yili; Sun, Yongye; Zhai, Long; Zhang, Dongfeng (J Alzheimers Dis, 2017)
BACKGROUND: Uric acid (UA) is a powerful antioxidant that may have neuroprotective properties, yet it is also a risk factor of vascular disease that predisposes individuals to cognitive impairment. Results from longitudinal studies on UA and cognitive decline remain controversial. OBJECTIVE: We examined the associations of baseline plasma UA level with follow-up cognitive function as well as cognitive decline over time among a large sample of middle-aged and older Chinese. METHODS: Data from China Health and Retirement Longitudinal Study (CHARLS) were used. Cognitive function, including episodic memory, mental intactness, and global cognition, were tested twice with 2-year interval. Plasma UA was measured at baseline. Basic demographics, life habits, and health status were considered as potential confounders. Multiple linear regression models and mixed-effects regression models were fitted. RESULTS: A total of 12,798 individuals aged above 45 years were eligible with the follow-up time ranging from 1.33 to 2.42 years. Both global cognitive function and mental intactness declined, while episodic memory remained stable over time. In multiple linear regression models, compared with the lowest baseline UA level, 3rd baseline UA quartile was associated with better follow-up global cognitive function (b = 0.425, p = 0.041) and episodic memory (b = 0.413, p = 0.004), and highest baseline UA quartile was associated with better follow-up mental intactness (b = 0.253, p = 0.041) in males; highest baseline UA level was associated with better follow-up cognition for each measure (b = 0.281∼0.768, p≤0.046) in females. Mixed-effects regression models suggested no significant baseline UA-by-time interactions on any cognitive measure. CONCLUSION: Higher baseline UA level was associated with better cognition in later life but not with rates of cognitive decline among middle-aged and older Chinese.

Proteomics Analysis of Blood Serums from Alzheimer's Disease Patients Using iTRAQ Labeling Technology. - Shen, Liming; Liao, Liping; Chen, Cheng; Guo, Yi; Song, Dalin; Wang, Yong; Chen, Youjiao; Zhang, Kaoyuan; Ying, Ming; Li, Shuiming; Liu, Qiong; Ni, Jiazuan (J Alzheimers Dis, 2017)
Alzheimer' disease (AD) is the most common form of dementia affecting up to 6% of the population over the age of 65. In order to discover differentially expressed proteins that might serve as potential biomarkers, the serums from AD patients and healthy controls were compared and analyzed using the proteomics approach of isobaric tagging for relative and absolute quantitation (iTRAQ). For the first time, AD biomarkers in serums are investigated in the Han Chinese population using iTRAQ labeled proteomics strategy. Twenty-two differentially expressed proteins were identified and out of which nine proteins were further validated with more sample test. Another three proteins that have been reported in the literature to be potentially associated with AD were also investigated for alteration in expression level. Functions of those proteins were mainly related to the following processes: amyloid-β (Aβ) metabolism, cholesterol transport, complement and coagulation cascades, immune response, inflammation, hemostasis, hyaluronan metabolism, and oxidative stress. These results support current views on the molecular mechanism of AD. For the first time, differential expression of zinc-alpha-2-glycoprotein (AZGP1), fibulin-1 (FBLN1), platelet basic protein (PPBP), thrombospondin-1 (THBS1), S100 calcium-binding protein A8 (S100A8), and S100 calcium-binding protein A9 (S100A9) were detected in the serums of AD patients compared with healthy controls. These proteins might play a role in AD pathophysiology and serve as potential biomarkers for AD diagnosis. Specifically, our results strengthened the crucial role of Aβ metabolism and blood coagulation in AD pathogenesis and proteins related to these two processes may be used as peripheral blood biomarkers for AD.

Psychotropic Polypharmacy in Patients with Dementia: Prevalence and Predictors. - Nørgaard, Ane; Jensen-Dahm, Christina; Gasse, Christiane; Hansen, Elsebet Steno; Waldemar, Gunhild (J Alzheimers Dis, 2017)
BACKGROUND: Antipsychotics and other psychotropics are frequently used to treat neuropsychiatric symptoms in patients with dementia, even though the evidence for effect is limited. Concerns have been raised about the safety of antipsychotics, but concomitant use of multiple psychotropic drug classes (psychotropic polypharmacy) may also pose a risk for patients. OBJECTIVE: To investigate the prevalence and predictors associated with use of psychotropic polypharmacy in patients with dementia. METHODS: A population-based study using nationwide registers. Patients with dementia were identified among all Danish residents ≥65 years on January 1, 2012. Data on prescriptions and comorbidity was included in the analysis. Overlapping prescriptions for different psychotropic drug classes were used to determine psychotropic polypharmacy. A multivariable logistic regression analysis was conducted to evaluate factors independently associated with the prescription of other psychotropic drug classes among patients already using antipsychotics. RESULTS: Among all patients registered with dementia (34,553), 25.3% (8,728) used ≥2 psychotropic drugs. Among patients treated with antipsychotics 75.8% (5,403) used at least one other psychotropic drug during the antipsychotic treatment period. Nursing home residency, number of non-psychotropic medications used in 2011, and prior psychiatric diagnosis were associated with psychotropic polypharmacy among antipsychotic drug users. The most frequent combination of psychotropic drugs was antipsychotics and antidepressants. CONCLUSION: Concomitant use of psychotropic drugs was frequent in dementia patients. Patients living in nursing homes had the highest risk of receiving a combination of antipsychotics and other psychotropic drugs. Concomitant use of psychotropics may cause adverse events, and potential consequences for patients' safety call for further investigation.

Rare Genetic Variant in SORL1 May Increase Penetrance of Alzheimer's Disease in a Family with Several Generations of APOE-ɛ4 Homozygosity. - Louwersheimer, Eva; Cohn-Hokke, Petra E; Pijnenburg, Yolande A L; Weiss, Marjan M; Sistermans, Erik A; Rozemuller, Annemieke J; Hulsman, Marc; van Swieten, John C; van Duijn, Cock M; Barkhof, Frederik; Koene, Teddy; Scheltens, Philip; et al. (J Alzheimers Dis, 2017)
BACKGROUND: The major genetic risk factor for late onset Alzheimer's disease (AD) is the APOE-ɛ4 allele. However, APOE-ɛ4 homozygosity is not fully penetrant, suggesting co-occurrence of additional genetic variants. OBJECTIVE: To identify genetic factors that, next to APOE-ɛ4 homozygosity, contribute to the development of AD. METHODS: We identified a family with nine AD patients spanning four generations, with an inheritance pattern suggestive of autosomal dominant AD, with no variants in PSEN1, PSEN2, or APP. We collected DNA from four affected and seven unaffected family members and performed exome sequencing on DNA from three affected and one unaffected family members. RESULTS: All affected family members were homozygous for the APOE-ɛ4 allele. Statistical analysis revealed that AD onset in this family was significantly earlier than could be expected based on APOE genotype and gender. Next to APOE-ɛ4 homozygosity, we found that all four affected family members carried a rare variant in the VPS10 domain of the SORL1 gene, associated with AβPP processing and AD risk. Furthermore, three of four affected family members carried a rare variant in the TSHZ3 gene, also associated with AβPP processing. Affected family members presented between 61 and 74 years, with variable presence of microbleeds/cerebral amyloid angiopathy and electroencephalographic abnormalities. CONCLUSION: We hypothesize that next to APOE-ɛ4 homozygosity, impaired SORL1 protein function, and possibly impaired TSHZ3 function, further disturbed Aβ processing. The convergence of these genetic factors over several generations might clarify the increased AD penetrance and the autosomal dominant-like inheritance pattern of AD as observed in this family.

Recovery from Proactive Semantic Interference in Mild Cognitive Impairment and Normal Aging: Relationship to Atrophy in Brain Regions Vulnerable to Alzheimer's Disease. - Loewenstein, David A; Curiel, Rosie E; Wright, Clinton; Sun, Xiaoyan; Alperin, Noam; Crocco, Elzabeth; Czaja, Sara J; Raffo, Arlene; Penate, Ailyn; Melo, Jose; Capp, Kimberly; Gamez, Monica; et al. (J Alzheimers Dis, 2017)
BACKGROUND: There is growing evidence that proactive semantic interference (PSI) and failure to recover from PSI may represent early features of Alzheimer's disease (AD). OBJECTIVE: This study investigated the association between PSI, recovery from PSI, and reduced MRI volumes in AD signature regions among cognitively impaired and unimpaired older adults. METHODS: Performance on the LASSI-L (a novel test of PSI and recovery from PSI) and regional brain volumetric measures were compared between 38 cognitively normal (CN) elders and 29 older participants with amnestic mild cognitive impairment (MCI). The relationship between MRI measures and performance on the LASSI-L as well as traditional memory and non-memory cognitive measures was also evaluated in both diagnostic groups. RESULTS: Relative to traditional neuropsychological measures, MCI patients' failure to recover from PSI was associated with reduced volumes in the hippocampus (rs = 0.48), precuneus (rs = 0.50); rostral middle frontal lobules (rs = 0.54); inferior temporal lobules (rs = 0.49), superior parietal lobules (rs = 0.47), temporal pole (rs = 0.44), and increased dilatation of the inferior lateral ventricle (rs = -0.49). For CN elders, only increased inferior lateral ventricular size was associated with vulnerability to PSI (rs = -0.49), the failure to recover from PSI (rs = -0.57), and delayed recall on the Hopkins Verbal Learning Test-Revised (rs = -0.48). DISCUSSION: LASSI-L indices eliciting failure to recover from PSI were more highly associated with more MRI regional biomarkers of AD than other traditional cognitive measures. These results as well as recent amyloid imaging studies with otherwise cognitively normal subjects, suggest that recovery from PSI may be a sensitive marker of preclinical AD and deserves further investigation.

Reduced Cardiovascular Functions in Patients with Alzheimer's Disease. - Jin, Wang-Sheng; Bu, Xian-Le; Wang, Ye-Ran; Li, Ling; Li, Wei-Wei; Liu, Yu-Hui; Zhu, Chi; Yao, Xiu-Qing; Chen, Yang; Gao, Chang-Yue; Zhang, Tao; Gao, Chang-Yue; et al. (J Alzheimers Dis, 2017)
Previous studies have suggested that cardiovascular functions might play a critical role in Alzheimer's disease (AD) pathogenesis. However, the relationship among heart function, blood flow of cerebral vessels, and AD remains unclear. In the present study, AD patients (n = 34) and age- and gender-matched cognitively normal controls (n = 34) were recruited. Comorbidity information was collected. The ejection fraction was measured using echocardiography, and the mean velocity, pulsatility index (PI), and resistance index (RI) of the basilar artery (BA), left terminal internal carotid artery (LTICA), and right terminal internal carotid artery (RTICA) were measured using transcranial Doppler. The lacunae, white matter changes, and plaque in the aortic arch and carotid arteries were collected from brain magnetic resonance imaging and computed tomography angiography images. Compared with normal controls, AD patients had lower ejection fractions and cerebral blood flow velocities and a higher RI and PI in the BA, LTICA, and RTICA, as well as more plaques in the aortic and carotid arteries. In the multivariate logistic regression analysis, the ejection fraction and the mean velocity of the BA and LTICA were independently associated with AD after adjusting for age, gender, education, vascular risk factors, arterial plaques, and brain ischemic lesions detected in the brain images. These findings suggest that heart function and vascular condition may play important roles in AD pathogenesis. Improving cardiovascular functions could be a promising approach for the prevention and treatment of AD.

Reduced Cerebrospinal Fluid Concentration of Apolipoprotein A-I in Patients with Alzheimer's Disease. - Johansson, Per; Almqvist, Erik G; Bjerke, Maria; Wallin, Anders; Johansson, Jan-Ove; Andreasson, Ulf; Blennow, Kaj; Zetterberg, Henrik; Svensson, Johan (J Alzheimers Dis, 2017)
BACKGROUND: Apolipoprotein E (ApoE) has been extensively studied in Alzheimer's disease (AD), but little is known of apolipoprotein A-I (ApoA-I) in cerebrospinal fluid (CSF). OBJECTIVE: Plasma lipids as well as ApoA-I and ApoE in plasma and CSF were determined and related to Mini-Mental State Examination (MMSE) score, APOE genotype, and CSF AD biomarkers. METHODS: Consecutive patients with AD (n = 29), stable mild cognitive impairment (n = 13), other dementias (n = 14), and healthy controls (n = 18) were included at a single center. RESULTS: AD patients had higher plasma triglycerides and lower CSF ApoA-I concentration than controls (both p < 0.05). CSF ApoE concentration was reduced in other dementias (p < 0.01). In AD as well as other dementias, the ratios between CSF and plasma concentrations of both ApoA-I and ApoE were lower than those in the controls. ApoA-I and ApoE in plasma and CSF were not influenced by APOEɛ4 allele distribution. In the total study population (n = 74), CSF ApoA-I correlated positively with MMSE score (r = 0.26, p < 0.05) and negatively with CSF P-tau (r = -0.25, p < 0.05). CSF ApoE correlated positively with CSF concentrations of T-tau and P-tau in the total study population and in AD patients. CONCLUSION: CSF ApoA-I was reduced in AD patients and associated with measures of cognitive function and AD disease status. The mechanisms underlying the decreased CSF:plasma ratios of ApoA-I and ApoE in AD and other dementias need to be explored in further studies.

Reduction of RPT6/S8 (a Proteasome Component) and Proteasome Activity in the Cortex is associated with Cognitive Impairment in Lewy Body Dementia. - Alghamdi, Amani; Vallortigara, Julie; Howlett, David R; Broadstock, Martin; Hortobágyi, Tibor; Ballard, Clive; Thomas, Alan J; O'Brien, John T; Aarsland, Dag; Attems, Johannes; Francis, Paul T; Whitfield, David R (J Alzheimers Dis, 2017)
Lewy body dementia is the second most common neurodegenerative dementia and is pathologically characterized by α-synuclein positive cytoplasmic inclusions, with varying amounts of amyloid-β (Aβ) and hyperphosphorylated tau (tau) aggregates in addition to synaptic loss. A dysfunctional ubiquitin proteasome system (UPS), the major proteolytic pathway responsible for the clearance of short lived proteins, may be a mediating factor of disease progression and of the development of α-synuclein aggregates. In the present study, protein expression of a key component of the UPS, the RPT6 subunit of the 19S regulatory complex was determined. Furthermore, the main proteolytic-like (chymotrypsin- and PGPH-) activities have also been analyzed. The middle frontal (Brodmann, BA9), inferior parietal (BA40), and anterior cingulate (BA24) gyrus' cortex were selected as regions of interest from Parkinson's disease dementia (PDD, n = 31), dementia with Lewy bodies (DLB, n = 44), Alzheimer's disease (AD, n = 16), and control (n = 24) brains. Clinical and pathological data available included the MMSE score. DLB, PDD, and AD were characterized by significant reductions of RPT6 (one-way ANOVA, p < 0.001; Bonferroni post hoc test) in prefrontal cortex and parietal cortex compared with controls. Strong associations were observed between RPT6 levels in prefrontal, parietal cortex, and anterior cingulate gyrus and cognitive impairment (p = 0.001, p = 0.001, and p = 0.008, respectively). These findings highlight the involvement of the UPS in Lewy body dementia and indicate that targeting the UPS may have the potential to slow down or reduce the progression of cognitive impairment in DLB and PDD.

Relation of Odor Identification with Alzheimer's Disease Markers in Cerebrospinal Fluid and Cognition. - Reijs, Babette L R; Ramakers, Inez H G B; Elias-Sonnenschein, Lyzel; Teunissen, Charlotte E; Koel-Simmelink, Marleen; Tsolaki, Magda; Wahlund, Lars-Olof; Waldemar, Gunhild; Hausner, Lucrezia; Johannsen, Peter; Vanderstichele, Hugo; Verhey, Frans; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Impaired olfactory function is an early characteristic of Alzheimer's disease (AD), but it remains unclear if odor identification also relates to early markers of AD in cerebrospinal fluid (CSF). OBJECTIVE: To investigate the association between odor identification and amyloid-β 1-42 (Aβ42) and total tau (t-tau) concentrations in CSF. In addition, to examine the relation between odor identification and cognitive function at baseline and at follow-up, and whether these associations are moderated by CSF Aβ42 and t-tau and apolipoprotein E (APOE) genotype. METHODS: We included 160 individuals (40 with normal cognition, 45 with mild cognitive impairment (MCI), 42 with AD-type dementia, and 26 individuals with non-AD dementia) from the EDAR study. Individuals were recruited from six memory clinics across Europe. Odor identification was tested with the brief University of Pennsylvania Smell Identification Test. CSF Aβ42 and t-tau were assessed with INNO-BIA AlzBio3 Luminex assay. Neuropsychological assessment included tests for verbal memory, verbal fluency, attention, executive function, and visuoconstruction. Follow-up was performed within 3 years after baseline. RESULTS: Lower odor identification scores correlated with increased CSF t-tau concentrations and with lower scores on all cognitive measures at baseline independent of diagnostic group. Lower odor identification scores predicted decline on the MMSE in the total group, and decline on wordlist learning and delayed recall in APOE ɛ4 carriers and in individuals with abnormal Aβ42. CONCLUSION: Odor identification impairment may be an indicator of neuronal injury rather than amyloid pathology.

Role of Glutamate and NMDA Receptors in Alzheimer's Disease. - Wang, Rui; Reddy, P Hemachandra (J Alzheimers Dis, 2017)
Excitatory glutamatergic neurotransmission via N-methyl-d-aspartate receptor (NMDAR) is critical for synaptic plasticity and survival of neurons. However, excessive NMDAR activity causes excitotoxicity and promotes cell death, underlying a potential mechanism of neurodegeneration occurred in Alzheimer's disease (AD). Studies indicate that the distinct outcomes of NMDAR-mediated responses are induced by regionalized receptor activities, followed by different downstream signaling pathways. The activation of synaptic NMDARs initiates plasticity and stimulates cell survival. In contrast, the activation of extrasynaptic NMDARs promotes cell death and thus contributes to the etiology of AD, which can be blocked by an AD drug, memantine, an NMDAR antagonist that selectively blocks the function of extrasynaptic NMDARs.

Screening for Alzheimer's Disease: Cognitive Impairment in Self-Referred and Memory Clinic-Referred Patients. - Kirsebom, Bjørn-Eivind; Espenes, Ragna; Waterloo, Knut; Hessen, Erik; Johnsen, Stein Harald; Bråthen, Geir; Aarsland, Dag; Fladby, Tormod (J Alzheimers Dis, 2017)
BACKGROUND: Cognitive assessment is essential in tracking disease progression in AD. Presently, cohorts including preclinical at-risk participants are recruited by different means, which may bias cognitive and clinical features. We compared recruitment strategies to levels of cognitive functioning. OBJECTIVE: We investigate recruitment source biases in self-referred and memory clinic-referred patient cohorts to reveal potential differences in cognitive performance and demographics among at-risk participants. METHODS: We included 431 participants 40-80 years old. Participants were classified as controls (n = 132) or symptom group (n = 299). The symptom group comprised of subjective cognitive decline (SCD, n = 163) and mild cognitive impairment (MCI, n = 136). We compared cognitive performance and demographics in memory clinic-referrals (n = 86) to self-referred participants responding to advertisements and news bulletins (n = 179). Participants recruited by other means were excluded from analysis (n = 34). RESULTS: At symptom group level, we found significant reductions in cognitive performance in memory clinic-referrals compared to self-referrals. However, here reductions were only found within the MCI group. We found no differences in cognitive performance due to recruitment within the SCD group. The MCI group was significantly impaired compared to controls on all measures. Significant reductions in learning, and executive functions were also found for the SCD group. CONCLUSION: Regardless of recruitment method, both the SCD and MCI groups showed reductions in cognitive performance compared to controls. We found differences in cognitive impairment for memory clinic-referrals compared to self-referrals only within the MCI group, SCD-cases being equally affected irrespective of referral type.

Screening for Mild Cognitive Impairment and Dementia with Automated, Anonymous Online and Telephone Cognitive Self-Tests. - Van Mierlo, Lisa D; Wouters, Hans; Sikkes, Sietske A M; van der Flier, Wiesje M; Prins, Niels D; Bremer, Jonne A E; Koene, Teddy; Van Hout, Hein P J (J Alzheimers Dis, 2017)
BACKGROUND: Many older people worry about cognitive decline. Early cognitive screening in an anonymous and easily accessible manner may reassure older people who are unnecessarily worried about normal cognitive aging while it may also expedite help seeking in case of suspicious cognitive decline. OBJECTIVE: To develop and validate online and telephone-based automated self-tests of cognitive function. METHODS: We examined the feasibility and validity of the self-tests in a prospective study of 117 participants of whom 34 had subjective cognitive decline (SCD), 30 had mild cognitive impairment (MCI), and 53 had dementia. The ability of these self-tests to accurately distinguish MCI and dementia from SCD was examined with ROC curves. Convergent validity was examined by calculating rank correlations between the self-tests and neuropsychological tests. RESULTS: Both the online and telephone cognitive self-tests were feasible, because the majority of participants (86% and 80%, respectively) were able to complete them. The online self-test had adequate diagnostic accuracy in the screening for MCI and dementia versus SCD with an Area under the Curve (AUC) of 0.86 (95% CI: 0.78-0.93). The AUC of the MMSE was 0.82 (95% CI: 0.74-0.89). By contrast, the telephone self-test had lower diagnostic accuracy (AUC = 0.75, 95% CI: 0.64-0.86). Both self-tests had good convergent validity as demonstrated by moderate to strong rank correlations with neuropsychological tests. CONCLUSION: We demonstrated good diagnostic accuracy and convergent validity for the online self-test of cognitive function. It is therefore a promising tool in the screening for MCI and dementia.

Selenomethionine Attenuates the Amyloid-β Level by Both Inhibiting Amyloid-β Production and Modulating Autophagy in Neuron-2a/AβPPswe Cells. - Zhang, Zhong-Hao; Wu, Qiu-Yan; Chen, Chen; Zheng, Rui; Chen, Yao; Liu, Qiong; Ni, Jia-Zuan; Song, Guo-Li (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a complex and progressive neurological disorder, and amyloid-β (Aβ) has been recognized as the major cause of AD. Inhibiting Aβ production and/or enhancing the clearance of Aβ to reduce its levels are still the effective therapeutic strategies pursued in anti-AD research. In previous studies, we have reported that selenomethionine (Se-Met), a major form of selenium in animals and humans with significant antioxidant capacity, can reduce both amyloid-β (Aβ) deposition and tau hyperphosphorylation in a triple transgenic mouse model of AD. In this study, a Se-Met treatment significantly decreased the Aβ levels in Neuron-2a/AβPPswe (N2asw) cells, and the anti-amyloid effect of Se-Met was attributed to its ability to inhibit Aβ generation by suppressing the activity of BACE1. Furthermore, both the LC3-II/LC3-I ratio and the number of LC3-positive puncta were significantly decreased in Se-Met-treated cells, suggesting that Se-Met also promoted Aβ clearance by modulating the autophagy pathway. Subsequently, Se-Met inhibited the initiation of autophagy through the AKT-mTOR-p70S6K signaling pathway and enhanced autophagic turnover by promoting autophagosome-lysosome fusion and autophagic clearance. Our results further highlight the potential therapeutic effects of Se-Met on AD.

Selenoprotein S Reduces Endoplasmic Reticulum Stress-Induced Phosphorylation of Tau: Potential Role in Selenate Mitigation of Tau Pathology. - Rueli, Rachel H L H; Torres, Daniel J; Dewing, Andrea S T; Kiyohara, Arlene C; Barayuga, Stephanie M; Bellinger, Miyoko T; Uyehara-Lock, Jane H; White, Lon R; Moreira, Paula I; Berry, Marla J; Perry, George; Bellinger, Frederick P (J Alzheimers Dis, 2017)
Previous studies demonstrated that selenium in the form of sodium selenate reduces neurofibrillary tangle formation in Alzheimer's disease models. Hyperphosphorylation of tau, which leads to formation of neurofibrillary tangles in Alzheimer's disease, is increased by endoplasmic reticulum (ER) stress. Selenoprotein S (SelS) is part of an ER membrane complex that removes misfolded proteins from the ER as a means to reduce ER stress. Selenate, as with other forms of selenium, will increase selenoprotein expression. We therefore proposed that increased SelS expression by selenate would contribute to the beneficial actions of selenate in Alzheimer's disease. SelS expression increased with ER stress and decreased under conditions of elevated glucose concentrations in the SH-SY5Y neuronal cell line. Reducing expression of SelS with siRNA promoted cell death in response to ER stress. Selenate increased SelS expression, which significantly correlated with decreased tau phosphorylation. Restricting SelS expression during ER stress conditions increased tau phosphorylation, and also promoted aggregation of phosphorylated tau in neurites and soma. In human postmortem brain, SelS expression coincided with neurofibrillary tangles, but not with amyloid-β plaques. These results indicate that selenate can alter phosphorylation of tau by increasing expression of SelS in Alzheimer's disease and potentially other neurodegenerative disorders.

Sex Differences in the Psychophysical Response to Contact Heat in Moderate Cognitive Impairment Alzheimer's Disease: A Cross-Sectional Brief Report. - Cowan, Ronald L; Beach, Paul A; Atalla, Sebastian W; Dietrich, Mary S; Bruehl, Stephen P; Deng, Jie; Wang, Jinjiao; Newhouse, Paul A; Gore, John C; Monroe, Todd B (J Alzheimers Dis, 2017)
BACKGROUND: People with Alzheimer's disease (AD) report pain less frequently and receive less pain medication than people without AD. Recent studies have begun to elucidate how pain may be altered in those with AD. However, potential sex differences in pain responsiveness have never been explored in these patients. It is unclear whether sex differences found in prior studies of healthy young and older individuals extend to people with AD. OBJECTIVE: The purpose of this study was to examine sex differences in the psychophysical response to experimental thermal pain in people with AD. METHODS: Cross-sectional analysis of 14 male and 14 female age-matched (≥65 years of age, median = 74) and AD severity-matched (Mini-Mental State Exam score <24, median = 16) communicative people who completed thermal psychophysics. RESULTS: There was a statistically significant main effect of sex for both temperature and unpleasantness ratings that persisted after controlling for average and current pain (mixed-effects general liner model: temperature: p = 0.004, unpleasantness: p < 0.001). Females reported sensing mild pain and moderate pain percepts at markedly lower temperatures than did males (mild: Cohen's d = 0.72, p = 0.051, moderate: Cohen's d = 0.80, p = 0.036). By contrast, males rated mild and moderate thermal pain stimuli as more unpleasant than did females (mild: Cohen's d = 0.80, p = 0.072, moderate: Cohen's d = 1.32, p = 0.006). There were no statistically significant correlations of temperature with perceived unpleasantness for mild or moderate pain (rs = 0.29 and rs = 0.20 respectively, p > 0.05). CONCLUSIONS: Results suggest experimental pain-related sex differences persist in older adults with AD in a different manner than those previously demonstrated in cognitively intact older adults. These findings could potentially aid in developing targeted pain management approaches in this vulnerable population. Further studies are warranted to replicate the findings from this pilot work.

SH2B1 is Involved in the Accumulation of Amyloid-β42 in Alzheimer's Disease. - Shen, Yijun; Xia, Yiling; Meng, Shiquan; Lim, Nastasia K H; Wang, Wenan; Huang, Fude (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is characterized by deficits in learning and memory abilities, as well as pathological changes of amyloid-β (Aβ) plaque and neurofibrillary tangle formation in the brain. Insulin has been identified as a modulator of the neuronal pathways involved in learning and memory, and is also implicated as a modulator of Aβ and tau metabolism. Disrupted insulin signaling pathways are evident in AD patients and it is understood that type 2 diabetes can increase the risk of developing AD, suggesting a possible link between metabolic disorders and neurodegeneration. SH2B1 is a key protein in the insulin signaling pathway involved in regulating the activity of the insulin receptor. To further identify the role of the insulin signaling pathway in the pathology of AD, SH2B (dSH2B homologue in flies) in neurons was partially knocked out or overexpressed in an AD Drosophila model expressing Aβ42. Partial knockout of neuronal SH2B in the Aβ42-expressing Drosophila had a detrimental effect on mobility and neurotransmission, and increased levels and intraneuronal accumulation of Aβ42, as assessed by ELISA and immunostaining. Alternatively, partial overexpression of neuronal SH2B in the Aβ42-expressing Drosophila improved lifespan, mobility, and neurotransmission, as well as decreased levels and intraneuronal accumulation of Aβ42. Thus, SH2B1 may be an upstream modulator of Aβ metabolism, acting to inhibit Aβ accumulation, and has a role in the pathogenesis of AD. SH2B1 may therefore have potential as a therapeutic target for this common form of dementia.

Sildenafil Improves Vascular and Metabolic Function in Patients with Alzheimer's Disease. - Sheng, Min; Lu, Hanzhang; Liu, Peiying; Li, Yang; Ravi, Harshan; Peng, Shin-Lei; Diaz-Arrastia, Ramon; Devous, Michael D; Womack, Kyle B (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) is the leading cause of degenerative dementia in the aging population. Patients with AD have alterations in cerebral hemodynamic function including reduced cerebral blood flow (CBF) and cerebral metabolic rate. Therefore, improved cerebrovascular function may be an attractive goal for pharmaceutical intervention in AD. OBJECTIVE: We wished to observe the acute effects of sildenafil on cerebrovascular function and brain metabolism in patients with AD. METHODS: We used several novel non-invasive MRI techniques to investigate the alterations of CBF, cerebral metabolic rate of oxygen (CMRO2), and cerebrovascular reactivity (CVR) after a single dose of sildenafil administration in order to assess its physiological effects in patients with AD. CBF, CMRO2, and CVR measurements using MRI were performed before and one hour after the oral administration of 50 mg sildenafil. Baseline Montreal Cognitive Assessment score was also obtained. RESULTS: Complete CBF and CMRO2 data were obtained in twelve patients. Complete CVR data were obtained in eight patients. Global CBF and CMRO2 significantly increased (p = 0.03, p = 0.05, respectively) following sildenafil administration. Voxel-wise analyses of CBF maps showed that increased CBF was most pronounced in the bilateral medial temporal lobes. CVR significantly decreased after administration of sildenafil. CONCLUSION: Our data suggest that a single dose of sildenafil improves cerebral hemodynamic function and increases cerebral oxygen metabolism in patients with AD.

Sleep Deprivation Induced Plasma Amyloid-β Transport Disturbance in Healthy Young Adults. - Wei, Meng; Zhao, Beiyu; Huo, Kang; Deng, Yongning; Shang, Suhang; Liu, Jie; Li, Yanbo; Ma, Louyan; Jiang, Yu; Dang, Liangjun; Chen, Chen; Wei, Shan; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Sleep is an important physiological process and beneficial in the removal of brain metabolites and functional recovery. Prior studies have shown that sleep disorders are significant risk factors for Alzheimer's disease (AD). OBJECTIVE: The present study was designed to characterize the effect of short-term total sleep deprivation (TSD) on plasma amyloid-β (Aβ) concentrations. METHODS: A clinical trial was conducted between March 1, 2016, and April 1, 2016. Twenty volunteers (age 27.3±3.4 years) with normal cognitive function and sleeping habits were recruited from the local population. Participants underwent 24 h of TSD. Periprocedural blood samples were collected to compare the changes of plasma Aβ42, Aβ40, low-density lipoprotein receptor-related protein (sLRP-1), soluble receptors for advanced glycation end products (sRAGE), and serum superoxide dismutase (SOD) and malonaldehyde (MDA). RESULTS: TSD increased morning plasma Aβ40 levels by 32.6% (p < 0.001) and decreased the Aβ42/Aβ40 ratio by 19.3% (p < 0.001). A positive relationship was found between TSD duration and plasma Aβ40 level (r = 0.51, p < 0.001) and Aβ40/Aβ42 ratio (r = 0.25, p = 0.003). Plasma concentrations of sLRP1 (p = 0.018) and sRAGE (p = 0.001) decreased significantly after TSD. Aβ40 and Aβ42 plasma concentrations correlated with plasma levels of sLRP1 and sRAGE. Serum SOD decreased after TSD (p = 0.005), whereas serum MDA was increased (p = 0.001). CONCLUSION: Sleep deprivation can lead to an elevation of plasma Aβ40 and decrease of the Aβ42/Aβ40 ratio. The underlying mechanisms may be related to increased oxidative stress and impaired peripheral Aβ clearance as pathomechanisms of AD.
Keywords: Adult; Amyloid beta-Peptides; Female; Humans; Low Density Lipoprotein Receptor-Related Protein-1; Male; Malondialdehyde; Peptide Fragments; Receptor for Advanced Glycation End Products; Sleep Deprivation; Superoxide Dismutase; Time Factors; Young Adult

Smoking, APOE Genotype, and Cognitive Decline: The Rotterdam Study. - Wingbermühle, Robin; Wen, Ke-Xin; Wolters, Frank J; Ikram, M Arfan; Bos, Daniel (J Alzheimers Dis, 2017)
The association of smoking with preclinical cognitive decline remains unclear and may be modified by the APOEɛ4 genotype. In 5,705 participants (mean age: 63.9±9.1 years; 57.4% women) from the population-based Rotterdam Study, we investigated the relationship between smoking and cognitive decline over a 5.5-year period and examined potential effect modification by APOEɛ4 genotype. We found that current smoking was related to decline in global cognition [difference compared to never smoking: -0.06 (95% C.I.-0.10;-0.01)], as well as decline on specific cognitive tests including the Letter Digit Substitution Task, the 15-Word Learning Test, and the Purdue Pegboard. We found no evidence for effect modification by APOEɛ4 genotype on this relation.

Sphingolipid-Enriched Extracellular Vesicles and Alzheimer's Disease: A Decade of Research. - Dinkins, Michael B; Wang, Guanghu; Bieberich, Erhard (J Alzheimers Dis, 2017)
Extracellular vesicles (EVs), particularly exosomes, have emerged in the last 10 years as a new player in the progression of Alzheimer's disease (AD) with high potential for being useful as a diagnostic and treatment tool. Exosomes and other EVs are enriched with the sphingolipid ceramide as well as other more complex glycosphingolipids such as gangliosides. At least a subpopulation of exosomes requires neutral sphingomyelinase activity for their biogenesis and secretion. As ceramide is often elevated in AD, exosome secretion may be affected as well. Here, we review the available data showing that exosomes regulate the aggregation and clearance of amyloid-beta (Aβ) and discuss the differences in data from laboratories regarding Aβ binding, induction of aggregation, and glial clearance. We also summarize available data on the role of exosomes in extracellular tau propagation, AD-related exosomal mRNA/miRNA cargo, and the use of exosomes as biomarker and gene therapy vehicles for diagnosis and potential treatment.

Sporadic Cases with Novel Mutations and Pedigree in Hereditary Leukoencephalopathy with Axonal Spheroids. - Wu, Liyong; Liu, Jia; Sha, Longze; Wang, Xianling; Li, Jieying; Dong, Jing; Jia, Jianping (J Alzheimers Dis, 2017)
Hereditary diffuse leukoencephalopathy with spheroids (HDLS) is an autosomal dominant hereditary disease, featured by cerebral white matter degeneration with demyelination and axonal spheroids. We collected three gene-confirmed HDLS cases in our neurodegenerative clinic. Two HDLS cases were sporadic with novel mutations, while another case had a family history with previously described mutations. All three cases suffered memory problems with white matter lesions and pyramid signs. No obvious clinical differences were observed between sporadic and familial HDLS cases. Distinct features, such as subcortical calcification in brain computed tomography and asymmetric abnormal MRI signal along the pyramid tracts throughout brainstem and spinal cord (cervical, thoracic, and lumbar segments), were observed in one sporadic case with novel mutation. Therefore, the interactions of genotype-phenotype still need to be further investigated.

Synthesis, Radiosynthesis, and Preliminary in vitro and in vivo Evaluation of the Fluorinated Ceramide Trafficking Inhibitor (HPA-12) for Brain Applications. - Crivelli, Simone M; Paulus, Andreas; Markus, Jozef; Bauwens, Matthias; Berkes, Dusan; De Vries, Helga E; Mulder, Monique T; Walter, Jochen; Mottaghy, Felix M; Losen, Mario; Martinez-Martinez, Pilar (J Alzheimers Dis, 2017)
Ceramide levels are increased in blood and brain tissue of Alzheimer's disease (AD) patients. Since the ceramide transporter protein (CERT) is the only known protein able to mediate non-vesicular transfer of ceramide between organelle membranes, the modulation of CERT function may impact on ceramide accumulation. The competitive CERT inhibitor N-(3-hydroxy-1-hydroxymethyl-3-phenylpropyl) dodecanamide (HPA-12) interferes with ceramide trafficking. To understand the role of ceramide/CERT in AD, HPA-12 can be a useful tool to modulate ceramide trafficking. Here we first report the synthesis and in vitro properties of HPA-12 radiolabeled with fluorine-18 and present preliminary in vitro and in vivo positron emission tomography (PET) imaging and biodistribution data. In vitro results demonstrated that the fluorination did not alter the biological properties of HPA-12 since the [fluorine-19]HPA-12, interferes with 5-DMB-ceramide trafficking in HeLa cells. Radiolabeled HPA-12, [fluorine-18]HPA-12, was obtained with a radiochemical yield of 90% and a specific activity of 73 MBq/μmol. PET imaging on wild-type mice showed hepatobiliary clearance and a brain uptake on the order of 0.3 standard uptake value (SUV) one hour post injection. Furthermore, the biodistribution data showed that after removal of the blood by intracardial perfusion, radioactivity was still measurable in the brain demonstrating that the [fluorine-18]HPA-12 crosses the blood brain barrier and is retained in the brain.

Tai Chi Chuan and Baduanjin Increase Grey Matter Volume in Older Adults: A Brain Imaging Study. - Tao, Jing; Liu, Jiao; Liu, Weilin; Huang, Jia; Xue, Xiehua; Chen, Xiangli; Wu, Jinsong; Zheng, Guohua; Chen, Bai; Li, Ming; Sun, Sharon; Jorgenson, Kristen; et al. (J Alzheimers Dis, 2017)
The aim of this study is to investigate and compare how 12-weeks of Tai Chi Chuan and Baduanjin exercise can modulate brain structure and memory function in older adults. Magnetic resonance imaging and memory function measurements (Wechsler Memory Scale-Chinese revised, WMS-CR) were applied at both the beginning and end of the study. Results showed that both Tai Chi Chuan and Baduanjin could significantly increase grey matter volume (GMV) in the insula, medial temporal lobe, and putamen after 12-weeks of exercise. No significant differences were observed in GMV between the Tai Chi Chuan and Baduanjin groups. We also found that compared to healthy controls, Tai Chi Chuan and Baduanjin significantly improved visual reproduction subscores on the WMS-CR. Baduanjin also improved mental control, recognition, touch, and comprehension memory subscores of the WMS-CR compared to the control group. Memory quotient and visual reproduction subscores were both associated with GMV increases in the putamen and hippocampus. Our results demonstrate the potential of Tai Chi Chuan and Baduanjin exercise for the prevention of memory deficits in older adults.

Tailored and Adaptive Computerized Cognitive Training in Older Adults at Risk for Dementia: A Randomized Controlled Trial. - Bahar-Fuchs, Alex; Webb, Shannon; Bartsch, Lauren; Clare, Linda; Rebok, George; Cherbuin, Nicolas; Anstey, Kaarin J (J Alzheimers Dis, 2017)
BACKGROUND: Computerized Cognitive Training (CCT) has been shown to improve cognitive function in older adults with mild cognitive impairment (MCI) or mood-related neuropsychiatric symptoms (MrNPS), but many questions remain unresolved. OBJECTIVE: To evaluate the extent to which CCT benefits older adults with both MCI and MrNPS, and its effects on meta-cognitive and non-cognitive outcomes, as well as establish whether adapting difficulty levels and tailoring to individuals' profile is superior to generic training. METHODS: Older adults with MCI (n = 9), MrNPS (n = 11), or both (MCI+, n = 25) were randomized into a home-based individually-tailored and adaptive CCT (n = 21) or an active control condition (AC; n = 23) in a double-blind design. Interventions lasted 8-12 weeks and outcomes were assessed after the intervention, and at a 3-month follow-up. RESULTS: Participants in both conditions reported greater satisfaction with their everyday memory following intervention and at follow-up. However, participants in the CCT condition showed greater improvement on composite measures of memory, learning, and global cognition at follow-up. Participants with MrNPS in the CCT condition were also found to have improved mood at 3-month follow-up and reported using fewer memory strategies at the post-intervention and follow-up assessments. There was no evidence that participants with MCI+ were disadvantaged relative to the other diagnostic conditions. Finally, informant-rated caregiver burden declined at follow-up assessment in the CCT condition relative to the AC condition. CONCLUSIONS: Home-based CCT with adaptive difficulty and personal tailoring appears superior to more generic CCT in relation to both cognitive and non-cognitive outcomes. Mechanisms of treatment effect and future directions are discussed.

Tau Oligomers Associate with Inflammation in the Brain and Retina of Tauopathy Mice and in Neurodegenerative Diseases. - Nilson, Ashley N; English, Kelsey C; Gerson, Julia E; Whittle, T Barton; Crain, C Nicolas; Xue, Judy; Sengupta, Urmi; Castillo-Carranza, Diana L; Zhang, Wenbo; Gupta, Praveena; Kayed, Rakez (J Alzheimers Dis, 2017)
It is well-established that inflammation plays an important role in Alzheimer's disease (AD) and frontotemporal lobar dementia (FTLD). Inflammation and synapse loss occur in disease prior to the formation of larger aggregates, but the contribution of tau to inflammation has not yet been thoroughly investigated. Tau pathologically aggregates to form large fibrillar structures known as tangles. However, evidence suggests that smaller soluble aggregates, called oligomers, are the most toxic species and form prior to tangles. Furthermore, tau oligomers can spread to neighboring cells and between anatomically connected brain regions. In addition, recent evidence suggests that inspecting the retina may be a window to brain pathology. We hypothesized that there is a relationship between tau oligomers and inflammation, which are hallmarks of early disease. We conducted immunofluorescence and biochemical analyses on tauopathy mice, FTLD, and AD subjects. We showed that oligomers co-localize with astrocytes, microglia, and HMGB1, a pro-inflammatory cytokine. Additionally, we show that tau oligomers are present in the retina and are associated with inflammatory cells suggesting that the retina may be a valid non-invasive biomarker for brain pathology. These results suggest that there may be a toxic relationship between tau oligomers and inflammation. Therefore, the ability of tau oligomers to spread may initiate a feed-forward cycle in which tau oligomers induce inflammation, leading to neuronal damage, and thus more inflammation. Further mechanistic studies are warranted in order to understand this relationship, which may have critical implications for improving the treatment of tauopathies.

Tau Pathology Promotes the Reorganization of the Extracellular Matrix and Inhibits the Formation of Perineuronal Nets by Regulating the Expression and the Distribution of Hyaluronic Acid Synthases. - Li, Yin; Li, Ze-Xu; Jin, Tan; Wang, Zhan-You; Zhao, Pu (J Alzheimers Dis, 2017)
Hyaluronic acid (HA) is the backbone of the extracellular matrix (ECM) and provides biochemical and physical support to aggrecan-based perineuronal nets (PNNs), which are associated with the selective vulnerability of neurons in Alzheimer's disease (AD). Here, we showed that HA synthases (HASs), including Has1, Has2, and Has3, were widely expressed in murine central nervous system. All types of HASs were localized to cell bodies of neurons; only Has1 existed in the membranes of neural axons. By using TauP301S transgenic (Tg) mouse model, we found that the axonal-localization of Has1 was abolished in TauP301S overexpressed mouse brain, and the redistribution of Has1 was also observed in human AD brains, suggesting that the localization of Has1 is dependent on intact microtubules which are regulated partially by the phosphorylation and dephosphorylation cycles of tau proteins. Furthermore, Has1 was reduced and Has3 was increased in TauP301S Tg mouse brain, resulting in the upregulation of shorter-chain HA in the ECM. These findings suggest that by abolishing the axonal-localization of Has1 and promoting the expression of Has3 and the synthesis of shorter-chain HA, the tau pathology breaks the balance of ECM components, promotes the reorganization of the ECM, and inhibits the formation of PNNs in the hippocampus, and then regulates neuronal plasticity during the progression of AD.

TMEM230 Accumulation in Granulovacuolar Degeneration Bodies and Dystrophic Neurites of Alzheimer's Disease. - Siedlak, Sandra L; Jiang, Yinfei; Huntley, Mikayla L; Wang, Luwen; Gao, Ju; Xie, Fei; Liu, Jingyi; Su, Bo; Perry, George; Wang, Xinglong (J Alzheimers Dis, 2017)
Transmembrane Protein 230 (TMEM230) is a newly identified protein associated with Parkinson's disease (PD) found in Lewy bodies and Lewy neurites of patients with PD or dementia with Lewy body disease. However, TMEM230 has not yet been investigated in the most common neurodegenerative disorder, Alzheimer's disease (AD). Here, we demonstrate that the expression of TMEM230 is specifically increased in neurons in AD patients. Importantly, both granulovacuolar degeneration (GVD) and dystrophic neurites (DNs), two prominent characteristic pathological structures associated with AD, contain TMEM230 aggregates. TMEM230 immunoreactivity can be detected in neurofibrillary tangles-containing neurons and hyperphosphorylated tau positive DNs. TMEM230 accumulation is also noted around senile plaques. These findings identifying TMEM230 as a component of GVD and DNs suggest TMEM230 dysregulation as a likely mechanism playing an important role in the pathogenesis of AD.

Toward the Automation of Diagnostic Conversation Analysis in Patients with Memory Complaints. - Mirheidari, Bahman; Blackburn, Daniel; Harkness, Kirsty; Walker, Traci; Venneri, Annalena; Reuber, Markus; Christensen, Heidi (J Alzheimers Dis, 2017)
BACKGROUND: The early diagnosis of dementia is of great clinical and social importance. A recent study using the qualitative methodology of conversation analysis (CA) demonstrated that language and communication problems are evident during interactions between patients and neurologists, and that interactional observations can be used to differentiate between cognitive difficulties due to neurodegenerative disorders (ND) or functional memory disorders (FMD). OBJECTIVE: This study explores whether the differential diagnostic analysis of doctor-patient interactions in a memory clinic can be automated. METHODS: Verbatim transcripts of conversations between neurologists and patients initially presenting with memory problems to a specialist clinic were produced manually (15 with FMD, and 15 with ND). A range of automatically detectable features focusing on acoustic, lexical, semantic, and visual information contained in the transcripts were defined aiming to replicate the diagnostic qualitative observations. The features were used to train a set of five machine learning classifiers to distinguish between ND and FMD. RESULTS: The mean rate of correct classification between ND and FMD was 93% ranging from 97% by the Perceptron classifier to 90% by the Random Forest classifier.Using only the ten best features, the mean correct classification score increased to 95%. CONCLUSION: This pilot study provides proof-of-principle that a machine learning approach to analyzing transcripts of interactions between neurologists and patients describing memory problems can distinguish people with neurodegenerative dementia from people with FMD.

Treadmill Exercise Exerts Neuroprotection and Regulates Microglial Polarization and Oxidative Stress in a Streptozotocin-Induced Rat Model of Sporadic Alzheimer's Disease. - Lu, Yujiao; Dong, Yan; Tucker, Donovan; Wang, Ruimin; Ahmed, Mohammad Ejaz; Brann, Darrell; Zhang, Quanguang (J Alzheimers Dis, 2017)
Recent work has suggested that exercise may be beneficial in preventing or ameliorating symptoms of several neurological disorders, although the mechanism is not entirely understood. The current study was designed to examine the potential beneficial effect of treadmill exercise upon cognitive function in a streptozotocin (STZ)-induced rat model of Alzheimer's disease (AD). Animals underwent treadmill exercise (30 min/day, 5 days/week) for 4 weeks after bilateral STZ intracerebroventricular injection (2.4 mg/kg). We demonstrated that treadmill exercise significantly attenuated STZ-induced neurodegeneration in the rat hippocampal CA1 region and strongly preserved hippocampal-dependent cognitive functioning. Further mechanistic investigation displayed a marked suppression of STZ-induced amyloid-β accumulation and tau phosphorylation. Intriguingly, treadmill exercise remarkably inhibited reactive gliosis following STZ insult and effectively shifted activated microglia from a pro-inflammatory M1 to an anti-inflammatory M2 phenotype, which was correlated with a significantly reduced expression of pro-inflammatory mediators and a corresponding enhancement of anti-inflammatory cytokine expression in the hippocampus. Furthermore, treadmill exercise caused a robust suppression of oxidative damage as evidenced by significantly reduced peroxynitrite production, lipid peroxidation, and oxidized DNA damage. Finally, treadmill exercise strongly attenuated STZ-induced mitochondrial dysfunction manifested by a dramatically elevated intra-mitochondrial cytochrome c oxidase activity and ATP synthesis, and markedly inhibited neuronal apoptosis in the hippocampus. These findings demonstrate that treadmill exercise has a multifactorial effect to attenuate many of the pathological processes that play a key role in AD, and provide further support for the beneficial role of exercise as a potential therapeutic option in AD treatment.

Urine AD7c-NTP Predicts Amyloid Deposition and Symptom of Agitation in Patients with Alzheimer's Disease and Mild Cognitive Impairment. - Zhang, Nan; Zhang, Liling; Li, Yan; Gordon, Marc L; Cai, Li; Wang, Ying; Xing, Mengya; Cheng, Yan (J Alzheimers Dis, 2017)
BACKGROUND: Expression of neuronal thread protein (NTP), which is considered to be related to neuritic sprouting and neuronal death, may be elevated in brain tissue, cerebrospinal fluid, and even urine in patients with Alzheimer's disease (AD). OBJECTIVE: In this study, we analyzed the correlation between urine AD-associated NTP (AD7c-NTP) level, and amyloid-β (Aβ) deposition, and clinical symptoms in AD and mild cognitive impairment (MCI). METHODS: Twenty-two patients with mild to moderate AD and 8 subjects with MCI were recruited. Aβ deposition was measured with [11C]-labeled Pittsburgh compound B (PiB)-positron emission tomography (PET) in all participants. Urine AD7c-NTP levels were measured using enzyme-linked immunosorbent assay. Mini-Mental State Examination (MMSE) and Neuropsychiatric Inventory (NPI) were used to evaluate cognitive function and behavioral psychological symptoms, respectively. RESULTS: Fourteen (63.6%) of AD patients and 2 (25.0%) of MCI subjects were Aβ positive on PiB-PET. There was a significant difference in urine AD7c-NTP level between Aβ positive (2.27±2.22 ng/ml) and negative (0.55±0.60 ng/ml) subjects (p = 0.018). Using 1.46 ng/ml as a cut-off value, 68.8% of Aβ positive subjects showed elevated urine AD7c-NTP level, and 92.9% of Aβ negative subjects showed normal urine AD7c-NTP level. There were no relationships between urine AD7c-NTP level and MMSE and total NPI scores. However, AD7c-NTP level positively correlated with agitation score on NPI. CONCLUSIONS: Urine AD7c-NTP had high specificity and moderate sensitivity in predicting Aβ deposition among patients with cognitive impairment. Furthermore, urine AD7c-NTP level strongly correlated with the symptom of agitation.

Urine Formaldehyde Predicts Cognitive Impairment in Post-Stroke Dementia and Alzheimer's Disease. - Tong, Zhiqian; Wang, Weishan; Luo, Wenhong; Lv, Jihui; Li, Hui; Luo, Hongjun; Jia, Jianping; He, Rongqiao (J Alzheimers Dis, 2017)
Although Alzheimer's disease (AD) was first described over 100 years ago, there is still no suitable biomarker for diagnosing AD in easily collectable samples (e.g., blood plasma, saliva, and urine). Here, we investigated the relationship between morning urine formaldehyde concentration and cognitive impairment in patients with post-stroke dementia (PSD) or AD in this cross-sectional survey for 7 years. Cognitive abilities of the study participants (n = 577, four groups: 231 controls, 61 stroke, 65 PSD, and 220 AD) were assessed by Mini-Mental State Examination (MMSE). Morning urine formaldehyde concentrations were measured by high performance liquid chromatography (HPLC). Gender- and age-matched participants were selected from the four groups (n = 42 in each group). Both semicarbazide-sensitive amine oxidase (SSAO, a formaldehyde-generating enzyme) and formaldehyde levels in the blood and urine were analyzed by using an enzyme-linked immunosorbent assay (ELISA) and HPLC, respectively. We found that morning urine formaldehyde levels were inversely correlated with MMSE scores. The threshold value (the best Cut-Off value) of formaldehyde concentration for predicting cognitive impairment was 0.0418 mM in patients with PSD (Sensitivity: 92.3%; Specificity: 77.1%), and 0.0449 mM in patients with AD (Sensitivity: 94.1%; Specificity: 81.8%), respectively. The results of biochemical analysis revealed that the observed increase in urine formaldehyde resulted from an overexpression of SSAO in the blood. The findings suggest that measuring the concentration of formaldehyde in overnight fasting urine could be used as a potentially noninvasive method for evaluating the likelihood of ensuing cognitive impairment or dementia.

Use of Analgesics (Opioids and Nonsteroidal Anti-Inflammatory Drugs) and Dementia-Related Neuropathology in a Community-Based Autopsy Cohort. - Dublin, Sascha; Walker, Rod L; Gray, Shelly L; Hubbard, Rebecca A; Anderson, Melissa L; Yu, Onchee; Montine, Thomas J; Crane, Paul K; Sonnen, Josh A; Larson, Eric B (J Alzheimers Dis, 2017)
BACKGROUND: Opioids may influence the development of Alzheimer's disease (AD). Some studies have observed AD pathology in the brains of opioid abusers. No study has examined the association between prescription opioid use and dementia-related neuropathologic changes. OBJECTIVE: To examine the relationship between prescription opioid or NSAID use and dementia-related neuropathologic changes. METHODS: Within a community-based autopsy cohort (N = 420), we ascertained opioid and nonsteroidal anti-inflammatory drug (NSAID) use over a 10-year period from automated pharmacy data and calculated total standardized daily doses (TSDDs). A neuropathologist assessed outcomes including neuritic plaques, neurofibrillary tangles, and macroscopic infarcts. Outcome measures were dichotomized using established cutpoints. We used modified Poisson regression to calculate adjusted relative risks (RR) and 95% confidence intervals (CI), accounting for participant characteristics and using weighting to account for possible selection bias related to selection into the autopsy sample. RESULTS: Heavier opioid exposure was not associated with greater neuropathologic changes. For neuritic plaques, the adjusted RR [95% CI] was 0.99 [0.64-1.47] for 91+ TSDDs of opioids versus little to no use, and for neurofibrillary tangles, 0.97 [0.49-1.78]. People with heavy NSAID use had higher risk of neuritic plaques (RR 1.39 [1.01-1.89]) than those with little to no use, as we have previously reported. Neither opioid nor NSAID use was associated with higher risk of macroscopic infarcts or with Lewy body disease. CONCLUSION: Prescription opioid use is not associated with dementia-related neuropathologic changes, but heavy NSAID use may be. More research is needed examining chronic pain, its pharmacologic treatments, and neuropathologic changes.

Varying Degrees of Temporoparietal Hypometabolism on FDG-PET Reveal Amyloid-Positive Logopenic Primary Progressive Aphasia is not a Homogeneous Clinical Entity. - Krishnan, Kamini; Machulda, Mary M; Whitwell, Jennifer L; Butts, Alissa M; Duffy, Joseph R; Strand, Edythe A; Senjem, Matthew L; Spychalla, Anthony J; Jack, Clifford R; Lowe, Val J; Josephs, Keith A (J Alzheimers Dis, 2017)
BACKGROUND: The logopenic variant of primary progressive aphasia (lvPPA) manifests due to a breakdown of the language network with prominent hypometabolism of the left temporoparietal region. LvPPA is strongly associated with amyloid deposition, yet there is question as to whether it is a homogeneous clinical entity. OBJECTIVE: This study investigated whether differences in temporoparietal metabolic patterns on 18F fludeoxyglucose positron emission tomography (FDG-PET) could elucidate brain regions preferentially affected in lvPPA. METHOD: We used differences in FDG-PET metabolic z-scores relative to controls for means of left lateral temporal, left inferior parietal, and left superior parietal regions to classify 53 amyloid-positive lvPPA patients into temporal, parietal, or temporoparietal predominate groups. Clinical features and FDG-PET regions of hypometabolism outside of the temporoparietal region were then compared across the three groups; the latter using statistical parametric mapping. RESULTS: Of the 53 lvPPA patients, 15 were classified as temporal, 14 as temporoparietal, and 22 as parietal predominate. There were no significant differences between the groups on demographic measures, language evaluation, or apolipoprotein E genotype. Compared to the other two groups, individuals with the parietal predominate pattern had extensive hypometabolism in left frontal lobe and the precuneus. Furthermore, this group had greater behavioral dyscontrol and deficits in executive function, visuospatial skills, visual memory retention, working memory, and cognitive flexibility (Bonferronip < 0.05). CONCLUSIONS: This study demonstrates that there is clinical heterogeneity within amyloid-positive lvPPA. Patients with lvPPA with predominant parietal hypometabolism, unlike those with temporal or temporoparietal predominant hypometabolism, demonstrated widespread cognitive and behavioral changes.

Visual Rating of Posterior Atrophy as a Marker of Progression to Dementia in Mild Cognitive Impairment Patients. - Kim, Hang-Rai; Park, Young Ho; Jang, Jae-Won; Park, So Young; Wang, Min Jeong; Baek, Min Jae; Kim, Beom Joon; Ahn, Soyeon; Kim, SangYun (J Alzheimers Dis, 2017)
BACKGROUND: Although medial temporal atrophy (MTA) is a useful imaging marker of the progression to dementia in mild cognitive impairment (MCI), substantial numbers of MCI patients without MTA still progress to dementia. OBJECTIVE: We investigated whether visual ratings of posterior atrophy (PA) on magnetic resonance imaging show independent predictive value for the progression to dementia in MCI patients. METHODS: This was a retrospective cohort study of elderly patients who visited Seoul National University Bundang Hospital between 2004 and 2012. A total of 148 patients who were initially diagnosed with MCI were followed for up to 3 years (median 22 months) to determine whether they progressed to dementia. We used 4-point and 5-point visual rating scales to assess PA and MTA, respectively. PA and MTA scores were dichotomized into normal (no atrophy) or abnormal (atrophy) in each patient. We performed a Cox regression analysis to examine the hazard ratios (HRs) of PA and MTA for the progression to dementia with adjustment for age, APOEɛ4 allele status, and baseline Mini-Mental State Examination score. RESULTS: Among the study population, 47 patients progressed to dementia. Visual assessment of the MRI scans revealed that 67 patients (45.3%) showed PA, whereas 85 patients (57.3%) showed MTA. The HRs with 95% confidence intervals for PA and MTA were 2.516 (1.244-5.091) and 4.238 (1.680-10.687), respectively. The predictive values of visually assessed PA and MTA remained significant, independent of the covariates. CONCLUSION: Visual assessment of PA has independent predictive value for progression to dementia in MCI patients.

Vitamin D and the Risk of Dementia: The Rotterdam Study. - Licher, Silvan; de Bruijn, Renée F A G; Wolters, Frank J; Zillikens, M Carola; Ikram, M Arfan; Ikram, M Kamran (J Alzheimers Dis, 2017)
BACKGROUND: Vitamin D has gained interest as a potentially modifiable risk factor for dementia because of its putative neuroprotective effects. However, longitudinal studies examining the association between vitamin D and dementia have provided inconsistent results. OBJECTIVE: To determine the relationship of serum vitamin D with prevalent and incident dementia in the general population. METHODS: Within the prospective Rotterdam Study, we measured serum 25-hydroxyvitamin D concentrations between 1997 and 2001 using electrochemiluminescence-immunoassay in 6220 participants 55 years or older. We assessed dementia at baseline and continuously during follow-up until 1 January 2015. We used appropriate regression models to determine the relationship of vitamin D with prevalent and incident dementia, including Alzheimer's disease (AD). We adjusted models for age, sex, and season of blood collection. Additionally, we adjusted for ethnicity, education, cardiovascular risk factors, serum calcium, kidney function, depression, outdoor-activity and APOEɛ4 carriership. RESULTS: At baseline, 127 of 6,220 participants had dementia, of whom 97 had AD. Lower vitamin D concentrations were associated with a non-significantly higher prevalence of dementia (adjusted OR, per SD decrease 1.20, 95% CI 0.95;1.52), but not with AD (adjusted OR: 0.97, 95% CI 0.74;1.29). Among 6,087 non-demented participants with 68,884 person-years of follow-up, 795 participants developed dementia, of whom 641 had AD. Lower vitamin D concentrations were associated with higher risk of dementia (adjusted HR, per SD decrease 1.11, 95% CI 1.02;1.20) and AD (adjusted HR: 1.13, 95% CI 1.03;1.24). CONCLUSION: Lower serum vitamin D concentrations are associated with a higher incidence of dementia.

What Can Quantitative Gait Analysis Tell Us about Dementia and Its Subtypes? A Structured Review. - Mc Ardle, Ríona; Morris, Rosie; Wilson, Joanna; Galna, Brook; Thomas, Alan J; Rochester, Lynn (J Alzheimers Dis, 2017)
Distinguishing dementia subtypes can be difficult due to similarities in clinical presentation. There is increasing interest in discrete gait characteristics as markers to aid diagnostic algorithms in dementia. This structured review explores the differences in quantitative gait characteristics between dementia and healthy controls, and between four dementia subtypes under single-task conditions: Alzheimer's disease (AD), dementia with Lewy bodies and Parkinson's disease dementia, and vascular dementia. Twenty-six papers out of an initial 5,211 were reviewed and interpreted using a validated model of gait. Dementia was associated with gait characteristics grouped by slower pace, impaired rhythm, and increased variability compared to normal aging. Only four studies compared two or more dementia subtypes. People with AD are less impaired in pace, rhythm, and variability domains of gait compared to non-AD dementias. Results demonstrate the potential of gait as a clinical marker to discriminate between dementia subtypes. Larger studies using a more comprehensive battery of gait characteristics and better characterized dementia sub-types are required.

What Drives Country Differences in Cost of Alzheimer's Disease? An Explanation from Resource Use in the GERAS Study. - Reed, Catherine; Happich, Michael; Argimon, Josep Maria; Haro, Josep Maria; Wimo, Anders; Bruno, Giuseppe; Dodel, Richard; Jones, Roy W; Vellas, Bruno; Belger, Mark (J Alzheimers Dis, 2017)
BACKGROUND: Country differences in resource use and costs of Alzheimer's disease (AD) may be driven by differences in health care systems and resource availability. OBJECTIVE: To compare country resource utilization drivers of societal costs for AD dementia over 18 months. METHODS: GERAS is an observational study in France (n = 419), Germany (n = 550), and the UK (n = 526). Resource use of AD patients and caregivers contributing to >1% of total societal costs (year 2010) was assessed for country differences, adjusting for participant characteristics. RESULTS: Mean 18-month societal costs per patient were France €33,339, Germany €38,197, and UK €37,899 (£32,501). Caregiver time spent on basic and instrumental activities of daily living (ADL) contributed the most to societal costs (54% France, 64% Germany, 65% UK). Caregivers in France spent less time on ADL than UK caregivers and missed fewer work days than in other countries. Compared with other countries, patients in France used more community care services overall and were more likely to use home aid. Patients in Germany were least likely to use temporary accommodation or to be institutionalized at 18 months. UK caregivers spent the most time on instrumental ADL, UK patients used fewest outpatient resources, and UK patients/caregivers were most likely to receive financial support. CONCLUSION: Caregiver time on ADL contributed the most to societal costs and differed across countries, possibly due to use of community care services and institutionalization. Other resources had different patterns of use across countries, reflecting country-specific health and social care systems.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Caregivers; Cohort Studies; Cost of Illness; Europe; Female; Health Resources; Humans; International Cooperation; Male; Surveys and Questionnaires

What is the Relationship between Health, Mood, and Mild Cognitive Impairment? - Yates, Jennifer A; Clare, Linda; Woods, Robert T (J Alzheimers Dis, 2017)
Mild cognitive impairment (MCI) often co-exists with mood problems, and both cognitive functioning and mood are known to be linked with health. This study aims to investigate how health, mood, and cognitive impairment interact. Health is often assessed using a single proxy measure, but the use of a range of measures can provide a more informative picture and allows for combination into a comprehensive measure of health. We report an analysis of data from the Cognitive Function and Ageing Study Wales (CFAS Wales, N = 3,173), in which structured interviews with older people captured measures of cognition, mood, and health. Each measure of health was assessed independently in relation to cognition and mood, and then all measures were combined to form a latent health variable and tested using structural equation modeling (SEM). SEM confirmed the association between health and cognition, with depression acting as a mediator. All measures of health were individually associated with levels of anxiety and depression. Participants reporting mood problems were less likely to engage in physical activity and more likely to report poor or fair health, have more comorbid health conditions, use more services, and experience difficulties with instrumental activities of daily living. Perceived health was associated with cognitive status; participants with MCI were more likely to report fair or poor health than participants who were cognitively unimpaired. Careful intervention and encouragement to maintain healthy lifestyles as people age could help to reduce the risk of both mood problems and cognitive decline.

An 18-mer Peptide Derived from Prosaposin Ameliorates the Effects of Aβ1-42 Neurotoxicity on Hippocampal Neurogenesis and Memory Deficit in Mice. - Gao, Hui-Ling; Li, Cheng; Nabeka, Hiroaki; Shimokawa, Tetsuya; Wang, Zhan-You; Cao, Ya-Ming; Matsuda, Seiji (J Alzheimers Dis, 2016)
The pathological hallmarks of Alzheimer's disease (AD) include amyloid-β (Aβ) accumulation, neurofibrillary tangle formation, synaptic dysfunction, and neuronal loss. The present study was performed to investigate the protective effects and mechanism of action of a prosaposin-derived 18-mer peptide (PS18: LSELIINNATEELLIKGL) on mice hippocampal progenitor cell proliferation, neurogenesis, and memory tasks after intracerebroventricular injection of Aβ1-42 peptide. Seven days after Aβ1-42 injection, significant proliferation of hippocampal progenitor cells and memory impairment were evident. Two weeks after Aβ1-42 peptide injection, elevated numbers of surviving 5-bromo-2-deoxyuridine cells and newly formed neurons were detected. Treatment with PS18 attenuated these effects evoked by Aβ1-42. Our data indicate that treatment with PS18 partially attenuated the increase in hippocampal neurogenesis caused by Aβ1-42-induced neuroinflammation and prevented memory deficits associated with increased numbers of activated glial cells. We observed an increase in ADAM10 and decreases in BACE1, PS1/2, and AβPP protein levels, suggesting that PS18 enhances the nonamyloidogenic AβPP cleavage pathway. Importantly, our results further showed that PS18 activated the PI3K/Akt pathway, phosphorylated GSK-3α/β, and, as a consequence, exerted a neuroprotective effect. In addition, PS18 showed a protective effect against Aβ1-42-induced neurotoxicity via suppression of the caspase pathway; upregulation of Bcl-2; downregulation of BAX, attenuating mitochondrial damage; and inhibition of caspase-3. These findings suggest that PS18 may provide a valuable therapeutic strategy for the treatment of progressive neurodegenerative diseases, such as AD.

ABCA7 Genotypes Confer Alzheimer's Disease Risk by Modulating Amyloid-β Pathology. - Zhao, Qing-Fei; Wan, Yu; Wang, Hui-Fu; Sun, Fu-Rong; Hao, Xiao-Ke; Tan, Meng-Shan; Tan, Chen-Chen; Zhang, Dao-Qiang; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2016)
ABCA7 gene has been identified as a strong genetic locus for Alzheimer's disease (AD) susceptibility in genome wide association studies (GWAS). However, the possible roles of ABCA7 variants in AD pathology were not specifically assessed. Using tagger methods, we extracted 15 targeted ABCA7 loci to investigate their associations with cerebrospinal fluid (CSF) and neuroimaging markers in Alzheimer's Disease Neuroimaging Initiative (ADNI) dataset. Finally, although we did not detect any significant associations of previously published GWAS SNPs (rs3764650 and rs78117248) with all the CSF (Aβ1 - 42, T-tau, and P-tau) and neuroimaging markers, three other variants (rs3752242, rs3752240, and rs4147912) at ABCA7 loci were detected to show significant associations with amyloid deposition on AV-45 PET in brain. Moreover, haplotype and subgroup analysis confirmed these significant findings. Furthermore, there were no remarkable correlations between ABCA7 variants and neuronal degeneration biomarkers (elevated CSF tau, brain structure atrophy, and hypometabolism on imaging) in this study. Thus, our study suggested that ABCA7 genotypes contribute to the AD risk through involvement in amyloid-β deposition on in vivo imaging, but not in tau pathology, brain atrophy, or decreased glucose metabolism.

Aberrant Spontaneous Brain Activity in Patients with Mild Cognitive Impairment and concomitant Lacunar Infarction: A Resting-State Functional MRI Study. - Ni, Ling; Liu, Renyuan; Yin, Zhenyu; Zhao, Hui; Nedelska, Zuzana; Hort, Jakub; Zhou, Fei; Wu, Wenbo; Zhang, Xin; Li, Ming; Yu, Haiping; Zhu, Bin; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Lacunar infarctions (LI) have been associated with a cognitive decline and an increased risk of dementia. Whether and how the pattern of spontaneous brain activity in patients with mild cognitive impairment (MCI) differs in subjects with and without concomitant LI remains unclear. OBJECTIVE: To compare the pattern of spontaneous brain activity in MCI patients with versus those without LI using resting-state functional magnetic resonance imaging (rs-fMRI). METHODS: Forty-eight MCI patients, including 22 with LI [MCI-LI] and 26 without LI [MCI-no LI], and 28 cognitive normal subjects underwent rs-fMRI post-processed using regional homogeneity (ReHo) and the amplitude of low-frequency fluctuation (ALFF) methods. RESULTS: Compared with cognitively normal subjects, the MCI-LI patients had decreased ReHo in the precuneus/cuneus (Pcu/CU) and insula; decreased ALFF in the Pcu/CU and frontal lobe; and increased ALFF and ReHo in the temporal lobe. While the MCI-no LI group had increased ReHo and ALFF in the bilateral hippocampus and parahippocampal gyrus, frontal lobe, and decreased ALFF and ReHo in the temporal lobe. Compared with the MCI-no LI patients, those with MCI-LI had decreased ALFF in the frontal lobe; decreased ReHo in the Pcu/CU and insula; and increased ALFF and ReHo in the temporal lobe (p <  0.05, AlphaSim corrected). In MCI-LI patients, the MOCA scores showed a relatively weak correlation with ALFF values in the medial frontal gyrus (r = 0.432, p = 0.045) (of borderline significance after Bonferroni correction). CONCLUSIONS: The spontaneous brain activities in MCI-LI were distinct from MCI-no LI. The probable compensatory mechanism observed in MCI-no LI might be disrupted in MCI with LI due to vascular damage.
Keywords: Aged; Aged, 80 and over; Brain; Brain Mapping; Cognitive Dysfunction; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Rest; Stroke, Lacunar

Active Cigarette Smoking in Cognitively-Normal Elders and Probable Alzheimer's Disease is Associated with Elevated Cerebrospinal Fluid Oxidative Stress Biomarkers. - Durazzo, Timothy C; Korecka, Magdalena; Trojanowski, John Q; Weiner, Michael W; O' Hara, Ruth; Ashford, John W; Shaw, Leslie M (J Alzheimers Dis, 2016)
Neurodegenerative diseases and chronic cigarette smoking are associated with increased cerebral oxidative stress (OxS). Elevated F2-isoprostane levels in biological fluid is a recognized marker of OxS. This study assessed the association of active cigarette smoking with F2-isoprostane in concentrations in cognitively-normal elders (CN), and those with mild cognitive impairment (MCI) and probable Alzheimer's disease (AD). Smoking and non-smoking CN (n = 83), MCI (n = 164), and probable AD (n = 101) were compared on cerebrospinal fluid (CSF) iPF2α-III and 8,12, iso-iPF2α-VI F2-isoprostane concentrations. Associations between F2-isoprostane levels and hippocampal volumes were also evaluated. In CN and AD, smokers had higher iPF2α-III concentration; overall, smoking AD showed the highest iPF2α-III concentration across groups. Smoking and non-smoking MCI did not differ on iPF2α-III concentration. No group differences were apparent on 8,12, iso-iPF2α-VI concentration, but across AD, higher 8,12, iso-iPF2α-VI level was related to smaller left and total hippocampal volumes. Results indicate that active cigarette smoking in CN and probable AD is associated with increased central nervous system OxS. Further investigation of factors mediating/moderating the absence of smoking effects on CSF F2-isoprostane levels in MCI is warranted. In AD, increasing magnitude of OxS appeared to be related to smaller hippocampal volume. This study contributes additional novel information to the mounting body of evidence that cigarette smoking is associated with adverse effects on the human central nervous system across the lifespan.

Added Prognostic Value of Cerebrospinal Fluid Biomarkers in Predicting Decline in Memory Clinic Patients in a Prospective Cohort. - Handels, Ron L H; Joore, Manuela A; Vos, Stephanie J B; Aalten, Pauline; Ramakers, Inez H G B; Rikkert, Marcel Olde; Scheltens, Philip; Jansen, Willemijn J; Visser, Pieter-Jelle; van Berckel, Bart M N; van Domburg, Peter; Smid, Machiel; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Limited information is available on short-term prognosis of Alzheimer's disease (AD) biomarkers in cerebrospinal fluid (CSF) in addition to routine diagnostic workup. OBJECTIVE: This study aims to investigate the added prognostic value of AD CSF biomarkers. METHODS: In a prospective cohort study, clinical experts predicted cognitive and functional symptoms in 114 memory clinic patients by assessing comprehensive routine diagnostic test information (patient history, and physical, neurological, psychiatric, neuropsychological, and MRI examinations), without and with CSF biomarkers. The reference standard was the 'observed clinically relevant decline' using baseline and 1- and 2-year follow-up information. RESULTS: Decline over a 2-year period was observed in 51% of all participants (3% in SMC, 48% in MCI, 90% in mild dementia). In the total sample, the accuracy of predicted decline did not differ significantly between routine assessment without (79% correctly predicted) and with (74% correctly predicted) CSF biomarkers. Subgroup analyses revealed 25 (83%) correct predictions in SMC, 30 (68%) in MCI, and 35 (88%) in dementia without the use of CSF; and 21 (70%), 27 (61%), and 36 (90%), respectively, with the use of CSF in addition to the routine assessment. CONCLUSION: AD CSF biomarkers did not increase accuracy of 2-year prognosis of cognitive and functional decline when added to routine diagnostic workup. This suggests that the standard diagnostic workup without CSF biomarkers allows fairly accurate predictions for the short-term course of symptoms. Routine AD biomarkers in CSF have limited prognostic value over 2 years in persons with a suspected cognitive disorder.

Age and its association with low insulin and high amyloid-β peptides in blood. - Li, Huajie; Zhu, Haihao; Wallack, Max; Mwamburi, Mkaya; Abdul-Hay, Samer O; Leissring, Malcolm A; Qiu, Wei Qiao (J Alzheimers Dis, 2016)
Age is the major risk factor for developing Alzheimer's disease (AD), and modifying age-related factors may help to delay the onset of the disease. The goal of this study was to investigate the relationship between age and the metabolic factors related to the risk of developing AD. The concentrations of insulin, amylin, and amyloid-β peptide (Aβ) in plasma were measured. We further measured the activity of serum Aβ degradation by using fluorescein- and biotin-labeled Aβ40. Apolipoprotein E4 allele (ApoE4) and cognitive impairment were characterized. Subjects were divided into three age groups: 60-70, 70-80, and ≥80 years old. We found that the older the subjects, the lower the concentration of insulin (p = 0.001) and the higher the concentration of Aβ1-40 (p = 0.004) in plasma. However, age was not associated with the concentration of another pancreatic peptide, amylin, and only marginally with Aβ1-42. These relationships remained in the absence of diabetes, cardiovascular disease, and stroke, and regardless of the presence of ApoE4 and cognitive impairment. Both age and ApoE4 were inversely associated with, while insulin was positively associated with, the activities of Aβ degradation in serum. Our study suggested that low concentration of insulin and high concentration of Aβ40 are aging factors related to the risk of AD.
Keywords: Age Distribution; Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Biomarkers; Cognition Disorders; Cross-Sectional Studies; Female; Humans; Insulin; Islet Amyloid Polypeptide; Linear Models; Male; Middle Aged; Multivariate Analysis; Peptide Fragments

Aging as a Precipitating Factor in Chronic Restraint Stress-Induced Tau Aggregation Pathology, and the Protective Effects of Rosmarinic Acid. - Shan, Ye; Wang, Dan-Dan; Xu, Yu-Xia; Wang, Chu; Cao, Lan; Liu, Yun-Sheng; Zhu, Cui-Qing (J Alzheimers Dis, 2016)
Stress is an important risk factor of Alzheimer's disease (AD). It has been evidenced that stress could induce tau phosphorylation and increase tau insolubility in brain; however, little is known about the interactional effect of stress with aging on tauopathy. Therefore, we explored the effects of aging on stress-induced tauopathy and the potential mechanism in mouse model of chronic restraint stress (CRS). Here we found that in general, the level of phosphorylated tau (P-tau) was higher in brain of middle-aged mice than that in adult mice under physiological conditions. CRS-induced tau phosphorylation and its insolubility were more prominent in middle-aged mice. The increase of AT8-labeled insoluble P-tau was dramatic in middle-aged mice, which was highly ubiquitinated but did not form PHF structures. The levels of chaperones were relatively lower in middle-aged mice brain; CRS further reduced the expression, especially for HDJ2/HSP40. CRS also suppressed the expression of Pin1, the peptidylprolyl cis/trans isomerase, in middle-aged mice but not in adult mice. Downregulation of HSP40 or Pin1 caused an increase of transfected extraneous tau in 293 cells. Rosmarinic acid (RA) could effectively suppress the elevation of P-tau and insoluble P-tau formation induced by CRS, and reversed the abnormal changes of chaperones and Pin1 particularly in middle-aged mice. Taken together, our findings provided evidence that aging could be a promoting factor in stress-induced tauopathy, which was relevant with malregulation of chaperones and Pin1, and RA might be a promising beneficial agent for stress-induced tauopathy.
Keywords: Aging; Animals; Antioxidants; Brain; Cinnamates; Corticotropin-Releasing Hormone; Depsides; Disease Models, Animal; HEK293 Cells; HSP90 Heat-Shock Proteins; Humans; Male; Mice; Mice, Inbred C57BL; Microscopy, Immunoelectron; NIMA-Interacting Peptidylprolyl Isomerase; Peptidylprolyl Isomerase; Phosphorylation; Precipitating Factors; Receptors, Corticotropin; Restraint, Physical; Stress, Psychological; tau Proteins; Transfection

Altered Energy Metabolism Pathways in the Posterior Cingulate in Young Adult Apolipoprotein E ɛ4 Carriers. - Perkins, Michelle; Wolf, Andrew B; Chavira, Bernardo; Shonebarger, Daniel; Meckel, J P; Leung, Lana; Ballina, Lauren; Ly, Sarah; Saini, Aman; Jones, T Bucky; Vallejo, Johana; Jentarra, Garilyn; et al. (J Alzheimers Dis, 2016)
The APOE gene, encoding apolipoprotein E, is the primary genetic risk factor for late-onset Alzheimer's disease (AD). Apolipoprotein E ɛ4 allele (APOE4) carriers have alterations in brain structure and function (as measured by brain imaging) even as young adults. Examination of this population is valuable in further identifying details of these functional changes and their association with vulnerability to AD decades later. Previous work demonstrates functional declines in mitochondrial activity in the posterior cingulate cortex, a key region in the default mode network, which appears to be strongly associated with functional changes relevant to AD risk. Here, we demonstrate alterations in the pathways underlying glucose, ketone, and mitochondrial energy metabolism. Young adult APOE4 carriers displayed upregulation of specific glucose (GLUT1 & GLUT3) and monocarboxylate (MCT2) transporters, the glucose metabolism enzyme hexokinase, the SCOT & AACS enzymes involved in ketone metabolism, and complexes I, II, and IV of the mitochondrial electron transport chain. The monocarboxylate transporter (MCT4) was found to be downregulated in APOE4 carriers. These data suggest that widespread dysregulation of energy metabolism in this at-risk population, even decades before possible disease onset. Therefore, these findings support the idea that alterations in brain energy metabolism may contribute significantly to the risk that APOE4 confers for AD.

Altered sense of humor in dementia. - Clark, Camilla N; Nicholas, Jennifer M; Gordon, Elizabeth; Golden, Hannah L; Cohen, Miriam H; Woodward, Felix J; Macpherson, Kirsty; Slattery, Catherine F; Mummery, Catherine J; Schott, Jonathan M; Rohrer, Jonathan D; Warren, Jason D (J Alzheimers Dis, 2016)
Sense of humor is potentially relevant to social functioning in dementias, but has been little studied in these diseases. We designed a semi-structured informant questionnaire to assess humor behavior and preferences in patients with behavioral variant frontotemporal dementia (bvFTD; n = 15), semantic dementia (SD; n = 7), progressive nonfluent aphasia (PNFA; n = 10), and Alzheimer's disease (AD; n = 16) versus healthy age-matched individuals (n = 21). Altered (including frankly inappropriate) humor responses were significantly more frequent in bvFTD and SD (all patients) than PNFA or AD (around 40% of patients). All patient groups liked satirical and absurdist comedy significantly less than did healthy controls. This pattern was reported premorbidly for satirical comedy in bvFTD, PNFA, and AD. Liking for slapstick comedy did not differ between groups. Altered sense of humor is particularly salient in bvFTD and SD, but also frequent in AD and PNFA. Humor may be a sensitive probe of social cognitive impairment in dementia, with diagnostic, biomarker and social implications.
Keywords: Aged; Alzheimer Disease; Case-Control Studies; Cognition Disorders; Emotions; Female; Frontotemporal Dementia; Humans; Male; Middle Aged; Neuropsychological Tests; Primary Progressive Nonfluent Aphasia; Psychiatric Status Rating Scales; Surveys and Questionnaires

Amyloid-Related Imaging Abnormalities (ARIA) in Immunotherapy Trials for Alzheimer's Disease: Need for Prognostic Biomarkers? - Piazza, Fabrizio; Winblad, Bengt (J Alzheimers Dis, 2016)
At the 8th International Conference on Clinical Trials in Alzheimer's Disease held November 5-7, 2015 in Barcelona, Spain, promising data were presented on two candidate Alzheimer's disease immunotherapeutic agents, gantenerumab and aducanumab. Trial results demonstrated that the implementation of cerebrospinal fluid and Aβ-PET biomarkers improves trial enrichment and outcome, which has led to a change in targeting strategy as clinical trials would be conducted with earlier, even presymptomatic, stages of the disease. Promising findings of outcomes, as measured by Aβ-PET and cerebrospinal fluid tau and P-tau, were, nevertheless, associated with antibody dose-dependent increased risk of severe adverse effects, specifically amyloid-related imaging abnormalities (ARIA). Aducanumab was associated with concomitant time-, dose-, and APOE-related incidence of ARIA in more than one-half of the patients within the high-dose arm. The future challenge will thus be to find biomarkers more favorably balanced between effective dosing of antibody to remove Aβ versus dosing to limit deleterious side effects. Interest was shown by Roche and Biogen, which promoted high-dose phase 3 trials. However, this generated some concerns related to a reasonable expected further increase in the incidence of severe side effects. What has been learned is challenging primary industry strategies for following-up and monitoring safety and effectiveness of anti-Aβ antibodies in clinical trials. Here, we debate the issue of what is an acceptable balance of treatment side effects, i.e., therapeutic-induced ARIA, versus the positive prospects. Indeed, implementation of biomarkers for ARIA might increase value and reduce waste in the design of immunotherapy trials of Alzheimer's disease.

Analysis of Cerebrospinal Fluid and [11C]PIB PET Biomarkers for Alzheimer's Disease with Updated Protocols. - Wang, Min Jeong; Yi, SangHak; Han, Jee-Young; Park, So Young; Jang, Jae-Won; Chun, In Kook; Giau, Vo Van; Bagyinszky, Eva; Lim, Kun Taek; Kang, Sung Min; An, Seong Soo A; Park, Young Ho; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Recently, a Korean research group suggested a consensus protocol, based on the Alzheimer's Disease Neuroimaging Initiative study protocol but with modifications for minimizing the confounding factors, for the evaluation of cerebrospinal fluid (CSF) biomarkers. OBJECTIVE: Here, we analyzed fluid and imaging biomarkers of Alzheimer's disease (AD) in Korean population. We used the updated protocol to propose a more accurate CSF biomarker value for the diagnosis of AD. METHODS: Twenty-seven patients with AD and 30 cognitively normal controls (NC) were enrolled. CSF was collected from 55 subjects (patients with AD = 26, NC = 29) following the Korea consensus protocol. CSF biomarkers were measured using the INNO-BIA AlzBio3 immunoassay, and Pittsburgh compound B (PIB) positron emission tomography (PET) scans were also performed. RESULTS: The cutoff values of CSF amyloid beta 1-42 (Aβ42), total tau (t-Tau), and phosphorylated tau (p-Tau) proteins were 357.1 pg/ml, 83.35 pg/ml, and 38.00 pg/ml, respectively. The cutoff values of CSF t-Tau/Aβ42 and p-Tau/Aβ42 ratio- were 0.210 (sensitivity 100%, specificity 86.21%) and 0.1350 (sensitivity 88.46%, specificity of 92.86%). The concordance rate with PIB-PET was higher using the CSF t-Tau/Aβ42 ratio (κ= 0.849, CI 0.71-0.99) than CSF Aβ42 alone (κ= 0.703, CI 0.51-0.89). CONCLUSIONS: Here, we improved controversial factors associated with the previous CSF study protocol and suggested a new cutoff value for the diagnosis of AD. Our results showed good diagnostic performance for differentiation of AD. Thus, we expect our findings could be a cornerstone in the establishment and clinical application of biomarkers for AD diagnosis.

Anemia and Mild Cognitive Impairment in the German General Population. - Dlugaj, Martha; Winkler, Angela; Weimar, Christian; Dürig, Jan; Broecker-Preuss, Martina; Dragano, Nico; Moebus, Susanne; Jöckel, Karl-Heinz; Erbel, Raimund; Eisele, Lewin (J Alzheimers Dis, 2016)
There is increasing evidence that anemia is associated with cognitive impairment. Therefore, the aim of the study was to examine the cross-sectional association of anemia as well as the persistence of anemia over the last five years with mild cognitive impairment (MCI) and MCI subtypes (amnestic/non-amnestic MCI (aMCI/naMCI)). Out of 4,157 participants (50% men, 50-80 years) of the second examination (t1) of a cohort study (baseline (t0) 2000-2003), we included 4,033 participants with available hemoglobin information and complete cognitive assessment. Anemia was defined as hemoglobin <13 g/dl in men (n = 84) and <12 g/dl in women (n = 79). Group comparisons were used to compare the cognitive subtests. To determine the association of MCI with anemia at t1, with anemia five years prior to the cognitive assessment (t0) and anemia at both time points, we used logistic regression models and included 579 participants with MCI and 1,438 cognitively normal participants out of the total cohort. Anemic participants showed lower performances in verbal memory and executive functions. The fully adjusted odds ratios (OR) for MCI, aMCI, and naMCI in anemic versus non-anemic participants were 1.92 (95% -CI, 1.09-3.39), 1.96 (1.00-3.87), and 1.88 (0.91-3.87). Anemia at both times points showed a non-significant association with naMCI (OR 3.74, 0.94-14.81, fully adjusted). Our results suggest that anemia is associated with an increased risk of MCI independent of traditional cardiovascular risk factors. The association of anemia and MCI has important clinical relevance, because many causes of anemia can be treated effectively.
Keywords: Aged; Aged, 80 and over; Anemia; Cognitive Dysfunction; Cohort Studies; Executive Function; Female; Follow-Up Studies; Germany; Humans; Male; Memory; Middle Aged; Neuropsychological Tests; Prevalence; Speech Perception

Apolipoprotein ɛ4 is Associated with Dementia and Cognitive Impairment Predominantly Due to Alzheimer's Disease and Not with Vascular Cognitive Impairment: A Singapore-Based Cohort. - Chai, Yuek Ling; Yeo, Hazel Kai-Hui; Wang, Jiehao; Hilal, Saima; Ikram, Mohammad Kamran; Venketasubramanian, Narayanaswamy; Wong, Boon-Seng; Chen, Christopher Li-Hsian (J Alzheimers Dis, 2016)
BACKGROUND AND OBJECTIVE: While the association for apolipoprotein ɛ4 allele (APOE4) with Alzheimer's disease (AD) has been consistently confirmed, the association with vascular cognitive impairment (VCI) is unclear. We therefore explored the relationship of APOE with both AD and cerebrovascular disease (CeVD) by examining the prevalence of APOE4 in AD, AD with CeVD and vascular dementia (VaD), as well as in cognitive impairment no dementia (CIND) with and without CeVD. METHODS: We performed a case-control study with subjects recruited from memory clinics and the community. All subjects underwent standardized brain neuroimaging, clinical and neuropsychological assessments, following which they were classified using research criteria. RESULTS: A total of 411 subjects; 92 controls with no cognitive impairment (NCI), 77 CIND without CeVD, 87 CIND with CeVD, 55 AD without CeVD, 68 AD with CeVD, and 32 VaD patients were recruited. Compared to NCI (16.3%), the prevalence of APOE4 carriers was significantly higher only in CIND (37.7%) and AD in the absence of CeVD (45.5%), but not in the three subgroups of VCI, namely CIND with CeVD (20.7%), AD with CeVD (27.9%) and VaD (25.0%). Logistic regression analyses also showed that APOE4 carriers were more likely to have CIND without CeVD (Odds Ratio [OR]: 3.34; 95% Confidence Interval [CI]: 1.59-7.03) and AD without CeVD (OR: 7.21; 95% CI: 2.74-18.98), but no such association was observed in the VCI subgroups. CONCLUSION: APOE4 is significantly associated with dementia and CIND due to AD pathology, but not with VCI.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Apolipoprotein E4; Cognition Disorders; Cohort Studies; Dementia; Female; Genetic Association Studies; Genotype; Humans; Male; Middle Aged; Neuroimaging; Neuropsychological Tests; Psychiatric Status Rating Scales; Singapore; Vascular Diseases

Application of the IWG-2 Diagnostic Criteria for Alzheimer's Disease to the ADNI. - Wang, Hui-Fu; Tan, Lan; Cao, Lei; Zhu, Xi-Chen; Jiang, Teng; Tan, Meng-Shan; Liu, Ying; Wang, Chong; Tsai, Richard M; Jia, Jian-Ping; Yu, Jin-Tai (J Alzheimers Dis, 2016)
BACKGROUND: The International Working Group (IWG) recently proposed the revised diagnostic criteria for Alzheimer's disease (AD) to define and refine several types of AD, and to reclassify AD-related biomarkers into diagnostic and progression markers, but its performance is not known. OBJECTIVE: This study was designed to describe the application of the revised IWG criteria in the Alzheimer's Disease Neuroimaging Initiative (ADNI) dataset, and to ascertain whether diagnostic and progression markers show significant differences in their relationships to AD severity and progression. METHODS: Based on the requirements of the refined criteria, 857 ADNI subjects with memory evaluation and at least one pathophysiological marker (CSF or amyloid imaging biomarkers) were eligible and reclassified in this study, and we calculated the associations of diagnostic (CSF and amyloid PET) and progression markers (MRI and fluorodeoxyglucose-PET) with AD severity and progression respectively. RESULTS: The majority (84.2% ) of ADNI AD group (n = 117) and 173 MCI (37.4% ) subjects in ADNI met the definition of typical AD; and 105 cognitively normal (41.0% ) individuals were diagnosed as asymptomatic AD. Furthermore, diagnostic and progression markers showed significant differences when correlated to AD severity and progression. CONCLUSION: A large proportion of AD dementia subjects were categorized as typical AD, and the revised criteria could identify typical AD from MCI status as well as asymptomatic AD at the asymptomatic stage. Moreover, the significant differences between diagnostic and progression markers further supported the new biomarkers categorization in the refined criteria.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid Precursor Protein Secretases; Aspartic Acid Endopeptidases; Cognitive Dysfunction; Databases, Factual; Disease Progression; Female; Humans; Longitudinal Studies; Male; Multicenter Studies as Topic; Neuroimaging; Psychiatric Status Rating Scales; tau Proteins

Aquaporin-4 and Alzheimer's Disease. - Yang, Canhong; Huang, Xiaomin; Huang, Xiaoyu; Mai, Hantao; Li, Jie; Jiang, Tao; Wang, Xiaofeng; Lü, Tianming (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is the most common form of dementia. Although the pathogenesis of AD remains unclear, AD is thought to result from an imbalance in the production and clearance of amyloid-β protein (Aβ). Aquaporin-4 (AQP4) is the major aquaporin in the mammalian brain, is mostly expressed on astrocytic endfeet, and functions as a water transporter. However, the distribution and expression of AQP4 are altered in both AD clinical populations and animal models. Recent studies have revealed that AQP4 is important to the clearance of Aβ in brain via lymphatic clearance, transcytotic delivery, and glial degradation, as well as to the synaptic function. Thus, AQP4 likely plays an important role in the pathogenesis of AD. Further studies would provide new targets for prevention, ultimately leading to improved treatment options for AD.

Assessment and Reporting of Driving Fitness in Patients with Dementia in Clinical Practice: Data from SveDem, the Swedish Dementia Registry. - Lovas, Joel; Fereshtehnejad, Seyed-Mohammad; Cermakova, Pavla; Lundberg, Catarina; Johansson, Björn; Johansson, Kurt; Winblad, Bengt; Eriksdotter, Maria; Religa, Dorota (J Alzheimers Dis, 2016)
BACKGROUND: Driving constitutes a very important aspect of daily life and is dependent on cognitive functions such as attention, visuo-spatial skills and memory, which are often compromised in dementia. Therefore, the driving fitness of patients with dementia needs to be addressed by physicians and those that are deemed unfit should not be allowed to continue driving. OBJECTIVE: We aimed at investigating to what extent physicians assess driving fitness in dementia patients and determinant factors for revoking of their licenses. METHODS: This study includes 15113 patients with newly diagnosed dementia and driver's license registered in the Swedish Dementia Registry (SveDem). The main outcomes were reporting to the licensing authority and making an agreement about driving eligibility with the patients. RESULTS: Physicians had not taken any action in 16% of dementia patients, whereas 9% were reported to the authority to have their licenses revoked. Males (OR = 3.04), those with an MMSE score between 20-24 (OR = 1.35) and 10-19 (OR = 1.50), patients with frontotemporal (OR = 3.09) and vascular dementia (OR = 1.26) were more likely to be reported to the authority. CONCLUSION: For the majority of patients with dementia, driving fitness was assessed. Nevertheless, physicians did not address the issue in a sizeable proportion of dementia patients. Type of dementia, cognitive status, age, sex and burden of comorbidities are independent factors associated with the assessment of driving fitness in patients with dementia. Increased knowledge on how these factors relate to road safety may pave the way for more specific guidelines addressing the issue of driving in patients with dementia.

The Association Between Retinal Neuronal Layer and Brain Structure is Disrupted in Patients with Cognitive Impairment and Alzheimer's Disease. - Liu, Siwei; Ong, Yi-Ting; Hilal, Saima; Loke, Yng Miin; Wong, Tien Y; Chen, Christopher Li-Hsian; Cheung, Carol Y; Zhou, Juan (J Alzheimers Dis, 2016)
Both healthy and pathological aging due to Alzheimer's disease (AD) are associated with decreased brain grey matter volume (GMV) and disrupted white matter (WM) microstructure. Thinner macular ganglion cell-inner plexiform layer (GC-IPL) measured by spectral-domain optical coherence tomography has been reported in patients with AD and mild cognitive impairment. Emerging evidence suggested a link between thinner GC-IPL and lower GMV in subjects with no dementia using region-of-interest-based approach. However, it remains unknown whether GC-IPL thickness is associated with brain WM microstructure and how such association differed between normal and cognitively impaired subjects. Here, for subjects with no cognitive impairment (NCI), thinner GC-IPL was associated with lower WM microstructure integrity in the superior longitudinal fasciculus, inferior fronto-occipital fasciculus, corticospinal tracts, anterior thalamic radiation, and cingulum regions, while it was weakly associated with lower GMV in visual cortex and cerebellum. Nevertheless, these retina-brain associations were disrupted in the presence of cognitive impairment. Correlations between GMV and GC-IPL were lost in patients with cognitive impairment but no dementia (CIND) and AD patients. GC-IPL was related to WM microstructural disruption in similar regions with decreased significance. In contrast, lower WM microstructure integrity in the fornix showed a trend of correlation with thinner GC-IPL in both CIND and AD but not NCI. Collectively, our findings suggest the possible physiological retina-brain relationship in healthy aging, which might be disrupted by disease-induced changes in patients with cognitive impairment. Longitudinal study with larger patient sample should follow to confirm the disease mechanism behind these retina-brain relationship changes.

Association of Butyrylcholinesterase-K Allele and Apolipoprotein E ɛ4 Allele with Cognitive Decline in Dementia with Lewy Bodies and Alzheimer's Disease. - Vijayaraghavan, Swetha; Darreh-Shori, Taher; Rongve, Arvid; Berge, Guro; Sando, Sigrid B; White, Linda R; Auestad, Bjørn H; Witoelar, Aree; Andreassen, Ole A; Ulstein, Ingun D; Aarsland, Dag (J Alzheimers Dis, 2016)
BACKGROUND: A common polymorphism of the butyrylcholinesterase gene, the K-variant (BCHE-K) is associated with reduced butyrylcholinesterase (BuChE) activity. Insufficient studies exist regarding the frequency and role of BCHE-K in dementias. OBJECTIVE: To determine the association of BCHE-K and APOEɛ4 with diagnosis and rate of cognitive decline in dementia with Lewy bodies (DLB) and Alzheimer's disease (AD) patients. METHODS: Genomic DNA from 368 subjects (108 AD, 174 DLB, and 86 controls) from two routine clinical cohort studies in Norway; DemVest and TrønderBrain, were genotyped for BCHE-K and APOEɛ4. The mild dementia DemVest subjects received annual Mini-Mental State Examination assessments for five years. RESULTS: BCHE-K frequency was lower in DLB (33.9% ; p <  0.01) than in control subjects (51.2%), and was numerically lower in AD as well (38.9% ; p = 0.11). More rapid cognitive decline was associated with the APOEɛ4 genotype, but not with the BCHE-K genotype. In an exploratory analysis of patients who completed all five follow-up visits, there was greater cognitive decline in BCHE-K carriers in the presence of the APOEɛ4 allele than in the absence of these polymorphisms. CONCLUSION: BCHE-K is associated with a reduced risk for AD and DLB whereas APOEɛ4 is associated with more rapid cognitive decline. The greater cognitive decline in individuals with both APOEɛ4 and BCHE-K alleles require prospective confirmation in well-controlled trials.
Keywords: Aged; Aged, 80 and over; Alleles; Alzheimer Disease; Apolipoprotein E4; Butyrylcholinesterase; Cognition; Disease Progression; Female; Gene Frequency; Genotype; Humans; Lewy Body Disease; Male; Neuropsychological Tests

Association of Frontotemporal Dementia GWAS Loci with Late-Onset Alzheimer's Disease in a Northern Han Chinese Population. - Tan, Chen-Chen; Wan, Yu; Tan, Meng-Shan; Zhang, Wei; Wang, Zi-Xuan; Sun, Fu-Rong; Miao, Dan; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2016)
BACKGROUND: Both Alzheimer's disease (AD) and frontotemporal dementia (FTD) are a class of neurodegenerative diseases. Strong similarities in cerebrospinal fluid biomarker, imaging markers, and disease progression profiles suggest that some or most of the pathophysiology is shared between AD and FTD. A recent large genome-wide association study reported several single nucleotide polymorphisms (SNPs) at the RAB38, RAB38/CTSC, HLA-DRA/HLA-DRB5, and BTNL2 in association with FTD. OBJECTIVE: To explore whether these SNPs are associated with AD risk. METHODS: We conducted a case-control study to investigate the association of FTD-associated loci in 2338 Han Chinese subjects. RESULTS: We observed significant differences in genotype distributions of rs302668 (pc = 0.025), rs9268877 (pc = 0.025), rs9268856 (p <  0.001), and rs1980493 (pc = 0.045) between cases and controls. The SNPs rs16913634 for RAB38/CTSC was unrelated to LOAD risk (p = 0.088). CONCLUSION: The SNPs rs302668 in RAB38, rs9268877 and rs9268856 polymorphism in HLA-DRA/HLA-DRB5, and rs1980493 polymorphism in BTNL2 might play a role in the susceptibility to late-onset AD in the Han Chinese population.
Keywords: Age of Onset; Aged; Alzheimer Disease; Apolipoprotein E4; Asian Continental Ancestry Group; Case-Control Studies; China; Female; Frontotemporal Dementia; Gene Frequency; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Genotyping Techniques; Humans; Linkage Disequilibrium; Male; Mental Status Schedule; Polymorphism, Single Nucleotide

Association of Physical Function with Clinical and Subclinical Brain Disease: The Framingham Offspring Study. - Camargo, Erica C; Weinstein, Galit; Beiser, Alexa S; Tan, Zaldy S; DeCarli, Charles; Kelly-Hayes, Margaret; Kase, Carlos; Murabito, Joanne M; Seshadri, Sudha (J Alzheimers Dis, 2016)
BACKGROUND: Handgrip strength and gait speed are simple measures of physical capability and have been associated with current and future health outcomes. However, studies on their associations with brain structure and function in middle-aged adults are lacking. OBJECTIVE: To assess the relationship of fast-paced walking speed and handgrip strength with risk of dementia, Alzheimer's disease (AD), and stroke, as well as the cross-sectional associations with cognitive and brain magnetic resonance imaging (MRI) measures in a middle-aged community sample. METHODS: Framingham Offspring (n = 2,176; mean age 62, 54% female) had physical function, brain MRI, and cognitive evaluations between 1999 and 2005 and were followed-up for incident dementia AD and stroke until 11 years later. We related walking speed and handgrip strength to incident dementia, AD, and stroke using Cox models, and to brain and cognitive measures using multivariable linear and logistic regression. Models were adjusted for age, sex, education, and vascular risk factors. RESULTS: Slow walking and weak handgrip were associated with more than 2.5-fold increase in risk of AD. Weaker handgrip was associated with an increased risk of incident stroke (HR 1.74, 95% CI: 1.12-2.70/SDU, p = 0.01) in persons ≥65 years. Both measures were associated with lower total brain volume and poorer performance on tests of visual memory, language, executive function, and visuoperceptual function. Slower gait was also related to poorer verbal memory, and weaker handgrip to poorer abstraction. CONCLUSION: Tests of walking speed and handgrip strength may serve as clinical markers of brain structure and function and may improve dementia risk prediction.

Association of Plasma Aβ40 Peptides, But Not Aβ42, with Coronary Artery Disease and Diabetes Mellitus. - Roeben, Benjamin; Maetzler, Walter; Vanmechelen, Eugeen; Schulte, Claudia; Heinzel, Sebastian; Stellos, Konstantinos; Godau, Jana; Huber, Heiko; Brockmann, Kathrin; Wurster, Isabel; Gaenslen, Alexandra; Grüner, Eva; et al. (J Alzheimers Dis, 2016)
BACKGROUND/OBJECTIVE: Plasma levels of amyloid-beta (Aβ) 1-40 peptide have been proposed to be associated with cardiovascular mortality in patients with coronary artery disease (CAD). Therefore, we aimed to investigate the association of plasma Aβ levels with CAD, cardiovascular risk factors (CVRF), and APOE genotype in non-demented elderly individuals. METHODS: Plasma Aβ1 - 40 and Aβ1 - 42 levels of 526 individuals (mean age of 63.0±7.3 years) were quantified with the INNO-BIA plasma Aβ forms assay based on multiplextrademark technique. APOE genotype was determined with an established protocol. Presence of CAD and CVRFs were ascertained using a questionnaire and/or medical records. RESULTS: Plasma Aβ1 - 40 levels were significantly higher in individuals with CAD (p = 0.043) and, independently, in individuals with diabetes mellitus (DM) type 2 (p = 0.001) while accounting for age- and gender-effects. Plasma Aβ1 - 42 levels were higher in APOEɛ4 carriers (p = 0.004), but were neither relevantly associated with CAD nor with any CVRF. Plasma Aβ1 - 40 showed no association with APOE genotype. DISCUSSION: Our findings argue for an association of circulating plasma Aβ1 - 40 peptides with incident CAD and DM. Further investigations are needed to entangle the role of Aβ1 - 40 role in the pathophysiology of cardiovascular disease independent of its known role in Alzheimer's disease.

Association of Platelet Serotonin Levels in Alzheimer's Disease with Clinical and Cerebrospinal Fluid Markers. - Tajeddinn, Walid; Fereshtehnejad, Seyed-Mohammad; Seed Ahmed, Mohammed; Yoshitake, Takashi; Kehr, Jan; Shahnaz, Tasmin; Milovanovic, Micha; Behbahani, Homira; Höglund, Kina; Winblad, Bengt; Cedazo-Minguez, Angel; Jelic, Vesna; et al. (J Alzheimers Dis, 2016)
INTRODUCTION: Serotonin (5-HT) is involved in the pathology of Alzheimer's disease (AD). OBJECTIVE: We aimed to measure 5-HT level in platelets in AD and explore its association with cerebrospinal fluid (CSF), AD biomarkers (amyloid-β 1-42 (Aβ42), total tau (t-tau), and phosphorylated tau (p-tau)), and clinical symptoms. METHODS: 15 patients with AD and 20 patients with subjective cognitive impairment (SCI) were included. 5-HT metabolites were measured, in a specific fraction, using high performance liquid chromatography with electrochemical detection (HPLC-ECD). RESULTS: Significantly lower 5-HT concentrations were observed in AD patients compared to SCI patients both after normalization against total protein (p = 0.008) or platelet count (p = 0.019). SCI patients with lower 5-HT level have higher AD CSF biomarkers, total tau (p = 0.026) and tau/Aβ42 ratio (p = 0.001), compared to those with high 5-HT levels. CONCLUSION: AD patients have reduced platelet 5-HT levels. In SCI, lower 5-HT content was associated with a higher AD-CSF biomarker burden.

Association of Serum Vitamin D with the Risk of Incident Dementia and Subclinical Indices of Brain Aging: The Framingham Heart Study. - Karakis, Ioannis; Pase, Matthew P; Beiser, Alexa; Booth, Sarah L; Jacques, Paul F; Rogers, Gail; DeCarli, Charles; Vasan, Ramachandran S; Wang, Thomas J; Himali, Jayandra J; Annweiler, Cedric; Seshadri, Sudha (J Alzheimers Dis, 2016)
BACKGROUND: Identifying nutrition- and lifestyle-based risk factors for cognitive impairment and dementia may aid future primary prevention efforts. OBJECTIVE: We aimed to examine the association of serum vitamin D levels with incident all-cause dementia, clinically characterized Alzheimer's disease (AD), MRI markers of brain aging, and neuropsychological function. METHODS: Framingham Heart Study participants had baseline serum 25-hydroxyvitamin D (25(OH)D) concentrations measured between 1986 and 2001. Vitamin D status was considered both as a continuous variable and dichotomized as deficient (<10 ng/mL), or at the cohort-specific 20th and 80th percentiles. Vitamin D was related to the 9-year risk of incident dementia (n = 1663), multiple neuropsychological tests (n = 1291) and MRI markers of brain volume, white matter hyperintensities and silent cerebral infarcts (n = 1139). RESULTS: In adjusted models, participants with vitamin D deficiency (n = 104, 8% of the cognitive sample) displayed poorer performance on Trail Making B-A (β= -0.03 to -0.05±0.02) and the Hooper Visual Organization Test (β= -0.09 to -0.12±0.05), indicating poorer executive function, processing speed, and visuo-perceptual skills. These associations remained when vitamin D was examined as a continuous variable or dichotomized at the cohort specific 20th percentile. Vitamin D deficiency was also associated with lower hippocampal volumes (β= -0.01±0.01) but not total brain volume, white matter hyperintensities, or silent brain infarcts. No association was found between vitamin D deficiency and incident all-cause dementia or clinically characterized AD. CONCLUSIONS: In this large community-based sample, low 25(OH)D concentrations were associated with smaller hippocampal volume and poorer neuropsychological function.
Keywords: Adult; Aging; Brain; Cohort Studies; Dementia; Female; Humans; Incidence; Magnetic Resonance Imaging; Male; Middle Aged; Multivariate Analysis; Neuropsychological Tests; Regression Analysis; Risk; Sensitivity and Specificity; Vitamin D

The Associations between a Capsaicin-Rich Diet and Blood Amyloid-β Levels and Cognitive Function. - Liu, Cheng-Hui; Bu, Xian-Le; Wang, Jun; Zhang, Tao; Xiang, Yang; Shen, Lin-Lin; Wang, Qing-Hua; Deng, Bo; Wang, Xin; Zhu, Chi; Yao, Xiu-Qing; Zhang, Meng; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Capsaicin-rich diets are common worldwide. Capsaicin has been shown to have favorable effects on various diseases including atherosclerosis, cardiovascular diseases, stroke, obesity, hypertension, cancer, and gastrointestinal and inflammatory diseases. The impact of capsaicin on Alzheimer's disease (AD), which is the most common form of dementia in the elderly, remains unknown. OBJECTIVE: To investigate the correlations of capsaicin intake with cognition and blood markers of AD. METHODS: A total of 338 participants aged 40 years or older were enrolled from communities. Dietary habits regarding chili pepper consumption were collected using a Food Frequency Questionnaire (FFQ). Cognitive function was measured using the Chinese version of the Mini-Mental State Examination (MMSE). Blood amyloid-β (Aβ)40 and Aβ42 were measured with ELISA kits. RESULTS: In univariate analysis, MMSE scores (r = 0.209, p < 0.001), serum Aβ40 levels (r = -0.149, p = 0.006), the ratio of Aβ42/Aβ40 (r = 0.11, p = 0.043) and total serum Aβ levels (r = -0.097, p = 0.075), but not serum Aβ42 levels (r = 0.17, p = 0.757), were significantly correlated with total capsaicin diet scores. In multivariate analysis, total capsaicin diet scores were positively associated with MMSE scores and inversely associated with serum Aβ40 levels, and total serum Aβ levels, but not serum Aβ42 levels and the ratio of Aβ42/Aβ40, after adjustment for age, gender, educational level, smoking history, alcohol consumption, body mass index (BMI) and comorbidities. CONCLUSION: These findings suggest that a capsaicin-rich diet may exert favorable effects on AD blood biomarkers and cognitive function in middle-aged and elderly adults.

Associations between Serum Omega-3 Fatty Acid Levels and Cognitive Functions among Community-Dwelling Octogenarians in Okinawa, Japan: The KOCOA Study. - Nishihira, Junko; Tokashiki, Takashi; Higashiuesato, Yasushi; Willcox, Donald Craig; Mattek, Nora; Shinto, Lynne; Ohya, Yusuke; Dodge, Hiroko H (J Alzheimers Dis, 2016)
BACKGROUND: Epidemiological studies have found frequent consumption of fatty fish is protective against cognitive decline. However, the association between circulating omega-3 polyunsaturated fatty acid (PUFA) levels and cognitive functions among the oldest old is not well known. OBJECTIVE: To examine the association between serum PUFA levels and cognitive function among community-dwelling, non-demented elderly aged over 80 years old. METHODS: The data came from the Keys to Optimal Cognitive Aging (KOCOA) study; an ongoing cohort of relatively healthy volunteers aged over 80 years old, living in Okinawa, Japan. One hundred eighty five participants (mean age 84.1±3.4 years) assessed in 2011 who were free from frank dementia (defined as Clinical Dementia Rating <1.0) were used for the current cross-sectional study. We examined whether serum omega-3 PUFAs (docosahexaenoic acid [DHA] and eicosapentaenoic acid [EPA]), arachidonic acid (AA), EPA/AA ratio, DHA/AA ratio, and DHA+EPA are associated with (1) age and (2) global cognitive function (Japanese MMSE) and executive function (Verbal Fluency Letter). Data was analyzed univariately by t-test and multivariately by cumulative logistic regression models controlling for age, gender, years of education, obesity, hypertension, diabetes, and dyslipidemia. RESULTS: Serum DHA levels decreased with increasing age (p = 0.04). Higher global cognitive function was associated with higher levels of serum EPA (p = 0.03) and DHA + EPA (p = 0.03) after controlling for confounders. CONCLUSIONS: Higher serum EPA and DHA + EPA levels were independently associated with better scores on global cognitive function among the oldest old, free from dementia. Longitudinal follow-up studies are warranted.
Keywords: Age Factors; Aged, 80 and over; Arachidonic Acid; Blood Chemical Analysis; Cognition; Cross-Sectional Studies; Educational Status; Fatty Acids, Omega-3; Female; Humans; Japan; Logistic Models; Male; Mental Status Schedule; Obesity; Prospective Studies; Sex Factors

Astrocytes release HspB1 in response to amyloid-β exposure in vitro. - Nafar, Firoozeh; Williams, J Bradley; Mearow, Karen M (J Alzheimers Dis, 2016)
Although heat shock proteins are thought to function primarily as intracellular chaperones, the release and potential extracellular functions of heat shock proteins have been the focus of an increasing number of studies. Our particular interest is HspB1 (Hsp25/27) and as astrocytes are an in vivo source of HspB1 it is a reasonable possibility they could release HspB1 in response to local stresses. Using primary cultures of rat cortical astrocytes, we investigated the extracellular release of HspB1 with exposure to amyloid-β (Aβ). In order to assess potential mechanisms of release, we cotreated the cells with compounds that can modulate protein secretion including Brefeldin A, Methyl β-cyclodextrin, and MAP kinase inhibitors. Exposure to Aβ (0.1, 1.0, 2.0 μM) for 24-48 h resulted in a selective release of HspB1 that was insensitive to BFA treatment; none of the other inhibitors had any detectable influence. Protease protection assays indicated that some of the released HspB1 was associated with a membrane bound fraction, and analysis of exosomal preparations indicated the presence of HspB1 in exosomes. Finally, immunoprecipitation experiments demonstrated that the extracellular HspB1 was able to interact with extracellular Aβ. In summary, Aβ can stimulate release of HspB1 from astrocytes, this release is insensitive to Golgi or lipid raft disruption, and HspB1 can be found either free in the medium or associated with exosomes. This release suggests that there is a potential for extracellular HspB1 to be able to bind and sequester extracellular Aβ.
Keywords: Amyloid beta-Peptides; Animals; Astrocytes; Cells, Cultured; HSP27 Heat-Shock Proteins; Protein Transport; Rats

Astrocytic GluN2A and GluN2B Oppose the Synaptotoxic Effects of Amyloid-β1-40 in Hippocampal Cells. - Li, Yan; Chang, Lirong; Song, Yizhi; Gao, Xianghong; Roselli, Francesco; Liu, Jinping; Zhou, Wei; Fang, Yuan; Ling, Wei; Li, Hui; Almeida, Osborne F X; Wu, Yan (J Alzheimers Dis, 2016)
Early-stage Alzheimer's disease (AD) is characterized by synaptic dysfunction, a phenomenon in which soluble oligomers of amyloid-beta (Aβ) and N-methyl-D-aspartate receptor (NMDAR) are implicated. Here, we demonstrated that astrocytes express NMDARs and therefore have the potential to modulate the synaptotoxic actions of Aβ. We found that specific pharmacological antagonism of two of the major NMDAR subunits, GluN2A and GluN2B, exacerbates Aβ-induced synaptotoxicity suggesting, for the first time, that astrocytic GluN2A and GluN2B mediate synaptoprotection. From the perspective of the pathogenic mechanisms of Alzheimer's disease, in which Aβ and NMDAR play significant roles, these observations are striking since neuronal GluN2A and GluN2B are well known modulators of neurodegeneration. We did initial studies to understand the basis for the differential effects of astrocytic and neuronal GluN2A and GluN2B in the promotion of synapse survival, and identified a neurotrophin produced by astrocytes, nerve growth factor β (β-NGF), as a likely mediator of the synaptoprotective effects of astrocytic GluN2A and GluN2B activation. The results presented suggest that astrocytes may be suitable druggable targets for the prevention and/or delay of the synaptic loss that occurs during early stages of AD.

AβPP/PS1 Transgenic Mice Show Sex Differences in the Cerebellum Associated with Aging. - Ordoñez-Gutierrez, Lara; Fernandez-Perez, Ivan; Herrera, Jose Luis; Anton, Marta; Benito-Cuesta, Irene; Wandosell, Francisco (J Alzheimers Dis, 2016)
Cerebellar pathology has been related to presenilin 1 mutations in certain pedigrees of familial Alzheimer's disease. However, cerebellum tissue has not been intensively analyzed in transgenic models of mutant presenilins. Furthermore, the effect of the sex of the mice was not systematically analyzed, despite the fact that important gender differences in the evolution of the disease in the human population have been described. We analyzed whether the progression of amyloidosis in a double transgenic mouse, AβPP/PS1, is susceptible to aging and differentially affects males and females. The accumulation of amyloid in the cerebellum differentially affects males and females of the AβPP/PS1 transgenic line, which was found to be ten-fold higher in 15-month-old females. Amyloid-β accumulation was more evident in the molecular layer of the cerebellum, but glia reaction was only observed in the granular layer of the older mice. The sex divergence was also observed in other neuronal, survival, and autophagic markers. The cerebellum plays an important role in the evolution of the pathology in this transgenic mouse model. Sex differences could be crucial for a complete understanding of this disease. We propose that the human population could be studied in this way. Sex-specific treatment strategies in human populations could show a differential response to the therapeutic approach.

Biofunctionalized Silica Nanoparticles: Standards in Amyloid-β Oligomer-Based Diagnosis of Alzheimer's Disease. - Hülsemann, Maren; Zafiu, Christian; Kühbach, Katja; Lühmann, Nicole; Herrmann, Yvonne; Peters, Luriano; Linnartz, Christina; Willbold, Johannes; Kravchenko, Kateryna; Kulawik, Andreas; Willbold, Sabine; Bannach, Oliver; et al. (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) oligomers represent a promising biomarker for the early diagnosis of Alzheimer's disease (AD). However, state-of-the-art methods for immunodetection of Aβ oligomers in body fluids show a large variability and lack a reliable and stable standard that enables the reproducible quantitation of Aβ oligomers. At present, the only available standard applied in these assays is based on a random aggregation process of synthetic Aβ and has neither a defined size nor a known number of epitopes. In this report, we generated a highly stable standard in the size range of native Aβ oligomers that exposes a defined number of epitopes. The standard consists of a silica nanoparticle (SiNaP), which is functionalized with Aβ peptides on its surface (Aβ-SiNaP). The different steps of Aβ-SiNaP synthesis were followed by microscopic, spectroscopic and biochemical analyses. To investigate the performance of Aβ-SiNaPs as an appropriate standard in Aβ oligomer immunodetection, Aβ-SiNaPs were diluted in cerebrospinal fluid and quantified down to a concentration of 10 fM in the sFIDA (surface-based fluorescence intensity distribution analysis) assay. This detection limit corresponds to an Aβ concentration of 1.9 ng l-1 and lies in the sensitivity range of currently applied diagnostic tools based on Aβ oligomer quantitation. Thus, we developed a highly stable and well-characterized standard for the application in Aβ oligomer immunodetection assays that finally allows the reproducible quantitation of Aβ oligomers down to single molecule level and provides a fundamental improvement for the worldwide standardization process of diagnostic methods in AD research.

Blood-Based Biomarker Candidates of Cerebral Amyloid Using PiB PET in Non-Demented Elderly. - Westwood, Sarah; Leoni, Emanuela; Hye, Abdul; Lynham, Steven; Khondoker, Mizanur R; Ashton, Nicholas J; Kiddle, Steven J; Baird, Alison L; Sainz-Fuertes, Ricardo; Leung, Rufina; Graf, John; Hehir, Cristina Tan; et al. (J Alzheimers Dis, 2016)
Increasingly, clinical trials for Alzheimer's disease (AD) are being conducted earlier in the disease phase and with biomarker confirmation using in vivo amyloid PET imaging or CSF tau and Aβ measures to quantify pathology. However, making such a pre-clinical AD diagnosis is relatively costly and the screening failure rate is likely to be high. Having a blood-based marker that would reduce such costs and accelerate clinical trials through identifying potential participants with likely pre-clinical AD would be a substantial advance. In order to seek such a candidate biomarker, discovery phase proteomic analyses using 2DGE and gel-free LC-MS/MS for high and low molecular weight analytes were conducted on longitudinal plasma samples collected over a 12-year period from non-demented older individuals who exhibited a range of 11C-PiB PET measures of amyloid load. We then sought to extend our discovery findings by investigating whether our candidate biomarkers were also associated with brain amyloid burden in disease, in an independent cohort. Seven plasma proteins, including A2M, Apo-A1, and multiple complement proteins, were identified as pre-clinical biomarkers of amyloid burden and were consistent across three time points (p <  0.05). Five of these proteins also correlated with brain amyloid measures at different stages of the disease (q <  0.1). Here we show that it is possible to detect a plasma based biomarker signature indicative of AD pathology at a stage long before the onset of clinical disease manifestation. As in previous studies, acute phase reactants and inflammatory markers dominate this signature.

Brain Amyloid-β Plays an Initiating Role in the Pathophysiological Process of the PS1V97L-Tg Mouse Model of Alzheimer's Disease. - Wang, Wei; Lu, Lu; Wu, Qiao-Qi; Jia, Jian-Ping (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) aggregation, tau hyperphosphorylation, oxidative stress, and neuroinflammation are major pathophysiological events in Alzheimer's disease (AD). However, the relationships among these processes and which first exerts an effect are unknown. In the present study, we investigated age-dependent behavioral changes and the sequential pathological progression from the brain to the periphery in AD transgenic (PS1V97L-Tg) mice and their wild-type littermates. We discovered that the brain Aβ significantly increased at 6 months old, the increased brain Aβ caused memory dysfunction, and the ability of Aβ to induce tau hyperphosphorylation might be due to oxidative stress and neuroinflammatory reactions. The levels of Aβ42, total tau (t-tau), oxidative stress parameters, and proinflammatory cytokines in plasma can be used to differentiate between PS1V97L-Tg mice and their wild-type littermates at different time points. Collectively, our findings support the hypothesis that Aβ is a trigger among these pathophysiological processions and show that plasma biomarkers can reflect the condition of the AD brain.

Bridging Integrator 1 (BIN1) Genotypes Mediate Alzheimer's Disease Risk by Altering Neuronal Degeneration. - Wang, Hui-Fu; Wan, Yu; Hao, Xiao-Ke; Cao, Lei; Zhu, Xi-Chen; Jiang, Teng; Tan, Meng-Shan; Tan, Lin; Zhang, Dao-Qiang; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2016)
BACKGROUND: Bridging integrator 1 (BIN1) has been identified as one of the most associated loci for Alzheimer's disease (AD), and recently was reported to modulate tau pathology to mediate AD in vitro. However, the effects of BIN1 on the AD related biomarkers in AD continuum were not specifically assessed. OBJECTIVE: We explored the effects of BIN1 loci on AD specific biomarkers (CSF proteins, brain structures, glucose and amyloid-β (Aβ) metabolisms) to investigate the role BIN1 in AD pathogenesis. METHODS: We calculated the associations of BIN1 loci with these markers at baseline and follow-up in multiple linear models in 812 ADNI subjects. RESULTS: BIN1 loci were significantly associated with the levels of T-tau (rs744373: pc = 0.047, rs13031703: pc = 0.042) and P-tau (rs744373: pc = 0.044, rs13031703: pc = 0.019), but not with Aβ in CSF test. BIN1 genotypes were strongly related to atrophy of hippocampus (rs7561528: pc = 0.011), CA1 (rs1469980: pc = 0.029) and parahippocampus (rs72838284, pc = 0.017) on MRI, and to glucose metabolism on FDG-PET, but not to Aβ deposition on AV45-PET imaging. Furthermore, haplotype and subgroup analysis confirmed these significant findings. In addition, the loci associated with these markers were also identified to influence the risk for AD in the meta-analysis of 74 046 European individuals. CONCLUSION: This study supported that BIN1 contributes to the risk of AD by altering neural degeneration (abnormal tau, brain atrophy and glucose metabolism) but not Aβ pathology.
Keywords: Adaptor Proteins, Signal Transducing; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Brain; Databases, Factual; European Continental Ancestry Group; Female; Follow-Up Studies; Genetic Predisposition to Disease; Glucose; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Nerve Degeneration; Nuclear Proteins; Polymorphism, Single Nucleotide; Positron-Emission Tomography; Risk; tau Proteins; Tumor Suppressor Proteins

Cerebral Glucose Metabolism is Associated with Verbal but not Visual Memory Performance in Community-Dwelling Older Adults. - Gardener, Samantha L; Sohrabi, Hamid R; Shen, Kai-Kai; Rainey-Smith, Stephanie R; Weinborn, Michael; Bates, Kristyn A; Shah, Tejal; Foster, Jonathan K; Lenzo, Nat; Salvado, Olivier; Laske, Christoph; Laws, Simon M; et al. (J Alzheimers Dis, 2016)
Increasing evidence suggests that Alzheimer's disease (AD) sufferers show region-specific reductions in cerebral glucose metabolism, as measured by [18F]-fluoro-2-deoxyglucose positron emission tomography (18F-FDG PET). We investigated preclinical disease stage by cross-sectionally examining the association between global cognition, verbal and visual memory, and 18F-FDG PET standardized uptake value ratio (SUVR) in 43 healthy control individuals, subsequently focusing on differences between subjective memory complainers and non-memory complainers. The 18F-FDG PET regions of interest investigated include the hippocampus, amygdala, posterior cingulate, superior parietal, entorhinal cortices, frontal cortex, temporal cortex, and inferior parietal region. In the cohort as a whole, verbal logical memory immediate recall was positively associated with 18F-FDG PET SUVR in both the left hippocampus and right amygdala. There were no associations observed between global cognition, delayed recall in logical memory, or visual reproduction and 18F-FDG PET SUVR. Following stratification of the cohort into subjective memory complainers and non-complainers, verbal logical memory immediate recall was positively associated with 18F-FDG PET SUVR in the right amygdala in those with subjective memory complaints. There were no significant associations observed in non-memory complainers between 18F-FDG PET SUVR in regions of interest and cognitive performance. We observed subjective memory complaint-specific associations between 18F-FDG PET SUVR and immediate verbal memory performance in our cohort, however found no associations between delayed recall of verbal memory performance or visual memory performance. It is here argued that the neural mechanisms underlying verbal and visual memory performance may in fact differ in their pathways, and the characteristic reduction of 18F-FDG PET SUVR observed in this and previous studies likely reflects the pathophysiological changes in specific brain regions that occur in preclinical AD.

Cerebral Small Vessel Disease and Motoric Cognitive Risk Syndrome: Results from the Kerala-Einstein Study. - Wang, Nan; Allali, Gilles; Kesavadas, Chandrasekharan; Noone, Mohan L; Pradeep, Vayyattu G; Blumen, Helena M; Verghese, Joe (J Alzheimers Dis, 2016)
BACKGROUND: The contribution of cerebral small vessel disease to cognitive decline, especially in non-Caucasian populations, is not well established. OBJECTIVE: We examined the relationship between cerebral small vessel disease and motoric cognitive risk syndrome (MCR), a recently described pre-dementia syndrome, in Indian seniors. METHODS: 139 participants (mean age 66.6 ± 5.4 y, 33.1% female) participating in the Kerala-Einstein study in Southern India were examined in a cross-sectional study. The presence of cerebral small vessel disease (lacunar infarcts and cerebral microbleeds (CMB)) and white matter hyperintensities on MRI was ascertained by raters blinded to clinical information. MCR was defined by the presence of cognitive complaints and slow gait in older adults without dementia or mobility disability. RESULTS: Thirty-eight (27.3%) participants met MCR criteria. The overall prevalence of lacunar infarcts and CMB was 49.6% and 9.4% , respectively. Lacunar infarcts in the frontal lobe, but no other brain regions, were associated with MCR even after adjusting for vascular risk factors and presence of white matter hyperintensities (adjusted Odds Ratio (aOR): 4.67, 95% CI: 1.69-12.94). Frontal lacunar infarcts were associated with slow gait (aOR: 3.98, 95% CI: 1.46-10.79) and poor performance on memory test (β: -1.24, 95% CI: -2.42 to -0.05), but not with cognitive complaints or non-memory tests. No association of CMB was found with MCR, individual MCR criterion or cognitive tests. CONCLUSIONS: Frontal lacunar infarcts are associated with MCR in Indian seniors, perhaps, by contributing to slow gait and poor memory function.
Keywords: Aged; Brain; Cerebral Small Vessel Diseases; Cognition Disorders; Female; Humans; Image Processing, Computer-Assisted; India; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Risk Factors; Stroke, Lacunar; White Matter

Cerebrospinal Fluid Alzheimer's Disease Biomarkers Across the Spectrum of Lewy Body Diseases: Results from a Large Multicenter Cohort. - van Steenoven, Inger; Aarsland, Dag; Weintraub, Daniel; Londos, Elisabet; Blanc, Frédéric; van der Flier, Wiesje M; Teunissen, Charlotte E; Mollenhauer, Brit; Fladby, Tormod; Kramberger, Milica G; Bonanni, Laura; Lemstra, Afina W (J Alzheimers Dis, 2016)
BACKGROUND: Concomitant Alzheimer's disease (AD) pathology is observed in Lewy body diseases (LBD), but the clinical impact is unknown. Only a few biomarker studies in LBD exist and have included small cohorts from single centers. OBJECTIVE: We aimed to evaluate the prevalence of abnormal cerebrospinal fluid (CSF) AD biomarkers across the spectrum of LBD in a large multicenter cohort and to assess whether an AD biomarker profile was associated with demographic and clinical differences in dementia with Lewy bodies (DLB). METHODS: We included 375 DLB patients, 164 Parkinson's disease (PD) patients without dementia, and 55 PD patients with dementia (PDD) from 10 centers. CSF amyloid-beta42 (Aβ42), total tau (t-tau), and phosphorylated tau (p-tau) values were dichotomized as abnormal or normal according to locally available cut-off values. A CSF AD profile was defined as abnormal Aβ42 combined with abnormal t-tau and/or p-tau. RESULTS: A substantial proportion of DLB patients had abnormal values for CSF Aβ42, t-tau, and p-tau, while abnormal values were uncommon in PD without dementia. Patients with PDD had values in between. A CSF AD profile was observed in 25% of DLB patients, compared with only 9% of PDD and 3% of PD without dementia. Within DLB, patients with a CSF AD profile were older, more often female, performed worse on the Mini-Mental State Examination, and had shorter disease duration compared with patients with normal CSF. CONCLUSION: A CSF AD profile is more common in DLB compared with PDD and PD, and is associated with more severe cognitive impairment in DLB.

Cerebrospinal Fluid Alzheimer's Disease Biomarkers in Cerebral Amyloid Angiopathy-Related Inflammation. - Renard, Dimitri; Wacongne, Anne; Ayrignac, Xavier; Charif, Mahmoud; Fourcade, Genevieve; Azakri, Souhayla; Le Floch, Anne; Bouly, Stephane; Marelli, Cecilia; Arquizan, Caroline; Hirtz, Christophe; Gabelle, Audrey; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Decreased cerebrospinal fluid (CSF) amyloid-β 1-40 (Aβ40) and amyloid-β 1-42 (Aβ42) and increased total and phosphorylated tau (t-tau, p-tau) concentrations have been described in cerebral amyloid angiopathy (CAA). OBJECTIVE: Our aim was to analyze these biomarkers in patients with CAA-related inflammation (CAA-I). METHODS: We prospectively recruited nine patients with acute phase CAA-I fulfilling Chung criteria. CSF was analyzed for t-tau, p-tau, Aβ42, and Aβ40. Data were compared to controls (n = 14), patients with Alzheimer's disease (AD, n = 42), CAA (n = 10), and primary angiitis of the central nervous system (PACNS, n = 3). RESULTS: For the CAA-I group, statistically significant differences were: lower Aβ42 (p = 0.00053) compared to the control group; lower t-tau (p = 0.018), p-tau (p <  0.001), and Aβ40 (p <  0.001) compared to AD; lower Aβ42 (p = 0.027) compared to CAA; lower Aβ42 (p = 0.012) compared to PACNS. Nearly significantly lower Aβ40 (p = 0.051) and higher t-tau (p = 0.051) were seen in CAA-I compared to controls. CONCLUSION: CSF biomarkers profile similar to that of CAA was observed in CAA-I (with even lower levels of Aβ42 compared to CAA). Based on our findings, high p-tau seems more specific for AD, whereas low Aβ42 differentiates CAA-I from CAA, PACNS, and controls, and low Aβ40 differentiates CAA-I from AD.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cerebral Amyloid Angiopathy; Female; Humans; Inflammation; Male; Middle Aged; Retrospective Studies; tau Proteins

Cerebrospinal Fluid Fatty Acid-Binding Protein 3 is Related to Dementia Development in a Population-Based Sample of Older Adult Women Followed for 8 Years. - Bjerke, Maria; Kern, Silke; Blennow, Kaj; Zetterberg, Henrik; Waern, Margda; Börjesson-Hanson, Anne; Östling, Svante; Kern, Jürgen; Skoog, Ingmar (J Alzheimers Dis, 2016)
BACKGROUND: Increased fatty acid-binding protein 3 (FABP-3) levels have been reported in neurodegenerative diseases, including Alzheimer's disease (AD). Cerebrospinal fluid (CSF) FABP-3 has therefore been proposed as a putative marker for dementia. Population-based studies examining whether CSF FABP-3 predicts later development of dementia are lacking. OBJECTIVE: The aim of this study was to examine CSF levels of FABP-3 in relation to later development of dementia in elderly women and in relation to Aβ42, T-tau, P-tau181, and CSF: serum albumin ratio. METHODS: 86 non-demented women aged 70-84 years who participated in the Prospective Population Study of Women in Gothenburg, Sweden took part in a lumbar puncture in 1992-93. CSF-FABP-3, Aβ42, T-tau, P-tau181, and the CSF: serum albumin ratio were measured at baseline. Participants were examined with a neuropsychiatric exam at baseline and at follow-up in 2000. Dementia was diagnosed in accordance with DSM-III-R criteria. RESULTS: Between 1992 and 2000, 8 women developed dementia (4 AD, 3 vascular dementia, 1 mixed vascular dementia and AD). Higher levels of CSF-FABP-3 at baseline were related to development of dementia (OR 1.36 CI [1.05-1.76] p = 0.022) and the subtype AD (OR 1.38 CI [1.06-1.82), p = 0.019) during follow-up. FABP-3 correlated with CSF T-tau (r = 0.88, p <  0.001), P-tau181 (r = 0.619, p <  0.001), and CSF:serum albumin ratio (r = 0.233, p = 0.031), but not with Aβ42 (r = -0.08, p = 0.444)CONCLUSION:CSF FABP-3 may be an early marker for later development of dementia, probably related to neuronal degeneration, but independent of Aβ metabolism.
Keywords: Aged; Aged, 80 and over; Albumins; Amyloid beta-Peptides; Community Health Planning; Dementia; Fatty Acid-Binding Proteins; Female; Humans; Longitudinal Studies; Peptide Fragments; Sweden; tau Proteins

Changes in Brain Volume with Bapineuzumab in Mild to Moderate Alzheimer's Disease. - Novak, Gerald; Fox, Nick; Clegg, Shona; Nielsen, Casper; Einstein, Steven; Lu, Yuan; Tudor, Iulia Cristina; Gregg, Keith; Di, Jianing; Collins, Peter; Wyman, Bradley T; Yuen, Eric; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Bapineuzumab, an anti-amyloid-β monoclonal antibody, was evaluated in two placebo-controlled trials in APOE*ɛ4 carriers and noncarriers, respectively, with Alzheimer's disease. OBJECTIVES: A volumetric magnetic resonance imaging substudy was performed to determine if bapineuzumab altered brain volume rate of change. METHODS: Bapineuzumab dosages included 0.5 mg/kg in carriers and 0.5 or 1.0 mg/kg in noncarriers, every 13 weeks for 78 weeks. Volumetric outcomes included annualized brain, ventricular, and mean hippocampal boundary shift integrals (BBSI; VBSI; HBSI) up to Week 71. Treatment differences were estimated using mixed models for repeated measures. RESULTS: For BBSI and HBSI, there were no significant treatment-related differences within either study, but, compared to pooled carriers and noncarriers receiving placebo, noncarriers receiving1.0 mg/kg bapineuzumab had greater increases in these measures. Bapineuzumab-treated patients showed significantly greater VBSI rates compared with placebo for 0.5 mg/kg in carriers and 1.0 mg/kg (but not 0.5 mg/kg) in noncarriers. CONCLUSIONS: Bapineuzumab produced an increase in ventricular volume compared with placebo. Etiology for this increase is unclear but may be related to amyloid-β clearance or its consequences.
Keywords: Aged; Alzheimer Disease; Antibodies, Monoclonal, Humanized; Apolipoprotein E4; Brain; Double-Blind Method; Female; Heterozygote; Humans; Least-Squares Analysis; Magnetic Resonance Imaging; Male; Nootropic Agents; Organ Size; Severity of Illness Index; Treatment Outcome

Changes in Frailty Predict Changes in Cognition in Older Men: The Honolulu-Asia Aging Study. - Armstrong, Joshua J; Godin, Judith; Launer, Lenore J; White, Lon R; Mitnitski, Arnold; Rockwood, Kenneth; Andrew, Melissa K (J Alzheimers Dis, 2016)
BACKGROUND: As cognitive decline mostly occurs in late life, where typically it co-exists with many other ailments, it is important to consider frailty in understanding cognitive change. OBJECTIVE: Here, we examined the association of change in frailty status with cognitive trajectories in a well-studied cohort of older Japanese-American men. METHODS: Using the prospective Honolulu-Asia Aging Study (HAAS), 2,817 men of Japanese descent were followed (aged 71-93 at baseline). Starting in 1991 with follow-up health assessments every two to three years, cognition was measured using the Cognitive Abilities Screening Instrument (CASI). For this study, health data was used to construct an accumulation of deficits frailty index (FI). Using six waves of data, multilevel growth curve analyses were constructed to examine simultaneous changes in cognition in relation to changes in FI, controlling for baseline frailty, age, education, and APOE-ɛ4 status. RESULTS: On average, CASI scores declined by 2.0 points per year (95% confidence interval 1.9-2.1). Across six waves, each 10% within-person increase in frailty from baseline was associated with a 5.0 point reduction in CASI scores (95% confidence interval 4.7-5.2). Baseline frailty and age were associated both with lower initial CASI scores and with greater decline across the five follow-up assessments (p < 0.01). DISCUSSION: Cognition is adversely affected by impaired health status in old age. Using a multidimensional measure of frailty, both baseline status and within-person changes in frailty were predictive of cognitive trajectories.

Changes of Cerebral Perfusion and Functional Brain Network Organization in Patients with Mild Cognitive Impairment. - Lou, Wutao; Shi, Lin; Wong, Adrian; Chu, Winnie C W; Mok, Vincent C T; Wang, Defeng (J Alzheimers Dis, 2016)
Disruptions of the functional brain network and cerebral blood flow (CBF) have been revealed in patients with mild cognitive impairment (MCI). However, the neurophysiological mechanism of hypoperfusion as well as the reorganization of the intrinsic whole brain network due to the neuropathology of MCI are still unclear. In this study, we aimed to investigate the changes of CBF and the whole brain network organization in MCI by using a multimodal MRI approach. Resting state ASL MRI and BOLD MRI were used to evaluate disruptions of CBF and underlying functional connectivity in 27 patients with MCI and 35 cognitive normal controls (NC). The eigenvector centrality mapping (ECM) was used to assess the whole brain network reorganization in MCI, and a seed-based ECM approach was proposed to reveal the contributions of the whole brain network on the ECM alterations. Significantly decreased perfusion in the posterior parietal cortex as well as its connectivity within the default mode network and occipital cortex were found in the MCI group compared to the NC group. The ECM analysis revealed decreased EC in the middle cingulate cortex, parahippocampal gyrus, medial frontal gyrus, and increased EC in the right calcarine sulcus, superior temporal gyrus, and supplementary motor area in the MCI group. The results of this study indicate that there are deficits in cerebral blood flow and functional connectivity in the default mode network, and that sensory-processing networks might play a compensatory role to make up for the decreased connections in MCI.

Characterizing White Matter Tract Degeneration in Syndromic Variants of Alzheimer's Disease: A Diffusion Tensor Imaging Study. - Madhavan, Ajay; Schwarz, Christopher G; Duffy, Joseph R; Strand, Edythe A; Machulda, Mary M; Drubach, Daniel A; Kantarci, Kejal; Przybelski, Scott A; Reid, Robert I; Senjem, Matthew L; Gunter, Jeffrey L; Apostolova, Liana G; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Different clinical syndromes can arise from Alzheimer's disease (AD) neuropathology, including dementia of the Alzheimer's type (DAT), logopenic primary progressive aphasia (lvPPA), and posterior cortical atrophy (PCA). OBJECTIVE: To assess similarities and differences in patterns of white matter tract degeneration across these syndromic variants of AD. METHODS: Sixty-four subjects (22 DAT, 24 lvPPA, and 18 PCA) that had diffusion tensor imaging and showed amyloid-β deposition on PET were assessed in this case-control study. A whole-brain voxel-based analysis was performed to assess differences in fractional anisotropy, mean diffusivity, axial diffusivity, and radial diffusivity across groups. RESULTS: All three groups showed overlapping diffusion abnormalities in a network of tracts, including fornix, corpus callosum, posterior thalamic radiations, superior longitudinal fasciculus, inferior longitudinal fasciculus, inferior fronto-occipital fasciculus, and uncinate fasciculus. Subtle regional differences were also observed across groups, with DAT particularly associated with degeneration of fornix and cingulum, lvPPA with left inferior fronto-occipital fasciculus and uncinate fasciculus, and PCA with posterior thalamic radiations, superior longitudinal fasciculus, posterior cingulate, and splenium of the corpus callosum. CONCLUSION: These findings show that while each AD phenotype is associated with degeneration of a specific structural network of white matter tracts, striking spatial overlap exists among the three network patterns that may be related to AD pathology.
Keywords: Aged; Alzheimer Disease; Aniline Compounds; Anisotropy; Aphasia, Primary Progressive; Case-Control Studies; Diffusion Tensor Imaging; Female; Humans; Image Processing, Computer-Assisted; Male; Middle Aged; Nerve Fibers, Myelinated; Neurodegenerative Diseases; Neuropsychological Tests; Positron-Emission Tomography; Psychiatric Status Rating Scales; Retrospective Studies; Thiazoles; White Matter

Cholesterol, 24-Hydroxycholesterol, and 27-Hydroxycholesterol as Surrogate Biomarkers in Cerebrospinal Fluid in Mild Cognitive Impairment and Alzheimer's Disease: A Meta-Analysis. - Wang, Hua-Long; Wang, Yan-Yong; Liu, Xin-Gang; Kuo, Sheng-Han; Liu, Na; Song, Qiao-Yun; Wang, Ming-Wei (J Alzheimers Dis, 2016)
Abnormal cholesterol metabolism is an established feature of Alzheimer's disease (AD). Cerebrospinal fluid (CSF) is the fluid surrounding the central nervous system, and the protein and lipid content alterations in the CSF could be biomarkers for degenerative changes in the brain. The laboratory diagnosis of AD is limited to the analysis of three biomarkers in CSF: Aβ42, total tau, and phospho-tau. The purpose of this analysis is to systematically analyze the available data describing the biomarkers of cholesterol and its metabolites in the CSF of subjects with AD. MEDLINE, EMBASE, and the Cochrane Central database were systematically queried to collect studies that have evaluated the markers of cholesterol and its metabolites in the CSF of subjects with mild cognitive impairment (MCI) or AD and age-matched controls. Analysis of the published data shows that the levels of cholesterol are increased in MCI subjects; 24-hydroxycholesterol and 27-hydroxycholesterol are elevated in AD and MCI subjects compared to controls. There is a significant dysfunction of cholesterol metabolism in the CSF of AD subjects. This analysis indicates that in addition to the available biomarkers in the CSF, such as Aβ42, total tau, and phospho-tau, 24-hydroxycholesterol, 27-hydroxycholesterol, and cholesterol appear to be sensitive biomarkers for the evaluation of MCI and AD.
Keywords: Alzheimer Disease; Cholesterol; Cognitive Dysfunction; Databases, Bibliographic; Humans; Hydroxycholesterols

Cholesteryl Ester Transfer Protein Intimately Involved in Dyslipidemia-Related Susceptibility to Cognitive Deficits in Type 2 Diabetic Patients. - Sun, Jie; Cai, Rongrong; Huang, Rong; Wang, Pin; Tian, Sai; Sun, Haixia; Xia, Wenqing; Wang, Shaohua (J Alzheimers Dis, 2016)
BACKGROUND: Cholesteryl ester transfer protein (CETP) is involved in diabetic dyslipidemia. OBJECTIVE: We aim to test the hypothesis that CETP might be of importance in mediating dyslipidemia-related susceptibility to cognitive deficits in diabetic patients. METHODS: We recruited 190 type 2 diabetic patients and divided them into two groups according to the Montreal Cognitive Assessment (MoCA) score. The association between CETP and cognitive decline was analyzed with logistic regression and stratification. RESULTS: There were 110 diabetic patients with mild cognition impairment (MCI) and 80 healthy cognition subjects as controls. Dyslipidemia is more common among diabetic patients with MCI; they had a significant increase of serum CETP concentrations, which was negatively correlated with MoCA (r = -0.638; p < 0.001). Negative correlations were also found between the serum CETP concentration with the Auditory Verbal Learning Test (r = -0.266; p = 0.008), indicating memory deficit. Logistic regression analysis revealed that CETP concentration was an independent factor of diabetic MCI (p < 0.001). Further stratification study showed that high serum levels of CETP was an independent risk factor of MCI in diabetic patients with a low density lipoproteins level ≥2.59 mmol/L, or high density lipoproteins level ≤1.0 mmol/L for men and ≤1.3 mmol/L for women, or TG level ≥1.7 mmol/L, after adjusting for age, sex, education, and glucose control (all ps < 0.05). CONCLUSIONS: CETP was intimately involved in dyslipidemia-related susceptibility to cognitive decline, especially memory function in type 2 diabetic patients.

Chronic Stress Aggravates Cognitive Impairment and Suppresses Insulin Associated Signaling Pathway in APP/PS1 Mice. - Han, Bing; Yu, Lulu; Geng, Yuan; Shen, Li; Wang, Hualong; Wang, Yanyong; Wang, Jinhua; Wang, Mingwei (J Alzheimers Dis, 2016)
Differences in brain function are a central determinant of individual variability in the stress response. Brain dysfunction, resulting from aging, illness, or genetic mutations, could reduce the tolerance of glucocorticoid stress hormones. When glucocorticoids exceed tolerable limits in the brain, especially in the hippocampus, this state can cause or aggravate structural or functional damage. However, the underlying mechanisms are not well understood. This study investigated the effects of chronic unpredictable mild stress (CUMS) in APP/PS1 and control mice. We showed that 4 weeks of CUMS exposure increased the levels of glucocorticoids, reduced glucocorticoids receptor expression, and promoted senile plaque deposition, neuronal injury, and cognitive impairment in APP/PS1 mice compared to controls. The phosphorylation of insulin receptor, insulin receptor substrate 1 and associated signaling pathways (Akt, mTOR, p70S6K, ERK1/2, and PTEN) were decreased in hippocampus in APP/PS1 mice compared to control mice, while no changes were found in GSK3 and TSC2 phosphorylation. Furthermore, insulin and Akt/mTOR signaling pathways were further decreased in APP/PS1 mice after CUMS, which may be related to the activation of the stress-activated protein kinase JNK, while no alterations in the levels of phosphorylated ERK1/2, GSK3, PTEN, or TSC2 were observed. These results suggest that chronic stress may affect the insulin and Akt/mTOR pathway, accelerating the progression of Alzheimer's disease in vulnerable individuals.

Circulating microRNAs as Biomarkers of Alzheimer's Disease: A Systematic Review. - Wu, Helen Zong Ying; Ong, Kwok Leung; Seeher, Katrin; Armstrong, Nicola J; Thalamuthu, Anbupalam; Brodaty, Henry; Sachdev, Perminder; Mather, Karen (J Alzheimers Dis, 2016)
BACKGROUND: In recent years, microRNAs (miRNA), a class of non-coding RNA known to regulate protein expression post-transcriptionally, have been recognized as novel biomarkers of diseases. OBJECTIVE: In this systematic review, we identify miRNAs that are differentially expressed in Alzheimer's disease (AD) and/or mild cognitive impairment (MCI) and evaluate their accuracy as potential blood biomarkers. METHODS: Eligible studies of miRNAs in peripheral blood distinguishing patients with AD or MCI from cognitively normal controls were identified through standardized search strategies in Medline, PubMed, and Embase. MiRNAs that were differentially expressed were identified and where available their sensitivity and specificity for AD or MCI extracted from the retrieved studies. RESULTS: Eighteen studies investigated the diagnostic value of miRNAs as peripheral biomarkers of AD/MCI. Twenty miRNAs were significantly upregulated and 32 miRNAs downregulated in AD compared to controls in ten AD studies. Nine miRNAs were consistently dysregulated in more than one study. Of the 8 MCI studies, only one miRNA, miR-132, was consistently upregulated in three independent studies. Of the studies that reported diagnostic accuracy data, the majority of miRNA panels and individual miRNAs had a sensitivity and specificity greater than 0.75. CONCLUSION: Individual studies suggest that miRNAs can differentiate patients with AD/MCI from cognitively normal controls with modest accuracy. However, the literature is constrained by methodological differences between studies, with few studies assessing the same miRNAs. To become potential biomarkers for AD, further studies with standardized study designs for replication and validation are required. Results from this review may help researchers select candidate miRNAs for further investigation.
Keywords: Alzheimer Disease; Biomarkers; Databases, Bibliographic; Humans; MicroRNAs

Clinical Application of Automatic Segmentation of Medial Temporal Lobe Subregions in Prodromal and Dementia-Level Alzheimer's Disease. - Gertje, Eske Christiane; Pluta, John; Das, Sandhitsu; Mancuso, Lauren; Kliot, Dasha; Yushkevich, Paul; Wolk, David (J Alzheimers Dis, 2016)
BACKGROUND: Volumetry of medial temporal lobe (MTL) structures to diagnose Alzheimer's disease (AD) in its earliest symptomatic stage could be of great importance for interventions or disease modifying pharmacotherapy. OBJECTIVE: This study aimed to demonstrate the first application of an automatic segmentation method of MTL subregions in a clinical population. Automatic segmentation of magnetic resonance images (MRIs) in a research population has previously been shown to detect evidence of neurodegeneration in MTL subregions and to help discriminate AD and mild cognitive impairment (MCI) from a healthy comparison group. METHODS: Clinical patients were selected and T2-weighted MRI scan quality was checked. An automatic segmentation method of hippocampal subfields (ASHS) was applied to scans of 67 AD patients, 38 amnestic MCI patients, and 57 healthy controls. Hippocampal subfields, entorhinal cortex (ERC), and perirhinal cortex were automatically labeled and subregion volumes were compared between groups. RESULTS: One fourth of all scans were excluded due to bad scan quality. There were significant volume reductions in all subregions, except BA36, in aMCIs (p < 0.001), most prominently in Cornu Ammonis 1 (CA1) and ERC, and in all subregions in AD. However, sensitivity of CA1 and ERC hardly differed from sensitivity of WH in aMCI and AD. CONCLUSION: Applying automatic segmentation of MTL subregions in a clinical setting as a potential biomarker for prodromal AD is feasible, but issues of image quality due to motion remain to be addressed. CA1 and ERC provided strongest group discrimination in differentiating aMCIs from controls, but discriminatory power of different subfields was low overall.

Cohort Effects in the Prevalence and Survival of People with Dementia in a Rural Area in Northern Sweden. - Wimo, Anders; Sjölund, Britt-Marie; Sköldunger, Anders; Qiu, Chengxuan; Klarin, Inga; Nordberg, Gunilla; von Strauss, Eva (J Alzheimers Dis, 2016)
BACKGROUND: Recent studies suggest that trends in cardiovascular risk may result in a decrease in age-specific prevalence of dementia. Studies in rural areas are rare. OBJECTIVES: To study cohort effects in dementia prevalence and survival of people with dementia in a Swedish rural area. METHODS: Participants were from the 1995-1998 Nordanstig Project (NP) (n = 303) and the 2001-2003 Swedish National study on Aging and Care in Nordanstig (SNAC-N) (n = 384). Overall 6-year dementia prevalence and mortality in NP and SNAC-N were compared for people 78 years and older. Logistic regression analyses were used to calculate odds ratios (ORs) and 95% confidence intervals (CIs) for dementia occurrence using the NP study population as the reference group. Cox regression models were used to analyze time to death. RESULTS: The crude prevalence of dementia was 21.8% in NP and 17.4% in SNAC-N. When the NP cohort was used as the reference group, the age- and gender-adjusted OR of dementia was 0.71 (95% CI 0.48-1.04) in SNAC-N; the OR was 0.47 (0.24-0.90) for men and 0.88 (0.54-1.44) for women. In the extended model, the OR of dementia was significantly lower in SNAC-N than in the NP cohort as a whole (0.63; 0.39-0.99) and in men (0.34; 0.15-0.79), but not in women (0.81; 0.46-1.44). The Cox regression models indicated that the hazard ratio of dying was lower in the SNAC-N than NP population. CONCLUSIONS: Trends toward a lower prevalence of dementia in high-income countries seem to be evident in this Swedish rural area, at least in men.
Keywords: Aged; Aged, 80 and over; Aging; Cohort Effect; Dementia; Female; Humans; Male; Prevalence; Risk Factors; Rural Population; Sex Factors; Survival Rate; Sweden

Cohort Study on Predictors of Need for Nursing Care in Alzheimer's Disease: An Analysis of Healthcare Data. - Brüggenjürgen, Bernd; Andersohn, Frank; Burkowitz, Jörg; Ezzat, Nadja; Gaudig, Maren; Willich, Stefan N (J Alzheimers Dis, 2016)
BACKGROUND: The individual and societal burden of Alzheimer's disease (AD) is substantial. Identifying relevant factors deteriorating AD and inducing need for nursing care would be of high relevance for healthcare planning. OBJECTIVE: The main objective of this study was the identification of predictors of first assignment of a level of long-term care in AD, used as an approximation for disease progression. METHODS: In a retrospective cohort study using data from a large German statutory health and long-term care insurance (SHI) company, co-morbidities and drug exposure were evaluated with respect to their predictive value for disease progression (first day the amount of daily nursing care exceeded 1.5 hours). Time to disease progression was modeled using COX-proportional hazard regression with stepwise selection of predictor variables. RESULTS: The risk of nursing care need increased substantially with increasing age. Number of hospitalizations and number of different drugs used were significant indicators for progression, whereas outpatient visits were associated with a reduced need for care. Gender did not indicate significant influence on progression. Malignant neoplasms of ill-defined, secondary, and unspecified sites, malnutrition, renal failure, and injuries increased the risk of need for nursing care most significantly. Among prescribed drugs, significant increased risks were associated with drugs used in diabetes, preparations for treatment of wounds and ulcers, antiseptics and disinfectants, and analgesics. CONCLUSIONS: Physical comorbidities are relevant contributors to an increase in need for nursing care. Some medical predicting conditions may be linked to cognition, while others may be directly linked to demand for care. AD patients with these comorbidities should be monitored with special attention, as they may be under an increased risk of care dependency.

Combination of Structural MRI and FDG-PET of the Brain Improves Diagnostic Accuracy in Newly Manifested Cognitive Impairment in Geriatric Inpatients. - Ritter, Kerstin; Lange, Catharina; Weygandt, Martin; Mäurer, Anja; Roberts, Anna; Estrella, Melanie; Suppa, Per; Spies, Lothar; Prasad, Vikas; Steffen, Ingo; Apostolova, Ivayla; Bittner, Daniel; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The cause of cognitive impairment in acutely hospitalized geriatric patients is often unclear. The diagnostic process is challenging but important in order to treat potentially life-threatening etiologies or identify underlying neurodegenerative disease. OBJECTIVE: To evaluate the add-on diagnostic value of structural and metabolic neuroimaging in newly manifested cognitive impairment in elderly geriatric inpatients. METHODS: Eighty-one inpatients (55 females, 81.6±5.5 y) without history of cognitive complaints prior to hospitalization were recruited in 10 acute geriatrics clinics. Primary inclusion criterion was a clinical hypothesis of Alzheimer's disease (AD), cerebrovascular disease (CVD), or mixed AD+CVD etiology (MD), which remained uncertain after standard diagnostic workup. Additional procedures performed after enrollment included detailed neuropsychological testing and structural MRI and FDG-PET of the brain. An interdisciplinary expert team established the most probable etiologic diagnosis (non-neurodegenerative, AD, CVD, or MD) integrating all available data. Automatic multimodal classification based on Random Undersampling Boosting was used for rater-independent assessment of the complementary contribution of the additional diagnostic procedures to the etiologic diagnosis. RESULTS: Automatic 4-class classification based on all diagnostic routine standard procedures combined reproduced the etiologic expert diagnosis in 31% of the patients (p = 0.100, chance level 25%). Highest accuracy by a single modality was achieved by MRI or FDG-PET (both 45%, p≤0.001). Integration of all modalities resulted in 76% accuracy (p≤0.001). CONCLUSION: These results indicate substantial improvement of diagnostic accuracy in uncertain de novo cognitive impairment in acutely hospitalized geriatric patients with the integration of structural MRI and brain FDG-PET into the diagnostic process.

Community-Dwelling People Screened Positive for Dementia in Primary Care: A Comprehensive, Multivariate Descriptive Analysis Using Data from the DelpHi-Study. - Thyrian, Jochen René; Eichler, Tilly; Michalowsky, Bernhard; Wucherer, Diana; Reimann, Melanie; Hertel, Johannes; Richter, Steffen; Dreier, Adina; Hoffmann, Wolfgang (J Alzheimers Dis, 2016)
BACKGROUND: Efficient help and care for people with dementia (PWD) is dependent on knowledge about PWD in primary care. OBJECTIVE: This analysis comprehensively describes community-dwelling PWD in primary care with respect to various dementia care specific variables. METHODS: The analyses are based on baseline data of the ongoing general practitioner-based, randomized, controlled intervention trial DelpHi-MV (Dementia: life- and person-centered help). 6,838 patients were screened for dementia in 136 GP practices; 17.1% were screened positive, 54.4% of those agreed to participate and data could be assessed in n = 516 subjects. We assessed age, sex, living situation, cognitive status, functional status, level of impairment, comorbidities, formal diagnosis of dementia, depression, neuropsychiatric symptoms, quality of life, utilization of medical support, and pharmacological therapy. RESULTS: Concerning clinical-, dementia-, and health-related variables, the sample under examination was on average mildly cognitively and functionally impaired (MMSE, m = 22.2; BADL, m = 3.7). A level of care was assigned in 38.0%. Depression was identified in 15.4% and other frequent comorbidities were high blood pressure (83.3%), coronary heart diseases (37.1%), cerebrovascular diseases (22.3%), among others. In 48.6%, neuropsychiatric symptoms were present in a clinically relevant severity. Pharmacological treatment with antidementia medication was received by 25.8% and antidepressant medication by 14.0%. Utilization of services was generally low. CONCLUSION: The comprehensive description of people screened positive for dementia in primary care reveals a complex and unique population of patients. They are considerably underdiagnosed and in their majority mildly to moderately affected. More in-depth analyses are needed to study relations, associations and interactions between different variables.

Comparison of Different Matrices as Potential Quality Control Samples for Neurochemical Dementia Diagnostics. - Lelental, Natalia; Brandner, Sebastian; Kofanova, Olga; Blennow, Kaj; Zetterberg, Henrik; Andreasson, Ulf; Engelborghs, Sebastiaan; Mroczko, Barbara; Gabryelewicz, Tomasz; Teunissen, Charlotte; Mollenhauer, Brit; Parnetti, Lucilla; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Assay-vendor independent quality control (QC) samples for neurochemical dementia diagnostics (NDD) biomarkers are so far commercially unavailable. This requires that NDD laboratories prepare their own QC samples, for example by pooling leftover cerebrospinal fluid (CSF) samples. OBJECTIVE: To prepare and test alternative matrices for QC samples that could facilitate intra- and inter-laboratory QC of the NDD biomarkers. METHODS: Three matrices were validated in this study: (A) human pooled CSF, (B) Aβ peptides spiked into human prediluted plasma, and (C) Aβ peptides spiked into solution of bovine serum albumin in phosphate-buffered saline. All matrices were tested also after supplementation with an antibacterial agent (sodium azide). We analyzed short- and long-term stability of the biomarkers with ELISA and chemiluminescence (Fujirebio Europe, MSD, IBL International), and performed an inter-laboratory variability study. RESULTS: NDD biomarkers turned out to be stable in almost all samples stored at the tested conditions for up to 14 days as well as in samples stored deep-frozen (at - 80°C) for up to one year. Sodium azide did not influence biomarker stability. Inter-center variability of the samples sent at room temperature (pooled CSF, freeze-dried CSF, and four artificial matrices) was comparable to the results obtained on deep-frozen samples in other large-scale projects. CONCLUSION: Our results suggest that it is possible to replace self-made, CSF-based QC samples with large-scale volumes of QC materials prepared with artificial peptides and matrices. This would greatly facilitate intra- and inter-laboratory QC schedules for NDD measurements.
Keywords: Amyloid beta-Peptides; Animals; Anti-Bacterial Agents; Biomarkers; Cattle; Clinical Chemistry Tests; Dementia; Humans; Peptide Fragments; Quality Control; Reference Standards; Serum Albumin, Bovine; Sodium Azide; tau Proteins; Time Factors; Tissue Preservation

Comparison of Prefrontal Atrophy and Episodic Memory Performance in Dysexecutive Alzheimer's Disease and Behavioral-Variant Frontotemporal Dementia. - Wong, Stephanie; Bertoux, Maxime; Savage, Greg; Hodges, John R; Piguet, Olivier; Hornberger, Michael (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) sometimes presents with prominent executive dysfunction and associated prefrontal cortex atrophy. The impact of such executive deficits on episodic memory performance as well as their neural correlates in AD, however, remains unclear. The aim of the current study was to investigate episodic memory and brain atrophy in AD patients with relatively spared executive functioning (SEF-AD; n = 12) and AD patients with relatively impaired executive functioning (IEF-AD; n = 23). We also compared the AD subgroups with a group of behavioral-variant frontotemporal dementia patients (bvFTD; n = 22), who typically exhibit significant executive deficits, and age-matched healthy controls (n = 38). On cognitive testing, the three patient groups showed comparable memory profiles on standard episodic memory tests, with significant impairment relative to controls. Voxel-based morphometry analyses revealed extensive prefrontal and medial temporal lobe atrophy in IEF-AD and bvFTD, whereas this was limited to the middle frontal gyrus and hippocampus in SEF-AD. Moreover, the additional prefrontal atrophy in IEF-AD and bvFTD correlated with memory performance, whereas this was not the case for SEF-AD. These findings indicate that IEF-AD patients show prefrontal atrophy in regions similar to bvFTD, and suggest that this contributes to episodic memory performance. This has implications for the differential diagnosis of bvFTD and subtypes of AD.
Keywords: Aged; Alzheimer Disease; Atrophy; Databases, Factual; Diagnosis, Differential; Executive Function; Female; Frontotemporal Dementia; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Memory, Episodic; Middle Aged; Neuropsychological Tests; Prefrontal Cortex

Concanavalin agglutinin levels are decreased in peripheral blood of Alzheimer's disease patients. - Sun, Xuying; Ma, Ronghong; Yao, Xiuqing; Shang, Xiaoling; Wang, Qun; Wang, Jian-Zhi; Liu, Gongping (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) seriously threatens patients' lives and causes severe burden to the families. Early prevention and treatment can alleviate the development of the disease; therefore it is important to find new effective and non-traumatic biomarkers for early diagnosis. In this study, peripheral blood samples were collected from 24 AD patients and the same number of age- and gender-matched control subjects. Lectin reactive glycosylation levels including beta-D-galactosyl ricinus communis agglutinin 120 (RCA), peanut agglutinin (PNA), concanavalin agglutinin (Con A), alpha-L-fucosyl ulex europeus agglutinin (UEA), dolichos biflorus agglutinin (DBA), and galanthus nivalis (GNL), in the red blood cells of peripheral blood were examined by western blotting. We found that lectin levels were altered with aging and gender; some lectin levels were different between AD patients and the control subjects. Only Con A levels were significantly decreased in AD patients compared to age-matched control subjects. These results suggest that Con A levels in peripheral blood may be a potent diagnostic marker for AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Case-Control Studies; Concanavalin A; Female; Humans; Lectins; Male; Plant Lectins

Cortical Amyloid Burden Differences Across Empirically-Derived Mild Cognitive Impairment Subtypes and Interaction with APOE ɛ4 Genotype. - Bangen, Katherine J; Clark, Alexandra L; Werhane, Madeline; Edmonds, Emily C; Nation, Daniel A; Evangelista, Nicole; Libon, David J; Bondi, Mark W; Delano-Wood, Lisa (J Alzheimers Dis, 2016)
We examined cortical amyloid-β (Aβ) levels and interactions with apolipoprotein (APOE) ɛ4 genotype status across empirically-derived mild cognitive impairment (MCI) subgroups and cognitively normal older adults. Participants were 583 ADNI participants (444 MCI, 139 normal controls [NC]) with baseline florbetapir positron emission tomography (PET) amyloid imaging and neuropsychological testing. Of those with ADNI-defined MCI, a previous cluster analysis [1] classified 51% (n = 227) of the current sample as amnestic MCI, 8% (n = 37) as dysexecutive/mixed MCI, and 41% (n = 180) as cluster-derived normal (cognitively normal). Results demonstrated that the dysexecutive/mixed and amnestic MCI groups showed significantly greater levels of amyloid relative to the cluster-derived normal and NC groups who did not differ from each other. Additionally, 78% of the dysexecutive/mixed, 63% of the amnestic MCI, 42% of the cluster-derived normal, and 34% of the NC group exceeded the amyloid positivity threshold. Finally, a group by APOE genotype interaction demonstrated that APOE ɛ4 carriers within the amnestic MCI, cluster-derived normal, and NC groups showed significantly greater amyloid accumulation compared to non-carriers of their respective group. Such an interaction was not revealed within the dysexecutive/mixed MCI group which was characterized by both greater cognitive impairment and amyloid accumulation compared to the other participant groups. Our results from the ADNI cohort show considerable heterogeneity in Aβ across all groups studied, even within a group of robust NC participants. Findings suggest that conventional criteria for MCI may be susceptible to false positive diagnostic errors, and that onset of Aβ accumulation may occur earlier in APOE ɛ4 carriers compared to non-carriers.

Cost Related to Dementia in the Young and the Impact of Etiological Subtype on Cost. - Kandiah, Nagaendran; Wang, Vivian; Lin, Xuling; Nyu, Mei Mei; Lim, Linda; Ng, Adeline; Hameed, Shahul; Wee, Hwee Lin (J Alzheimers Dis, 2016)
BACKGROUND: Young onset dementia (YOD) presents in individuals who are economically productive and socially active. While the cost related to dementia in the elderly has been widely studied, the cost related to YOD is largely unknown. OBJECTIVE: To study the economic burden of community dwelling YOD in relation to late onset dementia (LOD) and cost of YOD based on etiology. METHODS: In this prospective cross-sectional study of 255 patients attending a tertiary neurology center, data on economic burden, clinical features, and caregiver burden were collected using structured financial questionnaire, standard cognitive and neuropsychiatric measures, and Zarit caregiver burden scale. Cost components were grouped into those relating to direct medical costs, direct non-medical costs, and those related to indirect costs. Cost was also categorized based on etiology of YOD. RESULTS: The mean age at symptom onset in the YOD and LOD cohort was 57.0 (SD 5.1) and 75.0 (SD 5.9) years, respectively. The median annual cost for patients with YOD was almost twice that of LOD (USD 15,815 versus USD 8,396). Indirect cost contributed heavily to cost related to YOD. Even when grouped by dementia etiology, YOD patients with Alzheimer's disease, frontotemporal dementia (FTD), and vascular dementia had higher cost compared to their elderly counterparts. Young onset FTD had the highest cost. 43.2% of YOD reported loss of employment due to dementia, which was significantly higher than that in LOD (2.4%). CONCLUSION: Patients with YOD have a high economic burden. Young patients with FTD have the highest cost followed by vascular dementia and Alzheimer's disease.
Keywords: Age of Onset; Aged; Cohort Studies; Costs and Cost Analysis; Cross-Sectional Studies; Dementia; Female; Humans; Independent Living; Male; Mental Disorders; Middle Aged; Perceptual Disorders; Prospective Studies; Psychiatric Status Rating Scales; Severity of Illness Index; Surveys and Questionnaires; Young Adult

The Cytome Assay as a Tool to Investigate the Possible Association Between Exposure to Extremely Low Frequency Magnetic Fields and an Increased Risk for Alzheimer's Disease. - Maes, Annemarie; Anthonissen, Roel; Wambacq, Sheleen; Simons, Koen; Verschaeve, Luc (J Alzheimers Dis, 2016)
Exposure to extremely low frequency magnetic fields (ELF-MF) has been identified as one of the potential environmental risk factors for Alzheimer's disease (AD). However, this is far from being established. So far there is no experimental evidence supporting this alleged association. We have performed an in vitro cytogenetic laboratory investigation to explore the plausibility of such association. Our investigation was based on possible similarities found in cells from AD patients and in cells exposed to ELF-MF. We especially found that 50  Hz ELF-MF increase the frequency of cells with (large) micronuclei and nuclear buds indicating that fields above 50 μT may induce chromosome instabilities as those found in AD patients. It should be stressed yet that results from the few published experimental studies on ELF-MF and AD are rather reassuring. Thus, our findings certainly do not prove anything. They only suggest that further investigations might be necessary.
Keywords: Apoptosis; Carcinoma; Cell Line, Tumor; Chromosome Aberrations; Cytokinesis; Dose-Response Relationship, Radiation; Humans; Magnetic Fields; Risk Factors

Decreased Levels of VAMP2 and Monomeric Alpha-Synuclein Correlate with Duration of Dementia. - Vallortigara, Julie; Whitfield, David; Quelch, William; Alghamdi, Amani; Howlett, David; Hortobágyi, Tibor; Johnson, Mary; Attems, Johannes; O'Brien, John T; Thomas, Alan; Ballard, Clive G; Aarsland, Dag; et al. (J Alzheimers Dis, 2016)
Alpha-synuclein (α-syn) aggregations are the key pathological hallmark of dementia with Lewy bodies (DLB) and Parkinson's disease dementia (PDD), but are also frequently present in Alzheimer's disease (AD). Much remains unknown about the role of α-syn in the synapse and the wider role of synaptic dysfunction in these dementias. Changes in concentrations of key 'SNAP (Soluble N-ethylmaleimide Sensitive Factor Attachment Protein) Receptor' (SNARE) proteins as a consequence of alterations in the aggregation state of α-syn may contribute to synaptic dysfunction in patients with DLB, PDD, and AD and result in impaired cognition. We have studied a large cohort (n = 130) of autopsy confirmed DLB, PDD, AD, and control brains. Using semi-quantitative western blotting, we have demonstrated significant changes across the diagnostic groups of DLB, PDD, and AD in the SNARE and vesicle proteins syntaxin, Munc18, VAMP2, and monomeric α-syn in the prefrontal cortex, with a significant reduction of Munc18 in AD patients (p <  0.001). This correlated to the final MMSE score before death (p = 0.016). We also identified a significant negative correlation between the duration of dementia and the levels of the binding partners VAMP2 (p = 0.0004) and monomeric α-syn (p = 0.0002). Our findings may indicate that an upregulation of SNARE complex related proteins occurs in the early stages of disease as an attempt at compensating for failing synapses, prior to widespread deposition of pathological α-syn.
Keywords: Aged; Aged, 80 and over; alpha-Synuclein; Amyloid beta-Peptides; Analysis of Variance; Cognition Disorders; Dementia; Female; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Regression Analysis; Synaptophysin; tau Proteins; Vesicle-Associated Membrane Protein 2

Dementia Apraxia Test (DATE): A Brief Tool to Differentiate Behavioral Variant Frontotemporal Dementia from Alzheimer's Dementia Based on Apraxia Profiles. - Johnen, Andreas; Frommeyer, Jana; Modes, Fenja; Wiendl, Heinz; Duning, Thomas; Lohmann, Hubertus (J Alzheimers Dis, 2016)
BACKGROUND: Standardized praxis assessments with modern, empirically validated screening tests have substantially improved clinical evaluation of apraxia in patients with stroke. Although apraxia may contribute to early differential diagnosis of Alzheimer's dementia (AD) and behavioral variant frontotemporal dementia (bvFTD), no comparable test is readily available to clinicians for this purpose to date. OBJECTIVE: To design a clinically useful apraxia test for the differentiation of AD and bvFTD. METHODS: 84 test items pertaining to twelve praxis subdomains were evaluated for their efficacy to discriminate between patients with bvFTD (n = 24), AD (n = 28), and elderly healthy controls (HC; n = 35). Items were then selected based on discriminative value and psychometric properties. RESULTS: Items indicative of mild AD comprised spatially complex imitation of hand and finger postures and to a lesser degree, pantomime of common object-use. Buccofacial apraxia including imitation of face postures, emblematic face postures, and repetition of multisyllabic pseudowords differentiated bvFTD from HC and AD. The final test version consisting of 20 items proved highly efficient for the discrimination of biologically confirmed dementia patients from HC (sensitivity 91% , specificity 71%) but also for differential diagnosis of bvFTD and AD (sensitivity 74% , specificity 93%). CONCLUSIONS: Assessment of praxis profiles effectively contributes to diagnosis and differential diagnosis of AD and bvFTD. The Dementia Apraxia Test (DATE) is a brief and easy to administer cognitive tool for dementia assessment, has a high inter-rater reliability (Cohen's κ= 0.885) and demonstrates content validity.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Apraxias; Diagnosis, Differential; Female; Frontotemporal Dementia; Humans; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Psychometrics; Reference Values

Dementia Risk and Protective Factors Differ in the Context of Memory Trajectory Groups. - Zahodne, Laura B; Schupf, Nicole; Brickman, Adam M; Mayeux, Richard; Wall, Melanie M; Stern, Yaakov; Manly, Jennifer J (J Alzheimers Dis, 2016)
BACKGROUND: Previous research has identified multiple risk and protective factors for late onset Alzheimer's disease (LOAD). However, it is not known whether these risk and protective factors differ for individuals who are cognitively stable versus those already experiencing declines. OBJECTIVE: This study examined how dementia risk factors differ across subgroups of older adults defined by memory trajectory. This line of research may lead to more individualized risk profiles. METHODS: Risk factors for incident LOAD were compared across previously-validated groups of older adults exhibiting different memory trajectories ("Stable-High," "Stable-Low," "Decliner," "Rapid Decliner") using stratified Cox regressions. Participants included 2,593 racially/ethnically diverse older adults (mean age of 76 at study entry) in the Washington Heights-Inwood Columbia Aging Project. RESULTS: Predictors of incident dementia differed across trajectory groups: older age only incurred independent risk in stable groups, education did not incur independent protection in the rapidly declining group, depression only incurred independent risk in the stable-low group, stroke incurred independent risk in the two extreme groups, and APOE-ɛ4 only incurred independent risk in the rapidly declining group. CONCLUSION: The finding that different risk factors for LOAD were associated with specific memory trajectories may reflect the existence of resilience or vulnerability factors that modify the individual influences of risk/protective factors. This study highlights the utility of considering interactions between dementia risk factors and a patient's unique cognitive history.

A Depressive Endophenotype for Predicting Cognitive Decline among Mexican American Adults and Elders. - Johnson, Leigh A; Gamboa, Adriana; Vintimilla, Raul; Edwards, Melissa; Hall, James; Weiser, Brent; Yadav, Menaka; Dickensheets, Tony; O'Bryant, Sid E (J Alzheimers Dis, 2016)
BACKGROUND: Late life depression is a prodromal feature and a risk factor for Alzheimer's disease (AD) and mild cognitive impairment (MCI). We identified five items in the Geriatric Depression scale (DepE) that are important as a risk for MCI and AD: memory problems, feeling blue, crying, feeling worthless, and trouble concentrating. OBJECTIVE: Our goal was to examine the relationship between DepE and cognition in a cohort of Mexican Americans. METHODS: Data from 317 Mexican Americans from the HABLE study were analyzed. DepE scores were dichotomized into two groups: endorsement of 1 item or less, and endorsement of 2 or more items. Cognition was assessed via neuropsychological tests, and diagnosis was based on consensus review. We utilized linear regression to examine the association between DepE and cognitive performance, and logistic regression to examine the utility of DepE in predicting MCI. To examine the impact of DepE on memory over 12 months, we performed ANOVA analysis. RESULTS: Elevated DepE scores were associated with poorer performance on various measures of memory and cognition, but not executive or visual spatial skills. Over 12 months, we found a decline in immediate memory among women but not men. Those with high scores were 4 times more likely to have MCI. ANOVA of total scores revealed differences between groups on immediate memory (p < 0.05) in women, with no significant differences on delay recall in either gender. CONCLUSION: DepE can be utilized in Mexican Americans to identify those at risk of memory related cognitive decline.

Detection of Alzheimer's Disease by Three-Dimensional Displacement Field Estimation in Structural Magnetic Resonance Imaging. - Wang, Shuihua; Zhang, Yudong; Liu, Ge; Phillips, Preetha; Yuan, Ti-Fei (J Alzheimers Dis, 2016)
BACKGROUND: Within the past decade, computer scientists have developed many methods using computer vision and machine learning techniques to detect Alzheimer's disease (AD) in its early stages. OBJECTIVE: However, some of these methods are unable to achieve excellent detection accuracy, and several other methods are unable to locate AD-related regions. Hence, our goal was to develop a novel AD brain detection method. METHODS: In this study, our method was based on the three-dimensional (3D) displacement-field (DF) estimation between subjects in the healthy elder control group and AD group. The 3D-DF was treated with AD-related features. The three feature selection measures were used in the Bhattacharyya distance, Student's t-test, and Welch's t-test (WTT). Two non-parallel support vector machines, i.e., generalized eigenvalue proximal support vector machine and twin support vector machine (TSVM), were then used for classification. A 50 × 10-fold cross validation was implemented for statistical analysis. RESULTS: The results showed that "3D-DF+WTT+TSVM" achieved the best performance, with an accuracy of 93.05 ± 2.18, a sensitivity of 92.57 ± 3.80, a specificity of 93.18 ± 3.35, and a precision of 79.51 ± 2.86. This method also exceled in 13 state-of-the-art approaches. Additionally, we were able to detect 17 regions related to AD by using the pure computer-vision technique. These regions include sub-gyral, inferior parietal lobule, precuneus, angular gyrus, lingual gyrus, supramarginal gyrus, postcentral gyrus, third ventricle, superior parietal lobule, thalamus, middle temporal gyrus, precentral gyrus, superior temporal gyrus, superior occipital gyrus, cingulate gyrus, culmen, and insula. These regions were reported in recent publications. CONCLUSIONS: The 3D-DF is effective in AD subject and related region detection.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Brain Mapping; Datasets as Topic; Female; Humans; Imaging, Three-Dimensional; Machine Learning; Magnetic Resonance Imaging; Male

Diagnosing Dementia in the Clinical Setting: Can Amyloid PET Provide Additional Value Over Cerebrospinal Fluid? - Weston, Philip S J; Paterson, Ross W; Dickson, John; Barnes, Anna; Bomanji, Jamshed B; Kayani, Irfan; Lunn, Michael P; Mummery, Catherine J; Warren, Jason D; Rossor, Martin N; Fox, Nick C; Zetterberg, Henrik; et al. (J Alzheimers Dis, 2016)
Cerebrospinal fluid (CSF) measures of amyloid and tau are the first-line Alzheimer's disease biomarkers in many clinical centers. We assessed if and when the addition of amyloid PET following CSF measurements provides added diagnostic value. Twenty patients from a cognitive clinic, who had undergone detailed assessment including CSF measures, went on to have amyloid PET. The treating neurologist's working diagnosis, and degree of diagnostic certainty, was assessed both before and after the PET. Amyloid PET changed the diagnosis in 7/20 cases. Amyloid PET can provide added diagnostic value, particularly in young-onset, atypical dementias, where CSF results are borderline and diagnostic uncertainty remains.

Diagnostic Accuracy of MRI and Additional [18F]FDG-PET for Behavioral Variant Frontotemporal Dementia in Patients with Late Onset Behavioral Changes. - Vijverberg, Everard G B; Wattjes, Mike P; Dols, Annemiek; Krudop, Welmoed A; Möller, Christiane; Peters, Anne; Kerssens, Cora J; Gossink, Flora; Prins, Niels D; Stek, Max L; Scheltens, Philip; van Berckel, Bart N M; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Neuroimaging has a reasonable accuracy to differentiate behavioral variant frontotemporal dementia (bvFTD) from other neurodegenerative disorders, its value for the differentiation of bvFTD among subjects with acquired behavioral disturbances is unknown. OBJECTIVE: To determine the diagnostic accuracy of MRI, additional [18F]FDG-PET, and their combination for bvFTD among subjects with late onset behavioral changes. METHODS: Patients with late onset behavioral changes referred to a memory clinic or psychiatric services were included. At baseline, 111 patients had a brain MRI scan and 74 patients received an additional [18F]FDG-PET when the MRI was inconclusive. The consensus diagnosis after two-year-follow-up was used as the gold standard to calculate sensitivity and specificity for baseline neuroimaging. RESULTS: 27 patients had probable/definite bvFTD and 84 patients had a non-bvFTD diagnosis (primary psychiatric diagnosis or other neurological disorders). MRI had a sensitivity of 70% (95% CI 52-85%) with a specificity of 93% (95% CI 86-97%). Additional [18F]FDG-PET had a sensitivity of 90% (95% CI 66-100%) with a specificity of 68% (95% CI 56-79%). The sensitivity of combined neuroimaging was 96% (95% CI 85-100%) with a specificity of 73% (95% CI 63-81%). In 66% of the genetic FTD cases, MRI lacked typical frontotemporal atrophy. 40% of cases with a false positive [18F]FDG-PET scan had a primary psychiatric diagnosis. CONCLUSION: A good diagnostic accuracy was found for MRI and additional [18F]FDG-PET for bvFTD in patients with late onset behavioral changes. Caution with the interpretation of neuroimaging results should especially be taken in cases with a genetic background and in cases with a primary psychiatric differential diagnosis where [18F]FDG-PET is the only abnormal investigation.

Differential Diagnosis of Dementia with High Levels of Cerebrospinal Fluid Tau Protein. - Grangeon, Lou; Paquet, Claire; Bombois, Stephanie; Quillard-Muraine, Muriel; Martinaud, Olivier; Bourre, Bertrand; Lefaucheur, Romain; Nicolas, Gaël; Dumurgier, Julien; Gerardin, Emmanuel; Jan, Mary; Laplanche, Jean-Louis; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Total Tau concentration in cerebrospinal fluid (CSF) is widely used as a biomarker in the diagnosis of neurodegenerative process primarily in Alzheimer's disease (AD). A particularly high Tau level may indicate AD but may also be associated with Creutzfeldt-Jakob disease (CJD). In such situations little is known about the distribution of differential diagnoses. OBJECTIVE: Our study aimed to describe the different diagnoses encountered in clinical practice for patients with dementia and CSF Tau levels over 1000 pg/ml. We studied the p-Tau/Tau ratio to specify its ability to distinguish AD from CJD. METHODS: Patients (n = 202) with CSF Tau levels over 1000 pg/ml were recruited in three memory clinics in France. All diagnoses were made using the same diagnostic procedure and criteria. RESULTS: Patients were diagnosed with AD (n = 148, 73.2%), mixed dementia (n = 38, 18.8%), CJD, vascular dementia (n = 4, 2.0% for each), Lewy body dementia, and frontotemporal dementia (n = 3, 1.5% for each). Dispersion of CSF Tau levels clearly showed an overlap between all diagnoses. Using the p-Tau/Tau ratio suggestive of CJD (<0.075), all CJD patients were correctly categorized and only two AD patients were miscategorized. This ratio was highly associated with CJD compared to AD (p < 0.0001). CONCLUSION: Our study showed that in clinical practice, extremely high CSF Tau levels are mainly related to diagnosis of AD. CJD patients represent a minority. Our results support a sequential interpretation algorithm for CSF biomarkers in dementia. High CSF Tau levels should alert clinicians to check the p-Tau/Tau ratio to consider a probable diagnosis of CJD.
Keywords: Adult; Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Creutzfeldt-Jakob Syndrome; Dementia, Vascular; Diagnosis, Differential; Female; France; Frontotemporal Dementia; Humans; Lewy Body Disease; Male; Mental Status Schedule; Middle Aged; Phosphorylation; Retrospective Studies; Sex Factors; tau Proteins

Differential Effects of APOE Genotypes on the Anterior and Posterior Subnetworks of Default Mode Network in Amnestic Mild Cognitive Impairment. - Yuan, Baoyu; Xie, Chunming; Shu, Hao; Liao, Wenxiang; Wang, Zan; Liu, Duan; Zhang, Zhijun (J Alzheimers Dis, 2016)
BACKGROUND: The apolipoprotein E (APOE) ɛ4 carriers are at increased risk of developing Alzheimer's disease (AD) while the ɛ2 carriers appear to be protected against the disease. The default mode network (DMN), based in ventromedial prefrontal cortex (vmPFC) and posterior cingulate cortex (PCC), consists of functionally differentiable anterior and posterior subnetworks. OBJECTIVE: This study was to investigate whether there are differential effects of APOE polymorphisms on DMN subnetworks in amnestic mild cognitive impairment (aMCI). METHODS: Functional connectivity (FC) analyses were performed in DMN subnetworks in 74 aMCI (9 APOE ɛ2ɛ3, 44 ɛ3ɛ3, and 21 ɛ3ɛ4) and 105 healthy controls (HC; 32 APOE ɛ2ɛ3, 39 ɛ3ɛ3, and 34 ɛ3ɛ4). Logistic regression analysis was performed to obtain a model for classifying aMCI and HC. RESULTS: Significant interactions of APOE by aMCI on FCs were found in right cerebellum posterior lobe, left lingual gyrus, and right middle cingulate cortex in the vmPFC subnetwork, and bilateral fusiform gyrus, left inferior frontal gyrus, and left precuneus in the PCC subnetwork. The impairment of episodic memory for ɛ4-carriers in aMCI negatively correlated with altered FC between vmPFC and right middle cingulate cortex, while positively correlated with altered FC between PCC and left fusiform gyrus. A model composed of episodic memory and FCs dexterity correctly classified 89.4% of aMCI and HC. CONCLUSIONS: APOE ɛ4 and ɛ2 alleles differentially mediate anterior and posterior DMN subnetworks. Furthermore, it further suggests that the anterior and posterior DMN subnetworks in aMCI play an opposing role on the impairment of episodic memory.

Differential Regulation of N-Methyl-D-Aspartate Receptor Subunits is an Early Event in the Actions of Soluble Amyloid-β(1-40) Oligomers on Hippocampal Neurons. - Chang, Lirong; Zhang, Yali; Liu, Jinping; Song, Yizhi; Lv, Angchu; Li, Yan; Zhou, Wei; Yan, Zhen; Almeida, Osborne F X; Wu, Yan (J Alzheimers Dis, 2016)
Synaptic dysfunction during early stages of Alzheimer's disease (AD) is triggered by soluble amyloid-β (Aβ) oligomers that interact with NMDA receptors (NMDARs). We previously showed that Aβ induces synaptic protein loss through NMDARs, albeit through undefined mechanisms. Accordingly, we here examined the contribution of individual NMDAR subunits to synaptotoxicity and demonstrate that Aβ exerts differential effects on the levels and distribution of GluN2A and GluN2B subunits of NMDAR in dendrites. Treatment of cultured hippocampal neurons with Aβ1-40 (10 μM, 1 h) induced a significant increase of dendritic and synaptic GluN2B puncta densities with parallel decreases in the puncta densities of denritic and synaptic pTyr1472-GluN2B. Conversely, Aβ significantly decreased dendritic and synaptic GluN2A and dendritic pTyr1325-GluN2A puncta densities and increased synaptic pTyr1325-GluN2A puncta densities. Unexpectedly, Aβ treatment resulted in a significant reduction of GluN2B and pTyr1472-GluN2B protein levels but did not influence GluN2A and pTyr1325-GluN2A levels. These results show that Aβ exerts complex and distinct regulatory effects on the trafficking and phosphorylation of GluN2A and GluN2B, as well as on their localization within synaptic and non-synaptic sites. Increased understanding of these early events in Aβ-induced synaptic dysfunction is likely to be important for the development of timely preventive and therapeutic interventions.
Keywords: Amyloid beta-Peptides; Animals; Animals, Newborn; Cells, Cultured; Dendrites; Gene Expression Regulation; Hippocampus; Male; Neurons; Peptide Fragments; Phosphorylation; Rats; Rats, Wistar; Receptors, N-Methyl-D-Aspartate

Differential Risk of Incident Alzheimer's Disease Dementia in Stable Versus Unstable Patterns of Subjective Cognitive Decline. - Wolfsgruber, Steffen; Kleineidam, Luca; Wagner, Michael; Mösch, Edelgard; Bickel, Horst; Lϋhmann, Dagmar; Ernst, Annette; Wiese, Birgitt; Steinmann, Susanne; König, Hans-Helmut; Brettschneider, Christian; Luck, Tobias; et al. (J Alzheimers Dis, 2016)
BACKGROUND: It is unknown whether longitudinal stability versus instability in subjective cognitive decline (SCD) is a modifying factor of the association between SCD and risk of incident Alzheimer's disease (AD) dementia. OBJECTIVE: We tested the modifying role of temporal stability of the SCD report on AD dementia risk in cognitively normal elderly individuals. METHODS: We analyzed data of 1,990 cognitively normal participants from the longitudinal AgeCoDe Study. We assessed SCD with/without associated worries both at baseline and first follow-up 18 months later. Participants were then classified either as (a) Controls (CO, with no SCD at both baseline and follow-up 1, n = 613), (b) inconsistent SCD (with SCD reported only at baseline or at follow-up 1, n = 637), (c) consistent SCD but without/or with inconsistent worries (n = 610) or (d) consistent SCD with worries (n = 130). We estimated incident AD dementia risk over up to 6 years for each group with Cox-Proportional Hazard Regression analyses adjusted for age, gender, education, ApoE4 status, and depression. RESULTS: Compared to CO, inconsistent SCD was not associated with increased risk of incident AD dementia. In contrast, risk was doubled in the group of consistent SCD without/ with inconsistent worries, and almost 4-fold in the group of consistent SCD with worries. These results could be replicated when using follow-up 1 to follow-up 2 response patterns for group definition. CONCLUSION: These findings suggest that longitudinal stability versus instability is an important modifying factor of the association between SCD and AD dementia risk. Worrisome SCD that is also consistently reported over time is associated with greatly increased risk of AD dementia.

Disrupted White Matter Network and Cognitive Decline in Type 2 Diabetes Patients. - Zhang, Junying; Liu, Zhen; Li, Zixiao; Wang, Yunxia; Chen, Yaojing; Li, Xin; Chen, Kewei; Shu, Ni; Zhang, Zhanjun (J Alzheimers Dis, 2016)
Type 2 diabetes mellitus is accompanied by cognitive impairment and is associated with an increased risk of dementia. Damage to brain structures such as white matter network disruption may underlie this cognitive disturbance. In the present study, 886 non-diabetic and 163 type 2 diabetic participants completed a battery of neuropsychological tests. Among them, 38 diabetic patients and 34 non-diabetic participants that matched the patients for age/sex/education received a magnetic resonance imaging-based diffusion tensor imaging. Then we calculated the topological properties of the white matter network using a graph theoretical method to investigate network efficiency differences between groups. We found that type 2 diabetic patients had inferior performances compared to the non-diabetic controls, in several cognitive domains involving executive function, spatial processing, memory, and attention. We also found that diabetic patients exhibited a disrupted topological organization of the white matter network (including the global network properties, i.e., network strength, global efficiency, local efficiency and shortest path length, and the nodal efficiency of the right rolandic operculum) in the brain. Moreover, those global network properties and the nodal efficiency of the right rolandic operculum both had positive correlations with executive function in the patient group. The results suggest that type 2 diabetes mellitus leads to an alteration in the topological organization of the cortical white matter network and this alteration may account for the observed cognitive decline.

Distinct Patterns of Cognitive Aging Modified by Education Level and Gender among Adults with Limited or No Formal Education: A Normative Study of the Mini-Mental State Examination. - Xie, Haiqun; Zhang, Chengguo; Wang, Yukai; Huang, Shuyun; Cui, Wei; Yang, Wenbin; Koski, Lisa; Xu, Xiping; Li, Youbao; Zheng, Meili; He, Mingli; Fu, Jia; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Dementia is increasingly prevalent due to rapid aging of the population, but under-recognized among people with low education levels. This is partly due to a lack of appropriate and precise normative data, which underestimates cognitive aging in the use of screening tools for dementia. OBJECTIVE: We aimed to improve the precision of screening for cognitive impairment, by characterizing the patterns of cognitive aging and derived normative data of the Mini-Mental State Examination (MMSE) for illiterate and low-educated populations. METHODS: This community-based study included data from 2,280 individuals aged 40 years or older from two rural areas. Multiple linear modeling examined the effect of aging on cognition reflected by the MMSE, stratified by education level and gender. Threshold effect of age on cognition was performed using a smoothing function. RESULTS: The majority of participants (60.4%) were illiterate or had attended only primary school (24.6%). The effect of aging on cognition varied by gender and education. Primary-school educated females and males remained cognitively stable up to 62 and 71 years of age, respectively, with MMSE score declining 0.4 and 0.8 points/year in females and males thereafter. Illiterates females scored 2.3 points lower than illiterate males, and scores for both declined 0.2 points/year. According to these results, normative data stratified by age, education and gender was generated. CONCLUSION: This study suggests gender and educational differences exist in cognitive aging among adults with limited or no formal education. To improve screening precision for cognitive impairment with the use of MMSE in low-educated population, age, gender, and education level should be considered.
Keywords: Adult; Aged; Aged, 80 and over; China; Cognition Disorders; Cognitive Aging; Educational Status; Female; Humans; Male; Mental Status Schedule; Middle Aged; Reference Values; Rural Population; Sex Characteristics

Do Chinese Researchers Conduct Ethical Research and Use Ethics Committee Review in Clinical Trials of Anti-Dementia Drugs? An Analysis of Biomedical Publications Originating from China. - Zeng, Lingfeng; Liang, Weixiong; Pan, Jianke; Cao, Ye; Liu, Jun; Wang, Qi; Wang, Lu; Zou, Yuanping; Wang, Kezhu; Kong, Lingshuo; Xie, Hui; Xu, Weihua; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Medical research using human participants must conform to the basic ethical principles found in the Declaration of Helsinki (DoH) of the World Medical Association. OBJECTIVE: The purpose of this review was to assess whether journals in China have improved in regard to the fulfillment of ethical disclosure procedures for clinical trials of anti-dementia drugs. METHODS: Four medical databases were searched for articles reporting clinical trials of oral anti-dementia drugs published in China in 2003, 2009, and 2014. The frequencies of reporting of informed consent from participants (ICP), approval of a regional ethical committee (REC), reference to DoH, and study registration were estimated respectively. Statistical analyses were conducted with SPSS v21 software. RESULTS: Among those randomized controlled trials published in 2003, 2009, and 2014, disclosure of REC approval was present for 2.67%, 1.15%, and 6.84%; statements of ICP were included in 9.33%, 7.76%, and 17.34%; reference to DoH was found for 4.00%, 1.44%, and 7.45%; and study registration reporting was included in 2.67%, 2.59%, and 9.28%, respectively. Improvements to reporting rates between 2009 and 2014 were seen, with more than twice as many trials reporting REC approval, ICP, reference to DoH, and study registration compared with 2009. CONCLUSION: Compared with 2003 and 2009, reporting rates for REC approval, ICP, reference to DoH, and study registration for clinical trials of anti-dementia drugs were enhanced in 2014 in the major medical journals of China. However, biomedical publications without definite statements of ethical considerations remain common, and this continues to be seen in Chinese journals. It is imperative that measures are taken to reinforce the ethical protection in clinical trials in China.

Dogs with Cognitive Dysfunction as a Spontaneous Model for Early Alzheimer's Disease: A Translational Study of Neuropathological and Inflammatory Markers. - Schütt, Trine; Helboe, Lone; Pedersen, Lars Østergaard; Waldemar, Gunhild; Berendt, Mette; Pedersen, Jan Torleif (J Alzheimers Dis, 2016)
Aged companion dogs with canine cognitive dysfunction (CCD) spontaneously develop varying degrees of progressive cognitive decline and particular neuropathological features correspondent to the changes associated with Alzheimer's disease (AD) in humans. The aim of the present study was to characterize certain aspects of neuropathology and inflammatory markers related to aging and CCD in dogs in comparison with human AD. Fifteen brains from aged dogs with normal cognitive function, mild cognitive impairment, or CCD were investigated and compared with two control brains from young dogs and brain sections from human AD subjects. The neuropathological investigations included evaluation of amyloid-β (Aβ) plaque deposition (N-terminally truncated and pyroglutamyl-modified Aβ included), tau pathology, and inflammatory markers in prefrontal cortex. Cortical Aβ deposition was found to be only of the diffuse subtype as no dense-core or neuritic plaques were found. The Aβ deposition followed a progressive pattern in four maturation stages. Accumulation of the Aβ peptide was also observed in the vessel walls. Both immunohistochemically and biochemically measured levels of Aβ pathology in prefrontal cortex showed a consistent positive correlation to age but not to cognitive deficit severity. No evidence of neurofibrillary tau pathology was found. The level of pro-inflammatory cytokines was generally low and showed no significant association to cognitive status. The findings of the present study support the senescent dog with spontaneous cognitive dysfunction as a valuable non-transgenic model for further investigations of the molecular events involved in the neurodegenerative processes associated with aging and early stage AD, especially the Aβ-related pathology.
Keywords: Aging; Alzheimer Disease; Animals; Brain; Cognitive Dysfunction; Cytokines; Denmark; Disease Models, Animal; Disease Progression; Dog Diseases; Dogs; Female; Humans; Immunohistochemistry; Longitudinal Studies; Male; Plaque, Amyloid; Severity of Illness Index; Species Specificity; tau Proteins; Translational Medical Research

Dose-Dependent Neuroprotection and Neurotoxicity of Simvastatin through Reduction of Farnesyl Pyrophosphate in Mice Treated with Intracerebroventricular Injection of Aβ 1-42. - Jin, Huafeng; Chen, Tingting; Li, Guoxi; Wang, Conghui; Zhang, Baofeng; Cao, Xinyuan; Sha, Sha; Wan, Qi; Chen, Ling (J Alzheimers Dis, 2016)
BACKGROUND: Simvastatin (SV) has been reported to improve dementia and slow progression of Alzheimer's disease (AD), however there are conflicting reports. OBJECTIVE & METHODS: Intracerebroventricular injection of aggregated Aβ1-42 in mice (Aβ1-42-mice) caused spatial cognitive deficits, long-term potentiation (LTP) impairment, and death of hippocampal pyramidal cells. The present study focused on exploring the dose-dependent effects of SV (10-80 mg/kg) on Aβ1-42-impaired spatial memory and the underlying mechanisms. RESULTS: The treatment of Aβ1-42-mice with SV for continuous 15 days could attenuate the spatial cognitive deficits and recover the LTP induction in a "U" type dose-dependent manner. The death of pyramidal cells in Aβ1-42-mice was significantly reduced by the SV-treatment at 20 mg/kg, but not at a dose of 10 or 40 mg/kg, even was aggravated at a dose of 80 mg/kg. Hippocampal NMDA receptor (NMDAr) NR2B phosphorylation (phospho-NR2B) was elevated in Aβ1-42-mice, which was further dose-dependently increased by SV-treatment. Replenishment of isoprenoid farnesyl pyrophosphate (FPP) by applying farnesol (FOH) could abolish the SV-increased phospho-NR2B in Aβ1-42-mice, but had no effect on the Aβ1-42-enhanced phospho-NR2B. NMDAr antagonist blocked the neurotoxicity of Aβ1-42 and SV (80 mg/kg) in Aβ1-42-mice, whereas FOH only inhibited SV (80 mg/kg)-neurotoxicity. The SV-treatment in Aβ1-42-mice corrected the decrease in hippocampal Akt phosphorylation. The PI3K inhibitor abolished the SV (20 mg/kg)-neuroprotection in Aβ1-42-mice. CONCLUSION: SV-treatment in Aβ1-42-mice exerts dose-dependent neuroprotection and neurotoxicity by reducing FPP to enhance the phosphorylation of NR2B and Akt.
Keywords: Amyloid beta-Peptides; Animals; Dose-Response Relationship, Drug; Hippocampus; Injections, Intraventricular; Male; Maze Learning; Mice; Neuroprotective Agents; Peptide Fragments; Phosphorylation; Polyisoprenyl Phosphates; Receptors, N-Methyl-D-Aspartate; Sesquiterpenes; Simvastatin; Spatial Memory

Dysregulation and diagnostic potential of microRNA in Alzheimer's disease. - Pan, Yaoqian; Liu, Ruizhu; Terpstra, Erin; Wang, Yanqing; Qiao, Fangfang; Wang, Jin; Tong, Yigang; Pan, Bo (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is one of the most common neurodegenerative diseases and is considered to be the main cause of cognitive impairment in elderly people. The major symptom of AD is progressive dementia that eventually results in dysfunction of daily life. Due to the fact that AD has a long period of incubation before clinical symptoms emerge, the available therapeutic treatments can only improve the symptoms but not delay the progression of AD. Therefore, there is an urgent need to explore effective diagnostic approaches to catch and better treat the disease before clinical symptoms appear. Recent research revealed that abnormal expression of certain miRNA could have a crucial role in the pathological process of neurodegenerative disease including AD. Furthermore, given that AD patients show increased level of miRNAs in the blood and cerebrospinal fluid, miRNAs are considered promising non-invasive candidates for AD diagnosis and prognosis. Here, we reviewed the current research related to implications of miRNAs during the development of AD, summarized of actively used approaches to identifying potential miRNA biomarkers in body fluids, and discussed the diagnostic potential of microRNAs as biomarkers for AD.
Keywords: Aged; Alzheimer Disease; Biomarkers; Disease Progression; Humans; MicroRNAs; Prognosis

Economic Analysis of Formal Care, Informal Care, and Productivity Losses in Primary Care Patients who Screened Positive for Dementia in Germany. - Michalowsky, Bernhard; Thyrian, Jochen René; Eichler, Tilly; Hertel, Johannes; Wucherer, Diana; Flessa, Steffen; Hoffmann, Wolfgang (J Alzheimers Dis, 2016)
BACKGROUND: The majority of people with dementia (PwD) live at home and require professional formal care and informal care that is generally provided by close relatives. OBJECTIVE: To determine the utilization and costs of formal and informal care for PwD, indirect costs because of productivity losses of caregivers, and the associations between cost, socio-demographic and clinical variables. METHODS: The analysis includes the data of 262 community-dwelling PwD and their caregivers. Socio-demographics, clinical variables, and the utilization of formal care were assessed within the baseline assessment. To evaluate informal care costs, the Resource Utilization in Dementia (RUD) questionnaire was used. Costs were calculated from a social perspective. Associations were evaluated using multiple linear and logistic regression models. RESULTS: Formal care services were utilized less (26.3%) than informal care (85.1%), resulting in a cost ratio of one to ten(1,646 €; 16,473 €, respectively). In total, 29% of caregivers were employed, and every seventh (14.3%) experienced productivity losses, which corresponded to 1,258 € annually. Whereas increasing deficits in daily living activities were associated with higher formal and higher informal costs, living alone was significantly associated with higher formal care costs and the employment of a caregiver was associated with lower informal care costs. CONCLUSION: Informal care contributes the most to total care costs. Living alone is a major cost driver for formal costs because of the lower availability of potential informal care. The availability of informal care is limited and productivity losses are increased when a caregiver is employed.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Caregivers; Cost of Illness; Cross-Sectional Studies; Dementia; Female; Germany; Health Care Costs; Home Care Services; Humans; Male; Patient Care; Sensitivity and Specificity; Surveys and Questionnaires

Effect of Continuous Propofol Infusion in Rat on Tau Phosphorylation with or without Temperature Control. - Huang, Chunxia; Ng, Olivia Tsz-Wa; Ho, Yuen-Shan; Irwin, Michael Garnet; Chang, Raymond Chuen-Chung; Wong, Gordon Tin-Chun (J Alzheimers Dis, 2016)
Several studies suggest a relationship between anesthesia-induced tau hyperphosphorylation and the development of postoperative cognitive dysfunction. This study further characterized the effects of continuous propofol infusion on tau protein phosphorylation in rats, with or without temperature control. Propofol was administered intravenously to 8-10-week-old male Sprague-Dawley rats and infused to the loss of the righting reflex for 2 h continuously. Proteins from cortex and hippocampus were examined by western blot and immunohistochemistry. Rectal temperature was significantly decreased during propofol infusion. Propofol with hypothermia significantly increased phosphorylation of tau at AT8, AT180, Thr205, and Ser199 in cortex and hippocampus except Ser396. With temperature maintenance, propofol still induced significant elevation of AT8, Thr205, and Ser199 in cortex and hippocampus; however, increase of AT180 and Ser396 was only found in hippocampus and cortex, respectively. Differential effects of propofol with or without hypothermia on multiple tau related kinases, such as Akt/GSK3β, MAPK pathways, or phosphatase (PP2A), were demonstrated in region-specific manner. These findings indicated that propofol increased tau phosphorylation under both normothermic and hypothermic conditions, and temperature control could partially attenuate the hyperphosphorylation of tau. Further studies are warranted to determine the long-term impact of propofol on the tau pathology and cognitive functions.
Keywords: Amyloid beta-Peptides; Analysis of Variance; Anesthetics, Intravenous; Animals; Body Temperature; Brain; Gene Expression Regulation; Glycogen Synthase Kinase 3 beta; Hypothermia, Induced; Male; Peptide Fragments; Phosphorylation; Propofol; Rats; Rats, Sprague-Dawley; Signal Transduction; tau Proteins

The Effect of Propofol Versus Isoflurane Anesthesia on Human Cerebrospinal Fluid Markers of Alzheimer's Disease: Results of a Randomized Trial. - Berger, Miles; Nadler, Jacob W; Friedman, Allan; McDonagh, David L; Bennett, Ellen R; Cooter, Mary; Qi, Wenjing; Laskowitz, Daniel T; Ponnusamy, Vikram; Newman, Mark F; Shaw, Leslie M; Warner, David S; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Preclinical studies have found differential effects of isoflurane and propofol on the Alzheimer's disease (AD)-associated markers tau, phosphorylated tau (p-tau) and amyloid-β (Aβ). OBJECTIVE: We asked whether isoflurane and propofol have differential effects on the tau/Aβ ratio (the primary outcome), and individual AD biomarkers. We also examined whether genetic/intraoperative factors influenced perioperative changes in AD biomarkers. METHODS: Patients undergoing neurosurgical/otolaryngology procedures requiring lumbar cerebrospinal fluid (CSF) drain placement were prospectively randomized to receive isoflurane (n = 21) or propofol (n = 18) for anesthetic maintenance. We measured perioperative CSF sample AD markers, performed genotyping assays, and examined intraoperative data from the electronic anesthesia record. A repeated measures ANOVA was used to examine changes in AD markers by anesthetic type over time. RESULTS: The CSF tau/Aβ ratio did not differ between isoflurane- versus propofol-treated patients (p = 1.000). CSF tau/Aβ ratio and tau levels increased 10 and 24 h after drain placement (p = 2.002×10-6 and p = 1.985×10-6, respectively), mean CSF p-tau levels decreased (p = 0.005), and Aβ levels did not change (p = 0.152). There was no interaction between anesthetic treatment and time for any of these biomarkers. None of the examined genetic polymorphisms, including ApoE4, were associated with tau increase (n = 9 polymorphisms, p > 0.05 for all associations). CONCLUSION: Neurosurgery/otolaryngology procedures are associated with an increase in the CSF tau/Aβ ratio, and this increase was not influenced by anesthetic type. The increased CSF tau/Aβ ratio was largely driven by increases in tau levels. Future work should determine the functional/prognostic significance of these perioperative CSF tau elevations.

Effect of Tween-20 on Core Biomarkers Measured in Cerebrospinal Fluid from Patients with Alzheimer's Disease, Mild Cognitive Impairment, or Healthy Control Individuals. - Berge, Guro; Lauridsen, Camilla; Sando, Sigrid Botne; Holder, Daniel Joseph; Møller, Ina; Aasly, Jan Olav; Bråthen, Geir; Savage, Mary Josephine; White, Linda Rosemary (J Alzheimers Dis, 2016)
BACKGROUND: There is substantial variation caused by preanalytical procedures in the measurement of cerebrospinal fluid (CSF) biomarkers for Alzheimer's disease (AD) reported in the literature. OBJECTIVE: Determine whether the detergent Tween-20 improves diagnostic accuracy. METHODS: CSF proteins (Aβ42, Aβ40, total tau, and phosphorylated tau) were measured by standard ELISA, in uncentrifuged CSF with or without 0.05% Tween-20 from patients with AD or amnestic mild cognitive impairment, and healthy elderly controls. In the main study, collection tubes containing Tween-20 (Sarstedt 15 mL) were filled with 5 mL CSF to ensure consistent detergent concentration across subsequent aliquots into Corning 2 mL tubes. These latter were also the primary collection vessel for samples without Tween-20. The effect of centrifugation, and extra tube transfer of samples with Tween-20 were also examined. RESULTS: 0.05% Tween-20 significantly increased mean measured CSF concentration of Aβ42 (30% ), Aβ40 (23% ), and total tau (4% ), but not phosphorylated tau. Generally, these increases were similar in all groups, although for Aβ42, the mean percentage increase with Tween-20 was slightly larger for AD. Areas under receiver-operator characteristic curves were similar whether Tween-20 was present or not. Centrifuged CSF without Tween-20 significantly reduced the measured concentration of Aβ42 versus non-centrifuged samples, a difference not seen when detergent was added. Similar CSF Aβ42 levels were found whether Tween-20 was added at collection in an extra tube or directly to the main collection tube. CONCLUSION: Addition of Tween-20 to CSF did not improve differentiation of patients from controls.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Enzyme-Linked Immunosorbent Assay; Female; Humans; Longitudinal Studies; Male; Middle Aged; Peptide Fragments; Phosphorylation; Polysorbates; ROC Curve; Surface-Active Agents; tau Proteins

The Effects of LW-AFC on Intestinal Microbiome in Senescence-Accelerated Mouse Prone 8 Strain, a Mouse Model of Alzheimer's Disease. - Wang, Jianhui; Ye, Fuqiang; Cheng, Xiaorui; Zhang, Xiaorui; Liu, Feng; Liu, Gang; Ni, Ming; Qiao, Shanyi; Zhou, Wenxia; Zhang, Yongxiang (J Alzheimers Dis, 2016)
Microbes have deserved broader attention as causal factors in Alzheimer's disease (AD), a neurodegenerative disorder. The senescence-accelerated mouse prone 8 (SAMP8) strain, a spontaneous mice of accelerated aging, are considered a robust model for sporadic AD. LW-AFC, an herbal medicine, was prepared from LiuweiDihuang decoction, which is a classical traditional Chinese medicine prescription. Here, we showed that the treatment of LW-AFC improved cognitive impairments of SAMP8 mice, including spatial learning and memory ability, active avoidance response, and object recognition memory capability. Our data indicated that there were significantly 8 increased and 12 decreased operational taxonomic units (OTUs) in the gut microbiota of SAMP8 mice compared with senescence accelerated mouse resistant 1 (SAMR1) strains, the control of SAMP8 mice. The treatment of LW-AFC altered 22 (16 increased and 6 decreased) OTUs in SAMP8 mice and among them, 15 OTUs could be reversed by LW-AFC treatment resulting in a microbial composition similar to that of SAMR1 mice. We further showed that there were 7 (3 negative and 4 positive correlation) OTUs significantly correlated with all the three types of cognitive abilities, at the order level, including Bacteroidales, Clostridiales, Desulfovibrionales, CW040, and two unclassified orders. LW-AFC had influences on bacterial taxa correlated with the abilities of learning and memory in SAMP8 mice and restored them to SAMR1 mice. Our results indicate that the effects of LW-AFC on improving cognitive impairments of SAMP8 mice might be via modulating intestinal microbiome and LW-AFC could be used as a potential anti-AD agent.

Efficacy and Safety of MMFS-01, a Synapse Density Enhancer, for Treating Cognitive Impairment in Older Adults: A Randomized, Double-Blind, Placebo-Controlled Trial. - Liu, Guosong; Weinger, Jason G; Lu, Zhong-Lin; Xue, Feng; Sadeghpour, Safa (J Alzheimers Dis, 2016)
BACKGROUND: Cognitive impairment is a major problem in elderly, affecting quality of life. Pre-clinical studies show that MMFS-01, a synapse density enhancer, is effective at reversing cognitive decline in aging rodents. OBJECTIVE: Since brain atrophy during aging is strongly associated with both cognitive decline and sleep disorder, we evaluated the efficacy of MMFS-01 in its ability to reverse cognitive impairment and improve sleep. METHODS: We conducted a randomized, double-blind, placebo-controlled, parallel-designed trial in older adult subjects (age 50-70) with cognitive impairment. Subjects were treated with MMFS-01 (n = 23) or placebo (n = 21) for 12 weeks and cognitive ability, sleep quality, and emotion were evaluated. Overall cognitive ability was determined by a composite score of tests in four major cognitive domains. RESULTS: With MMFS-01 treatment, overall cognitive ability improved significantly relative to placebo (p = 0.003; Cohen's d = 0.91). Cognitive fluctuation was also reduced. The study population had more severe executive function deficits than age-matched controls from normative data and MMFS-01 treatment nearly restored their impaired executive function, demonstrating that MMFS-01 may be clinically significant. Due to the strong placebo effects on sleep and anxiety, the effects of MMFS-01 on sleep and anxiety could not be determined. CONCLUSIONS: The current study demonstrates the potential of MMFS-01 for treating cognitive impairment in older adults.
Keywords: Aged; Anxiety; Butyrates; Cognition; Cognition Disorders; Double-Blind Method; Emotions; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Nootropic Agents; Sleep; Synapses; Treatment Outcome

Empirically Defining Trajectories of Late-Life Cognitive and Functional Decline. - Hochstetler, Helen; Trzepacz, Paula T; Wang, Shufang; Yu, Peng; Case, Michael; Henley, David B; Degenhardt, Elisabeth; Leoutsakos, Jeannie-Marie; Lyketsos, Constantine G (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD) is associated with variable cognitive and functional decline, and it is difficult to predict who will develop the disease and how they will progress. OBJECTIVE: This exploratory study aimed to define latent classes from participants in the Alzheimer's Disease Neuroimaging Initiative (ADNI) database who had similar growth patterns of both cognitive and functional change using Growth Mixture Modeling (GMM), identify characteristics associated with those trajectories, and develop a decision tree using clinical predictors to determine which trajectory, as determined by GMM, individuals will most likely follow. METHODS: We used ADNI early mild cognitive impairment (EMCI), late MCI (LMCI), AD dementia, and healthy control (HC) participants with known amyloid-β status and follow-up assessments on the Alzheimer's Disease Assessment Scale - Cognitive Subscale or the Functional Activities Questionnaire (FAQ) up to 24 months postbaseline. GMM defined trajectories. Classification and Regression Tree (CART) used certain baseline variables to predict likely trajectory path. RESULTS: GMM identified three trajectory classes (C): C1 (n = 162, 13.6%) highest baseline impairment and steepest pattern of cognitive/functional decline; C3 (n = 819, 68.7%) lowest baseline impairment and minimal change on both; C2 (n = 211, 17.7%) intermediate pattern, worsening on both, but less steep than C1. C3 had fewer amyloid- or apolipoprotein-E ɛ4 (APOE4) positive and more healthy controls (HC) or EMCI cases. CART analysis identified two decision nodes using the FAQ to predict likely class with 82.3% estimated accuracy. CONCLUSIONS: Cognitive/functional change followed three trajectories with greater baseline impairment and amyloid and APOE4 positivity associated with greater progression. FAQ may predict trajectory class.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Apolipoprotein E4; Cognition Disorders; Databases, Factual; Dementia; Disease Progression; Female; Follow-Up Studies; Humans; Male; Middle Aged; Neuroimaging; Neuropsychological Tests; Surveys and Questionnaires

Evaluation of Cerebrospinal Fluid Assay Variability in Alzheimer's Disease. - White, Matthew T; Shaw, Leslie M; Xie, Sharon X (J Alzheimers Dis, 2016)
Studies of cerebrospinal fluid (CSF) biomarkers in Alzheimer's disease (AD) have indicated that much of the variability observed in the biomarkers may be due to measurement error. Biomarkers are often obtained with measurement error, which may make the diagnostic biomarker appear less effective than it truly is. In the Alzheimer's Disease Neuroimaging Initiative (ADNI) database, technical replicates of CSF biomarkers are available; the National Alzheimer's Coordinating Center database contains longitudinal replicates of CSF biomarkers. We focus on the area under the receiver operating characteristic curve (AUC) as the measure of diagnostic effectiveness for differentiating AD from normal cognition using CSF biomarkers and compare AUC estimates obtained by a more standard, naïve method (which uses a single observation per subject and ignores measurement error) to a maximum likelihood (ML) based method (which uses all replicates per subject and adjusts for measurement error). The choice of analysis method depends upon the noise to signal ratio (i.e., the magnitude of the measurement error variability relative to the true biomarker variability); moderate to high ratios may significantly bias the naïve AUC estimate, and the ML-based method would be preferred. The noise to signal ratios were low for the ADNI biomarkers but high for the tTau and pTau biomarkers in NACC. Correspondingly, the naïve and ML-based AUC estimates were nearly identical in the ADNI data but dissimilar for the tTau and pTau biomarkers in the NACC data. Therefore, using the naïve method is adequate for analysis of CSF biomarkers in the ADNI study, but the ML method is recommended for the NACC data.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Area Under Curve; Biomarkers; Databases, Factual; Female; Humans; Likelihood Functions; Male; Peptide Fragments; Phosphorylation; ROC Curve; tau Proteins

Extracellular Tau Paired Helical Filaments Differentially Affect Tau Pathogenic Mechanisms in Mitotic and Post-Mitotic Cells: Implications for Mechanisms of Tau Propagation in the Brain. - Varghese, Merina; Santa-Maria, Ismael; Ho, Lap; Ward, Libby; Yemul, Shrishailam; Dubner, Lauren; Księżak-Reding, Hanna; Pasinetti, Giulio Maria (J Alzheimers Dis, 2016)
The release of paired helical filaments (PHFs) from neurons into the extracellular space may contribute to the propagation of tau pathology across brain regions in Alzheimer's disease (AD) and other tauopathies. The majority of available mechanistic studies exploring the pathologic role of extracellular PHFs are conducted in proliferating cell lines. Here, we compare how extracellular PHFs induce tauopathy in mitotic cells and in post-mitotic brain neurons. In a mitotic cell line (HEK 293T), extracellular exposure to AD PHFs leads to an intracellular "aggresomal" type deposition of tau, coincidental with redistribution of dynein, a retrograde motor protein. We also observed that PHFs impaired proteasome degradation, but not autophagy. Exposure of cells to proteasome inhibitors was sufficient to induce intracellular tau aggregate formation as well as reorganization of dynein and the intermediate filament protein, vimentin. Thus, in mitotic cells, extracellular PHFs promote cellular tau aggregation, in part, by interfering with cellular proteasome degradation processes. In contrast with our observations with proliferating cells, exposure of post-mitotic primary neuronal cultures to AD PHFs did not promote "aggresomal" tau deposition, but instead resulted in a widespread accumulation of phosphorylated tau-immunoreactive swellings in neuritic processes, characterized by disturbed cytoskeletal organization of dynein and vimentin. Collectively, our observations suggest that extracellular PHFs may contribute to the propagation of tau pathology by independent mechanisms in post-mitotic and mitotic brain cells. These outcomes indicate that in addition to post-mitotic brain neurons, mitotic brain cells should also be considered as targets for therapeutic interventions to attenuate propagation of tauopathy.

Feasibility of a Memory Clinic-Based Physical Activity Prescription Program. - Vidoni, Eric D; Watts, Amber S; Burns, Jeffrey M; Greer, Colby S; Graves, Rasinio S; Van Sciver, Angela; Black, Jessica R; Cooper, Sarah K; Nagely, Allison C; Uphoff, Elaine; Volmer, Jennifer M; Bieberle, Natalie A (J Alzheimers Dis, 2016)
BACKGROUND: Effective programs for promoting physical activity are needed for those with cognitive impairment. OBJECTIVE: To test the feasibility of mobile Health (mHealth) technology-supported physical activity prescription from a tertiary care memory clinic. METHODS: This feasibility study was designed as a 16-week randomized, crossover trial of a physical activity prescription: 8 weeks of intervention, 8 weeks of baseline or maintenance phase data collection. We recruited 2 cohorts: 21 individuals with Alzheimer-related cognitive impairment (mean age 72.3 (5.2), 9 females), and 9 individuals with normal cognition (mean age 69.6 (5.8), 8 females). We gave each cohort an mHealth accelerometer-based physical activity prescription to double number of steps taken. Our primary outcomes were feasibility and safety. Our secondary outcomes were change in weekly steps taken, Dementia Quality of Life Scale, Self-efficacy Scale, 6-minute Walk, and mini-Physical Performance Test. RESULTS: Set-up and use of the device was not a barrier to participation. However, only 62% of participants with cognitive impairment completed the intervention. The cohort with cognitive impairment did not change their weekly step count above Week 1. All participants in the cohort with normal cognition were able to set up and use their device and increased their weekly step count above Week 1. There were no differences between Week 1 and Week 8 for any secondary measures in either cohort. CONCLUSIONS: Setup and daily use of mHealth technology appears to be feasible for a person with cognitive impairment with the help of a partner, but increasing daily step counts over 8 weeks was not achieved. Future work needs to assess alternative activity prescription goals or additional support for patients and their partners.

Fine Particulate Matter, Residential Proximity to Major Roads, and Markers of Small Vessel Disease in a Memory Study Population. - Wilker, Elissa H; Martinez-Ramirez, Sergi; Kloog, Itai; Schwartz, Joel; Mostofsky, Elizabeth; Koutrakis, Petros; Mittleman, Murray A; Viswanathan, Anand (J Alzheimers Dis, 2016)
BACKGROUND: Long-term exposure to ambient air pollution has been associated with impaired cognitive function and vascular disease in older adults, but little is known about these associations among people with concerns about memory loss. OBJECTIVE: To examine associations between exposures to fine particulate matter and residential proximity to major roads and markers of small vessel disease. METHODS: From 2004-2010, 236 participants in the Massachusetts Alzheimer's Disease Research Center Longitudinal Cohort participated in neuroimaging studies. Residential proximity to major roads and estimated 2003 residential annual average of fine particulate air pollution (PM2.5) were linked to measures of brain parenchymal fraction (BPF), white matter hyperintensities (WMH), and cerebral microbleeds. Associations were modeled using linear and logistic regression and adjusted for clinical and lifestyle factors. RESULTS: In this population (median age [interquartile range] = 74 [12], 57% female) living in a region with median 2003 PM2.5 annual average below the current Environmental Protection Agency (EPA) standard, there were no associations between living closer to a major roadway or for a 2μg/m3 increment in PM2.5 and smaller BPF, greater WMH volume, or a higher odds of microbleeds. However, a 2μg/m3 increment in PM2.5 was associated with -0.19 (95% Confidence Interval (CI): -0.37, -0.005) lower natural log-transformed WMH volume. Other associations had wide confidence intervals. CONCLUSIONS: In this population, where median 2003 estimated PM2.5 levels were below the current EPA standard, we observed no pattern of association between residential proximity to major roads or 2003 average PM2.5 and greater burden of small vessel disease or neurodegeneration.

Formulaic Language in People with Probable Alzheimer's Disease: A Frequency-Based Approach. - Zimmerer, Vitor C; Wibrow, Mark; Varley, Rosemary A (J Alzheimers Dis, 2016)
BACKGROUND: Language change can be a valuable biological marker of overall cognitive change in Alzheimer's disease (AD) and other forms of dementia. Previous reports have described increased use of language formulas in AD, i.e., combinations likely processed in a holistic manner. Words that commonly occur together are more likely to become a formula. OBJECTIVE: To determine if frequency of co-occurrence as one indicator for formulaic language can distinguish people with probable AD from controls and if variables are sensitive to time post-symptom onset. METHODS: We developed the Frequency in Language Analysis Tool (FLAT), which indicates degrees of formulaicity in an individual language sample. The FLAT accomplishes this by comparing individual language samples to co-occurrence data from the British National Corpus (BNC). Our analysis also contained more conventional language variables in order to assess novel contributions of the FLAT. We analyzed data from the Pitt Corpus, which is part of DementiaBank. RESULTS: Both conventional and co-occurrence variables were able to distinguish AD and control groups. According to co-occurrence data, people with probable AD produced more formulaic language than controls. Only co-occurrence variables correlated with disease progression. DISCUSSION: Frequency of word co-occurrences is one indicator for formulaicity and a valuable contribution to characterizing language change in AD.

Gene Expression Profiling in the APP/PS1KI Mouse Model of Familial Alzheimer's Disease. - Weissmann, Robert; Hüttenrauch, Melanie; Kacprowski, Tim; Bouter, Yvonne; Pradier, Laurent; Bayer, Thomas A; Kuss, Andreas W; Wirths, Oliver (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a devastating neurodegenerative disorder characterized by early intraneuronal amyloid-β (Aβ) accumulation, extracellular deposition of Aβ peptides, and intracellular hyperphosphorylated tau aggregates. These lesions cause dendritic and synaptic alterations and induce an inflammatory response in the diseased brain. Although the neuropathological characteristics of AD have been known for decades, the molecular mechanisms causing the disease are still under investigation. Studying gene expression changes in postmortem AD brain tissue can yield new insights into the molecular disease mechanisms. To that end, one can employ transgenic AD mouse models and the next-generation sequencing technology. In this study, a whole-brain transcriptome analysis was carried out using the well-characterized APP/PS1KI mouse model for AD. These mice display a robust phenotype reflected by working memory deficits at 6 months of age, a significant neuron loss in a variety of brain areas including the CA1 region of the hippocampus and a severe amyloid pathology. Based on deep sequencing, differentially expressed genes (DEGs) between 6-month-old WT or PS1KI and APP/PS1KI were identified and verified by qRT-PCR. Compared to WT mice, 250 DEGs were found in APP/PS1KI mice, while 186 DEGs could be found compared to PS1KI control mice. Most of the DEGs were upregulated in APP/PS1KI mice and belong to either inflammation-associated pathways or lysosomal activation, which is likely due to the robust intraneuronal accumulation of Aβ in this mouse model. Our comprehensive brain transcriptome study further highlights APP/PS1KI mice as a valuable model for AD, covering molecular inflammatory and immune responses.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Brain; Disease Models, Animal; Gene Expression Profiling; Male; Mice; Mice, Transgenic; Nerve Degeneration; Presenilin-1; Transcriptome

A Genetic Variant of the Sortilin 1 Gene is Associated with Reduced Risk of Alzheimer's Disease. - Andersson, Carl-Henrik; Hansson, Oskar; Minthon, Lennart; Andreasen, Niels; Blennow, Kaj; Zetterberg, Henrik; Skoog, Ingmar; Wallin, Anders; Nilsson, Staffan; Kettunen, Petronella (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a neurodegenerative disorder represented by the accumulation of intracellular tau protein and extracellular deposits of amyloid-β (Aβ) in the brain. The gene sortilin 1 (SORT1) has previously been associated with cardiovascular disease in gene association studies. It has also been proposed to be involved in AD pathogenesis through facilitating Aβ clearance by binding apoE/Aβ complexes prior to cellular uptake. However, the neuropathological role of SORT1 in AD is not fully understood. To evaluate the associations between gene variants of SORT1 and risk of AD, we performed genetic analyses in a Swedish case-control cohort. Ten single nucleotide polymorphisms (SNPs), covering the whole SORT1 gene, were selected and genotyped in 620 AD patients and 1107 controls. The SNP rs17646665, located in a non-coding region of the SORT1 gene, remained significantly associated with decreased risk of AD after multiple testing (pc = 0.0061). In addition, other SNPs were found to be nominally associated with risk of AD, as well as altered cognitive function and the CSF biomarker Aβ42, but these associations did not survive correction for multiple testing. The fact that SORT1 has been strongly associated with risk of cardiovascular disease is intriguing as cardiovascular disease is also regarded as a risk factor for AD. Finally, increased knowledge about SORT1 function has a potential to increase our understanding of APOE, the strongest risk factor for AD.

Genetic Variations in ABCA7 Can Increase Secreted Levels of Amyloid-β40 and Amyloid-β42 Peptides and ABCA7 Transcription in Cell Culture Models. - Bamji-Mirza, Michelle; Li, Yan; Najem, Dema; Liu, Qing Yan; Walker, Douglas; Lue, Lih-Fen; Stupak, Jacek; Chan, Kenneth; Li, Jianjun; Ghani, Mahdi; Yang, Ze; Rogaeva, Ekaterina; et al. (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is characterized by extracellular deposits of amyloid-β (Aβ) in the brain. ABCA7 is highly expressed in the brain and a susceptibility gene for late-onset AD (LOAD). The minor alleles at two ABCA7 single-nucleotide polymorphisms (SNPs), rs3764650 (T>G; intron13) and rs3752246 at a predicted myristoylation site (C>G; exon33; p.Gly1527Ala), are significantly associated with LOAD risk; however, the mechanism of this association is unknown. Functional consequences of both SNPs were examined in HEK293 and CHO cells stably expressing AβPPSwe. Luciferase reporter assays in HEK293 cells suggested that intron13 carrying rs3764650 major T-allele (int13-T) possessed promoter-enhancing capabilities. Co-transfection experiments with hABCA7 and int13-T resulted in significantly increased ABCA7 protein level relative to that with int13-G. Expression of hABCA7 carrying rs3752246 risk allele led to increases in secreted Aβ40 and Aβ42 and β-secretase activity in CHO- and HEK-AβPPSwe cells. Hydroxymyristic acid treatment of cells expressing hABCA7 carrying the rs3752246 major G allele resulted in increased β-secretase activity and levels of Aβ, suggesting that lack of myristoylation contributes to the observed cell-phenotypes. Molecular weight determination, by gel-electrophoresis and mass spectrometry, of hABCA7 peptides spanning position 1527 showed loss of post-translational modification in the risk-allele peptide. These results suggest that decreased expression, or impaired function, of ABCA7 may contribute to AD pathology.

Geographical Variation in Antipsychotic Drug Use in Elderly Patients with Dementia: A Nationwide Study. - Zakarias, Johanne Købstrup; Jensen-Dahm, Christina; Nørgaard, Ane; Stevnsborg, Lea; Gasse, Christiane; Andersen, Bodil Gramkow; Søren, Jakobsen; Waldorff, Frans Boch; Moos, Torben; Waldemar, Gunhild (J Alzheimers Dis, 2016)
BACKGROUND: Use of antipsychotics in elderly patients with dementia has decreased in the past decade due to safety regulations; however use is still high. Geographical variation may indicate discrepancies in clinical practice and lack of adherence to evidence-based guidelines for the management of behavioral symptoms. OBJECTIVE: To investigate potential geographical variances in use of antipsychotic drugs in dementia care. METHODS: A registry-based cross-sectional study in the entire elderly population of Denmark (≥65 years) conducted in 2012. Data included place of residence, prescriptions filled, and hospital discharge diagnoses. Antipsychotic drug use among elderly with (n = 34,536) and without (n = 931,203) a dementia diagnosis was compared across the five regions and 98 municipalities in Denmark, adjusted for age and sex. RESULTS: In 2012, the national prevalence of antipsychotic drug use was 20.7% for elderly patients with dementia, with a national incidence of 3.9%. The prevalence ranged from 17.0% to 23.3% in the five regions and from 7.5% to 33.1% in the 98 municipalities, demonstrating an over four-fold difference. CONCLUSION: The observed geographical variation was more pronounced at municipal level as compared to regional level, suggesting that the variation may be related to variances in clinical practice in primary care. This study highlights an urgent need for further educating professional carers and physicians to guide non-pharmacological as well as pharmacological management of neuropsychiatric symptoms in elderly patients with dementia.

Greater specificity for cerebrospinal fluid P-tau231 over P-tau181 in the differentiation of healthy controls from Alzheimer's disease. - Spiegel, Jonathan; Pirraglia, Elizabeth; Osorio, Ricardo S; Glodzik, Lidia; Li, Yi; Tsui, Wai; Saint Louis, Leslie A; Randall, Catherine; Butler, Tracy; Xu, Jinfeng; Zinkowski, Raymond P; Zetterberg, Henrik; et al. (J Alzheimers Dis, 2016)
Cerebrospinal fluid (CSF) measures of phosphorylated-tau (P-tau) 231 and P-tau181 are two biomarkers for the identification of tau pathology as related to Alzheimer's disease (AD). While both are pathologically validated, their relative diagnostic performances are not well known. This cross-sectional diagnostic study of 87 normal (NL) subjects and 28 AD subjects compared CSF P-tau231 with CSF P-tau181. Logistic regression modeling demonstrated that the P-tau231 was superior to the P-tau181 in the diagnostic classifications. At a fixed 85% sensitivity cutoff, the ROC analysis shows that P-tau231 has greater overall specificity than P-tau181. While both P-tau analytes demonstrated equivalent negative predictive accuracies, P-tau231 yielded significantly fewer false positives. Moreover, P-tau231, but not P-tau181, demonstrated sensitivity to the E4 genotype. A postmortem validation with 9 AD subjects confirmed the superiority of the CSF P-tau231 specificity. This study suggests that P-tau231 has the potential to improve the CSF tau biomarker diagnosis of AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Case-Control Studies; Cross-Sectional Studies; Female; Humans; Logistic Models; Male; Middle Aged; Phosphorylation; ROC Curve; Sensitivity and Specificity; tau Proteins

Gx-50 Inhibits Neuroinflammation via α7 nAChR Activation of the JAK2/STAT3 and PI3K/AKT Pathways. - Shi, Shi; Liang, Dongli; Bao, Min; Xie, Yilin; Xu, Wangjie; Wang, Lianyun; Wang, Zhaoxia; Qiao, Zhongdong (J Alzheimers Dis, 2016)
Recent studies have revealed that the α7 nicotinic acetylcholine receptor (α7 nAChR) is a critical link between inflammation and neurodegeneration, which is closely associated with Alzheimer's disease (AD). The JAK2/STAT3 and PI3K/AKT signaling pathways contribute to the neuroprotective and anti-inflammatory effects of α7nAChR. Our previous studies have shown that treatment with gx-50 improves cognitive function and is neuroprotective. Here, we investigated the effect of gx-50 on α7 nAChR and Aβ-induced inflammation in microglia. First, the binding affinity of gx-50 to α7 nAChR was examined using the fluorescence-based Octet RED system, and the expression of α7 nAChR was detected using real-time PCR and western blotting. We also investigated downstream events of α7 nAChR activity, including the translocation of p-STAT3 and the phosphorylation of JAK2, STAT3, PI3K, and AKT. Finally, the effect of gx-50 on Aβ-induced inflammation via α7 nAChR-mediated signaling pathways was investigated using cytokine assays. The results showed that gx-50 is able to act as a specific ligand to activate α7 nAChR, which then upregulates the JAK2/STAT3 and PI3K/AKT signaling pathways to inhibit the secretions of pro-inflammatory cytokines, such as IL-1β. In conclusion, the results suggest that gx-50 could inhibit the Aβ-induced inflammatory response in microglia via α7 nAChR activity, which might be a successful therapeutic target against AD.
Keywords: Acrylamides; alpha7 Nicotinic Acetylcholine Receptor; Amyloid beta-Peptides; Analysis of Variance; Animals; Anti-Inflammatory Agents; Cell Line, Transformed; Cytokines; Enzyme Inhibitors; Enzyme-Linked Immunosorbent Assay; Gene Expression Regulation; Janus Kinase 2; Mice; Microglia; Phosphatidylinositol 3-Kinases; Protein Binding; RNA, Messenger; Signal Transduction

Gypenoside XVII Enhances Lysosome Biogenesis and Autophagy Flux and Accelerates Autophagic Clearance of Amyloid-β through TFEB Activation. - Meng, Xiangbao; Luo, Yun; Liang, Tian; Wang, Mengxia; Zhao, Jingyu; Sun, Guibo; Sun, Xiaobo (J Alzheimers Dis, 2016)
A strategy for activating transcription factor EB (TFEB) to restore autophagy flux may provide neuroprotection against Alzheimer's disease. Our previous study reported that gypenoside XVII (GP-17), which is a major saponin abundant in ginseng and Panax notoginseng, ameliorated amyloid-β (Aβ)25-35-induced apoptosis in PC12 cells by regulating autophagy. In the present study, we aimed to determine whether GP-17 has neuroprotective effects on PC12 cells expressing the Swedish mutant of APP695 (APP695swe) and APP/PS1 mice. We also investigated the underlying mechanism. We found that GP-17 could significantly increase Atg5 expression and the conversion of LC3-I to LC3-II in APP695 cells, which was associated with a reduction in p62 expression. GP-17 also elevated the number of LC3 puncta in APP695 cells transduced with pCMV-GFP-LC3. GP-17 promoted the autophagy-based elimination of AβPP, Aβ40, and Aβ42 in APP695swe cells and prevented the formation of Aβ plaques in the hippocampus and cortex of APP/PS1 mice. Furthermore, spatial learning and memory deficits were cured. Atg5 knockdown could abrogate the GP-17-mediated removal of AβPP, Aβ40, and Aβ42 in APP695swe cells. GP-17 upregulated LAMP-1, increased LysoTracker staining, and augmented LAMP-1/LC3-II co-localization. GP-17 could release TFEB from TFEB/14-3-3 complexes, which led to TFEB nuclear translocation and the induction of autophagy and lysosome biogenesis and resulted in the amelioration of autophagy flux. The knockdown of TFEB could abolish these effects of GP-17. In summary, these results demonstrated that GP-17 conferred protective effects to the cellular and rodent models of Alzheimer's disease by activating TFEB.

Halting of Caspase Activity Protects Tau from MC1-Conformational Change and Aggregation. - Mead, Emma; Kestoras, Dimitra; Gibson, Yolanda; Hamilton, Lucy; Goodson, Ross; Jones, Sophie; Eversden, Sarah; Davies, Peter; O'Neill, Michael; Hutton, Michael; Szekeres, Philip; Wolak, Joanna (J Alzheimers Dis, 2016)
Intracellular neurofibrillary tangles (NFTs) are the hallmark of Alzheimer's disease and other tauopathies in which tau, a microtubule-associated protein, loses its ability to stabilize microtubules. Several post-translational modifications including phosphorylation and truncation increase tau's propensity to aggregate thus forming NFTs; however, the mechanisms underlying tau conformational change and aggregation still remain to be defined. Caspase activation and subsequent proteolytic cleavage of tau is thought to be a potential trigger of this disease-related pathological conformation. The aim of this work was to investigate the link between caspase activation and a disease-related conformational change of tau in a neuroblastoma cell-based model of spontaneous tau aggregation. We demonstrated that caspase induction initiates proteolytic cleavage of tau and generation of conformationally altered and aggregated tau recognized by the MC1 conformational antibody. Most importantly, these events were shown to be attenuated with caspase inhibitors. This implies that therapeutics aimed at inhibiting caspase-mediated tau cleavage may prove beneficial in slowing cleavage and aggregation, thus potentially halting tau pathology and disease progression.

Heterogeneous Language Profiles in Patients with Primary Progressive Aphasia due to Alzheimer's Disease. - Louwersheimer, Eva; Keulen, M Antoinette; Steenwijk, Martijn D; Wattjes, Mike P; Jiskoot, Lize C; Vrenken, Hugo; Teunissen, Charlotte E; van Berckel, Bart N M; van der Flier, Wiesje M; Scheltens, Philip; van Swieten, John C; Pijnenburg, Yolande A L (J Alzheimers Dis, 2016)
BACKGROUND: The logopenic variant of Primary Progressive Aphasia (lvPPA) is associated with underlying Alzheimer's disease (AD) pathology and characterized by impaired single word retrieval and repetition of phrases and sentences. OBJECTIVE: We set out to study whether logopenic aphasia is indeed the prototypic language profile in PPA patients with biomarker evidence of underlying AD pathology and to correlate language profiles with cortical atrophy patterns on MRI. METHODS: Inclusion criteria: (I) clinical diagnosis of PPA; (II) CSF profile and/or PiB-PET scan indicative for amyloid pathology; (III) availability of expert language evaluation. Based on language evaluation, patients were classified as lvPPA (fulfilling lvPPA core criteria), lvPPA extended (fulfilling core criteria plus other language disturbances), or PPA unclassifiable (not fulfilling lvPPA core criteria). Cortical atrophy patterns on MRI were visually rated and quantitative measurements of cortical thickness were performed using FreeSurfer. RESULTS: We included 22 patients (age 67±7 years, 50% female, MMSE 21±6). 41% were classified as lvPPA, 36% as lvPPA extended with additional deficits in language comprehension and/or confrontation naming, and 23% as PPA unclassifiable. By both qualitative and quantitative measurements, patients with lvPPA showed mild global cortical atrophy on MRI, whereas patients with lvPPA extended showed more focal cortical atrophy, predominantly at the left tempo-parietal side. For PPA unclassifiable, qualitative measurements revealed a heterogeneous atrophy pattern. CONCLUSION: Although most patients fulfilled the lvPPA criteria, we found that their language profiles were heterogeneous. The clinical and radiological spectrum of PPA due to underlying AD pathology is broader than pure lvPPA.
Keywords: Aged; Alzheimer Disease; Aphasia, Primary Progressive; Atrophy; Biomarkers; Brain; Female; Humans; Language; Language Tests; Magnetic Resonance Imaging; Male; Mental Status Schedule; Organ Size; Positron-Emission Tomography; Retrospective Studies

Homocysteine and Alzheimer's Disease: Evidence for a Causal Link from Mendelian Randomization. - Hu, Qingting; Teng, Wenhui; Li, Jiajia; Hao, Fangfang; Wang, Naidong (J Alzheimers Dis, 2016)
BACKGROUND/OBJECTIVE: The relationship between plasma homocysteine (Hcy) levels and Alzheimer's disease (AD) has been studied for many years, but remains controversial. While a recent meta-analysis of epidemiological studies, which included observational studies, indicated that homocysteine may be a risk factor for AD, there remains a need to further demonstrate this link due to the large degree of heterogeneity between studies. Epidemiological studies have certain limitations, as their results can be affected by confounding factors and reverse causation. In this study, we evaluated the relationship between plasma homocysteine and AD by using a Mendelian randomization method to avoid problems of confounding bias and reverse causality. METHODS: We searched the PubMed and EMBASE databases for reports regarding the MTHFR C677T polymorphism (rs1801133) from the time of their inception to September 2015. These reports were combined with related observational studies, and used to evaluate the effect of MTHFR C677T (rs1801133) on the risk for AD. A recent meta-analysis of genome-wide association studies had previously suggested a relationship between homocysteine and MTHFR C677T (rs 1801133). RESULTS: Our met-analysis included 34 studies with 9397 subjects, and demonstrated a significant relationship between plasma total homocysteine levels and the risk for AD (OR = 3.37; 95% CI = 1.90-5.95; p = 2.9×10-5). CONCLUSION: Our meta-analysis demonstrated a causal link between plasma total homocysteine and the risk for AD, and provides a new insight into the etiology and prevention of AD.

Human ApoE ɛ2 Promotes Regulatory Mechanisms of Bioenergetic and Synaptic Function in Female Brain: A Focus on V-type H+-ATPase. - Woody, Sarah K; Zhou, Helen; Ibrahimi, Shaher; Dong, Yafeng; Zhao, Liqin (J Alzheimers Dis, 2016)
Humans possess three major isoforms of the apolipoprotein E (ApoE) gene encoded by three alleles: ApoE ɛ2 (ApoE2), ApoE ɛ3 (ApoE3), and ApoE ɛ4 (ApoE4). It is established that the three ApoE isoforms confer differential susceptibility to Alzheimer's disease (AD); however, an in-depth molecular understanding of the underlying mechanisms is currently unavailable. In this study, we examined the cortical proteome differences among the three ApoE isoforms using 6-month-old female, human ApoE2, ApoE3, and ApoE4 gene-targeted replacement mice and two-dimensional proteomic analyses. The results reveal that the three ApoE brains differ primarily in two areas: cellular bioenergetics and synaptic transmission. Of particular significance, we show for the first time that the three ApoE brains differentially express a key component of the catalytic domain of the V-type H+-ATPase (Atp6v), a proton pump that mediates the concentration of neurotransmitters into synaptic vesicles and thus is crucial in synaptic transmission. Specifically, our data demonstrate that ApoE2 brain exhibits significantly higher levels of the B subunit of Atp6v (Atp6v1B2) when compared to both ApoE3 and ApoE4 brains, with ApoE4 brain exhibiting the lowest expression. Our additional analyses show that Atp6v1B2 is significantly impacted by aging and AD pathology and the data suggest that Atp6v1B2 deficiency could be involved in the progressive loss of synaptic integrity during early development of AD. Collectively, our findings indicate that human ApoE isoforms differentially modulate regulatory mechanisms of bioenergetic and synaptic function in female brain. A more efficient and robust status in both areas-in which Atp6v may play a role-could serve as a potential mechanism contributing to the neuroprotective and cognition-favoring properties associated with the ApoE2 genotype.

Human Truncated Tau Induces Mature Neurofibrillary Pathology in a Mouse Model of Human Tauopathy. - Zimova, Ivana; Brezovakova, Veronika; Hromadka, Tomas; Weisova, Petronela; Cubinkova, Veronika; Valachova, Bernadeta; Filipcik, Peter; Jadhav, Santosh; Smolek, Tomas; Novak, Michal; Zilka, Norbert (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) represents the most common neurodegenerative disorder. Several animal models have been developed in order to test pathophysiological mechanisms of the disease and to predict effects of pharmacological interventions. Here we examine the molecular and behavioral features of R3m/4 transgenic mice expressing human non-mutated truncated tau protein (3R tau, aa151-391) that were previously used for efficacy testing of passive tau vaccine. The mouse model reliably recapitulated crucial histopathological features of human AD, such as pre-tangles, neurofibrillary tangles, and neuropil threads. The pathology was predominantly located in the brain stem. Transgenic mice developed mature sarkosyl insoluble tau complexes consisting of mouse endogenous and human truncated and hyperphosphorylated forms of tau protein. The histopathological and biochemical features were accompanied by significant sensorimotor impairment and reduced lifespan. The sensorimotor impairment was monitored by a highly sensitive, fully-automated tool that allowed us to assess early deficit in gait and locomotion. We suggest that the novel transgenic mouse model can serve as a valuable tool for analysis of the therapeutic efficacy of tau vaccines for AD therapy.

"I Don't Think Of It As An Illness": Illness Representations in Mild to Moderate Dementia. - Clare, Linda; Quinn, Catherine; Jones, Ian Rees; Woods, Robert T (J Alzheimers Dis, 2016)
The self-regulatory model proposes that illness representations influence adjustment and coping in chronic conditions. Better understanding of the illness representations held by people with dementia could help with targeting information and support so as to optimize adjustment and coping. In this mixed-methods study of illness representations among people with mild to moderate Alzheimer's, vascular, or mixed dementia we aimed to clarify the nature of the representations held, to determine whether specific profiles can be identified based on perceptions of the identity and cause of the condition, and to examine associations between these profiles and other participant characteristics. Data were collected in the second wave of the Memory Impairment and Dementia Awareness Study (MIDAS). Sixty-four people with dementia, who had been told their diagnosis at a memory clinic, completed interviews and responded to questionnaires. In each case a carer was also interviewed. Cluster analysis based on responses about identity and cause identified three profiles. 'Illness' cluster participants saw themselves as living with an illness and used diagnostic labels, 'ageing' cluster participants did not use diagnostic labels and viewed their difficulties as related to ageing, and 'no problem' cluster participants considered that they did not have any difficulties. 'Illness' cluster participants had better cognition and better awareness, but lower mood, and perceived more practical consequences, than 'ageing' cluster participants. Holding an 'illness' model may not be advantageous. Rather than encouraging adoption of such a model, it may be preferable to target information and select interventions in line with the person's representation profile.
Keywords: Adaptation, Psychological; Aged; Aged, 80 and over; Aging; Awareness; Caregivers; Dementia; Female; Follow-Up Studies; Humans; Male; Middle Aged; Psychiatric Status Rating Scales; Residence Characteristics; Self Concept; Statistics, Nonparametric; Surveys and Questionnaires

Identification of Physician-Diagnosed Alzheimer's Disease and Related Dementias in Population-Based Administrative Data: A Validation Study Using Family Physicians' Electronic Medical Records. - Jaakkimainen, R Liisa; Bronskill, Susan E; Tierney, Mary C; Herrmann, Nathan; Green, Diane; Young, Jacqueline; Ivers, Noah; Butt, Debra; Widdifield, Jessica; Tu, Karen (J Alzheimers Dis, 2016)
BACKGROUND: Population-based surveillance of Alzheimer's and related dementias (AD-RD) incidence and prevalence is important for chronic disease management and health system capacity planning. Algorithms based on health administrative data have been successfully developed for many chronic conditions. The increasing use of electronic medical records (EMRs) by family physicians (FPs) provides a novel reference standard by which to evaluate these algorithms as FPs are the first point of contact and providers of ongoing medical care for persons with AD-RD. OBJECTIVE: We used FP EMR data as the reference standard to evaluate the accuracy of population-based health administrative data in identifying older adults with AD-RD over time. METHODS: This retrospective chart abstraction study used a random sample of EMRs for 3,404 adults over 65 years of age from 83 community-based FPs in Ontario, Canada. AD-RD patients identified in the EMR were used as the reference standard against which algorithms identifying cases of AD-RD in administrative databases were compared. RESULTS: The highest performing algorithm was "one hospitalization code OR (three physician claims codes at least 30 days apart in a two year period) OR a prescription filled for an AD-RD specific medication" with sensitivity 79.3% (confidence interval (CI) 72.9-85.8%), specificity 99.1% (CI 98.8-99.4%), positive predictive value 80.4% (CI 74.0-86.8%), and negative predictive value 99.0% (CI 98.7-99.4%). This resulted in an age- and sex-adjusted incidence of 18.1 per 1,000 persons and adjusted prevalence of 72.0 per 1,000 persons in 2010/11. CONCLUSION: Algorithms developed from health administrative data are sensitive and specific for identifying older adults with AD-RD.

Immunization with Small Amyloid-β-derived Cyclopeptide Conjugates Diminishes Amyloid-β-Induced Neurodegeneration in Mice. - Mulder, Cornelis K; Dong, Yun; Brugghe, Humphrey F; Timmermans, Hans A M; Tilstra, Wichard; Westdijk, Janny; van Riet, Elly; van Steeg, Harry; Hoogerhout, Peter; Eisel, Ulrich L M (J Alzheimers Dis, 2016)
BACKGROUND: Soluble oligomeric (misfolded) species of amyloid-β (Aβ) are the main mediators of toxicity in Alzheimer's disease (AD). These oligomers subsequently form aggregates of insoluble fibrils that precipitate as extracellular and perivascular plaques in the brain. Active immunization against Aβ is a promising disease modifying strategy. However, eliciting an immune response against Aβ in general may interfere with its biological function and was shown to cause unwanted side-effects. Therefore, we have developed a novel experimental vaccine based on conformational neo-epitopes that are exposed in the misfolded oligomeric Aβ, inducing a specific antibody response. OBJECTIVE: Here we investigate the protective effects of the experimental vaccine against oligomeric Aβ1-42-induced neuronal fiber loss in vivo. METHODS: C57BL/6 mice were immunized or mock-immunized. Antibody responses were measured by enzyme-linked immunosorbent assay. Next, mice received a stereotactic injection of oligomeric Aβ1-42 into the nucleus basalis of Meynert (NBM) on one side of the brain (lesion side), and scrambled Aβ1-42 peptide in the contralateral NBM (control side). The densities of choline acetyltransferase-stained cholinergic fibers origination from the NBM were measured in the parietal neocortex postmortem. The percentage of fiber loss in the lesion side was determined relative to the control side of the brain. RESULTS: Immunized responders (79%) showed 23% less cholinergic fiber loss (p = 0.01) relative to mock-immunized mice. Moreover, fiber loss in immunized responders correlated negatively with the measured antibody responses (R2 = 0.29, p = 0.02). CONCLUSION: These results may provide a lead towards a (prophylactic) vaccine to prevent or at least attenuate (early onset) AD symptoms.

Impact of Omega-3 Fatty Acid Supplementation on Memory Functions in Healthy Older Adults. - Külzow, Nadine; Witte, A Veronica; Kerti, Lucia; Grittner, Ulrike; Schuchardt, Jan Philipp; Hahn, Andreas; Flöel, Agnes (J Alzheimers Dis, 2016)
As the process of Alzheimer's disease (AD) begins years before disease onset, searching for prevention strategies is of major medical and economic importance. Nutritional supplementation with long-chain polyunsaturated omega-3 fatty acids (LC-n3-FA) may exert beneficial effects on brain structure and function. However, experimental evidence in older adults without clinical dementia is inconsistent, possibly due to low sensitivity of previously employed test batteries for detecting subtle improvements in cognition in healthy individuals. Here we used LOCATO, recently described as a robust and sensitive tool for assessing object-location memory (OLM) in older adults, to evaluate the impact of LC-n3-FA supplementation on learning and memory formation. In a double-blind placebo-controlled proof-of-concept study, 44 (20 female) cognitively healthy individuals aged 50-75 years received either LC-n3-FA (2,200 mg/day, n = 22) or placebo (n = 22) for 26 weeks. Before and after intervention, memory performance in the OLM-task (primary) was tested. As secondary outcome parameters, performance in Rey Auditory Verbal Learning Test (AVLT), dietary habits, omega-3-index, and other blood-derived parameters were assessed. Omega-3 index increased significantly in the LC-n3-FA group compared with the placebo group. Moreover, recall of object locations was significantly better after LC-n3-FA supplementation compared with placebo. Performance in the AVLT was not significantly affected by LC-n3-FA. This double-blind placebo-controlled proof-of-concept study provides further experimental evidence that LC-n3-FA exert positive effects on memory functions in healthy older adults. Our findings suggest novel strategies to maintain cognitive functions into old age.
Keywords: Aged; Apolipoproteins E; Auditory Perception; Blood Chemical Analysis; Cognitive Aging; Dietary Supplements; Double-Blind Method; Fatty Acids, Omega-3; Feeding Behavior; Female; Humans; Learning; Male; Memory; Middle Aged; Neuropsychological Tests; Nootropic Agents; Treatment Outcome

Impacts of High Serum Total Cholesterol Level on Brain Functional Connectivity in Non-Demented Elderly. - Zhang, Ting; Li, He; Zhang, Junying; Li, Xin; Qi, Di; Wang, Nuo; Zhang, Zhanjun (J Alzheimers Dis, 2016)
Epidemiological and clinical studies suggest that high serum cholesterol is a risk factor of dementia. However, the effects of cholesterol on cognition and brain remain largely unclear. This study aims to investigate the associations between serum total cholesterol (TC) and neuropsychological performance, and intrinsic functional networks in non-demented elderly. Among a cohort of 120 community-dwelling Beijing residents, 29 subjects in the high-TC group (1st quartile) and 31 in the low-TC group (4th quartile) were included in this study, and underwent a battery of neuropsychological tests and magnetic resonance imaging (MRI) scans, including T2- and T1-weighted imaging, and resting-state functional MRI. No significant group difference was found in any of the neuropsychological tests used. Stronger connectivity in the default mode network was observed in the high-TC group compared to that in the low-TC group (p <  0.001, uncorrected). While in the salience network (SN), the high-TC group showed lower connectivity in the anterior cingulate cortex and frontal regions, compared to the low-TC group (p <  0.05, FWE corrected). Our findings suggest that in non-demented elderly persons, high serum cholesterol is associated with disruption of functional connectivity in the SN. The results not only deepen our understanding of how cholesterol affects the brain, but are also significant for selecting sensitive indicators for monitoring the impairments of cholesterol on the neural system.
Keywords: Aged; Brain; Brain Mapping; Cholesterol; Cognition; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Nerve Net; Neuropsychological Tests

Increase of α-Secretase ADAM10 in Platelets Along Cognitively Healthy Aging. - Schuck, Florian; Wolf, Dominik; Fellgiebel, Andreas; Endres, Kristina (J Alzheimers Dis, 2016)
ADAM10 is one of the key players in ectodomain-shedding of the amyloid-β protein precursor (AβPP). Previous research with postmortem tissue has shown reduced expression and activity of ADAM10 within the central nervous system (CNS) of Alzheimer's disease (AD) patients. Determination of cerebral ADAM10 in living humans is hampered by its transmembrane property; only the physiological AβPP cleavage product generated by ADAM10, sAβPPα, can be assessed in cerebrospinal fluid. Establishment of surrogate markers in easily accessible material therefore is crucial. It has been demonstrated that ADAM10 is expressed in platelets and that platelet amount is decreased in AD patients. Just recently it has been shown that platelet ADAM10 and cognitive performance of AD patients positively correlate. In contrast to AD patients, to our knowledge almost no information has been published regarding ADAM10 expression during normal aging. We investigated ADAM10 amount and activity in platelets of cognitively healthy individuals from three different age groups ranging from 22-85 years. Interestingly, we observed an age-dependent increase in ADAM10 levels and activity in platelets.
Keywords: ADAM Proteins; ADAM10 Protein; Adult; Age Factors; Aged; Aged, 80 and over; Aging; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Analysis of Variance; Apolipoprotein E4; Cognition; Female; Healthy Volunteers; Humans; Integrin beta3; Male; Membrane Proteins; Middle Aged; Neuropsychological Tests; Young Adult

Increased Intrinsic Activity of Medial-Temporal Lobe Subregions is Associated with Decreased Cortical Thickness of Medial-Parietal Areas in Patients with Alzheimer's Disease Dementia. - Pasquini, Lorenzo; Scherr, Martin; Tahmasian, Masoud; Myers, Nicholas E; Ortner, Marion; Kurz, Alexander; Förstl, Hans; Zimmer, Claus; Grimmer, Timo; Akhrif, Atae; Wohlschläger, Afra M; Riedl, Valentin; et al. (J Alzheimers Dis, 2016)
In Alzheimer's disease (AD), disrupted connectivity between medial-parietal cortices and medial-temporal lobes (MTL) is linked with increased MTL local functional connectivity, and parietal atrophy is associated with increased MTL memory activation. We hypothesized that intrinsic activity in MTL subregions is increased and associated with medial-parietal degeneration and impaired memory in AD. To test this hypothesis, resting-state-functional and structural-MRI was assessed in 22 healthy controls, 22 mild cognitive impairment patients, and 21 AD-dementia patients. Intrinsic activity was measured by power-spectrum density of blood-oxygenation-level-dependent signal, medial-parietal degeneration by cortical thinning. In AD-dementia patients, intrinsic activity was increased for several right MTL subregions. Raised intrinsic activity in dentate gyrus and cornu ammonis 1 was associated with cortical thinning in posterior cingulate cortices, and at-trend with impaired delayed recall. Critically, increased intrinsic activity in the right entorhinal cortex was associated with ipsilateral posterior cingulate degeneration. Our results provide evidence that in AD, intrinsic activity in MTL subregions is increased and associated with medial-parietal atrophy. Results fit a model in which medial-parietal degeneration contributes to MTL dysconnectivity from medial-parietal cortices, potentially underpinning disinhibition-like changes in MTL activity.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Memory Disorders; Middle Aged; Nerve Net; Parietal Lobe; Temporal Lobe

Increased Levels of Extracellular Microvesicle Markers and Decreased Levels of Endocytic/Exocytic Proteins in the Alzheimer's Disease Brain. - Musunuri, Sravani; Khoonsari, Payam Emami; Mikus, Maria; Wetterhall, Magnus; Häggmark-Mänberg, Anna; Lannfelt, Lars; Erlandsson, Anna; Bergquist, Jonas; Ingelsson, Martin; Shevchenko, Ganna; Nilsson, Peter; Kultima, Kim (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD) is a chronic neurodegenerative disorder accounting for more than 50% of all dementia cases. AD neuropathology is characterized by the formation of extracellular plaques and intracellular neurofibrillary tangles consisting of aggregated amyloid-β and tau, respectively. The disease mechanism has only been partially elucidated and is believed to also involve many other proteins. OBJECTIVE: This study intended to perform a proteomic profiling of post mortem AD brains and compare it with control brains as well as brains from other neurological diseases to gain insight into the disease pathology. METHODS: Here we used label-free shotgun mass spectrometry to analyze temporal neocortex samples from AD, other neurological disorders, and non-demented controls, in order to identify additional proteins that are altered in AD. The mass spectrometry results were verified by antibody suspension bead arrays. RESULTS: We found 50 proteins with altered levels between AD and control brains. The majority of these proteins were found at lower levels in AD. Pathway analyses revealed that several of the decreased proteins play a role in exocytic and endocytic pathways, whereas several of the increased proteins are related to extracellular vesicles. Using antibody-based analysis, we verified the mass spectrometry results for five representative proteins from this group of proteins (CD9, HSP72, PI42A, TALDO, and VAMP2) and GFAP, a marker for neuroinflammation. CONCLUSIONS: Several proteins involved in exo-endocytic pathways and extracellular vesicle functions display altered levels in the AD brain. We hypothesize that such changes may result in disturbed cellular clearance and a perturbed cell-to-cell communication that may contribute to neuronal dysfunction and cell death in AD.

Inequalities in Access to Treatment and Care for Patients with Dementia and Immigrant Background: A Danish Nationwide Study. - Stevnsborg, Lea; Jensen-Dahm, Christina; Nielsen, Thomas R; Gasse, Christiane; Waldemar, Gunhild (J Alzheimers Dis, 2016)
BACKGROUND: Previous studies demonstrated lower quality diagnostic assessment of dementia in immigrant populations, but knowledge about the quality of treatment and care for dementia is still lacking. OBJECTIVE: To conduct a nationwide registry-based study to determine whether inequality exists regarding access to anti-dementia treatment and care between immigrant and Danish-born patients with dementia. METHODS: A cross-sectional register-based study was conducted in the entire elderly (60≥years) population with dementia in Denmark in 2012 (n = 34,877). The use of anti-dementia drugs and residency in a nursing home were compared among Danish-born and Western and non-Western immigrants with dementia. Logistic regression analysis was done with adjustment for age, sex, comorbidity, marital status, basis of inclusion, and time since dementia diagnosis. RESULTS: Immigrant background was associated with a significantly lower likelihood of receiving anti-dementia drug therapy (odds ratio (OR) [95% confidence interval (CI)]): non-Western = 0.70 [0.56-0.87]; Western = 0.74 [0.63-0.87]). No significant differences were found in type or amount of anti-dementia medication dispensed between the population groups (proxy measure for adherence). Non-Western immigrants were significantly less likely to live in a nursing home (0.52 [0.41-0.65]). CONCLUSION: This nationwide registry-based study indicated a worrisome difference in access to anti-dementia treatment and care for dementia patients with an immigrant background, but similar levels of adherence compared with the Danish-born population. Further research is necessary to pinpoint barriers to access to suitable healthcare among elderly immigrants with dementia but also to identify and develop culturally sensitive methods for their treatment and care.

Insight into the Dissociation of Behavior from Histology in Synucleinopathies and in Related Neurodegenerative Diseases. - Sekiyama, Kazunari; Takamatsu, Yoshiki; Koike, Wakako; Waragai, Masaaki; Takenouchi, Takato; Sugama, Shuei; Hashimoto, Makoto (J Alzheimers Dis, 2016)
Recent clinical trials using immunization approaches against Alzheimer's disease (AD) have failed to demonstrate improved cognitive functions in patients, despite potent suppression in the formation of both senile plaques and other amyloid-β deposits in postmortem brains. Similarly, we observed that treatment with ibuprofen, a non-steroidal anti-inflammatory drug, was effective in improving the histopathology, such as reducing both protein aggregation and glial activation, in the brains of transgenic mice expressing dementia with Lewy bodies-linked P123H β-synuclein. In contrast, only a small improvement in cognitive functions was observed in these mice. Collectively, it is predicted that histology does not correlate with behavior that is resilient and resistant to therapeutic stimuli. Notably, such a 'discrepancy between histology and behavior' is reminiscent of AD-like pathologies and incidental Lewy bodies, which are frequently encountered in postmortem brains of the elderly who had been asymptomatic for memory loss and Parkinsonism during their lives. We suggest that 'the discrepancy between histology and behavior' may be a universal feature that is associated with various aspects of neurodegenerative diseases. Furthermore, given that the cognitive reserve is specifically observed in human brains, human behavior may be evolutionally distinct from that in other animals, thus, contributing to the differential efficiency of therapy between human and lower animals, an important issue in the therapy of neurodegenerative diseases. Overall, it is important to better understand 'the discrepancy between histology and behavior' in the mechanism of neurodegeneration for the development of effective therapies against neurodegenerative diseases.

Integrated Analysis of Alzheimer's Disease and Schizophrenia Dataset Revealed Different Expression Pattern in Learning and Memory. - Li, Wen-Xing; Dai, Shao-Xing; Liu, Jia-Qian; Wang, Qian; Li, Gong-Hua; Huang, Jing-Fei (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) and schizophrenia (SZ) are both accompanied by impaired learning and memory functions. This study aims to explore the expression profiles of learning or memory genes between AD and SZ. We downloaded 10 AD and 10 SZ datasets from GEO-NCBI for integrated analysis. These datasets were processed using RMA algorithm and a global renormalization for all studies. Then Empirical Bayes algorithm was used to find the differentially expressed genes between patients and controls. The results showed that most of the differentially expressed genes were related to AD whereas the gene expression profile was little affected in the SZ. Furthermore, in the aspects of the number of differentially expressed genes, the fold change and the brain region, there was a great difference in the expression of learning or memory related genes between AD and SZ. In AD, the CALB1, GABRA5, and TAC1 were significantly downregulated in whole brain, frontal lobe, temporal lobe, and hippocampus. However, in SZ, only two genes CRHBP and CX3CR1 were downregulated in hippocampus, and other brain regions were not affected. The effect of these genes on learning or memory impairment has been widely studied. It was suggested that these genes may play a crucial role in AD or SZ pathogenesis. The different gene expression patterns between AD and SZ on learning and memory functions in different brain regions revealed in our study may help to understand the different mechanism between two diseases.
Keywords: Adult; Aged; Aged, 80 and over; Algorithms; Alzheimer Disease; Bayes Theorem; Brain; Datasets as Topic; Gene Expression Profiling; Humans; Learning; Memory; Microarray Analysis; Middle Aged; Schizophrenia; Schizophrenic Psychology; Young Adult

Interaction Between Midlife Blood Glucose and APOE Genotype Predicts Later Alzheimer's Disease Pathology. - Bangen, Katherine J; Himali, Jayandra J; Beiser, Alexa S; Nation, Daniel A; Libon, David J; Fox, Caroline S; Seshadri, Sudha; Wolf, Philip A; McKee, Ann C; Au, Rhoda; Delano-Wood, Lisa (J Alzheimers Dis, 2016)
Elevated blood glucose and the apolipoprotein (APOE) ɛ4 allele have both been associated with increased dementia risk; however, the neuropathological mechanisms underlying these associations remain unclear. We examined the impact of APOE genotype and midlife blood glucose on post-mortem vascular and Alzheimer's disease (AD) neuropathology. Ninety-four participants from the Framingham Heart Study without diagnosed diabetes underwent health examination at midlife and brain autopsy at death. Histopathological measures of vascular and AD neuropathology were obtained and analyzed. Results demonstrated that, among APOE ɛ4 carriers, elevated blood glucose was associated with more severe AD pathology. There was no such relationship with vascular pathology. In a relatively healthy sample with low vascular risk burden, midlife elevated blood glucose was associated with greater AD pathology among APOE ɛ4 carriers. A better understanding of interactive effects of APOE genotype and vascular risk on neuropathology has implications for identification of individuals at risk for decline and long-term preventive treatment.

The Language Profile of Behavioral Variant Frontotemporal Dementia. - Hardy, Chris J D; Buckley, Aisling H; Downey, Laura E; Lehmann, Manja; Zimmerer, Vitor C; Varley, Rosemary A; Crutch, Sebastian J; Rohrer, Jonathan D; Warrington, Elizabeth K; Warren, Jason D (J Alzheimers Dis, 2016)
BACKGROUND: The language profile of behavioral variant frontotemporal dementia (bvFTD) remains to be fully defined. OBJECTIVE: We aimed to quantify the extent of language deficits in this patient group. METHODS: We assessed a cohort of patients with bvFTD (n = 24) in relation to patients with semantic variant primary progressive aphasia (svPPA; n = 14), nonfluent variant primary progressive aphasia (nfvPPA; n = 18), and healthy age-matched individuals (n = 24) cross-sectionally and longitudinally using a comprehensive battery of language and general neuropsychological tests. Neuroanatomical associations of language performance were assessed using voxel-based morphometry of patients' brain magnetic resonance images. RESULTS: Relative to healthy controls, and after accounting for nonverbal executive performance, patients with bvFTD showed deficits of noun and verb naming and single word comprehension, diminished spontaneous propositional speech, and deterioration in naming performance over time. Within the bvFTD group, patients with MAPT mutations had more severe impairments of noun naming and single word comprehension than patients with C9orf72 mutations. Overall the bvFTD group had less severe language deficits than patients with PPA, but showed a language profile that was qualitatively similar to svPPA. Neuroanatomical correlates of naming and word comprehension performance in bvFTD were identified predominantly in inferior frontal and antero-inferior temporal cortices within the dominant hemispheric language network. CONCLUSIONS: bvFTD is associated with a language profile including verbal semantic impairment that warrants further evaluation as a novel biomarker.
Keywords: Aged; Aphasia, Primary Progressive; Atrophy; Brain; Cognition; Comprehension; Female; Frontotemporal Dementia; Humans; Language; Magnetic Resonance Imaging; Male; Middle Aged; Neuroimaging; Neuropsychological Tests; Primary Progressive Nonfluent Aphasia

A Late Life Risk Index for Severe Cognitive Impairment in Mexico. - Downer, Brian; Veeranki, Sreenivas P; Wong, Rebeca (J Alzheimers Dis, 2016)
BACKGROUND: Several dementia risk indices have been developed for older adults in high-income countries. However, no index has been developed for populations in low- or middle-income countries. OBJECTIVE: To create a risk index for predicting severe cognitive impairment among adults aged ≥60 in Mexico and to compare the accuracy of this index to the Dementia Screening Indicator (DSI). METHODS: This study included 3,002 participants from the Mexican Health and Aging Study (MHAS) interviewed in 2001 and 2012. The MHAS risk index included sociodemographic, health, and functional characteristics collected in 2001. A point value based on the beta coefficients from a multivariable logistic regression model was assigned to each risk factor and the total score was calculated. RESULTS: The MHAS risk index (AUC = 0.74 95% CI = 0.70-0.77) and DSI (AUC = 0.72 95% CI = 0.69-0.77) had similar accuracy for discriminating between participants who developed severe cognitive impairment from those who did not. A score of ≥16 on the MHAS risk index had a sensitivity of 0.69 (95% CI = 0.64-0.70) and specificity of 0.67 (95% CI = 0.66-0.69). A score of ≥23 on the DSI had a sensitivity of 0.56 (95% CI = 0.50-0.63) and specificity of 0.78 (95% CI = 0.76-0.79). DISCUSSION: The MHAS risk index and DSI have moderate accuracy for predicting severe cognitive impairment among older adults in Mexico. This provides evidence that existing dementia risk indices may be applicable in low- and middle-income countries such as Mexico. Future research should seek to identify additional risk factors that can improve the accuracy of the MHAS risk index.
Keywords: Age Factors; Aged; Cognitive Dysfunction; Female; Humans; Life Style; Logistic Models; Longitudinal Studies; Male; Mexico; Middle Aged; Multivariate Analysis; Risk Factors; Social Behavior; Socioeconomic Factors

Late-Life Depressive Symptoms and Lifetime History of Major Depression: Cognitive Deficits are Largely Due to Incipient Dementia rather than Depression. - Heser, Kathrin; Bleckwenn, Markus; Wiese, Birgitt; Mamone, Silke; Riedel-Heller, Steffi G; Stein, Janine; Lühmann, Dagmar; Posselt, Tina; Fuchs, Angela; Pentzek, Michael; Weyerer, Siegfried; Werle, Jochen; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Late-life depression is frequently accompanied by cognitive impairments. OBJECTIVE: Whether these impairments indicate a prodromal state of dementia, or are a symptomatic expression of depression per se is not well-studied. METHODS: In a cohort of very old initially non-demented primary care patients (n = 2,709, mean age = 81.1 y), cognitive performance was compared between groups of participants with or without elevated depressive symptoms and with or without subsequent dementia using ANCOVA (adjusted for age, sex, and education). Logistic regression analyses were computed to predict subsequent dementia over up to six years of follow-up. The same analytical approach was performed for lifetime major depression. RESULTS: Participants with elevated depressive symptoms without subsequent dementia showed only small to medium cognitive deficits. In contrast, participants with depressive symptoms with subsequent dementia showed medium to very large cognitive deficits. In adjusted logistic regression models, learning and memory deficits predicted the risk for subsequent dementia in participants with depressive symptoms. Participants with a lifetime history of major depression without subsequent dementia showed no cognitive deficits. However, in adjusted logistic regression models, learning and orientation deficits predicted the risk for subsequent dementia also in participants with lifetime major depression. CONCLUSION: Marked cognitive impairments in old age depression should not be dismissed as "depressive pseudodementia", but require clinical attention as a possible sign of incipient dementia. Non-depressed elderly with a lifetime history of major depression, who remained free of dementia during follow-up, had largely normal cognitive performance.

The Latent Dementia Phenotype δ is Associated with Cerebrospinal Fluid Biomarkers of Alzheimer's Disease and Predicts Conversion to Dementia in Subjects with Mild Cognitive Impairment. - Koppara, Alexander; Wolfsgruber, Steffen; Kleineidam, Luca; Schmidtke, Klaus; Frölich, Lutz; Kurz, Alexander; Schulz, Stefanie; Hampel, Harald; Heuser, Isabella; Peters, Oliver; Reischies, Friedel M; Jahn, Holger; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The recently proposed latent variable δ is a new tool for dementia case finding. It is built in a structural equation modeling framework of cognitive and functional data and constitutes a novel endophenotype for Alzheimer's disease (AD) research and clinical trials. OBJECTIVE: To investigate the association of δ with AD biomarkers and to compare the prediction of δ with established scales for conversion to dementia in patients with mild cognitive impairment (MCI). METHODS: Using data from a multicenter memory clinic study, we examined the external associations of the latent variable δ and compared δ with well-established cognitive and functional scales and cognitive-functional composite scores. For that purpose, logistic regressions with cerebrospinal fluid (CSF) biomarkers and conversion to dementia as dependent variables were performed with the investigated scores. The models were tested for significant differences. RESULTS: In patients with MCI, δ based on a broad range of cognitive scales (including the ADAS-cog, the MMSE, and the CERAD neuropsychological battery) predicted an abnormal CSF Aβ42/tau ratio indicative of AD (n = 340, AUC = 0.78, p <  0.001), and predicted incident dementia within 1-3 years of follow-up (n = 525, AUC = 0.84, p <  0.001). These associations were generally stronger than for any other scale or cognitive-functional composite examined. Homologs of δ based on reduced test batteries yielded somewhat lower effects. CONCLUSION: These findings support the interpretation of δ as a construct capturing the disease-related "essence" of cognitive and functional impairments in patients with MCI and dementia, and suggest that δ might become an analytical tool for dementia research.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Dementia; Disease Progression; Female; Humans; Logistic Models; Longitudinal Studies; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptide Fragments; Phenotype; Predictive Value of Tests; Retrospective Studies; tau Proteins

Lifelong Reading Disorder and Mild Cognitive Impairment: Implications for Diagnosis. - Lebowitz, Brian K; Weinstein, Cheryl; Beiser, Alexa; Seshadri, Sudha; Wolf, Philip A; Auerbach, Sandford; Au, Rhoda (J Alzheimers Dis, 2016)
Although neuropsychological tests are commonly used in the evaluation of possible mild cognitive impairment (MCI), poor test scores may be indicative of factors other than neurological compromise. The current study assessed the role of lifelong reading disorder on MCI classification. Community dwelling older adults with a suspected developmental reading disorder were identified by inference based on reading test performance. Individuals with a suspected reading disorder were significantly more likely to perform at a level consistent with MCI on several commonly used neuropsychological tests. The findings suggest a relationship between a history of reading disorder and MCI classification.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Dyslexia; Female; Humans; Independent Living; Longitudinal Studies; Male; Neuropsychological Tests; Psychometrics; Retrospective Studies

Life's Simple 7's Cardiovascular Health Metrics are Associated with Hispanic/Latino Neurocognitive Function: HCHS/SOL Results. - González, Hector M; Tarraf, Wassim; Gouskova, Natalia; Rodríguez, Carlos J; Rundek, Tatjana; Grober, Ellen; Pirzada, Amber; González, Patricia; Lutsey, Pamela L; Camacho, Alvaro; Daviglus, Martha L; Wright, Clinton; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Hispanics/Latinos are purportedly at increased risk for neurocognitive decline and dementias. Without dementia cures, low-cost, well-tolerated public health means for mitigating neurocognitive decline are needed. OBJECTIVE: We examined associations between neurocognition and cardiovascular health (CVH) metrics (Life's Simple 7; LS7) among diverse Hispanics/Latinos. We hypothesized that higher LS7 would be associated with healthier brain function (neurocognitive performance). METHODS: We used baseline (2008-2011) Hispanic Community Health Study/Study of Latinos (HCHS/SOL; N = 9,623; ages 45-74 years) to examine neurocognition in relation to CVH LS7 scores. RESULTS: In age and sex adjusted models, a one unit LS7 score increase (range = 0-14) was associated with higher neurocognitive function on the B-SEVLT sum (0.23 [p < 0.01]; range = 3-42), B-SEVLT recall (0.12 [p < 0.01]; range = 0-15), Word Fluency (phonemic; 0.46 (p < 0.01); range = 0-49), and Digit Symbol Substitution (0.49 (p < 0.01); range = 0-83) tests, respectively. Stated differently, a change from the minimum LS7 (0) to maximum LS7 (14) score corresponded to higher scores on verbal learning (4.62) and memory (2.24), verbal fluency (7.0), and psychomotor processing speed (12). In fully adjusted models the associations were attenuated, but remained statistically significant. Incremental adjustments indicated that Latino background and, to a lesser extent, education were primary contributors to the evinced attenuations. CONCLUSIONS: We found that higher neurocognitive function was associated with better LS7 CVH metrics among middle-aged and older Hispanics/Latinos. Associations between neurocognitive function and LS7 were strongest among two at-risk groups for neurocognitive decline and dementia, women and Hispanics/Latinos with lower education. Public health efforts to reduce cardiovascular disease morbidity and mortality may have additional neurocognitive benefits among at-risk Hispanics/Latinos.

Living Alone with Dementia: Prevalence, Correlates and the Utilization of Health and Nursing Care Services. - Eichler, Tilly; Hoffmann, Wolfgang; Hertel, Johannes; Richter, Steffen; Wucherer, Diana; Michalowsky, Bernhard; Dreier, Adina; Thyrian, Jochen René (J Alzheimers Dis, 2016)
BACKGROUND: Little is known about the proportion and the characteristics of community-dwelling people with dementia (PWD) living alone in Germany. OBJECTIVES: To analyze the prevalence of PWD living alone (with and without the support of an informal caregiver) and socio-demographical and clinical characteristics as well as health and nursing care utilization associated with living alone. METHODS: DelpHi-MV (Dementia: Life- and person-centered help in Mecklenburg-Western Pomerania) is a general practitioner-based, randomized controlled intervention trial. The present analyses are based on baseline data of 511 patients (≥70 years, community-dwelling) who had screened positive for dementia (DemTect <9). RESULTS: N = 251 (51%) of the patients lived alone. PWD living alone were statistically significantly more often female, older, and more often widowed than those not living alone. About 9% of the patients (n = 24) were not supported by any informal caregiver. Regarding the clinical variables (cognitive and functional impairment, depression, falls, number of drug-related problems, malnutrition, quality of life), there were no statistically significant group differences. Patients living alone utilized professional services such as home care, help with medication, home-delivered meals, or housekeeping assistance significantly more often. Multivariate analyses confirmed these findings. CONCLUSION: Our results reveal the high proportion of PWD living alone in Germany. PWD living alone did not seem to be at an increased health risk. Our findings indicate that living alone with dementia is possible. In order to ensure the sufficient provision of health and nursing care services for PWD living alone, providers should consider the present results for future planning.

Longitudinal Protein Changes in Blood Plasma Associated with the Rate of Cognitive Decline in Alzheimer's Disease. - Sattlecker, Martina; Khondoker, Mizanur; Proitsi, Petroula; Williams, Stephen; Soininen, Hilkka; Kłoszewska, Iwona; Mecocci, Patrizia; Tsolaki, Magda; Vellas, Bruno; Lovestone, Simon; Dobson, Richard Jb (J Alzheimers Dis, 2016)
Biomarkers of Alzheimer's disease (AD) progression are needed to support the development of urgently needed disease modifying drugs. We employed a SOMAscan assay for quantifying 1,001 proteins in blood samples from 90 AD subjects, 37 stable mild cognitive impaired (MCI) subjects, 39 MCI subjects converting to AD within a year and 69 controls at baseline and one year follow up. We used linear mixed effects models to identify proteins changing significantly over one year with the rate of cognitive decline, which was quantified as the reduction in Mini Mental State Examination (MMSE) scores. Additionally, we investigated proteins changing differently across disease groups and during the conversion from MCI to AD. We found that levels of proteins belonging to the complement cascade increase significantly in fast declining AD patients. Longitudinal changes in the complement cascade might be a surrogate biomarker for disease progression. We also found that members of the cytokine-cytokine receptor interaction pathway change during AD when compared to healthy aging subjects.
Keywords: Aged; Alzheimer Disease; Biomarkers; Cognition; Cognitive Dysfunction; Disease Progression; Female; Follow-Up Studies; Humans; Linear Models; Longitudinal Studies; Male; Mental Status Schedule; Neuropsychological Tests

Lower Prevalence of Alzheimer's Disease among Tibetans: Association with Religious and Genetic Factors. - Huang, Fukai; Shang, Ying; Luo, Yuandai; Wu, Peng; Huang, Xue; Tan, Xiaohui; Lu, Xingyi; Zhen, Lifang; Hu, Xianda (J Alzheimers Dis, 2016)
BACKGROUND: The prevalence of dementia differs among racial groups, the highest prevalence being in Latin America (8.5%) compared to sub-Saharan African regions (2-4%). The most common type of dementia is Alzheimer's disease (AD). OBJECTIVE: To estimate the prevalence of AD in the Qinghai-Tibet plateau and to investigate the related factors. METHODS: This was a cross-sectional, multistage cluster sampling design survey. Data was collected from May 2014 to September 2014 from 4,060 Tibetan aged >60 years. Participants underwent clinical examinations and neuropsychological evaluations. MALDI-TOF was used to test the genotypes of CLU, TFAM, TP53INP1, IGHV1-67, CR1, ApoE, and BIN1. Logistic regression models were used to ascertain the associations with AD. RESULTS: The prevalence of AD among Tibetan individuals aged >60 years was 1.33% (95% CI: 0.98-1.69). The CLU haplotypes AA+GA (odds ratio (OR) = 4.483; 95% CI: 1.069-18.792) of rs2279590 was correlated with AD. The CLU haplotypes GG+GC (OR = 0.184; 95% CI: 0.038-0.888) of rs9331888 and kowtow (OR = 0.203; 95% CI 0.046-0.896) were negatively correlated with AD. CONCLUSION: A low prevalence of AD was found in Tibetans from the Qinghai-Tibet plateau. Multivariate analysis might suggest that regular "mind-body" religious meditative activities may be negatively associated with AD in this population, as well as the CLU genotype at rs9331888.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Clusterin; Cognition Disorders; Cross-Sectional Studies; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Polymorphism, Single Nucleotide; Psychiatric Status Rating Scales; Religion; Risk Factors; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Tibet

LRP/LR Antibody Mediated Rescuing of Amyloid-β-Induced Cytotoxicity is Dependent on PrPc in Alzheimer's Disease. - Pinnock, Emma C; Jovanovic, Katarina; Pinto, Maxine G; Ferreira, Eloise; Dias, Bianca Da Costa; Penny, Clement; Knackmuss, Stefan; Reusch, Uwe; Little, Melvyn; Schatzl, Hermann M; Weiss, Stefan F T (J Alzheimers Dis, 2016)
The neuronal perturbations in Alzheimer's disease are attributed to the formation of extracellular amyloid-β (Aβ) neuritic plaques, composed predominantly of the neurotoxic Aβ42 isoform. Although the plaques have demonstrated a role in synaptic dysfunction, neuronal cytotoxicity has been attributed to soluble Aβ42 oligomers. The 37kDa/67kDa laminin receptor has been implicated in Aβ42 shedding and Aβ42-induced neuronal cytotoxicity, as well as internalization of this neurotoxic peptide. As the cellular prion protein binds to both LRP/LR and Aβ42, the mechanism underlying this cytotoxicity may be indirectly due to the PrPc-Aβ42 interaction with LRP/LR. The effects of this interaction were investigated by 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide assays. PrPc overexpression significantly enhanced Aβ42 cytotoxicity in vitro, while PrP-/-  cells were more resistant to the cytotoxic effects of Aβ42 and exhibited significantly less cell death than PrPc expressing N2a cells. Although anti-LRP/LR specific antibody IgG1-iS18 significantly enhanced cell viability in both pSFV1-huPrP1-253 transfected and non-transfected cells treated with exogenous Aβ42, it failed to have any cell rescuing effect in PrP-/-  HpL3-4 cells. These results suggest that LRP/LR plays a significant role in Aβ42-PrPc mediated cytotoxicity and that anti-LRP/LR specific antibodies may serve as potential therapeutic tools for Alzheimer's disease.
Keywords: Amyloid beta-Peptides; Animals; Antibodies; Cell Line, Transformed; Cell Survival; Flow Cytometry; Gene Expression Regulation; Humans; Mice; Peptide Fragments; Prions; Receptors, Laminin; Transfection

Matrix Metalloproteinase in Blood-Brain Barrier Breakdown in Dementia. - Weekman, Erica M; Wilcock, Donna M (J Alzheimers Dis, 2016)
The neurovascular unit, which consists of astrocytic end-feet, neurons, pericytes, and endothelial cells, plays a key role in maintaining brain homeostasis by forming the blood-brain barrier and carefully controlling local cerebral blood flow. When the blood-brain barrier is disrupted, blood components can leak into the brain, damage the surrounding tissue and lead to cognitive impairment. This disruption in the blood-brain barrier and subsequent impairment in cognition are common after stroke and during cerebral amyloid angiopathy and Alzheimer's disease. Matrix metalloproteinases are proteases that degrade the extracellular matrix as well as tight junctions between endothelial cells and have been implicated in blood-brain barrier breakdown in neurodegenerative diseases. This review will focus on the roles of MMP2 and MMP9 in dementia, primarily post-stroke events that lead to dementia, cerebral amyloid angiopathy, and Alzheimer's disease.
Keywords: Animals; Blood-Brain Barrier; Dementia; Humans; Matrix Metalloproteinase 2; Matrix Metalloproteinase 9

A Meta-Analysis of Alzheimer's Disease Incidence and Prevalence Comparing African-Americans and Caucasians. - Steenland, Kyle; Goldstein, Felicia C; Levey, Allan; Wharton, Whitney (J Alzheimers Dis, 2016)
BACKGROUND: Several studies have shown higher Alzheimer's disease (AD) incidence rates are in African-Americans (AAs) than Caucasians (CCs). If this finding is consistent across studies, it raises important etiologic questions regarding factors responsible for this discrepancy. It also affects the likely public health burden of AD in the US in the future, as the non-Caucasian population becomes the majority. OBJECTIVE: Estimate the AA/CC rate ratio for AD incidence across all available studies. METHODS: We conducted a meta-analysis of population-based studies for the rate ratio (RR) of AD incidence for AAs versus CCs, after identifying six relevant studies from the literature. We calculated an AA/CC rate ratio across all studies using inverse-variance weighting, and assessed inter-study heterogeneity. Using these incidence data, as well as data on survival after diagnosis, and on all-cause mortality, we also estimated the US prevalence of AD among AAs and CCs. RESULTS: There were six population-based studies with data comparing AD incidence between AAs and CCs, with an estimated 370 AA and 640 CC incident cases. The meta-analysis RR showed that the AD rate for AAs was 64% higher than for CCs (RR = 1.64 (95% CI 1.35-2.00)) 1.35-2.00)), with no evidence of heterogeneity. We estimated the current US AD prevalence for ages 65-90 to be 5.5% for CCs, and 8.6% for AAs (prevalence ratio 1.56). CONCLUSION: AAs have an increased risk of incident and prevalent AD compared to CCs for reasons which are unknown, but are hypothesized to reflect biological, psychological, and socioeconomic factors.
Keywords: African Americans; Alzheimer Disease; Community Health Planning; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Incidence; Male; Prevalence

Meta-Analysis of Transcriptome Data Related to Hippocampus Biopsies and iPSC-Derived Neuronal Cells from Alzheimer's Disease Patients Reveals an Association with FOXA1 and FOXA2 Gene Regulatory Networks. - Wruck, Wasco; Schröter, Friederike; Adjaye, James (J Alzheimers Dis, 2016)
Although the incidence of Alzheimer's disease (AD) is continuously increasing in the aging population worldwide, effective therapies are not available. The interplay between causative genetic and environmental factors is partially understood. Meta-analyses have been performed on aspects such as polymorphisms, cytokines, and cognitive training. Here, we propose a meta-analysis approach based on hierarchical clustering analysis of a reliable training set of hippocampus biopsies, which is condensed to a gene expression signature. This gene expression signature was applied to various test sets of brain biopsies and iPSC-derived neuronal cell models to demonstrate its ability to distinguish AD samples from control. Thus, our identified AD-gene signature may form the basis for determination of biomarkers that are urgently needed to overcome current diagnostic shortfalls. Intriguingly, the well-described AD-related genes APP and APOE are not within the signature because their gene expression profiles show a lower correlation to the disease phenotype than genes from the signature. This is in line with the differing characteristics of the disease as early-/late-onset or with/without genetic predisposition. To investigate the gene signature's systemic role(s), signaling pathways, gene ontologies, and transcription factors were analyzed which revealed over-representation of response to stress, regulation of cellular metabolic processes, and reactive oxygen species. Additionally, our results clearly point to an important role of FOXA1 and FOXA2 gene regulatory networks in the etiology of AD. This finding is in corroboration with the recently reported major role of the dopaminergic system in the development of AD and its regulation by FOXA1 and FOXA2.
Keywords: Alzheimer Disease; Biopsy; Cells, Cultured; Gene Regulatory Networks; Hepatocyte Nuclear Factor 3-alpha; Hepatocyte Nuclear Factor 3-beta; Hippocampus; Humans; Induced Pluripotent Stem Cells; Transcriptome

Midlife Physical Activity and Cognition Later in Life: A Prospective Twin Study. - Iso-Markku, Paula; Waller, Katja; Vuoksimaa, Eero; Heikkilä, Kauko; Rinne, Juha; Kaprio, Jaakko; Kujala, Urho M (J Alzheimers Dis, 2016)
BACKGROUND: Physical activity has been associated with a reduced risk of cognitive decline but the nature of this association remains obscure. OBJECTIVE: To study associations between midlife physical activity and cognition in old age for a prospective cohort of Finnish twins. METHODS: Physical activity in the Finnish Twin Cohort was assessed using questionnaire responses collected in 1975 and 1981. After a mean follow-up of 25.1 years, the subjects' (n = 3050; mean age 74.2; range 66-97) cognition was evaluated with a validated telephone interview. Both participation in vigorous physical activity, and the volume of physical activity, divided into quintiles, were used as predictors of cognitive impairment. Metrics collected by TELE were used to categorize participants as: cognitively impaired, suffering mild cognitive impairment, or cognitively healthy. RESULTS: Participation in vigorous physical activity compared to non-participation for both 1975 and 1981 was associated with a lower risk of cognitive impairment in individual-based analyses (fully adjusted OR 0.50, 95% CI 0.35-0.73). Pairwise analyses yielded similar but statistically non-significant associations. In terms of the volume of physical activity, the most active quintile of individuals (OR 0.69, 95% CI 0.46-1.04) had a reduced risk of cognitive decline compared with the most sedentary quintile in the fully adjusted model although no clear dose-response was found. CONCLUSION: Vigorous midlife physical activity was associated with less cognitive impairment but without a clear dose-response association between the volume of physical activity and cognition.

Moderate-to-High Intensity Physical Exercise in Patients with Alzheimer's Disease: A Randomized Controlled Trial. - Hoffmann, Kristine; Sobol, Nanna A; Frederiksen, Kristian S; Beyer, Nina; Vogel, Asmus; Vestergaard, Karsten; Brændgaard, Hans; Gottrup, Hanne; Lolk, Annette; Wermuth, Lene; Jacobsen, Søren; Laugesen, Lars P; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Studies of physical exercise in patients with Alzheimer's disease (AD) are few and results have been inconsistent. OBJECTIVE: To assess the effects of a moderate-to-high intensity aerobic exercise program in patients with mild AD. METHODS: In a randomized controlled trial, we recruited 200 patients with mild AD to a supervised exercise group (60-min sessions three times a week for 16 weeks) or to a control group. Primary outcome was changed from baseline in cognitive performance estimated by Symbol Digit Modalities Test (SDMT) in the intention-to-treat (ITT) group. Secondary outcomes included changes in quality of life, ability to perform activities of daily living, and in neuropsychiatric and depressive symptoms. RESULTS: The ITT analysis showed no significant differences between intervention and control groups in change from baseline of SDMT, other cognitive tests, quality of life, or activities of daily living. The change from baseline in Neuropsychiatric Inventory differed significantly in favor of the intervention group (mean: -3.5, 95% confidence interval (CI) -5.8 to -1.3, p = 0.002). In subjects who adhered to the protocol, we found a significant effect on change from baseline in SDMT as compared with the control group (mean: 4.2, 95% CI 0.5 to 7.9, p = 0.028), suggesting a dose-response relationship between exercise and cognition. CONCLUSIONS: This is the first randomized controlled trial with supervised moderate-to-high intensity exercise in patients with mild AD. Exercise reduced neuropsychiatric symptoms in patients with mild AD, with possible additional benefits of preserved cognition in a subgroup of patients exercising with high attendance and intensity.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Depression; Exercise; Exercise Therapy; Female; Humans; Male; Middle Aged; Quality of Life; Treatment Outcome

Modulation of miR-19 in Aluminum-Induced Neural Cell Apoptosis. - Zhu, Mingming; Huang, Cong; Ma, Xiao; Wu, Rui; Zhu, Weiwei; Li, Xiaoting; Liang, Zhaofeng; Deng, Feifei; Zhu, Jianyun; Xie, Wei; Yang, Xue; Jiang, Ye; et al. (J Alzheimers Dis, 2016)
Neuronal cell death is an important feature of neurodegeneration. Aluminum is associated with neurodegenerative disorders, particularly Alzheimer's disease. However, the underlying mechanisms by which aluminum induces neuronal apoptosis remain to be elucidated. miR-19 is a key miRNA implicated in regulating cell survival process, while the role of miR-19 in Alzheimer's disease has not been investigated. In the present study, we showed that Aluminum maltolate (Al-malt), a lipophilic Al complex which is a common component of human diet with the ability to facilitate the entry of Al into the brain, induced apoptosis in human neuroblastoma SH-SY5Y cells, along with downregulation of miR-19a/miR-19b, upregulation of miR-19-targeted PTEN, and alterations of its downstream apoptosis related proteins including AKT, p53, Bax, and Bcl-2. miR-19 overexpression attenuated Al-malt-induced apoptosis as well as changes in the expression of apoptosis related proteins in SH-SY5Y cells. We further revealed that exposure of rats to Al-malt for 12 weeks at doses relevant to human exposure significantly elevated Al concentrations in serum and brain tissues. Al-malt dose-dependently induced apoptosis in rat brain, as evidenced by increased caspase activation and increased TUNEL staining. Consistent with in vitro results, Al-malt reduced miR-19 expression and altered the expression of apoptotic related proteins in rat brain. Taken together, our data suggest for the first time that miR-19 modulation is critically involved in Al-induced neural cell apoptosis. Findings from this study could provide new insight into the molecular mechanisms of Al-associated neurodegenerative pathogenesis.
Keywords: Aluminum; Animals; Apoptosis; Brain; Cell Line, Tumor; Dose-Response Relationship, Drug; Humans; Male; MicroRNAs; Neurons; Proto-Oncogene Proteins c-akt; PTEN Phosphohydrolase; Rats, Sprague-Dawley; Tumor Suppressor Protein p53

Molecular markers of amnestic mild cognitive impairment among Mexican Americans. - Edwards, Melissa; Hall, James; Williams, Benjamin; Johnson, Leigh; O'Bryant, Sid (J Alzheimers Dis, 2016)
BACKGROUND: Mexican Americans face a significant health disparity when it comes to Alzheimer's disease (AD) as they present with higher rates of the disease and develop AD at an earlier age compared to other ethnic groups. Recent work identified a proteomic profile of AD among this population; however, no work to date has sought to examine the biological profile of pre-AD among Mexican Americans. OBJECTIVE: This study aims to identify an amnestic mild cognitive impairment (aMCI) proteomic profile among Mexican Americans. METHODS: Data were analyzed from 284 Mexican American participants (aMCI, n = 73; normal controls, n = 211) from the Health & Aging Brain among Latino Elders study. Fasting serum samples were analyzed using a multi-plex biomarker assay platform. A biomarker profile was generated using random forest analyses. RESULTS: Among aMCI cases, the biomarker profile was found to be largely inflammatory with the top three markers shown to include TNFα, IL10, and TARC. The overall diagnostic accuracy of the biomarkers in detecting aMCI was 96% (sensitivity = 0.82; specificity = 0.97). Inclusion of clinical variables with the selected biomarkers did not impact the overall detection accuracy (area under the curve = 0.96) but led to a slight improvement in specificity (specificity = 0.99) and decrease in sensitivity (sensitivity = 0.74). CONCLUSION: The biomarker profile of aMCI was shown to be different from our previously generated AD profile among Mexican Americans, which was largely metabolic in nature. The findings implicate a possible interplay between inflammatory and metabolic processes and additional work is needed to further examine this.
Keywords: Aged; Alzheimer Disease; Area Under Curve; Biomarkers; Cognitive Dysfunction; Female; Humans; Male; Mexican Americans; Middle Aged; Neuropsychological Tests; Proteome; Sensitivity and Specificity; United States

Morroniside-Induced PP2A Activation Antagonizes Tau Hyperphosphorylation in a Cellular Model of Neurodegeneration. - Yang, Cui-cui; Kuai, Xue-xian; Gao, Wen-bin; Yu, Jian-chun; Wang, Qi; Li, Lin; Zhang, Lan (J Alzheimers Dis, 2016)
BACKGROUND: An accumulation of hyperphosphorylated tau in the brain is a hallmark of Alzheimer's disease (AD). Deficits in protein phosphatase 2A (PP2A) are associated with tau hyperphosphorylation in AD. OBJECTIVE: To investigate the effects of morroniside (MOR), isolated from Cornus officinalis, on tau hyperphosphorylation and its underlying mechanisms related to PP2A. METHODS: SK-N-SH cells were pretreated with 50-200 μM MOR for 24 h followed by 20 nM okadaic acid (OA) for 6 h. PP2Ac siRNA was transfected into HEK293 cells to determine the direct interaction of MOR with PP2A. Western blotting was used to measure the expression of proteins and enzymes. PP2A activity was measured by molybdenum blue spectrophotometry. RESULTS: Pretreatment with MOR improved the cellular morphological damage and inhibited tau hyperphosphorylation in SK-N-SH cells induced by OA, a PP2A inhibitor. Moreover, MOR increased PP2A activity, concurrent with a decrease in the expression of demethylated PP2A at Leu309 and phosphorylated PP2A at Tyr307. MOR decreased protein phosphatase methylesterase 1 (PME-1) expression and the ratio of PME-1/leucine carboxyl methyltransferase 1 (LCMT-1). Furthermore, MOR treatment decreased the phosphorylation of Src at Tyr416, which regulates the phosphorylation of PP2A. MOR had no effect on PP2Ac expression and tau hyperphosphorylation in PP2Ac siRNA-transfected cells. CONCLUSION: MOR attenuated OA-induced tau hyperphosphorylation via PP2A activation, and its mechanism might be related to the regulation of PP2Ac post-translational modification and upstream enzymes such as Src and PME-1.
Keywords: Analysis of Variance; Cell Line; Enzyme Inhibitors; Gene Expression Regulation; Glycogen Synthase Kinase 3 beta; Glycosides; HEK293 Cells; Humans; Neuroblastoma; Okadaic Acid; Phosphorylation; Protein Phosphatase 2; RNA, Small Interfering; tau Proteins; Transfection; Tyrosine

Mortality in Mild Cognitive Impairment: A Longitudinal Study in Memory Clinics. - Connors, Michael H; Ames, David; Boundy, Karyn; Clarnette, Roger; Kurrle, Sue; Mander, Alastair; Ward, John; Woodward, Michael; Brodaty, Henry (J Alzheimers Dis, 2016)
BACKGROUND: Patients with mild cognitive impairment (MCI) are at greater risk of mortality than the general population. Comparatively little research has examined predictors of mortality in MCI and no research has examined whether time-varying variables, such as change in cognition and function, predict survival. OBJECTIVE: To identify predictors of mortality in patients with MCI. METHODS: 185 patients with MCI were recruited from nine memory clinics around Australia. Patients completed measures of cognition, function, and neuropsychiatric symptoms over three years. Mortality data were obtained from state registries eight years after baseline. RESULTS: 55 (30%) patients died within this period. Older age, lower cognitive and functional ability at baseline, and greater decline in functional ability over six months predicted mortality. CONCLUSION: Easily measurable clinical data predict mortality in patients with MCI. Longitudinal assessment over time can provide additional information about patients' risk.

Multimodal Classification of Mild Cognitive Impairment Based on Partial Least Squares. - Wang, Pingyue; Chen, Kewei; Yao, Li; Hu, Bin; Wu, Xia; Zhang, Jiacai; Ye, Qing; Guo, Xiaojuan (J Alzheimers Dis, 2016)
In recent years, increasing attention has been given to the identification of the conversion of mild cognitive impairment (MCI) to Alzheimer's disease (AD). Brain neuroimaging techniques have been widely used to support the classification or prediction of MCI. The present study combined magnetic resonance imaging (MRI), 18F-fluorodeoxyglucose PET (FDG-PET), and 18F-florbetapir PET (florbetapir-PET) to discriminate MCI converters (MCI-c, individuals with MCI who convert to AD) from MCI non-converters (MCI-nc, individuals with MCI who have not converted to AD in the follow-up period) based on the partial least squares (PLS) method. Two types of PLS models (informed PLS and agnostic PLS) were built based on 64 MCI-c and 65 MCI-nc from the Alzheimer's Disease Neuroimaging Initiative (ADNI) database. The results showed that the three-modality informed PLS model achieved better classification accuracy of 81.40%, sensitivity of 79.69%, and specificity of 83.08% compared with the single-modality model, and the three-modality agnostic PLS model also achieved better classification compared with the two-modality model. Moreover, combining the three modalities with clinical test score (ADAS-cog), the agnostic PLS model (independent data: florbetapir-PET; dependent data: FDG-PET and MRI) achieved optimal accuracy of 86.05%, sensitivity of 81.25%, and specificity of 90.77%. In addition, the comparison of PLS, support vector machine (SVM), and random forest (RF) showed greater diagnostic power of PLS. These results suggested that our multimodal PLS model has the potential to discriminate MCI-c from the MCI-nc and may therefore be helpful in the early diagnosis of AD.

Multi-Vitamin B Supplementation Reverses Hypoxia-Induced Tau Hyperphosphorylation and Improves Memory Function in Adult Mice. - Yu, Lixia; Chen, Yuan; Wang, Weiguang; Xiao, Zhonghai; Hong, Yan (J Alzheimers Dis, 2016)
Hypobaric hypoxia (HH) leads to reduced oxygen delivery to brain. It could trigger cognitive dysfunction and increase the risk of dementia including Alzheimer's disease (AD). The present study was undertaken in order to examine whether B vitamins (B6, B12, folate, and choline) could exert protective effects on hypoxia-induced memory deficit and AD related molecular events in mice. Adult male Kunming mice were assigned to five groups: normoxic control, hypoxic model (HH), hypoxia+vitamin B6/B12/folate (HB), hypoxia+choline (HC), hypoxia+vitamin B6/B12/folate+choline (HBC). Mice in the hypoxia, HB, HC, and HBC groups were exposed to hypobaric hypoxia for 8 h/day for 28 days in a decompression chamber mimicking 5500 meters of high altitude. Spatial and passive memories were assessed by radial arm and step-through passive test, respectively. Levels of tau and glycogen synthase kinase (GSK)-3β phosphorylation were detected by western blot. Homocysteine (Hcy) concentrations were determined using enzymatic cycling assay. Mice in the HH group exhibited significant spatial working and passive memory impairment, increased tau phosphorylation at Thr181, Ser262, Ser202/Thr205, and Ser396 in the cortex and hippocampus, and elevated Hcy levels compared with controls. Concomitantly, the levels of Ser9-phosphorylated GSK-3β were significantly decreased in brain after hypoxic treatment. Supplementations of vitamin B6/B12/folate+choline could significantly ameliorate the hypoxia-induced memory deficits, observably decreased Hcy concentrations in serum, and markedly attenuated tau hyperphosphorylation at multiple AD-related sites through upregulating inhibitory Ser9-phosphorylated GSK-3β. Our finding give further insight into combined neuroprotective effects of vitamin B6, B12, folate, and choline on brain against hypoxia.

Neuroimaging Correlates of Frontotemporal Dementia Associated with SQSTM1 Mutations. - Luis, Elkin; Ortiz, Alexandra; Eudave, Luis; Ortega-Cubero, Sara; Borroni, Barbara; van der Zee, Julie; Gazzina, Stefano; Caroppo, Paola; Rubino, Elisa; D'Agata, Federico; Le Ber, Isabelle; Santana, Isabel; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Frontotemporal lobar degeneration (FTLD) is a progressive dementia characterized by focal atrophy of frontal and/or temporal lobes caused by mutations in the gene coding for sequestosome 1 (SQSTM1), among other genes. Rare SQSTM1 gene mutations have been associated with Paget's disease of bone, amyotrophic lateral sclerosis, and, more recently, frontotemporal lobar degeneration (FTLD). OBJECTIVE: The aim of the study was to determine whether a characteristic pattern of grey and white matter loss is associated with SQSTM1 dysfunction. METHODS: We performed a voxel-based morphometry (VBM) study in FTD subjects carrying SQSTM1 pathogenic variants (FTD/SQSTM1 mutation carriers; n = 10), compared with FTD subjects not carrying SQSTM1 mutations (Sporadic FTD; n = 20) and healthy controls with no SQSTM1 mutations (HC/SQSTM1 noncarriers; n = 20). The groups were matched according to current age, disease duration, and gender. RESULTS: After comparing FTD/SQSTM1 carriers with Sporadic FTD, a predominantly right cortical atrophy pattern was localized in the inferior frontal, medial orbitofrontal, precentral gyri, and the anterior insula. White matter atrophy was found in both medial and inferior frontal gyri, pallidum, and putamen. FTD/SQSTM1 carriers compared with HC/SQSTM1 noncarriers showed atrophy at frontal, temporal, and parietal lobes of both hemispheres whereas the MRI pattern found in Sporadic FTD compared with controls was frontal and left temporal lobe atrophy, extending toward parietal and occipital lobes of both hemispheres. CONCLUSIONS: These results suggest that fronto-orbito-insular regions including corticospinal projections as described in ALS are probably more susceptible to the damaging effect of SQSTM1 mutations delineatinga specific gene-linked atrophy pattern.

Non-Catalytic Roles of Presenilin Throughout Evolution. - Otto, Grant P; Sharma, Devdutt; Williams, Robin S B (J Alzheimers Dis, 2016)
Research into Alzheimer's disease pathology and treatment has often focused on presenilin proteins. These proteins provide the key catalytic activity of the γ-secretase complex in the cleavage of amyloid-β precursor protein and resultant amyloid tangle deposition. Over the last 25 years, screening novel drugs to control this aberrant proteolytic activity has yet to identify effective treatments for the disease. In the search for other mechanisms of presenilin pathology, several studies have demonstrated that mammalian presenilin proteins also act in a non-proteolytic role as a scaffold to co-localize key signaling proteins. This role is likely to represent an ancestral presenilin function, as it has been described in genetically distant species including non-mammalian animals, plants, and a simple eukaryotic amoeba Dictyostelium that diverged from the human lineage over a billion years ago. Here, we review the non-catalytic scaffold role of presenilin, from mammalian models to other biomedical models, and include recent insights using Dictyostelium, to suggest that this role may provide an early evolutionary function of presenilin proteins.

Non-Fibrillar Oligomeric Amyloid-β within Synapses. - Pickett, Eleanor K; Koffie, Robert M; Wegmann, Susanne; Henstridge, Christopher M; Herrmann, Abigail G; Colom-Cadena, Marti; Lleo, Alberto; Kay, Kevin R; Vaught, Melissa; Soberman, Roy; Walsh, Dominic M; Hyman, Bradley T; et al. (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is characterized by memory loss, insidious cognitive decline, profound neurodegeneration, and the extracellular accumulation of amyloid-β (Aβ) peptide in senile plaques and intracellular accumulation of tau in neurofibrillary tangles. Loss and dysfunction of synapses are believed to underlie the devastating cognitive decline in AD. A large amount of evidence suggests that oligomeric forms of Aβ associated with senile plaques are toxic to synapses, but the precise sub-synaptic localization of Aβ and which forms are synaptotoxic remain unknown. Here, we characterize the sub-synaptic localization of Aβ oligomers using three high-resolution imaging techniques, stochastic optical reconstruction microscopy, immunogold electron microscopy, and Förster resonance energy transfer in a plaque-bearing mouse model of AD. With all three techniques, we observe oligomeric Aβ inside synaptic terminals. Further, we tested a panel of Aβ antibodies using the relatively high-throughput array tomography technique to determine which forms are present in synapses. Our results show that different oligomeric Aβ species are present in synapses and highlight the potential of array tomography for rapid testing of aggregation state specific Aβ antibodies in brain tissue.

N-Terminal Pro-B-Type Natriuretic Peptide and Risk of Future Cognitive Impairment in the REGARDS Cohort. - Cushman, Mary; Callas, Peter W; McClure, Leslie A; Unverzagt, Frederick W; Howard, Virginia J; Gillett, Sarah R; Thacker, Evan L; Wadley, Virginia G (J Alzheimers Dis, 2016)
BACKGROUND: Improved understanding of the etiology of cognitive impairment is needed to develop effective preventive interventions. Higher amino-terminal pro-B-type natriuretic peptide (NT-proBNP) is a biomarker of cardiac dysfunction associated with risk of cardiovascular diseases and stroke in apparently healthy people. OBJECTIVE: To study the association of NT-proBNP with risk of incident cognitive impairment. METHODS: The Reasons for Geographic and Racial Differences in Stroke is a national cohort study of 30,239 black and white Americans age 45 and older at baseline, enrolled in 2003-7. Among participants without prebaseline stroke or cognitive impairment, baseline NT-proBNP was measured in 470 cases of incident cognitive impairment and 557 controls. Cases were participants scoring below the 6th percentile of demographically-adjusted means on at least 2 of 3 serially administered tests (word list learning, word list recall and semantic fluency) over 3.5 years follow-up. RESULTS: Adjusting for age, gender, race, region of residence, education, and income, there was an increased odds ratio of incident cognitive impairment with increasing NT-proBNP; participants in the 4th versus 1st quartile (>127 versus ≤33 pg/ml) had a 1.69-fold increased odds (95% CI 1.11-2.58). Adjustment for cardiovascular risk factors and presence of an apolipoprotein E4 allele had no substantial impact on the odds ratio. Results did not differ by age, race, gender, or presence of an apolipoprotein E4 allele. CONCLUSION: Higher NT-pro-BNP was associated with incident cognitive impairment in this prospective study, independent of atherogenic and Alzheimer's disease risk factors. Future work should clarify pathophysiologic connections of NT-proBNP and cognitive dysfunction.

N-truncated Aβ2-X starting with position two in sporadic Alzheimer's disease cases and two Alzheimer mouse models. - Savastano, Adriana; Klafki, Hans; Haußmann, Ute; Oberstein, Timo Jan; Muller, Petr; Wirths, Oliver; Wiltfang, Jens; Bayer, Thomas A (J Alzheimers Dis, 2016)
According to the modified amyloid hypothesis, the key event in the pathogenesis of Alzheimer's disease (AD) is the deposition of neurotoxic amyloid β-peptides (Aβs) in plaques and cerebral blood vessels. Additionally to full-length peptides, a great diversity of N-truncated Aβ variants is derived from the larger amyloid-β protein precursor (AβPP). Vast evidence suggests that Aβx-42 isoforms play an important role in triggering neurodegeneration due to their high abundance, amyloidogenic propensity and toxicity. Although N-truncated Aβ peptides and Aβx-42 species appear to be the crucial players in AD etiology, the Aβ2-X isoforms did not receive much attention yet. The present study is the first to show immunohistochemical evidence of Aβ2-X in cases of AD and its distribution in AβPP/PS1KI and 5XFAD transgenic mouse models using a novel antibody pAB77 that has been developed using Aβ2-14 as antigen. Positive plaques and congophilic amyloid angiopathy (CAA) were observed in AD cases and in both mouse models. While in AD cases, abundant CAA and less pronounced plaque pathology was evident, the two mouse models showed predominantly extracellular Aβ deposits and minor CAA staining. Western blotting and a capillary isoelectric focusing immunoassay demonstrated the high specificity of the antibody pAb77 against Aβ-variants starting with the N-terminal Alanine-2.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Animals; Blotting, Western; Brain; Cerebral Amyloid Angiopathy; Disease Models, Animal; Female; Humans; Male; Mice; Mice, Transgenic; Plaque, Amyloid

Nutritional Status is Associated with Faster Cognitive Decline and Worse Functional Impairment in the Progression of Dementia: The Cache County Dementia Progression Study1. - Sanders, Chelsea; Behrens, Stephanie; Schwartz, Sarah; Wengreen, Heidi; Corcoran, Chris D; Lyketsos, Constantine G; Tschanz, JoAnn T (J Alzheimers Dis, 2016)
Nutritional status may be a modifiable factor in the progression of dementia. We examined the association of nutritional status and rate of cognitive and functional decline in a U.S. population-based sample. Study design was an observational longitudinal study with annual follow-ups up to 6 years of 292 persons with dementia (72% Alzheimer's disease, 56% female) in Cache County, UT using the Mini-Mental State Exam (MMSE), Clinical Dementia Rating Sum of Boxes (CDR-sb), and modified Mini Nutritional Assessment (mMNA). mMNA scores declined by approximately 0.50 points/year, suggesting increasing risk for malnutrition. Lower mMNA score predicted faster rate of decline on the MMSE at earlier follow-up times, but slower decline at later follow-up times, whereas higher mMNA scores had the opposite pattern (mMNA by time β= 0.22, p = 0.017; mMNA by time2 β= -0.04, p = 0.04). Lower mMNA score was associated with greater impairment on the CDR-sb over the course of dementia (β= 0.35, p <  0.001). Assessment of malnutrition may be useful in predicting rates of progression in dementia and may provide a target for clinical intervention.
Keywords: Age of Onset; Aged, 80 and over; Alzheimer Disease; Dementia, Vascular; Disease Progression; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Mental Status Schedule; Nutritional Status; Severity of Illness Index; Sex Factors; Utah

Partial Amelioration of Synaptic and Cognitive Deficits by Inhibiting Cofilin Dephosphorylation in an Animal Model of Alzheimer's Disease. - Deng, Yulei; Wei, Jing; Cheng, Jia; Zhong, Ping; Xiong, Zhe; Liu, Aiyi; Lin, Lin; Chen, Shengdi; Yan, Zhen (J Alzheimers Dis, 2016)
The loss of synaptic structure and function has been linked to the cognitive impairment of Alzheimer's disease (AD). Dysregulation of the actin cytoskeleton, which plays a key role in regulating the integrity of synapses and the transport of synaptic proteins, has been suggested to contribute to the pathology of AD. In this study, we found that glutamate receptor surface expression and synaptic function in frontal cortical neurons were significant diminished in a familial AD (FAD) model, which was correlated with the reduction of phosphorylated cofilin, a key protein regulating the dynamics of actin filaments. Injecting a cofilin dephosphorylation inhibitory peptide to FAD mice led to the partial rescue of the surface expression of AMPA and NMDA receptor subunits, as well as the partial restoration of AMPAR- and NMDAR-mediated synaptic currents. Moreover, the impaired working memory and novel object recognition memory in FAD mice were partially ameliorated by injections of the cofilin dephosphorylation inhibitory peptide. These results suggest that targeting the cofilin-actin signaling holds promise to mitigate the physiological and behavioral abnormality in AD.

Perfusion Neuroimaging Abnormalities Alone Distinguish National Football League Players from a Healthy Population. - Amen, Daniel G; Willeumier, Kristen; Omalu, Bennet; Newberg, Andrew; Raghavendra, Cauligi; Raji, Cyrus A (J Alzheimers Dis, 2016)
BACKGROUND: National Football League (NFL) players are exposed to multiple head collisions during their careers. Increasing awareness of the adverse long-term effects of repetitive head trauma has raised substantial concern among players, medical professionals, and the general public. OBJECTIVE: To determine whether low perfusion in specific brain regions on neuroimaging can accurately separate professional football players from healthy controls. METHOD: A cohort of retired and current NFL players (n = 161) were recruited in a longitudinal study starting in 2009 with ongoing interval follow up. A healthy control group (n = 124) was separately recruited for comparison. Assessments included medical examinations, neuropsychological tests, and perfusion neuroimaging with single photon emission computed tomography (SPECT). Perfusion estimates of each scan were quantified using a standard atlas. We hypothesized that hypoperfusion particularly in the orbital frontal, anterior cingulate, anterior temporal, hippocampal, amygdala, insular, caudate, superior/mid occipital, and cerebellar sub-regions alone would reliably separate controls from NFL players. Cerebral perfusion differences were calculated using a one-way ANOVA and diagnostic separation was determined with discriminant and automatic linear regression predictive models. RESULTS: NFL players showed lower cerebral perfusion on average (p < 0.01) in 36 brain regions. The discriminant analysis subsequently distinguished NFL players from controls with 90% sensitivity, 86% specificity, and 94% accuracy (95% CI 95-99). Automatic linear modeling achieved similar results. Inclusion of age and clinical co-morbidities did not improve diagnostic classification. CONCLUSION: Specific brain regions commonly damaged in traumatic brain injury show abnormally low perfusion on SPECT in professional NFL players. These same regions alone can distinguish this group from healthy subjects with high diagnostic accuracy. This study carries implications for the neurological safety of NFL players.

Peripheral Administration of GSK-3β Antisense Oligonucleotide Improves Learning and Memory in SAMP8 and Tg2576 Mouse Models of Alzheimer's Disease. - Farr, Susan A; Sandoval, Karin E; Niehoff, Michael L; Witt, Ken A; Kumar, Vijaya B; Morley, John E (J Alzheimers Dis, 2016)
Glycogen synthase kinase (GSK)-3β is a multifunctional protein that has been implicated in the pathological characteristics of Alzheimer's disease (AD), including the heightened levels of neurofibrillary tangles, amyloid-beta (Aβ), and neurodegeneration. We have previously shown that an antisense oligonucleotide directed at the Tyr 216 site on GSK-3β (GAO) when injected centrally can decrease GSK-3β levels, improve learning and memory, and decrease oxidative stress. In addition, we showed that GAO can cross the blood-brain barrier. Herein the impact of peripherally administered GAO in both the non-transgenic SAMP8 and transgenic Tg2576 (APPswe) models of AD were examined respective to learning and memory. Brain tissues were then evaluated for expression changes in the phosphorylated-Tyr 216 residue, which leads to GSK-3β activation, and the phosphorylated-Ser9 residue, which reduces GSK-3β activity. SAMP8 GAO-treated mice showed improved acquisition and retention using aversive T-maze, and improved declarative memory as measured by the novel object recognition (NOR) test. Expression of the phosphorylated-Tyr 216 was decreased and the phosphorylated-Ser9 was increased in GAO-treated SAMP8 mice. Tg2576 GAO-treated mice improved acquisition and retention in both the T-maze and NOR tests, with an increased phosphorylated-Ser9 GSK-3β expression. Results demonstrate that peripheral administration of GAO improves learning and memory, corresponding with alterations in GSK-3β phosphorylation state. This study supports peripherally administered GAO as a viable means to mediate GSK-3β activity within the brain and a possible treatment for AD.

Pharmacological Modulations of the Serotonergic System in a Cell-Model of Familial Alzheimer's Disease. - Tajeddinn, Walid; Persson, Torbjörn; Calvo-Garrido, Javier; Seed Ahmed, Mohammed; Maioli, Silvia; Vijayaraghavan, Swetha; Kazokoglu, Mehmet Selim; Parrado-Fernández, Cristina; Yoshitake, Takashi; Kehr, Jan; Francis, Paul; Winblad, Bengt; et al. (J Alzheimers Dis, 2016)
Serotonin (5-HT) plays a central role in the integrity of different brain functions. The 5-HT homeostasis is regulated by many factors, including serotonin transporter (SERT), monoamine oxidase enzyme (MAO), and several 5-HT receptors, including the 5-HT1B. There is little knowledge how the dynamics of this system is affected by the amyloid-β (Aβ) burden of Alzheimer's disease (AD) pathology. SH-SY5Y neuroblastoma cells transfected with the amyloid precursor protein (APP) gene containing the Swedish mutations causing familial AD (APPswe), were used as a model to explore the effect of Aβ pathology on 5-HT1B and related molecules including the receptor adaptor protein (p11), SERT and MAOA gene expression, and MAOA activity after treatment with selective serotonin reuptake inhibitor (SSRI) (sertraline), and a 5-HT1B receptor antagonist. Sertraline led more than 70 fold increase of 5-HT1B gene expression (p < 0.001), an increased serotonin turnover in both APPswe and control cells and reduced intracellular serotonin levels by 75% in APPswe cells but not in controls (p > 0.05). Treatment with the 5-HT1B receptor antagonist increased SERT gene-expression in control cells but not in the APPswe cells. 5-HT and 5-HT1B antagonist treatment resulted in different p11 expression patterns in APPswe cells compared to controls. Although MAOA gene expression was not changed by APPswe overexpression, adding 5-HT lead to a significant increase in MAOA gene expression in APPswe but not control cells. These findings suggest that the sensitivity of the 5-HT1B receptor and related systems is affected by APPswe overexpression, with potential relevance for pharmacologic intervention in AD. This may at least partly explain the lack of effect of SSRIs in patients with AD and depression.

A Phase II, Randomized, Double-Blind, Placebo-Controlled Study of Safety, Pharmacokinetics, and Biomarker Results of Subcutaneous Bapineuzumab in Patients with mild to moderate Alzheimer's disease. - Brody, Mark; Liu, Enchi; Di, Jianing; Lu, Ming; Margolin, Richard A; Werth, John L; Booth, Kevin; Shadman, Anna; Brashear, H Robert; Novak, Gerald (J Alzheimers Dis, 2016)
BACKGROUND: Bapineuzumab, a humanized monoclonal antibody, targets amyloid-β (Aβ1-40/1 -42) that is believed to play a key role in the pathogenesis of Alzheimer disease (AD). OBJECTIVES: To assess the effects of monthly subcutaneous (SC) bapineuzumab versus placebo on cerebral amyloid signal in amyloid-positive patients with mild to moderate AD. The incidence of amyloid-related imaging abnormalities-edema/effusion (ARIA-E), pharmacokinetics, pharmacodynamics, immunogenicity, and other safety aspects of bapineuzumab were also evaluated. METHODS: In this multicenter, double-blind study, 146 patients were randomized (1 : 1:1 : 1) to SC bapineuzumab 2, 7, or 20 mg/month or placebo. Lack of efficacy of intravenous (IV) bapineuzumab in Phase III studies led to truncation of the treatment duration from 24 months to 12 months. Primary endpoint: change from baseline to month 12 in brain amyloid signal as measured by standardized uptake value ratio (SUVR) using florbetapir positron emission tomography (PET). RESULTS: Florbetapir PET SUVR decreased significantly (p = 0.038) from baseline to month 12 for the bapineuzumab 7 mg/month group only; reductions versus placebo were not significant for any dosage. One patient each in bapineuzumab 2 mg/month and 20 mg/month groups had ARIA-E. The percentages of patients with treatment-emergent adverse events were similar in placebo (77.8%) and bapineuzumab 2 mg/month (78.4%) group, but higher in 7 mg/month (94.4%) and 20 mg/month (89.2%) groups. CONCLUSION: Bapineuzumab SC once-monthly did not demonstrate significant treatment difference over placebo on cerebral amyloid signal at one year but was well-tolerated. There was less ARIA-E than had been expected based on prior experience with comparable exposure on IV bapineuzumab.

A Phase II Study of Fornix Deep Brain Stimulation in Mild Alzheimer's Disease. - Lozano, Andres M; Fosdick, Lisa; Chakravarty, M Mallar; Leoutsakos, Jeannie-Marie; Munro, Cynthia; Oh, Esther; Drake, Kristen E; Lyman, Christopher H; Rosenberg, Paul B; Anderson, William S; Tang-Wai, David F; Pendergrass, Jo Cara; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Deep brain stimulation (DBS) is used to modulate the activity of dysfunctional brain circuits. The safety and efficacy of DBS in dementia is unknown. OBJECTIVE: To assess DBS of memory circuits as a treatment for patients with mild Alzheimer's disease (AD). METHODS: We evaluated active "on" versus sham "off" bilateral DBS directed at the fornix-a major fiber bundle in the brain's memory circuit-in a randomized, double-blind trial (ClinicalTrials.gov NCT01608061) in 42 patients with mild AD. We measured cognitive function and cerebral glucose metabolism up to 12 months post-implantation. RESULTS: Surgery and electrical stimulation were safe and well tolerated. There were no significant differences in the primary cognitive outcomes (ADAS-Cog 13, CDR-SB) in the "on" versus "off" stimulation group at 12 months for the whole cohort. Patients receiving stimulation showed increased metabolism at 6 months but this was not significant at 12 months. On post-hoc analysis, there was a significant interaction between age and treatment outcome: in contrast to patients  CONCLUSION: DBS for AD was safe and associated with increased cerebral glucose metabolism. There were no differences in cognitive outcomes for participants as a whole, but participants aged≥65 years may have derived benefit while there was possible worsening in patients below age 65 years with stimulation.

Plasma Ceramides and Neuropsychiatric Symptoms of Alzheimer's Disease. - Xing, Yi; Tang, Yi; Zhao, Lina; Wang, Qi; Qin, Wei; Zhang, Jin-Lan; Jia, Jianping (J Alzheimers Dis, 2016)
BACKGROUND: Various evidence demonstrates the influences of ceramides on Alzheimer's disease (AD) pathogenesis. Furthermore, increased ceramides were also suggested to be related to cognitive decline. However, the association between ceramides and neuropsychiatric symptoms of AD remains unclear. OBJECTIVE: This study sought to investigate the association between plasma ceramide levels and multiple neuropsychiatric symptoms in AD. METHODS: A total of 98 patients and 92 cognitively normal controls participated in this study, including 56 with mild AD and 42 with moderate to severe AD. The Neuropsychiatric Inventory (NPI) was used to assess neuropsychiatric symptoms. Considering the influences of dementia severity on ceramide levels and neuropsychiatric symptoms, a subgroup analysis was conducted by dementia severity. RESULTS: Except for C24 : 0, all ceramide species were significantly higher in AD patients than in controls. After controlling for confounding factors, the C16 : 0 and C20 : 0 levels were positively associated with delusions, and the quartiles of C22 : 0 and C24 : 0 were positively associated with depression. In the subgroup analysis, association between ceramide species and delusions were only observed in mild AD, and the association between ceramides and depression were prominent in moderate to severe AD. In mild AD, after controlling for age, gender, anti-dementia medications, diabetes status, and ApoE ɛ4 status, the C16 : 0, C20 : 0, and quartiles of C24 : 1 were associated with delusions. In moderate to severe AD, depression was associated with C22 : 0 and C24 : 0. CONCLUSION: There were stage-specific associations between ceramides and neuropsychiatric symptoms of AD. The potential mechanisms deserve further investigation.

Plasma Phospholipid and Sphingolipid Alterations in Presenilin1 Mutation Carriers: A Pilot Study. - Chatterjee, Pratishtha; Lim, Wei L F; Shui, Guanghou; Gupta, Veer B; James, Ian; Fagan, Anne M; Xiong, Chengjie; Sohrabi, Hamid R; Taddei, Kevin; Brown, Belinda M; Benzinger, Tammie; Masters, Colin; et al. (J Alzheimers Dis, 2016)
BACKGROUND AND OBJECTIVE: Aberrant lipid metabolism has been implicated in sporadic Alzheimer's disease (AD). The current study investigated plasma phospholipid and sphingolipid profiles in individuals carrying PSEN1 mutations responsible for autosomal dominant AD (ADAD). METHODS: Study participants evaluated were from the Perth and Melbourne sites of the Dominantly Inherited Alzheimer Network (DIAN) study. Plasma phospholipid and sphingolipid profiles were measured using liquid chromatography coupled with mass spectrometry in 20 PSEN1 mutation carriers (MC; eight of whom were symptomatic and twelve asymptomatic, based on Clinical Dementia Rating scores) and compared with six non carriers (NC) using linear mixed models. Further, AD gold standard biomarker data obtained from the DIAN database were correlated with lipid species significantly altered between MC and NC, using Spearman's correlation coefficient. RESULTS: One-hundred and thirty-nine plasma phospholipid and sphingolipid species were measured. Significantly altered species in MC compared to NC primarily belonged to choline and ethanolamine containing phospholipid classes and ceramides. Further phosphatidylcholine species (34:6, 36:5, 40:6) correlated with cerebrospinal fluid tau (p <  0.05), and plasmalogen ethanolamine species (34:2, 36:,4) correlated with both cerebrospinal fluid tau and brain amyloid load within the MC group (p <  0.05). CONCLUSION: These findings indicate altered phospholipid and sphingolipid metabolism in ADAD and provide insight into the pathomolecular changes occurring with ADAD pathogenesis. Further, findings reported in this study allow comparison of lipid alterations in ADAD with those reported previously in sporadic AD. The findings observed in the current pilot study warrant validation in the larger DIAN cohort.
Keywords: Adult; Alzheimer Disease; Apolipoproteins E; Female; Humans; Linear Models; Male; Middle Aged; Mutation; Phospholipids; Pilot Projects; Presenilin-1; Sphingolipids

Possible Involvement of Adiponectin, the Anti-Diabetes Molecule, in the Pathogenesis of Alzheimer's Disease. - Waragai, Masaaki; Adame, Anthony; Trinh, Ivy; Sekiyama, Kazunari; Takamatsu, Yoshiki; Une, Kaori; Masliah, Eliezer; Hashimoto, Makoto (J Alzheimers Dis, 2016)
Adiponectin (APN) is protective in animal models of neurodegenerative diseases, but the role of APN in human brain has not been established. Using an enzyme-linked immunosorbent assay, we found that APN was significantly decreased in cerebrospinal fluid (CSF) of patients with Alzheimer's disease (AD), compared to those in patients with mild cognitive impairment (MCI) and in normal controls (NC), despite elevation of APN in serum of patients with MCI and AD compared to that in NC. The discrepancy of CSF APN from serum APN in AD may suggest some critical actions of APN in the pathogenesis of AD. Indeed, it was histologically observed that APN was co-localized with tau in neurofibrillary tangles and immunoblot analysis showed that the functional trimers of APN were significantly decreased in AD compared to those in NC. Collectively, a loss of function of APN may be involved in the pathogenesis of AD.

Post Hoc Analyses of ApoE Genotype-Defined Subgroups in Clinical Trials. - Kennedy, Richard E; Cutter, Gary R; Wang, Guoqiao; Schneider, Lon S (J Alzheimers Dis, 2016)
BACKGROUND: Many post hoc analyses of clinical trials in Alzheimer's disease (AD) and mild cognitive impairment (MCI) are in small Phase 2 trials. Subject heterogeneity may lead to statistically significant post hoc results that cannot be replicated in larger follow-up studies. OBJECTIVE: We investigated the extent of this problem using simulation studies mimicking current trial methods with post hoc analyses based on ApoE4 carrier status. METHODS: We used a meta-database of 24 studies, including 3,574 subjects with mild AD and 1,171 subjects with MCI/prodromal AD, to simulate clinical trial scenarios. Post hoc analyses examined if rates of progression on the Alzheimer's Disease Assessment Scale-cognitive (ADAS-cog) differed between ApoE4 carriers and non-carriers. RESULTS: Across studies, ApoE4 carriers were younger and had lower baseline scores, greater rates of progression, and greater variability on the ADAS-cog. Up to 18% of post hoc analyses for 18-month trials in AD showed greater rates of progression for ApoE4 non-carriers that were statistically significant but unlikely to be confirmed in follow-up studies. The frequency of erroneous conclusions dropped below 3% with trials of 100 subjects per arm. In MCI, rates of statistically significant differences with greater progression in ApoE4 non-carriers remained below 3% unless sample sizes were below 25 subjects per arm. CONCLUSIONS: Statistically significant differences for ApoE4 in post hoc analyses often reflect heterogeneity among small samples rather than true differential effect among ApoE4 subtypes. Such analyses must be viewed cautiously. ApoE genotype should be incorporated into the design stage to minimize erroneous conclusions.
Keywords: Alzheimer Disease; Apolipoprotein E4; Clinical Trials as Topic; Cognitive Dysfunction; Data Interpretation, Statistical; Humans; Research Design

Posterior Accumulation of Tau and Concordant Hypometabolism in an Early-Onset Alzheimer's Disease Patient with Presenilin-1 Mutation. - Smith, Ruben; Wibom, Moa; Olsson, Tomas; Hägerström, Douglas; Jögi, Jonas; Rabinovici, Gil D; Hansson, Oskar (J Alzheimers Dis, 2016)
It is unclear whether the distribution of tau pathology differs between cases with early-onset familial Alzheimer's disease (AD) and sporadic AD. We present positron emission tomography (PET) data from a young patient with a presenilin-1 mutation (Thr116Asn). 18F-flutemetamol PET showed a distribution of amyloid-β fibrils similar to sporadic AD. However, the pattern of tau pathology, revealed using 18F-AV1451 PET, showed higher uptake in posterior cingulate, precuneus, parietal and occipital cortices compared to late-onset sporadic AD. Further, the tau pathology, but not amyloid pathology, exhibited a very clear inverse relationship with 18F-fluorodeoxyglucose-metabolism, indicating neuronal hypometabolism in regions affected by tau aggregates.
Keywords: Adult; Age of Onset; Alzheimer Disease; Amyloid beta-Peptides; Aniline Compounds; Benzothiazoles; Brain; Brain Mapping; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Positron-Emission Tomography; Presenilin-1; Radiopharmaceuticals; tau Proteins

Prediction of Progressive Mild Cognitive Impairment by Multi-Modal Neuroimaging Biomarkers. - Xu, Lele; Wu, Xia; Li, Rui; Chen, Kewei; Long, Zhiying; Zhang, Jiacai; Guo, Xiaojuan; Yao, Li (J Alzheimers Dis, 2016)
For patients with mild cognitive impairment (MCI), the likelihood of progression to probable Alzheimer's disease (AD) is important not only for individual patient care, but also for the identification of participants in clinical trial, so as to provide early interventions. Biomarkers based on various neuroimaging modalities could offer complementary information regarding different aspects of disease progression. The current study adopted a weighted multi-modality sparse representation-based classification method to combine data from the Alzheimer's Disease Neuroimaging Initiative (ADNI) database, from three imaging modalities: Volumetric magnetic resonance imaging (MRI), fluorodeoxyglucose (FDG) positron emission tomography (PET), and florbetapir PET. We included 117 normal controls (NC) and 110 MCI patients, 27 of whom progressed to AD within 36 months (pMCI), while the remaining 83 remained stable (sMCI) over the same time period. Modality-specific biomarkers were identified to distinguish MCI from NC and to predict pMCI among MCI. These included the hippocampus, amygdala, middle temporal and inferior temporal regions for MRI, the posterior cingulum, precentral, and postcentral regions for FDG-PET, and the hippocampus, amygdala, and putamen for florbetapir PET. Results indicated that FDG-PET may be a more effective modality in discriminating MCI from NC and in predicting pMCI than florbetapir PET and MRI. Combining modality-specific sensitive biomarkers from the three modalities boosted the discrimination accuracy of MCI from NC (76.7%) and the prediction accuracy of pMCI (82.5%) when compared with the best single-modality results (73.6% for MCI and 75.6% for pMCI with FDG-PET).
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Aniline Compounds; Biomarkers; Brain; Cognitive Dysfunction; Disease Progression; Ethylene Glycols; Female; Fluorodeoxyglucose F18; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Positron-Emission Tomography; Predictive Value of Tests; Psychiatric Status Rating Scales; Sensitivity and Specificity

Predictors of Mortality in Dementia: The PRIME Study. - Connors, Michael H; Ames, David; Boundy, Karyn; Clarnette, Roger; Kurrle, Sue; Mander, Alastair; Ward, John; Woodward, Michael; Brodaty, Henry (J Alzheimers Dis, 2016)
BACKGROUND: Dementia is a terminal illness. While various baseline characteristics of patients, such as age, sex, and dementia severity, are known to predict mortality, little research has examined how changes in patients' symptoms over time predict survival. There are also limited data on patients seen in memory clinics, as opposed to other health care settings, and whether antipsychotic medications are associated with mortality in dementia once patients' demographic and clinical features are controlled for. OBJECTIVE: To identify predictors of mortality in patients with dementia. METHOD: Of 970 patients recruited from nine memory clinics around Australia, 779 patients had dementia at baseline. Patients completed measures of dementia severity, cognition, functional ability, neuropsychiatric symptoms, caregiver burden, and medication use at baseline and at regular intervals over a three-year period. Mortality data were obtained from state registries eight years after baseline. RESULTS: Overall, 447 (57.4%) of the patients with dementia died within the eight years. Older age, male sex, more severe dementia and functional impairment at baseline, greater decline in dementia severity and functional impairment over six months, taking a larger number of medications, and use of atypical antipsychotic medication predicted earlier mortality. CONCLUSIONS: The findings confirm that demographic and diagnostic features predict the survival of patients with dementia. Importantly, the findings indicate that changes in dementia severity and functional impairment over time predict mortality independently of baseline levels, and provide further evidence for the higher mortality risk of patients taking antipsychotic medications.

The Presence of Select Tau Species in Human Peripheral Tissues and Their Relation to Alzheimer's Disease. - Dugger, Brittany N; Whiteside, Charisse M; Maarouf, Chera L; Walker, Douglas G; Beach, Thomas G; Sue, Lucia I; Garcia, Angelica; Dunckley, Travis; Meechoovet, Bessie; Reiman, Eric M; Roher, Alex E (J Alzheimers Dis, 2016)
Tau becomes excessively phosphorylated in Alzheimer's disease (AD) and is widely studied within the brain. Further examination of the extent and types of tau present in peripheral tissues and their relation to AD is warranted given recent publications on pathologic spreading. Cases were selected based on the presence of pathological tau spinal cord deposits (n = 18). Tissue samples from sigmoid colon, scalp, abdominal skin, liver, and submandibular gland were analyzed by western blot and enzyme-linked immunosorbent assays (ELISAs) for certain tau species; frontal cortex gray matter was used for comparison. ELISAs revealed brain to have the highest total tau levels, followed by submandibular gland, sigmoid colon, liver, scalp, and abdominal skin. Western blots with antibodies recognizing tau phosphorylated at threonine 231(pT231), serine 396 and 404 (PHF-1), and an unmodified total human tau between residues 159 and 163 (HT7) revealed multiple banding patterns, some of which predominated in peripheral tissues. As submandibular gland had the highest levels of peripheral tau, a second set of submandibular gland samples were analyzed (n = 36; 19 AD, 17 non-demented controls). ELISAs revealed significantly lower levels of pS396 (p = 0.009) and pT231 (p = 0.005) in AD cases but not total tau (p = 0.18). Furthermore, pT231 levels in submandibular gland inversely correlated with Braak neurofibrillary tangle stage (p = 0.04), after adjusting for age at death, gender, and postmortem interval. These results provide evidence that certain tau species are present in peripheral tissues. Of potential importance, submandibular gland pT231 is progressively less abundant with increasing Braak neurofibrillary tangle stage.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Blotting, Western; Colon; Enzyme-Linked Immunosorbent Assay; Female; Frontal Lobe; Gray Matter; Humans; Immunohistochemistry; Liver; Male; Neurofibrillary Tangles; Phosphorylation; Severity of Illness Index; Sex Characteristics; Skin; Submandibular Gland; tau Proteins

Prevention Trials in Alzheimer's Disease: Current Status and Future Perspectives. - Wang, Jun; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is the most common form of dementia in the elderly. Over the past 20 years, both pharmacological and lifestyle interventions have been studied for AD prevention, but the overall results have been disappointing. The majority of disappointing results have raised questions and great challenges for the future of AD prevention trials. Ongoing advances in the knowledge of pathogenesis, in the identification of novel targets, in improved outcome measures, and in identification and validation of biomarkers may lead to effective strategies for AD prevention. In this paper, we review the selection of participants and interventions, trial design, outcome assessments, and promising biomarkers in prevention trials, and summarize the lessons learned from completed trials and perspectives from ongoing trials in AD prevention. Selection of optimal participants and interventions, coupled with more refined outcomes and more efficient trial design, may have the capacity to deliver a new era of preventive discovery in this challenging area.
Keywords: Alzheimer Disease; Biomarkers; Clinical Trials as Topic; Humans

Primary Progressive Aphasia in the Network of French Alzheimer Plan Memory Centers. - Magnin, Eloi; Démonet, Jean-François; Wallon, David; Dumurgier, Julien; Troussière, Anne-Cécile; Jager, Alain; Duron, Emmanuelle; Gabelle, Audrey; de la Sayette, Vincent; Volpe-Gillot, Lisette; Tio, Gregory; Evain, Sarah; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Few demographical data about primary progressive aphasia (PPA) are available, and most knowledge regarding PPA is based on tertiary centers' results. OBJECTIVE: Our aims were to describe demographical characteristics of the PPA population in a large sample of PPA patients from the network of French Alzheimer plan memory centers (Sample 1), and to describe the stratification of cerebrospinal fluid (CSF) biomarkers in two different samples of PPA patients (Samples 2 and 3). METHODS: All registered PPA patients in the French Alzheimer's disease (AD) databank (Sample 1: n = 2,035) and a subsample (Sample 2: n = 65) derived from a multicentric prospective cohort with CSF biomarker analysis were analyzed. A multicentric retrospective cohort from language expert tertiary centers (Sample 3: n = 97) with CSF biomarker analysis was added. Sample 3 was added to replicate the CSF results of the Sample 2 and to evaluate repartition of AD pathology in the three variant of PPA according to the latest classification. RESULTS: Non-Fluent/Agrammatic, Logopenic, and Unclassifiable PPA patients (NF/A-Logo-Unclass PPA) were older and more frequent than Semantic PPA patients (2.2 versus 0.8/100,000 inhabitants; p < 0.00001). Male predominance occurred after the age of 80 (p < 0.00001). A higher level of education was observed in the PPA population compared to a typical amnesic AD group. No demographical significant difference between PPA due to AD and not due to AD was observed. The Logopenic variant was most frequent with 85% of AD CSF biomarker profiles (35% in NF/A PPA; 20% in Semantic PPA). CONCLUSION: PPA occurs also in an elderly population, especially in male patients over 80. CSF biomarkers are useful to stratify PPA. The epidemiology of PPA should be further investigated to confirm gender and cognitive reserve role in PPA to better understand the factors and mechanisms leading to this language-predominant deficit during neurodegenerative diseases.

Protective Effect of Amyloid-β Peptides Against Herpes Simplex Virus-1 Infection in a Neuronal Cell Culture Model. - Bourgade, Karine; Le Page, Aurélie; Bocti, Christian; Witkowski, Jacek M; Dupuis, Gilles; Frost, Eric H; Fülöp, Tamás (J Alzheimers Dis, 2016)
Senile amyloid plaques are one of the main hallmarks of Alzheimer's disease (AD). They correspond to insoluble deposits of amyloid-β peptides (Aβ) and are responsible for the inflammatory response and neurodegeneration that lead to loss of memory. Recent data suggest that Aβ possess antimicrobial and anti-viral activity in vitro. Here, we have used cocultures of neuroglioma (H4) and glioblastoma (U118-MG) cells as a minimal in vitro model to investigate whether Aβ is produced by neuroglioma cells and whether this could result in protective anti-viral activity against HSV-1 infection. Results showed that H4 cells secreted Aβ42 in response to HSV-1 challenge and that U118-MG cells could rapidly internalize Aβ42. Production of pro-inflammatory cytokines TNFα and IL-1β by H4 and U118-MG cells occurred under basal conditions but infection of the cells with HSV-1 did not significantly upregulate production. Both cell lines produced low levels of IFNα. However, extraneous Aβ42 induced strong production of these cytokines. A combination of Aβ42 and HSV-1 induced production of pro-inflammatory cytokines TNFα and IL-1β, and IFNα in the cell lines. The reported anti-viral protection of Aβ42 was revealed in transfer experiments involving conditioned medium (CM) of HSV-1-infected H4 cells. CM conferred Aβ-dependent protection against HSV-1 replication in de novo cultures of H4 cells challenged with HSV-1. Type 1 interferons did not play a role in these assays. Our data established that H4 neuroglioma cells produced Aβ42 in response to HSV-1 infection thus inhibiting secondary replication. This mechanism may play a role in the etiology of AD.
Keywords: Amyloid beta-Peptides; Amyloid Precursor Protein Secretases; Cell Line, Tumor; Coculture Techniques; Culture Media, Conditioned; Herpes Simplex; Herpesvirus 1, Human; Humans; Interferon-alpha; Interleukin-1beta; Neuroglia; Neurons; Peptide Fragments; Tumor Necrosis Factor-alpha; Virus Replication

Quantitative Proteomics Reveals the Mechanism of Oxygen Treatment on Lenses of Alzheimer's Disease Model Mice. - Wang, Hao; Wang, Ying; Hong, Xiaoyu; Li, Shuiming; Wang, Yong (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD) is a neurodegenerative disease with well-characterized pathological features. Yet the underlying mechanisms have not been resolved and an effective therapeutic approach is lacking. Cerebral hypoxia is considered a risk factor of AD. OBJECTIVE: We tested whether oxygen supplementation can relieve AD symptoms and how it affects the expression levels of proteins in the lens. METHODS: Triple transgenic AD model (3xTg-AD) mice were divided into oxygen treated (OT) and control (Ctrl) groups. Their cognitive performances were tested in a Morris water maze (MWM) paradigm. Then, their eye lens tissues were subjected to quantitative proteomics analysis by the iTRAQ (isobaric tags for relative and absolute quantification) method. The up- and downregulated proteins were classified according to a Gene Ontology (GO) database in PANTHER. Behavioral and proteomic data were compared between the groups. RESULTS: Mice in the OT group had better learning and memorizing performance compared with the Ctrl group in MWM test. Lenses from the OT group had 205 differentially regulated proteins, relative to lenses from the Ctrl group, including proteins that are involved in the clearance of amyloid β-protein. CONCLUSION: The results of this study indicate that oxygen treatment can improve cognitive function in AD model mice and alters protein expression in a manner consistent with improved redox regulation.

Regular Benzodiazepine and Z-Substance Use and Risk of Dementia: An Analysis of German Claims Data. - Gomm, Willy; von Holt, Klaus; Thomé, Friederike; Broich, Karl; Maier, Wolfgang; Weckbecker, Klaus; Fink, Anne; Doblhammer, Gabriele; Haenisch, Britta (J Alzheimers Dis, 2016)
BACKGROUND: While acute detrimental effects of benzodiazepine (BDZ), and BDZ and related z-substance (BDZR) use on cognition and memory are known, the association of BDZR use and risk of dementia in the elderly is controversially discussed. Previous studies on cohort or claims data mostly show an increased risk for dementia with the use of BDZs or BDZRs. For Germany, analyses on large population-based data sets are missing. OBJECTIVE: To evaluate the association between regular BDZR use and incident any dementia in a large German claims data set. METHODS: Using longitudinal German public health insurance data from 2004 to 2011 we analyzed the association between regular BDZR use (versus no BDZR use) and incident dementia in a case-control design. We examined patient samples aged≥60 years that were free of dementia at baseline. To address potential protopathic bias we introduced a lag time between BDZR prescription and dementia diagnosis. Odds ratios were calculated applying conditional logistic regression, adjusted for potential confounding factors such as comorbidities and polypharmacy. RESULTS: The regular use of BDZRs was associated with a significant increased risk of incident dementia for patients aged≥60 years (adjusted odds ratio [OR] 1.21, 95% confidence interval [CI] 1.13-1.29). The association was slightly stronger for long-acting substances than for short-acting ones. A trend for increased risk for dementia with higher exposure was observed. CONCLUSION: The restricted use of BDZRs may contribute to dementia prevention in the elderly.

Reproductive history and risk of cognitive impairment in elderly women: a cross-sectional study in eastern China. - Li, Fu-Dong; He, Fan; Chen, Ting-Rui; Xiao, Yuan-Yuan; Lin, Shang-Tong; Shen, Wei; Wang, Xin-Yi; Zhai, Yu-Jia; Shang, Xiao-Peng; Lin, Jun-Fen (J Alzheimers Dis, 2016)
BACKGROUND: Epidemiological studies suggest that proxies of higher lifetime estrogen exposure are associated with better cognitive function in postmenopausal women, but this has not been found consistently. OBJECTIVE: To determine whether reproductive history, an important modifier of estrogen exposure across the lifetime, is associated with risk of cognitive impairment in postmenopausal women. METHODS: We analyzed the baseline data from Zhejiang Major Public Health Surveillance Program (ZPHS) including 4,796 postmenopausal women. Cognitive impairment was assessed through the application of Mini-Mental State Examination questionnaire. Logistic regression models, controlled for an extensive range of potential confounders, were generated to examine the associations between women's reproductive history and risk of cognitive impairment in their later life. RESULTS: The length of reproductive period was inversely associated with risk of cognitive impairment (p = 0.001). Odds ratio (OR) of cognitive impairment were 1.316 (95% CI 1.095∼1.582) for women with 5 or more times of full-term pregnancies, compared with those with 1∼4 times of full-term pregnancies. Women without incomplete pregnancy had a significant higher risk of cognitive impairment (OR = 1.194, 95% CI 1.000∼1.429), compared with the reference (1∼2 times of incomplete pregnancies). Oral contraceptive use (OR = 0.489, 95% CI 0.263∼0.910) and intrauterine device (IUD) use (OR = 0.684, 95% CI 0.575∼0.815) were associated with significantly reduced risk of cognitive impairment. CONCLUSION: Our results indicated that shorter reproductive period, higher number of full-term pregnancies and no incomplete pregnancy history were associated with an increased risk of cognitive impairment. In contrast, oral contraceptive and IUD use corresponded to reduced risk of cognitive impairment.
Keywords: Aged; Aged, 80 and over; China; Cognition; Cognition Disorders; Contraceptives, Oral; Cross-Sectional Studies; Estrogens; Female; Humans; Intrauterine Devices; Logistic Models; Middle Aged; Neuropsychological Tests; Odds Ratio; Postmenopause; Psychiatric Status Rating Scales; Reproductive History

Resting-State Cardiac Workload is Related to Both Increased Neocortical Aggregation of Amyloid-β and Relative Impairments in Spatial Working Memory in Pre-Clinical Alzheimer's Disease. - Santos, Cláudia Yang; Lim, Yen Ying; Wu, Wen-Chih; Machan, Jason Timothy; Polynice, Shahena; Schindler, Rachel; Maruff, Paul; Snyder, Peter Jeffrey (J Alzheimers Dis, 2016)
We sought to determine whether there is any association between a cardiac workload marker, rate pressure product (RPP), working memory, and cortical amyloid-β (Aβ) burden in 63 cognitively normal midlife adults (Mage = 62.8 years; range = 55 to 75 years) at risk for Alzheimer's disease (AD). The results show a small-to-moderate relationship between increasing cardiac workload (at rest) and neocortical amyloidosis in individuals at the preclinical stage of AD. Moreover, increasing RPP was linearly related to increasing relative impairments on a spatial working memory task (R2 = 0.30), but only for those individuals with neuroimaging evidence suggestive of preclinical AD. These results support a relationship between the aggregation of Aβ protein plaques in the neocortex, increased cognitive impairment, and more inefficient myocardial oxygen use in the absence of significant metabolic demands.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Blood Pressure; Disease Progression; Female; Heart Rate; Humans; Male; Maze Learning; Memory Disorders; Middle Aged; Neocortex; Neuropsychological Tests; Positron-Emission Tomography; Protein Aggregation, Pathological; Workload

The Role of Cerebrovascular Disease in Amyloid Deposition. - Noh, Young; Seo, Sang Won; Jeon, Seun; Lee, Jong Min; Kim, Jae Seung; Lee, Jae-Hong; Kim, Jung-Hyun; Kim, Geon Ha; Ye, Byoung Seok; Cho, Hanna; Kim, Hee Jin; Yoon, Cindy W; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Some patients clinically diagnosed with subcortical vascular cognitive impairment (SVCI) have co-morbidity with AD pathology. OBJECTIVE: We investigated topographical differences in amyloid burden between SVCI and Alzheimer's disease type cognitive impairment (ADCI) using [11C] Pittsburgh compound B (PiB) positron emission tomography (PET). The purpose of this study was to investigate the role of cerebrovascular disease (CVD) in amyloid deposition. METHODS: We recruited 44 patients with SVCI and 44 patients with ADCI (amnestic mild cognitive impairment or Alzheimer's disease) with absent or minimal white matter hyperintensities, all with PiB-positive PET scans [PiB+]. As controls, we included 13 participants with normal cognition and PiB-negative scans. We divided the SVCI and ADCI patients into three groups according to global PiB retention ratio of SVCI, and then compared the tertiles in terms of the distribution of PiB retention using statistical parametric mapping analyses. Lobar to global PiB retention ratio and asymmetry indices were also compared between SVCI and ADCI groupsResults: Compared to PiB+ ADCI patients, PiB+ SVCI patients exhibited: 1) increased left-right asymmetry, and increased anterior-posterior difference; and 2) increased PiB retention in the parietal cortex, the occipital cortex and the precuneus-posterior cingulate cortex. In contrast, ADCI patients showed increased PiB retention in the striatum. When stratified by level of PiB retention, each group showed different characteristics. CONCLUSION: Our results showed that the distribution of amyloid deposition differed between patients with PiB+ SVCI and ADCI. These suggest that CVD contribute to and alter the known progression pattern in amyloid deposition in Alzheimer's disease.

Safety and Tolerability of R(+) Pramipexole in Mild-to-Moderate Alzheimer's Disease. - Bennett, James; Burns, Jeffrey; Welch, Paul; Bothwell, Rebecca (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is an aging-related, degenerative brain disease of adults. Most (∼95%) of AD occurs sporadically and is associated with early-appearing deficits in brain regional glucose uptake, changes in cerebrospinal fluid (CSF) AD-related proteins, regional brain atrophy, and oxidative stress damage. We treated mild-moderate AD individuals with R(+)-pramipexole-dihydrochloride (R(+)PPX), a neuroprotective, lipophilic-cation, free-radical scavenger that accumulates into brain and mitochondria. 19 subjects took R(+)PPX twice a day in increasing daily doses up to 300 mg/day under a physician-sponsor IND (60,948, JPB), IRB-approved protocol and quarterly external safety committee monitoring. 15 persons finished and contributed baseline and post-treatment serum, lumbar spinal fluid, brain 18F-2DG PET scans, and ADAS-Cog scores. ADAS-Cog scores did not change (n = 1), improved (n = 2), declined 1-3 points (n = 5), or declined 4-13 points (n = 8) over 6 months of R(+)PPX treatment. Serum PPX levels were not related to changes in ADAS-Cog scores. Fasting AM serum PPX levels at 6 months varied considerably across subjects and correlated strongly with CSF [PPX] (r = 0.97, p <  0.0001). CSF [PPX] was not related to CSF [Aβ(42)], [Tau], or [P-Tau]. Regional 18F-2DG measures of brain glucose uptake demonstrated a 3-6% decline during R(+)PPX treatment. 56 mild-moderate adverse events occurred, 26 probably/definitely related to R(+)PPX use, with 4 withdrawals. R(+)PPX was generally well-tolerated and entered brain extracellular space linearly. Further studies of R(+)PPX in AD should include a detailed pharmacokinetic study of peak and trough serum [PPX] variations among subjects prior to planning any larger studies that would be needed to determine efficacy in altering disease progression.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Benzothiazoles; Biomarkers; Brain; Female; Glucose; Humans; Male; Neuropsychological Tests; Nootropic Agents; Peptide Fragments; Positron-Emission Tomography; Severity of Illness Index; tau Proteins; Treatment Outcome

Self-Reported Traumatic Brain Injury and Mild Cognitive Impairment: Increased Risk and Earlier Age of Diagnosis. - LoBue, Christian; Denney, David; Hynan, Linda S; Rossetti, Heidi C; Lacritz, Laura H; Hart, John; Womack, Kyle B; Woon, Fu L; Cullum, C Munro (J Alzheimers Dis, 2016)
This study examined whether history of traumatic brain injury (TBI) is associated with increased risk and earlier onset of mild cognitive impairment (MCI). Subjects with MCI (n = 3,187) and normal cognition (n = 3,244) were obtained from the National Alzheimer's Coordinating Center database. TBI was categorized based on lifetime reported TBI with loss of consciousness (LOC) without chronic deficit. Logistic regression was used to examine TBI history as a predictor of MCI, adjusted for demographics, apolipoprotein E-ɛ4 (ApoE4), a composite vascular risk score, and history of psychiatric factors. ANCOVA was used to examine whether age at MCI diagnosis and estimated age of onset differed between those with (TBI+) and without (TBI-) a history of TBI. TBI history was a significant predictor (p <  0.01) and associated with increased odds of MCI diagnosis in unadjusted (OR = 1.25; 95% CI = 1.05-1.49) and adjusted models, accounting for age, education, ApoE4, and a composite vascular score (OR = 1.32; 95% CI = 1.10-1.58). This association, however, was largely attenuated (OR = 1.14; 95% CI = 0.94-1.37; p = 0.18) after adjustment for reported history of depression. MCI was diagnosed a mean of 2.3 years earlier (p <  0.001) in the TBI+ group, and although TBI+ subjects had an estimated mean of decline 1.7 years earlier, clinician-estimated age of onset failed to differ (p = 0.13) when gender and psychiatric factors were controlled. This is the first report of a possible role for TBI as a risk factor in MCI, but its association may be related to other factors such as gender and depression and requires further investigation.
Keywords: Age of Onset; Aged; Apolipoproteins E; Brain Injuries, Traumatic; Cognitive Dysfunction; Cohort Studies; Databases, Factual; Depression; Educational Status; Female; Humans; Logistic Models; Male; Risk Factors; Self Report; United States

Serum Adiponectin Levels, Neuroimaging, and Cognition in the Mayo Clinic Study of Aging. - Wennberg, Alexandra M V; Gustafson, Deborah; Hagen, Clinton E; Roberts, Rosebud O; Knopman, David; Jack, Clifford; Petersen, Ronald C; Mielke, Michelle M (J Alzheimers Dis, 2016)
BACKGROUND: Adiponectin, a protein involved in inflammatory pathways, may impact the development and progression of Alzheimer's disease (AD). Adiponectin levels have been associated with mild cognitive impairment (MCI) and AD; however, its association with Alzheimer-associated neuroimaging and cognitive outcomes is unknown. OBJECTIVE: Determine the cross-sectional association between plasma adiponectin and neuroimaging and cognitive outcomes in an older population-based sample. METHODS: Multivariable adjusted regression models were used to investigate the association between plasma adiponectin and hippocampal volume (HVa), PiB-PET, FDG PET, cortical thickness, MCI diagnosis, and neuropsychological test performance. Analyses included 535 non-demented participants aged 70 and older enrolled in the Mayo Clinic Study of Aging. RESULTS: Women had higher adiponectin than men (12,631 ng/mL versus 8,908 ng/mL, p < 0.001). Among women, higher adiponectin was associated with smaller HVa (B = -0.595; 95% CI -1.19, -0.005), poorer performance in language (B = -0.676; 95% CI -1.23, -0.121), and global cognition (B = -0.459; 95% CI -0.915, -0.002), and greater odds of a MCI diagnosis (OR = 6.23; 95% CI 1.20, 32.43). In analyses stratified by sex and elevated amyloid (PiB-PET SUVR >1.4), among women with elevated amyloid, higher adiponectin was associated with smaller HVa (B = -0.723; 95% CI -1.43, -0.014), poorer performance in memory (B = -1.02; 95% CI -1.73, -0.312), language (B = -0.896; 95% CI -1.58, -0.212), global cognition (B = -0.650; 95% CI -1.18, -0.116), and greater odds of MCI (OR = 19.34; 95% CI 2.72, 137.34). CONCLUSION: Higher plasma adiponectin was associated with neuroimaging and cognitive outcomes among women. Longitudinal analyses are necessary to determine whether higher adiponectin predicts neurodegeneration and cognitive decline.

Sideritis spp. Extracts Enhance Memory and Learning in Alzheimer's β-Amyloidosis Mouse Models and Aged C57Bl/6 Mice. - Hofrichter, Jacqueline; Krohn, Markus; Schumacher, Toni; Lange, Cathleen; Feistel, Bjöorn; Walbroel, Bernd; Pahnke, Jens (J Alzheimers Dis, 2016)
Nowadays, Alzheimer's disease is the most prevalent epiphenomenon of the aging population. Although soluble amyloid-β (Aβ) species (monomers, oligomers) are recognized triggers of the disease, no therapeutic approach is able to stop it. Herbal medicines are used to treat different diseases in many regions of the world. On the Balkan Peninsula, at the eastern Mediterranean Sea, and adjacent regions, Sideritis species are used as traditional medicine to prevent age-related problems in elderly. To evaluate this traditional knowledge in controlled experiments, we tested extracts of two commonly used Sideritis species, Sideritis euboea and Sideritis scardica, with regard to their effects on cognition in APP-transgenic and aged, non-transgenic C57Bl/6 mice. Additionally, histomorphological and biochemical changes associated with Aβ deposition and treatment were assessed. We found that daily oral treatment with Sideritis spp. extracts highly enhanced cognition in aged, non-transgenic as well as in APP-transgenic mice, an effect that was even more pronounced when extracts of both species were applied in combination. The treatment strongly reduced Aβ42 load in APP-transgenic mice, accompanied by increased phagocytic activity of microglia, and increased expression of the α-secretase ADAM10. Moreover, the treatment was able to fully rescue neuronal loss of APP-transgenic mice to normal levels as seen in non-transgenic controls. Having the traditional knowledge in mind, our results imply that treatment with Sideritis spp. extracts might be a potent, well-tolerated option for treating symptoms of cognitive impairment in elderly and with regard to Alzheimer's disease by affecting its most prominent hallmarks: Aβ pathology and cognitive decline.

A Six-Month Cognitive-Motor and Aerobic Exercise Program Improves Executive Function in Persons with an Objective Cognitive Impairment: A Pilot Investigation Using the Antisaccade Task. - Heath, Matthew; Weiler, Jeffrey; Gregory, Michael A; Gill, Dawn P; Petrella, Robert J (J Alzheimers Dis, 2016)
Persons with an objective cognitive impairment (OCI) are at increased risk for progression to Alzheimer's disease and related dementias. The present pilot project sought to examine whether participation in a long-term exercise program involving cognitive-motor (CM) dual-task gait training and aerobic exercise training improves executive function in persons with an OCI. To accomplish our objective, individuals with an OCI (n = 12) as determined by a Montreal Cognitive Assessment (MoCA) score of less than 26 and older adults (n = 11) deemed to be cognitively healthy (i.e., control group: MoCA score ≥26) completed a six-month moderate-to-high intensity (65-85% maximum heart rate) treadmill-based CM and aerobic exercise training program wherein pre- and post-intervention executive control was examined via the antisaccade task. Notably, antisaccades require a goal-directed eye-movement mirror-symmetrical to a target and represent an ideal tool for the study of executive deficits because of its hands- and language-free nature. As well, the cortical networks mediating antisaccades represent regions associated with neuropathology in cognitive decline and dementia (e.g., dorsolateral prefrontal cortex). Results showed that antisaccade reaction times for the OCI group reliably decreased by 30 ms from pre- to post-intervention, whereas the control group did not produce a reliable pre- to post-intervention change in reaction time (i.e., 6 ms). Thus, we propose that in persons with OCI long-term CM and aerobic training improves the efficiency and effectiveness of the executive mechanisms mediating high-level oculomotor control.

So Close Yet So Far: Executive Contribution to Memory Processing in Behavioral Variant Frontotemporal Dementia. - Bertoux, Maxime; Ramanan, Siddharth; Slachevsky, Andrea; Wong, Stephanie; Henriquez, Fernando; Musa, Gada; Delgado, Carolina; Flanagan, Emma; Bottlaender, Michel; Sarazin, Marie; Hornberger, Michael; Dubois, Bruno (J Alzheimers Dis, 2016)
BACKGROUND: Memory impairment in behavioral variant frontotemporal dementia (bvFTD) is traditionally considered to be mild and attributed to prefrontal cortex dysfunction. Recent studies, however, indicated that some patients can present with a memory impairment of the hippocampal type, showing storage and consolidation deficits in addition to the more executive/prefrontal related encoding and strategic difficulties. OBJECTIVE: This study aimed to study the relationship between executive functions (EF) and memory processes in bvFTD via a data-driven approach. METHOD: Participants consisted of 71 bvFTD (among which 60.6% had a lumbar puncture showing non-Alzheimer biomarker profile) and 60 controls (among which 45% had amyloid imaging showing a normal profile). EF were assessed by the Frontal Assessment Battery, semantic/lexical verbal fluency tests, and forward/backward digit spans. Patients were split into amnestic (n = 33) and non-amnestic (n = 38) subgroups based on normative data (total recall score) from the Free and Cued Selective Reminding Test (FCSRT). Relationships between FCSRT subscores and EF measures were explored through hierarchical clustering analysis, partial correlation analysis with an EF component, and automated linear modeling. RESULTS: Convergent findings across the statistical approaches show that, overall, memory performance was independent from EF in bvFTD whereas the relationship was stronger in controls. Indeed, in bvFTD, memory performance did not cluster with EF, was not correlated with the EF component, and was only partially (4% - 12.7%) predicted by EF. DISCUSSION: These findings show that executive dysfunctions cannot solely explain the memory deficits occurring in bvFTD. Indeed, some patients present with a genuine amnesia affecting storage and consolidation abilities, which are independent from executive dysfunctions. On the clinical level, this study highlights the importance of revising the neuropsychological diagnosis criteria for bvFTD.

Specific Binding of Cu(II) Ions to Amyloid-Beta Peptides Bound to Aggregation-Inhibiting Molecules or SDS Micelles Creates Complexes that Generate Radical Oxygen Species. - Tiiman, Ann; Luo, Jinghui; Wallin, Cecilia; Olsson, Lisa; Lindgren, Joel; Jarvet, Jϋri; Per, Roos; Sholts, Sabrina B; Rahimipour, Shai; Abrahams, Jan Pieter; Karlström, Amelie Eriksson; Gräslund, Astrid; et al. (J Alzheimers Dis, 2016)
Aggregation of the amyloid-beta (Aβ) peptide into insoluble plaques is a major factor in Alzheimer's disease (AD) pathology. Another major factor in AD is arguably metal ions, as metal dyshomeostasis is observed in AD patients, metal ions modulate Aβ aggregation, and AD plaques contain numerous metals including redox-active Cu and Fe ions. In vivo, Aβ is found in various cellular locations including membranes. So far, Cu(II)/Aβ interactions and ROS generation have not been investigated in a membrane environment. Here, we study Cu(II) and Zn(II) interactions with Aβ bound to SDS micelles or to engineered aggregation-inhibiting molecules (the cyclic peptide CP-2 and the ZAβ3(12-58)Y18L Affibody molecule). In all studied systems the Aβ N-terminal segment was found to be unbound, unstructured, and free to bind metal ions. In SDS micelles, Aβ was found to bind Cu(II) and Zn(II) with the same ligands and the same KD as in aqueous solution. ROS was generated in all Cu(II)/Aβ complexes. These results indicate that binding of Aβ to membranes, drugs, and other entities that do not interact with the Aβ N-terminal part, appears not to compromise the N-terminal segment's ability to bind metal ions, nor impede the capacity of N-terminally bound Cu(II) to generate ROS.

Stability of Progranulin Under Pre-Analytical Conditions in Serum and Cerebrospinal Fluid. - Willemse, Eline A J; Durieux-Lu, Sisi; van der Flier, Wiesje M; Pijnenburg, Yolande A L; de Jonge, Robert; Teunissen, Charlotte E (J Alzheimers Dis, 2016)
Progranulin (PGRN) levels in blood and cerebrospinal fluid (CSF) are increasingly studied as potential markers for neurodegenerative disorders. We aimed to 1) characterize two commercially available PGRN ELISAs on several assay validation parameters, 2) assess the stability of PGRN in serum and CSF under pre-analytical conditions, and 3) compare stability in the two assays. Intra- and inter-assay variation, inter-lot variation, linearity, lower limit of detection, and kit correlations were assessed for the Adipogen and R&D PGRN ELISA kits. Blood and serum samples were experimentally exposed to ≤9 freeze/thaw cycles, delayed processing for ≤24 h at room temperature and 4°C, and to temperature stability tests for ≤3 weeks at -20°C, 4°C, room temperature, and 37°C. Both commercial PGRN ELISA kits showed acceptable ranges for intra- and inter-assay variation, where the R&D kit performed more accurate than the Adipogen kit, especially for inter-assay variation (intra-assay serum: 6.7 and 8.3%, respectively; inter-assay serum: 9.2 and 21.0%; intra-assay CSF: 3.6 and 12.0%; inter-assay CSF: 16.0 and 44.5%). Absolute serum PGRN concentrations were 1.9-fold higher in Adipogen than R&D (p < 0.001) and strongly correlated between both kits (ρ= 0.86, p < 0.0001) and CSF PGRN levels were on the borderline of detection in both kits. PGRN was typically stable under all pre-analytical conditions addressed, although two weeks at 37°C resulted in decreased PGRN concentrations in CSF, only when using the Adipogen kit. These results support further examination of PGRN as a potential marker in neurodegenerative diseases, since PGRN is stable in serum and CSF and can be measured using ELISA kits from several providers.

Staging Alzheimer's Disease Risk by Sequencing Brain Function and Structure, Cerebrospinal Fluid, and Cognition Biomarkers. - Chen, Guangyu; Shu, Hao; Chen, Gang; Ward, B Douglas; Antuono, Piero G; Zhang, Zhijun; Li, Shi-Jiang (J Alzheimers Dis, 2016)
This study aims to develop a composite biomarker that can accurately measure the sequential biological stages of Alzheimer's disease (AD) on an individual level. We selected 144 subjects from the Alzheimer's Disease Neuroimaging Initiative 2 datasets. Ten biomarkers, from brain function and structure, cerebrospinal fluid, and cognitive performance, were integrated using the event-based probabilistic model to estimate their optimal temporal sequence (Soptimal). We identified the numerical order of the Soptimal as the characterizing Alzheimer's disease risk events (CARE) index to measure disease stage. The results show that, in the Soptimal, hippocampal and posterior cingulate cortex network biomarkers occur first, followed by aberrant cerebrospinal fluid amyloid-β and p-tau levels, then cognitive deficit, and finally regional gray matter loss and fusiform network abnormality. The CARE index significantly correlates with disease severity and exhibits high reliability. Our findings demonstrate that use of the CARE index would advance AD stage measurement across the whole AD continuum and facilitate personalized treatment of AD.

Subjective Memory Complaints in APOEɛ4 Carriers are Associated with High Amyloid-β Burden. - Zwan, Marissa D; Villemagne, Victor L; Doré, Vincent; Buckley, Rachel; Bourgeat, Pierrick; Veljanoski, Robyn; Salvado, Olivier; Williams, Rob; Margison, Laura; Rembach, Alan; Macaulay, S Lance; Martins, Ralph; et al. (J Alzheimers Dis, 2016)
BACKGROUND: APOEɛ4 genotype and aging have been identified as risk factors for Alzheimer's disease (AD). In addition, subjective memory complaints (SMC) might be a first clinical expression of the effect of AD pathology on cognitive functioning. OBJECTIVE: To assess whether APOEɛ4 genotype, age, SMC, and episodic memory are risk factors for high amyloid-β (Aβ) burden in cognitively normal elderly. METHODS: 307 cognitively normal participants (72.7 ± 6.8 years, 53% female, 55% SMC) from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study underwent amyloid PET and APOE genotyping. Logistic regression analyses were performed to determine the association of APOEɛ4 genotype, age, SMC, and episodic memory with Aβ pathology. RESULTS: Odds of high Aβ burden were greater at an older age (OR = 3.21; 95% CI = 1.68-6.14), when SMC were present (OR = 1.90; 95% CI = 1.03-3.48), and for APOEɛ4 carriers (OR = 7.49; 95% CI = 3.96-14.15), while episodic memory was not associated with odds of high Aβ burden. Stratified analyses showed that odds of SMC for high Aβ burden were increased in specifically APOEɛ4 carriers (OR = 4.58, 95% CI = 1.83-11.49) and younger participants (OR = 3.73, 95% CI = 1.39-10.01). CONCLUSION: Aging, APOEɛ4 genotype, and SMC were associated with high Aβ burden. SMC were especially indicative of high Aβ burden in younger participants and in APOEɛ4 carriers. These findings suggest that selection based on the presence of SMC, APOEɛ4 genotype and age may help identify healthy elderly participants with high Aβ burden eligible for secondary prevention trials.
Keywords: Aged; Aging; Amyloid beta-Peptides; Aniline Compounds; Apolipoprotein E4; Benzothiazoles; Brain; Cognition Disorders; Female; Genotyping Techniques; Heterozygote; Humans; Logistic Models; Male; Neuropsychological Tests; Positron-Emission Tomography; Radiopharmaceuticals; Thiazoles

The Synergistic Roles of the Chronic Prenatal and Offspring Stress Exposures in Impairing Offspring Learning and Memory. - Tang, Wei; Cheng, Juan; Wang, Zheng-Yu; Chen, Ke-Yang; Han, Zhen-Min; Wang, Qi-Hong; Yao, Yu-You (J Alzheimers Dis, 2016)
In Alzheimer's disease (AD), extensive experimental studies have demonstrated a negative impact of chronic stress during various stages of life (including prenatal phase) on some aspects of AD pathology. Nevertheless, presently, few studies have been involved in the learning and memory impairments, as well as neuropathology elicited by the chronic prenatal stress (CPS) and the chronic offspring stress (COS) exposures simultaneously, particularly for the adult male APPswe/PS1dE9 murine offspring. Therefore, the aim of the present study was to investigate the influence of CPS on learning and memory impairments induced by COS in 6-month-old male APPswe/PS1dE9 offspring mice and the related mechanism. Our study firstly demonstrates that 14-day exposure to CPS could exacerbate the learning and memory impairments, as well as neuropathological damages in the CA3 regions of the hippocampus and cortex neurons, which is induced by the 28-day exposure to COS in 6-month-old male APPswe/PS1dE9 offspring mice. In addition, CPS could potentiate the production of AβPP, Aβ42, and corticosterone in 6-month-old male APPswe/PS1dE9 offspring that also suffer COS. In conclusion, our novel findings strongly implicate the synergistic roles of the CPS and COS exposures in impairing offspring learning and memory. Moreover, CPS potentiating the production of Aβ42 might be mediated by glucocorticoids through increasing the expression of APP and BACE1 gene.

Three-Dimensional Eigenbrain for the Detection of Subjects and Brain Regions Related with Alzheimer's Disease. - Zhang, Yudong; Wang, Shuihua; Phillips, Preetha; Yang, Jiquan; Yuan, Ti-Fei (J Alzheimers Dis, 2016)
BACKGROUND: Considering that Alzheimer's disease (AD) is untreatable, early diagnosis of AD from the healthy elderly controls (HC) is pivotal. However, computer-aided diagnosis (CAD) systems were not widely used due to its poor performance. OBJECTIVE: Inspired from the eigenface approach for face recognition problems, we proposed an eigenbrain to detect AD brains. Eigenface is only for 2D image processing and is not suitable for volumetric image processing since faces are usually obtained as 2D images. METHODS: We extended the eigenbrain to 3D. This 3D eigenbrain (3D-EB) inherits the fundamental strategies in either eigenface or 2D eigenbrain (2D-EB). All the 3D brains were transferred to a feature space, which encoded the variation among known 3D brain images. The feature space was named as the 3D-EB, and defined as eigenvectors on the set of 3D brains. We compared four different classifiers: feed-forward neural network, support vector machine (SVM) with linear kernel, polynomial (Pol) kernel, and radial basis function kernel. RESULTS: The 50x10-fold stratified cross validation experiments showed that the proposed 3D-EB is better than the 2D-EB. SVM with Pol kernel performed the best among all classifiers. Our "3D-EB + Pol-SVM" achieved an accuracy of 92.81% ± 1.99% , a sensitivity of 92.07% ± 2.48% , a specificity of 93.02% ± 2.22% , and a precision of 79.03% ± 2.37% . Based on the most important 3D-EB U1, we detected 34 brain regions related with AD. The results corresponded to recent literature. CONCLUSIONS: We validated the effectiveness of the proposed 3D-EB by detecting subjects and brain regions related to AD.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alzheimer Disease; Brain; Datasets as Topic; Early Diagnosis; Female; Humans; Image Interpretation, Computer-Assisted; Imaging, Three-Dimensional; Magnetic Resonance Imaging; Male; Middle Aged; Sensitivity and Specificity; Young Adult

Thyroid-Stimulating Hormone and Mild Cognitive Impairment: Results of the Heinz Nixdorf Recall Study. - Winkler, Angela; Weimar, Christian; Jöckel, Karl-Heinz; Erbel, Raimund; Dragano, Nico; Broecker-Preuss, Martina; Moebus, Susanne; Führer-Sakel, Dagmar; Dlugaj, Martha (J Alzheimers Dis, 2016)
BACKGROUND: Although some studies reported on the association of serum thyroid-stimulating hormone (TSH) concentration and cognition, only one population-based study investigated the association of TSH concentration and mild cognitive impairment (MCI). OBJECTIVE: To investigate the gender-specific association of low- and high-normal TSH concentrations with MCI in euthyroid participants. METHODS: Analysis sample 1 included 2,563 euthyroid participants (aged 50-80 years) from the second examination of the population-based Heinz Nixdorf Recall study. Gender-specific TSH quintiles (Q1 low, Q2-Q4 middle, Q5 high TSH concentration) were determined and group comparisons of age- and education-adjusted mean scores were performed for all cognitive subtests. Analysis sample 2 included 378 participants with MCI and 931 cognitively normal participants. MCI was diagnosed according to previously published MCI criteria. Multivariate logistic regression models were performed using TSH quintiles (Q2-Q4 as reference) to assess the association of low- and high-normal TSH concentration with MCI. Models were performed unadjusted and adjusted for sociodemographic and cardiovascular risk factors. RESULTS: Group comparisons showed significant differences only in the immediate recall of the verbal memory task in women. Only women showed a strong association of high-normal TSH concentration with MCI (unadjusted: odds ratio 2.09, 95% confidence interval 1.29-3.37, full adjusted: 1.86, 1.06-3.27). There was no association with low-normal TSH concentration in women and no association of either low- or high-normal TSH concentration with MCI in men. CONCLUSIONS: These results suggest that women with high-normal TSH concentration might be at higher risk of cognitive decline. This needs to be confirmed in the longitudinal analysis.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Case-Control Studies; Cognitive Dysfunction; Female; Follow-Up Studies; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Risk Factors; Sex Characteristics; Statistics, Nonparametric; Thyrotropin

Time trends in antipsychotic drug use in patients with dementia: a nationwide study. - Nørgaard, Ane; Jensen-Dahm, Christina; Gasse, Christiane; Hansen, Hanne Vibe; Waldemar, Gunhild (J Alzheimers Dis, 2016)
BACKGROUND: Antipsychotics are often used to treat neuropsychiatric symptoms in dementia, but the evidence for effect is limited. Antipsychotics have been associated with increased risk of adverse events and mortality in patients with dementia, leading to safety regulations worldwide. OBJECTIVE: To investigate time trends in use of antipsychotics and other psychotropic drugs in dementia care. METHODS: The study included longitudinal data on all Danish residents ≥65 years. The study population was defined on January 1 of each year from 2000-2012. Data included prescriptions, discharge diagnoses, and somatic and psychiatric comorbidities. Multivariate time trend analyses of psychotropic drug use in patients with dementia within 4-year age bands were performed. RESULTS: Overall, among patients with dementia the prevalence of antipsychotic drug use decreased from 31.3% in 2000 to 20.4% in 2012. The decreasing use of antipsychotics was accompanied by decreasing use of anxiolytics and hypnotics/sedatives, but an increase in the use of antidepressants from 43.3% in 2000 to 53.8% in 2012. These changes were significant across almost all age groups. Treatment intensity among patients using antipsychotics increased as the annual median number of defined daily doses (DDD) increased from 33.3 to 42.0 DDD. CONCLUSIONS: The changing patterns of psychotropic drug use may be caused by warnings against use of antipsychotics. Further research is needed to explore the implications for patient safety.
Keywords: Aged; Aged, 80 and over; Anti-Anxiety Agents; Antidepressive Agents; Antipsychotic Agents; Dementia; Denmark; Drug Prescriptions; Female; Homes for the Aged; Humans; Hypnotics and Sedatives; Longitudinal Studies; Male; Multivariate Analysis; Nursing Homes; Registries

Towards a Pathway Inventory of the Human Brain for Modeling Disease Mechanisms Underlying Neurodegeneration. - Iyappan, Anandhi; Gündel, Michaela; Shahid, Mohammad; Wang, Jiali; Li, Hui; Mevissen, Heinz-Theodor; Müller, Bernd; Fluck, Juliane; Jirsa, Viktor; Domide, Lia; Younesi, Erfan; Hofmann-Apitius, Martin (J Alzheimers Dis, 2016)
Molecular signaling pathways have been long used to demonstrate interactions among upstream causal molecules and downstream biological effects. They show the signal flow between cell compartments, the majority of which are represented as cartoons. These are often drawn manually by scanning through the literature, which is time-consuming, static, and non-interoperable. Moreover, these pathways are often devoid of context (condition and tissue) and biased toward certain disease conditions. Mining the scientific literature creates new possibilities to retrieve pathway information at higher contextual resolution and specificity. To address this challenge, we have created a pathway terminology system by combining signaling pathways and biological events to ensure a broad coverage of the entire pathway knowledge domain. This terminology was applied to mining biomedical papers and patents about neurodegenerative diseases with focus on Alzheimer's disease. We demonstrate the power of our approach by mapping literature-derived signaling pathways onto their corresponding anatomical regions in the human brain under healthy and Alzheimer's disease states. We demonstrate how this knowledge resource can be used to identify a putative mechanism explaining the mode-of-action of the approved drug Rasagiline, and show how this resource can be used for fingerprinting patents to support the discovery of pathway knowledge for Alzheimer's disease. Finally, we propose that based on next-generation cause-and-effect pathway models, a dedicated inventory of computer-processable pathway models specific to neurodegenerative diseases can be established, which hopefully accelerates context-specific enrichment analysis of experimental data with higher resolution and richer annotations.

UCH-L1 Inhibition Decreases the Microtubule-Binding Function of Tau Protein. - Xie, Min; Han, Yun; Yu, Quntao; Wang, Xia; Wang, Shaohui; Liao, Xiaomei (J Alzheimers Dis, 2016)
Ubiquitin C-terminal hydrolase L1 (UCH-L1) is critical for protein degradation and free ubiquitin recycling. In Alzheimer's disease brains, UCH-L1 is negatively related to neurofibrillary tangles whose major component is hyperphosphorylated tau protein, but the direct action of UCH-L1 on tau has not been reported. In the current study, mouse neuroblastoma Neuro2a (N2a) cells were treated by the different concentrations of UCH-L1 inhibitor LDN (2.5, 5 and 10 μM) to inhibit the hydrolase activity of UCH-L1. In addition, we also used UCH-L1 siRNA to treat the HEK293/tau441 cells to decrease the expression of UCH-L1. After LDN and UCH-L1 siRNA treatment, we used immunofluorescence, immunoprecipitation, and tau-microtubule binding assay to measure the microtubule-binding ability and post-translational modifications of tau protein. All the results presented that both inhibition of the activity and expression of UCH-L1 induced the decreased microtubule-binding ability and increased phosphorylation of tau protein. Abnormal aggregation and ubiquitination of tau protein was also observed after UCH-L1 inhibition. The above results suggested that aggregation of tau protein might be devoted to the abnormal post-translational modifications of tau protein. Our study first indicates that dysfunction of UCH-L1 most likely affected normal biological function of tau protein through decreasing degradation of ubiquitinated and hyperphosphorylated tau.
Keywords: Animals; Cell Line, Tumor; Dose-Response Relationship, Drug; HEK293 Cells; Humans; Immunoprecipitation; Indoles; Mice; Microtubules; Neuroblastoma; Oximes; Protein Binding; Proteolysis; RNA, Small Interfering; tau Proteins; Ubiquitin Thiolesterase; Ubiquitination

Uncovering the Neural Bases of Cognitive and Affective Empathy Deficits in Alzheimer's Disease and the Behavioral-Variant of Frontotemporal Dementia. - Dermody, Nadene; Wong, Stephanie; Ahmed, Rebekah; Piguet, Olivier; Hodges, John R; Irish, Muireann (J Alzheimers Dis, 2016)
Loss of empathy is a core presenting feature of the behavioral-variant of frontotemporal dementia (bvFTD), resulting in socioemotional difficulties and behavioral transgressions. In contrast, interpersonal functioning remains relatively intact in Alzheimer's disease (AD), despite marked cognitive decline. The neural substrates mediating these patterns of loss and sparing in social functioning remain unclear, yet are relevant for our understanding of the social brain. We investigated cognitive versus affective aspects of empathy using the Interpersonal Reactivity Index (IRI) in 25 AD and 24 bvFTD patients and contrasted their performance with 22 age- and education-matched controls. Cognitive empathy was comparably compromised in AD and bvFTD, whereas affective empathy was impaired exclusively in bvFTD. While controlling for overall cognitive dysfunction ameliorated perspective-taking deficits in AD, empathy loss persisted across cognitive and affective domains in bvFTD. Voxel-based morphometry analyses revealed divergent neural substrates of empathy loss in each patient group. Perspective-taking deficits correlated with predominantly left-sided temporoparietal atrophy in AD, whereas widespread bilateral frontoinsular, temporal, parietal, and occipital atrophy was implicated in bvFTD. Reduced empathic concern in bvFTD was associated with atrophy in the left orbitofrontal, inferior frontal, and insular cortices, and the bilateral mid-cingulate gyrus. Our findings suggest that social cognitive deficits in AD arise largely as a consequence of global cognitive dysfunction, rather than a loss of empathy per se. In contrast, loss of empathy in bvFTD reflects the deterioration of a distributed network of frontoinsular and temporal structures that appear crucial for monitoring and processing social information.

Unmet Needs of Community-Dwelling Primary Care Patients with Dementia in Germany: Prevalence and Correlates. - Eichler, Tilly; Thyrian, Jochen René; Hertel, Johannes; Richter, Steffen; Wucherer, Diana; Michalowsky, Bernhard; Teipel, Stefan; Kilimann, Ingo; Dreier, Adina; Hoffmann, Wolfgang (J Alzheimers Dis, 2016)
BACKGROUND: To provide an optimal care for persons with dementia (PWD), their individual unmet needs have to be identified and comprehensively addressed. OBJECTIVES: Present analyses aim to describe the number and types of unmet needs of German primary care patients screened positive for dementia and factors associated with the number of unmet needs. METHODS: DelpHi-MV (Dementia: life- and person-centered help in Mecklenburg-Western Pomerania) is a general practitioner-based, cluster-randomized controlled intervention trial. Analyses are based on the baseline data of 227 PWD (≥70 years, living at home) of the intervention group who had screened positive for dementia (DemTect<9) and received a standardized computer-assisted needs assessment. RESULTS: PWD had on average 8.77±5.04 unmet needs (Range = 0-31). More than 90% of the PWD had three or more unmet needs. Unmet needs were identified across all predefined 26 subcategories. The majority of unmet needs occurred in the domains "nursing treatment and care" (38%), "social counseling and legal support" (20%), and "pharmacological treatment and care" (15%). More impairment in the activities of daily living was the only factor that was significantly associated with a higher number of unmet needs, independent of age, gender, living situation, presence of an informal caregiver, cognitive impairment, and depression. CONCLUSIONS: Present results demonstrate that community-dwelling PWD had a broad range of varying unmet needs. These findings emphasize the importance of a comprehensive needs assessment that allows the identification of individual needs as the basis for a tailored intervention- such as Dementia Care Management- that can address these needs.
Keywords: Aged, 80 and over; Caregivers; Cross-Sectional Studies; Dementia; Depression; Female; Germany; Health Services Needs and Demand; Humans; Male; Needs Assessment; Prevalence

The Utilization of Retinal Nerve Fiber Layer Thickness to Predict Cognitive Deterioration. - Shi, Zhongyong; Zhu, Yingbo; Wang, Meijuan; Wu, Yujie; Cao, Jing; Li, Chunbo; Xie, Zhongcong; Shen, Yuan (J Alzheimers Dis, 2016)
Our previous studies have shown that longitudinal reduction in retinal nerve fiber layer (RNFL) thickness is associated with cognitive deterioration. However, whether the combination of longitudinal reduction in RNFL thickness with baseline episodic memory performance can better predict cognitive deterioration remains unknown. Therefore, we set out to re-analyze the data obtained from our previous studies with 78 elderly adults (mean age 74.4 ± 3.83 years, 48.7% male) in the community over a 25-month period. The participants were categorized as either stable participants whose cognitive status did not change (n = 60) or converted participants whose cognitive status deteriorated (n = 18). A logistic regression analysis was applied to determine a conversion score for predicting the cognitive deterioration in the participants. We found that the area under the receiver operating characteristic curve (AUC) for the multivariable model was 0.854 (95% CI 0.762-0.947) using baseline story recall as a predictor, but the AUC increased to 0.915 (95% CI 0.849-0.981) with the addition of the longitudinal reduction of RNFL thickness in the inferior quadrant. The conversion score was significantly higher for the converted participants than the stable participants (0.59 ± 0.30 versus 0.12 ± 0.19, p <  0.001). Finally, the optimal cutoff value of the conversion score (0.134) was determined by the analysis of receiver operating characteristic curve, and this conversion score generated a sensitivity of 0.944 and a specificity of 0.767 in predicting the cognitive deterioration. These findings have established a system to perform a larger scale study to further test whether the longitudinal reduction in RNFL thickness could serve as a biomarker of Alzheimer's disease.
Keywords: Aged; Cognition Disorders; Female; Humans; Logistic Models; Longitudinal Studies; Male; Nerve Fibers; Neuropsychological Tests; Predictive Value of Tests; Retina; ROC Curve; Statistics, Nonparametric; Tomography, Optical Coherence

Validation of a Commercial Chemiluminescence Immunoassay for the Simultaneous Measurement of Three Different Amyloid-β Peptides in Human Cerebrospinal Fluid and Application to a Clinical Cohort. - Klafki, Hans-W; Hafermann, Henning; Bauer, Chris; Haussmann, Ute; Kraus, Inga; Schuchhardt, Johannes; Muck, Stephan; Scherbaum, Norbert; Wiltfang, Jens (J Alzheimers Dis, 2016)
A comprehensive assay validation campaign of a commercially available chemiluminescence multiplex immunoassay for the simultaneous measurement of the amyloid-β peptides Aβ38, Aβ40, and Aβ42 in human cerebrospinal fluid (CSF) is presented. The assay quality parameters we addressed included impact of sample dilution, parallelism, lower limits of detection, lower limits of quantification, intra- and inter-assay repeatability, analytical spike recoveries, and between laboratory reproducibility of the measurements. The assay performed well in our hands and fulfilled a number of predefined acceptance criteria. The CSF levels of Aβ40 and Aβ42 determined in a clinical cohort (n = 203) were statistically significantly correlated with available ELISA data of Aβ1-40 (n = 158) and Aβ1-42 (n = 179) from a different laboratory. However, Bland-Altman method comparison indicated systematic differences between the assays. The data presented here furthermore indicate that the CSF concentration of Aβ40 can surrogate total CSF Aβ and support the hypothesis that the Aβ42/Aβ40 ratio outperforms CSF Aβ42 alone as a biomarker for Alzheimer's disease due to a normalization to total Aβ levels.

Validation of the Total Cerebrovascular Disease Burden Scale in a Community Sample. - Xu, Xin; Hilal, Saima; Collinson, Simon L; Chan, Qun Lin; Yi Chong, Eddie Jun; Ikram, Mohammad Kamran; Venketasubramanian, Narayanaswamy; Cheng, Ching-Yu; Wong, Tien Yin; Chen, Christopher Li-Hsian (J Alzheimers Dis, 2016)
BACKGROUND: A total cerebrovascular disease (CeVD) burden scale was previously constructed and an inverse association of CeVD burden and cognition was found. However, the generalizability of the CeVD scale has not been examined. OBJECTIVE: The objective was to validate the previously constructed total CeVD burden scale by establishing its association with cognitive function and dementia diagnosis in a community sample. METHODS: Eligible participants were assessed on an extensive neuropsychological battery and underwent MRI scans. The total CeVD scale, comprising markers of both small- and large-vessel diseases, was derived according to previously described criteria. Association of total CeVD burden with global and domain-based cognitive performance and dementia diagnostic utility of the scale was established. RESULTS: A total of 863 participants were included in the analysis. A stepwise association of CeVD burden score with global and domain-specific cognitive function was found. Per score increase on the total CeVD burden scale was associated with 3.6 (95% CI = 2.1-6.4) times higher odds of dementia compared to dementia-free. DISCUSSION: The total CeVD burden scale is associated with cognition and dementia in a community sample. Longitudinal studies are required to establish the predictive ability of this scale.

A Validation Study of Vascular Cognitive Impairment Genetics Meta-Analysis Findings in an Independent Collaborative Cohort. - Skrobot, Olivia Anna; McKnight, Amy Jayne; Passmore, Peter Anthony; Seripa, Davide; Mecocci, Patrizia; Panza, Francesco; Kalaria, Rajesh; Wilcock, Gordon; Munafò, Marcus; Erkinjuntti, Timo; Karhunen, Pekka; Pessi, Tanja; et al. (J Alzheimers Dis, 2016)
Vascular cognitive impairment (VCI), including its severe form, vascular dementia (VaD), is the second most common form of dementia. The genetic etiology of sporadic VCI remains largely unknown. We previously conducted a systematic review and meta-analysis of all published genetic association studies of sporadic VCI prior to 6 July 2012, which demonstrated that APOE (ɛ4, ɛ2) and MTHFR (rs1801133) variants were associated with susceptibility for VCI. De novo genotyping was conducted in a new independent relatively large collaborative European cohort of VaD (nmax = 549) and elderly non-demented samples (nmax = 552). Where available, genotype data derived from Illumina's 610-quad array for 1210 GERAD1 control samples were also included in analyses of genes examined. Associations were tested using the Cochran-Armitage trend test: MTHFR rs1801133 (OR = 1.36, 95% CI 1.16-1.58, p = <0.0001), APOE rs7412 (OR = 0.62, 95% CI 0.42-0.90, p = 0.01), and APOE rs429358 (OR = 1.59, 95% CI 1.17-2.16, p = 0.003). Association was also observed with APOE epsilon alleles; ɛ4 (OR = 1.85, 95% CI 1.35-2.52, p = <0.0001) and ɛ2 (OR = 0.67, 95% CI 0.46-0.98, p = 0.03). Logistic regression and Bonferroni correction in a subgroup of the cohort adjusted for gender, age, and population maintained the association of APOE rs429358 and ɛ4 allele.

Vascular Contributions in Alzheimer's Disease-Related Neuropathological Changes: First Autopsy Evidence from a South Asian Aging Population. - Wijesinghe, Printha; Shankar, S K; Yasha, T C; Gorrie, Catherine; Amaratunga, Dhammika; Hulathduwa, Sanjayah; Kumara, K Sunil; Samarasinghe, Kamani; Suh, Yoo-Hun; Steinbusch, Harry W M; De Silva, K Ranil D (J Alzheimers Dis, 2016)
BACKGROUND: Evidence from various consortia on vascular contributions has been inconsistent in determining the etiology of sporadic Alzheimer's disease (AD). OBJECTIVE: To investigate vascular risk factors and cerebrovascular pathologies associated in manifestation of AD-related neuropathological changes of an elderly population. METHODS: Postmortem brain samples from 76 elderly subjects (≥50 years) were used to study genetic polymorphisms, intracranial atherosclerosis of the circle of Willis (IASCW), and microscopic infarcts in deep white matters. From this cohort, 50 brains (≥60 years) were subjected to neuropathological diagnosis using immunohistopathological techniques. RESULTS: Besides the association with age, the apolipoprotein E ɛ4 allele was significantly and strongly associated with Thal amyloid-β phases ≥1 [odds ratio (OR) = 6.76, 95% confidence interval (CI) 1.37-33.45] and inversely with Braak neurofibrillary tangle (NFT) stages ≥III (0.02, 0.0-0.47). Illiterates showed a significant positive association for Braak NFT stages ≥IV (14.62, 1.21-176.73) and a significant negative association for microscopic infarcts (0.15, 0.03-0.71) in deep white matters. With respect to cerebrovascular pathologies, cerebral small vessel lesions (white matter hyperintensities and cerebral amyloid angiopathy) showed a higher degree of associations among them and with AD-related neuropathological changes (p < 0.05) compared to large vessel pathology (IASCW), which showed a significant association only with Braak NFT stages ≥I (p = 0.050). CONCLUSION: These findings suggest that besides age, education, and genetic factors, other vascular risk factors were not associated with AD-related neuropathological changes and urge prompt actions be taken against cerebral small vessel diseases since evidence for effective prevention is still lacking.

Vitamin D Supplementation Appears to Increase Plasma Aβ40 in Vitamin D Insufficient Older Adults: A Pilot Randomized Controlled Trial. - Miller, Brendan J; Whisner, Corrie M; Johnston, Carol S (J Alzheimers Dis, 2016)
Low plasma amyloid-β (Aβ) is linked to Alzheimer's disease. Since vitamin D cleared brain Aβ in vitro, this 8-week trial examined whether vitamin D increased plasma Aβ40. Vitamin D insufficient adults (6/18 M/F; 64.3 ± 10.9 y) were randomized to placebo or vitamin (50,000 IU/week) treatments. The vitamin group experienced greater plasma Aβ40 change than controls, +14.9 ± 12.0 and +12.8 ± 12.8 pg/mL (p = 0.045; effect size, 0.228). Change in Aβ40 for older participants (≥60 y) was +18.3 ± 33.6 and -3.2 ± 44.5 pg/mL for vitamin (n = 4) and placebo (n = 4) groups (effect size, 0.295). Thus, vitamin D may increase plasma Aβ, particularly in older adults, suggesting decreased brain Aβ.

Within-Individual Variability: An Index for Subtle Change in Neurocognition in Mild Cognitive Impairment. - Roalf, David R; Quarmley, Megan; Mechanic-Hamilton, Dawn; Wolk, David A; Arnold, Steven E; Moberg, Paul J (J Alzheimers Dis, 2016)
BACKGROUND: The transition from mild cognitive impairment (MCI) to Alzheimer's disease is characterized by a decline in cognitive performance in many domains. Cognitive performance profiles in MCI are heterogeneous, however, and additional insights into markers of incipient dementia are needed. Typically, studies focus on average or mean performance, but ignore consistency of performance across domains. WIV (within-individual variability) provides an index of this consistency and is a potential marker of cognitive decline. OBJECTIVE: To use neurocognitive data from the Alzheimer's Disease Neuroimaging Initiative cohort to measure neurocognitive variability. METHODS: The utility of WIV was measured, in addition to global neurocognitive performance (GNP), for identifying AD and MCI. In addition, the association between changes in neurocognitive variability and diagnostic transition over 12 months was measured. RESULTS: As expected, variability was higher in AD and MCI as compared to healthy controls; GNP was lower in both groups as compared to healthy subjects. Global neurocognitive performance alone best distinguished those with dementia from healthy older adults. Yet, for individuals with MCI, including variability along with GNP improved diagnostic classification. Variability was higher at baseline in individuals transitioning from MCI to AD over a 12-month period. CONCLUSION: We conclude that variability offers complementary information about neurocognitive performance in dementia, particularly in individuals with MCI, and may provide beneficial information about disease transition.

Analysis of the Inhibitory Elements in the p5 Peptide Fragment of the CDK5 Activator, p35, CDKR1 Protein. - Binukumar, B K; Shukla, Varsha; Amin, Niranjana D; Bhaskar, Manju; Skuntz, Suzanne; Steiner, Joseph; Winkler, Dirk; Pelech, Steven L; Pant, Harish C (J Alzheimers Dis, 2015)
Besides the hallmark pathology of amyloid plaques and neurofibrillary tangles, it is well documented that cyclin-dependent kinase 5 (CDK5), a critical neuronal protein kinase in nervous system development, function, and survival, when deregulated and hyperactivated induces Alzheimer's disease (AD) and amyotrophic lateral sclerosis and Parkinson's disease-like phenotypes in mice. In a recent study, we demonstrated that p5, a small, truncated fragment of 24 amino acid residues derived from the CDK5 activator protein 35 (NCK5A, p35), selectively inhibited deregulated CDK5 hyperactivity and ameliorated AD phenotypes in model mice. In this study, we identified the most inhibitory elements in the p5 peptide fragment. Each amino acid residue in p5 was systematically replaced with its homologous residues that may still be able to functionally substitute. The effects of these p5 peptide analogs were studied on the phosphotransferase activities of CDK5/p35, CDK5/p25, ERK1, and GSK3β. The mimetic p5 peptide (A/V substitution at the C-terminus of the peptide) in the sequence, KNAFYERALSIINLMTSKMVQINV (p5-MT) was the most effective inhibitor of CDK5 kinase activity of 79 tested mimetic peptides including the original p5 peptide, KEAFWDRCLSVINLMSSKMLQINA (p5-WT). Replacement of the residues in C-terminus end of the peptide affected CDK5 phosphotransferase activity most significantly. These peptides were strong inhibitors of CDK5, but not the related proline-directed kinases, ERK1 and GSK3β.

Ankle-Brachial Index but Neither Intima Media Thickness Nor Coronary Artery Calcification is Associated With Mild Cognitive Impairment. - Weimar, Christian; Winkler, Angela; Dlugaj, Martha; Lehmann, Nils; Hennig, Frauke; Bauer, Marcus; Kröger, Knut; Kälsch, Hagen; Mahabadi, Amir-Abass; Dragano, Nico; Moebus, Susanne; Hoffmann, Barbara; et al. (J Alzheimers Dis, 2015)
BACKGROUND: Several studies have reported an association of atherosclerosis with mild cognitive impairment (MCI) and dementia independent of cardiovascular risk factors. OBJECTIVE: To compare the cross-sectional association of the ankle-brachial index (ABI), intima media thickness (IMT), and coronary artery calcification (CAC) with MCI and its subtypes, amnestic MCI (aMCI) and non-amnestic MCI (naMCI) in the population-based Heinz Nixdorf Recall cohort study. METHODS: 4,086 participants performed a validated brief cognitive assessment at the first follow-up examination (2006-2008). MCI was diagnosed according to previously published criteria. Prevalence ratio (PR) regression models adjusted for age, gender, education, cardiovascular risk factors, and APOE genotype were used to compare the association of the ABI, the CAC-Agatston score and the IMT with MCI and its subtypes. RESULTS: We identified 490 participants with MCI (mean age 66.1 ± 7.8, 46.9 % male, aMCI n = 249, naMCI n = 241) and 1,242 cognitively normal participants. A decreasing ABI (per 0.1) was significantly associated with a higher MCI prevalence in fully adjusted models (PR 1.06; 95% confidence interval (CI) 1.01-1.11), whereas an increasing CAC (log(CAC+1)) or IMT (per 0.1 mm) were not associated after adjustment. A decreasing ABI was also significantly associated with naMCI in fully adjusted models (PR 1.12; CI 1.03-1.21) but not with aMCI. CONCLUSIONS: Our data show that the degree of generalized atherosclerosis as measured by the ABI is associated with MCI and with naMCI in a population-based cohort.

Diabetes is Associated with Worse Executive Function in Both Eastern and Western Populations: Shanghai Aging Study and Mayo Clinic Study of Aging. - Zhao, Qianhua; Roberts, Rosebud O; Ding, Ding; Cha, Ruth; Guo, Qihao; Meng, Haijiao; Luo, Jianfeng; Machulda, Mary M; Shane Pankratz, V; Wang, Bei; Christianson, Teresa J H; Aakre, Jeremiah A; et al. (J Alzheimers Dis, 2015)
BACKGROUND AND OBJECTIVES: It remains unknown whether the association between diabetes mellitus (DM) and cognitive function differs in Eastern and Western populations. This study aimed to elucidate whether DM is associated with worse cognitive performance in both populations. METHODS: The Shanghai Aging Study (SAS) and the Mayo Clinic Study of Aging (MCSA) are two population-based studies with similar design and methodology in Shanghai, China and Rochester, MN, USA. Non-demented participants underwent cognitive testing, and DM was assessed from the medical record. Separate analyses were performed in SAS and MCSA regarding the association between DM and cognitive performance. RESULTS: A total of 3,348 Chinese participants in the SAS and 3,734 American subjects in the MCSA were included. Compared with MCSA subjects, SAS participants were younger, less educated, and had lower frequency of vascular disease, APOE ɛ4 carriers and obesity. Participants with DM (compared to non-DM participants) performed significantly worse on all the cognitive domains in both the SAS and MCSA. After adjustment for age, gender, education, and vascular covariates, DM was associated with worse performance in executive function (β=-0.15, p = 0.001 for SAS, and β=-0.10, p = 0.008 for MCSA) in the total sample and in the cognitively normal sub-sample. Furthermore, DM was associated with poor performance in visuospatial skills, language, and memory in the SAS, but not in the MCSA. CONCLUSIONS: Diabetes is associated with cognitive dysfunction and, in particular, exerts a negative impact on executive function regardless of race, age, and prevalence of vascular risk factors.

The Multi-Target Drug M30 Shows Pro-Cognitive and Anti-Inflammatory Effects in a Rat Model of Alzheimer's Disease. - Pimentel, Luisa S; Allard, Simon; Do Carmo, Sonia; Weinreb, Orly; Danik, Marc; Hanzel, Cecilia E; Youdim, Moussa B; Cuello, A Claudio (J Alzheimers Dis, 2015)
Current therapies for Alzheimer's disease (AD) offer partial symptomatic relief and do not modify disease progression. There is substantial evidence indicating a disease onset years before clinical diagnosis, at which point no effective therapy has been found. In this study, we investigated the efficacy of a new multi-target drug, M30, at relatively early stages of the AD-like amyloid pathology in a robust rat transgenic model. McGill-R-Thy1-APP transgenic rats develop the full AD-like amyloid pathology in a progressive fashion, and have a minimal genetic burden. McGill rats were given 5 mg/kg M30 or vehicle per os, every 2 days for 4 months, starting at a stage where the transgenic animals suffer detectable cognitive impairments. At the completion of the treatment, cognitive functions were assessed with Novel Object Location and Novel Object Recognition tests. The brains were then analyzed to assess amyloid-β (Aβ) burden and the levels of key inflammatory markers. Long-term treatment with M30 was associated with both the prevention and the reversal of transgene-related cognitive decline. The effects on cognition were accompanied by a shift of the Aβ-immunoreactive material toward an amyloid plaque aggregated molecular form, diminished molecular signs of CNS inflammation and a change in microglia morphology toward a surveying phenotype. This study is the first to demonstrate the therapeutic potential of M30 in a rat model of the AD amyloid pathology. It provides a rationale for further investigations with M30 and with potential multi-target approaches to delay, prevent or reverse the progression the AD pathology at early disease-stages.

Tracking Discourse Complexity Preceding Alzheimer's Disease Diagnosis: A Case Study Comparing the Press Conferences of Presidents Ronald Reagan and George Herbert Walker Bush. - Berisha, Visar; Wang, Shuai; LaCross, Amy; Liss, Julie (J Alzheimers Dis, 2015)
Changes in some lexical features of language have been associated with the onset and progression of Alzheimer's disease. Here we describe a method to extract key features from discourse transcripts, which we evaluated on non-scripted news conferences from President Ronald Reagan, who was diagnosed with Alzheimer's disease in 1994, and President George Herbert Walker Bush, who has no known diagnosis of Alzheimer's disease. Key word counts previously associated with cognitive decline in Alzheimer's disease were extracted and regression analyses were conducted. President Reagan showed a significant reduction in the number of unique words over time and a significant increase in conversational fillers and non-specific nouns over time. There was no significant trend in these features for President Bush.

C9orf72 nucleotide repeat structures initiate molecular cascades of disease. - Haeusler, Aaron R; Donnelly, Christopher J; Periz, Goran; Simko, Eric A J; Shaw, Patrick G; Kim, Min-Sik; Maragakis, Nicholas J; Troncoso, Juan C; Pandey, Akhilesh; Sattler, Rita; Rothstein, Jeffrey D; Wang, Jiou (Nature, 2014)
A hexanucleotide repeat expansion (HRE), (GGGGCC)n, in C9orf72 is the most common genetic cause of the neurodegenerative diseases amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Here we identify a molecular mechanism by which structural polymorphism of the HRE leads to ALS/FTD pathology and defects. The HRE forms DNA and RNA G-quadruplexes with distinct structures and promotes RNA•DNA hybrids (R-loops). The structural polymorphism causes a repeat-length-dependent accumulation of transcripts aborted in the HRE region. These transcribed repeats bind to ribonucleoproteins in a conformation-dependent manner. Specifically, nucleolin, an essential nucleolar protein, preferentially binds the HRE G-quadruplex, and patient cells show evidence of nucleolar stress. Our results demonstrate that distinct C9orf72 HRE structural polymorphism at both DNA and RNA levels initiates molecular cascades leading to ALS/FTD pathologies, and provide the basis for a mechanistic model for repeat-associated neurodegenerative diseases.
Keywords: Amyotrophic Lateral Sclerosis; B-Lymphocytes; Base Sequence; Cell Nucleolus; DNA; DNA Repeat Expansion; Frontotemporal Dementia; G-Quadruplexes; HEK293 Cells; Humans; Models, Molecular; Neurons; Open Reading Frames; Phosphoproteins; Ribonucleoproteins; RNA; RNA-Binding Proteins; Stress, Physiological; Transcription, Genetic

Ten-year effects of the advanced cognitive training for independent and vital elderly cognitive training trial on cognition and everyday functioning in older adults. - Rebok, George W; Ball, Karlene; Guey, Lin T; Jones, Richard N; Kim, Hae-Young; King, Jonathan W; Marsiske, Michael; Morris, John N; Tennstedt, Sharon L; Unverzagt, Frederick W; Willis, Sherry L (J Am Geriatr Soc, 2014)
OBJECTIVES: To determine the effects of cognitive training on cognitive abilities and everyday function over 10 years. DESIGN: Ten-year follow-up of a randomized, controlled single-blind trial (Advanced Cognitive Training for Independent and Vital Elderly (ACTIVE)) with three intervention groups and a no-contact control group. SETTING: Six U.S. cities. PARTICIPANTS: A volunteer sample of 2,832 persons (mean baseline age 73.6; 26% African American) living independently. INTERVENTION: Ten training sessions for memory, reasoning, or speed of processing; four sessions of booster training 11 and 35 months after initial training. MEASUREMENTS: Objectively measured cognitive abilities and self-reported and performance-based measures of everyday function. RESULTS: Participants in each intervention group reported less difficulty with instrumental activities of daily living (IADLs) (memory: effect size = 0.48, 99% confidence interval (CI) = 0.12-0.84; reasoning: effect size = 0.38, 99% CI = 0.02-0.74; speed of processing: effect size = 0.36, 99% CI = 0.01-0.72). At a mean age of 82, approximately 60% of trained participants, versus 50% of controls (P < .05), were at or above their baseline level of self-reported IADL function at 10 years. The reasoning and speed-of-processing interventions maintained their effects on their targeted cognitive abilities at 10 years (reasoning: effect size = 0.23, 99% CI = 0.09-0.38; speed of processing: effect size = 0.66, 99% CI = 0.43-0.88). Memory training effects were no longer maintained for memory performance. Booster training produced additional and durable improvement for the reasoning intervention for reasoning performance (effect size = 0.21, 99% CI = 0.01-0.41) and the speed-of-processing intervention for speed-of-processing performance (effect size = 0.62, 99% CI = 0.31-0.93). CONCLUSION: Each Advanced Cognitive Training for Independent and Vital Elderly cognitive intervention resulted in less decline in self-reported IADL compared with the control group. Reasoning and speed, but not memory, training resulted in improved targeted cognitive abilities for 10 years.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Cognition Disorders; Cognitive Therapy; Female; Follow-Up Studies; Humans; Independent Living; Male; Memory Disorders; Mental Processes; Single-Blind Method; United States

A three-dimensional human neural cell culture model of Alzheimer's disease. - Choi, Se Hoon; Kim, Young Hye; Hebisch, Matthias; Sliwinski, Christopher; Lee, Seungkyu; D'Avanzo, Carla; Chen, Hechao; Hooli, Basavaraj; Asselin, Caroline; Muffat, Julien; Klee, Justin B; Zhang, Can; et al. (Nature, 2014)
Alzheimer's disease is the most common form of dementia, characterized by two pathological hallmarks: amyloid-β plaques and neurofibrillary tangles. The amyloid hypothesis of Alzheimer's disease posits that the excessive accumulation of amyloid-β peptide leads to neurofibrillary tangles composed of aggregated hyperphosphorylated tau. However, to date, no single disease model has serially linked these two pathological events using human neuronal cells. Mouse models with familial Alzheimer's disease (FAD) mutations exhibit amyloid-β-induced synaptic and memory deficits but they do not fully recapitulate other key pathological events of Alzheimer's disease, including distinct neurofibrillary tangle pathology. Human neurons derived from Alzheimer's disease patients have shown elevated levels of toxic amyloid-β species and phosphorylated tau but did not demonstrate amyloid-β plaques or neurofibrillary tangles. Here we report that FAD mutations in β-amyloid precursor protein and presenilin 1 are able to induce robust extracellular deposition of amyloid-β, including amyloid-β plaques, in a human neural stem-cell-derived three-dimensional (3D) culture system. More importantly, the 3D-differentiated neuronal cells expressing FAD mutations exhibited high levels of detergent-resistant, silver-positive aggregates of phosphorylated tau in the soma and neurites, as well as filamentous tau, as detected by immunoelectron microscopy. Inhibition of amyloid-β generation with β- or γ-secretase inhibitors not only decreased amyloid-β pathology, but also attenuated tauopathy. We also found that glycogen synthase kinase 3 (GSK3) regulated amyloid-β-mediated tau phosphorylation. We have successfully recapitulated amyloid-β and tau pathology in a single 3D human neural cell culture system. Our unique strategy for recapitulating Alzheimer's disease pathology in a 3D neural cell culture model should also serve to facilitate the development of more precise human neural cell models of other neurodegenerative disorders.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cell Culture Techniques; Cell Differentiation; Drug Evaluation, Preclinical; Extracellular Space; Glycogen Synthase Kinase 3; Humans; Microtubule-Associated Proteins; Models, Biological; Neural Stem Cells; Neurites; Phosphorylation; Presenilin-1; Protein Aggregation, Pathological; Reproducibility of Results; tau Proteins

Two phase 3 trials of bapineuzumab in mild-to-moderate Alzheimer's disease. - Salloway, Stephen; Sperling, Reisa; Fox, Nick C; Blennow, Kaj; Klunk, William; Raskind, Murray; Sabbagh, Marwan; Honig, Lawrence S; Porsteinsson, Anton P; Ferris, Steven; Reichert, Marcel; Ketter, Nzeera; et al. (N Engl J Med, 2014)
BACKGROUND: Bapineuzumab, a humanized anti-amyloid-beta monoclonal antibody, is in clinical development for the treatment of Alzheimer's disease. METHODS: We conducted two double-blind, randomized, placebo-controlled, phase 3 trials involving patients with mild-to-moderate Alzheimer's disease--one involving 1121 carriers of the apolipoprotein E (APOE) ε4 allele and the other involving 1331 noncarriers. Bapineuzumab or placebo, with doses varying by study, was administered by intravenous infusion every 13 weeks for 78 weeks. The primary outcome measures were scores on the 11-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog11, with scores ranging from 0 to 70 and higher scores indicating greater impairment) and the Disability Assessment for Dementia (DAD, with scores ranging from 0 to 100 and higher scores indicating less impairment). A total of 1090 carriers and 1114 noncarriers were included in the efficacy analysis. Secondary outcome measures included findings on positron-emission tomographic amyloid imaging with the use of Pittsburgh compound B (PIB-PET) and cerebrospinal fluid phosphorylated tau (phospho-tau) concentrations. RESULTS: There were no significant between-group differences in the primary outcomes. At week 78, the between-group differences in the change from baseline in the ADAS-cog11 and DAD scores (bapineuzumab group minus placebo group) were -0.2 (P=0.80) and -1.2 (P=0.34), respectively, in the carrier study; the corresponding differences in the noncarrier study were -0.3 (P=0.64) and 2.8 (P=0.07) with the 0.5-mg-per-kilogram dose of bapineuzumab and 0.4 (P=0.62) and 0.9 (P=0.55) with the 1.0-mg-per-kilogram dose. The major safety finding was amyloid-related imaging abnormalities with edema among patients receiving bapineuzumab, which increased with bapineuzumab dose and APOE ε4 allele number and which led to discontinuation of the 2.0-mg-per-kilogram dose. Between-group differences were observed with respect to PIB-PET and cerebrospinal fluid phospho-tau concentrations in APOE ε4 allele carriers but not in noncarriers. CONCLUSIONS: Bapineuzumab did not improve clinical outcomes in patients with Alzheimer's disease, despite treatment differences in biomarkers observed in APOE ε4 carriers. (Funded by Janssen Alzheimer Immunotherapy and Pfizer; Bapineuzumab 301 and 302 ClinicalTrials.gov numbers, NCT00575055 and NCT00574132, and EudraCT number, 2009-012748-17.).
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Antibodies, Monoclonal, Humanized; Apolipoproteins E; Biomarkers; Brain; Cognition; Double-Blind Method; Edema; Female; Humans; Intention to Treat Analysis; Male; Middle Aged; Neuropsychological Tests; Phosphorylation; Positron-Emission Tomography; Severity of Illness Index; tau Proteins; Treatment Failure

Young blood reverses age-related impairments in cognitive function and synaptic plasticity in mice. - Villeda, Saul A; Plambeck, Kristopher E; Middeldorp, Jinte; Castellano, Joseph M; Mosher, Kira I; Luo, Jian; Smith, Lucas K; Bieri, Gregor; Lin, Karin; Berdnik, Daniela; Wabl, Rafael; Udeochu, Joe; et al. (Nat Med, 2014)
As human lifespan increases, a greater fraction of the population is suffering from age-related cognitive impairments, making it important to elucidate a means to combat the effects of aging. Here we report that exposure of an aged animal to young blood can counteract and reverse pre-existing effects of brain aging at the molecular, structural, functional and cognitive level. Genome-wide microarray analysis of heterochronic parabionts--in which circulatory systems of young and aged animals are connected--identified synaptic plasticity-related transcriptional changes in the hippocampus of aged mice. Dendritic spine density of mature neurons increased and synaptic plasticity improved in the hippocampus of aged heterochronic parabionts. At the cognitive level, systemic administration of young blood plasma into aged mice improved age-related cognitive impairments in both contextual fear conditioning and spatial learning and memory. Structural and cognitive enhancements elicited by exposure to young blood are mediated, in part, by activation of the cyclic AMP response element binding protein (Creb) in the aged hippocampus. Our data indicate that exposure of aged mice to young blood late in life is capable of rejuvenating synaptic plasticity and improving cognitive function.
Keywords: Age Factors; Aging; Animals; Blood Transfusion; Blotting, Western; Cell Line; Cognition Disorders; Cyclic AMP Response Element-Binding Protein; DNA Primers; Hippocampus; Immunohistochemistry; Mice; Mice, Inbred C57BL; Microarray Analysis; Neuronal Plasticity; Parabiosis; Polymerase Chain Reaction

Integrated systems approach identifies genetic nodes and networks in late-onset Alzheimer's disease. - Zhang, Bin; Gaiteri, Chris; Bodea, Liviu-Gabriel; Wang, Zhi; McElwee, Joshua; Podtelezhnikov, Alexei A; Zhang, Chunsheng; Xie, Tao; Tran, Linh; Dobrin, Radu; Fluder, Eugene; Clurman, Bruce; et al. (Cell, 2013)
The genetics of complex disease produce alterations in the molecular interactions of cellular pathways whose collective effect may become clear through the organized structure of molecular networks. To characterize molecular systems associated with late-onset Alzheimer's disease (LOAD), we constructed gene-regulatory networks in 1,647 postmortem brain tissues from LOAD patients and nondemented subjects, and we demonstrate that LOAD reconfigures specific portions of the molecular interaction structure. Through an integrative network-based approach, we rank-ordered these network structures for relevance to LOAD pathology, highlighting an immune- and microglia-specific module that is dominated by genes involved in pathogen phagocytosis, contains TYROBP as a key regulator, and is upregulated in LOAD. Mouse microglia cells overexpressing intact or truncated TYROBP revealed expression changes that significantly overlapped the human brain TYROBP network. Thus the causal network structure is a useful predictor of response to gene perturbations and presents a framework to test models of disease mechanisms underlying LOAD.
Keywords: Adaptor Proteins, Signal Transducing; Alzheimer Disease; Animals; Bayes Theorem; Brain; Gene Regulatory Networks; Humans; Membrane Proteins; Mice; Microglia

Meta-analysis of 74,046 individuals identifies 11 new susceptibility loci for Alzheimer's disease. - Lambert, J C; Ibrahim-Verbaas, C A; Harold, D; Naj, A C; Sims, R; Bellenguez, C; DeStafano, A L; Bis, J C; Beecham, G W; Grenier-Boley, B; Russo, G; Thorton-Wells, T A; et al. (Nat Genet, 2013)
Eleven susceptibility loci for late-onset Alzheimer's disease (LOAD) were identified by previous studies; however, a large portion of the genetic risk for this disease remains unexplained. We conducted a large, two-stage meta-analysis of genome-wide association studies (GWAS) in individuals of European ancestry. In stage 1, we used genotyped and imputed data (7,055,881 SNPs) to perform meta-analysis on 4 previously published GWAS data sets consisting of 17,008 Alzheimer's disease cases and 37,154 controls. In stage 2, 11,632 SNPs were genotyped and tested for association in an independent set of 8,572 Alzheimer's disease cases and 11,312 controls. In addition to the APOE locus (encoding apolipoprotein E), 19 loci reached genome-wide significance (P < 5 × 10(-8)) in the combined stage 1 and stage 2 analysis, of which 11 are newly associated with Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cohort Studies; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Modeling Alzheimer's disease with iPSCs reveals stress phenotypes associated with intracellular Aβ and differential drug responsiveness. - Kondo, Takayuki; Asai, Masashi; Tsukita, Kayoko; Kutoku, Yumiko; Ohsawa, Yutaka; Sunada, Yoshihide; Imamura, Keiko; Egawa, Naohiro; Yahata, Naoki; Okita, Keisuke; Takahashi, Kazutoshi; Asaka, Isao; et al. (Cell Stem Cell, 2013)
Oligomeric forms of amyloid-β peptide (Aβ) are thought to play a pivotal role in the pathogenesis of Alzheimer's disease (AD), but the mechanism involved is still unclear. Here, we generated induced pluripotent stem cells (iPSCs) from familial and sporadic AD patients and differentiated them into neural cells. Aβ oligomers accumulated in iPSC-derived neurons and astrocytes in cells from patients with a familial amyloid precursor protein (APP)-E693Δ mutation and sporadic AD, leading to endoplasmic reticulum (ER) and oxidative stress. The accumulated Aβ oligomers were not proteolytically resistant, and docosahexaenoic acid (DHA) treatment alleviated the stress responses in the AD neural cells. Differential manifestation of ER stress and DHA responsiveness may help explain variable clinical results obtained with the use of DHA treatment and suggests that DHA may in fact be effective for a subset of patients. It also illustrates how patient-specific iPSCs can be useful for analyzing AD pathogenesis and evaluating drugs.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cell Differentiation; Cerebral Cortex; Docosahexaenoic Acids; Humans; Induced Pluripotent Stem Cells; Intracellular Space; Models, Biological; Mutant Proteins; Neurons; Oxidative Stress; Phenotype; Protein Structure, Quaternary

Tracking pathophysiological processes in Alzheimer's disease: an updated hypothetical model of dynamic biomarkers. - Jack, Clifford R; Knopman, David S; Jagust, William J; Petersen, Ronald C; Weiner, Michael W; Aisen, Paul S; Shaw, Leslie M; Vemuri, Prashanthi; Wiste, Heather J; Weigand, Stephen D; Lesnick, Timothy G; Pankratz, Vernon S; et al. (Lancet Neurol, 2013)
In 2010, we put forward a hypothetical model of the major biomarkers of Alzheimer's disease (AD). The model was received with interest because we described the temporal evolution of AD biomarkers in relation to each other and to the onset and progression of clinical symptoms. Since then, evidence has accumulated that supports the major assumptions of this model. Evidence has also appeared that challenges some of our assumptions, which has allowed us to modify our original model. Refinements to our model include indexing of individuals by time rather than clinical symptom severity; incorporation of interindividual variability in cognitive impairment associated with progression of AD pathophysiology; modifications of the specific temporal ordering of some biomarkers; and recognition that the two major proteinopathies underlying AD biomarker changes, amyloid β (Aβ) and tau, might be initiated independently in sporadic AD, in which we hypothesise that an incident Aβ pathophysiology can accelerate antecedent limbic and brainstem tauopathy.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognition Disorders; Humans; Models, Biological; Nonlinear Dynamics; tau Proteins

TREM2 variants in Alzheimer's disease. - Guerreiro, Rita; Wojtas, Aleksandra; Bras, Jose; Carrasquillo, Minerva; Rogaeva, Ekaterina; Majounie, Elisa; Cruchaga, Carlos; Sassi, Celeste; Kauwe, John S K; Younkin, Steven; Hazrati, Lilinaz; Collinge, John; et al. (N Engl J Med, 2013)
BACKGROUND: Homozygous loss-of-function mutations in TREM2, encoding the triggering receptor expressed on myeloid cells 2 protein, have previously been associated with an autosomal recessive form of early-onset dementia. METHODS: We used genome, exome, and Sanger sequencing to analyze the genetic variability in TREM2 in a series of 1092 patients with Alzheimer's disease and 1107 controls (the discovery set). We then performed a meta-analysis on imputed data for the TREM2 variant rs75932628 (predicted to cause a R47H substitution) from three genomewide association studies of Alzheimer's disease and tested for the association of the variant with disease. We genotyped the R47H variant in an additional 1887 cases and 4061 controls. We then assayed the expression of TREM2 across different regions of the human brain and identified genes that are differentially expressed in a mouse model of Alzheimer's disease and in control mice. RESULTS: We found significantly more variants in exon 2 of TREM2 in patients with Alzheimer's disease than in controls in the discovery set (P=0.02). There were 22 variant alleles in 1092 patients with Alzheimer's disease and 5 variant alleles in 1107 controls (P<0.001). The most commonly associated variant, rs75932628 (encoding R47H), showed highly significant association with Alzheimer's disease (P<0.001). Meta-analysis of rs75932628 genotypes imputed from genomewide association studies confirmed this association (P=0.002), as did direct genotyping of an additional series of 1887 patients with Alzheimer's disease and 4061 controls (P<0.001). Trem2 expression differed between control mice and a mouse model of Alzheimer's disease. CONCLUSIONS: Heterozygous rare variants in TREM2 are associated with a significant increase in the risk of Alzheimer's disease. (Funded by Alzheimer's Research UK and others.).
Keywords: Aged; Alzheimer Disease; Animals; Brain; Exome; Genetic Variation; Genome-Wide Association Study; Genotype; Genotyping Techniques; Heterozygote; Humans; Membrane Glycoproteins; Mice; Mice, Inbred A; Mutation; Receptors, Immunologic; Risk Factors; RNA, Messenger; Sequence Analysis, DNA

Cerebrospinal fluid levels of β-amyloid 1-42, but not of tau, are fully changed already 5 to 10 years before the onset of Alzheimer dementia. - Buchhave, Peder; Minthon, Lennart; Zetterberg, Henrik; Wallin, Asa K; Blennow, Kaj; Hansson, Oskar (Arch Gen Psychiatry, 2012)
CONTEXT: Early detection of prodromal Alzheimer disease (AD) is important because new disease-modifying therapies are most likely to be effective when initiated during the early stages of disease. OBJECTIVES: To assess the ability of the cerebrospinal fluid (CSF) biomarkers total tau (T-tau), phosphorylated tau (P-tau), and β-amyloid 1-42 (Aβ42) to predict future development of AD dementia within 9.2 years in patients with mild cognitive impairment (MCI) and to compare CSF biomarkers between early and late converters to AD. DESIGN: A clinical study with a median follow-up of 9.2 years (range, 4.1-11.8 years). SETTING: Memory disorder clinic. Patients A total of 137 patients with MCI who underwent lumbar puncture at baseline. MAIN OUTCOME MEASURE Conversion to AD dementia. RESULTS: During follow-up, 72 patients (53.7%) developed AD and 21 (15.7%) progressed to other forms of dementia. At baseline, CSF Aβ42 levels were reduced and T-tau and P-tau levels were elevated in patients who converted to AD during follow-up compared with nonconverters (P < .001). Baseline CSF Aβ42 levels were equally reduced in patients with MCI who converted to AD within 0 to 5 years (early converters) compared with those who converted between 5 and 10 years (late converters). However, CSF T-tau and P-tau levels were significantly higher in early converters vs late converters. A baseline Aβ42:P-tau ratio predicted the development of AD within 9.2 years with a sensitivity of 88%, specificity of 90%, positive predictive value of 91%, and negative predictive value of 86%. CONCLUSIONS: Approximately 90% of patients with MCI and pathologic CSF biomarker levels at baseline develop AD within 9 to 10 years. Levels of Aβ42 are already fully decreased at least 5 to 10 years before conversion to AD dementia, whereas T-tau and P-tau seem to be later markers. These results provide direct support in humans for the hypothesis that altered Aβ metabolism precedes tau-related pathology and neuronal degeneration.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Female; Follow-Up Studies; Humans; Male; Mild Cognitive Impairment; Peptide Fragments; Predictive Value of Tests; tau Proteins; Time Factors

Demonstrated brain insulin resistance in Alzheimer's disease patients is associated with IGF-1 resistance, IRS-1 dysregulation, and cognitive decline. - Talbot, Konrad; Wang, Hoau-Yan; Kazi, Hala; Han, Li-Ying; Bakshi, Kalindi P; Stucky, Andres; Fuino, Robert L; Kawaguchi, Krista R; Samoyedny, Andrew J; Wilson, Robert S; Arvanitakis, Zoe; Schneider, Julie A; et al. (J Clin Invest, 2012)
While a potential causal factor in Alzheimer's disease (AD), brain insulin resistance has not been demonstrated directly in that disorder. We provide such a demonstration here by showing that the hippocampal formation (HF) and, to a lesser degree, the cerebellar cortex in AD cases without diabetes exhibit markedly reduced responses to insulin signaling in the IR→IRS-1→PI3K signaling pathway with greatly reduced responses to IGF-1 in the IGF-1R→IRS-2→PI3K signaling pathway. Reduced insulin responses were maximal at the level of IRS-1 and were consistently associated with basal elevations in IRS-1 phosphorylated at serine 616 (IRS-1 pS⁶¹⁶) and IRS-1 pS⁶³⁶/⁶³⁹. In the HF, these candidate biomarkers of brain insulin resistance increased commonly and progressively from normal cases to mild cognitively impaired cases to AD cases regardless of diabetes or APOE ε4 status. Levels of IRS-1 pS⁶¹⁶ and IRS-1 pS⁶³⁶/⁶³⁹ and their activated kinases correlated positively with those of oligomeric Aβ plaques and were negatively associated with episodic and working memory, even after adjusting for Aβ plaques, neurofibrillary tangles, and APOE ε4. Brain insulin resistance thus appears to be an early and common feature of AD, a phenomenon accompanied by IGF-1 resistance and closely associated with IRS-1 dysfunction potentially triggered by Aβ oligomers and yet promoting cognitive decline independent of classic AD pathology.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Brain; Cerebellar Cortex; Cognition Disorders; Diabetes Complications; Drug Resistance; Female; Glucose; Hippocampus; Humans; Insulin; Insulin Receptor Substrate Proteins; Insulin Resistance; Insulin-Like Growth Factor I; Male; Middle Aged; Phosphorylation; Phosphoserine; Protein Processing, Post-Translational; Recombinant Proteins; Signal Transduction

An epigenetic blockade of cognitive functions in the neurodegenerating brain. - Gräff, Johannes; Rei, Damien; Guan, Ji-Song; Wang, Wen-Yuan; Seo, Jinsoo; Hennig, Krista M; Nieland, Thomas J F; Fass, Daniel M; Kao, Patricia F; Kahn, Martin; Su, Susan C; Samiei, Alireza; et al. (Nature, 2012)
Cognitive decline is a debilitating feature of most neurodegenerative diseases of the central nervous system, including Alzheimer's disease. The causes leading to such impairment are only poorly understood and effective treatments are slow to emerge. Here we show that cognitive capacities in the neurodegenerating brain are constrained by an epigenetic blockade of gene transcription that is potentially reversible. This blockade is mediated by histone deacetylase 2, which is increased by Alzheimer's-disease-related neurotoxic insults in vitro, in two mouse models of neurodegeneration and in patients with Alzheimer's disease. Histone deacetylase 2 associates with and reduces the histone acetylation of genes important for learning and memory, which show a concomitant decrease in expression. Importantly, reversing the build-up of histone deacetylase 2 by short-hairpin-RNA-mediated knockdown unlocks the repression of these genes, reinstates structural and synaptic plasticity, and abolishes neurodegeneration-associated memory impairments. These findings advocate for the development of selective inhibitors of histone deacetylase 2 and suggest that cognitive capacities following neurodegeneration are not entirely lost, but merely impaired by this epigenetic blockade.
Keywords: Acetylation; Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Disease Models, Animal; Epigenesis, Genetic; Gene Expression Regulation; Gene Knockdown Techniques; Hippocampus; Histone Deacetylase 2; Histones; Humans; Hydrogen Peroxide; Memory Disorders; Mice; Neurodegenerative Diseases; Neuronal Plasticity; Peptide Fragments; Phosphorylation; Promoter Regions, Genetic; Receptors, Glucocorticoid; RNA Polymerase II

A mutation in APP protects against Alzheimer's disease and age-related cognitive decline. - Jonsson, Thorlakur; Atwal, Jasvinder K; Steinberg, Stacy; Snaedal, Jon; Jonsson, Palmi V; Bjornsson, Sigurbjorn; Stefansson, Hreinn; Sulem, Patrick; Gudbjartsson, Daniel; Maloney, Janice; Hoyte, Kwame; Gustafson, Amy; et al. (Nature, 2012)
The prevalence of dementia in the Western world in people over the age of 60 has been estimated to be greater than 5%, about two-thirds of which are due to Alzheimer's disease. The age-specific prevalence of Alzheimer's disease nearly doubles every 5 years after age 65, leading to a prevalence of greater than 25% in those over the age of 90 (ref. 3). Here, to search for low-frequency variants in the amyloid-β precursor protein (APP) gene with a significant effect on the risk of Alzheimer's disease, we studied coding variants in APP in a set of whole-genome sequence data from 1,795 Icelanders. We found a coding mutation (A673T) in the APP gene that protects against Alzheimer's disease and cognitive decline in the elderly without Alzheimer's disease. This substitution is adjacent to the aspartyl protease β-site in APP, and results in an approximately 40% reduction in the formation of amyloidogenic peptides in vitro. The strong protective effect of the A673T substitution against Alzheimer's disease provides proof of principle for the hypothesis that reducing the β-cleavage of APP may protect against the disease. Furthermore, as the A673T allele also protects against cognitive decline in the elderly without Alzheimer's disease, the two may be mediated through the same or similar mechanisms.
Keywords: Aging; Alleles; Alzheimer Disease; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Aspartic Acid Endopeptidases; Cognition; Cognition Disorders; Genetic Predisposition to Disease; HEK293 Cells; Humans; Mutation; Plaque, Amyloid

An operational approach to National Institute on Aging-Alzheimer's Association criteria for preclinical Alzheimer disease. - Jack, Clifford R; Knopman, David S; Weigand, Stephen D; Wiste, Heather J; Vemuri, Prashanthi; Lowe, Val; Kantarci, Kejal; Gunter, Jeffrey L; Senjem, Matthew L; Ivnik, Robert J; Roberts, Rosebud O; Rocca, Walter A; et al. (Ann Neurol, 2012)
OBJECTIVE: A workgroup commissioned by the Alzheimer's Association (AA) and the National Institute on Aging (NIA) recently published research criteria for preclinical Alzheimer disease (AD). We performed a preliminary assessment of these guidelines. METHODS: We employed Pittsburgh compound B positron emission tomography (PET) imaging as our biomarker of cerebral amyloidosis, and (18) fluorodeoxyglucose PET imaging and hippocampal volume as biomarkers of neurodegeneration. A group of 42 clinically diagnosed AD subjects was used to create imaging biomarker cutpoints. A group of 450 cognitively normal (CN) subjects from a population-based sample was used to develop cognitive cutpoints and to assess population frequencies of the different preclinical AD stages using different cutpoint criteria. RESULTS: The new criteria subdivide the preclinical phase of AD into stages 1 to 3. To classify our CN subjects, 2 additional categories were needed. Stage 0 denotes subjects with normal AD biomarkers and no evidence of subtle cognitive impairment. Suspected non-AD pathophysiology (SNAP) denotes subjects with normal amyloid PET imaging, but abnormal neurodegeneration biomarker studies. At fixed cutpoints corresponding to 90% sensitivity for diagnosing AD and the 10th percentile of CN cognitive scores, 43% of our sample was classified as stage 0, 16% stage 1, 12 % stage 2, 3% stage 3, and 23% SNAP. INTERPRETATION: This cross-sectional evaluation of the NIA-AA criteria for preclinical AD indicates that the 1-3 staging criteria coupled with stage 0 and SNAP categories classify 97% of CN subjects from a population-based sample, leaving only 3% unclassified. Future longitudinal validation of the criteria will be important.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Aniline Compounds; Biomarkers; Brain; Cognition Disorders; Disease Progression; Female; Fluorodeoxyglucose F18; Humans; Longitudinal Studies; Male; Mental Status Schedule; National Institute on Aging (U.S.); Neuropsychological Tests; Positron-Emission Tomography; Thiazoles; United States

A paravascular pathway facilitates CSF flow through the brain parenchyma and the clearance of interstitial solutes, including amyloid β. - Iliff, Jeffrey J; Wang, Minghuan; Liao, Yonghong; Plogg, Benjamin A; Peng, Weiguo; Gundersen, Georg A; Benveniste, Helene; Vates, G Edward; Deane, Rashid; Goldman, Steven A; Nagelhus, Erlend A; Nedergaard, Maiken (Sci Transl Med, 2012)
Because it lacks a lymphatic circulation, the brain must clear extracellular proteins by an alternative mechanism. The cerebrospinal fluid (CSF) functions as a sink for brain extracellular solutes, but it is not clear how solutes from the brain interstitium move from the parenchyma to the CSF. We demonstrate that a substantial portion of subarachnoid CSF cycles through the brain interstitial space. On the basis of in vivo two-photon imaging of small fluorescent tracers, we showed that CSF enters the parenchyma along paravascular spaces that surround penetrating arteries and that brain interstitial fluid is cleared along paravenous drainage pathways. Animals lacking the water channel aquaporin-4 (AQP4) in astrocytes exhibit slowed CSF influx through this system and a ~70% reduction in interstitial solute clearance, suggesting that the bulk fluid flow between these anatomical influx and efflux routes is supported by astrocytic water transport. Fluorescent-tagged amyloid β, a peptide thought to be pathogenic in Alzheimer's disease, was transported along this route, and deletion of the Aqp4 gene suppressed the clearance of soluble amyloid β, suggesting that this pathway may remove amyloid β from the central nervous system. Clearance through paravenous flow may also regulate extracellular levels of proteins involved with neurodegenerative conditions, its impairment perhaps contributing to the mis-accumulation of soluble proteins.
Keywords: Amyloid beta-Peptides; Animals; Aquaporin 4; Astrocytes; Biological Transport; Brain; Cerebral Ventricles; Cerebrospinal Fluid; Extracellular Fluid; Imaging, Three-Dimensional; Male; Mice; Mice, Inbred C57BL; Microscopy, Fluorescence, Multiphoton; Water

Propagation of tau pathology in a model of early Alzheimer's disease. - de Calignon, Alix; Polydoro, Manuela; Suárez-Calvet, Marc; William, Christopher; Adamowicz, David H; Kopeikina, Kathy J; Pitstick, Rose; Sahara, Naruhiko; Ashe, Karen H; Carlson, George A; Spires-Jones, Tara L; Hyman, Bradley T (Neuron, 2012)
Neurofibrillary tangles advance from layer II of the entorhinal cortex (EC-II) toward limbic and association cortices as Alzheimer's disease evolves. However, the mechanism involved in this hierarchical pattern of disease progression is unknown. We describe a transgenic mouse model in which overexpression of human tau P301L is restricted to EC-II. Tau pathology progresses from EC transgene-expressing neurons to neurons without detectable transgene expression, first to EC neighboring cells, followed by propagation to neurons downstream in the synaptic circuit such as the dentate gyrus, CA fields of the hippocampus, and cingulate cortex. Human tau protein spreads to these regions and coaggregates with endogenous mouse tau. With age, synaptic degeneration occurs in the entorhinal target zone and EC neurons are lost. These data suggest that a sequence of progressive misfolding of tau proteins, circuit-based transfer to new cell populations, and deafferentation induced degeneration are part of a process of tau-induced neurodegeneration.
Keywords: Age Factors; Alzheimer Disease; Animals; Disease Models, Animal; Disease Progression; Entorhinal Cortex; Epitopes; Gene Expression Regulation; Glial Fibrillary Acidic Protein; Gliosis; Hippocampus; Humans; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Nerve Degeneration; Neurofibrillary Tangles; Neurons; RNA, Messenger; Serine; tau Proteins; Tauopathies

Astrocyte-neuron lactate transport is required for long-term memory formation. - Suzuki, Akinobu; Stern, Sarah A; Bozdagi, Ozlem; Huntley, George W; Walker, Ruth H; Magistretti, Pierre J; Alberini, Cristina M (Cell, 2011)
We report that, in the rat hippocampus, learning leads to a significant increase in extracellular lactate levels that derive from glycogen, an energy reserve selectively localized in astrocytes. Astrocytic glycogen breakdown and lactate release are essential for long-term but not short-term memory formation, and for the maintenance of long-term potentiation (LTP) of synaptic strength elicited in vivo. Disrupting the expression of the astrocytic lactate transporters monocarboxylate transporter 4 (MCT4) or MCT1 causes amnesia, which, like LTP impairment, is rescued by L-lactate but not equicaloric glucose. Disrupting the expression of the neuronal lactate transporter MCT2 also leads to amnesia that is unaffected by either L-lactate or glucose, suggesting that lactate import into neurons is necessary for long-term memory. Glycogenolysis and astrocytic lactate transporters are also critical for the induction of molecular changes required for memory formation, including the induction of phospho-CREB, Arc, and phospho-cofilin. We conclude that astrocyte-neuron lactate transport is required for long-term memory formation.
Keywords: Animals; Arabinose; Astrocytes; Glycogen; Hippocampus; Imino Furanoses; Lactic Acid; Memory, Long-Term; Monocarboxylic Acid Transporters; Muscle Proteins; Neurons; Rats; Sugar Alcohols; Symporters

The diagnosis of dementia due to Alzheimer's disease: recommendations from the National Institute on Aging-Alzheimer's Association workgroups on diagnostic guidelines for Alzheimer's disease. - McKhann, Guy M; Knopman, David S; Chertkow, Howard; Hyman, Bradley T; Jack, Clifford R; Kawas, Claudia H; Klunk, William E; Koroshetz, Walter J; Manly, Jennifer J; Mayeux, Richard; Mohs, Richard C; Morris, John C; et al. (Alzheimers Dement, 2011)
The National Institute on Aging and the Alzheimer's Association charged a workgroup with the task of revising the 1984 criteria for Alzheimer's disease (AD) dementia. The workgroup sought to ensure that the revised criteria would be flexible enough to be used by both general healthcare providers without access to neuropsychological testing, advanced imaging, and cerebrospinal fluid measures, and specialized investigators involved in research or in clinical trial studies who would have these tools available. We present criteria for all-cause dementia and for AD dementia. We retained the general framework of probable AD dementia from the 1984 criteria. On the basis of the past 27 years of experience, we made several changes in the clinical criteria for the diagnosis. We also retained the term possible AD dementia, but redefined it in a manner more focused than before. Biomarker evidence was also integrated into the diagnostic formulations for probable and possible AD dementia for use in research settings. The core clinical criteria for AD dementia will continue to be the cornerstone of the diagnosis in clinical practice, but biomarker evidence is expected to enhance the pathophysiological specificity of the diagnosis of AD dementia. Much work lies ahead for validating the biomarker diagnosis of AD dementia.
Keywords: Alzheimer Disease; Biomarkers; Diagnosis, Differential; Diagnostic Imaging; Disease Progression; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; Societies, Medical; United States

Evidence for ordering of Alzheimer disease biomarkers. - Jack, Clifford R; Vemuri, Prashanthi; Wiste, Heather J; Weigand, Stephen D; Aisen, Paul S; Trojanowski, John Q; Shaw, Leslie M; Bernstein, Matthew A; Petersen, Ronald C; Weiner, Michael W; Knopman, David S (Arch Neurol, 2011)
OBJECTIVE: To empirically assess the concept that Alzheimer disease (AD) biomarkers significantly depart from normality in a temporally ordered manner. DESIGN: Validation sample. SETTING: Multisite, referral centers. PARTICIPANTS: A total of 401 elderly participants in the Alzheimer's Disease Neuroimaging Initiative who were cognitively normal, who had mild cognitive impairment, or who had AD dementia. We compared the proportions of 3 AD biomarker values (the Aβ42 level in cerebrospinal fluid [CSF], the total tau level in CSF, and the hippocampal volume adjusted for intracranial volume [hereafter referred to as the adjusted hippocampal volume]) that were abnormal as cognitive impairment worsened. Cut points demarcating normal vs abnormal for each biomarker were established by maximizing diagnostic accuracy in independent autopsy samples. MAIN OUTCOME MEASURES: Three AD biomarkers (ie, the CSF Aβ42 level, the CSF total tau level, and the adjusted hippocampal volume). RESULTS: Within each clinical group of the entire sample (n = 401), the CSF Aβ42 level was abnormal more often than was the CSF total tau level or the adjusted hippocampal volume. Among the 298 participants with both baseline and 12-month data, the proportion of participants with an abnormal Aβ42 level did not change from baseline to 12 months in any group. The proportion of participants with an abnormal total tau level increased from baseline to 12 months in cognitively normal participants (P = .05) but not in participants with mild cognitive impairment or AD dementia. For 209 participants with an abnormal CSF Aβ42 level at baseline, the percentage with an abnormal adjusted hippocampal volume but normal CSF total tau level increased from baseline to 12 months in participants with mild cognitive impairment. No change in the percentage of MCI participants with an abnormal total tau level was seen between baseline and 12 months. CONCLUSIONS: A reduction in the CSF Aβ42 level denotes a pathophysiological process that significantly departs from normality (ie, becomes dynamic) early, whereas the CSF total tau level and the adjusted hippocampal volume are biomarkers of downstream pathophysiological processes. The CSF total tau level becomes dynamic before the adjusted hippocampal volume, but the hippocampal volume is more dynamic in the clinically symptomatic mild cognitive impairment and AD dementia phases of the disease than is the CSF total tau level.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Female; Hippocampus; Humans; Longitudinal Studies; Male; Mild Cognitive Impairment; tau Proteins

Exercise training increases size of hippocampus and improves memory. - Erickson, Kirk I; Voss, Michelle W; Prakash, Ruchika Shaurya; Basak, Chandramallika; Szabo, Amanda; Chaddock, Laura; Kim, Jennifer S; Heo, Susie; Alves, Heloisa; White, Siobhan M; Wojcicki, Thomas R; Mailey, Emily; et al. (Proc Natl Acad Sci U S A, 2011)
The hippocampus shrinks in late adulthood, leading to impaired memory and increased risk for dementia. Hippocampal and medial temporal lobe volumes are larger in higher-fit adults, and physical activity training increases hippocampal perfusion, but the extent to which aerobic exercise training can modify hippocampal volume in late adulthood remains unknown. Here we show, in a randomized controlled trial with 120 older adults, that aerobic exercise training increases the size of the anterior hippocampus, leading to improvements in spatial memory. Exercise training increased hippocampal volume by 2%, effectively reversing age-related loss in volume by 1 to 2 y. We also demonstrate that increased hippocampal volume is associated with greater serum levels of BDNF, a mediator of neurogenesis in the dentate gyrus. Hippocampal volume declined in the control group, but higher preintervention fitness partially attenuated the decline, suggesting that fitness protects against volume loss. Caudate nucleus and thalamus volumes were unaffected by the intervention. These theoretically important findings indicate that aerobic exercise training is effective at reversing hippocampal volume loss in late adulthood, which is accompanied by improved memory function.
Keywords: Aged; Aging; Brain-Derived Neurotrophic Factor; Enzyme-Linked Immunosorbent Assay; Exercise; Hippocampus; Humans; Magnetic Resonance Imaging; Memory; Middle Aged; Organ Size; Space Perception

Neuronal basis of age-related working memory decline. - Wang, Min; Gamo, Nao J; Yang, Yang; Jin, Lu E; Wang, Xiao-Jing; Laubach, Mark; Mazer, James A; Lee, Daeyeol; Arnsten, Amy F T (Nature, 2011)
Many of the cognitive deficits of normal ageing (forgetfulness, distractibility, inflexibility and impaired executive functions) involve prefrontal cortex (PFC) dysfunction. The PFC guides behaviour and thought using working memory, which are essential functions in the information age. Many PFC neurons hold information in working memory through excitatory networks that can maintain persistent neuronal firing in the absence of external stimulation. This fragile process is highly dependent on the neurochemical environment. For example, elevated cyclic-AMP signalling reduces persistent firing by opening HCN and KCNQ potassium channels. It is not known if molecular changes associated with normal ageing alter the physiological properties of PFC neurons during working memory, as there have been no in vivo recordings, to our knowledge, from PFC neurons of aged monkeys. Here we characterize the first recordings of this kind, revealing a marked loss of PFC persistent firing with advancing age that can be rescued by restoring an optimal neurochemical environment. Recordings showed an age-related decline in the firing rate of DELAY neurons, whereas the firing of CUE neurons remained unchanged with age. The memory-related firing of aged DELAY neurons was partially restored to more youthful levels by inhibiting cAMP signalling, or by blocking HCN or KCNQ channels. These findings reveal the cellular basis of age-related cognitive decline in dorsolateral PFC, and demonstrate that physiological integrity can be rescued by addressing the molecular needs of PFC circuits.
Keywords: Action Potentials; Adrenergic alpha-2 Receptor Agonists; Aging; Animals; Biomedical Enhancement; Cues; Cyclic AMP; Cyclic Nucleotide-Gated Cation Channels; Guanfacine; Humans; Hyperpolarization-Activated Cyclic Nucleotide-Gated Channels; KCNQ Potassium Channels; Macaca mulatta; Male; Memory, Short-Term; Models, Neurological; Neural Pathways; Potassium Channel Blockers; Potassium Channels; Prefrontal Cortex; Receptors, Adrenergic, alpha-2; Signal Transduction; Time Factors

Pathogenic protein seeding in Alzheimer disease and other neurodegenerative disorders. - Jucker, Mathias; Walker, Lary C (Ann Neurol, 2011)
The misfolding and aggregation of specific proteins is a seminal occurrence in a remarkable variety of neurodegenerative disorders. In Alzheimer disease (the most prevalent cerebral proteopathy), the two principal aggregating proteins are β-amyloid (Aβ) and tau. The abnormal assemblies formed by conformational variants of these proteins range in size from small oligomers to the characteristic lesions that are visible by optical microscopy, such as senile plaques and neurofibrillary tangles. Pathologic similarities with prion disease suggest that the formation and spread of these proteinaceous lesions might involve a common molecular mechanism-corruptive protein templating. Experimentally, cerebral β-amyloidosis can be exogenously induced by exposure to dilute brain extracts containing aggregated Aβ seeds. The amyloid-inducing agent probably is Aβ itself, in a conformation generated most effectively in the living brain. Once initiated, Aβ lesions proliferate within and among brain regions. The induction process is governed by the structural and biochemical nature of the Aβ seed, as well as the attributes of the host, reminiscent of pathogenically variant prion strains. The concept of prionlike induction and spreading of pathogenic proteins recently has been expanded to include aggregates of tau, α-synuclein, huntingtin, superoxide dismutase-1, and TDP-43, which characterize such human neurodegenerative disorders as frontotemporal lobar degeneration, Parkinson/Lewy body disease, Huntington disease, and amyotrophic lateral sclerosis. Our recent finding that the most effective Aβ seeds are small and soluble intensifies the search in bodily fluids for misfolded protein seeds that are upstream in the proteopathic cascade, and thus could serve as predictive diagnostics and the targets of early, mechanism-based interventions. Establishing the clinical implications of corruptive protein templating will require further mechanistic and epidemiologic investigations. However, the theory that many chronic neurodegenerative diseases can originate and progress via the seeded corruption of misfolded proteins has the potential to unify experimental and translational approaches to these increasingly prevalent disorders.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; DNA-Binding Proteins; Humans; Neurodegenerative Diseases; Prions; Proteins; tau Proteins

Soluble amyloid beta-protein dimers isolated from Alzheimer cortex directly induce Tau hyperphosphorylation and neuritic degeneration. - Jin, Ming; Shepardson, Nina; Yang, Ting; Chen, Gang; Walsh, Dominic; Selkoe, Dennis J (Proc Natl Acad Sci U S A, 2011)
Alzheimer disease is a major cause of cognitive failure, and a pathogenically related but more subtle process accounts for many cases of mild memory symptoms in older humans. Insoluble fibrillar plaques of amyloid β-proteins (Aβ) and neurofibrillary deposits of hyperphosphorylated tau proteins are the diagnostic lesions of AD, but their temporal mechanistic relationship has long been debated. The recent recognition that small, diffusible oligomers may be the principal bioactive form of Aβ raises the key question of whether these are sufficient to initiate cytoskeletal change and neurite degeneration. A few studies have examined the effects of oligomers of synthetic Aβ peptides of one defined length at supraphysiological concentrations, but the existence of such assemblies in the AD brain is not established. Here, we isolated Aβ dimers, the most abundant form of soluble oligomer detectable in the human brain, from the cortices of typical AD subjects and found that at subnanomolar concentrations, they first induced hyperphosphorylation of tau at AD-relevant epitopes in hippocampal neurons and then disrupted the microtubule cytoskeleton and caused neuritic degeneration, all in the absence of amyloid fibrils. Application of pure, synthetic dimers confirmed the effects of the natural AD dimers, although the former were far less potent. Knocking down endogenous tau fully prevented the neuritic changes, whereas overexpressing human tau accelerated them. Coadministering Aβ N-terminal antibodies neutralized the cytoskeletal disruption. We conclude that natural dimers isolated from the AD brain are sufficient to potently induce AD-type tau phosphorylation and then neuritic dystrophy, but passive immunotherapy mitigates this.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Blotting, Western; Chromatography, Gel; Dimerization; Genetic Vectors; Hippocampus; Humans; Immunohistochemistry; Immunoprecipitation; In Situ Nick-End Labeling; Lentivirus; Microscopy, Confocal; Microtubules; Neurites; Phosphorylation; Rats; Rats, Sprague-Dawley; tau Proteins

Toward defining the preclinical stages of Alzheimer's disease: recommendations from the National Institute on Aging-Alzheimer's Association workgroups on diagnostic guidelines for Alzheimer's disease. - Sperling, Reisa A; Aisen, Paul S; Beckett, Laurel A; Bennett, David A; Craft, Suzanne; Fagan, Anne M; Iwatsubo, Takeshi; Jack, Clifford R; Kaye, Jeffrey; Montine, Thomas J; Park, Denise C; Reiman, Eric M; et al. (Alzheimers Dement, 2011)
The pathophysiological process of Alzheimer's disease (AD) is thought to begin many years before the diagnosis of AD dementia. This long "preclinical" phase of AD would provide a critical opportunity for therapeutic intervention; however, we need to further elucidate the link between the pathological cascade of AD and the emergence of clinical symptoms. The National Institute on Aging and the Alzheimer's Association convened an international workgroup to review the biomarker, epidemiological, and neuropsychological evidence, and to develop recommendations to determine the factors which best predict the risk of progression from "normal" cognition to mild cognitive impairment and AD dementia. We propose a conceptual framework and operational research criteria, based on the prevailing scientific evidence to date, to test and refine these models with longitudinal clinical research studies. These recommendations are solely intended for research purposes and do not have any clinical implications at this time. It is hoped that these recommendations will provide a common rubric to advance the study of preclinical AD, and ultimately, aid the field in moving toward earlier intervention at a stage of AD when some disease-modifying therapies may be most efficacious.
Keywords: Alzheimer Disease; Biomarkers; Cognition Disorders; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; United States

Vascular risk factors promote conversion from mild cognitive impairment to Alzheimer disease. - Li, J; Wang, Y J; Zhang, M; Xu, Z Q; Gao, C Y; Fang, C Q; Yan, J C; Zhou, H D (Neurology, 2011)
OBJECTIVE: Growing evidence suggests that vascular risk factors (VRF) contribute to cognitive decline. The aim of this study was to investigate the impact of VRF on the conversion from mild cognitive impairment (MCI) to Alzheimer disease (AD) dementia. METHODS: A total of 837 subjects with MCI were enrolled at baseline and followed up annually for 5 years. The incidence of AD dementia was investigated. A mixed random effects regression model was used to analyze the association between VRF and the progression of MCI assessed with Mini-Mental State Examination and instrumental Activities of Daily Living. Cox proportional hazard models were used to identify the association between VRF and dementia conversion, and to examine whether treatment of VRF can prevent dementia conversion. RESULTS: At the end of the follow-up, 298 subjects converted to AD dementia, while 352 remained MCI. Subjects with VRF had a faster progression in cognition and function relative to subjects without. VRF including hypertension, diabetes, cerebrovascular diseases, and hypercholesterolemia increased the risk of dementia conversion. Those subjects with MCI in whom all VRF were treated had a lower risk of dementia than those who had some VRF treated. Treatment of individual VRF including hypertension, diabetes, and hypercholesterolemia was associated with the reduced risk of AD conversion. CONCLUSION: VRF increased the risk of incident AD dementia. Treatment of VRF was associated with a reduced risk of incident AD dementia. Although our findings are observational, they suggest active intervention for VRF might reduce progression in MCI to AD dementia.
Keywords: Aged; Alzheimer Disease; Cerebrovascular Disorders; Cognition Disorders; Disease Progression; Female; Humans; Incidence; Longitudinal Studies; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptides; Regression Analysis; Residence Characteristics; Retrospective Studies; Risk Factors; Statistics, Nonparametric

Alzheimer's Disease Neuroimaging Initiative (ADNI): clinical characterization. - Petersen, R C; Aisen, P S; Beckett, L A; Donohue, M C; Gamst, A C; Harvey, D J; Jack, C R; Jagust, W J; Shaw, L M; Toga, A W; Trojanowski, J Q; Weiner, M W (Neurology, 2010)
BACKGROUND: Neuroimaging measures and chemical biomarkers may be important indices of clinical progression in normal aging and mild cognitive impairment (MCI) and need to be evaluated longitudinally. OBJECTIVE: To characterize cross-sectionally and longitudinally clinical measures in normal controls, subjects with MCI, and subjects with mild Alzheimer disease (AD) to enable the assessment of the utility of neuroimaging and chemical biomarker measures. METHODS: A total of 819 subjects (229 cognitively normal, 398 with MCI, and 192 with AD) were enrolled at baseline and followed for 12 months using standard cognitive and functional measures typical of clinical trials. RESULTS: The subjects with MCI were more memory impaired than the cognitively normal subjects but not as impaired as the subjects with AD. Nonmemory cognitive measures were only minimally impaired in the subjects with MCI. The subjects with MCI progressed to dementia in 12 months at a rate of 16.5% per year. Approximately 50% of the subjects with MCI were on antidementia therapies. There was minimal movement on the Alzheimer's Disease Assessment Scale-Cognitive Subscale for the normal control subjects, slight movement for the subjects with MCI of 1.1, and a modest change for the subjects with AD of 4.3. Baseline CSF measures of Abeta-42 separated the 3 groups as expected and successfully predicted the 12-month change in cognitive measures. CONCLUSION: The Alzheimer's Disease Neuroimaging Initiative has successfully recruited cohorts of cognitively normal subjects, subjects with mild cognitive impairment (MCI), and subjects with Alzheimer disease with anticipated baseline characteristics. The 12-month progression rate of MCI was as predicted, and the CSF measures heralded progression of clinical measures over 12 months.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Cross-Sectional Studies; Diagnostic Imaging; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Middle Aged

Gamma-secretase activating protein is a therapeutic target for Alzheimer's disease. - He, Gen; Luo, Wenjie; Li, Peng; Remmers, Christine; Netzer, William J; Hendrick, Joseph; Bettayeb, Karima; Flajolet, Marc; Gorelick, Fred; Wennogle, Lawrence P; Greengard, Paul (Nature, 2010)
Accumulation of neurotoxic amyloid-beta is a major hallmark of Alzheimer's disease. Formation of amyloid-beta is catalysed by gamma-secretase, a protease with numerous substrates. Little is known about the molecular mechanisms that confer substrate specificity on this potentially promiscuous enzyme. Knowledge of the mechanisms underlying its selectivity is critical for the development of clinically effective gamma-secretase inhibitors that can reduce amyloid-beta formation without impairing cleavage of other gamma-secretase substrates, especially Notch, which is essential for normal biological functions. Here we report the discovery of a novel gamma-secretase activating protein (GSAP) that drastically and selectively increases amyloid-beta production through a mechanism involving its interactions with both gamma-secretase and its substrate, the amyloid precursor protein carboxy-terminal fragment (APP-CTF). GSAP does not interact with Notch, nor does it affect its cleavage. Recombinant GSAP stimulates amyloid-beta production in vitro. Reducing GSAP concentrations in cell lines decreases amyloid-beta concentrations. Knockdown of GSAP in a mouse model of Alzheimer's disease reduces levels of amyloid-beta and plaque development. GSAP represents a type of gamma-secretase regulator that directs enzyme specificity by interacting with a specific substrate. We demonstrate that imatinib, an anticancer drug previously found to inhibit amyloid-beta formation without affecting Notch cleavage, achieves its amyloid-beta-lowering effect by preventing GSAP interaction with the gamma-secretase substrate, APP-CTF. Thus, GSAP can serve as an amyloid-beta-lowering therapeutic target without affecting other key functions of gamma-secretase.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Benzamides; Cell Line; Disease Models, Animal; Gene Knockdown Techniques; Humans; Imatinib Mesylate; Mice; Peptide Fragments; Piperazines; Proteins; Pyrimidines; Receptor, Notch1; RNA Interference

Genetic evidence implicates the immune system and cholesterol metabolism in the aetiology of Alzheimer's disease. - Jones, Lesley; Holmans, Peter A; Hamshere, Marian L; Harold, Denise; Moskvina, Valentina; Ivanov, Dobril; Pocklington, Andrew; Abraham, Richard; Hollingworth, Paul; Sims, Rebecca; Gerrish, Amy; Pahwa, Jaspreet Singh; et al. (PLoS One, 2010)
BACKGROUND: Late Onset Alzheimer's disease (LOAD) is the leading cause of dementia. Recent large genome-wide association studies (GWAS) identified the first strongly supported LOAD susceptibility genes since the discovery of the involvement of APOE in the early 1990s. We have now exploited these GWAS datasets to uncover key LOAD pathophysiological processes. METHODOLOGY: We applied a recently developed tool for mining GWAS data for biologically meaningful information to a LOAD GWAS dataset. The principal findings were then tested in an independent GWAS dataset. PRINCIPAL FINDINGS: We found a significant overrepresentation of association signals in pathways related to cholesterol metabolism and the immune response in both of the two largest genome-wide association studies for LOAD. SIGNIFICANCE: Processes related to cholesterol metabolism and the innate immune response have previously been implicated by pathological and epidemiological studies of Alzheimer's disease, but it has been unclear whether those findings reflected primary aetiological events or consequences of the disease process. Our independent evidence from two large studies now demonstrates that these processes are aetiologically relevant, and suggests that they may be suitable targets for novel and existing therapeutic approaches.
Keywords: Alzheimer Disease; Apolipoproteins E; Cholesterol; Chromosome Mapping; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Immune System; Polymorphism, Single Nucleotide